MOOC learning experience design: issues and challenges - Fournier, Helen; Kop, Rita (International Journal on E-Learning, 2015)
This paper will present current work on various frameworks that are aimed at guiding the research, development, and evaluation efforts around Massive Open Online Courses (MOOCs). Initiatives and activities, including current work by the National Research Council (NRC) in the context of Learning and Performance Support Systems and MOOCs, will be presented along with outstanding challenges and issues to be addressed in the near future. Findings from case studies of Personal Learning Environments (PLEs) and MOOCs will be presented which suggest that learning experiences are impacted by much more than tools and technologies. There is the potential for an enormous palette of possibilities for creating effective, meaningful, and successful learning experiences, as well as many important issues and challenges to address. Recommendations coming of out of recent cMOOC surveys and forums will highlight participant focused and learner driven processes along with a changing notion of time and space in online learning environments. The paper also unveils current and future areas of research and development in a new Learning and Performance Support System (LPSS) program at NRC, including learning analytics, big data, and educational data mining, as well as ethics and privacy issues in networked environments and the use of personal learning data to feed into the research and development process.
Keywords: massive online open courses; MOOCs; connectivism; cMOOCs; MOOC research; open educational resources; OER

Experimental study of the unsteady aerodynamics during flapping flight of birds: European Starling, Western Sandpiper and American Robin - Segreto, J. M.; Kirchhefer, A. J.; Hackett, E. E.; Guglielmo, C. G.; Kopp, G. A.; Gurka, R. (10th Pacific Symposium on Flow Visualization and Image Processing, 15-18 June 2015, Naples, Italy: Proceedings, 2015)
Birds’ unique characteristics such as wing shape, flexibility, feathers, flapping motion, etc., result in high aerodynamic performance. Using various flight modes such as gliding, bounding, and flapping, birds can use a single propulsion system for multiple functions. In low Reynolds number flyers using flapping flight mechanisms, the contribution of unsteady effects on lift and drag is not entirely understood. To gain insight about the unsteady contributions, a controlled study on the near wake flow behind freely flying birds was performed. Long duration, time resolved particle image velocimetry (PIV), combined with high speed imaging has been used to characterize the various flow features in the wake that are associated with flapping flight. The specially designed PIV system can sample the flow field for twenty minutes yielding a continuous measurement, sampling several wingbeat cycles consecutively. Time series of the vorticity fields have been expressed as composite wake plots, which reveal various characteristics of the wake during the upstroke (US) and down stroke (DS) phase of the flapping as well as the transition between US to DS and vice versa. Comparison between the near wake fields behind the three birds show remarkable similarity in their wake structure. We have identified over multiple wing beat cycles the presence of what appears to be an overlap of two distinct wakes during the transition from US toDS, named “double branch”. Over the region of the double branch, the majority of net positive circulation is accumulated. Indicating this may be a key feature in producing lift, and thus contribute to the observed high aerodynamic performance.
Keywords: birds’ aerodynamics; high-speed PIV; wind tunnel; wakes

On the estimation of time dependent lift of a European starling (Sturnus vulgaris) during flapping flight - Stalnov, Oksana; Ben-Gida, Hadar; Kirchhefer, Adam J.; Guglielmo, Christopher G.; Kopp, Gregory A.; Liberzon, Alexander; Gurka, Roi (PLoS ONE, 2015)
We study the role of unsteady lift in the context of flapping wing bird flight. Both aerodynamicists and biologists have attempted to address this subject, yet it seems that the contribution of unsteady lift still holds many open questions. The current study deals with the estimation of unsteady aerodynamic forces on a freely flying bird through analysis of wingbeat kinematics and near wake flow measurements using time resolved particle image velocimetry. The aerodynamic forces are obtained through two approaches, the unsteady thin airfoil theory and using the momentum equation for viscous flows. The unsteady lift is comprised of circulatory and non-circulatory components. Both approaches are presented over the duration of wingbeat cycles. Using long-time sampling data, several wingbeat cycles have been analyzed in order to cover both the downstroke and upstroke phases. It appears that the unsteady lift varies over the wingbeat cycle emphasizing its contribution to the total lift and its role in power estimations. It is suggested that the circulatory lift component cannot assumed to be negligible and should be considered when estimating lift or power of birds in flapping motion.

SemEval-2015 task 10: sentiment analysis in twitter - Rosenthal, Sara; Nakov, Preslav; Kiritchenko, Svetlana; Mohammad, Saif; Ritter, Alan; Stoyanov, Veselin (Proceedings of the 9th International Workshop on Semantic Evaluation (SemEval-2015), 2015)
In this paper, we describe the 2015 iteration of the SemEval shared task on Sentiment Analysis in Twitter. This was the most popular sentiment analysis shared task to date with more than 40 teams participating in each of the last three years. This year’s shared task competition consisted of five sentiment prediction sub- tasks. Two were reruns from previous years: (A) sentiment expressed by a phrase in the context of a tweet, and (B) overall sentiment of a tweet. We further included three new sub- tasks asking to predict (C) the sentiment to- wards a topic in a single tweet, (D) the over- all sentiment towards a topic in a set of tweets, and (E) the degree of prior polarity of a phrase.

Blood brain barrier protection in stroke: taming tPA - Zhang, Wandong; Hou, Sheng; Stanimirovic, Danica (The Blood-Brain Barrier in Health and Disease, Volume Two, 2015)

Single-domain antibodies: building blocks for multifunctional biologics - Stanimirovic, Danica B.; Kemmerich, Kristin; Tanha, Jamshid (Monoclonal Antibodies: Development, Delivery and Applications, 2015)

Methodology development for investigation of slurry abrasion corrosion by integrating an electrochemical cell to a Miller tester - Wang, Sheng-Hui; Jiang, Jiaren; Stack, Margaret M. (Journal of Bio- and Tribo-Corrosion, 2015)
Material losses in slurry handling systems constitute a significant fraction of cost in oil sands, mining, and mineral processing operations. It is thus important to better understand wear attack mechanisms and major factors affecting wear in such applications. In this work, a methodology and a testing system have been developed to study the abrasion–corrosion synergism during slurry abrasion based on a Miller test machine by incorporating a three-electrode electrochemical cell. The proposed methodology has then been validated experimentally using QT 100 steel. It has been shown that cathodic protection using such system setup is effective in suppressing the corrosion effect on the total material loss. In general, corrosion-induced enhancement on slurry abrasion loss rate increases with slurry corrosivity but inversely with sliding speed.
Keywords: slurry abrasion; abrasion–corrosion; tribo-corrosion; Miller tester

Evidence of a role for S. cerevisiae α-arrestin Art1 (Ldb19) in mating projection and zygote formations - Choudhary, Pooja; Loewen, Michele C. (Cell Biology International, 2015)
The discovery of arrestin-mediated biased signalling mechanisms for mammalian G-protein coupled receptors (GPCRs) has revolutionized the field over the last decade. Now, with the recent demonstration of a role for α-arrestins in internalization of the yeast pheromone GPCR, Ste2p, the possibility of arrestin-mediated alternate GPCR functionalities in yeast also follows. Here, the effects of knockout and complementation of yeast α-arrestin expression during mating are reported. Although minor effects on classical pheromone-related signalling are noted for a few arrestins, much stronger effects were observed downstream of cell cycle arrest, in particular linking Ldb19 (Art1) to mediation of zygote formation. Subsequent phenotypic observations linked this activity to more pronounced projection formation in an Art1 complemented noncuple α-arrestin knockout line, compared to the knockout-line alone, or either of the Art3 or Art6 complemented lines. Together with the observation of ligand-stimulated localization of Art-GFP to the mating projection, a possible role for this arrestin-like protein in projection formation is supported. While leaving the full mechanism of alternate Art1 functionality to be elucidated, together these findings implicate Art1 in selective regulation of mating events downstream of receptor internalization and cell cycle arrest, leading to schmoo, and ultimately zygote formation.

α-tocopherol’s location in membranes is not affected by their composition - Marquardt, Drew; Kučerka, Norbert; Katsaras, John; Harroun, Thad A. (Langmuir, 2015)
To this day, α-tocopherol’s (aToc) role in humans is not well known. In previous studies, we have tried to connect aToc’s biological function with its location in a lipid bilayer. In the present study, we have determined, by means of small-angle neutron diffraction, that not only is aToc’s hydroxyl group located high in the membrane but its tail also resides far from the center of 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC) bilayers. In addition, we located aToc’s hydroxyl group above the lipid backbone in 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphoethanolamine (POPE), 1-palmitoyl-2-oleoyl-sn-glycero-3-phospho-l-serine (POPS), and sphingomyelin bilayers, suggesting that aToc’s location near the lipid–water interface may be a universal property of vitamin E. In light of these data, how aToc efficiently terminates lipid hydroperoxy radicals at the membrane center remains an open question.

α-tocopherol is well designed to protect polyunsaturated phospholipids: MD simulations - Leng, Xiaoling; Kinnun, Jacob J.; Marquardt, Drew; Ghefli, Mikel; Kučerka, Norbert; Katsaras, John; Atkinson, Jeffrey; Harroun, Thad A.; Feller, Scott E.; Wassall, Stephen R. (Biophysical Journal, 2015)
The presumptive function for alpha-tocopherol (αtoc) in membranes is to protect polyunsaturated lipids against oxidation. Although the chemistry of the process is well established, the role played by molecular structure that we address here with atomistic molecular-dynamics simulations remains controversial. The simulations were run in the constant particle NPT ensemble on hydrated lipid bilayers composed of SDPC (1-stearoyl-2-docosahexaenoylphosphatidylcholine, 18:0-22:6PC) and SOPC (1-stearoyl-2-oleoylphosphatidylcholine, 18:0-18:1PC) in the presence of 20 mol % αtoc at 37°C. SDPC with SA (stearic acid) for the sn-1 chain and DHA (docosahexaenoic acid) for the sn-2 chain is representative of polyunsaturated phospholipids, while SOPC with OA (oleic acid) substituted for the sn-2 chain serves as a monounsaturated control. Solid-state 2H nuclear magnetic resonance and neutron diffraction experiments provide validation. The simulations demonstrate that high disorder enhances the probability that DHA chains at the sn-2 position in SDPC rise up to the bilayer surface, whereby they encounter the chromanol group on αtoc molecules. This behavior is reflected in the van der Waals energy of interaction between αtoc and acyl chains, and illustrated by density maps of distribution for acyl chains around αtoc molecules that were constructed. An ability to more easily penetrate deep into the bilayer is another attribute conferred upon the chromanol group in αtoc by the high disorder possessed by DHA. By examining the trajectory of single molecules, we found that αtoc flip-flops across the SDPC bilayer on a submicrosecond timescale that is an order-of-magnitude greater than in SOPC. Our results reveal mechanisms by which the sacrificial hydroxyl group on the chromanol group can trap lipid peroxyl radicals within the interior and near the surface of a polyunsaturated membrane. At the same time, water-soluble reducing agents that regenerate αtoc can access the chromanol group when it locates at the surface.

α-synuclein dimer structures found from computational simulations - Sahu, Kamlesh Kumar; Woodside, Michael T.; Tuszynski, Jack A. (Biochimie, 2015)
Dimer formation is likely the first step in the oligomerization of α-synuclein in Lewy bodies. In order to prevent α-synuclein aggregation, knowledge of the atomistic structures of possible α-synuclein dimers and the interaction affinity between the dimer domains is a necessary prerequisite in the process of rational design of dimerization inhibitors. Using computational methodology, we have investigated several possible α-synuclein dimer structures, focusing on dimers formed from α-helical forms of the protein found when it is membrane-bound, and dimers formed from β-sheet conformations predicted by simulations. Structures and corresponding binding affinities for the interacting monomers in possible α-synuclein dimers, along with properties including the contributions from different interaction energies and the radii of gyration, were found through molecular docking followed by MD simulations and binding-energy calculations. We found that even though α-synuclein is highly charged, hydrophobic contributions play a significant role in stabilizing dimers.
Keywords: docking; molecular dynamics; MMGBSA; Alpha-synuclein; Alzheimers; neurodegenerative disease

When are old data new data? - Griffin, R. Elizabeth (GeoResJ, 2015)
What is the value of ‘old’ data when much more sophisticated data are being acquired today in huge quantities with modern equipment and served up in ready-to-use form? Why the hype over delving into the past, when the observers were undoubtedly less well informed than they are today? What can such old records possibly teach us that we don’t already know better from modern electronic data and today’s sophisticated experiments? As this paper demonstrates, the answers to those questions lie in the critical scientific advantages of the long-term date-stamps which only historical data carry.
Keywords: data rescue; heritage scientific data; analogue records; data-rescue initiatives; CODATA Task Group

Weak galactic halo-dwarf spheroidal connection from RR Lyrae stars - Fiorentino, Giuliana; Bono, Giuseppe; Monelli, Matteo; Stetson, Peter B.; Tolstoy, Eline; Gallart, Carme; Salaris, Maurizio; Martínez-vásquez, Clara E.; Bernard, Edouard J. (The Astrophysical Journal, 2015)
We discuss the role that dwarf galaxies may have played in the formation of the Galactic halo (Halo) using RR Lyrae stars (RRL) as tracers of their ancient stellar component. The comparison is performed using two observables (periods, luminosity amplitudes) that are reddening and distance independent. Fundamental mode RRL in 6 dwarf spheroidals (dSphs) and 11 ultra faint dwarf galaxies (~1300) show a Gaussian period distribution well peaked around a mean period of langPabrang = 0.610 ± 0.001 days (σ = 0.03). The Halo RRL (~15,000) are characterized by a broader period distribution. The fundamental mode RRL in all the dSphs apart from Sagittarius are completely lacking in High Amplitude Short Period (HASP) variables, defined as those having P lesssim 0.48 days and AV ≥ 0.75 mag. Such variables are not uncommon in the Halo and among the globular clusters and massive dwarf irregulars. To further interpret this evidence, we considered 18 globulars covering a broad range in metallicity (–2.3 lesssim [Fe/H] lesssim –1.1) and hosting more than 35 RRL each. The metallicity turns out to be the main parameter, since only globulars more metal-rich than [Fe/H] ~ –1.5 host RRL in the HASP region. This finding suggests that dSphs similar to the surviving ones do not appear to be the major building-blocks of the Halo. Leading physical arguments suggest an extreme upper limit of ~50% to their contribution. On the other hand, massive dwarfs hosting an old population with a broad metallicity distribution (Large Magellanic Cloud, Sagittarius) may have played a primary role in the formation of the Halo.
Keywords: Local Group: stars: variable: RR Lyrae

Wavelength-division multiplexing of nano-optomechanical doubly clamped beam systems - Sauer, Vincent T. K.; Diao, Zhu; Freeman, Mark R.; Hiebert, Wayne K. (Optics Letters, 2015)
Wavelength-division multiplexing is demonstrated for a set of two doubly clamped beams. Using a single input/output waveguide in a nanophotonic detection system, the two mechanical beams are independently addressable using different wavelength channels as determined by their respective racetrack resonator detection cavities. The two cavities slightly overlap, which also enables the mechanical frequency of both beams to be detected simultaneously with a single wavelength. Finally, to physically map which wavelength channel corresponds to which specific device, a heating laser is targeted individually on each beam to create a reversible mechanical frequency shift. This multiplexing method would allow for the simpler detection of large arrays of nanomechanical devices in a sensor system.
Keywords: integrated optics devices; micro-optical devices; sensors; optomechanics; optical microelectromechanical devices; nanophotonics and photonic crystals

W line shape in the resistively detected nuclear magnetic resonance - Desrat, W.; Piot, B. A.; Maude, D. K.; Wasilewski, Z. R.; Henini, M.; Airey, R. (Journal of Physics: Condensed Matter, 2015)
The resistively detected nuclear magnetic resonance (RDNMR) performed on a two-dimensional electron gas is known to exhibit a peculiar 'dispersive' line shape at some filling factors, especially around $ν =1$ . Here, we study in detail the inversion of the dispersive line shape as a function of the filling factor from $ν =1$ to $2/3$ . The RDNMR spectra show a new characteristic W line shape in the longitudinal resistance, whereas dispersive lines detected in the Hall resistance remain unchanged. This W resonance, like the dispersive line, can be fitted correctly by a model of two independent response functions, which are the signatures of polarized and unpolarized electronic sub-systems.
Keywords: quantum Hall effect; resistively detected nuclear magnetic resonance (RDNMR); electronic domains; electronic spin polarization

Variable stars in Local Group Galaxies: I. tracing the early chemical enrichment and radial gradients in the Sculptor dSph with RR Lyrae stars - Martínez-vázquez, C. E.; Monelli, M.; Bono, G.; Stetson, P. B.; Ferraro, I.; Bernard, E. J.; Gallart, C.; Fiorentino, G.; Iannicola, G.; Udalski, A. (Monthly Notices of the Royal Astronomical Society, 2015)
We identified and characterized the largest (536) RR Lyrae (RRL) sample in a Milky Way dSph satellite (Sculptor) based on optical photometry data collected over ∼24 years. The RRLs display a spread in V-magnitude (∼0.35 mag) which appears larger than photometric errors and the horizontal branch (HB) luminosity evolution of a mono-metallic population. Using several calibrations of two different reddening free and metal independent period–Wesenheit relations we provide a new distance estimate μ = 19.62 mag (σμ = 0.04 mag) that agrees well with literature estimates. We constrained the metallicity distribution of the old population, using the MI period–luminosity relation, and we found that it ranges from −2.3 to −1.5 dex. The current estimate is narrower than suggested by low and intermediate spectroscopy of RGBs (Δ [Fe/H]≤ 1.5). We also investigated the HB morphology as a function of the galactocentric distance. The HB in the innermost regions is dominated by red HB stars and by RRLs, consistent with a more metal-rich population, while in the outermost regions it is dominated by blue HB stars and RRLs typical of a metal-poor population. Our results suggest that fast chemical evolution occurred in Sculptor, and that the radial gradients were in place at an early epoch.
Keywords: Kstars: variables: RR Lyrae; galaxies: evolution; galaxies: individual: Sculptor dSph; Local Group; galaxies: stellar content

Using the inclined-plane test to evaluate the resistance of outdoor polymer insulating materials to electrical tracking and erosion - Ghunem, Refat Atef (IEEE Electrical Insulation Magazine, 2015)
Evaluating the electrical tracking and erosion resistance of polymeric housing materials is an essential task performed in the development of outdoor insulators. “Tracking” means the formation of a surface carbonaceous path, and “erosion” means weight loss of the housing material. An absolute measurement of the tracking and erosion resistance is not possible; only relative ranking of composites can be achieved using the standard tracking and erosion tests. During the early use of organic insulating materials, failure due to tracking was a major concern, and therefore standard screening methods were proposed to evaluate the tracking rather than the erosion resistance. Erosion has become more important following the development of tracking resistant composites containing high levels of inorganic fillers.
Keywords: DC inclined-plane test; inclined-plane test; tracking; erosion; dry-band arcing; polymer insulator; silicone rubber; inorganic fillers

Tuning the reactivity of nanostructured indium tin oxide electrodes toward chemisorption - Forget, A.; Tucker, R. T.; Brett, M. J.; Limoges, B.; Balland, V. (Chemical Communications, 2015)
This contribution highlights correlation between the surface concentration of a chemisorbed organophosphorous probe (flavin mononucleotide) and the relative hydroxyl surface coverage of nanostructured ITO electrodes, which can be tuned during post-deposition reductive annealing. The resulting modified electrodes are very stable in aqueous solution, highly hydrophilic and fully-accessible to the bulk solution.

Tuning of nanocavity optomechanical coupling using a near-field fiber probe - Hryciw, Aaron C.; Wu, Marcelo; Khanaliloo, Behzad; Barclay, Paul E. (Optica, 2015)
Optomechanical coupling in a nanocavity formed between two cantilevers is tuned through renormalization of the nanocavity field, allowing reconfiguration of the dominant optomechanical transduction mechanism and spatially selective optical readout of mechanical resonances. Tuning is mediated through evanescent interaction between the nanocavity and a fiber taper near-field probe that induces both dissipative and dispersive optomechanical coupling. Tunable optomechanical coupling can exceed 3 GHz/nm, and is shown to allow readout of out-of-plane cantilever nanomechanical resonances suitable for sensing applications.

Treating cancer stem cells and cancer metastasis using glucose-coated gold nanoparticles - Hu, Chenxia; Niestroj, Martin; Yuan, Daniel; Chang, Steven; Chen, Jie (International Journal of Nanomedicine, 2015)
Cancer ranks among the leading causes of human mortality. Cancer becomes intractable when it spreads from the primary tumor site to various organs (such as bone, lung, liver, and then brain). Unlike solid tumor cells, cancer stem cells and metastatic cancer cells grow in a non-attached (suspension) form when moving from their source to other locations in the body. Due to the non-attached growth nature, metastasis is often first detected in the circulatory systems, for instance in a lymph node near the primary tumor. Cancer research over the past several decades has primarily focused on treating solid tumors, but targeted therapy to treat cancer stem cells and cancer metastasis has yet to be developed. Because cancers undergo faster metabolism and consume more glucose than normal cells, glucose was chosen in this study as a reagent to target cancer cells. In particular, by covalently binding gold nanoparticles (GNPs) with thio-PEG (polyethylene glycol) and thio-glucose, the resulting functionalized GNPs (Glu-GNPs) were created for targeted treatment of cancer metastasis and cancer stem cells. Suspension cancer cell THP-1 (human monocytic cell line derived from acute monocytic leukemia patients) was selected because it has properties similar to cancer stem cells and has been used as a metastatic cancer cell model for in vitro studies. To take advantage of cancer cells’ elevated glucose consumption over normal cells, different starvation periods were screened in order to achieve optimal treatment effects. Cancer cells were then fed using Glu-GNPs followed by X-ray irradiation treatment. For comparison, solid tumor MCF-7 cells (breast cancer cell line) were studied as well. Our irradiation experimental results show that Glu-GNPs are better irradiation sensitizers to treat THP-1 cells than MCF-7 cells, or Glu-GNPs enhance the cancer killing of THP-1 cells 20% more than X-ray irradiation alone and GNP treatment alone. This finding can help oncologists to design therapeutic strategies to target cancer stem cells and cancer metastasis.
Keywords: glucose capped gold nanoparticles; cancer metastasis; cancer stem cells; irradiation therapy; targeted treatment; suspension cancer cells

Towards a quantitative, measurement-based estimate of the uncertainty in photon mass attenuation coefficients at radiation therapy energies - Ali, E. S. M.; Spencer, B.; McEwen, M. R.; Rogers, D. W. O. (Physics in Medicine and Biology, 2015)
In this study, a quantitative estimate is derived for the uncertainty in the XCOM photon mass attenuation coefficients in the energy range of interest to external beam radiation therapy—i.e. 100 keV (orthovoltage) to 25 MeV—using direct comparisons of experimental data against Monte Carlo models and theoretical XCOM data. Two independent datasets are used. The first dataset is from our recent transmission measurements and the corresponding EGSnrc calculations (Ali et al 2012 Med. Phys. 39 5990–6003) for 10–30 MV photon beams from the research linac at the National Research Council Canada. The attenuators are graphite and lead, with a total of 140 data points and an experimental uncertainty of ~0.5% (k = 1). An optimum energy-independent cross section scaling factor that minimizes the discrepancies between measurements and calculations is used to deduce cross section uncertainty. The second dataset is from the aggregate of cross section measurements in the literature for graphite and lead (49 experiments, 288 data points). The dataset is compared to the sum of the XCOM data plus the IAEA photonuclear data. Again, an optimum energy-independent cross section scaling factor is used to deduce the cross section uncertainty. Using the average result from the two datasets, the energy-independent cross section uncertainty estimate is 0.5% (68% confidence) and 0.7% (95% confidence). The potential for energy-dependent errors is discussed. Photon cross section uncertainty is shown to be smaller than the current qualitative 'envelope of uncertainty' of the order of 1–2%, as given by Hubbell (1999 Phys. Med. Biol 44 R1–22).

Torque-mixing magnetic resonance spectroscopy - Losby, J. E.; Sani, F. F.; Grandmont, D. T.; Diao, Z.; Belov, M.; Burgess, J. A. J.; Compton, S. R.; Hiebert, W. K.; Vick, D.; Mohammad, K.; Salimi, E.; Bridges, G. E.; et al. (Science, 2015)
A universal, torque-mixing method for magnetic resonance spectroscopy is presented. In analogy to resonance detection by magnetic induction, the transverse component of a precessing dipole moment can be measured in sensitive broadband spectroscopy, here using a resonant mechanical torque sensor. Unlike induction, the torque amplitude allows equilibrium magnetic properties to be monitored simultaneously with the spin dynamics. Comprehensive electron spin resonance spectra of a single-crystal, mesoscopic yttrium iron garnet disk at room temperature reveal assisted switching between magnetization states and mode-dependent spin resonance interactions with nanoscale surface imperfections. The rich detail allows analysis of even complex three-dimensional spin textures. The flexibility of microelectromechanical and optomechanical devices combined with broad generality and capabilities of torque-mixing magnetic resonance spectroscopy offers great opportunities for development of integrated devices.

Time-resolved photoelectron spectroscopy and Ab initio multiple spawning studies of hexamethylcyclopentadiene - Wolf, T. J. A.; Kuhlman, T. S.; Schalk, O.; Martínez, T. J.; Møller, K. B.; Stolow, A.; Unterreiner, A.-N. (Ultrafast Phenomena XIX: Proceedings of the 19th International Conference, Okinawa Convention Center, Okinawa, Japan, July 7-11, 2014, 2015)
Time-resolved photoelectron spectroscopy and ab initio multiple spawning were applied to the ultrafast non-adiabatic dynamics of hexamethylcyclopentadiene. The high level of agreement between experiment and theory associates wavepacket motion with a distinct degree of freedom.

Three years of measurements of the first years ridges in the barents sea and fram strait - Sand, Bjørnar; Bonath, Victoria; Sudom, Denise; Petrich, Chris (POAC'15: Proceedings of the 23rd International Conference on Port and Ocean Engineering under Arctic Conditions, June 14-18, 2015, Trondheim, Norway, 2015)
During three expeditions in March 2011, March 2012 and April/May 2013 with the Norwegian coastguard vessel “KV Svalbard”, two pressure ridges around Svalbard, one ridge in Fram Strait and three ridges in Olga strait have been studied with respect to ridge geometry and physical and mechanical properties. With a discrete measurement, which is of most interest here, information can be obtained on the overall size and shape of an individual ridge at one particular location, both above and below the waterline. This approach provides detailed quantitative information on both the sail and keel size and shape, of a specific ridge, as well as its porosity. It does not supply any information on ridge spacing. The results of individual profile measurements are discussed. Measurements of vertical profiles along the spine and transects perpendicular to the spine are presented for these ridges. The sail height, sail width, keel depth and keel width, consolidated layer thickness, rubble block sizes and porosities are examined for each ridge. The results presented in this paper contribute to more data in terms of geometry and morphology of the first-year ridge off Svalbard, in Fram Strait and Barents Sea. Compression and tensile strength properties are important input data for constitutive modelling. Still strength properties of ridged ice are not yet sufficiently investigated. Uniaxial compressive tests were performed with horizontal and vertical loading directions and the results from the testing of level ice and consolidated layer are summarized with consideration of total porosity.

Three dimensional accurate morphology measurements of polystyrene standard particles on silicon substrate by electron tomography - Hayashida, Misa; Kumagai, Kazuhiro; Malac, Marek (Micron, 2015)
Polystyrene latex (PSL) nanoparticle (NP) sample is one of the most widely used standard materials. It is used for calibration of particle counters and particle size measurement tools. It has been reported that the measured NP sizes by various methods, such as Differential Mobility Analysis, dynamic light scattering (DLS), optical microscopy (OM), scanning electron microscopy (SEM) and atomic force microscopy (AFM), differ from each other. Deformation of PSL NPs on mica substrate has been reported in AFM measurements: the lateral width of PSL NPs is smaller than their vertical height. To provide a reliable calibration standard, the deformation must be measured by a method that can reliably visualize the entire three dimensional (3D) shape of the PSL NPs. Here we present a method for detailed measurement of PSL NP 3D shape by means of electron tomography in a transmission electron microscope. The observed shape of the PSL NPs with 100 nm and 50 nm diameter were not spherical, but squished in direction perpendicular to the support substrate by about 7.4% and 12.1%, respectively. The high difference in surface energy of the PSL NPs and that of substrate together with their low Young modulus appear to explain the squishing of the NPs without presence of water film.
Keywords: electron tomography; (scanning) transmission electron microscopy ((S)TEM); polystyrene latex spheres; calibration sample; metrology; accurate shape measurement; surface energy; nanoparticle deformation; quantitative electron tomography

Theoretical modeling of tunneling barriers in carbon-based molecular electronic junctions - Kondratenko, Mykola; Stoyanov, Stanislav R.; Gusarov, Sergey; Kovalenko, Andriy; Mccreery, Richard L. (The Journal of Physical Chemistry C, 2015)
Density functional theory (DFT) is applied to three models for carbon-based molecular junctions containing fragments of graphene with covalent edge-bonding to aromatic and aliphatic molecules, with the graphene representing a sp2 hybridized carbon electrode and the molecule representing a molecular layer between two electrodes. The DFT results agree well with experimental work functions and transport barriers, including the electronic coupling between molecular layers and graphitic contacts, and predict the compression of tunnel barriers observed for both ultraviolet photoelectron spectroscopy (UPS) and experimental tunneling currents. The results reveal the strong effect of the dihedral angle between the planes of the graphene electrode and the aromatic molecule and imply that the molecules with the smallest dihedral angle are responsible for the largest local current densities. In addition, the results are consistent with the proposal that the orbitals which mediate tunneling are those with significant electron density in the molecular layer. These conclusions should prove valuable for understanding the relationships between molecular structure and electronic transport as an important step toward rational design of carbon-based molecular electronic devices.

The spatially-resolved star formation history of the M31 outer disc - Bernard, Edouard J.; Ferguson, Annette M. N.; Chapman, Scott C.; Ibata, Rodrigo A.; Irwin, Mike J.; Lewis, Geraint F.; McConnachie, Alan W. (Monthly Notices of the Royal Astronomical Society: Letters, 2015)
We present deep Hubble Space Telescope Advanced Camera for Surveys observations of the stellar populations in two fields lying at 20 and 23 kpc from the centre of M31 along the south-west semimajor axis. These data enable the construction of colour–magnitude diagrams reaching the oldest main-sequence turn-offs (∼13 Gyr) which, when combined with another field at 25 kpc from our previous work, we use to derive the first precision constraints on the spatially-resolved star formation history of the M31 disc. The star formation rates exhibit temporal as well as field-to-field variations, but are generally always within a factor of 2 of their time average. There is no evidence of inside-out growth over the radial range probed. We find a median age of ∼7.5 Gyr, indicating that roughly half of the stellar mass in the M31 outer disc was formed before z ∼ 1. We also find that the age–metallicity relations (AMRs) are smoothly increasing from [Fe/H] ≃ −0.4 to solar metallicity between 10 and 3 Gyr ago, contrary to the flat AMR of the Milky Way disc at a similar number of scalelengths. Our findings provide insight on the roles of stellar feedback and radial migration in the formation and evolution of large disc galaxies.
Keywords: galaxies: evolution; galaxies: formation; galaxies: individual: M31; local group; galaxies: stellar content; galaxies: structure

The quality of massive open online courses - Downes, Stephen; Khan, Badrul H.; Ally, Mohamed (International Handbook of E-Learning: Volume 1 Theoretical Perspectives and Research, 2015)
The author would like to address the question of assessing the quality of massive open online courses. The assessment of the quality of anything is fraught with difficulties, depending as it does on some commonly understood account of what would count as a good example of the thing, what factors constitute success, and how that success against that standard is to be measured.

The polar and lateral flagella from Plesiomonas shigelloides are glycosylated with legionaminic acid - Merino, Susana; Aquilini, Eleonora; Fulton, Kelly M.; Twine, Susan M.; Tomás, Juan M. (Frontiers in Microbiology, 2015)
Plesiomonas shigelloides is the unique member of the Enterobacteriaceae family able to produce polar flagella when grow in liquid medium and lateral flagella when grown in solid or semisolid media. In this study on P. shigelloides 302-73 strain, we found two different gene clusters, one exclusively for the lateral flagella biosynthesis and the other one containing the biosynthetic polar flagella genes with additional putative glycosylation genes. P. shigelloides is the first Enterobacteriaceae were a complete lateral flagella cluster leading to a lateral flagella production is described. We also show that both flagella in P. shigelloides 302-73 strain are glycosylated by a derivative of legionaminic acid (Leg), which explains the presence of Leg pathway genes between the two polar flagella regions in their biosynthetic gene cluster. It is the first bacterium reported with O-glycosylated Leg in both polar and lateral flagella. The flagella O-glycosylation is essential for bacterial flagella formation, either polar or lateral, because gene mutants on the biosynthesis of Leg are non-flagellated. Furthermore, the presence of the lateral flagella cluster and Leg O-flagella glycosylation genes are widely spread features among the P. shigelloides strains tested.

The Na-O anticorrelation in horizontal branch stars: V. NGC 6723 - Gratton, R. G.; Lucatello, S.; Sollima, A.; Carretta, E.; Bragaglia, A.; Momany, Y.; D’orazi, V.; Salaris, M.; Cassisi, S.; Stetson, P. B. (Astronomy & Astrophysics, 2015)
We used FLAMES+GIRAFFE (Medusa mode) at the VLT to obtain moderately high resolution spectra for 30 red horizontal branch (RHB) stars, 4 RR Lyrae variables, and 17 blue horizontal branch (BHB) stars in the low-concentration, moderately metal-rich globular cluster NGC 6723 ([Fe/H] = −1.22 ± 0.08 from our present sample). The spectra were optimized to derive O and Na abundances. In addition, we obtained abundances for other elements, including N, Fe, Mg, Ca, Ni, and Ba. We used these data to discuss the evidence of a connection between the distribution of stars along the horizontal branch (HB) and the multiple populations that are typically present in globular clusters. We found that all RHB and most (13 out of 17) BHB stars are O-rich, Na-poor, and N-poor; these stars probably belong to the first stellar generation in this cluster. Only the four warmest observed stars are (moderately) O-poor, Na-rich, and N-rich, and they probably belong to the second generation. While our sample is not fully representative of the whole HB population in NGC 6723, our data suggest that in this cluster only HB stars warmer than ~9000 K, that is one fourth of the total, belong to the second generation, if at all. Since in many other clusters this fraction is about two thirds, we conclude that the fraction of first/second generation in globular clusters may be strongly variable. In addition, the wide range in colour of chemically homogeneous first-generation HB stars requires a considerable spread in mass loss (>0.10 M⊙). The reason for this spread is yet to be understood. Finally, we found a high Ba abundance, with a statistically significant radial abundance gradient.
Keywords: stars: abundances; stars: Population II; globular clusters: general; globular clusters: individual: NGC 6723; stars: evolution

The massive survey. II. stellar population trends out to large radius in massive early-type galaxies - Greene, Jenny E.; Janish, Ryan; Ma, Chung-Pei; McConnell, Nicholas J.; Blakeslee, John P.; Thomas, Jens; Murphy, Jeremy D. (The Astrophysical Journal, 2015)
We examine stellar population gradients in ~100 massive early-type galaxies spanning 180 < σ < 370 km s−₁ and MK of −22.5 to −26.5 mag, observed as part of the MASSIVE survey. Using integral-field spectroscopy from the Mitchell Spectrograph on the 2.7 m telescope at McDonald Observatory, we create stacked spectra as a function of radius for galaxies binned by their stellar velocity dispersion, stellar mass, and group richness. With excellent sampling at the highest stellar mass, we examine radial trends in stellar population properties extending to beyond twice the effective radius (∼2.5 Re). Specifically, we examine trends in age, metallicity, and abundance ratios of Mg, C, N, and Ca, and discuss the implications for star formation histories and elemental yields. At a fixed physical radius of 3–6 kpc (the likely size of the galaxy cores formed at high redshift), stellar age and [α/Fe] increase with increasing σ* and depend only weakly on stellar mass, as we might expect if denser galaxies form their central cores earlier and faster. If we instead focus on 1-1.5Re, the trends in abundance and abundance ratio are washed out, as might be expected if the stars at large radius were accreted by smaller galaxies. Finally, we show that when controlling for σ*, there are only very subtle differences in stellar population properties or gradients as a function of group richness; even at large radius, internal properties matter more than environment in determining star formation history
Keywords: galaxies: elliptical and lenticular; cD-galaxies: evolution; galaxies: kinematics and dynamics; galaxies: stellar content

The leptin receptor, a driver of adult neurogenesis that may treat Alzheimer's disease, has been found in murine dentate granule Cells' ciliary toolbox - Whitfield, James F.; Chakravarthy, Balu; Chiarini, Anna; Pra, Ilaria Dal; Armato, Ubaldo (Horizons in Neuroscience Research: Volume 21, 2015)
This is a story about the dentate gyrus's (gyrus dentatus) granule cells that are parts of the hippocampal memories-recording machinery in the brain's temporal lobes. These little cells, each with its single immobile cilium, share, with hippocampal CA3 pyramidal neurons, data from entorhinal cortical neurons that receive streams of data from the brain's many sensory regions about external happenings. There are many on-going efforts to understand how the granule cells separate potentially overlapping, hence potentially interfering, trains of similar data into separate threads or circuits with which CA3 and CA1 neurons can produce unique activity patterns and thus distinct instead of distorted memories. These patterns are then sent up in polymodal chunks to sites in the neocortex from which they can later be reassembled when needed into the original or with elapsed time and frequent accessing increasingly modified memories. These granule cells are very different from other neurons: in fact, they are born as tabulae rasae neurons open for novel input in adult rodent, human and other mammalian brains. They then grow old and synaptically loaded with memories. However, while the modellers have focussed on the contributions of the successive batches of adult-born dentate gyral granule cells to memory formation, they have ignored what appears to be another of these cells' special characteristics, i.e., loading potent adult neurogenesis-driving tools such as the SSTR3 receptor and the pan-neurotrophin p75NTR receptor into their cilia. Now we have found that they also put the functional leptin receptor, LepRb (ObRb), into their ciliary toolboxes. We looked for the leptin receptor in the cilium's toolbox for two reasons: the already established involvement of cilia in adult neurogenesis and the reported ability of leptin to stimulate adult neurogenesis in the dentate gyri of normal and transgenic Alzheimer's disease model mice. Thus, further study may show that signals from the granule cell's LepRb may be able to slow or even stop the hippocampal damage and cognitive impairment of Alzheimer's disease, an intracerebrally spreading neuronal connectome-opathy. However, at least until then, it seems obvious that we will never be able to understand the dentate gyrus's critical roles in adult neurogenesis and memory formation without knowing how its granule cells use the battery of tools in their single cilia.

The influence of ice accretion on the aerodynamic performance of a UAS airfoil - Szilder, Krzysztof; Yuan, Weixing (53rd AIAA Aerospace Sciences Meeting, 2015)
In this paper, we describe the results of numerical prediction of ice accretion and the resulting aerodynamic penalties on an SD7037 airfoil. NRC in-house numerical codes were used to compute the airflow field, drop trajectories, ice accretion and finally aerodynamic characteristics. The analysis was performed for cruise and landing conditions and for a wide range of icing conditions identified in the FAA Appendix C icing envelope, which cover a range of drop sizes, air temperatures and liquid water contents. For selected icing conditions, the resulting decrease in lift, increase in drag and change in pitching moment have been examined.

The identification of cis-regulatory elements: a review from a machine learning perspective - Li, Yifeng; Chen, Chih-Yu; Kaye, Alice M.; Wasserman, Wyeth W. (Biosystems, 2015)
The majority of the human genome consists of non-coding regions that have been called junk DNA. However, recent studies have unveiled that these regions contain cis-regulatory elements, such as promoters, enhancers, silencers, insulators, etc. These regulatory elements can play crucial roles in controlling gene expressions in specific cell types, conditions, and developmental stages. Disruption to these regions could contribute to phenotype changes. Precisely identifying regulatory elements is key to deciphering the mechanisms underlying transcriptional regulation. Cis-regulatory events are complex processes that involve chromatin accessibility, transcription factor binding, DNA methylation, histone modifications, and the interactions between them. The development of next-generation sequencing techniques has allowed us to capture these genomic features in depth. Applied analysis of genome sequences for clinical genetics has increased the urgency for detecting these regions. However, the complexity of cis-regulatory events and the deluge of sequencing data require accurate and efficient computational approaches, in particular, machine learning techniques. In this review, we describe machine learning approaches for predicting transcription factor binding sites, enhancers, and promoters, primarily driven by next-generation sequencing data. Data sources are provided in order to facilitate testing of novel methods. The purpose of this review is to attract computational experts and data scientists to advance this field.
Keywords: cis-regulatory elements; gene regulation; enhancers; promoters; machine learning; deep learning; ensemble learning; data integration

The human saliva metabolome - Dame, Zerihun T.; Aziat, Farid; Mandal, Rupasri; Krishnamurthy, Ram; Bouatra, Souhaila; Borzouie, Shima; Guo, An Chi; Sajed, Tanvir; Deng, Lu; Lin, Hong; Liu, Philip; Dong, Edison; et al. (Metabolomics, 2015)
Saliva is a clear, watery biofluid produced by the salivary glands to protect and lubricate the oral cavity. While mostly composed of water (99 %), the chemical composition of saliva is known to change quite dramatically in response to a variety of different physiological states, stimuli, insults and stressors. Unfortunately, among the human biofluids typically used in medical testing (such as blood and urine), saliva is rarely used. Given that saliva is the most easily accessible and readily obtained biofluid, this is rather unfortunate. Part of the reluctance to use saliva in medical testing likely has to do with the fact that its chemical composition is not well known. Here, a comprehensive characterization of the human saliva metabolome is presented. Multiple analytical platforms including nuclear magnetic resonance spectroscopy, gas chromatography mass spectrometry, direct flow injection/liquid chromatography mass spectrometry, inductively coupled plasma mass spectrometry, and high performance liquid chromatography were employed to quantify the metabolites that can be commonly detected in human saliva. Using this multiplatform approach, we were able to quantify and/or identify 308 salivary metabolites or metabolite species in human saliva. This experimental work was complemented with computer-aided literature mining that led to the identification and annotation of another 708 salivary metabolites. The combined collection of 853 non-redundant salivary metabolites or metabolite species together with their concentrations, related literature references, and links to their known disease associations are freely available at http://www.hmdb.ca/
Keywords: human saliva; quantitative; multi-platform; metabolomics; NMR; LC–MS

The Hubble Wide Field Camera 3 test of surfaces in the outer solar system: spectral variation on Kuiper belt objects - Fraser, Wesley C.; Brown, Michael E.; Glass, Florian (The Astrophysical Journal, 2015)
Here, we present additional photometry of targets observed as part of the Hubble Wide Field Camera 3 (WFC3) Test of Surfaces in the Outer Solar System. Twelve targets were re-observed with the WFC3 in the optical and NIR wavebands designed to complement those used during the first visit. Additionally, all of the observations originally presented by Fraser and Brown were reanalyzed through the same updated photometry pipeline. A re-analysis of the optical and NIR color distribution reveals a bifurcated optical color distribution and only two identifiable spectral classes, each of which occupies a broad range of colors and has correlated optical and NIR colors, in agreement with our previous findings. We report the detection of significant spectral variations on five targets which cannot be attributed to photometry errors, cosmic rays, point-spread function or sensitivity variations, or other image artifacts capable of explaining the magnitude of the variation. The spectrally variable objects are found to have a broad range of dynamical classes and absolute magnitudes, exhibit a broad range of apparent magnitude variations, and are found in both compositional classes. The spectrally variable objects with sufficiently accurate colors for spectral classification maintain their membership, belonging to the same class at both epochs. 2005 TV189 exhibits a sufficiently broad difference in color at the two epochs that span the full range of colors of the neutral class. This strongly argues that the neutral class is one single class with a broad range of colors, rather than the combination of multiple overlapping classes.
Keywords: Kuiper belt: general; planets and satellites: composition; techniques: photometric

The globular cluster system of NGC 6822 - Veljanoski, J.; Ferguson, A. M. N.; Mackey, A. D.; Huxor, A. P.; Hurley, J. R.; Bernard, E. J.; Côté, P.; Irwin, M. J.; Martin, N. F.; Burgett, W. S.; Chambers, K. C.; Flewelling, H.; et al. (Monthly Notices of the Royal Astronomical Society, 2015)
We present a comprehensive analysis of the globular cluster (GC) system of the Local Group dwarf irregular galaxy NGC 6822. Our study is based on homogeneous optical and near-IR photometry, as well as long-slit spectroscopic observations which are used to determine new radial velocities for six GCs, two of which had no previous spectroscopic information. We construct optical-near-IR colour–colour diagrams and through comparison to simple stellar population models infer that the GCs have old ages consistent with being 9 Gyr or older, while their metallicities are in the range between −1.6 ≲ [Fe/H] ≲ −0.4. We conduct a kinematic analysis of the GC population and find tentative evidence for weak net rotation of the GC system, in the same sense as that exhibited by the underlying spheroid. The most likely amplitude of rotation is ≈10 km s−1, approximately half the magnitude of the observed velocity dispersion. Finally, we use the GCs to estimate the dynamical mass of NGC 6822 within ∼11 kpc and we formally find it to be in the range between (3 and 4) × 109 M⊙. This implies an overall mass-to-light ratio in the range of ∼30–40 and indicates that NGC 6822 is highly dark-matter-dominated. The mass and the corresponding mass-to-light ratio estimates are affected by various additional systematic effects due to limitations of the data and the model that are not necessary reflected in the formal uncertainties.
Keywords: globular clusters: general; galaxies: individual: NGC 6822; galaxies: kinematics and dynamics; local group

The FRK1 mitogen-activated protein kinase kinase kinase (MAPKKK) from Solanum chacoense is involved in embryo sac and pollen development - Lafleur, E.; Kapfer, C.; Joly, V.; Liu, Yang; Tebbji, F.; Daigle, C.; Gray-mitsumune, M.; Cappadocia, M.; Nantel, A.; Matton, D. P. (Journal of Experimental Botany, 2015)
The fertilization-related kinase 1 (ScFRK1), a nuclear-localized mitogen-activated protein kinase kinase kinase (MAPKKK) from the wild potato species Solanum chacoense, belongs to a small group of pMEKKs that do not possess an extended N- or C-terminal regulatory domain. Initially selected based on its highly specific expression profile following fertilization, in situ expression analyses revealed that the ScFRK1 gene is also expressed early on during female gametophyte development in the integument and megaspore mother cell and, later, in the synergid and egg cells of the embryo sac. ScFRK1 mRNAs are also detected in pollen mother cells. Transgenic plants with lower or barely detectable levels of ScFRK1 mRNAs lead to the production of small fruits with severely reduced seed set, resulting from a concomitant decline in the number of normal embryo sacs produced. Megagametogenesis and microgametogenesis were affected, as megaspores did not progress beyond the functional megaspore (FG1) stage and the microspore collapsed around the first pollen mitosis. As for other mutants that affect embryo sac development, pollen tube guidance was severely affected in the ScFRK1 transgenic lines. Gametophyte to sporophyte communication was also affected, as observed from a marked change in the transcriptomic profiles of the sporophytic tissues of the ovule. The ScFRK1 MAPKKK is thus involved in a signalling cascade that regulates both male and female gamete development.

The establishment of high DC shunt calibration system at KRISS and comparison with NRC - Kim, Kyu-Tae; Jung, Jae Kap; Lee, Young Seob; So, Eddy; Bennett, David (IEEE Transactions on Instrumentation and Measurement, 2015)
The application of a binary step-up method has been investigated at the Korea Research Institute of Standards and Science (KRISS) for establishment of high dc standards based on the calibration system of high dc shunts up to a few thousand amperes in which the current dependence of the shunt resistance can be measured. A successive step-up method with a pair of high dc shunts was suggested to link the unknown high current to the values of low current level which are already known. The step-up approach was further modified with employing a current monitor to extract the information on the current dependence of the shunt and the source current changes during the step-up measurement. To validate the modified step-up technology, a comparison of high dc shunt resistance was carried out with National Research Council (NRC) in which both the KRISS and the NRC results agreed well within the standard deviation of the measurement on the order of about 0.01%.
Keywords: shunts; calibration; current measurement; current supplies; current transformers; electrical resistance measurement

Subwavelength waveguide structures for optical interconnects - Cheben, P.; Benedikovic, D.; Alonso-Ramos, C.; Schmid, J. H.; Papes, M.; Xu, D.-X; Janz, S.; Wang, S.; Vachon, M.; Wanguemert-Perez, G.; Halir, R.; Ortega-Monux, A.; et al. (2015 17th International Conference on Transparent Optical Networks (ICTON), 2015)
We report our advances in development of subwavelength engineered waveguide structures. This unique NRC patented technology [1,2] allows synthesis of a metamaterial with an unprecedented control of material properties, constituting a powerful tool for a designer of photonic integrated circuits. We have demonstrated a number of subwavelength engineered devices operating at telecom wavelengths [3-7], for example fibre-chip couplers, waveguide crossings, WDM multiplexers, ultra-fast optical switches, athermal waveguides, evanescent field sensors, polarization rotators, transceiver hybrids and ultra-broadband interference couplers. The subwavelength metamaterial concept has been adopted by industry (IBM) for fibre-chip coupling and subwavelength structures are likely to become key building blocks for the next generation of integrated photonic circuits. Here we present an overview of recent examples of our subwavelength engineered structures, with an emphasis on couplers for optical interconnects and evanescent field sensors. We demonstrate an unprecedented control over the light coupling between optical fibers and silicon chips by constructing metamaterial couplers operating at telecom (1.55 μm) and datacom (1.3 μm) wavelengths. We also show that by subwavelength patterning of silicon-wire waveguides the field delocalization can be engineered to increase the sensitivity of evanescent field waveguide sensors [8]. Finally, we discuss some emerging applications of subwavelength engineered structures in mid-infrared photonics.
Keywords: wavelength 1.3 mum; subwavelength waveguide structures; optical interconnects; material properties; photonic integrated circuits; fibre-chip couplers; WDM multiplexers; ultra-fast optical switches; athermal waveguides; evanescent field sensors; polarization rotators; transceiver hybrids; ultra-broadband interference couplers; IBM; fibre-chip coupling; subwavelength structures; integrated photonic circuits; light coupling; optical fibers; metamaterial couplers; datacom; evanescent field waveguide sensors; mid-infrared photonics; wavelength 1.55 mum

Ion channels: small molecules versus biologics: the quest for the ideal Nav1.7 inhibitor - Perkins, Martin; Martina, Marzia (Drug Target Review, 2015)
Ion channels modulate and control many fundamental physiological processes in various tissues and alterations in their functions give rise to a wide range of pathophysiologies, which makes them important drug targets. Indeed, for decades, drugs modulating ion channel activity have been targeted by the pharmaceutical industry. Historically, however, developing drugs targeting this protein class has been difficult, the most challenging aspect being the identification of an appropriate drug lead with desirable selectivity. This has been a particular issue for small molecules targeting ion channels.
Keywords: drug targets; Ion channels

The emission nebula Sh 2-174: a radio investigation of the surrounding region - Ransom, R. R.; Kothes, R.; Geisbuesch, J.; Reich, W.; Landecker, T. L. (The Astrophysical Journal, 2015)
Sh 2-174 is believed to be either a planetary nebula (PN) or ionized, ambient interstellar medium (ISM). We present in this paper 1420 MHz polarization, 1420 MHz total intensity (Stokes-I), and neutral hydrogen (H I) images of the region around Sh 2-174. The radio images address not only the nature of the object, but also the history of the relationship between Sh 2-174 and its surrounding environment. The H I images show that Sh 2-174 sits presently at the center of a ~1fdg2 × ~0fdg4 cloud (with peak hydrogen density n H = 4 ± 2 cm–3). The Stokes-I image shows thermal-emission peaks (with electron densities ne = 11 ± 3 cm–3) coincident with the R-band optical nebula, as well as low-surface-brightness emission from an ionized "halo" around Sh 2-174 and from an ionized "plateau" extending southeast from the cloud. The polarization images reveal Faraday-rotation structures along the projected trajectory of Sh 2-174, including a high-contrast structure with "arms" that run precisely along the eastern edge of the H I cloud and a wide central region that merges with the downstream edge of Sh 2-174. The high-contrast structure is consistent with an ionized tail that has both early-epoch (before Sh 2-174 entered the cloud) and present-epoch (after Sh 2-174 entered the cloud) components. Furthermore, our rotation-measure analysis indicates that the ISM magnetic field is deflected at the leading edge of Sh 2-174. The downstream tail and upstream field deflection point to a PN-ISM interaction. Our estimated space velocity for the host white dwarf (GD 561) demonstrates that Sh 2-174 entered the cloud ~27,000 yr ago, and gives a PN-ISM interaction timescale lesssim 2.0 × 105 yr. We estimate an ambient magnetic field in the cloud of 11 ± 3 μG.
Keywords: ISM: magnetic fields; ISM: structure; planetary nebulae: individual (Sh 2-174); stars: individual (GD 561); stars: kinematics and dynamics; techniques: polarimetric

The Carina Project: VIII. the α-element abundances - Fabrizio, M.; Nonino, M.; Bono, G.; Primas, F.; Thévenin, F.; Stetson, P. B.; Cassisi, S.; Buonanno, R.; Coppola, G.; Da Silva, R. O.; Dall’ora, M.; Ferraro, I.; et al. (Astronomy & Astrophysics, 2015)
We have performed a new abundance analysis of Carina red giant (RG) stars from spectroscopic data collected with UVES (high spectral resolution) and FLAMES/GIRAFFE (high and medium resolution) at ESO/VLT. The former sample includes 44 RGs, while the latter consists of 65 (high-resolution) and ~800 (medium-resolution) RGs, covering a significant fraction of the galaxy’s RG branch, and red clump stars. To improve the abundance analysis at the faint magnitude limit, the FLAMES/GIRAFFE data were divided into ten surface gravity and effective temperature bins. The spectra of the stars belonging to the same gravity and temperature bin were stacked. This approach allowed us to increase the signal-to-noise ratio in the faint magnitude limit (V≥ 20.5 mag) by at least a factor of five. We took advantage of the new photometry index cU,B,I introduced recently as an age and probably a metallicity indicator to split stars along the red giant branch. These two stellar populations display distinct [Fe/H] and [Mg/H] distributions: their mean iron abundances are −2.15 ± 0.06 dex (σ = 0.28), and −1.75 ± 0.03 dex (σ = 0.21), respectively. The two iron distributions differ at the 75% level. This supports preliminary results. Moreover, we found that the old and intermediate-age stellar populations have mean [Mg/H] abundances of −1.91 ± 0.05 dex (σ = 0.22) and −1.35 ± 0.03 dex (σ = 0.22); these differ at the 83% level. Carina’s α-element abundances agree, within 1σ, with similar abundances for field halo stars and for cluster (Galactic and Magellanic) stars. The same outcome applies to nearby dwarf spheroidals and ultra-faint dwarf galaxies in the iron range covered by Carina stars. Finally, we found evidence of a clear correlation between Na and O abundances, thus suggesting that Carina’s chemical enrichment history is quite different from that in the globular clusters.
Keywords: galaxies: dwarf; galaxies: stellar content; stars: fundamental parameters; galaxies: individual: Carina; stars: abundances

The Carina project. IX. on hydrogen and helium burning variables - Coppola, G.; Marconi, M.; Stetson, P. B.; Bono, G.; Braga, V. F.; Ripepi, V.; Dall’ora, M.; Musella, I.; Buonanno, R.; Fabrizio, M.; Ferraro, I.; Fiorentino, G.; et al. (The Astrophysical Journal, 2015)
We present new multiband (UBVI) time-series data of helium burning variables in the Carina dwarf spheroidal galaxy. The current sample includes 92 RR Lyrae—six of them are new identifications—and 20 Anomalous Cepheids, one of which is new identification. The analysis of the Bailey diagram shows that the luminosity amplitude of the first overtone component in double-mode variables is located along the long-period tail of regular first overtone variables, while the fundamental component is located along the short-period tail of regular fundamental variables. This evidence further supports the transitional nature of these objects. Moreover, the distribution of Carina double-mode variables in the Petersen diagram (P1/P0 versus P0) is similar to metal-poor globulars (M15, M68), to the dwarf spheroidal Draco, and to the Galactic Halo. This suggests that the Carina old stellar population is metal-poor and affected by a small spread in metallicity. We use trigonometric parallaxes for five field RR Lyrae stars to provide an independent estimate of the Carina distance using the observed reddening free Period–Wesenheit [PW, (BV)] relation. Theory and observations indicate that this diagnostic is independent of metallicity. We found a true distance modulus of μ = 20.01 ± 0.02 (standard error of the mean) ± 0.05 (standard deviation) mag. We also provided independent estimates of the Carina true distance modulus using four predicted PW relations (BV, BI, VI, BVI) and we found: μ = (20.08 ± 0.007 ± 0.07) mag, μ = (20.06 ± 0.006 ± 0.06) mag, μ = (20.07 ± 0.008 ± 0.08) mag, and μ = (20.06 ± 0.006 ± 0.06) mag. Finally, we identified more than 100 new SX Phoenicis stars that together with those already known in the literature (340) make Carina a fundamental laboratory for constraining the evolutionary and pulsation properties of these transitional variables.

The ACS Fornax cluster survey. XI. catalog of globular cluster candidates - Jordán, Andrés; Peng, Eric W.; Blakeslee, John P.; Côté, Patrick; Eyheramendy, Susana; Ferrarese, Laura (The Astrophysical Journal Supplement Series, 2015)
We present catalogs of globular cluster (GC) candidates for 43 galaxies from the ACS Fornax Cluster survey, a program designed to carry out imaging of early-type members of the Fornax cluster using the Advanded Camera for Surveys (ACS) on board the Hubble Space Telescope. The procedure to select bona fide GC candidates from the full list of detections is based on model-based clustering methods, similar to those adopted for a survey of 100 galaxies in the Virgo cluster, the ACS Virgo Cluster Survey. For each detected source, we measure its position, magnitudes in the F475W (≈Sloan g) and F850LP (≈Sloan z) bandpasses, half-light radii obtained by fitting point-spread function-convolved King models to the observed light distribution, and an estimate of the probabilty PGC that each cataloged source is a GC. These measurements are presented for 9136 sources, of which 6275 have PGC ≥ 0.5, and are thus likely GCs.

Tabletop imaging of structural evolutions in chemical reactions - Ibrahim, Heide; Wales, Benji; Beaulieu, Samuel; Schmidt, Bruno E.; Thiré, Nicolas; Fowe, Emmanuel P.; Bisson, Éric; Hebeisen, Christoph T.; Wanie, Vincent; Giguére, Mathieu; Kieffer, Jean-claude; Spanner, Michael; et al. (Ultrafast Phenomena XIX, 2015)
The first high-resolution molecular movie of proton migration in the acetylene cation is obtained using a tabletop multiphoton pump-probe approach—an alternative to demanding free-electron-lasers and other VUV light sources when ionizing from the HOMO-1.

Synthesis, structure, and magnetic properties of novel B-site ordered double perovskites, SrLaMReO6 (M = Mg, Mn, Co and Ni) - Thompson, Corey M.; Chi, Lisheng; Hayes, John R.; Hallas, Alannah M.; Wilson, Murray N.; Munsie, Timothy J. S.; Swainson, Ian P.; Grosvenor, Andrew P.; Luke, Graeme M.; Greedan, John E. (Dalton Transactions, 2015)
Four new double perovskites, SrLaMReO6 (M = Mg, Mn, Co, Ni) in which Re5+ (5d2) is present, were prepared via conventional solid state reactions and characterized by X-ray and neutron powder diffraction, XANES, SQUID magnetometry, and muon spin relaxation (μSR). Synchrotron X-ray and neutron diffraction experiments confirmed that all compounds crystallize in the monoclinic P21/n structure type, which consists of alternately corner-shared octahedra of MO6 and ReO6. Rietveld refinement results indicated anti-site mixing of less than 7% on the M/Re sites. Bond valence sum calculations (BVS) suggest all M and Re ions are 2+ and 5+, respectively, and for the Mn-containing phase this is also supported by XANES measurements. All of the materials are paramagnetic at room-temperature and their Curie–Weiss temperatures are positive (except for Mg) indicating net ferromagnetic interactions. No evidence for long-range magnetic order is evident in the dc magnetic susceptibility and μSR measurements for SrLaMgReO6 to 2 K. The Mn-phase shows long-range order at TC = 190 K and neutron diffraction revealed a ferromagnetic structure with a refined net moment of ∼3.7μB. Both Co- and Ni-containing phases exhibit spin glass behavior at TG = 23 and 30 K, respectively, which is supported by neutron diffraction and a.c. susceptibility data. The structure and physical properties of these four new rhenium based ordered double perovskites are compared to the closely related “pillared perovskites”, La5Re3MO16, the isoelectronic Os6+ (5d2) double perovskite Sr2CoOsO6, and the Re6+ (5d1) double perovskites, Sr2MReO6, (M = Mg, Ca, Mn, Co, Ni).

Synthesis and characterization of poly(ω-pentadecalactone) for its industrial-scale production - Chang, Qing; Li, Li; Yang, Dalei; Zhang, Mingyao; Ton-That, Minh-Tan; Hu, Wei; Lü, Shuai (Chemical Research in Chinese Universities, 2015)
The synthesis of biomaterial poly(ω-pentadecalactone)(PPDL) with yttrium isopropoxide as initiator in bulk was explored for its industrial-scale production. The weight-average molecular weight(M¯w) of PPDL could be controlled by the molar ratio of monomer to initiator(M/I), polymerization temperature(Tp) and period(tp). The synthesis conditions were optimized, and a high M¯w of 9.2×104 of PPDL could be obtained by the reaction at an M/I molar ratio of 1000/1 and 100 °C for only 30 min, which presented tough properties with a tensile strength of about 20 MPa and an elongation at break of about 300%. This mechanical property was comparable to that of high density polyethylene(HDPE). The melting point was about 96 °C, and 5% of mass loss temperature(T5%) was as high as 340 °C. Thus, the PPDL with good mechanical properties and high thermal stability can be synthesized without solvent at low expenses.
Keywords: poly(ω-pentadecalactone); polymerization; characterization

Sub-mm jet properties of the X-ray binary swift J1745–26 - Tetarenko, A. J.; Sivakoff, G. R.; Miller-Jones, J. C. A.; Curran, P. A.; Russell, T. D.; Coulson, I. M.; Heinz, S.; Maitra, D.; Markoff, S. B.; Migliari, S.; Petitpas, G. R.; Rupen, M. P.; et al. (The Astrophysical Journal, 2015)
We present the results of our observations of the early stages of the 2012–2013 outburst of the transient black hole X-ray binary (BHXRB), Swift J1745–26, with the Very Large Array, Submillimeter Array, and James Clerk Maxwell telescope (SCUBA–2). Our data mark the first multiple-band mm and sub-mm observations of a BHXRB. During our observations the system was in the hard accretion state producing a steady, compact jet. The unique combination of radio and mm/sub-mm data allows us to directly measure the spectral indices in and between the radio and mm/sub-mm regimes, including the first mm/sub-mm spectral index measured for a BHXRB. Spectral fitting revealed that both the mm (230 GHz) and sub-mm (350 GHz) measurements are consistent with extrapolations of an inverted power law from contemporaneous radio data (1–30 GHz). This indicates that, as standard jet models predict, a power law extending up to mm/sub-mm frequencies can adequately describe the spectrum, and suggests that the mechanism driving spectral inversion could be responsible for the high mm/sub-mm fluxes (compared to radio fluxes) observed in outbursting BHXRBs. While this power law is also consistent with contemporaneous optical data, the optical data could arise from either jet emission with a jet spectral break frequency of Vbreak ≳ 1 x 10^14 Hz or the combination of jet emission with a lower jet spectral break frequency of Vbreak ≳ 2 x 10^11 Hz and accretion disk emission. Our analysis solidifies the importance of the mm/sub-mm regime in bridging the crucial gap between radio and IR frequencies in the jet spectrum, and justifies the need to explore this regime further.
Keywords: black hole physics; ISM: jets and outflows; radio continuum: stars; stars: individual (Swift J1745-26); submillimeter: stars; X-rays: binaries

Study of the mechanism for electrodeposition of dendrite-free zinc in an alkaline electrolyte modified with 1-ethyl-3-methylimidazolium dicyanamide - Xu, M.; Ivey, D. G.; Qu, W.; Xie, Z. (Journal of Power Sources, 2015)
Electrodeposition of Zn was conducted in a new electrolyte system composed of an alkaline solution (9 M KOH + 5 wt% ZnO) modified with a small amount (0.5 wt%) of room temperature ionic liquid 1-ethyl-3-methylimidazolium dicyanamide (EMI-DCA). At a high deposition current density of 80 mA cm−2, a porous, dendrite-free Zn film characterized by clusters of small Zn particles was obtained. The mechanism for the modified Zn morphology in the EMI-DCA containing electrolyte was studied by cyclic voltammetry, chronoamperometry, electrochemical impedance spectroscopy (EIS) and scanning electron microscopy. It was found that the addition of EMI-DCA changed the Zn nucleation process and reduced the potential variation during electrodeposition, which suppressed the uneven growth of Zn deposits and the formation of Zn dendrites. EIS results indicated that there was adsorption of EMI+ cations at the Zn film/electrolyte interface, which may have contributed to suppressed dendritic Zn growth.
Keywords: Zn electrodeposition; alkaline; room temperature ionic liquids; batteries

Structural investigation of cell wall polysaccharides of Lactobacillus delbrueckii subsp. bulgaricus 17 - Vinogradov, E.; Sadovskaya, I.; Cornelissen, A.; Van sinderen, D. (Carbohydrate Research, 2015)
Lactobacilli are valuable strains for commercial (functional) food fermentations. Their cell surface-associated polysaccharides (sPSs) possess important functional properties, such as acting as receptors for bacteriophages (bacterial viruses), influencing autolytic characteristics and providing protection against antimicrobial peptides. The current report provides an elaborate molecular description of several surface carbohydrates of Lactobacillus delbrueckii subsp. bulgaricus strain 17. The cell surface of this strain was shown to contain short chain poly(glycerophosphate) teichoic acids and at least two different sPSs, designated here as sPS1 and sPS2, whose chemical structures were examined by 2D nuclear magnetic resonance spectroscopy and methylation analysis. Neutral branched sPS1, extracted with n-butanol, was shown to be composed of hexasaccharide repeating units (-[α-d-Glcp-(1-3)-]-4-β-l-Rhap2OAc-4-β-d-Glcp-[α-d-Galp-(1-3)]-4-α-Rhap-3-α-d-Galp-), while the major component of the TCA-extracted sPS2 was demonstrated to be a linear d-galactan with the repeating unit structure being (-[Gro-3P-(1-6)-]-3-β-Galf-3-α-Galp-2-β-Galf-6-β-Galf-3-β-Galp-).

Structural and magnetic phase transitions near optimal superconductivity in BaFe2(As1−xPx)2 - Hu, Ding; Lu, Xingye; Zhang, Wenliang; Luo, Huiqian; Li, Shiliang; Wang, Peipei; Chen, Genfu; Han, Fei; Banjara, Shree R.; Sapkota, A.; Kreyssig, A.; Goldman, A. I.; et al. (Physical Review Letters, 2015)
We use nuclear magnetic resonance (NMR), high-resolution x-ray, and neutron scattering studies to study structural and magnetic phase transitions in phosphorus-doped BaFe2(As1−xPx)2. Previous transport, NMR, specific heat, and magnetic penetration depth measurements have provided compelling evidence for the presence of a quantum critical point (QCP) near optimal superconductivity at x=0.3. However, we show that the tetragonal-to-orthorhombic structural (Ts) and paramagnetic to antiferromagnetic (AF, TN) transitions in BaFe2(As1−xPx)2 are always coupled and approach TN≈Ts≥Tc (≈29  K) for x=0.29 before vanishing abruptly for x≥0.3. These results suggest that AF order in BaFe2(As1−xPx)2 disappears in a weakly first-order fashion near optimal superconductivity, much like the electron-doped iron pnictides with an avoided QCP.

Statistical analysis of the ice loading events on the confederation bridge - Poirier, L.; Babaei, H.; Frederking, R. (POAC '15: Proceedings of the 23rd International Conference on Port and Ocean Engineering under Arctic Conditions, 2015)
We have examined the ice loading forces on two piers of the Confederation Bridge during the 2012-13 ice season using the updated NRC ice load monitoring system. The new system allows better time synchronization of the tiltmeter and video data from each pier as well as the anemometer. The new system has allowed for the analysis of two large ice loading events simultaneously occurring at two adjacent Confederation Bridge piers and discussion of the relation between the forces on each pier during the events. The maximum load on a single pier was 3640 kN, when a large flow with embedded ridges stalled against two adjacent piers on April 6th, 2013. The maximum total load on the two adjacent piers was 5130 kN, fifty-six minutes after the single pier maximum. General statistics on the ice loads during a subset of the ice season were performed. Average ice loads during our observation period were 150 - 200 kN. Further refinement of the ice load and wind coefficients used at the NRC monitored bridge piers may be suggested from this work.
Keywords: bridge piers; ice; loads (forces); ocean engineering; confederation bridge; general statistics; maximum load; observation period; time synchronization; wind coefficients

Special track on computational biology and bioinformatics (CO-BIO2) - Lecca, P.; Tulpan, D.; Corchado, J. M. (Proceedings of the 30th Annual ACM Symposium on Applied Computing, 2015)

Spatio-angular minimum-variance tomographic controller for multi-object adaptive-optics systems - Correia, Carlos M.; Jackson, Kate; Véran, Jean-Pierre; Andersen, David; Lardière, Olivier; Bradley, Colin (Applied Optics, 2015)
Multi-object astronomical adaptive optics (MOAO) is now a mature wide-field observation mode to enlarge the adaptive-optics-corrected field in a few specific locations over tens of arcminutes. The work-scope provided by open-loop tomography and pupil conjugation is amenable to a spatio-angular linear-quadratic-Gaussian (SA-LQG) formulation aiming to provide enhanced correction across the field with improved performance over static reconstruction methods and less stringent computational complexity scaling laws. Starting from our previous work, we use stochastic time-progression models coupled to approximate sparse measurement operators to outline a suitable SA-LQG formulation capable of delivering near optimal correction. Under the spatio-angular framework the wavefronts are never explicitly estimated in the volume, providing considerable computational savings on 10-m-class telescopes and beyond. We find that for Raven, a 10-m-class MOAO system with two science channels, the SA-LQG improves the limiting magnitude by two stellar magnitudes when both the Strehl ratio and the ensquared energy are used as figures of merit. The sky coverage is therefore improved by a factor of ∼5.

Simulations of interdigitated electrode interactions with gold nanoparticles for impedance-based biosensing applications - Mackay, Scott; Hermansen, Peter; Wishart, David; Chen, Jie (Sensors, 2015)
In this paper, we describe a point-of-care biosensor design. The uniqueness of our design is in its capability for detecting a wide variety of target biomolecules and the simplicity of nanoparticle enhanced electrical detection. The electrical properties of interdigitated electrodes (IDEs) and the mechanism for gold nanoparticle-enhanced impedance-based biosensor systems based on these electrodes are simulated using COMSOL Multiphysics software. Understanding these properties and how they can be affected is vital in designing effective biosensor devices. Simulations were used to show electrical screening develop over time for IDEs in a salt solution, as well as the electric field between individual digits of electrodes. Using these simulations, it was observed that gold nanoparticles bound closely to IDEs can lower the electric field magnitude between the digits of the electrode. The simulations are also shown to be a useful design tool in optimizing sensor function. Various different conditions, such as electrode dimensions and background ion concentrations, are shown to have a significant impact on the simulations.
Keywords: COMSOL; biosensor; gold nanoparticles; interdigitated electrodes

Simulating electrical properties of interdigitated electrode designs for impedance-based biosensing applications - Mackay, Scott; Hermansen, Peter; Wishart, David; Hiebert, Wayne; Chen, Jie (2015 IEEE 28th Canadian Conference on Electrical and Computer Engineering (CCECE), 2015)
In this paper, we describe a point-of-care biosensor design. The uniqueness of our design is in its capability for detecting a wide variety of target biomolecules and the simplicity of nanoparticle enhanced electrical detection. The electrical properties of interdigitated electrodes and the mechanism for gold nanoparticle-enhanced impedance-based biosensor systems based on these electrodes were simulated using COMSOL Multiphysics software. Understanding these properties and how they can be affected by the design of the sensor, environment during detection, and target biomolecules is vital in designing effective biosensor devices. Simulations were used to show electrical screening for interdigitated electrodes in a salt solution as well as the electric field between individual digits of electrodes. Using these simulations, it was observed that gold nanoparticles bound closely to interdigitated electrodes can lower the electric field magnitude between the digits of the electrode.
Keywords: electrodes; biological system modeling; electric fields; biosensors; gold; nanoparticles; electric variables measurement

Sampling current ratio measurement system for calibration of current transducers up to 10 kA With 5 • 10‾⁶ uncertainty - Van den brom, Helko E.; Rietveld, Gert; So, Eddy (IEEE Transactions on Instrumentation and Measurement, 2015)
A sampling current ratio measurement system has been developed, tested, and validated for the accurate complex ratio measurement of ac current transducers. Calibrations can be performed for primary currents up to 10 kA with typical expanded uncertainties of 5 • 10‾⁶ in magnitude and 5 μrad in phase (k = 2). A unique property of the system is the use of digitizers for sampling of the secondary current signals and step-down transformers with a large number of current ratios. Therefore, the system does not require the current transducer under test to be a current transformer having a nominal ratio equal to the reference current transformer. Furthermore, it allows for the accurate calibration of a large variety of different current transformers and other types of current transducers. A bilateral comparison between VSL and NRC confirms the stated uncertainty.

Rutile phase n- and p-type anodic titania nanotube arrays with square-shaped pore morphologies - Kar, Piyush; Zhang, Yun; Farsinezhad, Samira; Mohammadpour, Arash; Wiltshire, Benjamin D.; Sharma, Himani; Shankar, Karthik (Chemical Communications, 2015)
Rutile-phase TiO2 nanotube arrays without broken walls were formed by annealing of anodically formed nanotubes in a propane flame at 650 °C and in air at 750 °C. An unusual morphological transformation was observed from the ellipsoidal pore-shapes of titania nanotubes grown in aqueous electrolyte to a square-shaped pore structure subsequent to the anneals. 750 °C annealed nanotubes were found to be lightly p-type, rare in TiO2.

Rosette nanotubes alter IgE-Mediated degranulation in the rat basophilic leukemia (RBL)-2H3 cell line - Ede, James D.; Ortega, Van A.; Boyle, David; Beingessner, Rachel L.; Hemraz, Usha D.; Fenniri, Hicham; Stafford, James L.; Goss, Greg G. (Toxicological Sciences, 2015)
In this study, the effects of rosette nanotube (RNT) exposure on immune cell viability and function were investigated in vitro using the rat basophilic leukemia (RBL)-2H3 cell line. RBL-2H3 viability was decreased in a dose- and time-dependent manner after lysine-functionalized RNT (K-RNT) exposure. In addition, K-RNTs had a significant effect on RBL-2H3 degranulation. When K-RNT exposure was concurrent with IgE sensitization, 50 and 100 mg l−1 K-RNTs elicited a heightened degranulatory response compared with IgE alone. Exposure to 50 and 100 mg l−1 K-RNTs also caused degranulation in RBL-2H3 cells not sensitized with IgE (0 ng ml−1 IgE). Furthermore, in cells preexposed to K-RNTs for 2 h and subsequently washed, sensitized, and stimulated with IgE, a potentiated degranulatory response was observed. Using confocal laser scanning microscopy and a fluorescein isothiocyanate (FITC)-functionalized RNT construct (termed FITC1/TBL19-RNT), we demonstrated a strong and direct affiliation between RNTs and RBL-2H3 cell membranes. We also demonstrated cellular internalization of RNTs after 2 h of exposure. Together, these data demonstrate that RNTs may affiliate with the cellular membrane of RBL-2H3 cells and can be internalized. These interactions can affect viability and alter the ability of these cells to elicit IgE-FcεR mediated degranulation.
Keywords: degranulation; nanotoxicology; inflammation; self-assembly; rosette nanotubes

Role of water in ligand binding to maltose-binding protein: insight from a new docking protocol based on the 3D-RISM-KH molecular theory of solvation - Huang, Wenjuan; Blinov, Nikolay; Wishart, David S.; Kovalenko, Andriy (Journal of Chemical Information and Modeling, 2015)
Maltose-binding protein is a periplasmic binding protein responsible for transport of maltooligosaccarides through the periplasmic space of Gram-negative bacteria, as a part of the ABC transport system. The molecular mechanisms of the initial ligand binding and induced large scale motion of the protein’s domains still remain elusive. In this study, we use a new docking protocol that combines a recently proposed explicit water placement algorithm based on the 3D-RISM-KH molecular theory of solvation and conventional docking software (AutoDock Vina) to explain the mechanisms of maltotriose binding to the apo-open state of a maltose-binding protein. We confirm the predictions of previous NMR spectroscopic experiments on binding modes of the ligand. We provide the molecular details on the binding mode that was not previously observed in the X-ray experiments. We show that this mode, which is defined by the fine balance between the protein–ligand direct interactions and solvation effects, can trigger the protein’s domain motion resulting in the holo-closed structure of the maltose-binding protein with the maltotriose ligand in excellent agreement with the experimental data. We also discuss the role of water in blocking unfavorable binding sites and water-mediated interactions contributing to the stability of observable binding modes of maltotriose.

Resonant wavelength conversion in gallium phosphide nanostructures - Lake, David; Mitchell, Matthew; Hryciw, Aaron; Jayakumar, Harishankar; Barclay, Paul E. (CLEO: 2015, 2015)
Second Harmonic Generation in gallium phosphide microdisks is demonstrated.

Representation based translation evaluation metrics - Chen, Boxing; Guo, Hongyu (Proceedings of the 53rd Annual Meeting of the Association for Computational Linguistics and the 7the International Joint Conference on Natural Language Processing (Short Papers), Beijing, China, July 26-31, 2015, 2015)
Precisely evaluating the quality of a translation against human references is a challenging task due to the flexible word ordering of a sentence and the existence of a large number of synonyms for words. This paper proposes to evaluate translations with distributed representations of words and sentences. We study several metrics based on word and sentence representations and their combination. Experiments on the WMT metric task shows that the metric based on the combined representations achieves the best performance, outperforming the state-of-the-art translation metrics by a large margin. In particular , training the distributed representations only needs a reasonable amount of mono-lingual, unlabeled data that is not necessary drawn from the test domain.

Reference and relative dosimetry of standard and small photon fields with new commercially available detectors - Muir, B. R.; Mcewen, M. R. (World Congress on Medical Physics and Biomedical Engineering, June 7-12, 2015, Toronto, Canada, 2015)
The PTW microDiamond synthetic diamond detector and the Exradin W1 plastic scintillation detector (PSD) are new commercially available detectors designed for small field dosimetry. This work aims to examine the performance of a single version of each detector for reference and relative dosimetry applications in standard and small fields. Uncertainties are analyzed to assess the accuracy of measurements made using these detectors.
Keywords: small field dosimetry; output factor; plastic scintillation detector; diamond detectorionization chamber

Reconstructing folding energy landscapes from splitting probability analysis of single-molecule trajectories - Manuel, Ajay P.; Lambert, John; Woodside, Michael T. (Proceedings of the National Academy of Sciences, 2015)
Structural self-assembly in biopolymers, such as proteins and nucleic acids, involves a diffusive search for the minimum-energy state in a conformational free-energy landscape. The likelihood of folding proceeding to completion, as a function of the reaction coordinate used to monitor the transition, can be described by the splitting probability, pfold(x). Pfold encodes information about the underlying energy landscape, and it is often used to judge the quality of the reaction coordinate. Here, we show how pfold can be used to reconstruct energy landscapes from single-molecule folding trajectories, using force spectroscopy measurements of single DNA hairpins. Calculating pfold(x) directly from trajectories of the molecular extension measured for hairpins fluctuating in equilibrium between folded and unfolded states, we inverted the result expected from diffusion over a 1D energy landscape to obtain the implied landscape profile. The results agreed well with the landscapes reconstructed by established methods, but, remarkably, without the need to deconvolve instrumental effects on the landscape, such as tether compliance. The same approach was also applied to hairpins with multistate folding pathways. The relative insensitivity of the method to the instrumental compliance was confirmed by simulations of folding measured with different tether stiffnesses. This work confirms that the molecular extension is a good reaction coordinate for these measurements, and validates a powerful yet simple method for reconstructing landscapes from single-molecule trajectories.
Keywords: single-molecule biophysics; force spectroscopy; nucleic acid folding; protein folding; optical tweezers

Rechargeable Zn-air batteries: progress in electrolyte development and cell configuration advancement - Xu, M.; Ivey, D. G.; Xie, Z.; Qu, W. (Journal of Power Sources, 2015)
Zn-air batteries, which are cost-effective and have high energy density, are promising energy storage devices for renewable energy and power sources for electric transportation. Nevertheless, limited charge and discharge cycles and low round-trip efficiency have long been barriers preventing the large-scale deployment of Zn-air batteries in the marketplace. Technology advancements for each battery component and the whole battery/cell assembly are being pursued, with some key milestones reached during the past 20 years. As an example, commercial Zn-air battery products with long lifetimes and high energy efficiencies are being considered for grid-scale energy storage and for automotive markets. In this review, we present our perspectives on improvements in Zn-air battery technology through the exploration and utilization of different electrolyte systems. Recent studies ranging from aqueous electrolytes to nonaqueous electrolytes, including solid polymer electrolytes and ionic liquids, as well as hybrid electrolyte systems adopted in Zn-air batteries have been evaluated. Understanding the benefits and drawbacks of each electrolyte, as well as the fundamental electrochemistry of Zn and air electrodes in different electrolytes, are the focus of this paper. Further consideration is given to detailed Zn-air battery configurations that have been studied and applied in commercial or nearing commercial products, with the purpose of exposing state-of-the-art technology innovations and providing insights into future advancements.
Keywords: Zn-air batteries; aqueous electrolytes; non-aqueous electrolytes; cell assembly

Ras transformation results in cleavage of reticulon protein Nogo-B that is associated with impairment of IFN response - Ahn, Dae-gyun; Sharif, Tanveer; Chisholm, Kenneth; Pinto, Devanand m; Gujar, Shashi a; Lee, Patrick wk (Cell Cycle, 2015)
Dysregulation of Ras signaling is the major cause of various cancers. Aberrant Ras signaling, however, provides a favorable environment for many viruses, making them suitable candidates as cancer-killing therapeutic agents. Susceptibility of cancer cells to such viruses is mainly due to impaired type I interferon (IFN) response, often as a result of activated Ras/ERK signaling in these cells. In this study, we searched for cellular factors modulated by Ras signaling and their potential involvement in promoting viral oncolysis. We found that upon Ras transformation of NIH-3T3 cells, the N-terminus of Nogo-B (reticulon 4) was proteolytically cleaved. Interestingly, Nogo knockdown (KD) in non-transformed and Ras-transformed cells both enhanced virus-induced IFN response, suggesting that both cleaved and uncleaved Nogo can suppress IFN response. However, pharmacological blockade of Nogo cleavage in Ras-transformed cells significantly enhanced virus-induced IFN response, suggesting that cleaved Nogo contributes to enhanced IFN suppression in these cells. We further showed that IFN suppression associated with Ras-induced Nogo-B cleavage was distinct from but synergistic with that associated with an activated Ras/ERK pathway. Our study therefore reveals an important and novel role of Nogo-B and its cleavage in the suppression of anti-viral immune responses by oncogenic Ras transformation.
Keywords: cleavage; interferon; Nogo; reticulon 4B; transformed cells

Radio polarimetry as a probe of unresolved jets: the 2013 outburst of XTE J1908+094 - Curran, P. A.; Miller-jones, J. C. A.; Rushton, A. P.; Pawar, D. D.; Anderson, G. E.; Altamirano, D.; Krimm, H. A.; Broderick, J. W.; Belloni, T. M.; Fender, R. P.; Körding, E. G.; Maitra, D.; et al. (Monthly Notices of the Royal Astronomical Society, 2015)
XTE J1908+094 is an X-ray transient black hole candidate in the Galactic plane that was observed in outburst in 2002 and 2013. Here we present multifrequency radio and X-ray data, including radio polarimetry, spanning the entire period of the 2013 outburst. We find that the X-ray behaviour of XTE J1908+094 traces the standard black hole hardness–intensity path, evolving from a hard state, through a soft state, before returning to a hard state and quiescence. Its radio behaviour is typical of a compact jet that becomes quenched before discrete ejecta are launched during the late stages of X-ray softening. The radio and X-ray fluxes, as well as the light-curve morphologies, are consistent with those observed during the 2002 outburst of this source. The polarization angle during the rise of the outburst infers a jet orientation in agreement with resolved observations but also displays a gradual drift, which we associate with observed changes in the structure of the discrete ejecta. We also observe an unexpected 90° rotation of the polarization angle associated with a second component.
Keywords: binaries: close; stars: individual: XTE J1908+094; X-rays: binaries; X-rays: bursts

Radio monitoring of the hard state jets in the 2011 outburst of MAXI J1836-194 - Russell, T. D.; Miller-jones, J. C. A.; Curran, P. A.; Soria, R.; Altamirano, D.; Corbel, S.; Coriat, M.; Moin, A.; Russell, D. M.; Sivakoff, G. R.; Slaven-blair, T. J.; Belloni, T. M.; et al. (Monthly Notices of the Royal Astronomical Society, 2015)
MAXI J1836-194 is a Galactic black hole candidate X-ray binary that was discovered in 2011 when it went into outburst. In this paper, we present the full radio monitoring of this system during its 'failed' outburst, in which the source did not complete a full set of state changes, only transitioning as far as the hard intermediate state. Observations with the Karl G. Jansky Very Large Array (VLA) and Australia Telescope Compact Array (ATCA) show that the jet properties changed significantly during the outburst. The VLA observations detected linearly polarised emission at a level of ~1% early in the outburst, increasing to ~3% as the outburst peaked. High-resolution images with the Very Long Baseline Array (VLBA) show a ~15 mas jet along the position angle -21 ± 2o, in agreement with the electric vector position angle found from our polarisation results (-21 ± 4o), implying that the magnetic field is perpendicular to the jet. Astrometric observations suggest that the system required an asymmetric natal kick to explain its observed space velocity. Comparing quasi-simultaneous X-ray monitoring with the 5 GHz VLA observations from the 2011 outburst shows an unusually steep hard-state radio/X-ray correlation of LR ∝ LX1.8±0.2, where LR and LX denote the radio and X-ray luminosities, respectively. With ATCA and Swift monitoring of the source during a period of re-brightening in 2012, we show that the system lay on the same steep correlation. Due to the low inclination of this system, we then investigate the possibility that the observed correlation may have been steepened by variable Doppler boosting.
Keywords: proper motions; stars: individual: MAXI J1836−194; ISM: jets and outflows; radio continuum: stars; X-rays: binaries

Protein misfolding occurs by slow diffusion across multiple barriers in a rough energy landscape - Yu, Hao; Dee, Derek R.; Liu, Xia; Brigley, Angela M.; Sosova, Iveta; Woodside, Michael T. (Proceedings of the National Academy of Sciences, 2015)
The timescale for the microscopic dynamics of proteins during conformational transitions is set by the intrachain diffusion coefficient, D. Despite the central role of protein misfolding and aggregation in many diseases, it has proven challenging to measure D for these processes because of their heterogeneity. We used single-molecule force spectroscopy to overcome these challenges and determine D for misfolding of the prion protein PrP. Observing directly the misfolding of individual dimers into minimal aggregates, we reconstructed the energy landscape governing nonnative structure formation. Remarkably, rather than displaying multiple pathways, as typically expected for aggregation, PrP dimers were funneled into a thermodynamically stable misfolded state along a single pathway containing several intermediates, one of which blocked native folding. Using Kramers’ rate theory, D was found to be 1,000-fold slower for misfolding than for native folding, reflecting local roughening of the misfolding landscape, likely due to increased internal friction. The slow diffusion also led to much longer transit times for barrier crossing, allowing transition paths to be observed directly for the first time to our knowledge. These results open a new window onto the microscopic mechanisms governing protein misfolding.
Keywords: intrachain diffusion; protein aggregation; prion protein; optical tweezers; single-molecule force spectroscopy

Projected changes to winter temperature characteristics over Canada based on an RCM ensemble - Jeong, Dae Il; Sushama, Laxmi; Diro, Gulilat Tefera; Khaliq, M. Naveed (Climate Dynamics, 2015)
Cold temperature and associated extremes often impact adversely human health and environment and bring disruptions in economic activities during winter over Canada. This study investigates projected changes in winter (December to March) period cold extreme days (i.e., cold nights, cold days, frost days, and ice days) and cold spells over Canada based on 11 regional climate model (RCM) simulations for the future 2040–2069 period with respect to the current 1970–1999 period. These simulations, available from the North American Regional Climate Change Assessment Program, were obtained with six different RCMs, when driven by four different Atmosphere–Ocean General Circulation Models, under the Special Report on Emissions Scenarios A2 scenario. Based on the reanalysis boundary conditions, the RCM simulations reproduce spatial patterns of observed mean values of the daily minimum and maximum temperatures and inter-annual variability of the number of cold nights over different Canadian climatic regions considered in the study. A comparison of current and future period simulations suggests decreases in the frequency of cold extreme events (i.e., cold nights, cold days and cold spells) and in selected return levels of maximum duration of cold spells over the entire study domain. Important regional differences are noticed as the simulations generally indicate smaller decreases in the characteristics of extreme cold events over western Canada compared to the other regions. The analysis also suggests an increase in the frequency of midwinter freeze–thaw events, due mainly to a decrease in the number of frost days and ice days for all Canadian regions. Especially, densely populated southern and coastal Canadian regions will require in depth studies to facilitate appropriate adaptation strategies as these regions are clearly expected to experience large increases in the frequency of freeze–thaw events.
Keywords: climate change; cold temperature extremes; regional climate model; Canada

Probing the structural dynamics of proteins and nucleic acids with optical tweezers - Ritchie, Dustin B.; Woodside, Michael T. (Current Opinion in Structural Biology, 2015)
Conformational changes are an essential feature of most molecular processes in biology. Optical tweezers have emerged as a powerful tool for probing conformational dynamics at the single-molecule level because of their high resolution and sensitivity, opening new windows on phenomena ranging from folding and ligand binding to enzyme function, molecular machines, and protein aggregation. By measuring conformational changes induced in a molecule by forces applied by optical tweezers, new insight has been gained into the relationship between dynamics and function. We discuss recent advances from studies of how structure forms in proteins and RNA, including non-native structures, fluctuations in disordered proteins, and interactions with chaperones assisting native folding. We also review the development of assays probing the dynamics of complex protein–nucleic acid and protein–protein assemblies that reveal the dynamic interactions between biomolecular machines and their substrates.

Probing molecular chirality on a sub-femtosecond timescale - Cireasa, R.; Boguslavskiy, A. E.; Pons, B.; Wong, M. C. H.; Descamps, D.; Petit, S.; Ruf, H.; Thiré, N.; Ferré, A.; Suarez, J.; Higuet, J.; Schmidt, B. E.; et al. (Nature Physics, 2015)
Chiral molecules that are non-superimposable mirror images of each other, known as enantiomers, have identical chemical and physical properties unless they interact with another chiral entity, such as chiral light. Chiroptical effects arising from such interactions are used to detect enantiomers in mixtures and to induce enantioselective synthesis and catalysis. Chiroptical effects often arise from the interplay between light-induced electric- and magnetic-dipole transitions in a molecule and evolve on ultrafast electronic timescales. Here we use high-harmonic generation from a randomly oriented gas of molecules subjected to an intense laser field, to probe chiral interactions on these sub-femtosecond timescales. We show that a slight disparity in the laser-driven electron dynamics in the two enantiomers is recorded and amplified by several orders of magnitude in the harmonic spectra. Our work shows that chiroptical detection can go beyond detecting chiral structure to resolving and controlling chiral dynamics on electronic timescales.
Keywords: chemical physics; high-harmonic generation; ultrafast photonics

Precipitation of aluminum and magnesium secondary minerals from uranium mill raffinate (pH 1.0–10.5) and their controls on aqueous contaminants - Robertson, Jared; Hendry, M. Jim; Essilfie-dughan, J.; Chen, J. (Applied Geochemistry, 2015)
Models of geochemical controls on elements of concern (EOCs; e.g., As, Se, Mo, Ni) in U tailings are dominated by ferrihydrite. However, the evolution of aqueous concentrations of Al and Mg through the Key Lake (KL) U mill bulk neutralization process indicates that secondary Al and Mg minerals comprise a large portion of the tailings solids. X-ray diffraction, Al K-edge XAS, and TEM elemental mapping of solid samples collected from a pilot-scale continuous-flow synthetic raffinate neutralization system of the KL mill indicate the secondary Al–Mg minerals present include Mg–Al hydrotalcite, amorphous Al(OH)3, and an amorphous hydrobasaluminite-type phase. The ferrihydrite present contains Al and may be more accurately described as Al–Fe(OH)3. In the final combined tailings sample (pH 10.5) collected from the model experiments using raffinate with Al, Mg, and Fe, solid phase EOCs were associated with Al–Fe(OH)3 and Mg–Al hydrotalcite. In model experiments using raffinate devoid of Fe, aqueous EOC concentrations decreased greatly at pH 4.0 (i.e., where ferrihydrite would precipitate) and largely remained in the solid phase when increased to the terminal pH of 10.5; this suggests Al–Mg minerals can control aqueous concentrations of EOCs in the raffinate in the absence of Fe. Maximum adsorption capacities for individual and mixtures of adsorbates by Mg–Al hydrotalcite were determined. A revised model of the geochemical controls in U mill tailings is presented in which Al and Mg minerals co-exist with Fe minerals to control EOC concentrations.
Keywords: tailings; uranium; aluminum; magnesium; arsenic; nickel

Polar glycosylated and lateral non-glycosylated flagella from Aeromonas hydrophila strain AH-1 (serotype O11) - Fulton, Kelly; Mendoza-barberá, Elena; Twine, Susan; Tomás, Juan; Merino, Susana (International Journal of Molecular Sciences, 2015)
Polar and but not lateral flagellin proteins from Aeromonas hydrophila strain AH-1 (serotype O11) were found to be glycosylated. Top-down mass spectrometry studies of purified polar flagellins suggested the presence of a 403 Da glycan of mass. Bottom-up mass spectrometry studies showed the polar flagellin peptides to be modified with 403 Da glycans in O-linkage. The MS fragmentation pattern of this putative glycan was similar to that of pseudaminic acid derivative. Mutants lacking the biosynthesis of pseudaminic acid (pseB and pseI homologues) were unable to produce polar flagella but no changes were observed in lateral flagella by post-transcriptional regulation of the flagellin. Complementation was achieved by reintroduction of the wild-type pseB and pseI. We compared two pathogenic features (adhesion to eukaryotic cells and biofilm production) between the wild-type strain and two kinds of mutants: mutants lacking polar flagella glycosylation and lacking the O11-antigen lipopolysaccharide (LPS) but with unaltered polar flagella glycosylation. Results suggest that polar flagella glycosylation is extremely important for A. hydrophila AH-1 adhesion to Hep-2 cells and biofilm formation. In addition, we show the importance of the polar flagella glycosylation for immune stimulation of IL-8 production via toll-“like” receptor 5 (TLR5).
Keywords: O-flagellin polar glycosylation; lateral flagellin non-glycosylated; adhesion; biofilm; immune stimulation

Piezoelectric deicing system for rotorcraft - Villeneuve, Eric; Harvey, Derek; Zimcik, David; Aubert, Roger; Perron, Jean (Journal of the American Helicopter Society, 2015)
Deicing using piezoelectric actuators is considered as a potential solution to the development of low-energy ice protection systems for rotorcraft. This type of system activates resonant frequencies of a structure using piezoelectric actuators to generate sufficient stress to break the bond between the ice and the substrate. First, a numerical method was validated to assist the design of such systems. Numerical simulations were performed for the case of a flat plate and validated experimentally. The model was then used to study important design parameters such as actuator positioning and activation strategies, and it was concluded that positioning actuators at antinode locations, and activating them in phase with those antinodes to obtain maximum displacements for a given vibration mode. The findings were then used to apply piezoelectric deicing to structures more representative of a helicopter rotor blade. The method was implemented on a thinned Bell 206 main rotor blade and a Bell 206 tail rotor blade. Deicing performance was demonstrated in an icing wind tunnel. Power input to the actuators was below 19 kW/m2 (12 W/inch2) for all structures.

Photodissociation Dynamics of Cyclopropenylidene, c-C3H2 - Schuurman, Michael S.; Giegerich, Jens; Pachner, Kai; Lang, Daniel; Kiendl, Benjamin; Macdonell, Ryan J.; Krueger, Anke; Fischer, Ingo (Chemistry - A European Journal, 2015)
In this joint experimental and theoretical study we characterize the complete dynamical “life cycle” associated with the photoexcitation of the singlet carbene cyclopropenylidene to the lowest lying optically bright excited electronic state: from the initial creation of an excited-state wavepacket to the ultimate fragmentation of the molecule on the vibrationally hot ground electronic state. Cyclopropenylidene is prepared in this work using an improved synthetic pathway for the preparation of the precursor quadricyclane, thereby greatly simplifying the assignment of the molecular origin of the measured photofragments. The excitation process and subsequent non-adiabatic dynamics have been previously investigated employing time-resolved photoelectron spectroscopy and are now complemented with high-level ab initio trajectory simulations that elucidate the specific vibronic relaxation pathways. Lastly, the fragmentation channels accessed by the molecule following internal conversion are probed using velocity map imaging (VMI) so that the identity of the fragmentation products and their corresponding energy distributions can be definitively assigned.

Permanent phase correction in a polarization diversity Si PIC by femtosecond laser pulses - Bachman, Daniel; Chen, Zhijiang; Westwood-bachman, Jocelyn N.; Hiebert, Wayne K.; Painchaud, Yves; Poulin, Michel; Fedosejevs, Robert; Tsui, Ying Y.; Van, Vien (IEEE Photonics Technology Letters, 2015)
We report a fast and efficient method for permanently correcting fabrication-induced phase errors in silicon photonic circuits. The method uses femtosecond laser pulses at 400-nm wavelength to amorphize a thin layer of crystalline silicon near the waveguide surface, thereby inducing a change in the effective index of the waveguide. Using a single femtosecond laser pulse, we reduced the polarization-dependent frequency shift between the two interferometers of a polarization diversity differential phase shift keying silicon demodulator from 11 GHz to less than 0.5 GHz, thereby restoring the polarization diversity operation of the circuit with little degradation to the circuit performance.
Keywords: femtosecond laser tuning; silicon photonics; DPSK demodulator; polarization diversity

Orbitally modulated photoexcited Si I emission in the eclipsing composite-spectrum binary ζ Aurigae - Harper, G. M.; Griffin, R. E. M.; Bennett, P. D.; O'riain, N. (Monthly Notices of the Royal Astronomical Society, 2015)
We examine the little-known phenomenon of orbitally modulated Si i emission at λ 3905.523 Å and λ 4102.936 Å in composite-spectrum binaries, with specific reference to ζ Aurigae (K4 Ib + B5 V). The emission is detected in the isolated spectrum of the B-type dwarf secondary, and while λ 4102 Å is heavily blended with Hδ, λ 3905 Å falls in the B-star's featureless continuum. The narrowness of the emission (vturb ≃ 6 km s−1) demonstrates that it originates in the upper photosphere or deep chromosphere of the K star primary. We propose that photoexcitation by the hot star's UV continuum, followed by recombination and cascades, leads to resonant scattering and subsequent pumping of lower opacity transitions in the singlet and triplet systems of Si i. This process channels the UV continuum into select narrow emission lines. We have also identified weaker photoexcited emission of Fe ii at λ 3938.289 Å. The strengths, positions, and widths of the λ 3905 Å emission line vary with orbital phase owing to changes in the dilution of the irradiating flux and in the geometrical aspect of the irradiated hemisphere. Utilizing the inherent spatial resolution provided by the illuminated patch, and assuming that the K star is spherical with isotropic emission, yields vsin i ∼ 5.7 km s−1. Evidence of tidal distortion was deduced from the timing of the rapidly rising phase of the emission just after periastron. Increasing the diagnostic potential requires radiative transfer modelling of the formation and centre-to-limb variation of the emission.

Optimization of the double spike technique using peak jump collection by a Monte Carlo method: an example for the determination of Ca isotope ratios - Feng, Lanping; Zhou, Lian; Yang, Lu; Tong, Shuoyun; Hu, Zhaochu; Gao, Shan (Journal of Analytical Atomic Spectrometry, 2015)
Three important factors, including the choice of an appropriate spike isotope pair, the composition of the double spike, and the ratio of the double spike to the sample, have been proven to have a significant effect on the precision of the double spike technique. Moreover, peak jump (i.e., dynamic) collection mode is frequently used, which could lead to more variable parameters such as cup configurations, ratio combinations and integration times in different jump lines. In order to optimize the above conditions under the peak jump mode, a Monte Carlo method that simulates uncertainties from Johnson noise and counting statistics is applied for the prediction of the precisions of measured results using the double spike technique. As an example, this model was used to predict the possibility of cup configurations and ratio combinations of three double spike pairs of 42Ca–48Ca, 43Ca–48Ca and 46Ca–48Ca, respectively, in two jump lines. Predicted internal precisions improved by 25%, 20% and 25% by using 42Ca–48Ca, 43Ca–48Ca and 46Ca–48Ca double spikes, respectively, under optimized conditions. The theoretically predicted optimum precision was verified by repeatedly measuring two standards of NIST SRM 915a and NIST SRM 915b using the 42Ca–48Ca double spike over several months. The observed internal precisions of δ44Ca in these two standards are in good agreement with the predicted internal precisions, validating the effectiveness of the proposed Monte Carlo technique. The observed external precisions in two standards are 8–9 times poorer than the internal precisions, probably due to an extra uncertainty source. Nevertheless, the optimal ratio combination yields the best external precision. As demonstrated, the proposed Monte Carlo simulation is an effective method to predict the optimal cup configurations, ratio combinations and integration times for the double spike technique using peak jump collection mode.

Optimization of cutting conditions in vibration assisted drilling of composites via a multi-objective EGO implementation - Sadek, Ahmed; Aly, Mohamed; Hamza, Karim; Meshreki, Mouhab; Nassef, Ashraf O.; Attia, Helmi (Volume 2A: 41st Design Automation Conference, 2015)
A recent and promising technique to overcome the challenges of conventional drilling is vibration-assisted drilling (VAD) whereby a controlled harmonic motion is superimposed over the principal drilling feed motion in order to create an intermittent cutting state. Two additional variables other than the feed and the speed are introduced, namely the frequency and the amplitude of the imposed vibrations. Optimum selection of cutting conditions in VAD operations of composite materials is a challenging task due to several reasons; such as the increase in the number of controllable variables, the need for costly experimentation, and the limitation on the number of experiments that can be performed before tool degradation becomes an issue in the reliability of measurements. Additionally, there are often several objectives to consider, some of which may be conflicting, while others may be somewhat correlated. Pareto-optimality analysis is needed for conflicting objectives; however the existence of several objectives (high-dimension Pareto space) makes the generation and interpretation of Pareto solutions difficult. An attractive approach to the optimization task is thus to employ Kriging meta-models in a multi-objective efficient global optimization (m-EGO) framework for incremental experimentation of optimal setting of the cutting parameters. Additional challenge posed by constraints on machine capabilities is accounted for through domain transformation of the design variables prior to the construction of the Kriging models. Study results using a baseline exhaustive experimental data shows opportunity for employing m-EGO for the generation of well distributed Pareto-frontiers with fewer experiments.
Keywords: composite materials; drilling; optimization; vibration; cutting

On time–temperature-dependent viscoelastic behavior of an amorphous polyimide - Crochon, Thibaut; Li, Chun; Lévesque, Martin (Mechanics of Time-Dependent Materials, 2015)
Development of new polyimide formulas has led to an increase of the use of polymer matrix composites by the aerospace industry in critical applications such as aircraft engines. In such an extreme environment, the polymer matrix is likely to exhibit a viscoelastic behavior due to the elevated temperatures. Furthermore, physical ageing is likely to appear during the service life of the material. In order for engineers to design with such materials, constitutive theories able to take into account those effects, must be developed. This paper deals with the mechanical behavior of a new polyimide matrix tested under complex thermo-mechanical histories while accounting for physical ageing. The experimental data obtained was modeled with a newly developed constitutive theory stemming from Schapery’s thermodynamical framework. The model parameters were obtained from creep-recovery data under various temperatures, ageing times, and loads. The model was subsequently validated against independent complex thermo-mechanical histories. An excellent agreement between the experiments and the predictions has been obtained.
Keywords: viscoelasticity; physical ageing; temperature; modeling

On the distance of the globular cluster M4 (ngc 6121) using RR Lyrae stars. II. mid-infrared period–luminosity relations - Neeley, J. R.; Marengo, M.; Bono, G.; Braga, V. F.; Dall’ora, M.; Stetson, P. B.; Buonanno, R.; Ferraro, I.; Freedman, W. L.; Iannicola, G.; Madore, B. F.; Matsunaga, N.; et al. (The Astrophysical Journal, 2015)
New mid-infrared (MIR) period–luminosity (PL) relations are presented for RR Lyræ variables in the globular cluster M4 (NGC 6121). Accurate photometry was obtained for 37 RR Lyræ variables using observations from the Infrared Array Camera on board the Spitzer Space Telescope. The dispersion of M4's PL relations is 0.056, and the uncertainty in the slope is 0.11 mag. Additionally, we established calibrated PL relations at 3.6 and 4.5 μm using published Hubble Space Telescope geometric parallaxes of five Galactic RR Lyræ stars. The resulting band-averaged distance modulus for M4 is μ=11.399 ± 0.007(stat) ± $0.080(syst) ± 0.015(cal) ± 0.020(ext). The systematic uncertainty will be greatly reduced when parallaxes of more stars become available from the GAIA mission. Optical and infrared period–color (PC) relations are also presented, and the lack of an MIR PC relation suggests that RR Lyræ stars are not affected by CO absorption in the 4.5 μm band.
Keywords: globular clusters; individual (M$); star; RR Lyrae

On the absolute age of the metal-rich globular M71 (NGC 6838). I. Optical photometry - Cecco, A. Di; Bono, G.; Moroni, P. G. Prada; Tognelli, E.; Allard, F.; Stetson, P. B.; Buonanno, R.; Ferraro, I.; Iannicola, G.; Monelli, M.; Nonino, M.; Pulone, L. (The Astronomical Journal, 2015)
We investigated the absolute age of the Galactic globular cluster M71 (NGC 6838) using optical ground-based images (u', g', r', i', z') collected with the MegaCam camera at the Canada–France–Hawaii Telescope (CFHT). We performed a robust selection of field and cluster stars by applying a new method based on the 3D (r', u'-g', g'-r') color–color–magnitude diagram. A comparison between the color–magnitude diagram (CMD) of the candidate cluster stars and a new set of isochrones at the locus of the main sequence turn-off (MSTO) suggests an absolute age of 12 ± 2 Gyr. The absolute age was also estimated using the difference in magnitude between the MSTO and the so-called main sequence knee, a well-defined bending occurring in the lower main sequence. This feature was originally detected in the near-infrared bands and explained as a consequence of an opacity mechanism (collisionally induced absorption of molecular hydrogen) in the atmosphere of cool low-mass stars. The same feature was also detected in the r', u'-g', and in the r', g'-r' CMD, thus supporting previous theoretical predictions by Borysow et al. The key advantage in using the ΔKnee TO as an age diagnostic is that it is independent of uncertainties affecting the distance, the reddening, and the photometric zero point. We found an absolute age of 12 ± 1 Gyr that agrees, within the errors, with similar age estimates, but the uncertainty is on average a factor of two smaller. We also found that the ΔKnee TO is more sensitive to the metallicity than the MSTO, but the dependence vanishes when using the difference in color between the MSK and the MSTO.
Keywords: globular cluster; individual (M71)

Non-specific interaction of carbon nanotubes with the resazurin assay reagent: impact on in vitro assessment of nanoparticle cytotoxicity - Breznan, Dalibor; Das, Dharani; Mackinnon-roy, Christine; Simard, Benoit; Kumarathasan, Premkumari; Vincent, Renaud (Toxicology in Vitro, 2015)
In vitro cytotoxicity assays are essential tools in the screening of engineered nanomaterials (NM) for cellular toxicity. The resazurin live cell assay is widely used because it is non-destructive and is well suited for high-throughput platforms. However, NMs, in particular carbon nanotubes (CNT) can interfere in assays through quenching of transmitted light or fluorescence. We show that using the resazurin assay with time-point reading of clarified supernatants resolves this problem. Human lung epithelial (A549) and murine macrophage (J774A.1) cell lines were exposed to NMs in 96-well plates in 200 μL of media/well. After 24 h incubation, 100 μL of supernatant was removed, replaced with resazurin reagent in culture media and aliquots at 10 min and 120 min were transferred to black-wall 96-well plates. The plates were quick-spun to sediment the residual CNTs and fluorescence was top-read (λEx = 540 nm, λEm = 600 nm). The procedure was validated for CNTs as well as silica nanoparticles (SiNP). There was no indication of reduction of resazurin by the CNTs. Stability of resorufin, the fluorescent product of the resazurin reduction was then assessed. We found that polar CNTs could decrease the fluorescence signal for resorufin, possibly through oxidation to resazurin or hyper-reduction to hydroxyresorufin. This effect can be easily quantified for elimination of the bias. We recommend that careful consideration must be given to fluorimetric/colorimetric in vitro toxicological assessments of optically/chemically active NMs in order to relieve any potential artifacts due to the NMs themselves.
Keywords: carbon nanotubes; in vitro; cell viability; cytotoxicity; resazurin; interaction

Nonlinear optomechanical paddle nanocavities - Kaviani, Hamidreza; Healey, Chris; Wu, Marcelo; Ghobadi, Roohollah; Hryciw, Aaron; Barclay, Paul E. (Optica, 2015)
Nonlinear optomechanical coupling is the basis for many potential future experiments in quantum optomechanics (e.g., quantum nondemolition measurements, preparation of nonclassical states), which to date have been difficult to realize due to small nonlinearity in typical optomechanical devices. Here we introduce an optomechanical system combining strong nonlinear optomechanical coupling, low mass, and large optical mode spacing. This nanoscale “paddle nanocavity” supports mechanical resonances with hundreds of femtograms of mass that couple nonlinearly to optical modes with a quadratic optomechanical coupling coefficient g(2)>2π×400  MHz/nm2, and a single-photon to two-phonon optomechanical coupling rate of Δω0>2π×16  Hz. This coupling relies on strong phonon–photon interactions in a structure whose optical mode spectrum is highly nondegenerate. Nonlinear optomechanical readout of thermally driven motion in these devices should be observable for T>50  mK, and measurement of phonon shot noise is achievable. This shows that strong nonlinear effects can be realized without relying on coupling between nearly degenerate optical modes, thus avoiding the parasitic linear coupling present in two-mode systems.

Nonlinear conversion efficiency of InAs/InP nanostructured Fabry-Perot lasers - Huang, Heming; Schires, Kevin; Chaibi, Mohamed; Poole, Philip; Erasme, Didier; Grillot, Frédéric; Witzigmann, Bernd; Osiński, Marek; Henneberger, Fritz; Arakawa, Yasuhiko (Physics and Simulation of Optoelectronic Devices XXIII, 2015)
Non-degenerate four-wave mixing effects are investigated in an injection-locked InAs/InP nanostructure Fabry-Perot laser. Locking a longitudinal mode at various wavelengths within the gain spectrum and using the locked mode as the pump for the wave mixing shows different levels of asymmetry between up- and down-conversion. Experiments reveal that the normalized conversion efficiency is less asymmetric when the pump is locked at wavelengths below that of the gain peak. The values of nonlinear conversion efficiencies are maintained above -60 dB for pump-probe frequency detunings up to 3.5 THz. The role of the linewidth enhancement factor on the asymmetry is discussed and the value of the nonlinear susceptibility is compared to similar InAs/InP nanostructure semiconductor optical amplifiers. From an end-user viewpoint, data transmission experiments have also confirmed the possibility to propagate up-converted signals over 100 km at a 5 Gb/s bit rate under an OOK modulation format. © (2015) COPYRIGHT Society of Photo-Optical Instrumentation Engineers (SPIE). Downloading of the abstract is permitted for personal use only.

Naturally occurring bactericidal antibodies specific for Haemophilus influenzae Lipooligosaccharide are present in healthy adult individuals - Choi, Joshua; Nix, Eli B.; Gaultier, Gabrielle N.; Cox, Andrew D.; Mccready, William; Ulanova, Marina (Vaccine, 2015)
Nontypeable Haemophilus influenzae (NTHi), a typical mucosal pathogen largely responsible for respiratory infections and pediatric otitis media, has been increasingly recognized as a significant cause of invasive disease, especially in immunocompromised individuals. Lipooligosaccharide (LOS) is a conserved molecule with an important role in H. influenzae virulence and immune evasion, and it may be considered as a vaccine candidate. However, abilities of H. influenzae LOS to induce protective immune response are poorly understood. The goal of this study was to determine whether antibodies against LOS isolated from H. influenzae strains Eagan, Rd and NTHi 375 are present in the sera of normal individuals. Antigen specific IgG and IgM were studied in sera of 71 and 30 healthy adults, respectively. IgG specific for LOS of all three strains was ubiquitously present in our sample population while IgM specific for Eagan, Rd and NTHi 375 LOS compounds was detected in 37%, 63%, and 40% of samples, respectively. All tested serum samples exhibited bactericidal activity against all three H. influenzae strains; the removal of anti-LOS antibodies from the sera resulted in significant increases in bacterial survival of the corresponding strain. NTHi 375 exhibited the highest serum resistance, whereas the Rd strain was the least resistant. Serum bactericidal activity of anti-LOS antibody was mediated via the classical complement pathway. These findings suggest that in healthy adults, naturally acquired complement-activating anti-LOS antibodies significantly contribute to the overall serum bactericidal activity against both encapsulated and non-encapsulated strains of H. influenzae.
Keywords: NTHi; LOS; serum resistance; adaptive response; bactericidal antibody; BAFF; APRIL

Naturally acquired antibodies against Haemophilus influenzae type a in aboriginal adults, Canada - Nix, Eli B.; Williams, Kylie; Cox, Andrew D.; St. Michael, Frank; Romero-steiner, Sandra; Schmidt, Daniel S.; Mccready, William G.; Ulanova, Marina (Emerging Infectious Diseases, 2015)
In the post-Haemophilus influenzae type b (Hib) vaccine era that began in the 1980's, H. influenzae type a (Hia) emerged as a prominent cause of invasive disease in North American Aboriginal populations. To test whether a lack of naturally acquired antibodies may underlie increased rates of invasive Hia disease, we compared serum bactericidal activity against Hia and Hib and IgG and IgM against capsular polysaccharide between Canadian Aboriginal and non-Aboriginal healthy and immunocompromised adults. Both healthy and immunocompromised Aboriginal adults exhibited significantly higher bactericidal antibody titers against Hia than did non-Aboriginal adults (p = 0.042 and 0.045 respectively), with no difference in functional antibody activity against Hib. IgM concentrations against Hia were higher than IgG in most study groups; the inverse was true for antibody concentrations against Hib. Our results indicate that Aboriginal adults possess substantial serum bactericidal activity against Hia that is mostly due to IgM antibodies. The presence of sustained IgM against Hia suggests recent Hia exposure.

Nanomechanical torque magnetometry of an individual aggregate of ∼350 nanoparticles - Firdous, T.; Vick, D.; Belov, M.; Fani sani, F.; McDermott, A.; Losby, J. E.; Bazylinski, D. A.; Prozorov, T.; Potter, D. K.; Freeman, M. R. (Canadian Journal of Physics, 2015)
The measurements of magnetic hysteresis for aggregates of nanoparticles deposited on a surface are reported. Magnetite nanoparticles derived from magnetotactic bacteria are studied using nanomechanical torque magnetometry. The nanoparticles are deposited on high-stress Si3N4 membranes, to allow inspection by electron microscopy, followed by focused ion-beam milling of torsional resonators precisely located to capture selected aggregates within the membrane area. Torque magnetometry is performed using the resonators. We investigate also the magnetic torque-driven AC resonant modes of the modified supporting membrane. The observations are compared to numerical simulations of the mechanical modes, and to micromagnetic modeling of the hysteresis of a specific measured cluster of ∼350 nanoparticles.

Nanocomposites of graphene oxide, Ag nanoparticles, and magnetic ferrite nanoparticles for elemental mercury (Hg0) removal - Liu, Yuxi; Tian, Chong; Yan, Bin; Lu, Qingye; Xie, Yijun; Chen, Jian; Gupta, Rajender; Xu, Zhenghe; Kuznicki, Steven M.; Liu, Qingxia; Zeng, Hongbo (RSC Advances, 2015)
Mercury emission from combustion flue gas causes considerable environmental challenges and serious adverse health threats, and elemental mercury (Hg0) is the most challenging chemical form for removal. In this work, four types of graphene oxide (GO) based composite adsorbents were successfully synthesized by depositing Ag nanoparticles (NPs) and/or magnetic ferrite NPs on GO sheets (denoted as GO, GO–Ag, MGO and MGO–Ag), characterized and applied for the removal of Hg0 for the first time. The presence of Ag NPs on GO greatly enhances the Hg0 removal capability of GO–Ag and MGO–Ag as compared to that of pure GO, which is mainly attributed to the amalgamation of Hg0 on Ag NPs. MGO–Ag shows the best Hg0 removal performance and thermal tolerance among the four types of adsorbents developed, which can effectively capture Hg0 up to 150–200 °C in a simulated flue gas environment and can be also effectively recycled and reused. Our results indicate that the graphene oxide based composites (i.e. MGO–Ag) have significant potential applications for mercury emission control in coal-fired power plants.

n-3 polyunsaturated fatty acids inhibit Fc ε receptor I-mediated mast cell activation - Wang, Xiaofeng; Ma, David W. L.; Kang, Jing X.; Kulka, Marianna (The Journal of Nutritional Biochemistry, 2015)
In vivo models show that n-3 polyunsaturated fatty acids (PUFA) inhibit some of the processes associated with allergic inflammation but the direct effect of n-3 PUFA on mast cells, the major effector cells in allergy, is poorly understood. We sought to determine the effect and mechanism of n-3 PUFA on Fc ε receptor I (FcεRI)-mediated signal transduction and mast cell activation. Bone marrow-derived mast cells (BMMC) were differentiated from bone marrow obtained from C57BL/6 wild-type (WT) and fat-1 transgenic mice. The fat-1 mice express fatty acid n-3 desaturase and produce endogenous n-3 PUFA. For comparison, exogenous n-3 PUFA were supplemented to WT BMMC and human mast cell (LAD2) cultures. Fat-1 BMMC released less β-hexosaminidase (β-hex) and cysteinyl leukotrienes and produced less tumor necrosis factor and chemokine (C-C motif) ligand 2. n-3 PUFA supplementation reduced LAD2 and BMMC degranulation (β-hex release) following FcεRI activation. Fat-1 BMMC expressed less constitutive Lyn and linker of activated T cells (LAT), and FcεRI-mediated phosphorylation of Lyn, spleen tyrosine kinase and LAT were reduced in fat-1 BMMC. Although the expression of surface and whole cell FcεRI was similar in WT and fat-1 BMMC, unstimulated fat-1 BMMC showed reduced FcεRI localization to lipid rafts, and stimulation with antigen resulted in aberrant FcεRI shuttling to the rafts. Our results show that n-3 PUFA suppress FcεRI-mediated activation of mast cells, which results in reduced mediator release. This effect is associated with a decrease in LAT and Lyn expression as well as abnormal shuttling of FcεRI to lipid rafts.
Keywords: n-3 polyunsaturated fatty acids; mast cell; FcεRI; signal transduction; lipid rafts

MTS-MD of biomolecules steered with 3D-RISM-KH mean solvation forces accelerated with generalized solvation force extrapolation - Omelyan, Igor; Kovalenko, Andriy (Journal of Chemical Theory and Computation, 2015)
We developed a generalized solvation force extrapolation (GSFE) approach to speed up multiple time step molecular dynamics (MTS-MD) of biomolecules steered with mean solvation forces obtained from the 3D-RISM-KH molecular theory of solvation (three-dimensional reference interaction site model with the Kovalenko-Hirata closure). GSFE is based on a set of techniques including the non-Eckart-like transformation of coordinate space separately for each solute atom, extension of the force-coordinate pair basis set followed by selection of the best subset, balancing the normal equations by modified least-squares minimization of deviations, and incremental increase of outer time step in motion integration. Mean solvation forces acting on the biomolecule atoms in conformations at successive inner time steps are extrapolated using a relatively small number of best (closest) solute atomic coordinates and corresponding mean solvation forces obtained at previous outer time steps by converging the 3D-RISM-KH integral equations. The MTS-MD evolution steered with GSFE of 3D-RISM-KH mean solvation forces is efficiently stabilized with our optimized isokinetic Nosé–Hoover chain (OIN) thermostat. We validated the hybrid MTS-MD/OIN/GSFE/3D-RISM-KH integrator on solvated organic and biomolecules of different stiffness and complexity: asphaltene dimer in toluene solvent, hydrated alanine dipeptide, miniprotein 1L2Y, and protein G. The GSFE accuracy and the OIN efficiency allowed us to enlarge outer time steps up to huge values of 1–4 ps while accurately reproducing conformational properties. Quasidynamics steered with 3D-RISM-KH mean solvation forces achieves time scale compression of conformational changes coupled with solvent exchange, resulting in further significant acceleration of protein conformational sampling with respect to real time dynamics. Overall, this provided a 50- to 1000-fold effective speedup of conformational sampling for these systems, compared to conventional MD with explicit solvent. We have been able to fold the miniprotein from a fully denatured, extended state in about 60 ns of quasidynamics steered with 3D-RISM-KH mean solvation forces, compared to the average physical folding time of 4–9 μs observed in experiment.

Mott-Kondo insulator behavior in the iron oxychalcogenides - Freelon, B.; Liu, Yu Hao; Chen, Jeng-Lung; Craco, L.; Laad, M. S.; Leoni, S.; Chen, Jiaqi; Tao, Li; Wang, Hangdong; Flauca, R.; Yamani, Z.; Fang, Minghu; et al. (Physical Review B, 2015)
We perform a combined experimental-theoretical study of the Fe-oxychalcogenides (FeOCh) series La2O2Fe2OM2 (M=S, Se), which are among the latest Fe-based materials with the potential to show unconventional high-Tc superconductivity (HTSC). A combination of incoherent Hubbard features in x-ray absorption and resonant inelastic x-ray scattering spectra, as well as resistivity data, reveal that the parent FeOCh are correlation-driven insulators. To uncover microscopics underlying these findings, we perform local density approximation-plus-dynamical mean field theory (LDA+DMFT) calculations that reveal a novel Mott-Kondo insulating state. Based upon good agreement between theory and a range of data, we propose that FeOCh may constitute an ideal testing ground to explore HTSC arising from a strange metal proximate to a novel selective-Mott quantum criticality.

Motoneurons derived from induced pluripotent stem cells develop mature phenotypes typical of endogenous spinal motoneurons - Toma, J. S.; Shettar, B. C.; Chipman, P. H.; Pinto, D. M.; Borowska, J. P.; Ichida, J. K.; Fawcett, J. P.; Zhang, Y.; Eggan, K.; Rafuse, V. F. (Journal of Neuroscience, 2015)
Induced pluripotent cell-derived motoneurons (iPSCMNs) are sought for use in cell replacement therapies and treatment strategies for motoneuron diseases such as amyotrophic lateral sclerosis (ALS). However, much remains unknown about the physiological properties of iPSCMNs and how they compare with endogenous spinal motoneurons or embryonic stem cell-derived motoneurons (ESCMNs). In the present study, we first used a proteomic approach and compared protein expression profiles between iPSCMNs and ESCMNs to show that <4% of the proteins identified were differentially regulated. Like ESCs, we found that mouse iPSCs treated with retinoic acid and a smoothened agonist differentiated into motoneurons expressing the LIM homeodomain protein Lhx3. When transplanted into the neural tube of developing chick embryos, iPSCMNs selectively targeted muscles normally innervated by Lhx3 motoneurons. In vitro studies showed that iPSCMNs form anatomically mature and functional neuromuscular junctions (NMJs) when cocultured with chick myofibers for several weeks. Electrophysiologically, iPSCMNs developed passive membrane and firing characteristic typical of postnatal motoneurons after several weeks in culture. Finally, iPSCMNs grafted into transected mouse tibial nerve projected axons to denervated gastrocnemius muscle fibers, where they formed functional NMJs, restored contractile force. and attenuated denervation atrophy. Together, iPSCMNs possess many of the same cellular and physiological characteristics as ESCMNs and endogenous spinal motoneurons. These results further justify using iPSCMNs as a source of motoneurons for cell replacement therapies and to study motoneuron diseases such as ALS.

Molecular theory of solvation: methodology summary and illustrations - Kovalenko, A. (Condensed Matter Physics, 2015)
Integral equation theory of molecular liquids based on statistical mechanics is quite promising as an essential part of multiscale methodology for chemical and biomolecular nanosystems in solution. Beginning with a molecular interaction potential force field, it uses diagrammatic analysis of the solvation free energy to derive integral equations for correlation functions between molecules in solution in the statistical-mechanical ensemble. The infinite chain of coupled integral equations for many-body correlation functions is reduced to a tractable form for 2- or 3-body correlations by applying the so-called closure relations. Solving these equations produces the solvation structure with accuracy comparable to molecular simulations that have converged but has a critical advantage of readily treating the effects and processes spanning over a large space and slow time scales, by far not feasible for explicit solvent molecular simulations. One of the versions of this formalism, the three-dimensional reference interaction site model (3D-RISM) integral equation complemented with the Kovalenko-Hirata (KH) closure approximation, yields the solvation structure in terms of 3D maps of correlation functions, including density distributions, of solvent interaction sites around a solute (supra)molecule with full consistent account for the effects of chemical functionalities of all species in the solution. The solvation free energy and the subsequent thermodynamics are then obtained at once as a simple integral of the 3D correlation functions by performing thermodynamic integration analytically. Analytical form of the free energy functional permits the self-consistent field coupling of 3D-RISM-KH with quantum chemistry methods in multiscale description of electronic structure in solution, the use of 3D maps of potentials of mean force as scoring functions for molecular recognition and protein-ligand binding in docking protocols for fragment based drug design, and the hybrid MD simulation running quasidynamics of biomolecules steered with 3D-RISM-KH mean solvation forces. The 3D-RISM-KH theory has been validated on both simple and complex associating liquids with different chemical functionalities in a wide range of thermodynamic conditions, at different solid-liquid interfaces, in soft matter, and various environments and confinements. The 3D-RISM-KH theory offers a "mental microscope" capable of providing an insight into structure and molecular mechanisms of formation and functioning of various chemical and biomolecular systems and nanomaterials.
Keywords: solution chemistry; biomolecular solvation; integral equation theory of liquids; 3D-RISM-KH molecular theory of solvation; solvation structure and thermodynamics; potential of mean force

Molecular structures of fluid phosphatidylethanolamine bilayers obtained from simulation-to-experiment comparisons and experimental scattering density profiles - Kučerka, Norbert; Van oosten, Brad; Pan, Jianjun; Heberle, Frederick A.; Harroun, Thad A.; Katsaras, John (The Journal of Physical Chemistry B, 2015)
Following our previous efforts in determining the structures of commonly used PC, PG, and PS bilayers, we continue our studies of fully hydrated, fluid phase PE bilayers. The newly designed parsing scheme for PE bilayers was based on extensive MD simulations, and is utilized in the SDP analysis of both X-ray and neutron (contrast varied) scattering measurements. Obtained experimental scattering form factors are directly compared to our simulation results, and can serve as a benchmark for future developed force fields. Among the evaluated structural parameters, namely, area per lipid A, overall bilayer thickness DB, and hydrocarbon region thickness 2DC, the PE bilayer response to changing temperature is similar to previously studied bilayers with different headgroups. On the other hand, the reduced hydration of PE headgroups, as well as the strong hydrogen bonding between PE headgroups, dramatically affects lateral packing within the bilayer. Despite sharing the same glycerol backbone, a markedly smaller area per lipid distinguishes PE from other bilayers (i.e., PC, PG, and PS) studied to date. Overall, our data are consistent with the notion that lipid headgroups govern bilayer packing, while hydrocarbon chains dominate the bilayer’s response to temperature changes.

Molecular dynamics, Monte Carlo simulations, and langevin dynamics: a computational review - Paquet, Eric; Viktor, Herna L. (BioMed Research International, 2015)
Macromolecular structures, such as neuraminidases, hemagglutinins, and monoclonal antibodies, are not rigid entities. Rather, they are characterised by their flexibility, which is the result of the interaction and collective motion of their constituent atoms. This conformational diversity has a significant impact on their physicochemical and biological properties. Among these are their structural stability, the transport of ions through the M2 channel, drug resistance, macromolecular docking, binding energy, and rational epitope design. To assess these properties and to calculate the associated thermodynamical observables, the conformational space must be efficiently sampled and the dynamic of the constituent atoms must be simulated. This paper presents algorithms and techniques that address the abovementioned issues. To this end, a computational review of molecular dynamics, Monte Carlo simulations, Langevin dynamics, and free energy calculation is presented. The exposition is made from first principles to promote a better understanding of the potentialities, limitations, applications, and interrelations of these computational methods.

Magnetoluminescence and valley polarized state of a two-dimensional electron gas in WS2 monolayers - Scrace, T.; Tsai, Y.; Barman, B.; Schweidenback, L.; Petrou, A.; Kioseoglou, G.; Ozfidan, I.; Korkusinski, M.; Hawrylak, P. (Nature Nanotechnology, 2015)
Materials often exhibit fundamentally new phenomena in reduced dimensions that potentially lead to novel applications. This is true for single-layer, two-dimensional semiconductor crystals of transition-metal dichalcogenides, MX2 (M = Mo, W and X = S, Se). They exhibit direct bandgaps with energies in the visible region at the two non-equivalent valleys in the Brillouin zone. This makes them suitable for optoelectronic applications that range from light-emitting diodes to light harvesting and light sensors, and to valleytronics. Here, we report the results of a magnetoluminescence study of WS2 single-layer crystals in which the strong spin–orbit interaction additionally locks the valley and spin degrees of freedom. The recombination of the negatively charged exciton in the presence of a two-dimensional electron gas (2DEG) is found to be circularly polarized at zero magnetic field despite being excited with unpolarized light, which indicates that the existence of a valley polarized 2DEG is caused by valley and spin locking and strong electron–electron interactions.
Keywords: nanophotonics and plasmonics; two-dimensional materials

Magnetic structure of the antiferromagnetic half-Heusler compound NdBiPt - Müller, R. A.; Desilets-benoit, A.; Gauthier, N.; Lapointe, L.; Bianchi, A. D.; Maris, T.; Zahn, R.; Beyer, R.; Green, E.; Wosnitza, J.; Yamani, Z.; Kenzelmann, M. (Physical Review B, 2015)
We present results of single-crystal neutron-diffraction experiments on the rare-earth, half-Heusler antiferromagnet (AFM) NdBiPt. This compound exhibits an AFM phase transition at TN=2.18 K with an ordered moment of 1.78(9)μB per Nd atom. The magnetic moments are aligned along the [001] direction, arranged in a type-I AFM structure with ferromagnetic planes, alternating antiferromagnetically along a propagation vector τ of (100). The RBiPt (R = Ce–Lu) family of materials has been proposed as candidates for a new family of antiferromagnetic topological insulators (AFTIs) with a magnetic space group that corresponds to a type-II AFM structure where ferromagnetic sheets are stacked along the space diagonal. The resolved structure makes it unlikely that NdBiPt qualifies as an AFTI.

Magnetic and transport properties of Co1±δCr2∓δSe4 - Svitlyk, Volodymyr; Kolodiazhnyi, Taras; Cranswick, Lachlan M. D.; Luke, Graeme; Mozharivskyj, Yurij (Materials Research Express, 2015)
Single crystals of Co1±δCr2∓δSe4 were grown using chemical vapor method with CrCl3 as a transporting agent. Magnetic measurements on the Co1±δCr2∓δSe4 crystals confirm an antiferromagnetic ordering below the Neel temperature of T N = 230 K. Neutron diffraction studies performed on the Co1±δCr2∓δSe4 powder show that the long-range antiferromagnetic ordering is accompanied by a doubling of the c crystallographic axe. For the Co1±δCr2∓δSe4 single crystals electrical resistivity displays an anisotropic behavior: resistivitiy within the (100) plane increases till T N and then decreases as temperature increases. Resistivity in the orthogonal direction increases with temperature with a change in the slope above T N. Muon spin relaxation experiments on the Co1±δCr2∓δSe4 crystals confirm both the long-range magnetic order and ordering temperature established by other techniques.
Keywords: cobalt chromium selenide; magnetic structure; transport properties; muon spin relaxation

Low-noise amplifier design considerations for use in antenna arrays - Belostotski, Leonid; Veidt, Bruce; Warnick, Karl F.; Madanayake, Arjuna (IEEE Transactions on Antennas and Propagation, 2015)
This work analyzes the implications of noise coupling in arrays of antennas on the design of low-noise amplifiers (LNAs). To select LNA design parameters in a manner familiar to LNA designers, the effective noise temperatures Teff of LNAs are presented. The effect of beamformer coefficients and antenna coupling on Teff is analyzed in a manner similar to a stand-alone LNA analysis. This leads to the proposed LNA design strategy of selecting LNA Γopt near the reflection coefficient of antenna ports and selecting the largest practical |S11| with a proper phase. This strategy is based on the assumption that the antenna array may be used for various beamforming and nonbeamforming applications, unknown at the time of the design. Numerical simulations of a 38- and 41-element antenna arrays show that a global search of LNA S11 and Γopt, which result in the minimum average beam-equivalent receiver noise temperature Trec, finds nearly identical results to the proposed LNA design strategy. For a 41-element array with high antenna coupling at low frequencies, the proposed method shows as much as 80% improvement in the Trec over conventional LNA design strategies that do not account for the intended use of the amplifier in an array.
Keywords: coefficient; antenna arrays; noise coupling; low noise amplifier (LNA); active reflection

Long-lived LMCT in a d0 Vanadium(V) complex by internal conversion to a state of 3dxy character - Choing, Stephanie N.; Francis, Aaron J.; Clendenning, Graham; Schuurman, Michael S.; Sommer, Roger D.; Tamblyn, Isaac; Weare, Walter W.; Cuk, Tanja (The Journal of Physical Chemistry C, 2015)
The excited state dynamics of a d0 vanadium(V) oxido ligand-to-metal charge transfer (LMCT) complex, VOLF, were investigated via a combination of static optical and X-ray absorption (XAS) spectroscopy, transient optical absorption spectroscopy, and time-dependent density functional theory (TD-DFT). Upon excitation of the LMCT in the visible region, transient absorption data reveal that internal conversion traps the excited carrier population into a long-lived charge transfer state of 3dxy electron character, S1(dxy). The internal conversion is substantiated by an isosbestic point in the transient absorption data, two nearby charge transfer states that couple well by TD-DFT, multiple rates in the ground state recovery, and the decay kinetics of an excited state absorption with the energy of a d-d transition in O K-edge XAS spectra. The long lifetime (∼420 ps) of S1(dxy) can be ascribed to its poor optical and vibrational coupling to a distorted ground state (S0*) via a negligible electronic dipole transition in TD-DFT. The lack of luminescence or an identifiable triplet state also suggests attributing the lifetime to electronic contributions. In conjunction with its strong visible absorption and reduction potential, the long-lived LMCT suggests that molecules such as VOLF could have potential utility for energy conversion applications. Moreover, the results show that internal conversion between two nearby charge transfer states, differentiated by their 3d character, can form a long-lived charge transfer excitation, broadly informing the discovery of 3d metal-centered optical absorbers with long-lived charge transfer lifetimes.

Liquid sensing using active feedback assisted planar microwave resonator - Zarifi, Mohammad H.; Farsinezhad, Samira; Shankar, Karthik; Daneshmand, Mojgan (IEEE Microwave and Wireless Components Letters, 2015)
A novel electromagnetic sensor operating at microwave frequencies with quality factor of 22,000 at 1.4 GHz for real-time sensing of fluid properties is presented. The core of the sensor has a planar microstrip resonator, which is enhanced using an active feedback loop. The resonance frequency and quality factor of the sensor show clear differentiation between analytes composed of common solvents. To evaluate the sensor for water based concentration detection, we have demonstrated that KOH dilutions as low as 0.1 mM are detectable. The proposed sensor has advantages of inexpensiveness and high resolution as well as capability for miniaturization and CMOS compatibility.
Keywords: S-parameters and high resolution sensing; active device; liquid sensing; microwave passive resonator

Life cycle emissions and cost of transportation systems: case study on diesel and natural gas for light duty trucks in municipal fleet operations - Shahraeeni, Mehdi; Ahmed, Syed; Malek, Kourosh; Van drimmelen, Burke; Kjeang, Erik (Journal of Natural Gas Science and Engineering, 2015)
The green economy mandate seeks to reduce transportation emissions by replacing traditional fossil fuels with alternative low-carbon fuels. The present article provides a comparative “cradle-to-grave” life cycle assessment (LCA) of light duty commercial vehicles (LDCVs) powered by compressed natural gas (CNG) and diesel. The LCA scope is based on conditions for municipal vehicle fleet operation in a semi-urban Canadian city, suitable for adoption of alternative fuels such as CNG. An in-house application is developed to conduct the LCA with a combination of real-time vehicle fleet data and Natural Resources Canada's GHGenius as the inventory database. The results indicate that the net energy consumed is comparable for both fuels. Mixed results are obtained for criteria air contaminant (CAC) emissions, indicating the need for exhaust treatment for both vehicles. More importantly, a 34% reduction of GHG emissions is predicted by replacing the diesel vehicles with CNG vehicles. The analysis of fugitive methane emissions caused by newly developed hydraulic fracturing methods shows that CNG vehicles are still favorable. The lifetime fuel cost can also be reduced by about $30,000 per vehicle by switching to CNG. Therefore, fleet operators and policy developers are recommended to consider adoption of CNG-powered LDCVs.
Keywords: light duty commercial vehicle; LCA; CNG; natural gas; diesel

Isometrically invariant and allosterically aware description of deformable macromolecular surfaces: Application to the viral neuraminidase - Paquet, Eric; Viktor, Herna L. (Vaccine, 2015)
Motivation: The macromolecular surfaces associated with proteins and macromolecules play a key role in determining their functionality and interactions, and are also of importance in structural analysis and classification. As a result of their interaction with their environment, the macromolecular surfaces experience random conformational deformations. Consequently, a realistic description of the molecular surface must be invariant under these deformations. Further, the motion associated with disconnected regions on the molecular surface may be correlated. This property is known as the allosteric effect. In this paper, we address these two requirements. To this end, we propose an approach based on discrete differential geometry and the fractional Fokker–Planck equation which provides an isometrically invariant and allosteric aware description of macromolecular surfaces. Our method is applied to the influenza neuraminidase.
Keywords: macromolecular surface; description; neuraminidase; allosteric; deformable; heat kernel; fractional

Introducing new half-integer quadrupolar nuclei for solid state NMR of inclusion compounds - Moudrakovski, Igor L.; Ratcliffe, Christopher I.; Ripmeester, John A. (Canadian Journal of Chemistry, 2015)
Broad developments in experimental NMR techniques have opened new and exciting opportunities for application of solid state nuclear magnetic resonance (SS NMR) in studies of gas hydrates and inclusion compounds in general. Perhaps the most important advance of the last 10 years was the extension into very high magnetic fields beyond 20 T. This progress is especially significant in studies concerned with low-γ, low natural abundance, and quadrupolar nuclei. This work reports our recent exploration of clathrate hydrates and other inclusion compounds (β-quinol, tert-Bu-Calix[4], and dodecasil-3C) with SS NMR of nuclei that were not so long ago completely out of reach for NMR, namely 131Xe, 83Kr, and 33S. Although 129Xe is a widely used NMR probe, applications of the low-γ isotope 131Xe were very scarce. Being a quadrupolar spin 3/2 nucleus, 131Xe provides an additional probe for sampling the electric field gradients in inclusion compounds. Another nucleus that has been seriously under-explored is 83Kr, with its very low γ being the main obstacle, and along with quadrupolar coupling we report the first detection of the chemical shift anisotropy in krypton. The relative values of the Sternheimer antishielding factors for 131Xe and 83Kr, obtained by comparison of the spectra of the two in identical cage environments, are also discussed. Though 33S NMR of solids is notoriously difficult due to its low γ, low natural abundance, and relatively large quadrupolar moment, working at the field of 21.1 T it was possible to acquire, in a reasonable time, natural abundance 33S SS NMR spectra of various H2S and SO2 gas hydrates and inclusion compounds. In most cases the spectra are dominated by the quadrupolar interactions, providing information on the symmetry of the cages encapsulating the guest molecules, and also show the effects of very rapid reorientation of the encaged H2S and SO2. The impact of the introduction of new NMR nuclei on hydrate research is discussed.

Interfacial water and triboelectric charging: a theoretical study of the role of water on the PMMA/Silica tribopair - Li, Qingbin; Gusarov, Sergey; Kovalenko, Andriy; Veregin, Richard P. N. (Journal of Imaging Science and Technology, 2015)
Abstract In many real-world commercial applications, such as electrophotographic printing, the adsorption of water on critical surfaces has an overwhelming but poorly understood effect on the desired materials performance. This work is focussed to better understand the effect of water on the triboelectric charge transfer between surfaces in xerography.Molecular mechanics was used to find the most probably water adsorption sites for isolated polymethylmethacryate (PMMA) and isolated silica models, and for intermolecular complexes between PMMA and silica which are responsible for triboelectric charge transfer. Density functional theory (DFT) was used calculate the local energy minima, the adsorption of water molecules on different surface functional groups, and the analysis of the frontier orbitals, to quantitatively compare the energy gap differences for electronic charge transfer, and thus the effect of the hydration site on PMMA and silica on electronic charge transfer.Four ways were found for surface water adsorption to affect the electronic charge transfer between PMMA and silica: (1) adsorption of a water molecule on the carbonyl group of PMMA decreases the energy level of the highest occupied molecular orbital (HOMO) on PMMA, thus making electron charge transfer more difficult because of the transfer barrier increase; (2) a water molecule acts as part of the electron accepter when adsorbed at the active site of the lowest unoccupied molecular orbital (LUMO) on silica, which lowers the LUMO and thus lowers the charge transfer barrier, but at the same time creates a charge dissipation pathway as a part of the charge transfer is now to water, rather than to silica; (3) a water molecule acts as a spacer between PMMA and silica, which increases the energy gap for charge transfer and thus decreases the charge transfer; and (4) water molecules can act as a charge carrier, dissipating electrons by accepting charge when adsorbed on silica and then donating back charge when adsorbed on PMMA.This work provides a detailed mechanistic understanding of the effects of water on the surface electronic structure of amorphous silica and PMMA that are critical to electrophotographic applications, and no doubt to other applications where the surface electronic structure is relevant.

Interfacial band alignment for photocatalytic charge separation in TiO2 nanotube arrays coated with CuPt nanoparticles - Farsinezhad, Samira; Sharma, Himani; Shankar, Karthik (Physical Chemistry Chemical Physics, 2015)
n-Type anatase-phase one-dimensional TiO2 nanostructure arrays coated with nanoparticles of Cu or CuPt have emerged as high performance photocatalysts for both photooxidation and photoreduction. The properties of the catalyst-promoter interface are recognized to be critical to this high performance but are largely unknown. Using X-ray and ultraviolet photoelectron spectroscopies (XPS/UPS), we probed the electronic properties of the CuPt–TiO2 interface in transparent TiO2 nanotube arrays (TTNTAs) coated with photodeposited CuPt nanoparticles (CuPt–TTNTA hybrids) as well as those coated with sputtered CuPt (Sput-CuPt–TTNTA hybrids). XPS and UPS spectra provided the evidence of a Schottky barrier with a band-bending of 0.49–0.67 eV at the CuPt–TiO2 interface in CuPt–TTNTA hybrids due to which photoexcited electrons are expected to be retained in the TiO2 while photoexcited holes will be collected by the CuPt nanoparticles. For Sput-CuPt–TTNTA hybrids, no such band-bending was observed. These results point to the importance of the metal nanoparticle preparation technique on interfacial band-alignments and challenge the conventional understanding of the promoting action of noble metal nanoparticles on TiO2 photocatalysts as sinks for photoexcited electrons.

In-situ chemical analysis of molten photovoltaic silicon by Laser Induced Breakdown Spectroscopy - Patatut, L.; Serasset, M.; Lignier, H.; Pelletier, D.; Bouchard, P.; Sabsabi, M.; Benmansour, M. (2015 IEEE 42nd Photovoltaic Specialist Conference (PVSC), 14-19 June 2015, New Orleans, LA, 2015)
Laser induced breakdown spectroscopy (LIBS) has been used for the first time to determine in-situ the bulk chemical composition of a photovoltaic silicon melt. Our apparatus analyzes a freshly created and renewed surface inside the silicon melt which is truly representative of the melt composition in contrast to its surface. First, signal acquisition conditions are optimized to ensure that LIBS measurements overcome experimental fluctuations. Second, experimental parameters affecting plasma physics such as laser energy, bath temperature and bubbling gas are evaluated to maximize signal sensitivity and instrumental limits. Third, B, Al, Ti and Fe calibration curves are established. Selected conditions allow a reliable measurement which can be compared to classical ex-situ ICP-OES, with detection limit of few or even below ppmw. These results demonstrate the strong capabilities of LIBS for in-situ and in-line monitoring of metallurgical processes used in the photovoltaic industry.
Keywords: spectroscopy; calibration; chemical sensors; laser ablation; melt processing; silicon

Infrared thermography, ultrasound C-scan and microscope for non-destructive and destructive evaluation of 3D carbon fiber materials: a comparative study - Zhang, Hai; Genest, Marc; Robitaille, Francois; Maldague, Xavier; West, Lucas; Joncas, Simon; Leduc, Catherine (Thermosense: Thermal Infrared Applications XXXVII, 2015)
3D Carbon fiber polymer matrix composites (3D CF PMCs) are increasingly used for aircraft construction due to their exceptional stiffness and strength-to-mass ratios. However, defects are common in the 3D combining areas and are challenging to inspect. In this paper, Stitching is used to decrease these defects, but causes some new types of defects. Infrared NDT (non-destructive testing) and ultrasound NDT are used. In particular, a micro-laser line thermography technique (micro-LLT) and a micro-laser spot thermography (micro-LST) with locked-in technique are used to detect the micro-defects. In addition, a comparative study is conducted by using pulsed thermography (PT), vibrothermography (VT). In order to confirm the types of the defects, microscopic inspection is carried out before NDT work, after sectioning and polishing a small part of the sample.

Influence of soot aggregate size and internal multiple scattering on LII signal and the absorption function variation with wavelength determined by the TEW-LII method - Yon, J.; Therssen, E.; Liu, F.; Bejaoui, S.; Hebert, D. (Applied Physics B, 2015)
Laser-induced incandescence (LII) is a powerful and robust optical method for in situ determination of soot volume fraction and/or soot absorption/emission properties in flames and engine exhaust. The laser-induced signal is interpreted as thermal emission based on the Planck law. Up to now, the evaluation and interpretation of LII signal have been largely based on contributions from isolated primary particles that are assumed much smaller than wavelengths. In the present paper, the morphology, wavelength, and aggregate size-dependent effects of multiple scattering within fractal soot aggregates on their absorption and emission cross sections are taken into account in the evaluation of LII signal by proposing correction terms to the traditional model. The impact of accounting for the correction to soot aggregate emission due to multiple scattering on LII signal and on the two excitation wavelength-induced incandescence method for inferring the soot absorption function, E(m), is discussed. For wavelengths shorter than 532 nm, E(m, λ)/E(m, 1064 nm) increases more significantly with decreasing wavelength. For wavelengths longer than 532 nm, the wavelength dependence of E(m, λ)/E(m, 1064 nm) becomes very small and can be neglected. The proposed corrections, along with the soot morphology, are applied to re-analyze the experimental data of Bejaoui et al. (Appl Phys B Lasers Opt, 116:313, 2014) for deriving the relative soot absorption function variation with wavelength at different locations in a rich premixed methane flat flame at atmospheric pressure. The present analysis showed that the soot absorption function varies with the height above the burner exit and can be correlated with the degree of soot maturation.

In vivo optical resolution photoacoustic microscopy using glancing angle-deposited nanostructured Fabry–Perot etalons - Hajireza, Parsin; Sorge, Jason; Brett, Michael; Zemp, Roger (Optics Letters, 2015)
In this Letter, reflection-mode optical resolution photoacoustic microscopy (OR-PAM) using glancing angle-deposited (GLAD) nanostructured Fabry–Perot interferometers (FPI) for in vivo applications is reported. GLAD is a single-step physical vapor deposition (PVD) technique used to fabricate porous nanostructured thin films. Using titanium dioxide, a transparent semiconductor with a high refractive index (n=2.4), the GLAD technique can be employed to fabricate samples with tailored nano-porosity, refractive index periodicities, and high Q-factor reflectance spectra. The OR-PAM in vivo images of chorioallantoic membrane (CAM) of 5-day chicken embryo model are demonstrated. The phantom study shows lateral resolution and signal-to-noise ratio better than 7 μm and 35 dB, respectively. The sensitive GLAD FPI allows photoacoustic imaging down to a few-nJ pulse energy. To the best of our knowledge, this is the first time that a FPI-based reflection mode optical resolution photoacoustic imaging technique is demonstrated for in vivo applications.

Impregnation of La0.4Ce0.6O1.8–La0.4Sr0.6TiO3 as solid oxide fuel cell anode in H2S-containing fuels - Afshar, Milad R.; Yan, Ning; Zahiri, Beniamin; Mitlin, David; Chuang, Karl T.; Luo, Jing-Li (Journal of Power Sources, 2015)
Active anodes were fabricated via wet chemical impregnation of optimized amount of La0.4Sr0.6TiO3 (L4ST) into La0.4Ce0.6O1.8 (LDC) pre-infiltrated porous yttria-stabilized zirconia (YSZ) matrix. Impregnations of 10 wt% LDC with 16 wt% L4ST significantly improved the performance of the fuel cell from 48 mW cm−2 for pure L4ST to 161 mW cm−2 for LDC–L4ST at 900 °C in H2. The contribution of the pre-loaded LDC to this improvement was investigated using electrochemical impedance spectroscopy (EIS), scanning electron microscopy (SEM) as well as transmission electron microscopy (TEM). The measurement results indicated that pre-infiltrated LDC increased the activity of the anode more effectively by decreasing the total polarization resistance of the cell from 3.3 Ω cm2 to 1.0 Ω cm2 in humidified H2 at 900 °C. More importantly, the LDC nano-deposits (<20 nm) behaved as an effective “adhesive” that substantially enhanced the wettability of L4ST on YSZ matrix, resulting in finer and more uniform structure of L4ST infiltrates. The LDC–L4ST cells also demonstrated significantly improved performances in 0.5% H2S–H2 and 0.5% H2S–CH4 with higher stability than cells with pure L4ST anode.
Keywords: solid oxide fuel cells anode; H2S; impregnation; lanthanum strontium titanate; lanthanum cerium oxide

Impact of interface roughness distributions on the operation of quantum cascade lasers - Franckié, Martin; Winge, David O.; Wolf, Johanna; Liverini, Valeria; Dupont, Emmanuel; Trinité, Virginie; Faist, Jérôme; Wacker, Andreas (Optics Express, 2015)
We study the impact of interface roughness on the operation of mid-IR and THz quantum cascade lasers. Particular emphasis is given towards the differences between the Gaussian and exponential roughness distribution functions, for which we present results from simulation packages based on nonequilibrium Green’s functions and density matrices. The Gaussian distribution suppresses scattering at high momentum transfer which enhances the lifetime of the upper laser level in mid-IR lasers. For THz lasers, a broader range of scattering transitions is of relevance, which is sensitive to the entire profile of the interface fluctuations. Furthermore we discuss the implementation of interface roughness within a two band model.

Immunotoxicology testing of monoclonal antibodies in macaca fascicularis - Piché, Marie-Soleil; Mounho-zamora, Barbara; Lesauteur, Lynne; Burns-naas, Leigh Ann (The Nonhuman Primate in Nonclinical Drug Development and Safety Assessment, 2015)
Many therapeutic monoclonal antibodies (mAbs) are in development for a wide array of indications. Because of the nature of the product and/or the intended pharmacology, mAbs are assessed for their potential immunomodulation, whether intended or not. Immunomodulation and immunotoxicology (i.e., immunosuppression, immunogenicity, immunostimulation) can be related. The intended immunomodulatory effect of mAbs is the intended pharmacology for clinical efficacy. Exaggerated or prolonged pharmacological activity may, however, result in adverse immunomodulation, leading to unpredictable and unintended immunotoxicology outcomes. Nonhuman primates (NHPs) are often considered as the most relevant species to perform preclinical studies for the testing of mAb-induced immunomodulation and immunotoxicity. This chapter focuses on regulatory considerations associated with the testing of mAbs in NHPs, the mAb product and biomanufacturing process characteristics to take into consideration for immunogenicity testing, and the preclinical study designs in adult and juvenile NHPs to monitor immunomodulation.
Keywords: nonhuman primate; monoclonal antibodies; immunotoxicology; developmental immunotoxicology

Identifying panaxynol, a natural activator of nuclear factor erythroid-2 related factor 2 (Nrf2) from American ginseng as a suppressor of inflamed macrophage-induced cardiomyocyte hypertrophy - Qu, Chen; Li, Bin; Lai, Yimu; Li, Hechu; Windust, Anthony; Hofseth, Lorne J.; Nagarkatti, Mitzi; Nagarkatti, Prakash; Wang, Xing Li; Tang, Dongqi; Janicki, Joseph S.; Tian, Xingsong; et al. (Journal of Ethnopharmacology, 2015)
Ethnopharmacological relevance: American ginseng is capable of ameliorating cardiac dysfunction and activating Nrf2, a master regulator of antioxidant defense, in the heart. This study was designed to isolate compounds from American ginseng and to determine those responsible for the Nrf2-mediated resolution of inflamed macrophage-induced cardiomyocyte hypertrophy. Materials and methods: A standardized crude extract of American ginseng was supplied by the National Research Council of Canada, Institute for National Measurement Standards. A bioassay-based fractionization of American ginseng was performed to identify the putative substances which could activate Nrf2-mediated suppression of pro-inflammatory cytokine expression in macrophages and macrophage-mediated pro-hypertrophic growth in cardiomyocytes. Results: A hexane fraction of an anti-inflammatory crude extract of American ginseng was found to be most effective in suppressing the inflammatory responses in macrophages. Preparative, reverse-phase HPLC and a comparative analysis by analytical scale LC–UV/MS revealed the hexane fraction contains predominantly C17 polyacetylenes and linolenic acid. Panaxynol, one of the major polyacetylenes, was found to be a potent Nrf2 activator. Panaxynol posttranscriptionally activated Nrf2 by inhibiting Kelch-like ECH-associated protein (Keap) 1-mediated degradation without affecting the binding of Keap1 and Nrf2. Moreover, panaxynol suppressed a selected set of cytokine expression via the activation of Nrf2 while minimally regulating nuclear factor-kappa B (NF-κB)-mediated cytokine expression in macrophages. It also dramatically inhibited the inflamed macrophage-mediated cardiomyocyte death and hypertrophy by activating Nrf2 in macrophages. Conclusions: These results demonstrate that American ginseng-derived panaxynol is a specific Nrf2 activator and panaxynol-activated Nrf2 signaling is at least partly responsible for American ginseng-induced health benefit in the heart.
Keywords: American ginseng; panaxynol; Nrf2; inflammation; macrophages; cardiomyocytes

Hydrogen in metals studied by Thermal Desorption Spectroscopy (TDS) - Hultquist, G.; Graham, M. J.; Smialek, J. L.; Jönsson, B. (Corrosion Science, 2015)
Hydrogen in metals and metal-hydrogen bond strength are important considerations for air oxidation/reaction kinetics and mechanical properties [1], [2] and [3]. The present method of Thermal Desorption Spectroscopy (TDS) determines not only the hydrogen content in a sample, after long term exposure to ambient humid air at room temperature (RT), but also indicates the operative metal-hydrogen bond strength [4].
Keywords: A. copper; C. Hydrogen absorption; C. Oxidation

HOMO–LUMO energy gap control in platinum(II) biphenyl complexes containing 2,2′-bipyridine ligands - Rillema, D. Paul; Stoyanov, Stanislav R.; Cruz, Arvin J.; Nguyen, Huy; Moore, Curtis; Huang, Wei; Siam, Khamis; Jehan, Ali; Komreddy, Venugopal (Dalton Transactions, 2015)
A series of platinum(II) biphenyl 2,2′-bipyridine complexes containing electron-donating and electron-withdrawing moieties on the 4 and 4′ positions of the bipyridine ligand exhibit emission from excited states in the 600 nm region of the spectrum upon excitation in the metal-to-ligand charge transfer transition located near 450 nm. These complexes are distorted from planarity based on both single crystal structure determinations and density functional theory (DFT) calculations of isolated molecules in acetonitrile. The DFT also reveals the geometry of the lowest-lying triplet state (LLTS) of each complex that is important for emission behavior. The LLTS are assigned based on the electron spin density distributions and correlated with the singlet excited states to understand the mechanism of electronic excitation and relaxation. Time-dependent DFT calculations are performed to compute the singlet excited state energies of these complexes so as to help interpret their UV-Vis absorption spectra. Computational and experimental results, including absorption and emission energy maxima, electrochemical reduction potentials, LLTS, singlet excited states, and LUMO and HOMO energies, exhibit linear correlations with the Hammett constants for para-substituents σp. These correlations are employed to screen complexes that have not yet been synthesized. The correlation analysis indicates that the electronic structure and the HOMO–LUMO energy gap in Pt(II) complexes can be effectively controlled using electron-donating and electron-withdrawing moieties covalently bonded to the ligands. The information presented in this paper provides a better understanding of the fundamental electronic and thermodynamic behavior of these complexes and could be used to design systems with specific applications.

High-resolution images of diffuse neutral clouds in the milky way. I. observations, imaging, and basic cloud properties - Pidopryhora, Y.; Lockman, Felix J.; Dickey, J. M.; Rupen, M. P. (The Astrophysical Journal Supplement Series, 2015)
A set of diffuse interstellar clouds in the inner Galaxy within a few hundred parsecs of the Galactic plane has been observed at an angular resolution of ≈1&farcm;0 combining data from the NRAO Green Bank Telescope and the Very Large Array. At the distance of the clouds, the linear resolution ranges from ~1.9 to ~2.8 pc. These clouds have been selected to be somewhat outside of the Galactic plane, and thus are not confused with unrelated emission, but in other respects they are a Galactic population. They are located near the tangent points in the inner Galaxy, and thus at a quantifiable distance: $2.3\leqslant R\leqslant 6.0$ kpc from the Galactic Center and $-1000\leqslant z\leqslant +610$ pc from the Galactic plane. These are the first images of the diffuse neutral H i clouds that may constitute a considerable fraction of the interstellar medium (ISM). Peak H i column densities lie in the range NH i = 0.8–2.9 × 1020 cm−2. Cloud diameters vary between about 10 and 100 pc, and their H i mass spans the range from less than a hundred to a few thousands M⊙. The clouds show no morphological consistency of any kind, except that their shapes are highly irregular. One cloud may lie within the hot wind from the nucleus of the Galaxy, and some clouds show evidence of two distinct thermal phases as would be expected from equilibrium models of the ISM.

High-Q/V monolithic diamond microdisks fabricated with quasi-isotropic etching - Khanaliloo, Behzad; Mitchell, Matthew; Hryciw, Aaron C.; Barclay, Paul E. (Nano Letters, 2015)
Optical microcavities enhance light–matter interactions and are essential for many experiments in solid state quantum optics, optomechanics, and nonlinear optics. Single crystal diamond microcavities are particularly sought after for applications involving diamond quantum emitters, such as nitrogen vacancy centers, and for experiments that benefit from diamond’s excellent optical and mechanical properties. Light–matter coupling rates in experiments involving microcavities typically scale with Q/V, where Q and V are the microcavity quality-factor and mode-volume, respectively. Here we demonstrate that microdisk whispering gallery mode cavities with high Q/V can be fabricated directly from bulk single crystal diamond. By using a quasi-isotropic oxygen plasma to etch along diamond crystal planes and undercut passivated diamond structures, we create monolithic diamond microdisks. Fiber taper based measurements show that these devices support TE- and TM-like optical modes with Q > 1.1 × 105 and V < 11(λ/n) 3 at a wavelength of 1.5 μm.
Keywords: diamond; microcavity; microdisk; nanofabrication; nanophotonics

Guest–host interactions in gas clathrate hydrates under pressure - Izquierdo-ruiz, F.; Otero-de-la-roza, A.; Contreras-garcía, J.; Menéndez, J. M.; Prieto-ballesteros, O.; Recio, J. M. (High Pressure Research, 2015)
First-principles calculations were performed to determine equilibrium geometries, static equation of state parameters, the energetics and orientation of the guest molecule inside the 5 and 56 cages, and vibrational frequencies of methane clathrate hydrate. According to our results, the progressive inclusion of one molecule in each clathrate cavity is always a stabilizing process up to saturation. The released energy is very similar for both types of cages. In agreement with the experimental observation of roto-vibrational spectra in this hydrate, we calculate an energy barrier of less than 0.5 kcal/mol, indicating free rotation of methane inside the cages. The stabilizing effect of applied pressure leads to a red shift of the O–H stretching frequencies of the water molecules of around 80 cm in average at 1 GPa.
Keywords: methane clathrate hydrate; DFT calculations; EOS; vibrational modes

Graph edit distance based on triangle-stars decomposition for deformable 3D objects recognition - Madi, Kamel; Paquet, Eric; Seba, Hamida; Kheddouci, Hamamache (2015 International Conference on 3D Vision, 2015)
We consider the problem of comparing deformable 3D objects represented by graphs, i.e., Triangular tessellations. We propose a new algorithm to measure the distance between triangular tessellations using a new decomposition of triangular tessellations into triangle-Stars. The proposed algorithm assures a minimum number of disjoint triangle-Stars, offers a better measure by covering a larger neighborhood and uses a set of descriptors which are invariant or at least oblivious under most common deformations. We prove that the proposed distance is a pseudo-metric. We analyse its time complexity and we present a set of experimental results which confirm the high performance and accuracy of our algorithm.
Keywords: pattern recognition; edit distance; graph matching; graph decomposition; triangle-stars; deformable objects; 3D objects

Metabolomics in animal cell culture - Čuperlović-culf, Miroslava (Animal Cell Culture, 2015)
Metabolomics is defined as a global quantitative assessment of metabolites within a biological system. Metabolic profiling of cell cultures has many potential applications as well as advantages to currently utilized methods for cell-line testing. Metabolite concentrations represent sensitive markers of genomic changes and responses of cells to external stimuli. Effects of drugs or toxins on cell cultures can be observed through the changes in metabolite concentrations. When cell cultures used for production of various biomolecules metabolomics can aid in optimization of cell growth. Metabolomics can also be used as a method for routine monitoring of extracellular metabolic changes in real time measurements. Nuclear magnetic resonance spectroscopy and mass spectrometry are major analytical platforms used for metabolomics measurements. These methods provide detailed, non-biased and highly complementary chemical analyses of metabolic changes within cells (fingerprint) and in excreted metabolites (footprint). This chapter provides review of current applications of metabolomics in cell cultures with an overview of experimental and data analysis methodologies.
Keywords: metabolomics; nuclear magnetic resonance (NMR); mass spectrometry (MS); phenotype analysis; metabonomics; production systems optimization; feature selection; qualitative data analysis; quantitative data analysis; unsupervised analysis; supervised analysis

Helicopter pilot heart rate variability in relation to differences in rotor tuning and seat cushion impedance - Keillor, Jocelyn M.; Craig, Gregory L.; Wright Beatty, Heather E.; Alexander, Marc D.; Berezny, Nicholas; Wickramasinghe, Viresh (Annual Meeting of the Canadian Society for Brain Behaviour and Cognitive Science, 2015)
Exposure to whole-body vibration (WBV) has been related to stress, cognitive fatigue and a number of adverse health effects. However, the mechanisms for these effects are not clearly understood. Indeed "health effects" identified in the WBV standards (e.g. ISO- 2631) are weighted by frequency according to sensory magnitude rather than any measured physiological effects. NRC carried out a series of flights in which we manipulated the vibration profile of a Bell 412 helicopter was varied by altering the tuning of the main rotor, and observed differences in Heart Rate and Heart Rate Variability (HRV). We also manipulated the impedance properties of the seat cushion, and observed comparable relationships between vibration and HRV. HRV may prove to be a useful means of indexing the physiological effects of WBV exposure.

Glancing angle deposited Ni nanopillars coated with conformal, thin layers of Pt by a novel electrodeposition: application to the oxygen reduction reaction - Xu, Shuai; Wang, Chao; Francis, Sonja A.; Tucker, Ryan T.; Sorge, Jason B.; Moghaddam, Reza B.; Brett, Michael J.; Bergens, Steven H. (Electrochimica Acta, 2015)
Glancing Angle Deposition (GLAD) was used to prepare 500 nm long Ni nanopillars directly on glassy carbon disc electrodes (NiGLAD/GC). NiGLADPt/GC core-layer nanopillars were prepared by depositing Pt on the NiGLAD substrate via a novel rotating disc electrode galvanostatic deposition, where a stationary blackened Pt counter electrode served as the Pt source. Scanning electron microscopy, cyclic voltammetry, and inductively-coupled mass spectrometry were employed to characterize the deposits. Results indicated that the Pt was deposited in a conformal manner on the NiGLAD giving a loading of 11.6 μg. The NiGLADPt/GC electrode was ca. three fold more active than a Pt/GC (made with the same deposition in the absence of Ni) towards the oxygen reduction reaction (ORR) in 1.0 M KOH. As well, long term potentiostatic ORR studies showed the NiGLADPt/GC deposit was more durable than the Pt/GC, with the former completely retaining its initial performance after 5000 s polarization at 0.85 V vs. RHE, while Pt/GC lost 38% of its activity. Subsequent control experiments in the absence of O2 showed that such decay was not due to loss of Pt over the prolonged ORR.
Keywords: NiGLADPt; platinum; nickel; oxygen reduction; alkaline fuel cell

Detection, identification, and occurrence of thiotetronic acids in drinking water from underground sources by electrospray ionization-high field asymmetric waveform ion mobility spectrometry-quadrupole time-of-flight-mass spectrometry - Lyczko, Jadwiga; Beach, Daniel; Gabryelski, Wojciech (Analytical Chemistry, 2015)
This paper demonstrates that electrospray ionization (ESI) with differential ion mobility spectroscopy (FAIMS) and soft mass spectrometry (MS) provide unique analytical capabilities that led to the discovery of sulfur-containing polar congeners of thiotetronic acid (TA) in drinking water from underground sources in Canada and the United States. Polar TAs accumulate in underground aquifers and appear to be the most abundant class of organic compounds in bottled water but cannot be detected by conventional mass spectrometry methods. We show that normally stable TAs are converted into very reactive ions in ESI which have to be analyzed using special conditions in ESI-FAIMS-MS to avoid extensive dissociation and ion/molecule reactions. De novo identification of 10 TAs was accomplished by the comparative tandem mass spectrometry analysis of authentic TA derivatives from groundwater samples and synthetic TA analogues prepared for this study. We present highlights of gas phase ion chemistry of polar TAs to explain their unique properties and reactivity. TA derivatives were originally isolated from soil bacteria and are of interest in the pharmaceutical industry due to their potent activity against a broad spectrum of pathogenic bacteria and negligible toxicity to mammals. We suspect that TAs are natural disinfection agents protecting groundwater from bacterial contamination, but these compound undergo modifications or decompose during an ozonation water treatment.

A comparison between the NIST PJVS-based power standard and the NRC current: comparator-based power standard - Waltrip, Bryan C.; Nelson, Thomas L.; So, Eddy; Angelo, David (IEEE Transactions on Instrumentation and Measurement, 2015)
This paper presents the results of a comparison of active/reactive power meter calibrations between the National Institute of Standards and Technology and National Research Council. The comparison was implemented using a transfer standard consisting of a highly stable commercial sampling-type power/energy meter. Active and reactive power measurements were made at 120 V, 5 A, 50 Hz, and 60 Hz. For active power, the measurements were made at applied current phase angles of 0°, +60°, and -60°. For reactive power, the measurements were made at applied current phase angles of +60°, +90°, -60°, and -90° . The results of the comparison indicate agreement to within the stated uncertainties of the participants.
Keywords: NIST; power measurement; reactive power; calibration; current measurement; temperature measurement

Effect of pressure on the corrosion of materials in high temperature water - Li, W.; Woo, O. T.; Guzonas, D.; Li, J.; Huang, X.; Sanchez, R.; Bibby, C. D. (Characterization of Minerals, Metals, and Materials 2015, 2015)
One of the major challenges for the Canadian Gen IV Super-Critical Water-cooled reactor (SCWR) concept is the selection of fuel cladding materials. The Canadian SCWR concept will operate at a core outlet temperature of 625 oC and 25 MPa of pressure with peak cladding temperature reaching as high as 850 oC. Corrosion resistance is an important factor for materials selection. Austenitic stainless steels that contain Cr contents greater than 18 wt% are generally considered to provide adequate corrosion resistance. In this work, an austenitic stainless steel 310 containing 24 wt% Cr is assessed for corrosion resistance at 625 C for 1000 hours in superheated steam, in water at 8 MPa (subcritical) and at 25 MPa (supercritical). Results indicate that the material exposed to subcritical water has the thickest oxide, at  10 micrometer, while that exposed to supercritical water has a 1 micrometer thick oxide, and the oxide exposed to superheated steam was  0.2 micrometer thick. Transmission Electron Microscopy (TEM) revealed that 310 exposed to different pressure conditions at 625 oC. (i.e., superheated steam, subcritical and supercritical water conditions) had generally the same type of the oxide structure, i.e., a Cr rich spinel structure on the top surface. Cr-depleted recrystallized austenite grains were underneath the spinel structure. The adjacent large-grained austenite substrate had M23C6 carbides in the grain interior. The implications of these results are discussed.
Keywords: stainless steel; supercritical Water Reactor; corrosion mechanism

Expediting operational damage control laparotomy closure : iTClampTM vs suturing during damage control surgical simulation training - McKee, Jessica; Tien, Homer; Wright-Beatty, Heather; Keillor, Jocelyn; LaPorta, Anthony; Brien, Sue; Roberts, Derek; Ball, Chad; Louw, Deon; Kirkpatrick, Andrew (Canadian Journal of Surgery, 2015)
Background: As recent innovations in informatic technology allow for specialist support to point-of-care (POC) providers, advanced interventions, such as damage control surgery (DCS), may be possible on the front lines. However, for non-surgeons suturing is a very complex procedural skill, and thus other operational laparotomy closure techniques are needed. Methods: The study was a head-to-head comparison of laparotomy closure in an anatomically realistic surgical training mannequin (the “Cut-suit”) following a perihepatic DCS packing exercise. After skin-only closure with either the iTClamp or suture, the primary outcomes were completeness of closure and time to close. Six board-certified surgeons performed the same task as 12 military medical technicians (MT) who were randomized to unsupported (n = 5; UMT) or remotely telementored (n = 7; RTM) with real-time guidance by a trauma surgeon. Results: No study participants were able to close the incision with sutures and 0.55 achieved closure with the iTClamp. iTClamp application was superior to suturing when examining length of incision closed (p < 0.001), percent of incision closed (p < 0.001) and time to close incision (p = 0.008). Surgeons outperformed the RMT and UMTs on percent closed (p = 0.001, p = 0.004) and length closed (p = 0.001, p = 0.004) when suturing. However, MTs performed as well as the surgeons when using the iTClamp. All participants preferred the iTClamp to suturing, thought it was easy to use and learn to use and was applicable to DCS. Conclusion: Laparotomy closure following DCS in an anatomically realistic surgical mannequin was readily performed by military medical technicians and trained surgeons. The iTClamp proved to be a faster and easier modality to achieve incision closure compared to suturing.

The marriage of surgical simulation and telementoring for damage control surgical training of operational first-responders - Kirkpatrick, Andrew; Tien, Homer; LaPorta, Anthony; McKee, Jessica; Wright-Beatty, Heather; Keillorn, Jocelyn; Brien, Sue; Roberts, Derek; Wong, John; Beckett, Andrew; Mador, Brett; Ball, Chad; et al. (Canadian Journal of Surgery, 2015)
Background: Hemorrhage is the leading cause of preventable posttraumatic death. Many such deaths are potentially salvageable with damage control surgery (DCS). As recent innovations in informatic technology allow for remote specialist-support to point-of-care providers, advanced interventions, such as DCS, may be possible in remote settings. Methods: An anatomically realistic perfused surgical training mannequin with intrinsic fluid loss measurements (the “Cut-suit”) was used to study perihepatic packing with massive liver hemorrhage. The primary outcome was loss of simulated-blood (fluid) during 6 stages: incision, retraction, direction, identification, packing and post-packing. Six fully credentialed surgeons performed the same task as 12 military medical technicians (MT) who were randomized to unmentored (n = 5) (UMT) or remotely telementored (n = 7) (RTM) real-time guidance by a trauma surgeon. Results: There were no significant differences in fluid loss between the surgeons and the UMT group. However, when comparing surgeons to the RTM group, there was significantly more total fluid loss (p = 0.001) and greater loss during the identification (p = 0.002), retraction (p = 0.035), direction (p = 0.014) and packing (p = 0.022) stages. There were no significant differences in fluid loss after packing between the groups despite differences in the number of sponges used; RTM used more sponges than surgeons and significantly more than UMT (p = 0.048). However, mentoring significantly increased non-surgeon procedural confidence (p = 0.004). Conclusion: Perihepatic packing of an exsanguinating liver hemorrhage was performed by military medical technicians after a focused briefing. While real-time RTM did not reduce the surrogate outcome of fluid loss in this model, it significantly increased non-surgeon procedural confidence, which may increase the feasibility of the concept.

Supercapacitors' applications - Wang, Guoping; Wang, Hongqing; Zhong, Benhe; Zhang, Lei; Zhang, Jiujun (Electrochemical Energy, 2015)

Technical innovations that may facilitate real-time telementoring of damage control surgery in austere environments : a proof of concept comparative evaluation of the importance of surgical experience, telepresence, gravity and mentoring in the conduct of damage control laparotomies - Kirkpatrick, Andrew; Laporta, Anthony; Brien, Susan; Leslie, Tim; Glassberg, Elon; Mckee, Jessica; Ball, Chad; Wright Beatty, Heather; Keillor, Jocelyn; Roberts, Derek; Tien, Homer (Canadian Journal of Surgery, 2015)
Bleeding to death is the most preventable cause of posttraumatic death worldwide. Despite the fact that many of these deaths are anatomically salvageable with relatively basic surgical interventions, they remain lethal in actuality in prehospital environments when no facilities and skills exist to contemplate undertaking basic damage control surgery (DCS). With better attention to prehospital control of extremity hemorrhage, intracavitary bleeding (especially intraperitoneal) remains beyond the scope of prehospital providers. However, recent revolutions in the informatics and techniques of telementoring (TMT), DCS and highly realistic accelerated training of motivated first responders suggests that basic lifesaving DCS may have applicability to save bleeding patients in austere environments previously considered unsalvageable. Especially with informatic advances, any provider with Internet connectivity can potentially be supported by highly proficient specialists with content expertise in the index problem. This unprecedented TMT support may allow highly motivated but inexperienced personnel to provide advanced surgical interventions in extreme environments in many austere locations both on and above the planet.

Genetic diversity of folate profiles in seeds of common bean, lentil, chickpea and pea - Jha, Ambuj B.; Ashokkumar, Kaliyaperumal; Diapari, Marwan; Ambrose, Stephen J.; Zhang, Haixia; Tar’an, Bunyamin; Bett, Kirstin E.; Vandenberg, Albert; Warkentin, Thomas D.; Purves, Randall W. (Journal of Food Composition and Analysis, 2015)
Folates are water-soluble B vitamins and act as cofactors in many metabolic functions in the human body. Pulses have traditionally been considered as a good dietary source of folates. The objectives of this study were (1) to determine the concentration of folates in four cultivars each of common bean, lentil, chickpea and pea, and (2) to determine the effect of growing location on folate concentration. Six folate monoglutamates were quantified by ultra-performance liquid chromatography coupled with mass spectrometry (UPLC–MS/MS). Total folate concentration ranged from 351 to 589 μg/100 g in chickpea, 165 to 232 μg/100 g in common bean, 136 to 182 μg/100 g in lentil, and 23 to 30 μg/100 g in pea. The 5-methyltetrahydrofolate (5-MTHF) and 5-formyltetrahydrofolate (5-FTHF) folates were most abundant in common bean, lentil and chickpea, whereas 5-MTHF and tetrahydrofolate (THF) were the predominant forms in pea. Significant differences were detected among cultivars for all folates across the pulses, except for 5,10-methenyltetrahydrofolate (5,10-MTHF) in lentil, 5-MTHF in chickpea, and 5,10-MTHF and folic acid (FA) in pea. Significant effects for location and cultivar by location were also observed for the majority of the folates.
Keywords: Cultivars; Folates; Pulses; Liquid chromatography; Mass spectrometry; Quantification; Food analysis; Food composition

G2C2 - III. Structural parameters for Galactic globular clusters in SDSS passbands - Vanderbeke, Joachim; De Propris, Roberto; De Rijcke, Sven; Baes, Maarten; West, Michael J.; Blakeslee, John P. (Monthly Notices of the Royal Astronomical Society, 2015)
We use our Galactic Globular Cluster Catalog (G2C2) photometry for 111 Galactic globular clusters (GCs) in g and z, as well as r and i photometry for a subset of 60 GCs and u photometry for 22 GCs, to determine the structural parameters assuming King models. In general, the resulting core radii are in good comparison with the current literature values. However, our half-light radii are slightly lower than the literature. The concentrations (and therefore also the tidal radii) are poorly constrained mostly because of the limited radial extent of our imaging. Therefore, we extensively discuss the effects of a limited field of view on the derived parameters using mosaicked Sloan Digital Sky Survey data, which do not suffer from this restriction. We also illustrate how red giant branch (RGB) stars in cluster cores can stochastically induce artificial peaks in the surface brightness profiles. The issues related to these bright stars are scrutinized based on both our photometry and simulated clusters. We also examine colour gradients and find that the strongest central colour gradients are caused by central RGB stars and thus not representative for the cluster light or colour distribution. We recover the known relation between the half-light radius and the Galactocentric distance in the g band, but find a lower slope for redder filters. We did not find a correlation between the scatter on this relation and other cluster properties. We find tentative evidence for a correlation between the half-light radii and the [Fe/H], with metal-poor GCs being larger than metal-rich GCs. However, we conclude that this trend is caused by the position of the clusters in the Galaxy, with metal-rich clusters being more centrally located.
Keywords: globular clusters: general

Functionalized rosette nanotubes as novel electron donor materials for solution-processed organic photovoltaics - Shuai, Liang; Parthasarathy, Venkatakrishnan; Cho, Jae-Young; Yamazaki, Takeshi; Beingessner, Rachel L.; Fenniri, Hicham (Materials Research Society Symposium Proceedings, 2015)
Two self-assembling twin guanine-cytosine (G∧C) hybrid molecules featuring porphyrin (TPPO-(G∧C)₂) and oligothiophene groups (6T-(G∧C)₂) were synthesized. In organic solution, these molecules self-assemble into one-dimensional rosette nanotubes (RNTs) featuring the porphyrin or oligiothiophene groups on the outer surface. Using a combination of imaging and spectroscopic techniques we established the structure of the TPPO-(G∧C)₂ and 6T-(G∧C)₂ RNTs and compared the HOMO and LUMO energy levels with PC61BM, a well-known electron acceptor material. These studies, in combination with solid-state photoluminescence data of PC61BM-TPPO-(G∧C)₂ RNT blended thin films, indicates that these self-assembled nanomaterials have great potential as electron donor materials for solution-processed organic photovoltaics.
Keywords: Electron acceptor materials; Guanine cytosines; HOMO and LUMO energies; Hybrid molecules; Organic photovoltaics; Organic solutions; Solution-processed; Spectroscopic technique

Fucoxanthin enhances chain elongation and desaturation of alpha-linolenic acid in HepG2 cells - Wu, Meng-Ting; Su, Hui-Min; Cui, Yi; Windust, Anthony; Chou, Hong-Nong; Huang, Ching-jang (Lipids, 2015)
Dietary fucoxanthin (FX), a carotenoid compound from brown algae, was found to increase docosahexaenoic acid (DHA, 22:6n-3) and arachidonic acid (ARA, 20:4n-6) in the liver of mice. DHA and ARA are known to be biosynthesized from the respective precursor α-linolenic acid (ALA, 18:3n-3) and linoleic acid (LNA, 18:2n-6), through desaturation and chain elongation. We examined the effect of FX on the fatty acid metabolism in HepG2 cells (Hepatocellular carcinoma, human). In the first experiment, cells were co-treated with ALA (100 μM) and FX (0–100 μM) or vehicle for 48 h. FX increased eicosapentaenoic acid (EPA, 20:5n-3), docosapentaenoic acid (DPA, 22:5n-3), DHA at concentrations of ≥50 μM. To clarify the change in the metabolism of polyunsaturated fatty acid (PUFA), in the second experiment, cells were co-treated with universally-[¹³C]-labeled (U-[¹³C]-) ALA (100 μM) and FX (100 μM) for 0.5, 3, 6, 24 and 48 h. [¹³C] labeled-EPA, DPA and DHA content in HepG2 cells were all increased by FX after 48 h treatment. Furthermore, estimated delta-5 desaturase (D5D) but not delta-6 desaturase (D6D) activity index was increased at 48 h. These results suggested that FX may enhance the conversion of ALA to longer chain n-3 PUFA through increasing D5D activity in the liver.
Keywords: Fucoxanthin; Delta-5 desaturase; Elongation; ALA; EPA; DHA; n-3 PUFA

From soft harmonic phonons to fast relaxational dynamics in CH₃NH₃PbBr₃ - Swainson, I. P.; Stock, C.; Parker, S. F.; Van eijck, L.; Russina, M.; Taylor, J. W. (Physical Review B, 2015)
The lead-halide perovskites, including CH₃NH₃PbBr₃, are components in cost effective, highly efficient photovoltaics, where the interactions of the molecular cations with the inorganic framework are suggested to influence the electronic and ferroelectric properties. CH₃NH₃PbBr₃ undergoes a series of structural transitions associated with orientational order of the CH₃NH₃ (methylammonium) molecular cation and tilting of the PbBr₃ host framework. We apply high-resolution neutron scattering to study the soft harmonic phonons associated with these transitions, and find a strong coupling between the PbBr₃ framework and the quasistatic CH₃NH₃ dynamics at low energy transfers. At higher energy transfers, we observe a PbBr₆ octahedra soft mode driving a transition at 150 K from bound molecular excitations at low temperatures to relatively fast relaxational excitations that extend up to ∼50–100 meV. We suggest that these temporally overdamped dynamics enables possible indirect band gap processes in these materials that are related to the enhanced photovoltaic properties.

Frequency-dependent linewidth enhancement factor of optical injection-locked quantum dot/dash lasers - Wang, Cheng; Chaibi, Mohamed E.; Huang, Heming; Erasme, Didier; Poole, Philip; Even, Jacky; Grillot, Frédéric (Optics Express, 2015)
Combining theoretical and experimental studies show that optical injection strongly changes the behavior of the linewidth enhancement factor (αH-factor) and the FM-to-AM indices ratio (FAIR) in quantum dash/dot semiconductor lasers. In contrast to solitary lasers, both the αH-factor and the FAIR at low-frequency modulation are reduced by optical injection. At high modulation frequency, however, the phase-amplitude coupling characteristics are little influenced by optical injection.
Keywords: Frequency modulation; Modulation; Quantum dash lasers; Semiconductor lasers; Semiconductor quantum dots Frequency dependent; High modulation frequency; Linewidth enhancement factor; Low frequency modulation; Optical injection; Phaseamplitude couplings (PAC); Quantum dashes; Solitary laser

Fossil group origins : V. The dependence of the luminosity function on the magnitude gap - Zarattini, S.; Aguerri, J. A. L.; Sánchez-Janssen, R.; Barrena, R.; Boschin, W.; del Burgo, C.; Castro-Rodriguez, N.; Corsini, E. M.; D’onghia, E.; Girardi, M.; Iglesias-Páramo, J.; Kundert, A.; et al. (Astronomy and Astrophysics, 2015)
Context. In nature we observe galaxy aggregations that span a wide range of magnitude gaps between the two first-ranked galaxies of a system (Δm₁₂). Thus, there are systems with gaps close to zero (e.g., the Coma cluster), and at the other extreme of the distribution, the largest gaps are found among the so-called fossil systems. The observed distribution of magnitude gaps is thought to be a consequence of the orbital decay of M∗ galaxies in massive halos and the associated growth of the central object. As a result, to first order the amplitude of this gap is a good statistical proxy for the dynamical age of a system of galaxies. Fossil and non-fossil systems could therefore have different galaxy populations that should be reflected in their luminosity functions.
Keywords: galaxies: clusters: general; galaxies: groups: general; galaxies: luminosity function, mass function

First-order melting of a weak spin-orbit Mott insulator into a correlated metal - Hogan, Tom; Yamani, Z.; Walkup, D.; Chen, Xiang; Dally, Rebecca; Ward, Thomas Z.; Dean, M. P. M.; Hill, John; Islam, Z.; Madhavan, Vidya; Wilson, Stephen D. (Physical Review Letters, 2015)
The electronic phase diagram of the weak spin-orbit Mott insulator (Sr₁−xLax)₃Ir₂O₇ is determined via an exhaustive experimental study. Upon doping electrons via La substitution, an immediate collapse in resistivity occurs along with a narrow regime of nanoscale phase separation comprised of antiferromagnetic, insulating regions and paramagnetic, metallic puddles persisting until x≈0.04. Continued electron doping results in an abrupt, first-order phase boundary where the Néel state is suppressed and a homogenous, correlated, metallic state appears with an enhanced spin susceptibility and local moments. As the metallic state is stabilized, a weak structural distortion develops and suggests a competing instability with the parent spin-orbit Mott state.
Keywords: Magnetic susceptibility; Phase separation Antiferromagnetics; Electronic phase diagram; First-order melting; La substitutions; Mott insulators; Nano-scale phase separation; Spin susceptibility; Structural distortions

MOS testbed for the characterization of targeted alpha therapy pharmaceuticals - Griffin, Ryan H; Mcconnell, E. M.; Derosa, M. C.; Tarr, N. G. (IEEE Sensors Journal, 2015)
A metal-oxide-semiconductor (MOS) sensor has been designed, fabricated, and tested for use in the characterization of targeted alpha therapy pharmaceuticals. The sensor consists of a 16 × 16 array of 100-μm square alpha particle sensitive cells and has been fabricated in house using a simple MOS process. A subset of those cells is functionalized for the attachment of chelators under investigation for new pharmaceuticals. To demonstrate the utility of this sensor as a characterization platform, cells functionalized with 1,4,7, 10-tetraazacyclododecane-1,4,7,10-tetraacetic acid (DOTA)-DNA conjugates were used to chelate americium-241 from solution, and the alpha particle emissions over the surface of the integrated circuit (IC) measured. The IC was able to quantitatively determine the amount of alpha emitter present over each cell, allowing the chelator and chelating chemistry to be assessed. Without any optimization of the chelation chemistry, a 21% increase of emissions was detected on cells functionalized with DOTA.
Keywords: pharmaceutical development; Metal-Oxide-Semiconductor; MOS; Radioimmunotherapy; RIT; Targeted Alpha Therapy; TAT; Targeted Radionuclide Therapy; TRT; aptamer; DNA; chelator characterization; DOTA

Far-IR spectra and structures of small cationic ruthenium clusters : evidence for cubic motifs - Kerpal, Christian; Harding, Dan J.; Rayner, David M.; Lyon, Jonathan T.; Fielicke, André (The Journal of Physical Chemistry C, 2015)
Far-IR vibrational spectra of small ruthenium cluster cations (Ru₇⁺, Ru₈⁺, and Ru₉⁺) are measured via infrared multiple photon dissociation (IR-MPD) spectroscopy using Ar atoms as messenger for the absorption. These spectra are compared to results from density functional theory calculations, leading to structural assignments. The pure functional PBE leads to better agreement with the experimental data compared to the hybrid functional PBE0. For all three cluster sizes the structures assigned are based on a cubic motif and are a distorted cube missing one corner atom (Ru₇⁺), a slightly distorted cube (Ru₈⁺), and a face-capped cube (Ru₉⁺).
Keywords: Geometry; Ruthenium Ar atom; Cluster sizes; Hybrid functional; Infrared multiple photon dissociations; IR spectrum; Ruthenium clusters; Structural assignments

Faba bean : transcriptome analysis from etiolated seedling and developing seed coat of key cultivars for synthesis of proanthocyanidins, phytate, raffinose family oligosaccharides, vicine, and convicine - Ray, Heather; Bock, Cheryl; Georges, Fawzy (The Plant Genome, 2015)
Faba bean (Vicia faba L.) has been little examined from a genetic or genomic perspective despite its status as an established food and forage crop with some key pharmaceutical factors such as vicine and convicine (VC), which provoke severe haemolysis in genetically susceptible humans. We developed next-generation sequencing libraries to maximize information to elucidate the VC pathway or relevant markers as well as other genes of interest for the species. One selected cultivar, A01155, lacks synthesis of the favism-provoking factors, VC, and is low in tannin, while two cultivars, SSNS-1 and CDC Fatima, are wild-type for these factors. Tissues (5- to 6-d-old root and etiolated shoot and developing seed coat) were selected to maximize the utility and breadth of the gene expression profile. Approximately 1.2 × 106 expressed transcripts were sequenced and assembled into contigs. The synthetic pathways for phosphatidylinositol or phytate, the raffinose family oligosaccharides, and proanthocyanidin were examined and found to contain nearly a full complement of the synthetic genes for these pathways. A severe deficiency in anthocyanidin reductase expression was found in the low-tannin cultivar A01155. Approximately 5300 variants, including 234 variants specific to one of the three cultivars, were identified. Differences in expression and variants potentially related to VC synthesis were analyzed using strategies exploiting differences in expression between cultivars and tissues. These sequences should be of high utility for marker-assisted selection for the key traits vicine, convicine, and proanthocyanidin, and should contribute to the scant genetic maps available for this species.

Extreme wave loads on submerged water intakes in shallow water - Cornett, Andrew; Hecimovich, Mark; Nistor, Ioan (Journal of Hydrodynamics, Ser. B, 2015)
This paper provides new guidance concerning the hydrodynamic loads on submerged intake structures located in shallow water under breaking and non-breaking waves. Results from a series of experiments conducted in a large wave flume at 1:15 scale to study the hydrodynamic forces exerted on a generic intake structure located on a sloping seabed in shallow water below breaking and non-breaking irregular waves are presented. Based on analysis of the experimental data, empirical relationships are developed to describe the peak loads in terms of characteristic wave parameters such as significant wave height and peak wave period. The distribution of the peak loads across different parts of the intake structure is also described. Drag and inertia force coefficients for the horizontal forcing on the intake structure and for the main structural sub-components are derived and presented. It is shown that the well-known Morison equation, with appropriate drag and inertia force coefficients, can provide reasonable estimates of the moderate horizontal loads, but the peak loads are less well predicted.
Keywords: wave force; water intake; drag force; inertia force; coastal engineering

Experimental investigation of soot formation characteristics on gasoline-diesel blend flames - Dai, Y.-J.; Liu, F.-S.; He, X.; Liu, F.-S. (Neiranji Xuebao/Transactions of CSICE (Chinese Society for Internal Combustion Engines), 2015)
Stable laminar diffusion flames of different gasoline-diesel blends, namely G0, G20, G50, G80 and G100, were formed using a novel pre-vaporized liquid fuel burner system to investigate the soot formation characteristics in these flames. A two-dimensional line-of-sight attenuation technique was employed to acquire the twodimensional transmissivity images followed by an effective tomographic inversion algorithm for soot volume fraction distributions. Soot particles were also sampled using a rapid insertion probe for transmission electron microscope(TEM)image analysis to get soot morphology and primary particle size information. Test results show that, with the increase of gasoline to diesel, soot concentrations decrease to different levels at different heights, showing the stronger soot generation propensity of diesel. Soot particle sizes also decrease when more gasoline is added to diesel but primary soot particle diameters remain in the range from 14 nm, to 39, nm.
Keywords: Diesel; Gasoline; Liquid burner; Soot; Transmission electron microscope

Experimental investigation of chair type, row spacing, occupants, and carpet on theatre chair absorption - Choi, Young-Ji; Bradley, John S.; Jeong, Dae-Up (The Journal of the Acoustical Society of America, 2015)
This paper examines how the individual variations of chair type, row spacing, as well as the presence of occupants and carpet, combine to influence the absorption characteristics of theater chairs as a function of sample perimeter-to-area (P/A) ratios. Scale models were used to measure the interactive effects of the four test variables on the chair absorption characteristics, avoiding the practical difficulties of full scale measurements. All of the test variables led to effects that could lead to important changes to auditorium acoustics conditions. At mid and higher frequencies, the various effects can usually be explained as due to, more or less, porous absorbing material. In the 125 and 250 Hz octave bands, the major changes were attributed to resonant absorbing mechanisms. The results indicate that for accurate predictions of the effective absorption of the chairs in an auditorium, one should use the P/A method and reverberation chamber tests of the chair absorption coefficients to predict the absorption coefficients of each block of chairs and use these results as input in a room acoustics computer model of the auditorium. The application of these results to auditorium acoustics design is described, more approximate approaches are considered, and relations to existing methods are discussed.

Evidence that biosynthesis of the second and third sugars of the archaellin tetrasaccharide in the archaeon Methanococcus maripaludis occurs by the same pathway used by Pseudomonas aeruginosa to make a di-N-acetylated sugar - Siu, Sarah; Robotham, Anna; Logan, Susan M.; Kelly, John F.; Uchida, Kaoru; Aizawa, Shin-Ichi; Jarrell, Ken F.; Metcalf, W. W. (Journal of Bacteriology, 2015)
Methanococcus maripaludis has two surface appendages, archaella and type IV pili, which are composed of glycoprotein subunits. Archaellins are modified with an N-linked tetrasaccharide with the structure Sug-1,4-β-ManNAc3NAmA6Thr-1,4-β-GlcNAc3NAcA-1,3-β-GalNAc, where Sug is (5S)-2-acetamido-2,4-dideoxy-5-O-methyl-α-L-erythro-hexos-5-ulo-1,5-pyranose. The pilin glycan has an additional hexose attached to GalNAc. In this study, genes located in two adjacent, divergently transcribed operons (mmp0350-mmp0354 and mmp0359-mmp0355) were targeted for study based on annotations suggesting their involvement in biosynthesis of N-glycan sugars. Mutants carrying deletions in mmp0350, mmp0351, mmp0352, or mmp0353 were nonarchaellated and synthesized archaellins modified with a 1-sugar glycan, as estimated from Western blots. Mass spectroscopy analysis of pili purified from the Δmmp0352 strain confirmed a glycan with only GalNAc, suggesting mmp0350 to mmp0353 were all involved in biosynthesis of the second sugar (GlcNAc3NAcA). The Δmmp0357 mutant was archaellated and had archaellins with a 2-sugar glycan, as confirmed by mass spectroscopy of purified archaella, indicating a role for MMP0357 in biosynthesis of the third sugar (ManNAc3NAmA6Thr). M. maripaludis mmp0350, mmp0351, mmp0352, mmp0353, and mmp0357 are proposed to be functionally equivalent to Pseudomonas aeruginosa wbpABEDI, involved in converting UDP-N-acetylglucosamine to UDP-2,3-diacetamido-2,3-dideoxy-D-mannuronic acid, an O5-specific antigen sugar. Cross-domain complementation of the final step of the P. aeruginosa pathway with mmp0357 supports this hypothesis.
Keywords: tetrasaccharide; fimbria protein; glycoprotein; oligosaccharide

Evaluation of alanine as a reference dosimeter for therapy level dose comparisons in megavoltage electron beams - McEwen, Malcolm; Sharpe, Peter; Vörös, Sándor (Metrologia, 2015)
When comparing absorbed dose standards from different laboratories (e.g. National Measurement Institutes, NMIs, for Key or Supplementary comparisons) it is rarely possible to carry out a direct comparison of primary standard instruments, and therefore some form of transfer detector is required. Historically, air-filled, unsealed ionization chambers have been used because of the long history of using these instruments, very good stability over many years, and ease of transport. However, the use of ion chambers for therapy-level comparisons is not without its problems. Findings from recent investigations suggest that ion chambers are prone to non-random variations, they are not completely robust to standard courier practices, and failure at any step in a comparison can render all measurements potentially useless. An alternative approach is to identify a transfer system that is insensitive to some of these concerns—effectively a dosimeter that is inexpensive, simple to use, robust, but with sufficient precision and of a size relevant to the disseminated quantity in question. The alanine dosimetry system has been successfully used in a number of situations as an audit dosimeter and therefore the purpose of this investigation was to determine whether alanine could also be used as the transfer detector for dosimetric comparisons, which require a lower value for the measurement uncertainty. A measurement protocol was developed for comparing primary standards of absorbed dose to water in high-energy electron beams using alanine pellets irradiated in a water-equivalent plastic phantom. A trial comparison has been carried out between three NMIs and has indicated that alanine is a suitable alternative to ion chambers, with the system used achieving a precision of 0.1%. Although the focus of the evaluation was on the performance of the dosimeter, the comparison results are encouraging, showing agreement at the level of the combined uncertainties (~0.6%). Based on this investigation, a large-scale comparison of primary standards for high-energy electron beams is currently being developed under the auspices of the BIPM.
Keywords: dosimetry; electron beams; alanine; key comparison

Evaluation of air leakage properties of seam-fastened mechanically attached single-ply and polymer-modified bitumen roof membrane assemblies - Molleti, Sudhakar; Baskaran, Bas; Kalinger, Peter; Graham, Mark; Cote, J. F.; Malpezzi, Joe; Schwetz, Joe (Roofing Research and Standards Development: 8th Symposium, 2015)
The National Research Council of Canada (NRCC) in collaboration with the Canadian Roofing Contractors Association (CRCA), National Roofing Contractors Association (NRCA), Roofing Industry Alliance for Progress, and the Single-Ply Roofing Institute (SPRI) addressed the issue of air movement in roof assemblies through a research and development project designated air movement impacts on roof Systems (AIR). The AIR steering committee developed goals for a two-phase testing program: Phase 1, quantify air permeances of single-ply and polymer-modified bitumen membrane materials; and Phase 2, quantify air leakage rates of seam-fastened mechanically attached single-ply and polymer-modified bitumen roof membrane assemblies. In Phase 1, four roof membrane materials were tested using ASTM E2178 test protocol to measure the air permeability rates. The tested materials meet the air permeability criterion of ASHRAE 189.1, ASHRAE 90.1, and the International Energy Conservation Code (IECC) for effective air barrier materials. In Phase 2, a test method for measuring air leakage rates across membrane roof assemblies was developed. Test assemblies were constructed with seam-fastened mechanically attached Phase 1 roof membrane materials, rigid board roof insulation, and steel roof decks. Each test assembly also included five common roof penetrations flashed in accordance with the manufacturers' installation instructions. The results demonstrated that the tested assemblies comply with ASHRAE 189.1, ASHRAE 90.1, and the IECC air leakage requirement for effective air barrier assemblies. An ASTM work item under the D08 committee is underway on the developed test method for measuring air leakage rates across membrane roof assemblies.
Keywords: air permeability; air leakage; air barrier material; air barrier assembly; single-ply roof assembly; polymer-modified bitumen roof assembly

Evaluation and selection of high-temperature fixed-point cells for thermodynamic temperature assignment - Yamada, Y.; Anhalt, K.; Battuello, M.; Bloembergen, P.; Khlevnoy, B.; Machin, G.; Matveyev, M.; Sadli, M.; Todd, A.; Wang, T. (International Journal of Thermophysics, 2015)
A multi-partner project to determine the thermodynamic temperatures of a selected set of high-temperature fixed points based on metal-carbon eutectics is underway as a working group activity within the Comité International des Poids et Mesures. The investigation focuses on four fixed-point types, namely, the three metal-carbon eutectic points of Re-C (2474∘C)(2474∘C) , Pt-C (1738∘C)(1738∘C) , and Co-C (1324∘C)(1324∘C) , and the Cu point (1084.62∘C)(1084.62∘C) . This paper describes the construction, pre-evaluation, and screening stage of the cells prior to their thermodynamic temperature determinations. The construction of the HTFP cells was undertaken by nine national metrology institutes (NMIs) according to instructions laid out in a pre-agreed protocol that ensures production of best quality cells. Four NMIs conducted the evaluation, each for a certain fixed-point type, and screened out cells that did not meet pre-determined selection criteria while assuring sufficient variety in the sources of the cells in the final selected sets. In autumn 2012, the selected cells were successfully passed on to the final stage of the project, the thermodynamic temperature measurement, and assignment.
Keywords: High-temperature fixed points; Metal-carbon eutectics; Radiation thermometry; Temperature standards; Thermodynamic temperature

Enhanced killing of breast cancer cells by a d-amino acid analog of the winter flounder-derived pleurocidin NRC-03 - Hilchie, Ashley L.; Haney, Evan F.; Pinto, Devanand M.; Hancock, Robert E. W.; Hoskin, David W. (Experimental and Molecular Pathology, 2015)
Cationic antimicrobial peptides (CAPs) defend against pathogens and, in some cases, exhibit potent anticancer activities. We previously reported that the pleurocidin NRC-03 causes lysis of breast cancer and multiple myeloma cells. NRC-03 also reduces the EC₅₀ of other cytotoxic compounds and prevents tumor growth in vivo. However, the therapeutic utility of NRC-03 may be limited by its susceptibility to degradation by proteases. The goal of this study was to characterize the anticancer activities of a d-amino acid analog of NRC-03 ([D]-NRC-03) that was predicted to be resistant to proteolytic degradation. Unlike NRC-03, [D]-NRC-03 was not degraded by human serum or trypsin and, in comparison to NRC-03, showed increased killing of breast cancer cells, including multidrug-resistant cells; however, [D]-NRC-03 was somewhat more cytotoxic than NRC-03 for several types of normal cells. Importantly, [D]-NRC-03 was more effective than NRC-03 in vivo since 4-fold less peptide was required for an equivalent inhibitory effect on the growth of breast cancer cell xenografts in immune-deficient mice. These findings demonstrate that a d-amino acid analog of NRC-03 overcomes a major limitation to the therapeutic use of NRC-03, namely peptide stability. Further modification of [D]-NRC-03 is required to improve its selectivity for cancer cells.
Keywords: Antimicrobial peptide; Breast cancer; d-amino acid; Cytotoxicity; Pleurocidin

Electron transport, trapping and recombination in anodic TiO₂ nanotube arrays - Mohammadpour, Arash; Kar, Piyush; D. Wiltshire, Benjamin; M. Askar, Abdelrahman; Shankar, Karthik (Current Nanoscience, 2015)
Anodically synthesized TiO₂ nanotube arrays (TNTAs) constitute an exciting ordered large bandgap semiconductor nanoarchitecture for use as scaffolds and active layers for solution-processable devices including but not limited to, optoelectronic sensors, photovoltaics, photodetectors, photocatalysts and photoelectrochemical cells. Charge transport, trapping and recombination are key attributes of the material architecture that significantly influence the properties and performance of the resulting optoelectronic devices, thus motivating this review article. Since nanocrystalline mesoporous TiO2 films (np-TiO₂) are actively researched for the same applications, in many cases, TNTAs and np-TiO₂ are direct competitors and it is therefore meaningful to compare the optoelectronic properties of the two architectures head-to-head. In addition, there exists a whole host of TNTA-specific applications such as bottom-up fabricated photonic crystals, bulk heterojunction organic solar cells and metallodielectric metamaterials that leverage the ordered channel architecture. Recent studies have established the order of magnitude superior recombination lifetimes in sensitized TNTAs as compared to sensitized np-TiO₂ as well as the salutary effect of lower structural disorder in TNTAs resulting in trap-free electron diffusion coefficients approaching those of single crystals and two orders of magnitude larger than np-TiO₂. Photoconductivity measurements using bandgap illumination in both single nanotubes and nanotube ensembles have resulted in similar values of the mobility-lifetime product (10⁻⁵-10⁻⁴ cm²V⁻¹), which are four to six orders of magnitude higher than in nanoparti-cle electrodes. At the same time, TiO₂ nanotubes have a larger trap density and a greater average trap-depth than nanopar-ticulate TiO₂ films, pointing to the importance of synthesis modification to improve material quality and post-synthesis techniques for trap passivation.
Keywords: Cyclic Voltammetry; Electrochemical Impedance Spectroscopy; Imps/Imvs Studies; Open-Circuit Voltage Decay; Photoconductivity; Photoluminescence; Resistivity; TiO2 Nanotubes Arrays

Electric interfacial layer of modified cellulose nanocrystals in aqueous electrolyte solution : predictions by the molecular theory of solvation - Lyubimova, Olga; Stoyanov, Stanislav R.; Gusarov, Sergey; Kovalenko, Andriy (Langmuir, 2015)
The X-ray crystal structure-based models of Iα cellulose nanocrystals (CNC), both pristine and containing surface sulfate groups with negative charge 0–0.34 e/nm² produced by sulfuric acid hydrolysis of softwood pulp, feature a highly polarized “crystal-like” charge distribution. We perform sampling using molecular dynamics (MD) of the structural relaxation of neutral pristine and negatively charged sulfated CNC of various lengths in explicit water solvent and then employ the statistical mechanical 3D-RISM-KH molecular theory of solvation to evaluate the solvation structure and thermodynamics of the relaxed CNC in ambient aqueous NaCl solution at a concentration of 0.0–0.25 mol/kg. The MD sampling induces a right-hand twist in CNC and rearranges its initially ordered structure with a macrodipole of high-density charges at the opposite faces into small local spots of alternating charge at each face. This surface charge rearrangement observed for both neutral and charged CNC significantly affects the distribution of ions around CNC in aqueous electrolyte solution. The solvation free energy (SFE) of charged sulfated CNC has a minimum at a particular electrolyte concentration depending on the surface charge density, whereas the SFE of neutral CNC increases linearly with NaCl concentration. The SFE contribution from Na⁺ counterions exhibits behavior similar to the NaCl concentration dependence of the whole SFE. An analysis of the 3D maps of Na⁺ density distributions shows that these model CNC particles exhibit the behavior of charged nanocolloids in aqueous electrolyte solution: an increase in electrolyte concentration shrinks the electric interfacial layer and weakens the effective repulsion between charged CNC particles. The 3D-RISM-KH method readily treats solvent and electrolyte of a given nature and concentration to predict effective interactions between CNC particles in electrolyte solution. We provide CNC structural models and a modeling procedure for studies of effective interactions and the formation of ordered phases of CNC suspensions in electrolyte solution.

Efficient fiber collection of nitrogen-vacancy center emission from diamond nano beams - Jayakumar, Harishankar; Khanaliloo, Behzad; Barclay, Paul E. (CLEO 2015 : Conference on Lasers and Electro-Optics, 2015)
We present tapered diamond nano beams, which allows efficient collection of diamond nitrogen vacancy emission through phase-matched coupling to a tapered optical fiber.
Keywords: diamonds; couplings; optical coupling; optical fibers; photonics

Effects of varied row spacing and adding cushions, carpet and occupants on pew sound absorption - Choi, Young-Ji; Bradley, John S. (Applied Acoustics, 2015)
This work examines how the individual variations of row spacing, as well as the presence of cushions, carpet and occupants, combine to influence the absorption characteristics of church pews as a function of sample perimeter-to-area (P/A) ratios. Scale models were used to measure the interactive effects of the four test variables on church pew absorption characteristics. The effects of row spacing on frequency-averaged pew absorption coefficients (500–4 kHz) were generally quite small and were smallest for pews without cushions. The variations of absorption increments with varied row spacing tended to be smallest when the pews were less absorptive, i.e. with less cushions, carpet or occupants, similar to the previously studied model theatre chairs. Resonant absorption effects seem to influence the measured absorption of the model pews in the 125 and 250 Hz octave bands and these effects are expected to be modified by the height of the pew backs and the spacing between pews. The incremental absorption coefficients of adding absorptive materials, such as carpet or cushions, to the pews were different than the absorption characteristics of cushions or carpet tested independent of the pews, and these differences varied with frequency. Using the resulting absorption coefficients calculated for each block of pews in a church as input to a room acoustics computer model is expected to provide the best currently possible predictions of acoustical conditions.
Keywords: Absorption coefficients; Church pews; Perimeter to area ratio

Effect of sol stabilizer on the structure and electronic properties of solution-processed ZnO thin films - Adl, Ahmad Hossein; Kar, Piyush; Farsinezhad, Samira; Sharma, Himani; Shankar, Karthik (RSC Advances, 2015)
ZnO is an increasingly important wide bandgap semiconductor for optoelectronic applications. Solution processing provides a facile and inexpensive method to form ZnO thin films with high throughput. The sol stabilizer used in the solution processing of ZnO functions variously as a sol homogenizer, chelating agent, wettability improver and capping agent. In spite of its obvious importance in influencing ZnO film properties, a restricted set of short chain alkaline sol stabilizers have been used in prior reports. We examined the effect of six different sol stabilizers, including acidic and longer chain species, along with a recipe without any stabilizer, on the grain size, crystallographic texture, and resistivity of solution processed ZnO films on thermal oxide-coated silicon substrates, and found large variations in the structural and electrical properties as a consequence of the choice of sol stabilizer. We found that ZnO films formed using oleic acid as the sol stabilizer possessed a strong (002) preferred orientation with a Lotgering factor as high as 0.86. The key insight we obtained is that the sol stabilizer strongly influences the film surface area and activation energy barrier for inter-grain transport. We comprehensively studied the steady state and transient behavior of ZnO films deposited using different stabilizers and compared their lifetime and mobility-lifetime products. When exposed to illumination, the conductivity of the deposited films increased by several orders of magnitude. This is attributed to the trapping of the nonequilibrium holes by the surface adsorbed oxide species, which produces equivalent number of excess electrons in the conduction band. Impedance spectroscopy and C–V measurements were performed to calculate the doping of the ZnO thin films. ZnO thin film transistors were also fabricated and the effects of the sol stabilizer on the different parameters of the TFT like mobility and threshold voltage were investigated.

Effect of FRP retrofitting on post-blast axial capacity of reinforced concrete columns - Kadhom, B.; Almansour, H.; Saatcioglu, M. (Annual Conference - Canadian Society for Civil Engineering (2015), 2015)
An experimental study was performed to examine the enhancement in axial capacity of HP-CFRP wrapped reinforced concrete columns subjected to simulated air blast. Tests were conducted in an academic testing environment using a shock tube. Four half scale reinforced concrete columns (150 mm × 150 mm × 2438 mm) were tested under single blast shot. Two columns were externally strengthened with UD [0/90] W [±45]₂ UD [0] CFRP sheets, and the other two columns were left unprotected to serve as control columns. The columns were subjected to axial compression of 50 % of the column ultimate axial capacity. In order to examine the residual axial capacity of the tested columns, they were loaded axially up to ultimate load capacity after the application of the blast load. The damage generated at the critical zone was completely prevented by the application of the CFRP jacketing. It is found that columns externally strengthened with CFRP laminate are capable to carry high axial load compared to unprotected columns after a major blast event.
Keywords: Concrete construction; Concretes; Shock testing; Shock tubes Axial capacity; Blast events; CFRP laminate; Critical zones; FRP retrofitting; Reinforced concrete column; Testing environment; Ultimate load capacity

Effect of ethanol addition in gasoline on soot formation characteristics in diffusion flames - Dai, Y.-J.; Liu, F.-S.; He, X.; Zheng, L.; Liu, F.-S.; Wang, J.-X. (Chinese Internal Combustion Engine Engineering, 2015)
A novel liquid fuel combustion apparatus that can produce stable laminar diffusion flames was designed and set up. Gasoline-ethanol blends of 0%, 20%, 50% and 85% of ethanol in volume were used as fuel. Soot concentration profiles under atmospheric pressure were measured with an optical diagnostic technique to examine how adding ethanol to gasoline affects soot formation. The test results show that these gasoline-ethanol blends can generate stable diffusion flames with visible heights remaining at(50± 1) mm with increased amount of ethanol in gasoline under the condition of a fixed carbon flow rate of 6.05 g/h, that soot concentrations at different heights are reduced to different degrees, and that the total soot decreases almost linearly. The totals of soot in the flames fuelled by blends of 20%, 50%, and 85% ethanol are reduced by 16.20%, 37.77% and 61.66% respectively against that in the gasoline flame.
Keywords: 2D-LOSA; Ethanol-gasoline; IC engine; Liquid burner; Optical measurement; Soot

Effect of cholesterol on the structure of a five-component mitochondria-like phospholipid membrane - Cathcart, Kelly; Patel, Amit; Dies, Hannah; Rheinstädter, Maikel; Fradin, Cécile (Membranes, 2015)
Cellular membranes have a complex phospholipid composition that varies greatly depending on the organism, cell type and function. In spite of this complexity, most structural data available for phospholipid bilayers concern model systems containing only one or two different phospholipids. Here, we examine the effect of cholesterol on the structure of a complex membrane reflecting the lipid composition of mitochondrial membranes, with five different types of headgroups (phosphatidylcholine (PC), phosphatidylethanolamine (PE), phosphatidylinositol (PI), phosphatidylserine (PS) and cardiolipin (CL)) and a variety of hydrocarbon tails. This particular system was chosen because elevated cholesterol contents in mitochondrial membranes have been linked to a breaking down of Bax-mediated membrane permeabilization and resistance to cancer treatments. High resolution electron density profiles were determined by X-ray reflectivity, while the area per phospholipid chain, Apc, and the chain order parameter, SX-ray, were determined by wide-angle X-ray scattering (WAXS). We show that chain order increases upon the addition of cholesterol, resulting in both a thickening of the lipid bilayer and a reduction in the average surface area per phospholipid chain. This effect, well known as cholesterol’s condensation effect, is similar, but not as pronounced as for single-component phospholipid membranes. We conclude by discussing the relevance of these findings for the insertion of the pro-apoptotic protein Bax in mitochondrial membranes with elevated cholesterol content.
Keywords: phospholipid; cholesterol; mitochondria; cardiolipin; apoptosis; Bax; X-ray diffraction; reflectivity; wide angle X-ray scattering

First experimental demonstration of high-directionality fiber-chip grating coupler with interleaved trenches - Benedikovic, Daniel; Alonso-ramos, Carlos; Cheben, Pavel; Schmid, Jens H.; Wang, Shurui; Xu, Dan-xia; Halir, Robert; Ortega-monux, Alejandro; Fedeli, Jean-marc; Janz, Siegfried; Molina-fernandez, Inigo; Dado, Milan (2015 IEEE 12th International Conference on Group IV Photonics (GFP), 2015)
We present the first experimental demonstration of a new fiber-chip grating coupler concept that exploits the blazing effect by interleaving deep and shallow etch trenches to maximize directionality. The grating couplers were fabricated using both 193 nm deep-ultraviolet lithography and electron beam lithography. The measured peak fiber-chip coupling efficiency is -1.8 dB at a wavelength of 1550 nm, with a 3 dB bandwidth of 52 nm.

Dish verification antenna-1: a next generation antenna for cm-wave radio telescopes - Hovey, G.; Baker, L.; Cortes, G.; Deboer, D.; Fleming, M.; Imbriale, W.; Lacy, G.; Veidt, B.; Byrnes, P.; Fitzsimmons, J.; Knee, L.; Kesteven, M. (2015 1st URSI Atlantic Radio Science Conference (URSI AT-RASC), 2015)
Radio telescopes striving for orders of magnitude more sensitivity in the cm-wave band require reflector antennas with high performance at low relative cost compared to conventional approaches. The Composite Applications for Radio Telescopes (CART) programme at the National Research Council's (NRC's) Dominion Radio Astrophysical Observatory, near Penticton Canada has been investigating ways to build such telescopes since 2005. In 2010 a collaboration between NRC and the US-Technology Development Project (US TDP) was formed to develop a prototype 15m Gregorian offset antenna for the Square Kilometre Array (SKA). The telescope uses NRC's composite carbon fibre reflector technology to implement the highly optimized shaped optics design and innovative mechanical concepts developed by the US TDP. The result is Dish Verification Antenna-1 (DVA1), a next generation antenna that has exceptional sensitivity (> 9 m2/K), with low monotonically decreasing far out sidelobes (< −50 dB), and high stability over environmental conditions. As well, it is modular, highly reliable, and can be produced at competitive cost using mass production techniques.

Single-crystal diamond nanobeam waveguide optomechanics - Khanaliloo, Behzad; Jayakumar, Harishankar; Hryciw, Aaron C.; Lake, David P.; Kaviani, Hamidreza; Barclay, Paul E. (Physical Review X, 2015)
Single-crystal diamond optomechanical devices have the potential to enable fundamental studies and technologies coupling mechanical vibrations to both light and electronic quantum systems. Here, we demonstrate a single-crystal diamond optomechanical system and show that it allows excitation of diamond mechanical resonances into self-oscillations with amplitude >200  nm . The resulting internal stress field is predicted to allow driving of electron spin transitions of diamond nitrogen-vacancy centers. The mechanical resonances have a quality factor >7×10 5 and can be tuned via nonlinear frequency renormalization, while the optomechanical interface has a 150 nm bandwidth and 9.5  fm/Hz − − − √ sensitivity. In combination, these features make this system a promising platform for interfacing light, nanomechanics, and electron spins.

Donor–acceptor small molecules for organic photovoltaics: single-atom substitution (Se or S) - He, Xiaoming; Cao, Bing; Hauger, Tate C.; Kang, Minkyu; Gusarov, Sergey; Luber, Erik J.; Buriak, Jillian M. (ACS Applied Materials and Interfaces, 2015)
Two isostructural low-band-gap small molecules that contain a one-atom substitution, S for Se, were designed and synthesized. The molecule 7,7′-[4,8-bis(2-ethylhexyloxy)benzo[1,2-b:4,5-b′]dithiophene]bis[6-fluoro-4-(5′-hexyl-2,2′-bithiophen-5-yl)benzo[c][1,2,5]thiadiazole] (1) and its selenium analogue 7,7′-[4,8-bis(2-ethylhexyloxy)benzo[1,2-b:4,5-b′]dithiophene]bis[6-fluoro-4-(5′-hexyl-2,2′-bithiophen-5-yl)benzo[c][1,2,5]selenodiazole] (2) are both based on the electron-rich central unit benzo[1,2-b:4,5-b′]dithiophene. The aim of this work was to investigate the effect of one-atom substitution on the optoelectronic properties and photovoltaic performance of devices. Theoretical calculations revealed that this one-atom variation has a small but measurable effect on the energy of frontier molecular orbital (HOMO and LUMO), which, in turn, can affect the absorption profile of the molecules, both neat and when mixed in a bulk heterojunction (BHJ) with PC71BM. The Se-containing variant 2 led to higher efficiencies [highest power conversion efficiency (PCE) of 2.6%] in a standard organic photovoltaic architecture, when combined with PC71BM after a brief thermal annealing, than the S-containing molecule 1 (highest PCE of 1.0%). Studies of the resulting morphologies of BHJs based on 1 and 2 showed that one-atom substitution could engender important differences in the solubilities, which then influenced the crystal orientations of the small molecules within this thin layer. Brief thermal annealing resulted in rotation of the crystalline grains of both molecules to more energetically favorable configurations.
Keywords: bulk heterojunction; organic photovoltaics; organic solar cell; selenium; small molecules; sulfur

Direct evaluation of the quantum confinement effect in single isolated Ge nanocrystals - Millo, Oded; Balberg, Isacc; Azulay, Doron; Purkait, Tapas K.; Swarnakar, Anindya K.; Rivard, Eric; Veinot, Jonathan G. C. (The Journal of Physical Chemistry Letters, 2015)
To address the yet open question regarding the nature of quantum confinement in Ge nanocrystals (Ge NCs) we employed scanning tunneling spectroscopy to monitor the electronic structure of individual isolated Ge NCs as a function of their size. The (single-particle) band gaps extracted from the tunneling spectra increase monotonically with decreasing nanocrystal size, irrespective of the capping ligands, manifesting the effect of quantum confinement. Band-gap widening of ∼1 eV with respect to the bulk value was observed for Ge-NCs 3 nm in diameter. The picture emerging from comparison with theoretical calculations and other experimental results is discussed.
Keywords: band gap; germanium nanocrystals; quantum confinement; scanning tunneling spectroscopy

Detection of two power-law tails in the probability distribution functions of massive GMCs - Schneider, N.; Bontemps, S.; Girichidis, P.; Rayner, T.; Motte, F.; André, Ph; Russeil, D.; Abergel, A.; Anderson, L.; Arzoumanian, D.; Benedettini, M.; Csengeri, T.; et al. (Monthly notices Letters of the Royal Astronomical Society, 2015)
We report the novel detection of complex high column density tails in the probability distribution functions (PDFs) for three high-mass star-forming regions (CepOB3, MonR2, NGC 6334), obtained from dust emission observed with Herschel. The low column density range can be fitted with a lognormal distribution. A first power-law tail starts above an extinction (AV) of ∼6–14. It has a slope of α = 1.3–2 for the ρ ∝ r−α profile for an equivalent density distribution (spherical or cylindrical geometry), and is thus consistent with free-fall gravitational collapse. Above AV ∼40, 60, and 140, we detect an excess that can be fitted by a flatter power-law tail with α > 2. It correlates with the central regions of the cloud (ridges/hubs) of size ∼1 pc and densities above 104 cm−3. This excess may be caused by physical processes that slow down collapse and reduce the flow of mass towards higher densities. Possible are: rotation, which introduces an angular momentum barrier, (2) increasing optical depth and weaker cooling, (3) magnetic fields, (4) geometrical effects, and (5) protostellar feedback. The excess/second power-law tail is closely linked to high-mass star-formation though it does not imply a universal column density threshold for the formation of (high-mass) stars.
Keywords: ISM; clouds dust; extinction

Design of an advanced automatic inspection system for aircraft parts based on fluorescent penetrant inspection analysis - Zheng, J.; Xie, W. F.; Viens, M.; Birglen, L.; Mantegh, I. (Insight - Non-Destructive Testing and Condition Monitoring, 2015)
Non-destructive testing (NDT) of aircraft parts has become increasingly important in improving the safety and reliability of the aerospace industry, especially in the testing of high-temperature and high-pressure turbine engine parts. Among the various types of NDT methods available, fluorescent penetrant inspection (FPI) is comparably more cost-efficient and is widely used in NDT on aircraft parts. However, current FPI still requires considerable labour forces in its processing, inspection and analysis procedures. In this paper, we have developed an advanced automatic inspection system (AAIS) that uses image processing and pattern recognition techniques to aid human inspectors. The system can automatically detect, measure and classify discontinuities from the FPI images of aircraft parts. Tests have been performed on the sample images provided by our industrial partners to evaluate our developed AAIS. The test results demonstrate that the developed system has significantly improved the efficiency of FPI with satisfactory accuracy.
Keywords: discontinuities; FPI; image processing; pattern recognition; turbine blades

Design of a thermoacoustic sensor for low intensity ultrasound measurements based on an artificial neural network - Xing, Jida; Chen, Jie (Sensors, 2015)
In therapeutic ultrasound applications, accurate ultrasound output intensities are crucial because the physiological effects of therapeutic ultrasound are very sensitive to the intensity and duration of these applications. Although radiation force balance is a benchmark technique for measuring ultrasound intensity and power, it is costly, difficult to operate, and compromised by noise vibration. To overcome these limitations, the development of a low-cost, easy to operate, and vibration-resistant alternative device is necessary for rapid ultrasound intensity measurement. Therefore, we proposed and validated a novel two-layer thermoacoustic sensor using an artificial neural network technique to accurately measure low ultrasound intensities between 30 and 120 mW/cm2. The first layer of the sensor design is a cylindrical absorber made of plexiglass, followed by a second layer composed of polyurethane rubber with a high attenuation coefficient to absorb extra ultrasound energy. The sensor determined ultrasound intensities according to a temperature elevation induced by heat converted from incident acoustic energy. Compared with our previous one-layer sensor design, the new two-layer sensor enhanced the ultrasound absorption efficiency to provide more rapid and reliable measurements. Using a three-dimensional model in the K-wave toolbox, our simulation of the ultrasound propagation process demonstrated that the two-layer design is more efficient than the single layer design. We also integrated an artificial neural network algorithm to compensate for the large measurement offset. After obtaining multiple parameters of the sensor characteristics through calibration, the artificial neural network is built to correct temperature drifts and increase the reliability of our thermoacoustic measurements through iterative training about ten seconds. The performance of the artificial neural network method was validated through a series of experiments. Compared to our previous design, the new design reduced sensing time from 20 s to 12 s, and the sensor’s average error from 3.97 mW/cm2 to 1.31 mW/cm2 respectively.
Keywords: Low Intensity Pulsed Ultrasound (LIPUS); thermoacoustic sensor; ultrasound intensity measurement; artificial neural network

Design and experimental demonstration of optomechanical paddle nanocavities - Healey, Chris; Kaviani, Hamidreza; Wu, Marcelo; Khanaliloo, Behzad; Mitchell, Matthew; Hryciw, Aaron C.; Barclay, Paul E. (Applied Physics Letters, 2015)
We present the design, fabrication, and initial characterization of a paddle nanocavity consisting of a suspended sub-picogram nanomechanical resonator optomechanically coupled to a photonic crystal nanocavity. The optical and mechanical properties of the paddle nanocavity can be systematically designed and optimized, and the key characteristics including mechanical frequency can be easily tailored. Measurements under ambient conditions of a silicon paddle nanocavity demonstrate an optical mode with a quality factor Q o ∼6000 Qo∼6000 near 1550 nm and optomechanical coupling to several mechanical resonances with frequencies ω m /2π∼ 12−64 ωm/2π∼ 12−64  MHz, effective masses meff ∼350−650 meff∼350−650 fg, and mechanical quality factors Q m ∼ 44−327 Qm∼ 44−327. Paddle nanocavities are promising for optomechanical sensing and nonlinear optomechanics experiments.

Cytotoxicity of carbon nanotube variants: a comparative in vitro exposure study with A549 epithelial and J774 macrophage cells - Kumarathasan, Prem; Breznan, Dalibor; Das, Dharani; Salam, Mohamed A.; Siddiqui, Yunus; Mackinnon-roy, Christine; Guan, Jingwen; De silva, Nimal; Simard, Benoit; Vincent, Renaud (Nanotoxicology, 2015)
While production of engineered carbon nanotubes (CNTs) has escalated in recent years, knowledge of risk associated with exposure to these materials remains unclear. We report on the cytotoxicity of four CNT variants in human lung epithelial cells (A549) and murine macrophages (J774). Morphology, metal content, aggregation/agglomeration state, pore volume, surface area and modifications were determined for the pristine and oxidized single-walled (SW) and multi-walled (MW) CNTs. Cytotoxicity was evaluated by cellular ATP content, BrdU incorporation, lactate dehydrogenase (LDH) release, and CellTiter-Blue (CTB) reduction assays. All CNTs were more cytotoxic than respirable TiO2 and SiO2 reference particles. Oxidation of CNTs removed most metallic impurities but introduced surface polar functionalities. Although slopes of fold changes for cytotoxicity endpoints were steeper with J774 compared to A549 cells, CNT cytotoxicity ranking in both cell types was assay-dependent. Based on CTB reduction and BrdU incorporation, the cytotoxicity of the polar oxidized CNTs was higher compared to the pristine CNTs. In contrast, pristine CNTs were more cytotoxic than oxidized CNTs when assessed for cellular ATP and LDH. Correlation analyses between CNTs’ physico–chemical properties and average relative potency revealed the impact of metal content and surface area on the potency values estimated using ATP and LDH assays, while surface polarity affected the potency values estimated from CTB and BrdU assays. We show that in order to reliably estimate the risk posed by these materials, in vitro toxicity assessment of CNTs should be conducted with well characterized materials, in multiple cellular models using several cytotoxicity assays that report on distinct cellular processes.
Keywords: Carbon nanotubes; cytotoxicity; in vitro exposure; lung epithelial cells; macrophages; physico–chemical characteristics

Cytosolic detection of the bacterial metabolite HBP activates TIFA-dependent innate immunity - Gaudet, R. G.; Sintsova, A.; Buckwalter, C. M.; Leung, N.; Cochrane, A.; Li, Jianjun; Cox, Andrew D.; Moffat, J.; Gray-owen, S. D. (Science, 2015)
Host recognition of pathogen-associated molecular patterns (PAMPs) initiates an innate immune response that is critical for pathogen elimination and engagement of adaptive immunity. Here we show that mammalian cells can detect and respond to the bacterial-derived monosaccharide heptose-1,7-bisphosphate (HBP). A metabolic intermediate in lipopolysaccharide biosynthesis, HBP is highly conserved in Gram-negative bacteria, yet absent from eukaryotic cells. Detection of HBP within the host cytosol activated the nuclear factor κB pathway in vitro and induced innate and adaptive immune responses in vivo. Moreover, we used a genome-wide RNA interference screen to uncover an innate immune signaling axis, mediated by phosphorylation-dependent oligomerization of the TRAF-interacting protein with forkhead-associated domain (TIFA) that is triggered by HBP. Thus, HBP is a PAMP that activates TIFA-dependent immunity to Gram-negative bacteria.

Cross-talk between human mast cells and bronchial epithelial cells in plasminogen activator inhibitor-1 production via transforming growth factor-β1 - Cho, Seong H.; Lee, Sun H.; Kato, Atsushi; Takabayashi, Tetsuji; Kulka, Marianna; Shin, Soon C.; Schleimer, Robert P. (American Journal of Respiratory Cell and Molecular Biology, 2015)
Previous reports suggest that plasminogen activator inhibitor-1 (PAI-1) promotes airway remodeling and that human and mouse mast cells (MCs) are an important source of PAI-1. In the present study we investigated MC–epithelial cell (EC) interactions in the production of PAI-1. We stimulated the human MC line LAD2 with IgE-receptor cross-linking and collected the supernatants. We incubated the human bronchial EC line BEAS-2B with the LAD2 supernatants and measured the level of PAI-1. When the supernatants from IgE-stimulated LAD2 were added to BEAS-2B, there was a significant enhancement of PAI-1 production by BEAS-2B. When we treated the MC supernatants with a transforming growth factor (TGF)-β1 neutralizing antibody, the MC-derived induction of PAI-1 from BEAS-2B was completely abrogated. Although TGF-β1 mRNA was constitutively expressed in resting LAD2, it was not highly induced by IgE-mediated stimulation. Nonetheless, active TGF-β1 protein was significantly increased in LAD2 after IgE-mediated stimulation. Active TGF-β1 produced by primary cultured human MCs was significantly reduced in the presence of a chymase inhibitor, suggesting a role of MC chymase as an activator of latent TGF-β1. This study indicates that stimulation of human MCs by IgE receptor cross-linking triggers activation of TGF-β1, at least in part via chymase, which in turn induces the production of PAI-1 by bronchial ECs. Our data suggest that human MCs may play an important role in airway remodeling in asthma as a direct source of PAI-1 and by activating bronchial ECs to produce further PAI-1 via a TGF-β1–mediated activation pathway.l
Keywords: plasminogen activator inhibitor-1; mast cells, epithelial cells; transforming growth factor-β1; chymase

Critical process temperatures for resistive InGaAsP/InP heterostructures heavily implanted by Fe or Ga ions - Fekecs, André; Chicoine, Martin; Ilahi, Bouraoui; Springthorpe, Anthony J.; Schiettekatte, François; Morris, Denis; Charette, Paul G.; Arès, Richard (Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms, 2015)
We report on critical ion implantation and rapid thermal annealing (RTA) process temperatures that produce resistive Fe- or Ga-implanted InGaAsP/InP heterostructures. Two InGaAsP/InP heterostructure compositions, with band gap wavelengths of 1.3 lm and 1.57 lm, were processed by ion implantation sequences done at multiple MeV energies and high ﬂuence (1015 cm-2). The optimization of the fabrica- tion process was closely related to the implantation temperature which inﬂuences the type of implant-induced defect structures. With hot implantation temperatures, at 373 K and 473 K, X-ray diffraction (XRD) revealed that dynamic defect annealing was strong and prevented the amorphization of the InGaAsP layers. These hot-implanted layers were less resistive and RTA could not optimize them systematically in favor of high resistivity. With cold implantation temperatures, at 83 K and even at 300 K, dynamic annealing was minimized. Damage clusters could form and accumulate to produce resis- tive amorphous-like structures. After recrystallization by RTA, polycrystalline signatures were found on every low-temperature Fe- and Ga-implanted structures. For both ion species, electrical parameters evolved similarly against annealing temperatures, and resistive structures were produced near 500 °C. However, better isolation was obtained with Fe implantation. Differences in sheet resistivities between the two alloy compositions were less than band gap-related effects. These observations, related to damage accumulation and recovery mechanisms, have important implications for the realization ion-implanted resistive layers that can be triggered with near infrared laser pulses and suitable for ultrafast optoelectronics.
Keywords: III–V semiconductors; Ion implantation; Primary and secondary defects; Hall effect; X-ray diffraction

Consequences of many-cell correlations in clocked quantum-dot cellular automata - Taucer, Marco; Karim, Faizal; Walus, Konrad; Wolkow, Robert A. (IEEE Transactions on Nanotechnology, 2015)
Quantum-dot cellular automata (QCA) provides a basis for classical computation without transistors. Many simulations of QCA rely upon the so-called intercellular Hartree approximation (ICHA), which neglects the possibility of entanglement between cells. The ICHA was originally proposed as a solution to the problem of exponential scaling in the computational cost of fully quantum mechanical treatments. However, in some cases, the ICHA predicted errors in QCA operation, and quantum correlations were required for circuits to operate correctly. While quantum correlations can remedy certain problems that present themselves in ICHA calculations, here we present simulations that show that quantum correlations may in fact be problematic in other situations, such as clocked QCA. Small groups of QCA cells are modelled with a Hamiltonian analogous to a quantum mechanical Ising-like spin chain in a transverse field, including the effects of intercellular entanglement completely. When energy relaxation is included in the model, we find that intercellular entanglement changes the qualitative behavior of the system, and new features appear. In clocked QCA, isolated groups of active cells have a tendency to oscillate between polarization states as information propagates. Additionally, energy relaxation tends to bring groups of cells to an unpolarized steady state. This contrasts with the results of previous simulations, which employed the ICHA. The ICHA may in fact be a good approximation in the limit of very low tunneling rates, which can be realized in lithographically defined quantum dots. However, in molecular and atomic implementations of QCA, entanglement will play a greater role. The degree to which intercellular correlations pose a problem for memory, and clocking depends upon implementation-specific details of the interaction of the system with its environment, as well as the system's internal dynamics.
Keywords: nanoscale devices; quantum cellular automata; quantum dots

Composite spectra: XX. 45 Cancri - Griffin, R.E. M.; Griffin, R. F. (Astronomische Nachrichten, 2015)
From accurate radial-velocity measurements covering 11 circuits of the orbit of the composite-spectrum binary 45 Cnc, together with high-resolution spectroscopy spanning nearly 3 circuits, we have (i) isolated cleanly the spectrum of the early-type secondary, (ii) classified the component spectra as G8 III and A3 III, (iii) derived the first double-lined orbit for the system and a mass ratio (M1/M2) of 1.035 ± 0.01, and (iv) extracted physical parameters for the component stars, deriving the masses and (log) luminosities of the G star and A star as 3.11 and 3.00 M⊙, and 2.34 and 2.28 L⊙, respectively, with corresponding uncertainties of ±0.10 M⊙ and ±0.09 L⊙. Since the mass ratio is close to unity, we argue that the more evolved component is unlikely to have been a red giant long enough to have made multiple ascents of the RGB, an argument that is supported somewhat by the rather high eccentricity of the orbit (e = 0.46) and the evolutionary time-scales of the two components, but chiefly by the presence of significant Li I in the spectrum of the cool giant.
Keywords: binaries spectroscopic stars; individual (45 Cnc) techniques; radial velocities techniques

Comparing the observable properties of dwarf galaxies on and off the Andromeda plane - Collins, Michelle L. M.; Martin, Nicolas F.; Rich, R. M.; Ibata, Rodrigo A.; Chapman, Scott C.; Mcconnachie, Alan W.; Ferguson, Annette M.; Irwin, Michael J.; Lewis, Geraint F. (The Astrophysical Journal, 2015)
The thin, extended planes of satellite galaxies detected around both the Milky Way and Andromeda are not a natural prediction of the Λ-cold dark matter paradigm. Galaxies in these distinct planes may have formed and evolved in a different way (e.g., tidally) from their off-plane neighbors. If this were the case, one would expect the on- and off-plane dwarf galaxies in Andromeda to have experienced different evolutionary histories, which should be reflected by the chemistries, dynamics, and star formation histories of the two populations. In this work, we present new, robust kinematic observations for two on-plane M31 dwarf spheroidal galaxies (And XVI and XVII) and compile and compare all available observational metrics for the on- and off-plane dwarfs to search for a signal that would corroborate such a hypothesis. We find that, barring their spatial alignment, the on- and off-plane Andromeda dwarf galaxies are indistinguishable from one another, arguing against vastly different formative and evolutionary histories for these two populations.
Keywords: dark matter-galaxies; dwarf; fundamental parameters; kinematics and dynamics; local group

Collateral circulation formation determines the characteristic profiles of contrast-enhanced MRI in the infarcted myocardium of pigs - Wang, Jian; Xiang, Bo; Lin, Hung-yu; Liu, Hong-yu; Freed, Darren; Arora, Rakesh C.; Tian, Gang-hong (Acta Pharmacologica Sinica, 2015)
Aim: To investigate the relationship between the collateral circulation and contrast-enhanced MR signal change for myocardial infarction (MI) in pigs. Methods: Pigs underwent permanent ligation of two diagonal branches of the left anterior descending artery. First-pass perfusion (FPP) MRI (for detecting myocardial perfusion abnormalities) and delayed enhancement (DE) MRI (for estimating myocardial infarction) using Gd-DTPA were performed at 2 h, 7 d and 4 weeks after the coronary occlusion. Myocardial blood flow (MBF) was evaluated using nonradioactive red-colored microspheres. Histological examination was performed to characterize the infarcts. Results: Acute MI performed at 2 h afterwards was characterized by hypoenhancement in both FPP- and DE-MRI, with small and almost unchanged FPP-signal intensity (SI) and DE-SI due to negligible MBF. Subacute MI detected 7 d afterwards showed small but significantly increaseing FPP-SI, and was visible as a sluggish hyperenhancement in DE-MRI with considerably higher DE-SI compared to the normal myocardium; the MBF approached the half-normal value. Chronic MI detected at 4 weeks afterwards showed increasing FPP-SI comparable to the normal myocardium, and a rapid hyperenhancement in DE-MRI with even higher DE-SI; the MBF was close to the normal value. The MBF was correlated with FPP-SI (r=+0.94, P<0.01) and with the peak DE-SI (r=+0.92, P<0.01) at the three MI stages. Remodeled vessels were observed at intra-infarction and peri-infarction zones during the subacute and chronic periods. Conclusion: Progressive collateral recovery determines the characteristic profiles of contrast-enhanced MRI in acute, subacute and chronic myocardial infarction in pigs. The FPP- and DE-MRI signal profiles not only depend on the loss of tissue viability and enlarged interstitial space, but also on establishing a collateral circulation.
Keywords: myocardial infarction; myocardial reperfusion; contrast media; magnetic resonance imaging; gadolinium DTPA; coronary circulation; pigs; time factors

Cold dust emission from X-ray AGN in the SCUBA-2 Cosmology Legacy Survey: dependence on luminosity, obscuration and AGN activity - Banerji, Manda; Mcmahon, R. G.; Willott, C. J.; Geach, J. E.; Harrison, C. M.; Alaghband-zadeh, S.; Alexander, D. M.; Bourne, N.; Coppin, K. E. K.; Dunlop, J. S.; Farrah, D.; Jarvis, M.; et al. (Monthly Notices of the Royal Astronomical Society, 2015)
We study the 850-μm emission in X-ray-selected active galactic nuclei (AGN) in the ∼2 deg2 COSMOS field using new data from the SCUBA-2 Cosmology Legacy Survey. We find 19 850-μm bright X-ray AGN in a ‘high-sensitivity’ region covering 0.89 deg2 with flux densities of S850 = 4–10 mJy. The 19 AGN span the full range in redshift and hard X-ray luminosity covered by the sample – 0.7 ≲ z ≲ 3.5 and 43.2 ≲ log10(LX) ≲ 45. We report a highly significant stacked 850-μm detection of a hard X-ray flux-limited population of 699 z > 1 X-ray AGN – S850 = 0.71 ± 0.08 mJy. We explore trends in the stacked 850-μm flux densities with redshift, finding no evolution in the average cold dust emission over the redshift range probed. For type 1 AGN, there is no significant correlation between the stacked 850-μm flux and hard X-ray luminosity. However, in type 2 AGN the stacked submillimeter flux is a factor of 2 higher at high luminosities. When averaging over all X-ray luminosities, no significant differences are found in the stacked submillimeter fluxes of type 1 and type 2 AGN as well as AGN separated on the basis of X-ray hardness ratios and optical-to-infrared colours. However, at log10(L2 − 10/erg s−1) > 44.4, dependences in average submillimeter flux on the optical-to-infrared colours become more pronounced. We argue that these high-luminosity AGN represent a transition from a secular to a merger-driven evolutionary phase where the star formation rates and accretion luminosities are more tightly coupled. Stacked AGN 850-μm fluxes are compared to the stacked fluxes of a mass-matched sample of K-band-selected non-AGN galaxies. We find that at 10.5 <log10(M*/M⊙)<11.5, the non-AGN 850-μm fluxes are 1.5–2 times higher than in type 2 AGN of equivalent mass. We suggest these differences are due to the presence of massive dusty, red starburst galaxies in the K-band-selected non-AGN sample, which are not present in optically selected catalogues covering a smaller area.
Keywords: quasars: general; X-rays: galaxies; galaxies: evolution; submillimetre: galaxies

Cold spray copper coatings for used fuel containers - Keech, P.; Vo, P.; Poirier, D.; Legoux, J. G. (35th Annual CNS Conference: Proceedings, 2015)
Recently, the Nuclear Waste Management Organization has been developing copper coatings as a method of protecting steel used fuel containers (UFCs) from corrosion within a deep geological repository. The corrosion barrier design is based on the application of a copper coating bonded directly to the exterior surface of the UFC structural core. Copper coating technologies amendable to supply of pre-coated UFC vessel components and application to the weld zone following UFC closure within the radiological environment have been investigated. Copper cold spray has been assessed for both operations; this paper outlines the research and development to date of this technique.

Clear evidence for the presence of second-generation asymptotic giant branch stars in metal-poor galactic globular clusters - García-Hernández, D. A.; Mészáros, Sz.; Monelli, M.; Cassisi, S.; Stetson, P. B.; Zamora, O.; Shetrone, M.; Lucatello, S. (The Astrophysical Journal, 2015)
Galactic globular clusters (GCs) are known to host multiple stellar populations: a first generation (FG) with a chemical pattern typical of halo field stars and a second generation (SG) enriched in Na and Al and depleted in O and Mg. Both stellar generations are found at different evolutionary stages (e.g., the main-sequence turnoff, the subgiant branch, and the red giant branch (RGB)). The non detection of SG asymptotic giant branch (AGB) stars in several metal-poor ([Fe/H] < −1) GCs suggests that not all SG stars ascend the AGB phase, and that failed AGB stars may be very common in metal-poor GCs. This observation represents a serious problem for stellar evolution and GC formation/evolution theories. We report fourteen SG-AGB stars in four metal-poor GCs (M13, M5, M3, and M2) with different observational properties: horizontal branch (HB) morphology, metallicity, and age. By combining the H-band Al abundances obtained by the Apache Point Observatory Galactic Evolution Experiment survey with ground-based optical photometry, we identify SG Al-rich AGB stars in these four GCs and show that Al-rich RGB/AGB GC stars should be Na-rich. Our observations provide strong support for present, standard stellar models, i.e., without including a strong mass-loss efficiency, for low-mass HB stars. In fact, current empirical evidence is in agreement with the predicted distribution of FG and SG stars during the He-burning stages based on these standard stellar models.

Calibration of radiotherapy ionization chambers using Co-60 is outdated and should be replaced by direct calibration in linear accelerator beams - Ganesan, Ramanathan; Mcewen, Malcolm R.; Orton, Colin G. (Medical Physics, 2015)
Most medical linear accelerators worldwide are calibrated using ionization chambers that are themselves calibrated by a standards laboratory, or secondary standards laboratory, in a Co-60 beam. Because these chambers are actually used to calibrate high-energy x-ray beams, it has been suggested that calibration against Co-60 is outdated and should be replaced by calibration in linear accelerator beams. This is the claim debated in this month’s Point/Counterpoint.

Nutritional evaluation of whole and lipid-extracted biomass of the microalga Scenedesmus sp. AMDD isolated in Saskatchewan, Canada for animal feeds: proximate, amino acid, fatty acid, carotenoid and elemental composition - Tibbetts, Sean M.; Melanson, Ronald J.; Park, Kyoung C.; Banskota, Arjun H.; Stefanova, Roumiana; McGinn, Patrick J. (Current Biotechnology, 2015)
Keywords: Amino acids; carotenoids; composition; fatty acids; microalgae; minerals; proximate

Production of triterpenoid sapogenins in hairy root cultures of Silene vulgaris - Kim, Y. B.; Reed, D. W.; Covello, P. S. (Natural Product Communications, 2015)
Silene vulgaris (Moench) Garcke (Caryophyllaceae) is widely distributed in North America and contains bioactive oleanane-type saponins. In order to investigate in vitro production of triterpenoid saponins, hairy root cultures of S. vulgaris were established by infecting leaf explants with five strains of Agrobacterium rhizogenes (LBA9402, R1000, A4, 13333, and 15834). The A. rhizogenes strain LBA9402 had an infection of 100% frequency and induced the most hairy roots per plant. Methyl jasmonate (MeJA)-induced changes in triterpenoid saponins in S. vulgaris hairy roots were analyzed. Accumulation of segetalic acid and gypsogenic acid after MeJA treatment was 5-and 2-fold higher, respectively, than that of control root. We suggest that hairy root cultures of S. vulgaris could be an important alternative approach to the production of saponins.

Development and validation of Thinopyrum elongatum–expressed molecular markers specific for the long arm of chromosome 7E - Gou, Lulu; Hattori, Jiro; Fedak, George; Balcerzak, Margaret; Sharpe, Andrew; Visendi, Paul; Edwards, David; Tinker, Nicholas; Wei, Yu-Ming; Chen, Guo-Yue; Ouellet, Thérèse (Crop Science, 2015)
The ditelocentric addition line CS-7EL of the spring wheat (Triticum aestivum L.) cultivar Chinese Spring (CS) contains the long arm of the chromosome 7E from Thinopyrum elongatum (CS-7EL), which confers high resistance to Fusarium head blight. It is of great interest to breeders to integrate the resistance locus (loci) from Th. elongatum into commercial wheat varieties. The objectives of this study were to identify candidate genes expressed from the 7EL chromosome of CS-7EL, to develop 7EL-specific molecular markers, and to validate their usefulness for characterizing recombination between one of the group 7 chromosomes of wheat and Th. elongatum. High-throughput sequencing of Fusarium graminearum–infected and control CS and CS-7EL cDNA libraries was performed using RNA-Seq. A stepwise bioinformatics strategy was applied to assemble the sequences obtained from RNA-Seq and to create a conservative list of candidate genes expressed from the foreign chromosome 7EL. Polymerase chain reaction primer pairs were designed and tested for 135 candidate genes. A total of 48 expressed molecular markers specific for the chromosome 7EL were successfully developed. Screening of progenies from two BC1F2 families from the cross CS-7E(7D) × 2*CSph1b showed that these markers are useful for characterizing recombination events between the chromosomes 7D from wheat and 7E from Th. elongatum.

Automated defect and correlation length analysis of block copolymer thin film nanopatterns - Murphy, Jeffrey N.; Harris, Kenneth D.; Buriak, Jillian M. (PLOS ONE, 2015)
Line patterns produced by lamellae- and cylinder-forming block copolymer (BCP) thin films are of widespread interest for their potential to enable nanoscale patterning over large areas. In order for such patterning methods to effectively integrate with current technologies, the resulting patterns need to have low defect densities, and be produced in a short timescale. To understand whether a given polymer or annealing method might potentially meet such challenges, it is necessary to examine the evolution of defects. Unfortunately, few tools are readily available to researchers, particularly those engaged in the synthesis and design of new polymeric systems with the potential for patterning, to measure defects in such line patterns. To this end, we present an image analysis tool, which we have developed and made available, to measure the characteristics of such patterns in an automated fashion. Additionally we apply the tool to six cylinder-forming polystyrene-block-poly(2-vinylpyridine) polymers thermally annealed to explore the relationship between the size of each polymer and measured characteristics including line period, line-width, defect density, line-edge roughness (LER), line-width roughness (LWR), and correlation length. Finally, we explore the line-edge roughness, line-width roughness, defect density, and correlation length as a function of the image area sampled to determine each in a more rigorous fashion.

Atomistic simulations of electronic and optical properties of semiconductor nanostructures - Korkusinski, Marek (Nanoscale Materials and Devices for Electronics, Photonics and Solar Energy, 2015)
We present a tutorial introduction to atomistic calculations of electronic and optical properties of semiconductor nanostructures. The systems of interest, self-assembled quantum dots and colloidal nanocrystals, are composed of thousands to millions of atoms, beyond the applicability of ab initio schemes. Our approach, implemented as the QNANO computational package, consists of (1) atomistic geometry optimization using the valence force-field (VFF) model, (2) calculation of single-particle states confined in a nanostructure using the tight-binding scheme, (3) computation of Coulomb interaction matrix elements using the atomistic wave functions, and (4) calculation of multi-exciton spectra and optical response functions using the configuration interaction approach coupled with Fermi’s Golden Rule. We illustrate this methodology by computing the single-particle states and the exciton fine structure of a self-assembled quantum dot, and by analyzing the multiexciton generation processes in colloidal nanocrystals.

Assessment of donor heart viability during ex vivo heart perfusion - White, Christopher W.; Ambrose, Emma; Müller, Alison; Li, Yun; Le, Hoa; Hiebert, Brett; Arora, Rakesh; Lee, Trevor W.; Dixon, Ian; Tian, Ganghong; Nagendran, Jayan; Hryshko, Larry; et al. (Canadian Journal of Physiology and Pharmacology, 2015)
Ex vivo heart perfusion (EVHP) may facilitate resuscitation of discarded donor hearts and expand the donor pool; however, a reliable means of demonstrating organ viability prior to transplantation is required. Therefore, we sought to identify metabolic and functional parameters that predict myocardial performance during EVHP. To evaluate the parameters over a broad spectrum of organ function, we obtained hearts from 9 normal pigs and 37 donation after circulatory death pigs and perfused them ex vivo. Functional parameters obtained from a left ventricular conductance catheter, oxygen consumption, coronary vascular resistance, and lactate concentration were measured, and linear regression analyses were performed to identify which parameters best correlated with myocardial performance (cardiac index: mL·min⁻¹·g⁻¹). Functional parameters exhibited excellent correlation with myocardial performance and demonstrated high sensitivity and specificity for identifying hearts at risk of poor post-transplant function (ejection fraction: R² = 0.80, sensitivity = 1.00, specificity = 0.85; stroke work: R² = 0.76, sensitivity = 1.00, specificity = 0.77; minimum dP/dt: R² = 0.74, sensitivity = 1.00, specificity = 0.54; tau: R² = 0.51, sensitivity = 1.00, specificity = 0.92), whereas metabolic parameters were limited in their ability to predict myocardial performance (oxygen consumption: R² = 0.28; coronary vascular resistance: R² = 0.20; lactate concentration: R² = 0.02). We concluded that evaluation of functional parameters provides the best assessment of myocardial performance during EVHP, which highlights the need for an EVHP device capable of assessing the donor heart in a physiologic working mode.
Keywords: ex vivo heart perfusion, machine perfusion, heart transplant, organ preservation, organ evaluation, functional assessment, oxygen consumption, lactate metabolism; perfusion cardiaque ex vivo, machine de perfusion, greffe cardiaque, préservation des organes, évaluation des organes, évaluation fonctionnelle, consommation d’oxygène, métabolisme de l’acide lactique

An ultrasoft X-ray flare from 3XMM J152130.7+074916: a tidal disruption event candidate - Lin, Dacheng; Maksym, Peter W.; Irwin, Jimmy A.; Komossa, S.; Webb, Natalie A.; Godet, Olivier; Barret, Didier; Grupe, Dirk; Gwyn, Stephen D. J. (The Astrophysical Journal, 2015)
We report on the discovery of an ultrasoft X-ray transient source, 3XMM J152130.7+074916. It was serendipitously detected in an XMM-Newton observation on 2000 August 23, and its location is consistent with the center of the galaxy SDSS J152130.72+074916.5 (z = 0.17901 and dL = 866 Mpc). The high-quality X-ray spectrum can be fitted with a thermal disk with an apparent inner disk temperature of 0.17 keV and a rest-frame 0.24–11.8 keV unabsorbed luminosity of ~5 × 10⁴³ erg s⁻¹, subject to a fast-moving warm absorber. Short-term variability was also clearly observed, with the spectrum being softer at lower flux. The source was covered but not detected in a Chandra observation on 2000 April 3, a Swift observation on 2005 September 10, and a second XMM-Newton observation on 2014 January 19, implying a large variability (>260) of the X-ray flux. The optical spectrum of the candidate host galaxy, taken ~11 years after the XMM-Newton detection, shows no sign of nuclear activity. This, combined with its transient and ultrasoft properties, leads us to explain the source as tidal disruption of a star by the supermassive black hole in the galactic center. We attribute the fast-moving warm absorber detected in the first XMM-Newton observation to the super-Eddington outflow associated with the event and the short-term variability to a disk instability that caused fast change of the inner disk radius at a constant mass accretion rate.

Amplitude and polarization modulated hyperspectral Stimulated Raman Scattering Microscopy - Andreana, Marco; Houle, Marie-Andrée; Moffatt, Douglas J.; Ridsdale, Andrew; Buettner, Edlef; Légaré, François; Stolow, Albert (Optics Express, 2015)
We present a simple hyperspectral Stimulated Raman Scattering (SRS) microscopy method based on spectral focusing of chirped femtosecond pulses, combined with amplitude (AM) and polarization (PM) modulation. This approach permits the imaging of low concentration components with reduced background signals, combined with good hyperspectral resolution and rapid spectral scanning. We demonstrate, using PM-SRS in a Raman loss configuration, the spectrally resolved detection of deuterated dimethyl sulfoxide (DMSO-d6) at concentrations as low as 0.039 % (5.5 mM). In general, background signals due to cross-phase modulation (XPM), two-photon absorption (TPA) and thermal lensing (TL) can reduce the contrast in SRS microscopy. We show that the nonresonant background signal contributing to the SRS signal is, in our case, largely due to XPM. Polarization modulation of the Stokes beam eliminates the nonresonant XPM background, yielding high quality hyperspectral scans at low analyte concentration. The flexibility of our combined AM-PM approach, together with the use of variable modulation frequency and lock-in phase, should allow for optimization of SRS imaging in more complex samples.

Adsorption of bitumen model compounds on kaolinite in liquid and supercritical carbon dioxide solvents: a study by periodic density functional theory and molecular theory of solvation - Ribeiro Lage, Mateus; Stoyanov, Stanislav R.; de Mesquita Carneiro, José Walkimar; Dabros, Tadek; Kovalenko, Andriy (Energy & Fuels, 2015)
The geometry of phenanthridine, benzothiophene, tetralin, and naphthalene representative of the heterocyclic, naphthenic, and aromatic components of bitumen adsorbed on kaolinite is optimized using density functional theory and periodic boundary conditions in gas phase. These bitumen model compounds preferentially adsorb on the aluminum hydroxide surface of kaolinite with energy decreasing in the order phenanthridine > naphthalene > tetralin ∼ benzothiophene. The adsorption of phenanthridine is strengthened by hydrogen bonding between the pyridinic N atom and an axial hydroxyl group of kaolinite, while the rest of the molecules adsorb through van der Waals interactions. The mechanism of solvation in CO₂ and the effect of liquid and supercritical CO₂ on the adsorption thermodynamics are studied using the three-dimensional reference interaction site model theory with the closure approximation of Kovalenko and Hirata (3D-RISM-KH) molecular theory of solvation at 293–333 K and 10–30 MPa. The CO₂ solvent interacts with the aluminum hydroxide surface of kaolinite by hydrogen bonding, with the pyridinic N atom of phenanthridine by electrostatic interactions, and with the rest of the bitumen model compounds by hydrophobic interactions, as inferred from the 3D site density distribution functions of CO₂. The molecule–kaolinite potentials of mean force in CO₂ show that the adsorption of naphthalene and tetralin on kaolinite is substantially weakened as the pressure is increased and the temperature is decreased. Benzothiophene adsorption is the least sensitive to CO₂ temperature and pressure changes. In liquid CO₂ at 30 MPa and 293 K, the hydrocarbon molecules are weakly adsorbed and can be desorbed by CO₂, while the heterocycles would remain adsorbed, suggesting an approach for extraction of deasphalted bitumen from oil sands. While the most favorable thermodynamic conditions for desorption are in liquid CO₂, the kinetic barrier for desorption is the most sensitive to small changes in the temperature and pressure in supercritical CO₂, indicating that supercritical conditions are important for desorption rate control. These results suggest that the investigated bitumen components can be selectively desorbed from kaolinite by controlling the temperature and pressure of the CO₂ solvent and agree with experimental reports on heavy oil recovery. These insights are valuable for the development of improved techniques for extraction of bitumen from oil sands and deasphalting of bitumen using liquid and supercritical CO₂.

Adipose-derived stem cells from both visceral and subcutaneous fat deposits significantly improve contractile function of infarcted rat hearts - Chi, Chao; Wang, Fei; Xiang, Bo; Deng, Jixian; Liu, Shangdian; Lin, Hung-yu; Natarajan, Kanmani; Li, Gang; Wang, Lei; Wang, Jian; Lin, Francis; Freed, Darren H.; et al. (Cell Transplantation, 2015)
Adipose-derived stem cells (ASCs) from subcutaneous and visceral adipose tissues have been studied individually. No studies have compared their abilities in treatment of heart failure. This study was designed to evaluate whether ASCs from the two sources could provide a long-term improvement of cardiac function in infarcted hearts. Rat subcutaneous and visceral adipose tissues were excised for isolation of ASCs. Morphology, yield, proliferation, surface markers, differentiation, and cytokine secretion of the subcutaneous ASCs (S-ASCs) and visceral ASCs (V-ASCs) were analyzed. Then a rat model of myocardial infarction (MI) was established by a coronary occlusion. Seven days after occlusion, S-ASCs (n = 22), V-ASCs (n = 22), and Dulbecco’s modified Eagle medium (DMEM, n = 20) were injected into the infarct rim, respectively. Cardiac function was then monitored with MRI for up to 6 months. The hearts were then removed for histological assessments. The yield of V-ASCs per gram of the visceral adipose depot was significantly greater than that of S-ASCs in 1 g of the subcutaneous adipose depot. On the other hand, the S-ASCs showed a greater proliferation rate and colony-forming unit relative to the V-ASCs. In addition, the infarcted hearts treated with either S-ASCs or V-ASCs showed a significantly greater left ventricular ejection fraction (LVEF) than those treated with DMEM at 4 weeks and 6 months following the cell/DMEM transplantation. Moreover, the infarct sizes of both S-ASC- and V-ASC-treated hearts were significantly smaller than that in the DMEM-treated hearts. MRI showed the implanted ASCs at the end of 6 months of recovery. Despite the differences in cell yield, proliferation, and colony formation capacity, both S-ASCs and V-ASCs provide a long-lasting improvement of cardiac contractile function in infarcted hearts. We conclude that the subcutaneous and visceral adipose tissues are equally effective cell sources for cell therapy of heart failure.
Keywords: Heart failure; Magnetic resonance imaging; Myocardial infarction; Subcutaneous adipose-derived stem cells; Visceral adipose-derived stem cells

Accurate, fully automated NMR spectral profiling for metabolomics - Ravanbakhsh, Siamak; Liu, Philip; Bjordahl, Trent C.; Mandal, Rupasri; Grant, Jason R.; Wilson, Michael; Eisner, Roman; Sinelnikov, Igor; Hu, Xiaoyu; Luchinat, Claudio; Greiner, Russell; Wishart, David S.; et al. (PLOS ONE, 2015)
Many diseases cause significant changes to the concentrations of small molecules (a.k.a. metabolites) that appear in a person’s biofluids, which means such diseases can often be readily detected from a person’s “metabolic profile"—i.e., the list of concentrations of those metabolites. This information can be extracted from a biofluids Nuclear Magnetic Resonance (NMR) spectrum. However, due to its complexity, NMR spectral profiling has remained manual, resulting in slow, expensive and error-prone procedures that have hindered clinical and industrial adoption of metabolomics via NMR. This paper presents a system, BAYESIL, which can quickly, accurately, and autonomously produce a person’s metabolic profile. Given a 1D ¹H NMR spectrum of a complex biofluid (specifically serum or cerebrospinal fluid), BAYESIL can automatically determine the metabolic profile. This requires first performing several spectral processing steps, then matching the resulting spectrum against a reference compound library, which contains the “signatures” of each relevant metabolite. BAYESIL views spectral matching as an inference problem within a probabilistic graphical model that rapidly approximates the most probable metabolic profile. Our extensive studies on a diverse set of complex mixtures including real biological samples (serum and CSF), defined mixtures and realistic computer generated spectra; involving > 50 compounds, show that BAYESIL can autonomously find the concentration of NMR-detectable metabolites accurately (~ 90% correct identification and ~ 10% quantification error), in less than 5 minutes on a single CPU. These results demonstrate that BAYESIL is the first fully-automatic publicly-accessible system that provides quantitative NMR spectral profiling effectively—with an accuracy on these biofluids that meets or exceeds the performance of trained experts. We anticipate this tool will usher in high-throughput metabolomics and enable a wealth of new applications of NMR in clinical settings. BAYESIL is accessible at http://www.bayesil.ca.
Correction: 29 Jul 2015: Ravanbakhsh S, Liu P, Bjorndahl TC, Mandal R, Grant JR, et al. (2015) Correction: Accurate, Fully-Automated NMR Spectral Profiling for Metabolomics. doi: info:doi/10.1371/journal.pone.0132873

A vaccine approach for the prevention of infections by multidrug-resistant Enterococcus faecium - Kodali, Srinivas; Vinogradov, Evgeny; Lin, Fiona; Khoury, Nancy; Hao, Li; Pavliak, Vilo; Jones, C. Hal; Laverde, Diana; Huebner, Johannes; Jansen, Kathrin U.; Anderson, Annaliesa S.; Donald, Robert G. K. (Journal of Biological Chemistry, 2015)
The incidence of multidrug-resistant Enterococcus faecium hospital infections has been steadily increasing. With the goal of discovering new vaccine antigens, we systematically fractionated and purified four distinct surface carbohydrates from E. faecium endocarditis isolate Tx16, shown previously to be resistant to phagocytosis in the presence of human serum. The two most abundant polysaccharides consist of novel branched heteroglycan repeating units that include signature sugars altruronic acid and legionaminic acid, respectively. A minor high molecular weight polysaccharide component was recognized as the fructose homopolymer levan, and a glucosylated lipoteichoic acid (LTA) was identified in a micellar fraction. The polysaccharides were conjugated to the CRM₁₉₇ carrier protein, and the resulting glycoconjugates were used to immunize rabbits. Rabbit immune sera were evaluated for their ability to kill Tx16 in opsonophagocytic assays and in a mouse passive protection infection model. Although antibodies raised against levan failed to mediate opsonophagocytic killing, the other glycoconjugates induced effective opsonic antibodies, with the altruronic acid-containing polysaccharide antisera showing the greatest opsonophagocytic assay activity. Antibodies directed against either novel heteroglycan or the LTA reduced bacterial load in mouse liver or kidney tissue. To assess antigen prevalence, we screened a diverse collection of blood isolates (n = 101) with antibodies to the polysaccharides. LTA was detected on the surface of 80% of the strains, and antigens recognized by antibodies to the two major heteroglycans were co-expressed on 63% of these clinical isolates. Collectively, these results represent the first steps toward identifying components of a glycoconjugate vaccine to prevent E. faecium infection.
Keywords: antigen; carbohydrate structure; Enterococcus; teichoic acid; vaccine

A route to low temperature growth of single crystal GaN on sapphire - Motamedi, Pouyan; Dalili, Neda; Cadien, Kenneth (Journal of Materials Chemistry C, 2015)
Gallium nitride (GaN) is considered one of most important semiconductor materials for the 21st century due to its combination of properties (high breakdown field, high electron saturation velocity and mobility, and good thermal conductivity) that make it suitable for high power, high frequency and high temperature applications. In this paper we demonstrate a possible route for the deposition of single crystal GaN on sapphire at 275 °C using plasma enhanced atomic layer deposition. TEM images and electron diffraction show that the first 5 nm of growth is epitaxial then transitions to 3D growth. The films have a preferential (002) growth direction, and a small in-plane and out-of-plane misorientation. The refractive index, extinction coefficient, and optical band gap are on par with those of GaN films grown at higher temperatures. The films are p-type with a carrier concentration of 1.68 × 10¹⁸ cm⁻³ and hole mobility of 110 cm² V⁻¹ s⁻¹.

A robust algorithm for optimizing protein structures with NMR chemical shifts - Berjanskii, Mark; Arndt, David; Liang, Yongjie; Wishart, David S. (Journal of Biomolecular NMR, 2015)
Over the past decade, a number of methods have been developed to determine the approximate structure of proteins using minimal NMR experimental information such as chemical shifts alone, sparse NOEs alone or a combination of comparative modeling data and chemical shifts. However, there have been relatively few methods that allow these approximate models to be substantively refined or improved using the available NMR chemical shift data. Here, we present a novel method, called Chemical Shift driven Genetic Algorithm for biased Molecular Dynamics (CS-GAMDy), for the robust optimization of protein structures using experimental NMR chemical shifts. The method incorporates knowledge-based scoring functions and structural information derived from NMR chemical shifts via a unique combination of multi-objective MD biasing, a genetic algorithm, and the widely used XPLOR molecular modelling language. Using this approach, we demonstrate that CS-GAMDy is able to refine and/or fold models that are as much as 10 Å (RMSD) away from the correct structure using only NMR chemical shift data. CS-GAMDy is also able to refine of a wide range of approximate or mildly erroneous protein structures to more closely match the known/correct structure and the known/correct chemical shifts. We believe CS-GAMDy will allow protein models generated by sparse restraint or chemical-shift-only methods to achieve sufficiently high quality to be considered fully refined and “PDB worthy”. The CS-GAMDy algorithm is explained in detail and its performance is compared over a range of refinement scenarios with several commonly used protein structure refinement protocols. The program has been designed to be easily installed and easily used and is available at http://www.gamdy.ca.

A radial velocity and light curve study of pulsations and binarity in proto-planetary nebulae - Hrivnak, B. J.; Lu, W.; Van de Steene, G.; Van Winckel, H.; Sperauskas, J.; Bohlender, D.; Lagadec, E.; Millour, F.; Lanz, T. (The Physics of Evolved Stars: A Conference Dedicated to the Memory of Olivier Chesneau, 2015)
We have investigated pulsations and searched for binarity in 7 bright proto-planetary nebulae. All are found to pulsate, with dominant periods of 39−132 days. However, no strong evidence of binarity is found in any of them. This implies that any binary companion must have either a very long period (>30 yr) or low mass (<0.2 Msun). This appears to rule out Roche lobe overflow as a contribution to the shaping of the surrounding nebula.

A novel method for extracting the linewidth broadening factor of semiconductor diode lasers - Wang, Cheng; Schires, Kevin; Osinski, Marek; Poole, Philip; Grillot, Frederic (Frontiers in Optics 2015, 2015)
A novel experimental technique for extracting the linewidth broadening factor of semiconductor lasers is proposed. This approach is applicable to any types of diode lasers, both below- and above-threshold, and is insensitive to thermal effects.

A heuristic automatic clustering method based on hierarchical clustering - LaPlante, François; Belacel, Nabil; Kardouchi, Mustapha (Agents and Artificial Intelligence: 6th International Conference, ICAART 2014, Angers, France, March 6-8, 2014, Revised Selected Papers, 2015)
We propose a clustering method which produces valid results while automatically determining an optimal number of clusters. The proposed method achieves these results with minimal user input, of which none pertains to a number of clusters. Our method’s effectiveness in clustering, including its ability to produce valid results on data sets presenting nested or interlocking shapes, is demonstrated and compared with cluster validity analysis to other methods to which a known optimal number of clusters is provided, and to other automatic clustering methods. Depending on the particularities of the data set used, our method has produced results which are roughly equivalent or better than those of the compared methods.
Keywords: Data-mining; Automatic clustering; Unsupervised learning

A chemical trompe-l’oeil: no iron spread in the globular cluster N22 - Mucciarelli, A.; Lapenna, E.; Massari, D.; Pancino, E.; Stetson, P. B.; Ferraro, F. R.; Lanzoni, B.; Lardo, C. (The Astrophysical Journal, 2015)
We present the analysis of high-resolution spectra obtained with UVES and UVES-FLAMES at the Very Large Telescope of 17 giants in the globular cluster (GC) M22, a stellar system suspected to have an intrinsic spread in iron abundance. We find that when surface gravities are derived spectroscopically (in order to obtain the same iron abundance from Fe I and Fe II lines) the [Fe/H] distribution spans ∼0.5 dex, according to previous analyses. However, the gravities obtained in this way correspond to unrealistically low stellar masses (0.1–0.5 M) for most of the surveyed giants. Instead, when photometric gravities are adopted, the [Fe II/H] distribution shows no evidence of spread, in variance with the [Fe I/H] distribution. This difference has been recently observed in other clusters and could be due to non-local thermodynamical equilibrium effects driven by over-ionization mechanisms that mainly affect the neutral species (thus providing lower [Fe I/H]), but leave [Fe II/H] unaltered. We confirm that the s-process elements show significant star-to-star variations and their abundances appear to be correlated with the difference between [Fe I/H] and [Fe II/H]. This puzzling finding suggests that the peculiar chemical composition of some cluster stars may be related to effects able to spuriously decrease [Fe I/H]. We conclude that M22 is a GC with no evidence of intrinsic iron spread, ruling out that it has retained the supernovae ejecta in its gravitational potential well.
Keywords: stars: abundances; techniques: spectroscopic

60 years of research on free radical physical organic chemistry - Ingold, K. U. (The Foundations of Physical Organic Chemistry: Fifty Years of the James Flack Norris Award, 2015)
In this Chapter the reader is conducted on a gentle cruise through the green and pleasant land of mechanistic radical chemistry. My love of chemistry arrived with a bang (potassium metal + water) and I was already enamored by “how fast?”. These two loves combined at the NRC as I helped to convert radical chemistry from a tarry, black art, into clean, practical, useful, predictable and comprehensible chemistry.

The evolution of biomedical vibrational spectroscopy : a personal perspective - Mantsch, Henry Horst (Biomedical Spectroscopy and Imaging, 2015)

The golden years of spectroscopy at NRC in Ottawa : a personal perspective - Mantsch, Henry Horst (Journal of the Spectroscopical Society of Japan, 2015)

Biocomposites and bioblends based on engineering thermoplastics for automotive applications - Mihai, Mihaela (2015)

Biocomposites and bioblends based on engineering thermoplastics for automotive applications - Mihai, Mihaela (2015)

Lower-cost, ligther and greener polypropylene-based biocomposites for construction applications - Mihai, Mihaela (2015)
This presentation discloses the viability of the formulation, processing, and performance of advanced biocomposites and bioblends based on polypropylene (PP) designed for industrial manufacturing. The PP was compounded with three different types of cellulosic fibers, in a bioblends with polylactide (PLA) as bio-sourced polymer, and in PP/PLA/cellulosic biocomposites. These biomaterials were characterized in terms of morphology, mechanical and thermal properties. Tensile strength, tensile modulus, and the heat deflection temperature of the bioblends and the biocomposites presented at least equivalent values comparing with virgin PP and with PP current industrial grades. The extruded biocomposites, foamed in injection molding process, presented similar properties as the unfoamed and reference counterparts while being up to 25 wt.% lighter, up to 50% less expensive, and up to 50% greener.

Biocomposites and bioblends based on engineering thermoplastics for automotive applications - Mihai, Mihaela (ANTEC 2015: proceedings of the Technical Conference and Exhibition Orlando, Florida, USA March 23-25, 2015, 2015)
This paper presents innovative solutions concerning the utilization of engineering polymers in bioblends and biocomposites designated for automotive applications. The studied biomaterials have lower-cost, lower-weight, and at least same performance comparing with the current engineering thermoplastics used in automotive parts. Polyamide (PA6) and acrylonitrile-butadiene-styrene (ABS) were formulated using different types and concentrations of cellulosics, polylactic acid (PLA) as a bio-sourced polymer, and in a combination of cellulosics and PLA. These biomaterials were characterized in terms of morphology, mechanical properties, and heat deflection temperature. The extruded biocomposites, foamed in injection molding process, presented similar properties as the unfoamed and reference counterparts while being around 25-30% greener, lighter and less expensive.

Lower-cost, ligther and greener polypropylene-based biocomposites for industrial applications - Mihai, Mihaela (ANTEC 2015: proceedings of the Technical Conference and Exhibition Orlando, Florida, USA March 23-25, 2015, 2015)
This paper discloses the viability of the formulation, processing, and performance of advanced biocomposites and bioblends based on polypropylene (PP) designed for industrial manufacturing. The PP was compounded with three different types of cellulosic fibers, in a bioblends with polylactide (PLA) as bio-sourced polymer, and in PP/PLA/cellulosic biocomposites. These biomaterials were characterized in terms of morphology, mechanical and thermal properties. Tensile strength, tensile modulus, and the heat deflection temperature of the bioblends and the biocomposites presented at least equivalent values comparing with virgin PP and with PP current industrial grades. The extruded biocomposites, foamed in injection molding process, presented similar properties as the unfoamed and reference counterparts while being up to 25 wt.% lighter, up to 50% less expensive, and up to 50% greener.

Neutron diffraction investigation of phase compositions in as received and modified Zr–2·5Nb pressure tube materials - Fluke, A. I.; Fong, R. W. L.; Flacau, R. (Materials Science & Technology Conference and Exhibition 2013 (MS&T'13), 2015)
Zr-2.5Nb alloy is used for the pressure tubes in CANDU® reactor fuel channels. Three phases (α, β, and ω) of zirconium are known to exist in Zr-2.5Nb alloy pressure tube materials. An as received pressure tube is composed mainly of α-phase and approximately 8% β-phase material. In the last step of production, the pressure tube is given a steam-autoclave treatment (i.e., thermal ageing at 400°C for 24 h). This treatment results in decomposing the β-phase into an Nb-enriched β-phase and a metastable ω-phase material. In this present experiment, as received pressure tube materials were modified by high-temperature annealing and thermal ageing treatments. This paper presents a neutron diffraction investigation into the phase compositions in the modified materials at room temperature using the C-2 high-resolution neutron powder diffractometer at the Canadian Neutron Beam Centre.
Keywords: Neutron diffraction; Phase composition; Zr-2.5Nb pressure tube

Detecting outbreaks in time-series data with RecentMax - Carter, Dave; Martin, Joel D. (Online Journal of Public Health Informatics, 2015)
The RecentMax algorithm seeks to detect typical outbreaks of transmissible disease (particularly influenza-like illness) in time-series data better than existing algorithms like CDC EARS C1/C2/C3.
Keywords: aberration detection; algorithm; outbreak detection; surveillance; situational awareness

Preventing the spread of Alzheimer's disease neuropathology: a role for calcilytics? - Chiarini, Anna; Gardenal, Emanuela; Whitfield, James F; Chakravarthy, Balu; Armato, Ubaldo; Pra, Ilaria Dal (Current Pharmaceutical Biotechnology, 2015)
The "amyloid cascade hypothesis" posits that an extracellular build-up of amyloid-β oligomers (Aβ-os) and polymers (fibrils) subsequently inducing toxic hyperphosphorylated (p)-Tau oligomers (p-Tau-os) and neurofibrillary tangles starts the sporadic late-onset Alzheimer's disease (LOAD) in the aged lateral entorhinal cortex. Conversely, mutated genes cause a diffuse cerebral Aβs/Aβ-os overproduction promoting early-onset familiar AD (EOFAD). Surplus exogenous Aβ-os exert toxic actions at several levels. They reach the nuclei of human astrocyte-neurons teams (ANTs) to enhance the transcription of Aβ precursor protein (APP) and β-secretase/BACE1 genes. The overexpressed APP and BACE1 proteins act in concert with γ-secretase to overproduce endogenous Aβs/Aβ-os, of which a few enter the nuclei to upkeep Aβs overproduction, while the rest gather in the cytoplasm, damage mitochondria, and are oversecreted. Simultaneously, extracellular Aβ-os bind the ANTs' calcium-sensing receptors (CaSRs) activating signalings that hinder the proteolysis and hence favor the surplus hoarding/secretion of Aβs/Aβ-os. Overreleased Aβ-os spread, reach growing numbers of adjacent ANTs to recruit them to overproduce/oversecrete further Aβ-os amounts via the just mentioned mechanisms. Alongside, Aβ•CaSR signalings elicit a noxious overproduction/overrelease of nitric oxide (NO) and vascular endothelial growth factor (VEGF)-A from ANTs' astrocytes. While astrocytes survive the toxic onslaught, neurons die. Thus, AD progression is driven by ceaselessly self-sustaining neurotoxic cycles, which engender first Aβ-os and later p-Tau-os that cooperatively destroy increasingly wider cognition-related cortical areas. Notably, a highly selective allosteric CaSR antagonist (calcilytic), like NPS 2143, does preserve human cortical postnatal HCN-1A neurons viability notwithstanding the presence of exogenous Aβ-os by suppressing the otherwise elicited oversecretion and spread of newly synthesized Aβ-os. Therefore, if given at minimal cognitive impairment or earlier stages, calcilytics could halt AD progression and preserve the patients' cortical neurons, cognitive abilities, and eventually life.

Development and evaluation of hybrid seat cushions for helicopter aircrew vibration mitigation - Chen, Yong; Wickramasinghe, Viresh; Zimcik, David (Journal of Intelligent Material Systems and Structures, 2015)
This paper investigates the use of novel energy absorbing materials to reduce vibration transmitted through helicopter pilot seat cushions. A type of engineered material known as the Hybrid Air Cushioning System (HACS) was integrated into the design of helicopter seat cushions in addition to conventional foam materials. The prototype seat cushions were preliminarily evaluated as the bottom seat cushion on a Bell-412 non-armoured pilot seat through mechanical shaker tests. The promising cushion designs were further evaluated on a Bell-412 helicopter through extensive flight tests and aircrew configurations. The pilot whole-body vibration levels were assessed in accordance with ISO 2613-1:1997 standard. The flight test results demonstrated that the prototype cushions were able to reduce significantly the pilot whole-body vibration. Therefore, the integration of HACS with Bell-412 seat cushion can serve as a low cost solution to mitigate the vibration levels transmitted to helicopter pilots.
Keywords: Control; Autonomic structures; Optimization

National Energy Code of Canada for Buildings 2015 - National Research Council Canada. Construction (National Research Council Canada. Construction, 2015)
The National Energy Code of Canada for Buildings 2015 (NECB), published by NRC and developed by the Canadian Commission on Building and Fire Codes in collaboration with Natural Resources Canada (NRCan), sets out technical requirements for the energy efficient design and construction of new buildings. The NECB 2015 includes over ninety changes improving the overall energy performance of buildings over the 2011 edition. The 2015 edition broadens the scope to address all service water and introduces requirements for pressure-sensing controls which reduce the short-cycling of booster pumps when demand for water is low. Other HVAC and service water changes include equipment efficiency regulation of heat rejection equipment, such as cooling towers and (standalone) condensers, heating performance requirements for gas-fired outdoor packaged units and updated minimum pipe and duct insulation requirements. Lighting power density values and controls have been updated with more stringent lighting allowances and additional requirements for common spaces and exterior applications. The performance path modeling rules and guidance have been updated to reflect the changes to the prescriptive path as well as more current typical use profiles of buildings. Application of the code for residential and small buildings has also been clarified. The NECB 2015 has been re-organized to consolidate relevant information. Each Part now contains the Prescriptive Requirements, followed by the Attribution Table and related (appendix) Notes. The NECB is a must-have for building designers, energy consultants and subcontractors, construction professionals and regulatory officials.

National Plumbing Code of Canada 2015 - National Research Council Canada. Construction (National Research Council Canada. Construction, 2015)
The National Plumbing Code of Canada 2015 (NPC), published by NRC and developed by the Canadian Commission on Building and Fire Codes, sets out technical provisions for the design and installation of new plumbing systems and also applies to the extension, alteration, renewal and repair of existing plumbing systems. Twenty-eight technical changes are incorporated in the NPC 2015, increasing design and material choices and introducing water-use efficiency for plumbing fixtures, supply fittings and shower heads. The new water-efficiency requirements aim to reduce water usage in all buildings, regardless of water source. The Environment objective, already in the National Energy Code for Buildings and the National Building Code, was also introduced into the NPC 2015 to address “excessive use of water.” The NPC 2015 has been re-organized to consolidate relevant information. Each Part now contains the Prescriptive Requirements, followed by the Attribution Table and related (appendix) Notes. The NPC 2015 is an essential resource for anyone who designs or installs plumbing systems.

National Fire Code of Canada 2015 - National Research Council Canada. Construction (National Research Council Canada. Construction, 2015)
The National Fire Code of Canada 2015 (NFC), published by NRC and developed by the Canadian Commission on Building and Fire Codes, sets out the technical provisions regulating activities related to the construction, use or demolition of buildings and facilities, the condition of specific elements of buildings and facilities, and the design or construction of specific elements of facilities related to certain hazards as well as the protection measures for the current or intended use of buildings. There are 77 technical changes in the NFC. The most significant changes relate the construction of six-storey buildings using combustible construction. As a result, eight additional protection measures have been added to address fire hazards during construction when fire protection features are not yet in place. Following mid-rise combustible construction, the second most significant change in the NFC 2015 is the introduction of the classification system used by Workplace Hazardous Materials Information System (WHMIS) to define dangerous goods. These changes reflect harmonization of the dangerous goods classification system with the Globally Harmonized System (GHS) recently adopted in Canada. The NFC 2015 has been re-organized to consolidate relevant information. Each Part now contains the Prescriptive Requirements, followed by the Attribution Table and related (appendix) Notes.

National Building Code of Canada 2015 - National Research Council Canada. Construction (National Research Council Canada. Construction, 2015)
The National Building Code of Canada 2015 (NBC), published by NRC and developed by the Canadian Commission on Building and Fire Codes, sets out technical provisions for the design and construction of new buildings. It also applies to the alteration, change of use and demolition of existing buildings. Over 360 technical changes have been incorporated in this new edition. Thirty-four changes to the NBC and eight changes to the National Fire Code 2015 (NFC) now permit construction of six-storey buildings using combustible construction. As a result, additional protection measures have been added to address the risk of injury due to fire and structural collapse in the finished building as well as during construction. Special attention was also given to protect buildings during construction when fire protection features are not yet in place. The many changes in the 2015 edition also include updates to accessibility and associated design requirements in Part 3, aligning Code requirements with the current knowledge on accessibility. Hazard values for seismic design in Part 4 and Appendix C have been updated and design exemptions withdrawn so that all buildings in Canada will now be designed for earthquake forces regardless of the level of hazard. Apparent Sound Transmission Class (ASTC) is introduced in Part 5 to assess compliance with minimum airborne sound requirements between dwelling units. There are also significant changes to Part 9, housing and small buildings, with over half impacting stairs, ramps, handrails and guards. A key change in the NBC 2015 increases the run dimension of a step inside the house, a change which aims to reduce fall incidences and aligns NBC requirements with international codes. The NBC 2015 is divided into two Volumes and has been re-organized to consolidate relevant information. Each Part now contains the Prescriptive Requirements, followed by the related (appendix) Notes. Parts 1 to 8 are found in Volume 1 and Part 9 now forms Volume 2. The NBC 2015 complements the National Fire Code of Canada 2015, and both are indispensable for officials, educators and construction professionals.

Synthetic oversampling for advanced radioactive threat detection - Bellinger, Colin; Japkowicz, Nathalie; Drummond, Christopher (2015 IEEE 14th International Conference on Machine Learning and Applications (ICMLA), 2015)
Gamma-ray spectral classification requires the automatic identification of a large background class and a small minority class composed of instances that may pose a risk to humans and the environment. Accurate classification of such instances is required in a variety of domains, spanning event and port security to national monitoring for failures at industrial nuclear facilities. This work proposes a novel form of synthetic oversampling based on artificial neural network architecture and empirically demonstrates that it is superior to the state-of-the-art in synthetic oversampling on the target domain. In particular, we utilize gamma-ray spectral data collected for security purposes at the Vancouver 2010 winter Olympics and on a node of Health Canada's national monitoring networks.
Keywords: Radioactive waste; Gamma-ray spectra; Synthetic oversampling; Autoencoders; Class imbalance

Quantification of mutation-derived bias for alternate mating functionalities of the Saccharomyces cerevisiae Ste2p pheromone receptor - Choudhary, Pooja; Loewen, Michele C. (Journal of Biochemistry, 2015)
Although well documented for mammalian G-protein-coupled receptors, alternate functionalities and associated alternate signalling remain to be unequivocally established for the Saccharomyces cerevisiae pheromone Ste2p receptor. Here, evidence supporting alternate functionalities for Ste2p is re-evaluated, extended and quantified. In particular, strong mating and constitutive signalling mutations, focusing on residues S254, P258 and S259 in TM6 of Ste2p, are stacked and investigated in terms of their effects on classical G-protein-mediated signal transduction associated with cell cycle arrest, and alternatively, their impact on downstream mating projection and zygote formation events. In relative dose response experiments, accounting for systemic and observational bias, mutational-derived functional differences were observed, validating the S254L-derived bias for downstream mating responses and highlighting complex relationships between TM6-mutation derived constitutive signalling and ligand-induced functionalities. Mechanistically, localization studies suggest that alterations to receptor trafficking may contribute to mutational bias, in addition to expected receptor conformational stabilization effects. Overall, these results extend previous observations and quantify the contributions of Ste2p variants to mediating cell cycle arrest versus downstream mating functionalities.
Keywords: Alternate functionalities; G-protein-coupled receptor; Pheromone mating; Site-directed mutagenesis; Yeast

Mechanochemical formation of a 1:1 C₆₀: tert-butylcalix[4]azulene supramolecular complex: solid-state NMR and DFT computational studies - Georghiou, Paris E.; Schneider, Celine; Shamov, Grigory; Lash, Timothy D.; Rahman, Shofiur; Giddings, D. Sabrina (Supramolecular Chemistry, 2015)
Solid-state NMR data are presented to clearly support the formation of a 1:1 supramolecular complex between C₆₀ and the tetra-tert-butylated analogue of calix[4]azulene by a simple mechanochemical hand-grinding of host and guest in a mortar and pestle. The experimental results are supported by a DFT study.
Keywords: Solid-state NMR; DFT; Host-guest; Supramolecular; Mechanochemistry; C₆₀; Calixazulenes

Profiling kinase activity during hepatitis C virus replication using a wortmannin probe - Desrochers, Geneviève F.; Sherratt, Allison R.; Blais, David R.; Nasheri, Neda; Ning, Zhibin; Figeys, Daniel; Goto, Natalie K.; Pezacki, John Paul (ACS Infectious Diseases, 2015)
To complete its life cycle, the hepatitis C virus (HCV) induces changes to numerous aspects of its host cell. As kinases act as regulators of many pathways utilized by HCV, they are likely enzyme targets for virally induced inhibition or activation. Herein, we used activity-based protein profiling (ABPP), which allows for the identification of active enzymes in complex protein samples and the quantification of their activity, to identify kinases that displayed differential activity in HCV-expressing cells. We utilized an ABPP probe, wortmannin-yne, based on the kinase inhibitor wortmannin, which contains a pendant alkyne group for bioconjugation using bioorthogonal chemistry. We observed changes in the activity of kinases involved in the mitogen-activated protein kinase pathway, apoptosis pathways, and cell cycle control. These results establish changes to the active kinome, as reported by wortmannin-yne, in the proteome of human hepatoma cells actively replicating HCV. The observed changes include kinase activity that affect viral entry, replication, assembly, and secretion, implying that HCV is regulating the pathways that it uses for its life cycle through modulation of the active kinome.
Keywords: Activity-based protein profiling; Hepatitis C; Host-virus interactions; Kinase probes; MAPK pathway; Wortmannin

Soraphen A: a probe for investigating the role of de novo lipogenesis during viral infection - Singaravelu, Ragunath; Desrochers, Geneviève F.; Srinivasan, Prashanth; O’Hara, Shifawn; Lyn, Rodney K.; Müller, Rolf; Jones, Daniel M.; Russell, Rodney S.; Pezacki, John Paul (ACS Infectious Diseases, 2015)
Many viruses including the hepatitis C virus (HCV) induce changes to the infected host cell metabolism that include the up-regulation of lipogenesis to create a favorable environment for the virus to propagate. The enzyme acetyl-CoA carboxylase (ACC) polymerizes to form a supramolecular complex that catalyzes the rate-limiting step of de novo lipogenesis. The small molecule natural product Soraphen A (SorA) acts as a nanomolar inhibitor of acetyl-CoA carboxylase activity through disruption of the formation of long highly active ACC polymers from less active ACC dimers. We have shown that SorA inhibits HCV replication in HCV cell culture models expressing subgenomic and full-length replicons (IC₅₀ = 5 nM) as well as a cell culture adapted virus. Using coherent anti-Stokes Raman scattering (CARS) microscopy, we have shown that SorA lowers the total cellular lipid volume in hepatoma cells, consistent with a reduction in de novo lipogenesis. Furthermore, SorA treatment was found to depolymerize the ACC complexes into less active dimers. Taken together, our results suggest that SorA treatment reverses HCV-induced lipid accumulation and demonstrate that SorA is a valuable probe to study the roles of ACC polymerization and enzymatic activity in viral pathogenesis.
Keywords: CARS; Coherent anti-Stokes Raman spectroscopy; HCV; Hepatitis C virus; Lipids

Combination of LII and extinction measurements for determination of soot volume fraction and estimation of soot maturity in non-premixed laminar flames - Leschowski, M.; Thomson, K. A.; Snelling, D. R.; Schulz, C.; Smallwood, G. J. (Applied Physics B: Lasers and Optics, 2015)
The measurement of soot and soot precursors is important for understanding the formation of soot particles in flames. In this paper, we use the difference between laserinduced incandescence (LII) and two-dimensional extinction measurements to assess the contribution of soot precursors to the extinction measurement. LII measurements are performed with a high spatial resolution of 100 μm to determine the soot volume fraction (fV) in a laminar ethylene/ air non-premixed flame at the standard Gülder conditions. While LII is specific to mature soot only, the extinction data represent attenuation due to mature and young soot (absorption and elastic scattering) and also absorption by soot precursors. The difference between the two measurements indicates the contribution of soot precursors and allows a determination of the maturity of soot. This is important knowledge for those using extinction techniques to measure soot concentration, as the contribution from soot precursors may lead to an overestimation of the mature soot concentration. Further, regions with high soot-precursor concentrations, which lead to soot formation, can be identified.

Variation of molybdenum isotopes in molybdenite from porphyry and vein Mo deposits in the Gangdese metallogenic belt, Tibetan plateau and its implications - Wang, Yong; Zhou, Lian; Gao, Shan; Li, Jian-Wei; Hu, Zhi-Fang; Yang, Lu; Hu, Zhao-Chu (Mineralium Deposita, 2015)
We present Mo isotopic ratios of molybdenite from five porphyry molybdenum deposits (Chagele, Sharang, Jiru, Qulong, and Zhuonuo) and one quartz-molybdenite vein-type deposit (Jigongcun) along the Gangdese metallogenic belt in the Tibetan Plateau. These deposits represent a sequence of consecutive events of the India-Asia collision at different periods. Additional molybdenite samples from the Henderson Mo deposit (USA), the oceanic subduction-related El Teniente (Chile), and Bingham (USA) porphyry Cu-(Mo) deposits were analyzed for better understanding the controls on the Mo isotope systematics of molybdenite. The results show that molybdenite from Sharang, Jiru, Qulong, and Zhuonuo deposits have similar δ⁹⁷Mo (∼0 ‰), in agreement with the values of the Henderson Mo deposit (−0.10 ‰). In contrast, samples from the Changle and Jigongcun deposit have δ⁹⁷Mo of 0.85 ‰ to 0.88 ‰ and −0.48 %, respectively. Molybdenite from the El Teniente and Bingham deposits yields intermediate δ⁹⁷Mo of 0.27 and 0.46 ‰, respectively. The Mo isotopes, combined with Nd isotope data of the ore-bearing porphyries, indicate that source of the ore-related magmas has fundamental effects on the Mo isotopic compositions of molybdenite. Our study indicates that molybdenite related to crustal-, and mantle-derived magmas has positive or negative δ⁹⁷Mo values, respectively, whereas molybdenite from porphyries formed by crust-mantle mixing has δ⁹⁷Mo close to 0 ‰. It is concluded that the Mo isotope composition in the porphyry system is a huge source signature, without relation to the tectonic setting under which the porphyry deposits formed.
Keywords: Molybdenite; Molybdenum isotope; Gangdese; Tibetan Plateau

Boron nitride nanotube composites: production and properties - Jakubinek, M. B.; Martinez-Rubi, Y.; Kim, K. S.; Guan, J.; Homenick, C.; Kingston, C. T.; Simard, B.; Ashrafi, B.; O'Neill, K.; Rahmat, M.; Johnston, A.; Derdouri, S. (CAMX, The Composites and Advanced Materials Expo, 2015, 2015)
Boron nitride nanotubes (BNNTs) exhibit a range of properties that are as impressive as those of carbon nanotubes (CNTs), including comparable mechanical properties, but with different multifunctional advantages such as considerably higher thermal stability, polarizability, wide band gap, and high neutron absorption capability. These characteristics make BNNTs attractive for the fabrication of enhanced composites including for mechanical reinforcement, heat dissipation, high temperature composites, neutron shielding, and piezoelectric composites among other possibilities. Recent advances in large-scale production of BNNTs have resolved the supply limitation for BNNT nanocomposites research and the development of BNNT-enhanced composites is now poised to accelerate rapidly. Here we highlight the production of large-scale, composites-relevant quantities of BNNTs based on a scalable RF plasma torch method and present examples from our work on both bulk BNNT-polymer composites and nanocomposites based on BNNT sheets.

Battery life impact of vehicle-to-grid application of electric vehicles - Ribberink, Hajo; Darcovich, Ken; Pincet, Fleurine (28th International Electric Vehicle Symposium and Exhibition 2015, 2015)
In recent years, electric vehicles (EVs) have successfully been gaining a market foothold in many countries around the world. The number of plug-in vehicles is forecast to grow steadily to over 10 million vehicles before 2024. In many countries, concerns about the environmental impact of fossil fuel-based electricity production have resulted in a shift towards more sustainable power generation technologies. Electricity production from solar and wind, however, is intrinsically unsteady. Costly provisions therefore need to be made within electricity grids to ensure back-up power is available on demand. The power stored in the batteries of the growing fleets of EVs could potentially be a cost effective alternative to conventional spinning reserves through Vehicle-to-Grid (V2G) applications. Concerns arise over the use of EVs for V2G purposes; as such use is expected to negatively impact EV battery life. Data on additional battery degradation due to V2G is presently quite scarce. A detailed simulation model was developed to explore the various processes that impact EV battery life. The model was used in a simulation study to determine the battery life impact of various V2G scenarios in comparison to a base case of regular driving and charging. Scenarios with different driving styles, various charge levels and different V2G events were evaluated. The impact of fast charging of EVs on battery life was also considered. The study concluded that aggressive driving and fast charging have a great impact on EV battery life. A similar level of battery degradation was found for intense participation in V2G services, fully discharging the battery on a daily basis. However, less intense use of the EV battery can still provide useful V2G services with acceptable battery degradation. Manufacturers of EVs are therefore encouraged to implement V2G capability in their EVs.
Keywords: Electric vehicle; Battery life; Vehicle-to-Grid; Simulation

Thermal gradient behaviour of TBCs subjected to a laser gradient test rig: simulating an air-to-air combat flight - Lima, Rogerio S.; Marple, Basil R.; Marcoux, P. (Proceedings of the International Thermal Spray Conference, 2015)
A computer-controlled laser test rig (using a CO2 laser) offers an interesting alternative to traditional flame-based thermal gradient rigs in evaluating thermal barrier coatings (TBCs). The temperature gradient between the top and back surfaces of a TBC system can be controlled based on the laser power and a forced air back-face cooling system, enabling the temperature history of complete aircraft missions to be simulated. An air plasma spray (APS) deposited TBC was tested and, based on experimental data available in the literature, the temperature gradients across the TBC system (ZrO2-Y2O3 YSZ top coat / CoNiCrAlY bond coat / Inconel 625 substrate) and their respective frequencies during air-to- Air combat missions of fighter jets were replicated. The missions included (i) idle/taxi on the runway, (ii) take-off and climbing, (iii) cruise trajectory to rendezvous zone, (iv) air-to- Air combat maneuvering, (v) cruise trajectory back to runway and (vi) idle/taxi after landing. The results show that the TBC thermal gradient experimental data in turbine engines can be replicated in the laser gradient rig, leading to an important tool to better engineer TBCs.

Structural and conductive adhesives enabled by single-walled carbon nanotubes - Ashrafi, Behnam; Jakubinek, Michael B.; Martinez-Rubi, Yadienka; Zhang, Yunfa; Kingston, Christopher T.; Johnston, Andrew; Simard, Benoit (Proceedings of the American Society for Composites Thirtieth Technical Conference, 2015)
Adhesives are increasingly being employed as alternatives to mechanical fasteners in aerospace and other engineering applications. While structural adhesives are commonly employed on aircraft, electrical bonding continues to be achieved with rivets as the existing electrically conductive adhesives suffer from low strength due to the high loading (typically 25-30 vol.%) of conductive filler particles. Carbon nanotubes are one of the more attractive candidates for development of multifunctional adhesives for both structural and conductive bonding because of their high conductivity and high aspect ratio. The latter enables creation of conductive pathways at much lower loading (< 1 vol.%) and, therefore, conductivity can be achieved without degrading mechanical performance. Single-walled carbon nanotubes (SWCNTs) offer the highest intrinsic conductivity and aspect ratio as well as the lowest percolation threshold, which is associated with higher conductivity at a fixed loading. In this work, SWCNTs were incorporated at low loading (0.5 - 3 wt%) into an unfilled aerospace-grade epoxy system, to impart electrical conductivity while maintaining structural bonding capability. Mechanical properties of composite-tocomposite joints were evaluated using ASTM-based lap shear and peel tests. Bulk electrical conductivities over 1 S/m were achieved without degrading the joint structural performance in the selected test methods. The mechanical and electrical performance of a SWCNT-modified epoxy adhesive was also studied for aluminumto- aluminum bonding. It was found that the integration of 1 wt% SWCNTs can considerably improve joint Mode I fracture toughness by ~ 35% due to mechanisms such as crack bridging. The electrical resistance of the bondline was also consistent with the electrical conductivity of SWCNT-modified adhesive films (~10-3 S/m), but slightly lower than the bulk electrical conductivity measured on thicker samples.

A study of mechanical behavior of polycarbonate nanocomposites using molded disk specimens - Zhang, Yunfa; Martinez-Rubi, Yadienka; Derdouri, Salim; Simard, Benoit; Yang, Qi; Johnston, Andrew (Proceedings of the American Society for Composites Thirtieth Technical Conference, 2015)
This paper presents an experimental study of the mechanical behavior of polycarbonate modified with boron nitride nanotubes, an emerging type of nanotube with extraordinary mechanical performance that is optically transparent. Using molded disk specimens with the same geometry, equibiaxial flexural, supported punch shear, and low-speed impact tests were performed to determine the flexural stiffness, punch shear strength, and impact performance of nanocomposites. Polycarbonate nanocomposite samples with different nanotube content (up to 1 wt%) were investigated. Within the scope of the study, mechanical properties of the nanocomposite samples exhibited only very limited variations depending on the reinforcement content; however, noticeable improvement in flexural stiffness and dissipated energy in punch shear were observed, with the low-speed impact performance remaining essentially unchanged. In addition, the complex failure behavior in punch shear was studied with the aid of scanning electron microscopy and the preliminary results are reported.

Carbon nanotube based network heaters for composite adhesive bonding - Jakubinek, Michael B.; Rahmat, Meysam; Ashrafi, Behnam; Genest, Marc; Simard, Benoit; Johnston, Andrew.; Li, Chun (Proceedings of the American Society for Composites Thirtieth Technical Conference, 2015)
Adhesive bonding and bonded repair of metallic and composite aircraft structures have been used as effective methods for manufacturing and for restoring structural integrity of aircraft structures. Adhesive bonding requires the application of heat in order to cure the adhesive and complete the bonding operation; however, conventional heating methods are subject to several drawbacks and might be undesirable, particularly in cases involving repair of new, exotic aerospace materials. The motivation of this work is to develop a novel, cost-effective bonding method and apparatus using a network of carbon nanotubes (CNTs) to provide heating with uniform bondline temperature, rapid temperature response, and minimal energy cost by producing heat directly at the bondline. Such a solution is achieved through integrating a paper-like CNT network (i.e., buckypaper sheet) within film adhesive. This self-heated adhesive layer is applied in the same was as conventional film adhesive and cured through application of a voltage (or current) across the CNT network to cause Joule heating. The approach gives excellent temperature uniformity, fast response, and low energy consumption among other advantages.

Centre of excellence for structural full-scale testing 2015 - Paraschivoiu, D.; Beltempo, A.; Hind, S.; Rogers, J.; Yanishevsky, M.; Rutledge, B. (CAMX, The Composites and Advanced Materials Expo, 2015, 2015)
For many years, some in the aerospace industry believed that analysis and modeling would eventually replace testing, including: coupons with joints and design details, sub-components and components, and Structural Full-Scale Tests (SFST). As the aeronautical industry entered the composite materials and hybrid structures era, best illustrated by the development of all composite fuselage aircraft, there was also an additional expectation that much qualification and certification could be achieved by modeling and simulation. Though analyses and analytical modeling can help define the requirements and procedures for testing these composite/hybrid structures; however, due to the complexity of understanding and predicting their performance during all service conditions, modeling and simulation are not mature enough to entirely replace testing itself. Certification agencies throughout the globe still view testing as the gold standard for proof of structural compliance as outlined in existing regulations [1] to [6]. As a result, the demand for testing has never been stronger. Static, Fatigue and Residual Strength tests are and will continue to be performed to support certification of aircraft by Airworthiness Authorities. Furthermore, in several cases, in addition to certification testing, proof of concept and life extension tests are also being carried out by Original Equipment Manufacturers (OEMs). OEMs have found that they cannot avoid structural full-scale testing, even for legacy aircraft. Certification is viewed as a strategic capability by the major OEMs. Most of these, such as Embraer, Boeing, Lockheed and Gulfstream, continue to perform their structural tests in-house. Airbus on the other hand, has outsourced most, if not all, its structural full-scale testing to specialized firms in Europe, such as IABG, IMA and DGA. More recently Bombardier has initiated a similar approach to that of Airbus. Other than OEMs, there are few facilities in North America that can provide the entire range of testing services including flight testing, spectrum derivation, instrumentation and certification testing, complete with state-of-the-art nondestructive evaluation (NDE). NRC, in collaboration with its partners, is planning to expand its SFST capabilities in the near future with its Centre of Excellence (CoE) to accommodate the increase in demand for Life Extension structural testing, typically for military applications [7], Proof of Concept demonstration testing and Certification testing with OEMs. At the same time NRC (National Research Council) is committed to improving testing technologies. Efforts are being undertaken to offer clients the opportunity to perform a wider range of tests, better, faster and at lower cost.

Why the horizon is important for airborne sense and avoid applications - Minwalla, C.; Ellis, K. (ISPRS - International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2015)
The utility of the horizon for airborne sense-and-avoid (ABSAA) applications is explored in this work. The horizon is a feature boundary across which an airborne scene can be separated into surface and sky and serves as a salient, heading-independent feature that may be mapped into an electro-optical sensor. The virtual horizon as established in this paper represents the horizon that would be seen assuming a featureless earth model and infinite visibility and is distinct from the apparent horizon in an imaging sensor or the pilot’s eye. For level flight, non-maneuvering collision course trajectories, it is expected that targets of interest will appear in close proximity to this virtual horizon. This paper presents a model for establishing the virtual horizon and its projection into a camera reference plane as part of the sensing element in an ABSAA system. Evaluation of the model was performed on a benchmark dataset of airborne collision geometries flown at the National Research Council (NRC) using the Cerberus camera array. The model was compared against ground truth flight test data collected using high accuracy inertial navigation systems aboard aircraft on several ’near-miss’ intercepts. The paper establishes the concept of ’virtual horizon proximity’ (VHP), the minimum distance from a detected target and the virtual horizon, and investigates the utility of using this metric as a means of rejecting false positive detections, and increasing range at first detection through the use of a region of interest (ROI) mask centred on the virtual horizon. The use of this horizon-centred ROI was shown to increase the range at first detection by an average factor of two, and was shown to reduce false positives for six popular feature detector algorithms applied across the suite of flight test imagery.
Keywords: SAA; ABSAA; UAS; Horizon model; Horizon proximity; Region-of-interest; Feature detector

Design and performance of plasmonic lenses optimized for 325 GHz - Naylor, David A.; Heggie, Tanner J.; Gom, Brad G.; Trimboli, Grace; Bordatchev, Evgueni V. (2015 40th International Conference on Infrared, Millimeter, and Terahertz waves (IRMMW-THz), 2015)
Imaging applications at terahertz (THz) frequencies are limited to relatively low spatial resolution due to the effects of diffraction. A subwavelength aperture can be used to improve the resolution at the cost of low transmission. Plasmonic lenses in the form of bullseye structures, consisting of a single subwavelength circular aperture surrounded by concentric periodic corrugations, have shown enhanced transmission and beam confinement. In this paper, we discuss the design and performance of plasmonic lenses optimized for transmission at 325 GHz.

Femtosecond laser induced optical fiber Bragg gratings (FBGs) for harsh environment sensing applications - Mihailov, S. J.; Grobnic, D.; Walker, R. B.; Lu, P.; Ding, H. (2015 IEEE Photonics Conference (IPC), 2015)
FBGs made with femtosecond lasers have shown promise for sensing in extreme environments like high temperature, pressure or ionizing radiation. This presentation will give a review of some of the more recent developments.

Experimental and computational investigations of flapping wings for Nano-air-vehicles - Yuan, Weixing; Lee, Richard; Levasseur, Luc (Engineering Applications of Computational Fluid Mechanics, 2015)
This paper presents the finalized results of a recent project which investigated the aeromechanical aspects of aerodynamic force generation by making use of flapping wings. Flapping-wing experiments using small wings have some unique challenges posed by the low force level (∼1 N) and the cyclic wing motion. A tailored experimental water tunnel facility was developed for flapping wings operating at high reduced frequency with a complex two-dimensional and a three-dimensional motion profile. The experimental capability is demonstrated by the test cases of two-dimensional and three-dimensional flapping wings, designed according to a proposed notional nano-air-vehicle at a hovering condition. The features of the water tunnel, the geometric and kinematic parameters of the airfoils/wings, and the setups of the motion rigs for each test case are described. Measured forces and particle image velocimetry data are analyzed and cross-checked with the numerical results obtained from a code developed in-house. The comparisons of the experimental and numerical results show that the established experimental approach obtained a quantitatively reliable solution for the development of flapping wings and can serve for numerical validation of engineering tool developments. The investigation reveals that the kinematics of a rigid airfoil or wing is the dominant influence in the generation of aerodynamic forces, while the cross-section profile plays a secondary role. An asymmetric-wake-in-time is found behind the single airfoils and wings, which contributes to an asymmetry behavior of the resulting aerodynamic forces. In addition to the findings of single airfoils and wings, further analyses of the numerical and experimental results confirm that wing-wing interaction through the clap-fling mechanism can intensify the generation of the thrust force while accompanied by a small reduction in the overall propulsion efficiency.
Keywords: Flapping wing; Low Reynolds number flow; Micro air vehicle; Water tunnel; Computational fluid dynamics

Kinetics of methane hydrate replacement with carbon dioxide and nitrogen gas mixture using in situ NMR spectroscopy - Cha, Minjun; Shin, Kyuchul; Lee, Huen; Moudrakovski, Igor L.; Ripmeester, John A.; Seo, Yutaek (Environmental Science & Technology, 2015)
In this study, the kinetics of methane replacement with carbon dioxide and nitrogen gas in methane gas hydrate prepared in porous silica gel matrices has been studied by in situ ¹H and ¹³C NMR spectroscopy. The replacement process was monitored by in situ ¹H NMR spectra, where about 42 mol % of the methane in the hydrate cages was replaced in 65 h. Large amounts of free water were not observed during the replacement process, indicating a spontaneous replacement reaction upon exposing methane hydrate to carbon dioxide and nitrogen gas mixture. From in situ ¹³C NMR spectra, we confirmed that the replacement ratio was slightly higher in small cages, but due to the composition of structure I hydrate, the amount of methane evolved from the large cages was larger than that of the small cages. Compositional analysis of vapor and hydrate phases was also carried out after the replacement reaction ceased. Notably, the composition changes in hydrate phases after the replacement reaction would be affected by the difference in the chemical potential between the vapor phase and hydrate surface rather than a pore size effect. These results suggest that the replacement technique provides methane recovery as well as stabilization of the resulting carbon dioxide hydrate phase without melting.

Caffeic acid and its derivatives as inhibitors of lipoxygenases in different organisms - Cuperlovic-Culf, Miroslava; Touaibia, Mohamed (Caffeic Acid: Biological Properties, Structure and Health Effects, 2015)
Hydroxycinnamic acids including caffeic acid are major phenolic secondary metabolites in plants involved in growth and metabolism regulation as well as response to pathogen challenges. Caffeic acid is broadly distributed in several species of plant kingdom and is widely consumed in human diet. Caffeic acid and derivatives have been extensively studied revealing a broad spectrum of biological activities in different species. In addition to the antioxidant activity of caffeic acid, this molecule has been indicated as an inhibitor of number of proteins conserved across distinct species. This chapter will focus on the effect of caffeic acid and several targeted derivatives on lipoxygenases. Lipoxygenases (LOXs) are enzymes involved in peroxidation of lipids to bioactive lipid mediators such as leukotriene. LOXs are significant and highly conserved enzymes in eukaryotes with known function in metabolism of plant, fungal and mammalian cells. LOX inhibitory potential of caffeic acid has therefore major relevance to public health as well as agriculture and environment. This chapter is aimed at summarizing the current knowledge of the inhibition of LOXs by caffeic acid and its application as well as potential in human health and agriculture. In addition to reviewing literature on LOX inhibition we will provide analysis of the LOX protein conservation in highly distinct species and present computational illustration of pan-eukaryotic LOX inhibition by caffeic acid and its derivatives. © 2015 by Nova Science Publishers, Inc. All rights reserved.

Comparison of the detailed and simplified methods to calculate the apparent sound transmission class for the proposed 2015 National Building Code of Canada - Zeitler, Berndt; Mahn, Jeffrey; Quirt, David (44th International Congress and Exposition on Noise Control Engineering (Internoise 2015): Implementing Noise Control Technology, 2015)
A new approach to the control of sound transmission is among the changes proposed in the 2015 edition of the National Building Code of Canada (NBCC). The design objective is changing from a minimum Sound Transmission Class (STC) for the wall or floor/ceiling assembly separating adjacent units to a requirement for the Apparent Sound Transmission Class (ASTC) which includes flanking sound transmission. One of the compliance paths in the proposed 2015 NBCC allows for detailed and simplified calculations according to ISO 15712. In support of the proposed 2015 NBCC, the National Research Council Canada has developed a number of guides for the calculation of the direct and flanking STC data for different construction types including concrete and concrete block walls with and without linings. As part of the development of the guides, it was found that the use of the simplified calculations could result in higher values for the direct and flanking STC values compared to the detailed calculations. The higher values put builders at risk of designs which have lower ASTC values than predicted. An alternative method for calculating the direct and flanking STC data for concrete block walls with linings has been proposed which is shown to reduce the risk of overestimating the direct and flanking STC data for the examples considered in this study.

Inflection generation as discriminative string transduction - Nicolai, Garrett; Cherry, Colin; Kondrak, Grzegorz (Conference of the North American Chapter of the Association for Computational Linguistics: Human Language Technologies (NAACL HLT 2015), 2015)
We approach the task of morphological inflection generation as discriminative string transduction. Our supervised system learns to generate word-forms from lemmas accompanied by morphological tags, and refines them by referring to the other forms within a paradigm. Results of experiments on six diverse languages with varying amounts of training data demonstrate that our approach improves the state of the art in terms of predicting inflected word-forms.

Analysis of vessel besetting over the Gulf of St. Lawrence and the Strait of Belle Isle, Winter 2013-2014 - Kubat, Ivana; Sayed, Mohamed; Lamontagne, Philippe (23rd International Conference on Port and Ocean Engineering under Arctic Conditions (POAC 2015), 2015)
The threat of compression of ice covers to shipping has been the subject of several recent studies. Research projects in Europe and Canada have examined factors that trigger ice convergence and approaches for predicting the risk of besetting of vessels, among other aspects of the problem. This paper examines incidents of vessel besetting due to ice compression which took place over the eastern Gulf of St. Lawrence and the Strait of Belle Isle. The paper lists reported besetting incidents over these locations during the ice season of 2013-2014. The information includes the date, time, location, prevailing wind, and observations of ambient ice conditions. The distance to the nearest shoreline was also given. Analysis of certain incidents was done by hindcasting ice drift and deformation. The results give estimates of ice pressures (ice compression) and ridge ice thickness at besetting. For incidents that were apparently triggered by onshore wind and took place over the eastern Gulf of St. Lawrence, ice pressures ranged from 24.0 kN/m to 25.7 kN/m and the ridge thickness values were from 8.2 m to 10.5 m. These values are in agreement with previous estimates obtained for besetting incidents over other parts of the Gulf of St. Lawrence and Frobisher Bay. An analysis of incidents that corresponded to wind acting nearly parallel to the shoreline in the Strait of Belle Isle produced lower values of ice pressures and ridge thickness. However, the strain rates were particularly high, which evidently caused convergence of the ice cover and prompted the besetting incidents.

Direct airborne and impact sound insulation of steel-framed floors for mid-rise constructions - Hoeller, Christoph; Zeitler, Berndt; Sabourin, Ivan (44th International Congress and Exposition on Noise Control Engineering (Internoise 2015): Implementing Noise Control Technology, 2015)
In a recent study at the National Research Council of Canada, the direct airborne and impact sound insulation of steel-framed floors were investigated. This study forms one part of a project focusing on the direct and flanking sound transmission in lightweight steel-framed buildings for mid-rise constructions. Mid-rise constructions (4 to 6 stories) using lightweight steel framing are becoming more and more common in North America. The floors investigated in this study consisted of 38 mm lightweight gypsum concrete on a corrugated steel deck, fastened to steel joists with a gypsum board ceiling. The parameters investigated included the joist depth and the configuration of the ceiling. In addition, the influence of various floor coverings was examined. The airborne sound transmission loss was measured according to ASTM E90, and the light impact sound insulation was measured according to ASTM E492. The results are presented and discussed.

Light for life: emerging opportunities and challenges for using light to influence well-being - Veitch, J. A. (Information Display, 2015)
Both lighting technology and our understanding of the relationship between light and human health have advanced rapidly in recent years. The latter needs to be carefully evaluated, particularly as longer-lasting light sources enter the market.
Keywords: hardware; human health; lighting quality; lighting technology; wellbeing

A hybrid approach for prediction of sheet formation in twin sheet extrusion blow molding process - Benrabah, Z.; Mir, H. (72nd Annual Technical Conference of the Society of Plastics Engineers (ANTEC 2014): The Plastics Conference, 2015)
The sheet formation is the most critical stage in the Twin Sheet Extrusion Blow Molding (TSEBM) process, as the final dimensions of the blow molded part is directly related the initial extrudate sheet shape. A better understanding of the sheet swell/sag phenomena will ultimately lead to improvements in the prediction of the extrusion process, such as the optimization of both die design and processing parameters. Consequently, the development of a robust 2.5D numerical simulation tool of sheet formation in TSEBM process remains a challenging task, in order to achieve a prescribed accuracy with an optimal computational time, especially when it comes to industrial production rates featuring high Weissenberg numbers. The numerical validation, in terms of length and width distribution of the extruded sheet, is performed by comparing predicted solutions to experimental measurements obtained with different flow rates, die gap opening and extrusion time.

Foaming polymer blends of polystyrene and lignin - Gendron, Richard; Li, Hongbo; Champagne, Michel F. (12th International Conference on Foam Materials & Technology, 2015)
Lignin is the second most abundant natural polymer on earth after cellulose. Very large amounts of lignin are generated as a by-product of the pulp and paper and bioethanol industries. Numerous studies on lignin-based composites have been conducted. However, lignin complex and heterogeneous structure, in addition to chemistry are highly dependent on lignin sources and processing conditions, have mostly resulted in unsatisfactory results. Nevertheless, sheet extrusion foaming of blends of polystyrene and lignin has been performed and promising low-density foam results have been obtained. This presentation will focus on the morphology of such blends and their impact on the processing conditions and resulting foam structure. Preliminary results on the application of lignin for expandable polystyrene (EPS) will also be presented.

Microfluidic system for capture and release of listeria monocytogenes using functionalized core-shell magnetic nanoparticles - Malic, L.; Zhang, X.; Brassard, D.; Clime, L.; Daoud, J.; Boutin, A.; Luebbert, C.; Barrere, V.; Bidawid, S.; Corneau, N.; Farber, J.; Veres, T. (18th International Conference on Miniaturized Systems for Chemistry and Life Sciences (MicroTAS 2014), 2015)
An integrated polymer-based microfluidic device for capture and release of bacteria using antibodyspecific silica-shell-iron-oxide-core nanoparticles is presented. The magnetic capture-release chip (MCR) relies on a dense array of Nickel-coated high-aspect ratio pillars and a microfluidic channel network for sample delivery, capture, wash and recovery. The unique characteristic of the MCR lies in the ability to control the magnetic field distribution within the chamber without consequent remanence, thus allowing sample capture and release. The capture efficiency was validated using plate-culture method and the minimum detectable concentration for short 15 min bacteria-nanoparticle incubation corresponded to 10 cfu/ml for Listeria monocytogenes.
Keywords: Magnetic capture; Bacteria; Polymer microfluidic device; Array of pillars

Nonclassical correlations between terahertz-bandwidth photons mediated by rotational quanta in hydrogen molecules - Bustard, Philip J.; Erskine, Jennifer; England, Duncan G.; Nunn, Josh; Hockett, Paul; Lausten, Rune; Spanner, Michael; Sussman, Benjamin J. (Optics Letters, 2015)
Quantum photonics offers much promise for the development of new technologies. The ability to control the interaction of light and matter at the level of single quantum excitations is a prerequisite for the construction of potentially powerful devices. Here we use the rotational levels of a room temperature ensemble of hydrogen molecules to couple two distinct optical modes at the single photon level using femtosecond pulses with 2 THz bandwidth. We observe photon correlations that violate a Cauchy–Schwarz inequality, thereby verifying the creation of a nonclassical state. This work demonstrates the rich potential of molecules for use in ultrafast quantum photonic devices.

Development of pressure-sensitive paints for flexible parachutes - Mébarki, Youssef; Lascombes, Baptiste; Ferracina, Luca; Underwood, John C. (23rd AIAA Aerodynamic Decelerator Systems Technology Conference, 2015)
The pressure-sensitive paint technique (PSP) is used to measure the model surface pressures in wind tunnel testing. Generally, the models are rigid and their motion/deformation under the effect of the flowfield is small and easily corrected. The present study addresses the problem of surface pressure measurements on flexible parachute models as part of the European Space Agency MREP programme activity designed to identify parachutes for future missions. The paper explores the application of the lifetime method using double shutter cameras, the PCO.1600 (PCO) and Zyla (Andor), with a commercial PSP formulation (Unifib from ISSI) tested on solid samples. The effects of the acquisition settings on the noise level is analyzed. In addition, the effect of the paints and primers on the stiffness of polyester parachutes is presented. An original PSP formulation, combining a fluorinated polymer and a silicone rubber was developed to minimize the impact on the fabric stiffness. The noise levels on a single acquisition (no averaging) were too large for a low-speed wind tunnel testing and strategies to reduce the noise levels are proposed in the paper.

Spontaneous emission and reflectivity measurements for the characterization of facet-coatings of semiconductor lasers - Chang, Shoude; Liu, Jiaren; Lu, Zhenguo; Poitras, Daniel; Barrios, Pedro; Poole, Philip; Janz, Siegfried (2015 Photonics North, 2015)
A new method for measuring the spontaneous emissions and spectral reflectivity of the facet coating of ridge lasers is described and demonstrated. We present results of spectrally-controlled coated quantum-dot laser waveguides.
Keywords: Laser coating; Spontaneous emission; Reflectivity; Laser characterization

Comparison of ¹⁴C liquid scintillation counting at NIST and NRC Canada - Bergeron, Denis E.; Galea, Raphael; Laureano-Pérez, Lizbeth; Zimmerman, Brian E. (Applied Radiation and Isotopes, 2015)
An informal bilateral comparison of ¹⁴C liquid scintillation (LS) counting at the National Research Council of Canada (NRC) and the National Institute of Standards and Technology (NIST) has been completed. Two solutions, one containing ¹⁴C-labeled sodium benzoate and one containing ¹⁴C-labeled n-hexadecane, were measured at both laboratories. Despite observed LS cocktail instabilities, the two laboratories achieved accord in their standardizations of both solutions. At the conclusion of the comparison, the beta spectrum used for efficiency calculations was identified as inadequate and the data were reanalyzed with different inputs, improving accord.
Keywords: Efficiency tracing; CNET; Triple-to-double coincidence ratio; TDCR; ¹⁴C; Bilateral comparison; Benzoate; Hexadecane; Cocktail instability; Beta spectrum shape; Shape factor

Hydrodynamic and morphologic modeling of alternative design scenarios for Shippagan Gully, New Brunswick, Canada - Provan, Mitchel; Nistor, Ioan; Cornett, Andrew; Drouin, Alain (Coastal Engineering Proceedings, 2015)
This paper describes a comprehensive study comprising field measurements and numerical modeling of hydrodynamic and sedimentary processes undertaken to help assess alternative engineering measures for promoting and maintaining a stable and safe navigation channel through a dynamic tidal inlet. Shippagan Gully is a dynamic tidal inlet located on the Gulf of St-Lawrence near Le Goulet, New Brunswick, Canada. The tidal lagoon transects the Acadian Peninsula, hence the flows through the inlet are controlled by the tidal phase lag between the two open boundaries. Due to the nature of this phase lag, the ebb flows through Shippagan Gully, which regularly exceed 2 m/s, are typically twice as strong as the flood flows. As a consequence of this imbalance, the hydrodynamic and sedimentary processes at the inlet, and the morphologic features produced by these processes, are strongly dominated by the ebb flows. Over the past decades, shipping activities through Shippagan Gully have been threatened due to sediment deposition along the east side of the inlet which has caused the channel to narrow and shift westward. The objective of the present study was to develop an improved numerical model of the hydrodynamic and sedimentary processes at Shippahan Gully, and then apply the model to assess different engineering interventions for stabilizing the inlet and improving navigation safety.
Keywords: Tidal inlet; sediment transport; Morphological modeling; Coastal structures

Demonstration of the CPMA-electrometer system for calibrating black carbon particulate mass instruments - Dickau, Matthew; Johnson, Tyle J.; Thomson, Kevin; Smallwood, Greg; Olfert, Jason S. (Aerosol Science and Technology, 2015)
In an effort to improve regulations for particulate emissions from aircraft engines, the Aircraft Exhaust Emissions Measurement Committee, SAE E-31, is investigating instruments to measure black carbon mass concentration in real time. The current candidates are a laser-induced incandescence instrument (LII 300) and a photo-acoustic Micro-Soot Sensor (MSS). However, both of these instruments use indirect techniques, measuring parameters other than the actual mass of particulate in the exhaust, and therefore require calibration. Previously, it has been shown that a centrifugal particle mass analyzer (CPMA) can be used in conjunction with an aerosol electrometer to traceably generate an aerosol with known mass concentration. This system can be used to rapidly calibrate particle mass instruments (on the order of minutes), without the time-consuming process of filter sampling, which is often used for calibration and prone to sampling artifacts. Here, we demonstrate the feasibility of the CPMA-electrometer system for calibrating two LII 300 instruments and two MSS instruments, which were calibrated to the NIOSH 5040 standard. The correlations between the CPMA-electrometer system and the challenge instrument were highly linear for both the LII and the MSS, and agreed well with the previous calibration. All four instruments were found to correlate with the CPMA-electrometer system with R2 values of 0.993 to 0.999. The standard uncertainty in the CPMA-electrometer system averaged 4.3% and was as low as 2.6% for some measurements. With a simple improvement to the aerosol electrometer, we estimate this average uncertainty would be less than 3%. This lower uncertainty and much higher speed of measurement support the use of the CPMA-electrometer system as a mass measurement calibration method for black carbon instruments.

A bifunctional air electrode catalyzed by lead ruthenate for Li-Air batteries - Yuan, Xiao-Zi; Toupin, Mathieu; Qu, Wei; Laforgue, Alexis; Fahlman, Jason; Jiang, Max (ECS Transactions, 2015)
The performance of a catalyst enforced commercially available gas diffusion layer (GDL) electrode was evaluated at different discharge rates and depths in non-aqueous Li-O₂ batteries. The lead ruthenate (PbRuO) powder with a pyrochlore structure was employed as the catalyst. The lead ruthenate pyrochlore was prepared using a direct soft template method and characterized by X-ray diffraction (XRD), nitrogen physisorption techniques and transmission electron microscopy (TEM). The charge/discharge capabilities of the PbRuO/Ketjenblack (KB) composite were studied in tetraethyleneglycol dimethyl ether (TEGDME) containing 1M lithium triflate. The results show that PbRuO/KB can enhance the cell performance at high charge/discharge rates. Moreover, at a current density of 0.1mA/cm² it significantly increases the cell cyclability. With a cut-off capacity of 1000 mAh/g (PbRuO/KB only) the cell reached 100 cycles. As such, lead ruthenate has the potential to be used as an efficient bifunctional electrocatalyst for non-aqueous Li-O₂ batteries.

Renewing the radiopharmaceutical accuracy check service for Canadian radionuclide calibrators - Galea, R.; Gameil, K. (Applied Radiation and Isotopes, 2015)
From 1986 to 2000, a fraction of the Canadian nuclear medicine community participated in a service offered by the National Research Council (NRC) of Canada to check the accuracy of administered doses of radiopharmaceuticals. The NRC renewed this service in recent years with a revalidation and reviving of the Secondary Standard Ionizing Radiation Chamber System (SSIRCS). The NRC conducted mock services for ⁹⁹ mTc, in varying geometries (syringes and serum vials), on two NRC commercial radionuclide calibrators, and at a nuclear medicine department in Canada. These tests showed the measured doses to be within 10% of the prepared standard but in some cases were sufficiently different from unity to warrant specific geometry factors to be derived.
Keywords: Quality assurance; Radionuclide ionization chambers; Hospital radionuclide calibrators

Progress towards a 3D numerical simulation of ice accretion on a swept wing using the morphogenetic approach - Szilder, Krzysztof; Lozowski, Edward (SAE Technical Papers, 2015)
We have developed an original, three-dimensional icing modelling capability, called the “morphogenetic” approach, based on a discrete formulation and simulation of ice formation physics. Morphogenetic icing modelling improves on existing ice accretion models, in that it is capable of predicting simultaneous rime and glaze ice accretions and ice accretions with variable density and complex geometries. The objective of this paper is to show preliminary results of simulating complex three-dimensional features such as lobster tails and rime feathers forming on a swept wing. The results are encouraging. They show that the morphogenetic approach can predict realistically both the overall size and detailed structure of the ice accretion forming on a swept wing. Under cold ambient conditions, when drops freeze instantly upon impingement, the numerical ice structure has voids, which reduce its density. At warmer air temperatures, when drops do not freeze on impingement, larger cavities form, due to the shadowing process, along with the development of morphological features called lobster tails. Ice feathers also appear. As far as we know, no other numerical model can simulate these complex, three-dimensional ice structures that form on a swept wing.
Keywords: Simulation; Modeling; Icing; Ice detection; Aerodynamics

Aircraft in situ validation of hydrometeors and icing conditions inferred by ground-based NEXRAD polarimetric radar - Williams, Earle; Donovan, Michael F.; Smalley, David J.; Hallowell, Robert G.; Griffin, Elaine P.; Hood, Kenta T.; Bennett, Betty J.; Wolde, Mengistu; Korolev, Alexei V. (SAE Technical Papers, 2015)
MIT Lincoln Laboratory is tasked by the U.S. Federal Aviation Administration to investigate the use of the NEXRAD polarimetric radars* for the remote sensing of icing conditions hazardous to aircraft. A critical aspect of the investigation concerns validation that has relied upon commercial airline icing pilot reports and a dedicated campaign of in situ flights in winter storms. During the month of February in 2012 and 2013, the Convair-580 aircraft operated by the National Research Council of Canada was used for in situ validation of snowstorm characteristics under simultaneous observation by NEXRAD radars in Cleveland, Ohio and Buffalo, New York. The most anisotropic and easily distinguished winter targets to dual pol radar are ice crystals. Accordingly, laboratory diffusion chamber measurements in a tightly-controlled parameter space of temperature and humidity provide the linkage between shape and the expectation for the presence/absence of water saturation conditions necessary for icing hazard in situ. In agreement with the laboratory measurements pertaining to dendritic and hexagonal flat plate crystals, the aircraft measurements have verified the presence of supercooled water in mainly low concentrations coincident with regions showing layered anomalies of positive differential reflectivity (ZDR) by ground-based radar, otherwise known as +ZDR ‘bright bands’. Extreme values of ZDR (up to +8 dB) have also been found to be coincident with hexagonal flat plate crystals and intermittent supercooled water, also consistent with laboratory measurements. The icing conditions found with the anisotropic description are considered non-classical (condensation/collision-coalescence) and require the ascent of air and availability of ice nuclei. A modest ascent rate (<1 m/s) is needed for preservation of the anisotropic ice crystal shapes, making them identifiable to dual-pol radar. In the other limit of strong ascent (several m/s and greater), a vigorous riming process is present leading to graupel and hail, and with attendant radar reflectivity of 30 dBZ and greater. These rimed hydrometeors are also readily verified by dual pol hydrometeor classification and in situ aircraft measurements. For the intermediate level of ascent speed, snow can become rimed, diluting its anisotropy, and presents a challenge to unambiguous detection of an icing condition by dual pol radar. This challenge is under current study.
Keywords: Radar; Hazards; Icing; Ice detection

The GLACIER icing facility-lessons learnt in five years of operation - Macleod, James; Clarke, Michael; Marsh, Doug (SAE Technical Papers, 2015)
The Global Aerospace Centre for Icing and Environmental Research Inc. (GLACIER) facility is located in Thompson, Manitoba, Canada. This facility provides icing certification tests for large gas turbine engines, as well as performance, endurance and other gas turbine engine qualification testing. This globally unique outdoor engine test and certification facility was officially opened back in 2010. The prime purpose of this facility is for icing certification of aero gas turbines. As a generic engine test facility, it includes the infrastructure and test systems necessary for the installation of both current and future gas turbine engines. The GLACIER facility completed its commissioning in the winter of 2010/2011, and has now experienced five years of full icing seasons. Rolls-Royce and Pratt and Whitney have both successfully performed certification and engineering icing testing with 5 engines completing their icing certification. Behind the successes there have been some aspects that could have gone better. Some could be considered an inevitable part of engine testing in the real world, but there have been some learning experiences that can be usefully shared with the wider community. This paper aims to examine and publicize the lessons learnt from these first five years of operation, including how the facility hardware has performed, what availability has been achieved, what we have learnt about the icing spray system and how we plan to develop the facility for the future, including the possibility of incorporating ice crystal and mixed phase testing, as well as SLD (Supercooled Large Droplet) testing.
Keywords: Gas turbines; Icing; Ice detection; Certification

Development and application of an impedance-based instrument for measuring the liquid fraction and thickness of ice crystal accretions - Currie, Tom; Fuleki, Dan (SAE Technical Papers, 2015)
Ice crystals ingested by a jet engine at high altitude can partially melt and then accrete within the forward stages of the compressor, potentially causing performance loss, damage and/or flameout. Recent research into this ice crystal icing (ICI) phenomenon conducted at the National Research Council of Canada suggests that the liquid water content vliq of an accretion significantly affects the accretion's susceptibility to erosion by ice crystals, and therefore accretion growth. This paper describes the development and application of an instrument for measuring vliq, potentially providing a method for correlating erosion behavior (e.g. as ductile or brittle) and properties. The instrument measures the complex admittance Y* of a mixed-phase deposit bridging a pair of electrodes, which is modeled as a resistor and capacitor in parallel, and calculates the deposit's relative permittivity εr from the capacitance. Experiments and electrostatic simulations were conducted to correlate εr as a function of vliq for vliq up to ∼40%, using calorimetry to determine vliq. These measurements were made at an excitation frequency of 2MHz, where the relative permittivities of ice and liquid water are insensitive to change of frequency. The paper also describes icing tests where the instrument was used to measure vliq as a function of freestream liquid-to-total water content (LWC/TWC) for two test articles, a cone and a forward-facing cup. The measurements show that vliq lies in the range 25-33% when LWC/TWC is in the range giving worst accretion (LWC/TWC∼10-20%). The instrument is also used to measure thickness growth rate for the cup.
Keywords: Jet engines; Icing; Ice detection; Test facilities

Technique for ice crystal particle size measurements and results for the National Research Council of Canada altitude ice crystal test system - Fuleki, Dan; Chalmers, Jennifer L. Y.; Galeote, Brian (SAE Technical Papers, 2015)
This paper describes the equipment, analysis methods and results obtained for particle size measurements based on a particle imaging velocimetry (PIV) system in which a short duration laser pulse is used to backlight airborne particles. This produces high quality and high resolution images of fast moving airborne particles in a non-intrusive manner. This imaging technique is also used to examine particle morphology and 2D particle trajectory and velocity. The image analysis methods are outlined and validation test results discussed which show the measurement of reference glass beads between 20 and 400 microns were generally to within their stated size. As well, validation testing using known icing wind tunnel droplet distributions were compared with Spraytek 2000 Malvern droplet size measurements and showed agreement of the MVD's to be within ±5% for distributions having nominally 20, 40 and 80 micron MVD's. Implementing this non-intrusive shadowgraphy technique at the NRC ice crystal test system installed at its research altitude test facility (RATFac) showed ice particle size distributions could be generated from approximately 60 to700 micron median mass diameters (MMD's) with the ability to create larger particles well above 1 mm in diameter.
Keywords: Icing; Ice detection; Test procedures

Ice accretion measurements on an airfoil and wedge in mixed-phase conditions - Struk, Peter; Bartkus, Tadas; Tsao, Jen-Ching; Currie, Tom; Fuleki, Dan (SAE Technical Papers, 2015)
This paper presents measurements of ice accretion shape and surface temperature from ice-crystal icing experiments conducted jointly by the National Aeronautics and Space Administration (NASA) and the National Research Council (NRC) of Canada. The data comes from experiments performed at NRC's Research Altitude Test Facility (RATFac) in 2012. The measurements are intended to help develop models of the ice-crystal icing phenomenon associated with engine ice-crystal icing. Ice accretion tests were conducted using two different airfoil models (a NACA 0012 and wedge) at different velocities, temperatures, and pressures although only a limited set of permutations were tested. The wedge airfoil had several tests during which its surface was actively cooled. The ice accretion measurements included leading-edge thickness for both airfoils. The wedge and one case from the NACA 0012 model also included 2D cross-section profile shapes. Ice growth rate at mid-span and, in some cases, along the entire icing surface is reported. The airfoils had thermocouples embedded on model surfaces. Temperature measurements from select cases, including one with edge heaters activated on the model, are presented.
Keywords: Icing; Ice detection; Test facilities; Test procedures

Simulation of ice particle melting in the NRCC RATFac mixed-phase icing tunnel - Currie, Tom; Fuleki, Dan; Davison, Craig (SAE Technical Papers, 2015)
Ice crystals ingested by a jet engine at high altitude can partially melt and then accrete within the compressor, potentially causing performance loss, damage and/or flameout. Several studies of this ice crystal icing (ICI) phenomenon conducted in the RATFac (Research Altitude Test Facility) altitude chamber at the National Research Council of Canada (NRCC) have shown that liquid water is required for accretion. CFD-based tools for ICI must therefore be capable of predicting particle melting due to heat transfer from the air warmed by compression and possibly also due to impact with warm surfaces. This paper describes CFD simulations of particle melting and evaporation in the RATFac icing tunnel for the former mechanism, conducted using a Lagrangian particle tracking model combined with a stochastic random walk approach to simulate turbulent dispersion. Inter-phase coupling of heat and mass transfer is achieved with the particle source-in-cell method. Predictions are compared to turbulence measurements and measurements of total-water and liquid-water content (TWC, LWC) obtained with iso-kinetic and SEA multi-element probes respectively. They are also compared to measured changes in air temperature and humidity ratio resulting from particle evaporation and melting. Good agreement is obtained for these changes under (low pressure) conditions where they are large and interphase heat/mass coupling is very significant. Predicted LWC levels bracket the SEA measurements at low values but are much greater at higher LWC. These predictions suggest that the critical LWC/TWC range for ICI accretion may be higher than previously inferred from SEA measurements.
Keywords: Jet engines; Icing; Ice detection; Test facilities

Development of a supercooled large droplet environment within the NRC altitude icing wind tunnel - Orchard, David M.; Clark, Catherine; Oleskiw, Myron (SAE Technical Papers, 2015)
Simulations of supercooled large droplet (SLD) icing environments within the NRC's Altitude Icing Wind Tunnel (AIWT) have been performed in which broad band mass distribution spectra are achieved that include a distinct pattern of liquid water content (LWC) over a range of droplet sizes (i.e., bi-modal distribution). The mass distribution is achieved through modification of the existing spray system of the AIWT to allow two spray profiles with differing LWC and median volumetric diameter (MVD) to be simultaneously injected into the flow. Results of spray profile distributions measured in the test section have demonstrated that freezing drizzle conditions, where MVD is either less than or greater than 40 μm, can be achieved. Work performed to provide freezing rain conditions is also discussed and highlights the challenges of providing this environment as a result of limitations of the spray system in providing the large droplet sizes (up to 1 mm diameter) or where gravitational settling of these larger drops prevents them from reaching the test section.
Keywords: Aircraft deicing; Hazards; Icing; Ice detection

Effect of gypsum board orientation on board fall-off in fire resistance test assemblies - Sultan, Mohamed A. (Advances in Gypsum Technologies and Building Systems, 2015)
This paper presents and discusses the results of an attempt that was made to determine the Type X, 12.7 mm and 15.9-mm-thick, gypsum board fall-off in fire resistance tests of different orientations (horizontal and vertical assemblies) for 83 and 41 full-scale floor and wall test assemblies, respectively. These tests were conducted at the National Research Council of Canada in accordance with the CAN/ULC–S101 standard, which is similar in fire exposure to the ASTM E119 fire resistance standard for updating the fire resistance ratings in the listed wall and floor assemblies in Part 9, Appendix A, of the National Building Codes of Canada. The results of tests were further analyzed to investigate the gypsum board fall-off for wall and floor assemblies. Four different approaches were investigated using the floor assemblies' test results to identify board fall-off criterion. The proposed temperature criterion selected is based on the sudden temperature rise on the back side of the fire exposed gypsum board due to the board fall-off. The same criterion was also used in predicting the gypsum board fall-off in wall assemblies. A comparison of the gypsum board fall-off based on test observations and temperature measurements and temperature criteria for gypsum board fall-off for both vertical and horizontal applications are presented and discussed.
Keywords: Gypsum board; Fire resistance; Gypsum board fall-off; Wall assemblies; Floor assemblies

Optical fiber random grating-based multiparameter sensor - Xu, Yanping; Lu, Ping; Gao, Song; Xiang, Dao; Lu, Ping; Mihailov, Stephen; Bao, Xiaoyi (Optics Letters, 2015)
A novel multiparameter fiber-optic sensor based on a femtosecond laser micromachined random grating is proposed and demonstrated to realize simultaneous measurement of temperature, axial strain, and surrounding refractive index. A wavelength-division spectral cross-correlation algorithm is adopted to extract the phase variation induced spectral shift responding to different external disturbances. Sensitivities of 10.32 pm/°C, 1.24 pm/με, and −1520.6  pm/RIU were achieved for temperature, axial strain, and surrounding refractive index, respectively. The fiber random grating without phase mask fabrication and high physical strength is an excellent alternative aiming at simple and compact multifunctional fiber sensors.

Group IV mid-IR photonics - Reed, G. T.; Nedeljkovic, M.; Soler Penades, J.; Mitchell, C. J.; Khokhar, A. Z.; Littlejohns, C. J.; Stankovic, S.; Troia, B.; Passaro, V. M. N.; Shen, L.; Healy, N.; Peacock, A. C.; et al. (2015 IEEE Summer Topicals Meeting Series (SUM), 2015)
Silicon and germanium are transparent up to approximately 8 m and 15 m, respectively, thus offering a range of applications in biochemical and environmental sensing, medicine, astronomy and communications [1]. Silicon-on-insulator (SOI), can be used only up to 4 m due to the high absorption loss of silicon dioxide, and therefore alternative material platforms have to be utilized for longer wavelengths. Also, to fully exploit the transparency range of SOI, 400 or 500 nm thick overlayers need to be used rather than the most popular 220 nm platform [2]. In this paper we report record low loss MIR SOI strip and slot waveguides, as well as Vernier racetrack configurations. If the buried oxide can be removed and replaced with air, such a platform would be transparent up to 8 m. We report a robust design based on single etch suspended Si waveguides. Ge-on-Si waveguides have already been demonstrated with losses of 2.5-ぬ┻ど dB【cm at ぢサの┻ぱ ヅm by Chang et. al [3] and Shen et. al [4]. We report a record low loss in Ge-on-Si and a demonstration of all optical modulation in such waveguides. Although Si is transparent beyond 1.1 m, it has been demonstrated that it can be used as a photodetector if mid-bandgap states are created by ion implantation. In this paper we show that detection in Si can be extended to up to 2.5 m by implantation of SOI waveguides with boron. Finally, we also report theoretical analysis of electroabsorption and electrorefraction in Ge.

Traceable calibrations of Rogowski coils at high AC currents - Djokic, Branislav (IEEE Instrumentation & Measurement Magazine, 2015)
What is now commonly known as the Rogowski coil was first presented in 1887 by A.P. Chattock as a winding that was evenly placed on a flexible solid piece of India rubber with a constant cross-section [1]. It was intended for the measurement of magnetic potential, and thus called magnetic potentiometer, but it was recognized from the start that the voltage at its output could be used to measure time-varying current when the winding forms a closed loop around a current-carrying conductor. In his succinct paper, A. P. Chattock covered apparently everything that was necessary: the theory of operation, a method of precision manufacturing by means of a lathe, and calibration by means of mechanically switched dc currents, long before the power electronics evolved and evaluated its measurement error which was about 1%. However, the widespread name of this device, Rogowski coil, became associated with W. Rogowski who co-authored a widely cited paper on the same device some twenty-five years later [2]. The Chattock-Rogowski coil can be described as a conductive helical coil wound on a non-magnetic core encompassing the (primary) conductor carrying the current that is to be measured, as Fig. 1 shows. The coil output (secondary) is usually voltage, but it can also be current, in which case it is an air-core counterpart of the magnetic-core current transformer. For over one century after its inception, the essence of the Chattock-Rogowski coil remained the same but the technology of its manufacturing, the materials used, and the number of its applications have expanded tremendously [3]. The Chattock- Rogowski coil is a very versatile device used primarily for the measurement of ac steady-state, impulse [4], transient [5], and pulsed [6] currents. The currents that can be measured range from a milliampere to over 10 MA, and operating frequencies range from fractions of a hertz to over a gigahertz. They are used extensively in the electric power industry by electric utilities an- electrical equipment manufacturers for switchgear, metering, and protective relaying [7] in substations, on-site calibrations of current transformers [8], and measurements for hydropower plant efficiency testing [9]. They are also used in the steel industry for monitoring and control of electric arc furnaces, in the automotive industry for monitoring and control of current in resistance welding, in military applications, and in testing, calibration, and research laboratories, e.g., for measuring plasma currents in nuclear fusion research and measuring beam currents in particle accelerators.

Haptic handwritten signatures: the effect of deconcentrated dissimilarities on manifold extraction - Valdes, Julio J.; Alsulaiman, Fawaz A.; El Saddik, Abdulmotaleb (2015 IEEE International Symposium on Haptic, Audio and Visual Environments and Games (HAVE), 2015)
The use of a haptic-based handwritten signatures has an intrinsic biometric nature and an important potential in user identification/authentication because it incorporates tactile information. However, in order to exploit this potential for constructing decision systems, it is necessary to gain an appropriate understanding of the internal structure of the data, which in relational representations tend to be very highly dimensional. Most machine learning techniques i) are affected by the curse of dimensionality, ii) use algorithms involving distances (usually Euclidean), but in high dimensional spaces they suffer from the concentration phenomenon. This paper explores the behavior of different strategies for distance deconcentration of haptic data when used for nonlinear unsupervised mappings into low dimensional spaces. An aposteriori use of class information shows that deconcentration transformations improve class cohesion and separation, which can improve the performance of machine learning algorithms.

Sugar Point - a new cruise ship terminal for Barbados - Anglin, Dave; Macintosh, Kevin; Knox, Paul; Cornett, Andrew (Coastal Engineering Proceedings, 2015)
In late 2010, Barbados Port Inc. (BPI) selected the Sugar Point team, a joint venture of SMI Infrastructure Solutions and Royal Caribbean Cruise Lines (RCCL), to undertake a Front End Engineering Design (FEED) study for a new cruise ship terminal adjacent to the existing Port of Bridgetown. The proposed new facility has been designed to accommodate the largest cruise ships in the world (RCCL’s Oasis class), will alleviate congestion in the existing port (which presently serves both cargo and cruise operations) and will significantly improve the arrival experience of cruise passengers. This paper provides an overview of the FEED study, focusing on the technical investigations undertaken to assess the safe navigation, berthing and mooring of large cruise ships, and to define extreme wave loads on the piers. A companion paper (Knox et al., 2014) provides more detailed information on the physical modeling undertaken to support the FEED study.
Keywords: Cruise ships; Ports; Navigation; Moored ship response; Downtime; Physical modeling

Next generation vaccine biomarkers workshop October 30–31, 2014, Ottawa, Canada - Twine, Susan M.; Fulton, Kelly M.; Spika, John; Ouellette, Marc; Raven, Jennifer F.; Conlan, J. Wayne; Krishnan, Lakshmi; Barreto, Luis; Richards, James C. (Human Vaccines & Immunotherapeutics, 2015)
Vaccine biomarkers are critical to many aspects of vaccine development and licensure, including bridging findings in pre-clinical studies to clinical studies, predicting potential adverse events, and predicting vaccine efficacy. Despite advances in our understanding of various biological pathways, and advances in systems analyses of the immune response, there remains much to learn about qualitative and quantitative aspects of the human host response to vaccination. To stimulate discussion and identify opportunities for collaborative ways to advance the field of vaccine biomarkers, A Next Generation Vaccine Biomarker workshop was held in Ottawa. The two day workshop, sponsored by the National Research Council Canada, Canadian Institutes of Health Research, Public Health Agency of Canada, Pfizer, and Medicago, brought together stakeholders from Canadian and international industry, government and academia. The workshop was grouped in themes, covering vaccine biomarker challenges in the pre-clinical and clinical spaces, veterinary vaccines, regulatory challenges, and development of biomarkers for adjuvants and cancer vaccines. The use of case studies allowed participants to identify the needs and gaps requiring innovation. The workshop concluded with a discussion on opportunities for vaccine biomarker discovery, the Canadian context, and approaches for moving forward. This article provides a synopsis of these discussions and identifies steps forward for advancing vaccine biomarker research in Canada.
Keywords: Assay validation; Biomarkers; Correlates of protection; Immune monitoring; Immunization strategy; Surrogate markers; Vaccines; Vaccine safety; Vaccine efficacy

Mid-infrared silicon-on-insulator Fourier-transform spectrometer chip - Nedeljkovic, Milos; Velasco, Aitor V.; Khokhar, Ali Z.; Delage, Andre; Cheben, Pavel; Mashanovich, Goran Z. (IEEE Photonics Technology Letters, 2015)
Mid-infrared absorption spectroscopy is highly relevant for a wide range of sensing applications. In this letter, we demonstrate a Fourier-transform spectrometer chip based on the principle of spatial heterodyning implemented in the silicon-on-insulator waveguide platform, and operating near 3.75-μm wavelength. The spectrometer comprises a waveguide splitting tree feeding to an array of 42 Mach-Zehnder interferometers with linearly increasing optical path length differences. A spectral retrieval algorithm based on calibration matrices is applied to the stationary output pattern of the array, compensating for any phase and amplitude errors arising from fabrication imperfections. A spectral resolution below 3 nm is experimentally demonstrated.
Keywords: Silicon photonics; Spectroscopy; Infrared

Cold adaptive traits revealed by comparative genomic analysis of the eurypsychrophile Rhodococcus sp. JG3 isolated from high elevation McMurdo Dry Valley permafrost, Antarctica - Goordial, Jacqueline; Raymond-Bouchard, Isabelle; Zolotarov, Yevgen; de Bethencourt, Luis; Ronholm, Jennifer; Shapiro, Nicole; Woyke, Tanja; Stromvik, Martina; Greer, Charles W.; Bakermans, Corien; Whyte, Lyle (FEMS Microbiology Ecology, 2015)
The permafrost soils of the high elevation McMurdo Dry Valleys are the most cold, desiccating and oligotrophic on Earth. Rhodococcus sp. JG3 is one of very few bacterial isolates from Antarctic Dry Valley permafrost, and displays subzero growth down to −5°C. To understand how Rhodococcus sp. JG3 is able to survive extreme permafrost conditions and be metabolically active at subzero temperatures, we sequenced its genome and compared it to the genomes of 14 mesophilic rhodococci. Rhodococcus sp. JG3 possessed a higher copy number of genes for general stress response, UV protection and protection from cold shock, osmotic stress and oxidative stress. We characterized genome wide molecular adaptations to cold, and identified genes that had amino acid compositions favourable for increased flexibility and functionality at low temperatures. Rhodococcus sp. JG3 possesses multiple complimentary strategies which may enable its survival in some of the harshest permafrost on Earth.
Keywords: Rhodococcus; Permafrost; Eurypsychrophile; Cryophile; Antarctica; Genome sequence; Subzero

The MiMeS survey of magnetism in massive stars: introduction and overview - Wade, G. A.; Neiner, C.; Alecian, E.; Grunhut, J. H.; Petit, V.; de Batz, B.; Bohlender, D. A.; Cohen, D. H.; Henrichs, H. F.; Kochukhov, O.; Landstreet, J. D.; Manset, N.; et al. (Monthly Notices of the Royal Astronomical Society, 2015)
The MiMeS (Magnetism in Massive Stars) project is a large-scale, high-resolution, sensitive spectropolarimetric investigation of the magnetic properties of O- and early B-type stars. Initiated in 2008 and completed in 2013, the project was supported by three Large Program allocations, as well as various programmes initiated by independent principal investigators, and archival resources. Ultimately, over 4800 circularly polarized spectra of 560 O and B stars were collected with the instruments ESPaDOnS (Echelle SpectroPolarimetric Device for the Observation of Stars) at the Canada–France–Hawaii Telescope, Narval at the Télescope Bernard Lyot and HARPSpol at the European Southern Observatory La Silla 3.6 m telescope, making MiMeS by far the largest systematic investigation of massive star magnetism ever undertaken. In this paper, the first in a series reporting the general results of the survey, we introduce the scientific motivation and goals, describe the sample of targets, review the instrumentation and observational techniques used, explain the exposure time calculation designed to provide sensitivity to surface dipole fields above approximately 100 G, discuss the polarimetric performance, stability and uncertainty of the instrumentation, and summarize the previous and forthcoming publications.
Keywords: Polarimeters; Early-type stars; Magnetic field; Massive stars; Stars rotation

IR excesses around nearby Lambda Boo stars are caused by debris discs rather than ISM bow waves - Draper, Z. H.; Matthews, B. C.; Kennedy, G. M.; Wyatt, M. C.; Venn, K. A.; Sibthorpe, B. (Monthly Notices of the Royal Astronomical Society, 2015)
Lambda Boo stars are predominately A-type stars with solar abundant C, N, O, and S, but up to 2 dex underabundances of refractory elements. The stars’ unusual surface abundances could be due to a selective accretion of volatile gas over dust. It has been proposed that there is a correlation between the Lambda Boo phenomenon and IR excesses which are the result of a debris disc or interstellar medium (ISM) interaction providing the accreting material. We observe 70 or 100 and 160-μm excess emission around nine confirmed Lambda Boo stars with the Herschel Space Observatory, to differentiate whether the dust emission is from a debris disc or an ISM bow wave. We find that 3/9 stars observed host well-resolved debris discs. While the remaining 6/9 are not resolved; they are inconsistent with an ISM bow wave based on the dust emission being more compact for its temperature and predicted bow-wave models produce hotter emission than what is observed. We find the incidence of bright IR excesses around Lambda Boo stars is higher than normal A-stars. To explain this, given our observations, we explore Poynting–Robertson drag as a mechanism of accretion from a debris disc but find it insufficient. As an alternative, we propose the correlation is due to higher dynamical activity in the discs currently underway. Large impacts of planetesimals or a higher influx of comets could provide enough volatile gas for accretion. Further study on the transport of circumstellar material in relation to the abundance anomalies are required to explain the phenomenon through external accretion.
Keywords: Chemically peculiar stars; Circumstellar matter

Quantification of bovine immunoglobulin G using transmission and attenuated total reflectance infrared spectroscopy - Elsohaby, Ibrahim; McClure, J. Trenton; Riley, Christopher B.; Shaw, R. Anthony; Keefe, Gregory P. (Journal of Veterinary Diagnostic Investigation, 2015)
In this study, we evaluated and compared the performance of transmission and attenuated total reflectance (ATR) infrared (IR) spectroscopic methods (in combination with quantification algorithms previously developed using partial least squares regression) for the rapid measurement of bovine serum immunoglobulin G (IgG) concentration, and detection of failure of transfer of passive immunity (FTPI) in dairy calves. Serum samples (n = 200) were collected from Holstein calves 1–11 days of age. Serum IgG concentrations were measured by the reference method of radial immunodiffusion (RID) assay, transmission IR (TIR) and ATR-IR spectroscopy-based assays. The mean IgG concentration measured by RID was 17.22 g/L (SD ±9.60). The mean IgG concentrations predicted by TIR and ATR-IR spectroscopy methods were 15.60 g/L (SD ±8.15) and 15.94 g/L (SD ±8.66), respectively. RID IgG concentrations were positively correlated with IgG levels predicted by TIR (r = 0.94) and ATR-IR (r = 0.92). The correlation between 2 IR spectroscopic methods was 0.94. Using an IgG concentration <10 g/L as the cut-point for FTPI cases, the overall agreement between TIR and ATR-IR methods was 94%, with a corresponding kappa value of 0.84. The sensitivity, specificity, positive predictive value, negative predictive value, and accuracy for identifying FTPI by TIR were 0.87, 0.97, 0.91, 0.95, and 0.94, respectively. Corresponding values for ATR-IR were 0.87, 0.95, 0.86, 0.95, and 0.93, respectively. Both TIR and ATR-IR spectroscopic approaches can be used for rapid quantification of IgG level in neonatal bovine serum and for diagnosis of FTPI in dairy calves.
Keywords: Calf serum; Immunoglobulin G; Infrared spectroscopy; Multivariate calibration

Improving fracture toughness of alumina with multi- walled carbon nanotube and alumina fiber reinforcements - Lo, J.; Zhang, R.; Shalchi-Amirkhiz, B.; Walsh, D.; Bolduc, M.; Lin, S.; Simard, B.; Bosnick, K.; O'Toole, M.; Merati, A.; Bielawski, M. (Advances in Ceramic Armor XI: A Collection of Papers Presented at the 39th International Conference on Advanced Ceramics and Composites, 2015)
Alumina has been widely used for personal armour plate due to its relatively low cost, acceptable hardness and fracture toughness. With the increasing threat level, a much improved ceramic material with better ballistic performance and lighter weight is required. This paper is presents a research work, where alumina reinforced with 2D and 3D alumina fiber mats has been successfully developed for evaluation. The 2D alumina fiber reinforced alumina composite consists of an alumina matrix reinforced with 18 vol% of alumina fiber mats. And the 3D fiber reinforced alumina composite is made with alumina matrix with a 2D alumina fiber mats along with multi-walled carbon nanotubes vertically grown onto the fiber mats. In this study, a detailed examination on fracture surfaces of both 2D and 3D reinforced composites is conducted with scanning electron microscopy to elucidate the contribution of multi-walled carbon nanotubes and alumina fibers in enhancing the fracture toughness of the alumina matrix. Transmission electron microscopy investigation is also conducted on the composite with the 3D reinforcement to provide information on the morphological features at the fiber/matrix regions.
Keywords: Multi-walled carbon nanotube; Alumina fiber reinforcement; Electron microscopy; Alumina composite

Inhibition of viability, proliferation, cytokines secretion, surface antigen expression, and adipogenic and osteogenic differentiation of adipose-derived stem cells by seven-day exposure to 0.5 T static magnetic fields - Wang, Jian; Xiang, Bo; Deng, Jixian; Freed, Darren H.; Arora, Rakesh C.; Tian, Ganghong (Stem Cells International, 2015)
After seven-day exposure to 0.5-Tesla Static Magnetic Field (SMF), Adipose-derived Stem Cells (ASCs) and those labeled by superparamagnetic iron oxide (SPIO) nanoparticles were examined for viability by methyl thiazol tetrazolium (MTT) assay, proliferation by cell counting and bromodeoxyuridine (BrdU) incorporation, DNA integrity by single cell gel electrophoresis, surface antigen by flow cytometry analysis, and the expression of cytokines and genetic markers by reverse transcription-PCR and underwent adipogenic and osteogenic differentiation assessed by quantifying related specific genes expression. The SMF slightly reduced cell viability and proliferation and inhibited the expression of CD49d, CD54, and CD73 but did not damage DNA integrity. The SMF slightly downregulated the expression of cytokines including Vascular Endothelial Growth Factor (VEGF), Insulin-like Growth Factor-1 (IGF-1), Transforming Growth Factor Beta 1 (TGF-β1), genetic markers comprising Stem Cell Antigen-1 (Sca1), Octamer-4 (Oct-4), ATP-binding Cassette Subfamily B Member 1 (ABCB1), adipogenic marker genes containing Lipoprotein Lipase (LPL), Peroxisome Proliferator-Activated Receptor Gamma (PPAR-γ), and osteogenic marker genes including Secreted Phosphor-protein 1 (SPP1) and Osterix (OSX). Exposure to 0.5 T SMF for seven days inhibited viability, proliferation, surface antigen expression, cytokine secretion, stem cell genetic marker expression, and adipogenic and osteogenic differentiation but did not affect the DNA integrity in ASCs with or without SPIO labeling.

Role of physical modelling in developing a new cruise ship terminal at an exposed site - Knox, Paul; Anglin, Dave; Cornett, Andrew; Hall, Erin; Armstrong, Mathew (Coastal Engineering Proceedings, 2015)
This paper describes the role of physical modelling in the design of a new cruise ship terminal at an exposed site on the coast of Barbados, outside the Port of Bridgetown. Large scale 3D hydraulic model studies were conducted to focus on two of the key technical challenges surrounding the project: the risk of downtime due to excessive ship motions forced by the prevailing winds, seas and swells; and the extreme wave loads and overtopping associated with waves generated by hurricanes. The physical modelling was separated into two phases. The first phase investigated the moored ship response of two different model cruise ship vessels under a range of operational wind and wave conditions. The results of this phase helped determine the range of conditions where the motions of the ships and the associated loads on the portside elements were within acceptable limits, and showed that the expected downtime for the design vessels was satisfactory. The second phase of the study focused on wave-structure interactions, and in particular the impact of extreme waves on the proposed structures, including wave-induced loads on the pier decks, and the wave overtopping and flooding of the landside development. Several innovative measures were developed and tested to accommodate / mitigate the loads on the pier decks as well as reduce the wave overtopping. These physical model studies played a key role in the front end engineering design of the new port, and their results were crucial in assessing various alternatives, optimizing preliminary designs, and validating the layout, costing and construction of the new facility. Due to space limitations, this paper focuses on the second phase of the study, in particular the hydrodynamic loads on the pier decks.
Keywords: physical modelling; wave uplift loads; wave uplift pressures; pile support pier decks

Expanding paraphrase lexicons by exploiting lexical variants - Fujita, Atsushi; Isabelle, Pierre (Proceedings of the 2015 Conference of the North American Chapter of the Association for Computational Linguistics: Human Language Technologies, 2015)
This study tackles the problem of paraphrase acquisition: achieving high coverage as well as accuracy. Our method first induces paraphrase patterns from given seed paraphrases, exploiting the generality of paraphrases exhibited by pairs of lexical variants, e.g., “amendment” and “amending,” in a fully empirical way. It then searches monolingual corpora for new paraphrases that match the patterns. This can extract paraphrases comprising words that are completely different from those of the given seeds. In experiments, our method expanded seed sets by factors of 42 to 206, gaining 84% to 208% more coverage than a previous method that generalizes only identical word forms. Human evaluation through a paraphrase substitution test demonstrated that the newly acquired paraphrases retained reasonable quality, given substantially high-quality seeds

Sentiment after translation: a case-study on Arabic social media posts - Salameh, Mohammad; Mohammad, Saif; Kiritchenko, Svetlana (Proceedings of the 2015 Conference of the North American Chapter of the Association for Computational Linguistics: Human Language Technologies, 2015)
When text is translated from one language into another, sentiment is preserved to varying degrees. In this paper, we use Arabic social media posts as stand-in for source language text, and determine loss in sentiment predictability when they are translated into English, manually and automatically. As benchmarks, we use manually and automatically determined sentiment labels of the Arabic texts. We show that sentiment analysis of English translations of Arabic texts produces competitive results, w.r.t. Arabic sentiment analysis. We discover that even though translation significantly reduces the human ability to recover sentiment, automatic sentiment systems are still able to capture sentiment information from the translations

The unreasonable effectiveness of word representations for Twitter named entity recognition - Cherry, Colin; Guo, Hongyu (Proceedings of the 2015 Conference of the North American Chapter of the Association for Computational Linguistics: Human Language Technologies, 2015)
Named entity recognition (NER) systems trained on newswire perform very badly when tested on Twitter. Signals that were reliable in copy-edited text disappear almost entirely in Twitter’s informal chatter, requiring the construction of specialized models. Using well understood techniques, we set out to improve Twitter NER performance when given a small set of annotated training tweets. To leverage unlabeled tweets, we build Brown clusters and word vectors, enabling generalizations across distributionally similar words. To leverage annotated newswire data, we employ an importance weighting scheme. Taken all together, we establish a new state-of-the-art on two common test sets. Though it is wellknown that word representations are useful for NER, supporting experiments have thus far focused on newswire data. We emphasize the effectiveness of representations on Twitter NER, and demonstrate that their inclusion can improve performance by up to 20 F1.

Developing earthworm bioconcentration factors of nitrogen-based compounds for predicting environmentally significant parameters for new munition compounds in soil - Kuperman, Roman G.; Simini, Mike; Checkai, Ronald T.; Dodard, Sabine G.; Sarrazin, Manon; Al-Hawari, Jalal; Paquet, Louise; Sunahara, Geoffrey I.; Di Toro, Dominic M.; Allen, Herbert E.; Kuo, Dave Ta Fu; Torralba-Sanchez, Tifany L. (Applied Soil Ecology, 2015)
We investigated the bioconcentration potential of nitrogen-based compounds 4-nitroanisole (4-NAN), 3,5-dinitro-o-toluamide (3,5-DNoTAME), and 2-methoxy-5 nitropyridine (2-M-5-NPYNE) using earthworm Eisenia andrei exposures in aqueous exposure media in sand. Separate toxicity studies were conducted prior to bioconcentration studies using a range of chemical concentrations to establish the sublethal exposure conditions for the earthworms. The objectives of the present studies were to: (1) develop an experimental test system for estimating bioconcentration potentials of new and emerging munition compounds that partition into earthworms, using aqueous exposure media; and (2) apply this experimental model to establish original bioconcentration data for 4-NAN, 3,5-DNoTAME, and 2-M-5-NPYNE. Experimental design includes earthworm exposures to chemicals for up to 14 days in aqueous media (Römbke medium; 0.08 mM KCl, 2 mM CaCl₂, 0.5 mM MgSO₄, and 0.8 mM NaHCO₃) in the presence of water-washed coarse sand (0.5–1.0 mm) substrate. Concentrations of test chemicals in respective exposure media remained relatively stable during these independent studies. Tissue analyses revealed a rapid uptake of each chemical by the earthworms; a steady state was attained within 24 h from commencement of these exposures. Estimated steady-state bioconcentration factors (BCFss; mL/g dry tissue) were 47, 6, and 11 for 4-NAN, 3,5-DNoTAME, and 2-M-5-NPYNE, respectively. These results will contribute to the BCF database being developed for use in models aimed at predicting environmentally significant parameters for new munition compounds in soil.
Keywords: munition compounds; bioconcentration; toxicity; earthworms

Demonstration of the CPMA-electrometer system for calibrating black carbon particulate mass instruments - Dickau, Matthew; Johnson, Tyle J.; Thomson, Kevin; Smallwood, Greg; Olfert, Jason S. (Aerosol Science and Technology, 2015)
In an effort to improve regulations for particulate emissions from aircraft engines, the Aircraft Exhaust Emissions Measurement Committee, SAE E-31, is investigating instruments to measure black carbon mass concentration in real time. The current candidates are a laser-induced incandescence instrument (LII 300) and a photo-acoustic Micro-Soot Sensor (MSS). However, both of these instruments use indirect techniques, measuring parameters other than the actual mass of particulate in the exhaust, and therefore require calibration. Previously, it has been shown that a centrifugal particle mass analyzer (CPMA) can be used in conjunction with an aerosol electrometer to traceably generate an aerosol with known mass concentration. This system can be used to rapidly calibrate particle mass instruments (on the order of minutes), without the time-consuming process of filter sampling, which is often used for calibration and prone to sampling artifacts. Here, we demonstrate the feasibility of the CPMA-electrometer system for calibrating two LII 300 instruments and two MSS instruments, which were calibrated to the NIOSH 5040 standard. The correlations between the CPMA-electrometer system and the challenge instrument were highly linear for both the LII and the MSS, and agreed well with the previous calibration. All four instruments were found to correlate with the CPMA-electrometer system with R2 values of 0.993 to 0.999. The standard uncertainty in the CPMA-electrometer system averaged 4.3% and was as low as 2.6% for some measurements. With a simple improvement to the aerosol electrometer, we estimate this average uncertainty would be less than 3%. This lower uncertainty and much higher speed of measurement support the use of the CPMA-electrometer system as a mass measurement calibration method for black carbon instruments.

Data integration in machine learning - Li, Yifeng; Ngom, Alioune (2015 IEEE International Conference on Bioinformatics and Biomedicine (BIBM), 2015)
Modern data generated in many fields are in a strong need of integrative machine learning models in order to better make use of heterogeneous information in decision making and knowledge discovery. How data from multiple sources are incorporated in a learning system is key step for a successful analysis. In this paper, we provide a comprehensive review on data integration techniques from a machine learning perspective.
Keywords: data integration; Bayesian network; decision tree; random forest; multiple kernel learning; feature extraction; deep learning

Biomaterial value proposition of triticale - Ton-That, Minh-Tan; Li, Hongbo (Triticale, 2015)
Cereal starch and straw are particularly good candidates for the manufacturing of environmentally friendly polymer materials, especially as replacements, either fully or partially, for traditional synthetic plastic products because of their renewal ability, biodegradability, and low cost. However, the use of cereal starch for the development of bio-based plastics has generated a competition with the human food supply and also created lots of concerns. The use of triticale starch for such purpose can ease those competition and concerns. In this chapter, the development of triticale starch and straw for plastic products and their potential applications are presented. For starch, the most promising venue that can bring rapidly triticale starch into plastic market is as direct use to replace partially traditional plastics and is mainly focused in this chapter. In this case, starch is plasticized and gelatinized (so-called thermoplastic starch or TPS) prior to replace conventional plastics. TPS are also blended with other plastics at a molten stage to produce homogenous blends. All these steps can be performed in one step using conventional plastic processing equipment in order to reduce energy consumption and production cost. The triticale starch morphology, the blending and processing ability into plastic products, and the formulation and the properties of the obtained triticale TPS-based plastic products, such as crystallization structure, morphology, rheological behavior, mechanical properties, and biodegradability are quite comparable to those of other TPS-based plastics made from other starch sources. Thus, it confirms the benefits of TPS-based plastics made from triticale are equivalent with those of other food-grade TPS-based plastics. The straw was processed using different ways to produce either fibers or particles at different sizes prior to incorporating them in commodity plastics. While the starch-based plastics are focused for short-term uses due to the biodegradable nature of starch, the straw-reinforced plastics are aimed for more durable applications with good recycling ability. Different formulations have been developed for both hydrophobic and hydrophilic plastic systems. The processing ability, the performance, and the recycling ability of the triticale straw-reinforced plastics have been proven to be comparable with those of the virgin plastics with significant cost reduction. Finally, the potential of triticale plastic products made from different plastic systems and fabricated by different processes is also envisaged for various industrial applications. This development has registered new value-added products into triticale industrial product portfolio thus enhancing the value proposition for triticale. The massive volume consumption of plastic products can rapidly and significantly increase the net usages of biomass resources based on triticale thus reinforcing the sustainable development in the agricultural and manufacturing sectors in Canada.
Keywords: triticale; starch; straw; plastic; thermoplastic starch; polymer; blend; plastic processing; plastic morphology; rheology; mechanical properties; bio-based plastics; biodegradation

Physical modelling and design optimizations for a new port in Brazil - Baker, S.; Sultan, N.; Cornett, A.; Gunderson, W. (2015)
The role of physical modelling in advancing port design is demonstrated by means of a case study in which three-dimensional physical modeling is used to guide the design of an offshore logistics support base being developed at an unprotected site on the coast of Brazil. The project was driven by the need for a safe harbour for offshore supply vessels, to prevent vessel damage and damage to the dock and berth during normal operations, as well as during extreme storm events. A 1:70 scale model of the proposed supply port and a portion of the surrounding bathymetry was designed, constructed, operated, and then modified to simulate several alternative layouts and design concepts. Froude scaling laws were applied to estimate prototype behaviour from observations and measurements in the model. The physical model proved to be an effective method for assessing the operability of the new port in various metocean conditions and for optimizing its design. It allowed the design team to investigate and assess the impact of many factors influencing wave conditions and the corresponding behaviour of a moored drill supply ship in an efficient and cost-effective manner. The important influences of wave direction, wave height, wave period, and water level were investigated, as were the sensitivities to ship location, loading condition, mooring configuration, mooring line pretension, and mooring line stiffness. Numerous modifications to the port layout were also investigated, which included lengthening the main breakwater, altering the entrance geometry, constructing a new offshore breakwater (of several different lengths), and widening the navigation channel. The outputs from the physical model study have been used in combination with information on the local wave climate at the site to assess operability and estimate downtime due to adverse weather for different port layout and breakwater configurations.

A network model control system (NMCS) for model and full scale tests - Millan, D.; Gash, R.; Janes, G.; Mews, K.; Mills, J.; Williams, J.; Hackett, P.; Pearson, W. (2015)
This paper describes the integrated model and full scale Control and Data Acquisition (NMCS) technology used in the model and full scale tests in the Ocean Coastal and River Engineering Portfolio of National Research Council of Canada. The NMCS includes in a highly integrated suite of hardware and software all components required to: • Acquire real-time data from multiple analog and digital instruments • Store this data on digital media, • Use the real-time data as inputs to real-time control functions, such as autopilots and Dynamic positioning components, •Provide drive signals for multiple steering and propulsion elements, as well as other synchronized commands to devices such as winches, ballast systems, and roll compensation systems The NMCS is based almost entirely 011 Commercial off the Shelf (COTS) components. These include; • Power sub-system components, power sources including batteries for free-running models and remote systems, • Charging Systems, • Power Safety interlock systems, E-Stop functions, • Computers, • Computer networking equipment all communications is handled via standard Ethernet devices. • Motor Controllers and support components, • Data Acquisition, • Synchronization system, that coordinates, synchronizes all elements of acquisition and control, • NRC written custom software provides integration for all of the various hardware functions. The underlying principle of the design was to integrate complex functions into a very flexible system that can be applied to any of NRC's model testing requirements, field trials with models or full scale trials systems. The modularity of the system includes hardware and software aspects, that allow the experiment designer to tailor component content to their exact requirements, and makes it efficient to implement. The core system design allows for the continuous addition of new functions , ongoing improvement of functions , as new requirements are defined or new technologies become available.

Probability of detection and false detection for subsea leak detection systems: model and analysis - Aljaroudi, Alireda; Khan, Faisal; Akinturk, Ayhan; Haddara, Mahmoud; Thodi, Premkumar (Journal of Failure Analysis and Prevention, 2015)
Ensuring the integrity of subsea process components is one of the primary business objectives of the oil and gas industry. Leak detection system (LDS) is one type of system used to safeguard reliability of a pipeline. Different types of LDS use different technologies for detecting and locating leaks in pipelines. One technology, which is gaining wide acceptance by the industry, is the fiber opticbased LDS. This technology has great potential for subsea pipeline applications. It is the most suited for underwater applications due to the ease of installation and reliable sensing capabilities. Having pipelines underwater in the deep sea presents a great challenge and a potential threat to the environment and operation. Thus, there is a need to have a reliable and effective system to provide the assurances that the monitored subsea pipeline is safe and functioning as per operating conditions. Two important performance parameters that are of concern to operators are the probability of detection and probability of false alarm. This paper presents a probabilistic formulation of the probability of detection and probability of false detection for a fiber optic-based LDS.
Keywords: Probability of detection (PD); Probability of false alarm (PFA); Leak detection system (LDS); Oil and gas pipeline

A numerical study of fluid structure interaction of a flexible submerged cylinder mounted on an experimental rig - Cakir, Erkan; Akinturk, Ayhan; Allievi, Alejandro (Proceedings of the ASME 2015 34th International Conference on Ocean, Offshore and Arctic Engineering, OMAE2015, May 31-June 5, 2015, St. John's, Newfoundland, Canada, 2015)
The aim of the study is to investigate VIV effects, not only on a test cylinder but also on the experimental rig being towed under water at a prescribed depth and operating speeds. For this purpose, a numerical Multi-Physics model was created using one way coupled analysis simultaneously between the Mechanical and Fluent solvers of ANSYS software package. A system coupling was developed in order to communicate force data alternately between the solvers with the help of automatic mapping algorithms within millesimal time periods of a second. Numerical investigation into the dynamic characteristics of pressure and velocity fields for turbulent viscous fluid flow along with structural responses of the system, stressed the significance of time and space scales for convergence and accuracy of our Finite Volume (FV) CFD calculations.
The article from: V. 7, Ocean Engineering

Hydrodynamic study of submerged ice collisions - Chander, Subodh; Akinturk, Ayhan; Colbourne, Bruce (Proceedings of the ASME 2015 34th International Conference on Ocean, Offshore and Arctic Engineering, OMAE2015, May 31-June 5, 2015, St. John's, Newfoundland, Canada, 2015)
Most of the research done on ice-structure interaction deals with the ice at the sea surface. Whereas majority of icestrengthened regions of ships and offshore structures are well below the waterline. The aim of this research is to examine the mechanics of ice loads caused by submerged ice blocks colliding with the structure. The kinematics is an essential determinant of the energy that is available to drive the ice crushing process during the collision. The present research aims to develop a model to represent the mechanics of such collisions and set a direction for future work. This study includes experimental and numerical components. Various physical experiments have been conducted using a submerged ice model moving solely due to its buoyancy. Using high speed camera the experiments are recorded and analysed to determine the kinematics of collision. These include location, velocity and acceleration of the model ice as a function of time. In parallel, numerical simulations have being conducted using FLOW 3DTM software. The results of the experiments are used to validate the numerical model of the underwater collision. The results shows that added mass plays an important role during the underwater impact collisions. The paper presents some preliminary results obtained during this research.
The article from: V. 7, Ocean Engineering

Model-scale/full-scale correlation of NRC-OCRE’s model resistance, propulsion and maneuvering test results - Lau, Michael (Proceedings of the ASME 2015 34th International Conference on Ocean, Offshore and Arctic Engineering, OMAE2015, May 31-June 5, 2015, St. John's, Newfoundland, Canada, 2015)
There are a variety of model ices and test techniques adopted by model test facilities. Most often, the clients would ask: “How well can you predict the full scale performance from your model test results?” Model-scale/full-scale correlation becomes an important litmus test to validate a model test technique and its results. This paper summarizes the modelscale/ full-scale correlation performed on model test data generated at the National Research Council - Ocean, Coastal, and River Engineering’s (NRC-OCRE) test facility in St. John’s. This correlation includes ship performance predictions, i.e., resistance, propulsion and maneuvering. Selected works from NRC-OCRE on the USCGC icebreaker Healy, the CCGS icebreaker Terry-Fox, the CCGS R-Class icebreakers Pierre Radisson and Sir John Franklin and the CCGS icebreaker Louis S. St. Laurent were reviewed and summarized. The model tests were conducted at NRC-OCRE’s ice tank with the correct density (CD) EGADS model ice. This correlation is based on the concept that a “correlation friction coefficient” (CFC) can be used to predict full-scale ship icebreaking resistance from model test data. The CFCs have been compared for correlation studies using good-quality full-scale information for the five icebreaker models in the NRC-OCRE’s model test database. The review has shown a good agreement between NRCOCRE’s model test predictions and full-scale measurements. The resistance and power correlation were performed for five sets of full-scale data. Although there is substantial uncertainty on ice thickness and ice strength within the full scale data sets that contributes to data scattering, the data suggest a conservative estimate can be obtained to address reasonably this uncertainty by increasing the model prediction by 15% that envelopes most data points. Limited correlation for maneuvering in ice was performed for the USCGC icebreaker Healy. Selected test conditions from the sea trials were duplicated for the maneuvering tests and turning diameters were measured from the arcs of partial circles made in the ice tank. Performance predictions were then compared to the full-scale data previously collected. Despite some discrepancy in ice strength and power level between the model tests and sea trial, the model data agree well with the sea trial data except for three outliers. Otherwise, the maneuvering data show a good correlation between the model test and sea trial results.
The article from: V. 8, Ian Jordaan Honoring Symposium on Ice Engineerin

Comparison of thermal manikins to human thermoregulatory responses - Power, Jonathan; Baker, Andrew; Simões Ré, António (Extreme Physiology and Medicine, 2015)
Immersion suits are lifesaving appliances (LSA) designed to protect the wearer if they become accidently immersed in cold water by reducing the cold shock response and delaying the onset of hypothermia. Immersion suits are certified to both national and international standards; some of which require the thermal protective properties to be tested using humans or thermal manikins. The ethical nature of testing with humans has been questioned [1] due to the physically grueling nature of these tests, thus testing with manikins may be preferential. However, previous work has shown that discrepancies exist between thermal manikins and humans that could result in immersion suit selection that would benefit the former more than the latter who would ultimately use it [2]. This study investigated the thermoregulatory responses of humans and compared them to a thermal manikin while wearing immersion ensembles with insulation distributed in various configurations hypothesized to be beneficial to humans and manikins.

Model tests of the New Canadian Polar Icebreaker (John G. Diefenbaker) - Wang, Jungyong; Millan, James; McGreer, Dan (Symposia Papers SYMP, 2015)
This paper provides an overview of a model test program to evaluate performance of the new Canadian Polar icebreaker, John G. Diefenbaker design. The National Research Council Canada (NRC), the Canadian Coast Guard, STX Canada Marine (STXM) and Aker Arctic Technology (AARC) worked closely together to develop a test program, to carry out tests and to discuss test results as well as improvements. The model test program included resistance, propulsion and maneuvering (turning circle) tests both in ice and open water; ice ridge penetration tests; the wake survey, seakeeping and stationkeeping tests in open water. The model tests were carried out at the three model basins (ice tank, open water tow tank and ocean engineering basin) at the NRC’s facilities in St. John’s, NL. The test results were well utilized in the vessel’s design development as well as providing performance evaluation tools at the conceptual design stage. Some of the test results are presented here.
Keywords: Polar Icebreaker; John G. Diefenbaker; model testing; ice tank; offshore engineering basin; towing tank

aporModel testing and performance comparison of plastic and metal tidalturbine rotors - Liu, Pengfei; Bose, Neil; Frost, Rowan; Macfarlane, Gregor; Lilienthal, Tim; Penesis, Irene (Applied Ocean Research, 2015)
tExperimental model tests were conducted to predict the performance of two sets of metal and plastic bi-directional tidal turbine rotors. This test programme aims to provide reliable and accurate measurementdata as references for developers, designers and researchers on both model and full scale. The data setpresented in this paper makes available the detailed geometry and motion parameters that are valuablefor numerical tools validation. A rotor testing apparatus that was built using an off-the-shelf K&R propellerdynamometer, its configuration, testing set-up, calibration of the apparatus and data acquisition aredescribed. Comparison analysis between the metal and plastic rotors hydrodynamic performance interms of torque, drag and derived power and drag coefficients are also presented. The results show asubstantial decrease in maximum power performance for the plastic rotors – about 40% decrease at a tipspeed ratio of around 3.0, compared with rigid metal rotors. The plastic rotors have also a much highercut-in speed. It showed that materials for rotor models with low rigidity such as polyamide (nylon)produced by selective laser sintering (SLS) systems may substantially under-predict power generationcapacity. As a result, they are considered unsuitable for rotor model performance evaluation.
Keywords: Metal and plastic rotor testing; Bi-directional turbine; HATT; HACT

Measurements of spatial and temporal variations in ice impact pressures - Sopper, Regina; Gagnon, Robert; Daley, Claude; Colbourne, Bruce (Proceedings of the 23rd International Conference on Port and Ocean Engineering under Arctic Conditions, June 14-18, 2015, Trondheim, Norway, 2015)
This paper presents results of laboratory experiments involving a 1 m diameter ice cone colliding with an instrumented panel (Impact Module). The tests were performed using a double pendulum apparatus that provided high impact energy. Images taken with a high speed camera at 500 fps from within the Impact Module provide information about the true contact area and pressure distribution during the collision. The acquired images were translated into pressure distributions using a specifically developed software routine. These data are compared to the output of a separate pressure sensor located in the centre of the Impact Module. The images show increasing contact area as the collision proceeds and capture sudden losses of area as ice fracture and spalling occurred. Observations such as significant spalling events in the vicinity of the central pressure sensor are also reflected in its recordings. The results provide maps of the temporal and spatial variations in contact pressure, contact area and force as an ice impact progresses at speeds typical of impacts that might occur with icebreaking ships.

A large double-pendulum device to study load, pressure distribution and structure damage during ice impact tests in the lab - Gagnon, Robert; Daley, Claude; Colbourne, Bruce (Proceedings of the 23rd International Conference on Port and Ocean Engineering under Arctic Conditions, June 14-18, 2015, Trondheim, Norway, 2015)
The design and functioning of a new impact device is described, where its eventual intended use is the study of damage associated with pressure distributions arising from ice impacts on ships. The large apparatus is a double-pendulum type device that is capable of achieving fairly high impact energies and velocities while remaining relatively ‘compact’ with respect to the confines of the laboratory space that is available. For example, at a drop angle of 35o from vertical for each pendulum the impact energy and relative velocity are ~ 31 kJ and 5.32 m/s respectively. Conical-shaped ice samples, one meter in diameter are held in a cylindrical ice holder that attaches to one arm of the double pendulum. For one type of test a unique instrumented panel (Impact Module), that records load and high spatial resolution pressure distribution during impacts, attaches to the opposite pendulum arm. For another test type the Impact Module is replaced by ship grillage (full-scale or reduced scale) so that ice impact tests can be performed that cause damage to the grillage. The pendulum arms are designed in a manner such that no rotation of the colliding masses occurs during tests. The effective masses of the colliding objects can be adjusted by adding or removing heavy metal plates. Similarly, the drop angles of the pendulum arms can be adjusted to achieve a range of impact velocities. These two adjustable features enable a variety of impact velocities and energies to be obtainable and allow for some degree of parameter-based study where either velocity or energy is fixed while the other is varied. To date a number of tests have been performed involving ice impacts on the Impact Module. Some representative sensor data that includes a few examples of the ice pressure distribution from one test are presented.

Collection and use of data from school egress trials - Cuesta, A.; Ronchi, Enrico; Gwynne, S. (6th International Symposium on Human Behaviour in Fire 2015: symposium proceedings, 2015)
Data was collected from five evacuations from the same school building, conducted in Spain between 2011 and 2014. Children from 6 to 16 years old were observed during the evacuation exercises. Four of the evacuations were unannounced, while one was semi-announced: the staff being aware that the drill would be conducted on a particular day, while the students were unaware. Information was gathered on the key factors deemed to influence evacuation performance: a description of the geometry, the population involved, the procedures employed and the organization of the drill itself. This information should allow interested parties to gain a reasonably detailed understanding of the initial conditions of each of the five trials. Evacuation data was also collected, focusing on the pre-evacuation times, the routes employed, the speeds adopted and the arrival times. Where data is ambiguous, flawed or omitted, this is documented in an attempt at transparency. To demonstrate an application of this data, we performed a series of small test cases using the Pathfinder, STEPS and EXODUS evacuation tools. The purpose of this work is to (1) provide insight into the configuration of these models for equivalent scenarios; (2) examine any variation in the simulated conditions given equivalent initial conditions; and (3) make public the configuration files (e.g. architectural files, raw experimental data, etc.) and analysis to contribute to the understanding the emergency movement of school pupils and the subsequent use of this data as part of modelling validation exercise. It is suggested that the very transparency of this process is relatively novel in the area of egress modelling.

The impact of security bollards on evacuation flow - Galea, Ed; Cooney, D.; Sharp, G.; Gwynne, S. (6th International Symposium on Human Behaviour in Fire 2015: symposium proceedings, 2015)

Human behaviour in fire: model development and application - Gwynne, Steve; Kuligowski, E.; Kinsey, M. (6th International Symposium on Human Behaviour in Fire 2015: symposium proceedings, 2015)

Identification of a gene involved in the biosynthesis pathway of the terminal sugar of the archaellin N-linked tetrasaccharide in Methanococcus maripaludis - Ding, Yan; Jones, Gareth M.; Brimacombe, Cedric; Uchida, Kaoru; Aizawa, Shin-Ichi; Logan, Susan M.; Kelly, John F.; Jarrell, Ken F. (Antonie van Leeuwenhoek, 2015)
In Methanococcus maripaludis, the three archaellins which comprise the archaellum are modified at multiple sites with an N-linked tetrasaccharide with the structure of Sug-4-β-ManNAc3NAmA6Thr-4-β-GlcNAc3NAcA-3-β-GalNAc, where Sug is a unique sugar (5S)-2-acetamido-2,4-dideoxy-5-O-methyl-l-erythro-hexos-5-ulo-1,5-pyranose, so far found exclusively in this species. In this study, a six-gene cluster mmp1089–1094, neighboring one of the genomic regions already known to contain genes involved with the archaellin N-glycosylation pathway, was examined for its potential involvement in the archaellin N-glycosylation or sugar biosynthesis pathway. The co-transcription of these six genes was demonstrated by RT-PCR. Mutants carrying an in-frame deletion in mmp1090, mmp1091 or mmp1092 were successfully generated. The Δmmp1090 deletion mutant was archaellated when examined by electron microscopy and mass spectrometry analysis of purified archaella showed that the archaellins were modified with a truncated N-glycan in which the terminal sugar residue and the threonine linked to the third sugar residue were missing. Both gene annotation and bioinformatic analyses indicate that MMP1090 is a UDP-glucose 4-epimerase, suggesting that the unique terminal sugar of the archaellin N-glycan might be synthesised from UDP-glucose or UDP-N-acetylglucosamine with an essential early step in synthesis catalysed by MMP1090. In contrast, no detectable phenotype related to archaellin glycosylation was observed in mutants deleted for either mmp1091 or mmp1092 while attempts to delete mmp1089, mmp1093 and mmp1094 were unsuccessful. Based on its demonstrated involvement in the archaellin N-glycosylation pathway, we designated mmp1090 as aglW.
Keywords: Archaea; Methanogens; N-linked glycosylation; Archaella; Mass spectrometry; In-frame deletion

Identification of cross-reactive single-domain antibodies against serum albumin using next-generation DNA sequencing - Henry, Kevin A.; Tanha, Jamshid; Hussack, Greg (Protein Engineering, Design and Selection, 2015)
Antibodies that cross-react with multiple isoforms or homologue of a given protein are often desirable, especially in therapeutic applications. Here, we report the identification of several unique, clonally unrelated, single-domain antibodies (sdAbs) that bind to multiple serum albumin orthologues (human, rhesus, rat and mouse) with low-to-medium nanomolar affinity from a llama immunized only with human serum albumin. Using single-round panning of a phage-displayed sdAb library against serum albumins and next-generation DNA sequencing, we were able to predict patterns of sdAb reactivity to the albumins of different species with ∼90% accuracy. We expect this strategy to be generally applicable for identifying cross-reactive sdAbs, particularly when these exist at low frequency and/or are poorly enriched by panning. Moreover, the sdAbs identified here are of potential interest for serum half-life extension of biologics.
Keywords: next-generation DNA sequencing; phage display; serum albumin; single-domain antibody; VHH

Evaluation of the Wilma-SIE virtual screening method in community structure–activity resource 2013 and 2014 blind challenges - Hogues, Hervé; Sulea, Traian; Purisima, Enrico O. (Journal of Chemical Information and Modeling, 2015)
Prospective assessments of the Wilma-SIE (solvated interaction energy) platform for ligand docking and ranking were performed during the 2013 and 2014 editions of the Community Structure–Activity Resource (CSAR) blind challenge. Diverse targets like a steroid-binding protein, a serine protease (factor Xa), a tyrosine kinase (Syk), and a nucleotide methyltransferase (TrmD) were included. Pose selection was achieved with high precision; in all 24 tests Wilma-SIE top-ranked the native pose among carefully generated sets of decoy conformations. Good separation for the native pose was also observed indicating robustness in pose scoring. Cross-docking was also accomplished with high accuracy for the various systems, with ligand median-RMSD values around 1 Å from the crystal structures. Larger deviations were occasionally obtained due to the rigid-target approach even if multiple target structures were used. Affinity ranking of congeneric ligands after cross-docking was reasonable for three of the four systems, with Spearman ranking coefficients around 0.6. Poor affinity ranking for FXa is possibly due to missing structural domains, which are present during measurements. Assignment of protonation states is critical for affinity scoring with the SIE function, as shown here for the Syk system. Including the FiSH model improved cross-docking but worsened affinity predictions, pointing to the need for further fine-tuning of this newer solvation model. The consistently strong performance of the Wilma-SIE platform in recent CSAR and SAMPL blind challenges validates its applicability for virtual screening on a broad range of molecular targets.

Isolation of camelid single-domain antibodies against native protins using recombinant multivalent peptide ligands - Alturki, Norah A.; Henry, Kevin A.; MacKenzie, C. Roger; Arbabi-Ghahroudi, Mehdi (Peptide Antibodies: Methods and Protocols, 2015)
Generation of antibodies against desired epitopes on folded proteins may be hampered by various characteristics of the target protein, including antigenic and immunogenic dominance of irrelevant epitopes and/or steric occlusion of the desired epitope. In such cases, peptides encompassing linear epitopes of the native protein represent attractive alternative reagents for immunization and screening. Peptide antigens are typically prepared by fusing or conjugating the peptide of interest to a carrier protein. The utility of such antigens depends on many factors including the peptide's amino acid sequence, display valency, display format (synthetic conjugate vs. recombinant fusion) and characteristics of the carrier. Here we provide detailed protocols for: (i) preparation of DNA constructs encoding peptides fused to verotoxin (VT) multimerization domain; (ii) expression, purification and characterization of the multivalent peptide-VT ligands; (iii) concurrent panning of a non-immune phage-displayed camelid VHH library against the peptide-VT ligands and native protein; and (iv) identification of VHHs enriched via panning using next-generation sequencing techniques. These methods are simple, rapid and can be easily adapted to yield cusstom peptide-VT ligands that appear to maintain the antigenetic structures of the peptide. However, we caution that peptide sequences should be chosen with great care, taking into account structural, immunological, and biophysical information on the protein of interest.
Keywords: Single-domain antibody; VHH; Camelid; Peptide; Phage display; NGS

Rational plasmid design and bioprocess optimization to enhance recombinant adeno-associated virus (AAV) productivity in mammalian cells - Emmerling, Verena V.; Pegel, Antje; Milian, Ernest G.; Venereo-Sanchez, Alina; Kunz, Marion; Wegele, Jessica; Kamen, Amine A.; Kochanek, Stefan; Hoerer, Markus (Biotechnology Journal, 2015)
Viral vectors used for gene and oncolytic therapy belong to the most promising biological products for future therapeutics. Clinical success of recombinant adeno-associated virus (rAAV) based therapies raises considerable demand for viral vectors, which cannot be met by current manufacturing strategies. Addressing existing bottlenecks, we improved a plasmid system termed rep/cap split packaging and designed a minimal plasmid encoding adenoviral helper function. Plasmid modifications led to a 12-fold increase in rAAV vector titers compared to the widely used pDG standard system. Evaluation of different production approaches revealed superiority of processes based on anchorage- and serum-dependent HEK293T cells, exhibiting about 15-fold higher specific and volumetric productivity compared to well-established suspension cells cultivated in serum-free medium. As for most other viral vectors, classical stirred-tank bioreactor production is thus still not capable of providing drug product of sufficient amount. We show that manufacturing strategies employing classical surface-providing culture systems can be successfully transferred to the new fully-controlled, single-use bioreactor system IntegrityTM iCELLisTM. In summary, we demonstrate substantial bioprocess optimizations leading to more efficient and scalable production processes suggesting a promising way for flexible large-scale rAAV manufacturing.
Keywords: Bioreactors; Body fluids; DNA; Gene therapy; Mammals; Manufacture; Productivity; Viruses; Adeno-associated virus; Bioprocess optimization; HEK293T; ICELLis; Manufacturing strategy; Recombinant adeno-associated virus; Stirred tank bioreactors; Volumetric productivity; Vectors

The collection and compilation of school evacuation data for model use - Cuesta, A.; Gwynne, S. M. V. (Safety Science, 2015)
Numerous evacuation models are now able to represent populations with different movement abilities. However, this representation is not always supported by empirical data; i.e. the functionality can occasionally overreach the empirical support for it. The goals of this work are: (1) to provide data that adds to the understanding and quantification of vulnerable population's evacuation performance, and (2) to provide sufficiently detailed and transparent data-sets for model configuration and validation. Data was collected during five evacuations from the same school, conducted between 2011 and 2014. Children from 4 to 16 years old were involved in these drills. Four of the evacuations were unannounced, while one was semi-announced (i.e. staff were aware that the drill would be conducted on a particular day). In addition to the initial scenario conditions (e.g. the building geometry, population, procedures employed, etc.), a number of different performance data-sets were collected: pre-evacuation times, travel speeds, route use and evacuation arrival curves. Through the provision of detailed architectural diagrams and other initial conditions and raw data/analysis describing evacuee performance it is hoped that this data-set will be used in the development of evacuation models and their application. The limitations in the data collection and analysis process are outlined allowing the modeler to identify where issues might arise and take corrective actions where possible.
Keywords: Drills; Corrective actions; Evacuation datum; Evacuation modeling; Evacuation models; Initial conditions; Model configuration; Pre-evacuation time; Unannounced evacuation exercises; Population statistics; adolescent; building; child; data processing; nonbiological model; population dispersion; process design; safety; school; school evacuation; teacher; time; validation study; walking speed

High color rendering can enable better vision without requiring more power - Papamichael, Konstantinos; Siminovitch, Michael; Veitch, Jennifer A.; Whitehead, Lorne (LEUKOS - Journal of Illuminating Engineering Society of North America, 2015)
For many people, the correct perception of the colors of objects is an important part of life, and today it is being threatened by misinformed policy-making and associated business decisions. Some conservationists and lamp manufacturers have concluded that the accurate color rendering provided by ordinary incandescent lamps is an unaffordable luxury that good citizens should forgo as we employ more energy-efficient alternatives. Though this is not as extreme as suggesting that we should live in cold darkness, it is in the same general direction of deprivation. Yet research has shown that color rendering is important to people and highefficiency lamps can now also provide high color rendering, so there is no longer any need to have lighting that distorts color appearance. This article focuses on the tradeoff between color rendering accuracy and lamp efficiency to show that high color rendering accuracy is appropriate and, contrary to a common misconception, does not intrinsically require greater electrical energy consumption.
Keywords: Color image processing; Economics; Energy efficiency; Energy management; Energy utilization; Incandescent lamps; Light sources; Lighting; Business decisions; Color appearance; Color rendering; Color rendition; Electrical energy consumption; Energy efficient; High-efficiency; Visual perception; Color

Solid particle erosion behaviors of carbon-fiber epoxy composite and pure titanium - Cai, Feng; Gao, Feng; Pant, Shashank; Huang, Xiao; Yang, Qi (Journal of Materials Engineering and Performance, 2015)
Rotor blades of Bell CH-146 Griffon helicopter experience excessive solid particle erosion at low altitudes in desert environment. The rotor blade is made of an advanced light-weight composite which, however, has a low resistance to solid particle erosion. Coatings have been developed and applied to protect the composite blade. However, due to the influence of coating process on composite material, the compatibility between coating and composite base, and the challenges of repairing damaged coatings as well as the inconsistency between the old and new coatings, replaceable thin metal shielding is an alternative approach; and titanium, due to its high-specific strength and better formability, is an ideal candidate. This work investigates solid particle erosion behaviors of carbon-fiber epoxy composite and titanium in order to assess the feasibility of titanium as a viable candidate for erosion shielding. Experiment results showed that carbon-fiber epoxy composite showed a brittle erosion behavior, whereas titanium showed a ductile erosion mode. The erosion rate on composite was 1.5 times of that on titanium at impingement angle 15° and increased to 5 times at impact angle 90°.
Keywords: Carbon fibers; Coatings; Erosion; Fibers; Shielding; Titanium; Turbomachine blades; Carbon fiber composite; Carbon fiber epoxy composites; Coating process; Composite blades; Erosion behavior; High specific strength; Impingement angle; Solid particle erosion; Composite coatings

A novel method for the quantification of bovine colostral immunoglobulin G using infrared spectroscopy - Elsohaby, Ibrahim; McClure, J. Trenton; Hou, Siyuan; Riley, Christopher B.; Shaw, R. Anthony; Keefe, Gregory P. (International Dairy Journal, 2015)
Transmission infrared (IR) spectroscopy, in combination with partial least squares (PLS) regression, was used as the basis to develop a new method to quantify IgG in bovine colostrum. Colostrum samples (n = 250) were tested simultaneously by the reference radial immunodiffusion (RID) assay and IR spectroscopy. Colostral IgG concentrations obtained by RID assay were linked to pre-processed spectra and divided into two sets, i.e., calibration and test. PLS regression was applied to the calibration set and calibration models were developed, and the test set was used to assess the accuracy of the analytical method. The Pearson and concordance correlations between test set IgG concentrations as determined by the IR assay and the RID assay were 0.91. The Bland-Altman plot showed no evidence of systematic bias between IR and RID methods. Transmission IR spectroscopy is an effective method for quantification of bovine colostral IgG concentration and for assessment of colostrum quality.
Keywords: Antigen-antibody reactions; Calibration; Infrared spectroscopy; Mammals; Analytical method; Calibration model; Immunodiffusion; Immunoglobulin G; Partial least-squares regression; PLS regression; Systematic bias; Test sets; Least squares approximations

Isothermal and cyclic oxidation performance of vertically cracked and columnar thermal barrier coating structures produced using axial suspension plasma spraying process - Li, Xiaolong; Huang, Xiao; Yang, Qi; Tang, Zhaolin (Journal of Engineering for Gas Turbines and Power, 2015)
Oxidation performance of thermal barrier coatings (TBCs) deposited by the axial suspension plasma spraying (ASPS) method was evaluated under isothermal and cyclic conditions with a peak temperature of 1080â ‰°C. The TBC systems are based on two nickel-based superalloy substrates (CMSX-4 and IN738LC), platinum aluminide bond coat (BC), and yttria-stabilized zirconia (8YSZ) top coat (TC) of either vertically cracked (VC) or columnar structure. Samples with IN738LC substrate exhibited longer isothermal oxidation lives whereas the ones with CMSX-4 substrate showed greater cyclic oxidation lives. Outward diffusion of W and Ta in TBC systems containing CMSX-4 was found to have progressed to the interface between thermally grown oxide (TGO) and TC; this has contributed to the reduced isothermal oxidation life. The longer cyclic oxidation lives of TBC systems with CMSX-4 were attributed to less coefficient and thermal expansion (CTE) mismatch between coating layers (reduced strain energy) and better creep resistance of diffusional BC on CMSX-4, hence less TGO rumpling. TBC systems with columnar YSZ had longer isothermal oxidation lives while those with VC YSZ seemed to result in longer cyclic lives.
Keywords: Coatings; Cracks; Creep resistance; Isotherms; Oxidation; Plasma jets; Plasma spraying; Strain energy; Substrates; Thermal conductivity; Thermal expansion; Thermal spraying; Yttria stabilized zirconia; Zirconia; Columnar structures; Isothermal oxidations; Nickel- based superalloys; Peak temperatures; Platinum-aluminide bond coat; Suspension plasma spraying; Thermal barrier coating (TBCs); Thermally grown oxide; Thermal barrier coatings

Theory of optical properties of graphene quantum dots - Ozfidan, Isil; Güçlü, A. D.; Korkusinski, Marek; Hawrylak, Pawel (Physica Status Solidi - Rapid Research Letters, 2015)
We present here a theory of the optical properties of graphene quantum dots (GQDs) with tunable band gaps by lateral size confinement, from UV to THz. Starting from the Hartree-Fock ground state, we construct the correlated many-body ground and excited states of GQDs as a linear combination of a finite number of electron-hole pair excitations. We discuss the evolution of the band gap with size and its renormalization by self-energy and excitonic effects. We calculate and analyze the dipole moments of graphene quantum dots that possess a degenerate valence and conduction band edge, and construct a characteristic exciton and biexciton spectrum. We find an exciton band consisting of a pair of robust, spin singlet bright exciton states and a band of dark, spin singlet and spin triplet, exciton states at lower energies. We predict a characteristic band of biexciton levels at the band edge, discuss the Auger processes and identify a biexciton-exciton cascade. Our theoretical results are compared with experimental linear absorption and non-linear transient absorption spectra of colloidal GQDs. We next discuss the optical properties of triangular GQDs with zigzag edges whose magnetic moment can be controlled by gates. The control over the magnetic moment through carrier density manipulation results in optical spin blockade and gate tunable optical properties over a wide range of photon energies.
Keywords: Energy gap; Excited states; Excitons; Graphene; Ground state; Magnetic moments; Nanocrystals; Semiconductor quantum dots; Characteristic bands; Conduction band edge; Configuration interactions; Linear combinations; Mean field; Optical spectra; Transient absorption spectra; Tunable optical properties; Optical properties

Operational performance of textured journal bearings lubricated with a contaminated fluid - Dadouche, Azzedine; Conlon, Martin J. (Tribology International, 2015)
Contemporary machinery are required to operate under more demanding conditions such as high-temperature or possible contaminated environments. Such situations affect the proper operation of rotating components and sealing systems and could reduce their service life. For instance, hydrodynamic journal bearings may suffer serious performance issues due to contamination from moisture, dust, foreign particles and wear debris. This experimental study investigates the effect of surface texturing on the steady-state performance characteristics of highly-loaded journal bearings lubricated with a contaminated lubricant. Special attention is given to the bearings' load capacity and friction and wear at various contamination levels in the lubricant. Rig tests have been performed at selected speeds and loads on plain smooth and surface-textured journal bearings. Variable-size test dust was introduced into the lubrication system (at different rates) upstream of the test bearing while bearing characteristics were measured. Conclusions are then drawn on the effectiveness of the dimples in capturing contaminant particles and reducing the possibility of bearing failure.
Keywords: Dust; Journal bearings; Lubrication; Machinery; Bearing characteristic; Contaminated environment; Contamination levels; Hydrodynamic journal bearings; Lubrication system; Operational performance; Steady state performance; Textured surface; Contamination

Modeling, optimization and control of bioelectrochemical systems - Recio-Garrido, Dídac; Perrier, Michel; Tartakovsky, Boris (Chemical Engineering Journal, 2015)
Bioelectrochemical systems (BESs) such as Microbial Fuel Cells (MFCs) and Microbial Electrolysis Cells (MECs) are capable of producing energy from renewable organic materials. Over the last decade, extensive experimental work has been dedicated to exploring BES applications for combined energy production and wastewater treatment. These efforts have led to significant advancement in areas of BES design, electrode materials selection, as well as a deeper understanding of the associated microbiology, which helped to bring BES-based technologies within commercial reach. Further progress towards BES commercialization necessitates the development of model-based optimization and process control approaches. This work reviews existing MFC and MEC dynamic models as well as the emerging approaches for optimization and control.
Keywords: Beryllium; Fuel cells; Models; Optimization; Regenerative fuel cells; Wastewater treatment; Bio-electrochemical systems; Bioelectrochemical systems (BESs); Electrode material; Microbial electrolysis cell (MECs); Microbial fuel cells (MFCs); Model based optimization; Optimization and control; Organic materials; Microbial fuel cells

Hybrid Co-Cr/W-WC and Ni-W-Cr-B/W-WC coating systems - Vernhes, L.; Azzi, M.; Bousser, E.; Schmitt, T.; Lamarre, J. M.; Klemberg-Sapieha, J. E. (Journal of Thermal Spray Technology, 2015)
The aim of this study was to investigate the effects of subsurface materials on the performance of a wear-resistant thin film. The mechanical, tribological, and corrosion properties were assessed for two hybrid coating systems: (1) W-WC thin film and a laser cladded Co-Cr interlayer applied to a 316 stainless steel substrate and (2) the same W-WC thin film and a spray-and-fused Ni-W-Cr-B interlayer applied to an Inconel® 718 substrate. They were then compared to the same systems without an interlayer. The microstructures were analyzed by XRD, EDS, and SEM. The hardness and surface load-carrying capacity of the coating systems were determined by micro- and macrohardness testing. Rockwell indentation was used to assess coating adhesion (CEN/TS 1071-8). Tribological properties were assessed with a reciprocating tribometer, and corrosion resistance was determined by potentiodynamic polarization and electrochemical impedance spectroscopy. The originality of this work lies in the finding that, except for the Inconel 718/Ni-W-Cr-B/W-WC system, the wear rate decreases with decreasing hardness of the subsurface materials carrying the thin film due to the decreasing contact pressure for a given load. Another novel finding is the stress-induced phase transformation of the Co-Cr interlayer, which occurs beneath the thin film under high load.
Keywords: Coatings; Cobalt; Corrosion; Corrosion resistance; Electrochemical impedance spectroscopy; Load limits; Load testing; Loads (forces); Nickel; Stainless steel; Tribology; Tungsten carbide; Wear of materials; 316 stainless steel; Hybrid coating systems; Reciprocating tribometer; Rockwell indentation; Stress induced phase transformations; Sub-surface materials; Tribological properties; tribomechanical properties; Thin films

Abiotic factors influence plant storage lipid accumulation and composition - Singer, Stacy D.; Zou, Jitao; Weselake, Randall J. (Plant Science, 2015)
The demand for plant-derived oils has increased substantially over the last decade, and is sure to keep growing. While there has been a surge in research efforts to produce plants with improved oil content and quality, in most cases the enhancements have been small. To add further complexity to this situation, substantial differences in seed oil traits among years and field locations have indicated that plant lipid biosynthesis is also influenced to a large extent by multiple environmental factors such as temperature, drought, light availability and soil nutrients. On the molecular and biochemical levels, the expression and/or activities of fatty acid desaturases, as well as diacylglycerol acyltransferase 1, have been found to be affected by abiotic factors, suggesting that they play a role in the lipid content and compositional changes seen under abiotic stress conditions. Unfortunately, while only a very small number of strategies have been developed as of yet to minimize these environmental effects on the production of storage lipids, it is clear that this feat will be of the utmost importance for developing superior oil crops with the capability to perform in a consistent manner in field conditions in the future.

Characterization of emissions from the use of alternative aviation fuels - Chan, Tak W.; Chishty, Wajid A.; Canteenwalla, Pervez; Buote, David; Davison, Craig R. (Journal of Engineering for Gas Turbines and Power, 2015)
Alternative fuels for aviation are now a reality. These fuels not only reduce reliance on conventional petroleum-based fuels as the primary propulsion source, but also offer promise for environmental sustainability. While these alternative fuels meet the aviation fuels standards and their overall properties resemble those of the conventional fuel, they are expected to demonstrate different exhaust emissions characteristics because of the inherent variations in their chemical composition resulting from the variations involved in the processing of these fuels. This paper presents the results of back-to-back comparison of emissions characterization tests that were performed using three alternative aviation fuels in a GE CF-700-2D-2 engine core. The fuels used were an unblended synthetic kerosene fuel with aromatics (SKA), an unblended Fischer-Tropsch (FT) synthetic paraffinic kerosene (SPK) and a semisynthetic 50-50 blend of Jet A-1 and hydroprocessed SPK. Results indicate that while there is little dissimilarity in the gaseous emissions profiles from these alternative fuels, there is however a significant difference in the particulate matter emissions from these fuels. These differences are primarily attributed to the variations in the aromatic and hydrogen contents in the fuels with some contributions from the hydrogen-to-carbon ratio of the fuels.
Keywords: Blending; Carbon; Fighter aircraft; Fuels; Kerosene; Sustainable development; Synthetic fuels; Characterization tests; Chemical compositions; Conventional fuel; Environmental sustainability; Hydrogen-to-carbon ratio; Overall properties; Particulate matter emissions; Primary propulsion; Alternative fuels

Beaufort sea rubble fields: Characteristics and implications for nearshore petroleum operations - Barker, Anne; Timco, Garry (Cold Regions Science and Technology, 2015)
Experience with past offshore platforms in the Beaufort Sea has shown that in some regions, a stable rubble field of ice may surround the platform during the winter months. These rubble fields can influence marine operations, emergency evacuation systems and can reduce ice loads on the platform. This paper analyzes the historical rubble information that has been collected pertaining to the nearshore Beaufort Sea and it examines potential empirical relationships between rubble field characteristics and a variety of ice and environmental parameters. Historically, offshore structures in this region were in open water for approximately 100days. During the remaining time, quasi-stable, grounded rubble could be present around a structure for extended periods - for example, on average 65% of the time that there was moving pack ice in the autumn. Rubble fields formed between 76%-87% of the time when a drilling structure was in water depths from 5 to 32m. This review shows that grounded rubble fields in the Beaufort Sea can be extensive with areas up to 1km2 with maximum sail heights up to 14m. The extent and shape of each field is interdependent upon a number of factors, such as water depth, number of days the site is in moving ice, and the size and shape of an island, caisson or a submarine berm. But no one factor could guarantee the formation of grounded rubble. Upper bounds to the size of a rubble field are proposed based upon three separate data sets. The potential presence of rubble to such a great degree indicates that operators should clearly identify the strategies to be used to either manage grounded ice rubble or account for its presence with respect to marine operations and emergency evacuation methods. However, the data also show that rubble fields often don't form, even if conditions seem to be favorable for their formation.
Keywords: Drilling platforms; Beaufort sea; Emergency evacuation; Empirical relationships; Environmental parameter; Off shore platforms; Offshore; Operations; Rubble field; Ice; ice-structure interaction; nearshore environment; offshore engineering; offshore structure; sea ice; Arctic Ocean

Corrigendum to "Line shape parameters measurement and computations for self-broadened carbon dioxide transitions in the 30012←00001 and 30013←00001 bands, line mixing, and speed dependence" [J. Mol. Spectrosc. 245 (2007) 34-51] - Predoi-Cross, A.; Unni, A. V.; Liu, W.; Schofield, I.; Holladay, C.; McKellar, A. R. W.; Hurtmans, D. (Journal of Molecular Spectroscopy, 2015)

Correction factors for assessing immersion suits under harsh conditions - Power, Jonathan; Tikuisis, Peter; Simoes Ré, António; Barwood, Martin; Tipton, Michael (Applied Ergonomics, 2015)
Many immersion suit standards require testing of thermal protective properties in calm, circulating water while these suits are typically used in harsher environments where they often underperform. Yet it can be expensive and logistically challenging to test immersion suits in realistic conditions. The goal of this work was to develop a set of correction factors that would allow suits to be tested in calm water yet ensure they will offer sufficient protection in harsher conditions. Two immersion studies, one dry and the other with 500 mL of water within the suit, were conducted in wind and waves to measure the change in suit insulation. In both studies, wind and waves resulted in a significantly lower immersed insulation value compared to calm water. The minimum required thermal insulation for maintaining heat balance can be calculated for a given mean skin temperature, metabolic heat production, and water temperature. Combining the physiological limits of sustainable cold water immersion and actual suit insulation, correction factors can be deduced for harsh conditions compared to calm. The minimum in-situ suit insulation to maintain thermal balance is 1.553-0.0624·TW + 0.00018·TW 2 for a dry calm condition. Multiplicative correction factors to the above equation are 1.37, 1.25, and 1.72 for wind + waves, 500 mL suit wetness, and both combined, respectively. Calm water certification tests of suit insulation should meet or exceed the minimum in-situ requirements to maintain thermal balance, and correction factors should be applied for a more realistic determination of minimum insulation for harsh conditions.
Keywords: Hypothermia; Insulation; Standards; Certification tests; Cold water immersion; Correction factors; Immersion suits; Mean skin temperature; Multiplicative corrections; Protective properties; Realistic conditions; Thermal insulation

Infrared spectra reveal box-like structures for a pentamer and hexamer of mixed carbon dioxide-acetylene clusters - Rezaei, Mojtaba; Norooz Oliaee, J.; Moazzen-Ahmadi, N.; McKellar, A. R. W. (Physical Chemistry Chemical Physics, 2015)
Except for a few cases like water and carbon dioxide, identification and structural characterization of clusters with more than four monomers is rare. Here, we provide experimental and theoretical evidence for existence of box-like structures for a pentamer and a hexamer of mixed carbon dioxide-acetylene clusters. Two mid-infrared cluster absorption bands are observed in the CO2ν3 band region using a tunable diode laser to probe a pulsed supersonic jet. Each requires the presence of both carbon dioxide and acetylene in the jet, and (from observed rotational spacings) involves clusters containing about 4 to 7 molecules. Structures are predicted for mixed CO2 + C2H2 clusters using a distributed multipole model, and the bands are assigned to a specific pentamer, (CO2)3-(C2H2)2, and hexamer, (CO2)4-(C2H2)2. The hexamer has a box-like structure whose D2d symmetry is supported by observed intensity alternation in the spectrum. The pentamer has a closely related structure which is obtained by removing one CO2 molecule from the hexamer. These are among the largest mixed molecular clusters to be assigned by high-resolution spectroscopy.

Inkjet printed thin and uniform dielectrics for capacitors and organic thin film transistors enabled by the coffee ring effect - Graddage, Neil; Chu, Ta-Ya; Ding, Heping; Py, Christophe; Dadvand, Afshin; Tao, Ye (Organic Electronics: physics, materials, applications, 2015)
The deposition of a thin and uniform dielectric layer is required for high performance printed capacitors and thin film transistors (TFTs), however this is difficult to achieve with printing methods. We have demonstrated inkjet-printed dielectrics with a uniform thickness from 70 nm to 200 nm by taking advantage of the coffee ring effect. A high capacitance per unit area of 230 pF/mm2 is achieved from capacitors with linear morphologies fully printed onto flexible substrates. We also demonstrate organic TFTs with an average mobility of 0.86 cm2/Vs and a source drain current of 57 μA obtained with a supply voltage of 15 V. This performance was shown to be consistent, with a standard deviation of 15% obtained from hundreds of printed organic TFTs on PET substrates. This consistency was further validated by the production of functional NAND, NOR, AND and OR logic gates. Our results demonstrate that the coffee ring effect, which is usually viewed as undesirable, can enable higher performance in printed electronic devices.
Keywords: Capacitance; Capacitors; Deposition; Dielectric materials; Drain current; Thin films; Inkjet; Organic thin film transistors; Polymer dielectrics; Printed electronics; Source-drain current; Standard deviation; TFT; Thin-film transistor (TFTs)

A systems genetics approach identifies gene regulatory networks associated with fatty acid composition in brassica rapa seed - Basnet, Ram Kumar; Del Carpio, Dunia Pino; Xiao, Dong; Bucher, Johan; Jin, Mina; Boyle, Kerry; Fobert, Pierre; Visser, Richard G. F.; Maliepaard, Chris; Bonnema, Guusje (Plant Physiology, 2015)
Fatty acids in seeds affect seed germination and seedling vigor, and fatty acid composition determines the quality of seed oil. In this study, quantitative trait locus (QTL) mapping of fatty acid and transcript abundance was integrated with gene network analysis to unravel the genetic regulation of seed fatty acid composition in a Brassica rapa doubled haploid population from a cross between a yellow sarson oil type and a black-seeded pak choi. The distribution of major QTLs for fatty acids showed a relationship with the fatty acid types: linkage group A03 for monounsaturated fatty acids, A04 for saturated fatty acids, and A05 for polyunsaturated fatty acids. Using a genetical genomics approach, expression quantitative trait locus (eQTL) hotspots were found at major fatty acid QTLs on linkage groups A03, A04, A05, and A09. An eQTL-guided gene coexpression network of lipid metabolism-related genes showed major hubs at the genes BrPLA2-ALPHA, BrWD-40, a number of seed storage protein genes, and the transcription factor BrMD-2, suggesting essential roles for these genes in lipid metabolism. Three subnetworks were extracted for the economically important and most abundant fatty acids erucic, oleic, linoleic, and linolenic acids. Network analysis, combined with comparison of the genome positions of cis- or trans-eQTLs with fatty acid QTLs, allowed the identification of candidate genes for genetic regulation of these fatty acids. The generated insights in the genetic architecture of fatty acid composition and the underlying complex gene regulatory networks in B. rapa seeds are discussed.

Combined bioelectrochemical-electrical model of a microbial fuel cell - Recio-Garrido, Dídac; Perrier, Michel; Tartakovsky, Boris (Bioprocess and Biosystems Engineering, 2015)
Several recent studies demonstrated significant charge storage in electrochemical biofilms. Aiming to evaluate the impact of charge storage on microbial fuel cell (MFC) performance, this work presents a combined bioelectrochemical-electrical (CBE) model of an MFC. In addition to charge storage, the CBE model is able to describe fast (ms) and slow (days) nonlinear dynamics of MFCs by merging mass and electron balances with equations describing an equivalent electrical circuit. Parameter estimation was performed using results of MFC operation with intermittent (pulse-width modulated) connection of the external resistance. The model was used to compare different methods of selecting external resistance during MFC operation under varying operating conditions. Owing to the relatively simple structure and fast numerical solution of the model, its application for both reactor design and real-time model-based process control applications are envisioned.
Keywords: Dynamic models; Electric network parameters; Equivalent circuits; Fuel cells; Fuel storage; Nonlinear equations; Bio-electrochemical; Charge storage; Electrical modeling; Equivalent electrical circuits; Intermittent connections; Multi population; Operating condition; Pulse-width-modulated; Microbial fuel cells

Metabolic engineering of CHO cells to alter lactate metabolism during fed-batch cultures - Toussaint, Cécile; Henry, Olivier; Durocher, Yves (Journal of Biotechnology, 2015)
Recombinant yeast pyruvate carboxylase (PYC2) expression was previously shown to be an effective metabolic engineering strategy for reducing lactate formation in a number of relevant mammalian cell lines, but, in the case of CHO cells, did not consistently lead to significant improvement in terms of cell growth, product titer and energy metabolism efficiency. In the present study, we report on the establishment of a PYC2-expressing CHO cell line producing a monoclonal antibody and displaying a significantly altered lactate metabolism compared to its parental line. All clones exhibiting strong PYC2 expression were shown to experience a significant and systematic metabolic shift toward lactate consumption, as well as a prolonged exponential growth phase leading to an increased maximum cell concentration and volumetric product titer. Of salient interest, PYC2-expressing CHO cells were shown to maintain a highly efficient metabolism in fed-batch cultures, even when exposed to high glucose levels, thereby alleviating the need of controlling nutrient at low levels and the potential negative impact of such strategy on product glycosylation. In bioreactor operated in fed-batch mode, the higher maximum cell density achieved with the PYC2 clone led to a net gain (20%) in final volumetric productivity.
Keywords: CHO cells; pyruvate carboxylase; metabolic engineering; fed-batch; monoclonal antibody

Apocynaceae seed lipids: characterization and occurrence of Isoricinoleic acid and triacylglycerol estolides - Smith, Mark A.; Zhang, Haixia (JAOCS, Journal of the American Oil Chemists' Society, 2015)
Isoricinoleic acid (9-hydroxy-cis-12-octadecenoic acid; IR) is a potential renewable feedstock for the oleochemical industry, a precursor for the synthesis of antimicrobial compounds and a component of the seed oil of certain plants in the Apocynaceae. For a more detailed survey of this plant family, seeds of 18 species representing different subfamilies were obtained and acyl composition and oil content was determined. IR was observed only in species of the tribes Wrightieae and Nerieae in the Apocynoideae subfamily and is reported for the first time in the seed oil of the desert rose Adenium obesum in which it is present at a level of around 26 %. In contrast to previous reports, IR was not found in oil from Holarrhena species, H. antidysenterica and H. pubescens, nor in oil from Annona squamosa. To examine the oil structure, samples were analyzed using MALDI-TOF mass spectrometry. This technique proved to be a simple method to demonstrate the occurrence of the estolide 9-acetoxy-cis-12-octadecenoic acid in oil from Nerium oleander and gave further insight into the distribution of estolides within the oil, revealing the presence of tetra- and penta-acyl-TAG molecules, and molecules containing IR esterified to all three position of glycerol. For other species in which IR was observed, the HFA was found to be a component of seed TAG, but no secondary acylation of the hydroxyl groups was observed.
Keywords: Glycerol; Mass spectrometry; Molecules; Oils and fats; Adenium obesum; Apocynaceae; Estolides; MALDI TOF MS; Seed oil; Seed

Hydride generation for headspace solid-phase extraction with CdTe quantum dots immobilized on paper for sensitive visual detection of selenium - Huang, Ke; Xu, Kailai; Zhu, Wei; Yang, Lu; Hou, Xiandeng; Zheng, Chengbin (Analytical Chemistry, 2015)
A low-cost, simple, and highly selective analytical method was developed for sensitive visual detection of selenium in human urine both outdoors and at home, by coupling hydride generation with headspace solid-phase extraction using quantum dots (QDs) immobilized on paper. The visible fluorescence from the CdTe QDs immobilized on paper was quenched by H2Se from hydride generation reaction and headspace solid-phase extraction. The potential mechanism was investigated by using X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS) as well as Density Functional Theory (DFT). Potential interferences from coexisting ions, particularly Ag+, Cu2+, and Zn2+, were eliminated. The selectivity was significantly increased because the selenium hydride was effectively separated from sample matrices by hydride generation. Moreover, due to the high sampling efficiency of hydride generation and headspace solid phase extraction, the sensitivity and the limit of detection (LOD) were significantly improved compared to conventional methods. A LOD of 0.1 μg L-1 and a relative standard deviation (RSD, n = 7) of 2.4% at a concentration of 20 μg L-1 were obtained when using a commercial spectrofluorometer as the detector. Furthermore, a visual assay based on the proposed method was developed for the detection of Se, 5 μg L-1 of selenium in urine can be discriminated from the blank solution with the naked eye. The proposed method was validated by analysis of certified reference materials and human urine samples with satisfactory results.
Keywords: Body fluids; Cadmium telluride; Density functional theory; Hydrides; Nanocrystals; Phase separation; Selenium; Semiconductor quantum dots; X ray diffraction; X ray photoelectron spectroscopy; Conventional methods; Headspace solid-phase extraction; Human urine samples; Hydride generations; Potential interferences; Relative standard deviations; Spectrofluorometers; Extraction

Quantifying metal support interaction in ceria-supported Pt, PtSn and Ru nanoparticles using electrochemical technique - Dole, Holly A. E.; Costa, Ana C. G. S. A.; Couillard, Martin; Baranova, Elena A. (Journal of Catalysis, 2015)
Electrochemical promotion and metal-support interaction (MSI) have long been viewed as two separate phenomena; however, more recently it has been shown that, functionally, for ionic and mixed ionic-electronic conducting materials, both are linked by the transfer of ionic species at the interfaces. The purpose of this study was to exhibit a relationship between these two concepts through the use of an electrochemical technique to evaluate CeO2-supported Pt- and Ru-based nanoparticles. The presence of ceria was found to increase the reaction rate when compared to free-standing Pt and Ru nanoparticles with the metal-support interaction rate enhancement ratios, ρMSI, up to 14. Polarization measurements established that higher exchange current density, i0, values correspond to lower open circuit catalytic rates. An apparent self-induced Faradaic efficiency was proposed and determined for each catalyst; lowest value (|ΛMSI| =1053) corresponded to 1 wt% Pt-1/CeO2.
Keywords: Cerium compounds; Ethylene; Interfaces (materials); Metal nanoparticles; Metals; Nanoparticles; Platinum; Polarization; Electrochemical promotion; Electrochemical techniques; Ethylene oxidation; Exchange current densities; Faradaic efficiencies; Metal-support interactions; Polarization curves; Polarization measurements; Ruthenium

Formation of methane clathrate hydrates in coal moisture: Implications for coalbed methane resources and reservoir pressures - Bustin, A. M. M.; Bustin, R. M.; Moudrakovskim, I. L.; Takeya, S.; Ripmeester, J. A. (Energy and Fuels, 2015)
Adsorption, X-ray diffraction, and nuclear magnetic resonance analysis of subbituminous to high-volatile bituminous coal at in situ moisture content, low temperatures, and moderate pressures demonstrate that a significant proportion of the inherent moisture (nonmobile water) is available to form methane clathrate hydrates. These results have implications for coal gas resources and reservoir pressures in current areas of permafrost and the much larger regions that were glaciated during the Pleistocene. Methane adsorption tests indicate the clathrates form comparatively rapidly in coal micro- and mesopores from an immobile water phase, at lower pressures than those formed in macroporous materials. At successively higher experimental pressures, hydrates nucleate and grow rapidly on the scale of minutes to hours, until an apparent equilibrium pressure is reached. The onset of hydrate formation at 0 °C is at about 3.25 MPa for a Tarn coal with 33% moisture and at slightly higher pressures for the other coals with lower inherent moisture. The amount of gas consumed in hydrate formation, in excess of that attributed to sorption, is 11.6 cm3/g coal for the Tarn coal (Alaska) with 33% moisture, 8.15 cm3/g coal for a Dietz coal (Wyoming) with 22% moisture, and 1.85 cm3/g coal for a Texas coal with about 8% moisture. On a volume of gas (STP) per volume of water basis at 8 MPa, the Tarn and Dietz coal have similar values (35 and 37 cm3/cm3), whereas the Texas coal is measureably less (24 cm3/cm3). At 8 MPa and 0 °C, about 20% of the inherent moisture has participated in hydrate formation for the Tarn and Deitz coals and 13% for the Texas coal. If hydrate formation strips methane from the sorbed state, the proportion of water contributing to hydrate calculates was over 100% for the Texas coal, which suggests that methane is mainly forming from free gas. The methane hydrates analyzed by X-ray diffraction and nuclear magnetic resonance (NMR) spectroscopy are cubic (Pm3nspace group) and have small and large cage sI structures. NMR and PXRD spectra indicates that the small cages are about 90% occupied, while the large cages are completely full, yielding a stoichiometry of ca. CH4·6H2O, which is consistent with other natural hydrates. There is some evidence that some methane gas remains trapped in the smallest pores, whereas the hydrates occupy large pores, which may be due to the suppression of hydrate formation by high capillary pressures. The formation of methane hydrates, particularly in low-rank coals, markedly increases the capacity of the coal to store gas. Depending on the coal moisture content and coal rank, methane storage capacity in gas hydrates is up to 2 orders of magnitude greater than the gas storage capacity of the coal by sorption alone. Since low-rank coals invariably have high moisture content, if the strata lie with the hydrate stability zone, significant gas storage in hydrates is anticipated, if gas is available. At the low temperature required for hydrate formation, however, self-sourced methane from methanogenesis or thermal alteration is not anticipated. Successive formation and dissociation of methane hydrates during glacial and interglacial times in the Pleistocene can be anticipated to have impacted shallow gas reservoirs, including coals, to depth up to about 800 m, depending on the surface temperature and geothermal gradient. It is speculated that during the Pleistocene free and sorbed coal gas was scavenged during the formation of hydrates, and this process may explain the low gas content of some high-latitude coals. Similarly, lower than anticipated pore pressure and lack of free water in the Horseshoe Canyon coals in western Canada may be the result of dissociation of hydrates forming overpressures, which potentially could hydraulically fracture the coal and flush the coal of free water. Subsequent dissipation of the gas pressure would lead to the current low reservoir pressure.
Keywords: Atmospheric temperature; Bituminous coal; Coal; Coal bed methane; Coal deposits; Coal gas; Coal storage; Dissociation; Driers (materials); Energy resources; Gases; Hydration; Methane; Moisture; Moisture determination; Nuclear magnetic resonance; Nuclear magnetic resonance spectroscopy; Petroleum deposits; Porous materials; Storage (materials); X ray diffraction; Equilibrium pressure; Geothermal gradients; High moisture contents; In-situ moisture content; Macroporous materials; Methane clathrate hydrate; Nuclear magnetic resonance(NMR); Surface temperatures; Gas hydrates

Buckling behavior of variable-stiffness composite laminates manufactured by the tow-drop method - Marouene, A.; Boukhili, R.; Chen, J.; Yousefpour, A. (Composite Structures, 2015)
The current investigation deals with the buckling behavior of variable-stiffness composite panels manufactured by the automated fiber placement (AFP) process. In order to minimize the occurrence of AFP-inherent defects as gaps and overlaps, the so-called tow-drop method was adopted. Compression-buckling tests were performed on large panels containing gaps or overlaps under simply-supported boundary conditions. The specific responses of the out-of-plane deflections, which were tracked by four laser sensors focused on the axial centerline of the panels during compression loading, were explained by the measured initial geometric curvatures, which were characteristic of variable-stiffness panels. The tracking of the in-plane strains using sixteen strain gauges located strategically on the panels confirmed that the presence of gaps and overlaps does not affect the symmetry of variable-stiffness panels. Finally, it was established that the tow-drop method significantly improved the structural performance in terms of the pre-buckling stiffness, buckling load, and the failure load while keeping minimal geometric disturbances.
Keywords: Drops; Laminated composites; Stiffness; Strain; Compression buckling; Compression loading; Fiber placement; Gaps/overlaps; Geometric curvature; Out-of-plane deflection; Structural performance; Variable stiffness; Buckling

Correlations among thermophysical properties, ignition quality, volatility, chemical composition, and kinematic viscosity of petroleum distillates - Shen, Jun; Astrath, Nelson G. C.; Pedreira, Paulo R. B.; Guimarães, Francine B.; Gieleciak, Rafal; Wen, Qing; Michaelian, Kirk H.; Fairbridge, Craig; Malacarne, Luis C.; Rohling, Jurandir H.; Baesso, Mauro L. (Fuel, 2015)
Thermophysical measurements and Raman spectroscopy were utilized to investigate 17 hydrocarbon distillates derived from Canadian oil sands in this work. Thermal lens and optical interferometer techniques were used to determine the thermal diffusivity (D) and temperature coefficient of the refractive index (dn/dT), respectively. It was found that D and dn/dT are closely correlated with the cetane numbers, distillation temperatures, monocyclic aromatics contents, and kinematic viscosities of the fuels. Raman spectra yielded information on the chemical compositions of the distillates, with aromatic contents proving to be particularly relevant. Multivariate analysis elucidated the relationships among the samples, their properties according to ASTM analyses, and the influence of composition on D and dn/dT.
Keywords: Distillation; Kinematics; Lenses; Oil sands; Petroleum distillates; Raman spectroscopy; Temperature; Thermal diffusivity; Thermodynamic properties; Viscosity; Aromatic contents; Chemical compositions; Chemometrics; Distillation temperature; Multi variate analysis; Optical interferometer; Temperature coefficient; Thermophysical; Refractive index

Imaging the expanding shell of SN 2011dh - De Witt, A.; Bietenholz, M. F.; Kamble, A.; Soderberg, A. M.; Brunthaler, A.; Zauderer, B.; Bartel, N.; Rupen, M. P. (Monthly Notices of the Royal Astronomical Society, 2015)
We report on the third epoch of very long baseline interferometry (VLBI) observations of the radio-bright supernova SN 2011dh, located in the nearby (7.8 Mpc) galaxy M51. The observations took place at t = 453 d after the explosion and at a frequency of 8.4 GHz. We obtained a fairly well-resolved image of the shell of SN 2011dh, making it one of only six recent supernovae for which resolved images of the ejecta are available. SN 2011dh has a relatively clear shell morphology, being almost circular in outline, although there may be some asymmetry in brightness around the ridge. By fitting a spherical shell model directly to the visibility measurements we determine the angular radius of SN 2011dh's radio emission to be 636 ± 29 μas. At a distance of 7.8 Mpc, this angular radius corresponds to a linear radius of (7.4 ± 0.3) × 1016 cm and an average expansion velocity since the explosion of 19 000+2800 -2400 km s-1.We combine our VLBI measurements of SN 2011dh's radius with values determined from the radio spectral energy distribution under the assumption of a synchrotronself- absorbed spectrum, and find all the radii are consistent with a power-law evolution, with R ~ t0.97±0.01, implying almost free expansion over the period t = 4 d to 453 d.

A reference method for measuring emissions of SVOCs in small chambers - Wu, Yaoxing; Cox, Steven S.; Xu, Ying; Liang, Yirui; Won, Doyun; Liu, Xiaoyu; Clausen, Per A.; Rosell, Lars; Benning, Jennifer L.; Zhang, Yinping; Little, John C. (Building and Environment, 2015)
Semi-volatile organic compounds (SVOCs) are indoor air pollutants that may have significant adverse effects on human health. Although emissions of volatile chemicals from building materials and consumer products are usually characterized in small chambers, few chamber studies have been conducted for SVOCs due to the challenges associated with analysis and the lack of validation procedures. There is an urgent need for a reliable and accurate chamber test method to verify these measurements. A reference method employing a specially-designed chamber has been developed and is undergoing extensive evaluation. A pilot inter-laboratory study (ILS) has been conducted with six laboratories performing chamber tests under identical conditions for di-2-ethylhexyl phthalate (DEHP). Results from this study showed inter-laboratory variations of 24% for DEHP emission rates, with closer agreement observed among intra-laboratory measurements for most of the participating laboratories. A mechanistic emission model fits well to the measured concentration profiles, demonstrating the feasibility of the proposed reference method to independently assess laboratory performance and validate SVOC emission tests.
Keywords: Consumer products; Esters; Indoor air pollution; Organic compounds; Potassium compounds; DEHP; Laboratory studies; Semivolatile organic compounds; Laboratories; air quality; atmospheric pollution; concentration (composition); indoor air; phthalate; volatile organic compound

Growth performance, proximate and histological analysis of rainbow trout fed diets containing Camelina sativa seeds, meal (high-oil and solvent-extracted) and oil - Bullerwell, Christina N.; Collins, Stephanie A.; Lall, Santosh P.; Anderson, Derek M. (Aquaculture, 2015)
Two 112-day feeding trials were conducted to examine the effects of including camelina (Camelina sativa) products in rainbow trout diets. In the first experiment, 20 tanks (40. L) of rainbow trout (Oncorhynchus mykiss; 2.36. ±. 0.18. g, 30 fish/tank) were fed one of five diets containing solvent-extracted camelina meal (SECM) at dietary inclusion levels of 0, 50, 100, 150 or 200. g/kg. Weight gain and specific growth rate (SGR) of fish fed 200. g/kg SECM were significantly lower than those fed 0 and 50. g/kg SECM. The protein efficiency ratio (PER) of fish fed 50. g/kg SECM (2.4) was significantly higher than fish fed 0, 150 and 200. g/kg SECM (all 2.1). There were no significant differences among treatments for total feed consumption or FCR, although during earlier periods of the trial, fish fed 150 and 200. g/kg SECM had higher FCR than fish fed 0 and 50. g/kg SECM (P<. 0.05). In the second experiment, 24 tanks (40. L) of rainbow trout (1.0. ±. 0.1. g, 30 fish/tank) were fed one of eight diets: a control diet; six diets containing full-fat camelina seed or high oil residue camelina meal (HORM), at dietary inclusion levels of 100, 200 and 300. g/kg; or a diet that contained 100. g/kg SECM and 151. g/kg camelina oil (SECM. +. CO), with no added fish oil. After 112. days on feed, fish fed diet containing 300. g/kg camelina seed and 300. g/kg HORM gained less weight than fish fed the control diet (P<. 0.05). Fish that consumed 300. g/kg camelina seed also gained significantly less weight than fish fed 100. g/kg camelina seed and 100. g/kg HORM. Feed consumption was not affected by diet. FCR was higher in fish fed 300. g/kg HORM than in fish fed 100. g/kg camelina seed and the PER of the fish fed 300. g/kg HORM was lower than that of fish fed 100. g/kg camelina seed and HORM (P<. 0.05). There was no treatment effect on the intestinal histology of fish fed these diets (P<. 0.05). Fish fed up to 100. g/kg SECM, camelina seed and HORM, as well as the SECM. +. CO diet did not perform any differently than fish fed the control diet (P>. 0.05). Although there were a few negative effects on performance in fish fed 200. g/kg camelina seed and HORM early in the trial, this did not remain consistent for the entire trial. The maximum dietary inclusion threshold of these camelina products in juvenile rainbow trout diets is likely between 100 and 200. g/kg, although further research will be required to determine more definite values. Statement of relevance: This study determines the feed intake and growth response of rainbow trout fed camelina seed (dietary inclusion levels of 0, 100, 200 and 300. g/kg), high oil residue camelina meal (dietary inclusion levels of 0, 100, 200 and 300. g/kg) and solvent-extracted camelina meal (dietary inclusion levels of 0, 50, 100, 150 and 200. g/kg) and a combination of 100. g/kg solvent-extracted camelina meal and 151. g/kg camelina oil, as well as information regarding the carcass composition and intestinal morphology of fish fed the first two ingredients. This research provides data that will enable the formulation of practical diets using these feed ingredients.
Keywords: artificial diet; crop plant; experimental study; food consumption; food intake; growth rate; histology; salmonid culture; seed; vegetable oil; Camelina; Camelina sativa; Oncorhynchus mykiss

The effects of camelina oil and solvent extracted camelina meal on the growth, carcass composition and hindgut histology of Atlantic salmon (Salmo salar) parr in freshwater - Ye, Chang Lin; Anderson, Derek M.; Lall, Santosh P. (Aquaculture, 2015)
A study was conducted to evaluate the nutritional value of experimentally solvent extracted camelina meal (SECM) and camelina oil (CO) fed to Atlantic salmon parr. Fish (initial weight: 8.4. g) were fed a control diet, or diets containing 5, 10, 15 or 20% SECM, or 50% and 100% CO substituted for fish oil in diets. Fish were reared in freshwater at 11.7. ±. 0.5. °C for 16. weeks. Weight gain from week 13 to week 16 decreased in fish fed 10% SECM, and the daily growth coefficient (DGC) was lower in both 10% (1.22) and 15% (1.22) SECM groups (p. < 0.05), but was similar between the fish fed 20% SECM (1.23) diet and the control (1.37; p ≥ 0.05) diet. The final body weight was not affected by dietary treatments. Condition factor, feed conversion ratio, protein retention ratio and hepato-somatic index were similar among all groups (p ≥ 0.05). Carcass protein, fat, ash and moisture were also unaffected. The length, width and area of simple villi in the distal intestine were unaffected by treatments (p ≥ 0.05), however, increased size of lamina propria was observed in fish fed 15 and 20% SECM diets (p < 0.05). Results suggest that fish performance was not affected by the inclusion of 5% SECM in the diet, and 50 to 100% replacement CO by fish oil.Statement of relevance. This study investigated novel feed ingredients from Camelina sativa applied in aqua-feed for Atlantic salmon. Camelina oil is as good as fish oil, and it contains health-promoting factor for fish intestine. Solvent extracted camelina meal can be used at 5% in the diet. These findings can reduce reliance on fishmeal and fish oil in the future.
Keywords: anatomy; cells and cell components; community composition; freshwater environment; growth rate; histology; performance assessment; protein; salmonid; vegetable oil; Camelina; Camelina sativa; Salmo salar

Glucose-assisted synthesis of highly dispersed LiMnPO4 nanoparticles at a low temperature for lithium ion batteries - Xie, Zhengzheng; Chang, Kun; Li, Bao; Tang, Hongwei; Fu, Xiaoning; Chang, Zhaorong; Yuan, Xiao-Zi; Wang, Haijiang (Electrochimica Acta, 2015)
The cathode material of the LiMnPO4/C composite for lithium-ion batteries is successfully synthesized via a one-step glucose-assisted liquid-phase method in ethylene glycol (EG). The crystalline structure, morphology, micro-structure and particle size are characterized by X-ray diffraction (XRD), scanning electron microscope (SEM) and transmission electron microscope (TEM). XRD results show that the pure phase of LiMnPO4 with high crystallinity can directly be prepared in the liquid-phase assisted by glucose. SEM measurements confirm the uniform-sized nanorods of the LiMnPO4 morphology with a width of 20-50 nm and a length of 50-80 nm. TEM characterization reveals that the surface of the obtained LiMnPO4 nanorods is coated with a homogeneous carbon layer after a short heat treatment at a high temperature in the presence of glucose. This can be explained by the fact that the glycol glucoside generated during the refluxing of EG with glucose can effectively inhibit the growth and agglomeration of particles. Results of electrochemical tests show that the prepared LiMnPO4/C nanorods exhibit not only a high initial discharge capacity of 155.3 mAh g-1 but also a good cycling stability, which retains 94% of the initial capacity over 100 cycles at 0.05 C.
Keywords: Carbon; Cathodes; Characterization; Electric batteries; Electrodes; Ethylene; Glucose; Liquids; Lithium; Nanoparticles; Nanorods; Particle size; Scanning electron microscopy; Secondary batteries; Transmission electron microscopy; X ray diffraction; Cath-ode materials; Crystalline structure; Electrochemical test; High crystallinity; Initial discharge capacities; Liquid-phase method; Lithium manganese phosphates; TEM characterization; Lithium-ion batteries

Facile synthesis of silver@carbon nanocable-supported platinum nanoparticles as high-performing electrocatalysts for glycerol oxidation in direct glycerol fuel cells - Bai, Zhengyu; Shi, Min; Zhang, Yanxing; Zhang, Qing; Yang, Lin; Yang, Zongxian; Zhang, Jiujun (Green Chemistry, 2015)
Novel Ag@C nanocables are successfully synthesized through a hydrothermal self-assembly process, and employed as the support material to fabricate a uniformly distributed Pt nanoparticle electrocatalyst (Pt/Ag@C) for glycerol oxidation reaction (GOR). Electrochemical measurements demonstrate that this Pt/Ag@C catalyst can have both superior electrocatalytic GOR activity and stability, confirming that the Ag@C nanocables should be a great material for supporting the catalyst. Theoretical calculations are also carried out for fundamental understanding of the enhanced catalytic performance of this Pt/Ag@C catalyst. The results show that this Pt/Ag@C catalyst should be a great candidate as the anode catalyst for direct glycerol fuel cells.

Electronic properties and electron-electron interactions in graphene quantum dots - Ozfidan, Isil; Korkusinski, Marek; Hawrylak, Pawel (Physica Status Solidi - Rapid Research Letters, 2015)
We review the electronic properties of graphene quantum dots (GQD) with emphasis on the role of electron-electron interactions. We describe the electronic properties using a combination of tight binding, Hartree-Fock (HF), density functional theory and configuration interaction methods applied to interacting electrons on pz orbitals of carbon atoms. The electron-electron interactions are computed using Slater orbitals and screened by the environment and sigma electrons. We show that the electronic properties of graphene can be tuned by the lateral size, shape, character of edge, number of layers and screening. In particular, the energy gap can be tuned from THz to UV by varying the size of graphene quantum dot. The dependence of the gap on the size can be understood in terms of confined Dirac fermions. The effect of edges and edge reconstruction is discussed using ab-initio techniques. The role of screening is investigated using the HF approach. HF ground states corresponding to semiconductor, Mott-insulator, and spin-polarized phases are obtained as a function of the strength of the screened Coulomb interactions. For GQDs in the semiconductor phase, the role of correlations in ground and excited states is computed perturbatively and shown to result in size dependent band gap renormalization.
Keywords: Binding energy; Bins; Carbon; Density functional theory; Electron-electron interactions; Electronic properties; Electrons; Energy gap; Ground state; Molecular physics; Nanocrystals; Quantum chemistry; Screening; Semiconductor quantum dots; Ab initio techniques; Band gap renormalization; Configuration interaction method; Electronic properties of graphene; Hartree-Fock methods; Interacting electrons; Screened Coulomb interaction; Tight-binding Hamiltonians; Graphene

Linking low- to high-mass young stellar objects with Herschel -HIFI observations of water - San José-García, I.; Mottram, J. C.; Van Dishoeck, E. F.; Kristensen, L. E.; Van Der Tak, F. F. S.; Braine, J.; Herpin, F.; Johnstone, D.; Van Kempen, T. A.; Wyrowski, F. (Astronomy and Astrophysics, 2015)
Context. Water probes the dynamics in young stellar objects (YSOs) effectively, especially shocks in molecular outflows. It is therefore a key molecule for exploring whether the physical properties of low-mass protostars can be extrapolated to massive YSOs, an important step in understanding the fundamental mechanisms regulating star formation. Aims. As part of the WISH key programme, we investigate excited water line properties as a function of source luminosity, in particular the dynamics and the excitation conditions of shocks along the outflow cavity wall. Methods. Velocity-resolved Herschel-HIFI spectra of the H2O 202-111 (988 GHz), 211-202 (752 GHz) and 312-303 (1097 GHz) lines were analysed, together with 12CO J = 10-9 and 16-15, for 52 YSOs with bolometric luminosities ranging from <1 to >105 L⊙. The H2O and 12CO line profiles were decomposed into multiple Gaussian components which are related to the different physical structures of the protostellar system. The non-LTE radiative transfer code radex was used to constrain the excitation conditions of the shocks along the outflow cavity. Results. The profiles of the three excited water lines are similar, indicating that they probe the same gas. Two main emission components are seen in all YSOs: a broad component associated with non-dissociative shocks in the outflow cavity wall ("cavity shocks") and a narrow component associated with the quiescent envelope material. More than 60% of the total integrated intensity in the excited water lines comes from the broad cavity shock component, while the remaining emission comes mostly from the envelope for low-mass Class I, intermediate- and high-mass objects, and dissociative "spot shocks" for low-mass Class 0 protostars. The widths of the water lines are surprisingly similar from low- to high-mass YSOs, whereas 12CO J = 10-9 line widths increase slightly with Lbol. The excitation analysis of the cavity shock component shows stronger 752 GHz emission for high-mass YSOs, most likely due to pumping by an infrared radiation field. Finally, a strong correlation with slope unity is measured between the logarithms of the total H2O line luminosity, LH2O, and Lbol, which can be extrapolated to extragalactic sources. This linear correlation, also found for CO, implies that both species primarily trace dense gas directly related to star formation activity. Conclusions. The water emission probed by spectrally unresolved data is largely due to shocks. Broad water and high-J CO lines originate in shocks in the outflow cavity walls for both low- and high-mass YSOs, whereas lower-J CO transitions mostly trace entrained outflow gas. The higher UV field and turbulent motions in high-mass objects compared to their low-mass counterparts may explain the slightly different kinematical properties of 12CO J = 10-9 and H2O lines from low- to high-mass YSOs.
Keywords: Dissociation; Dynamics; Extrapolation; Infrared radiation; Luminance; Molecules; Probes; Radiative transfer; Water piping systems; ISM: Kinematics and dynamics; ISM: molecules; Line: Profiles; Stars: formation; Stars: protostars; Stars

Aspects of detection and tracking of ground targets from an airborne EO/IR sensor - Balaji, Bhashyam; Sithiravel, Rajiv; Daya, Zahir; Kirubarajan, Thiagalingam (SPIE - International Society for Optical Engineering. Proceedings, 2015)
An airborne EO/IR (electro-optical/infrared) camera system comprises of a suite of sensors, such as a narrow and wide field of view (FOV) EO and mid-wave IR sensors. EO/IR camera systems are regularly employed on military and search and rescue aircrafts. The EO/IR system can be used to detect and identify objects rapidly in daylight and at night, often with superior performance in challenging conditions such as fog. There exist several algorithms for detecting potential targets in the bearing elevation grid. The nonlinear filtering problem is one of estimation of the kinematic parameters from bearing and elevation measurements from a moving platform. In this paper, we developed a complete model for the state of a target as detected by an airborne EO/IR system and simulated a typical scenario with single target with 1 or 2 airborne sensors. We have demonstrated the ability to track the target with 'high precision' and noted the improvement from using two sensors on a single platform or on separate platforms. The performance of the Extended Kalman filter (EKF) is investigated on simulated data. Image/video data collected from an IR sensor on an airborne platform are processed using an image tracking by detection algorithm.
Keywords: Aircraft detection; Cameras; Electrooptical devices; Extended Kalman filters; Infrared detectors; Nonlinear filtering; Signal detection; Airborne platforms; Detection and tracking; Image tracking; Kinematic parameters; Non-linear filtering problems; Search-and-rescue aircrafts; Sensor fusion; Wide field of view; Signal processing

Correspondence: In support of the IES method of evaluating light source colour rendition - Ashdown, I.; Avilés, G.; Bennett, L.; Burkett, R.; Choi, A.; Conway, K.; Deroos, M.; Druzik, J.; Gregory, P.; Herst, D.; Houser, K.; Innes, M.; et al. (Lighting Research and Technology, 2015)

Detection of infall in the protostar B335 with ALMA - Evans, Neal J.; Di Francesco, James; Lee, Jeong-Eun; Jørgensen, Jes K.; Choi, Minho; Myers, Philip C.; Mardones, Diego (The Astrophysical Journal, 2015)
Observations of the isolated globule B335 with ALMA have yielded absorption features against the continuum that are redshifted from the systemic velocity in both HCN and HCO+ lines. These features provide unambiguous evidence for infall toward a central luminosity source. Previously developed models of inside-out collapse can match the observed line profiles of HCN and HCO+ averaged over the central 50 AU. At the new distance of 100 pc, the inferred infall radius is 0.012 pc, the mass infall rate is 3 × 10-6 Mo yr-1, the age is 5 × 104 years, and the accumulated mass in the central zone is 0.15 , most of which must be in the star or in parts of a disk that are opaque at 0.8 mm. The continuum detection indicates an optically thin mass (gas and dust) of only 7.5 × 10-4 in the central region, consistent with only a very small disk mass.

THE ACS LCID project: On the origin of dwarf galaxy types - a manifestation of the halo assembly bias? - Gallart, Carme; Monelli, Matteo; Mayer, Lucio; Aparicio, Antonio; Battaglia, Giuseppina; Bernard, Edouard J.; Cassisi, Santi; Cole, Andrew A.; Dolphin, Andrew E.; Drozdovsky, Igor; Hidalgo, Sebastian L.; Navarro, Julio F.; et al. (The Astrophysical Journal Letters, 2015)
We discuss how knowledge of the whole evolutionary history of dwarf galaxies, including details on the early star formation events, can provide insight on the origin of the different dwarf galaxy types. We suggest that these types may be imprinted by the early conditions of formation rather than only being the result of a recent morphological transformation driven by environmental effects. We present precise star formation histories of a sample of Local Group dwarf galaxies, derived from color-magnitude diagrams reaching the oldest main-sequence turnoffs. We argue that these galaxies can be assigned to two basic types: fast dwarfs that started their evolution with a dominant and short star formation event and slow dwarfs that formed a small fraction of their stars early and have continued forming stars until the present time (or almost). These two different evolutionary paths do not map directly onto the present-day morphology (dwarf spheroidal versus dwarf irregular). Slow and fast dwarfs also differ in their inferred past location relative to the Milky Way and/or M31, which hints that slow dwarfs were generally assembled in lower-density environments than fast dwarfs. We propose that the distinction between a fast and slow dwarf galaxy primarily.

Influence of acidity and auxiliary electrode reaction on the oxidation of epinephrine on the pre-anodized carbon paste electrode - Li, Jing; Shangguan, Enbo; Guo, Dan; Gao, Fengli; Li, Quanmin; Yuan, Xiao-Zi; Wang, Haijiang (Electrochimica Acta, 2015)
In this paper, the influence mechanisms of the solution acidity and the auxiliary electrode reaction on the oxidation peak current of epinephrine (EP) were researched on a pre-anodized carbon paste electrode in a "U" shape electrolytic cell. By changing the solution acidity in the auxiliary electrode electrolytic cell (AEEC) or the working electrode electrolytic cell (WREEC), the electrochemical behaviors of EP in the WREEC was investigated by cyclic voltammetry. It is found that the magnitude of the oxidation peak current of EP is closely related to the solution acidity for both WREEC and AEEC. The effects of the supporting electrolyte, the reduction reaction at the auxiliary electrode, distribution of the EP species and the molecular configuration of EP on the oxidation peak current of EP were also explored. Furthermore, the reaction mechanisms for both cathode and anode were proposed and interpreted. With the provided electrode reaction mechanisms, optimized pH value can be chosen based on the distribution coefficients for future related researches. Satisfactory results have been achieved for the determination of EP in injection using these mechanisms.
Keywords: Acidity; Cyclic voltammetry; Electrodes; Electrolysis; Electrolytes; Electrolytic cells; Oxidation; Carbon paste electrode; Distribution coefficient; Electrochemical behaviors; Electrode reaction mechanisms; Epinephrine; Molecular configurations; Supporting electrolyte; U shape; Electrochemical electrodes

A functional genomics method for assaying gene function in phytopathogenic fungi through host-induced gene silencing mediated by agroinfiltration - Panwar, Vinay; McCallum, Brent; Bakkeren, Guus (Plant Gene Silencing: Methods and Protocols, 2015)
With the rapid growth of genomic information, there is an increasing demand for efficient analysis tools to study the function of predicted genes coded in genomes. Agroinfiltration, the delivery of gene constructs into plant cells by Agrobacterium tumefaciens infiltrated into leaves, is one such versatile, simple, and rapid technique that is increasingly used for transient gene expression assay in plants. In this chapter, we focus on the use of agroinfiltration as a functional genomics research tool in molecular plant pathology. Specifically, we describe in detail its use in expressing phytopathogenic fungal gene sequences in a host plant to induce RNA silencing of corresponding genes inside the pathogen, a method which has been termed host-induced gene silencing (HIGS). We target the fungal pathogen Puccinia triticina which causes leaf rust on its wheat host, but the method is applicable to a variety of pathosystems.

Electron-electron interactions, topological phase, and optical properties of a charged artificial benzene ring - Ozfidan, Isil; Vladisavljevic, Milos; Korkusinski, Marek; Hawrylak, Pawel (Physical Review B - Condensed Matter and Materials Physics, 2015)
We present a theory of the electronic and optical properties of a charged artificial benzene ring (ABR). The ABR is described by the extended Hubbard model solved using exact diagonalization methods in both real and Fourier space as a function of the tunneling matrix element t, Hubbard on-site repulsion U, and interdot interaction V. In the strongly interacting case, we discuss exact analytical results for the spectrum of the hole in a half-filled ABR dressed by the spin excitations of the remaining electrons. The spectrum is interpreted in terms of the appearance of a topological phase associated with an effective gauge field piercing through the ring. We show that the maximally spin-polarized (S=5/2) and maximally spin-depolarized (S=1/2) states are the lowest energy, orbitally nondegenerate, states. We discuss the evolution of the phase diagram and level crossings as interactions are switched off and the ground state becomes spin nondegenerate but orbitally degenerate S=1/2. We present a theory of optical absorption spectra and show that the evolution of the ground and excited states, level crossings, and presence of artificial gauge can be detected optically.

Molecular dynamics simulation of halogen bonding in Cl2, BrCl, and mixed Cl2/Br2 clathrate hydrates - Dureckova, Hana; Woo, Tom K.; Alavi, Saman; Ripmeester, John A. (Canadian Journal of Chemistry, 2015)
Clathrate hydrate phases of dihalogen molecules have properties that differ from those of other guest molecules of similar size. The water oxygen-chlorine distances in the structure I (sI) Cl2 hydrate are smaller than the sum of the van der Waals radii of oxygen and chlorine. Bromine hydrate forms a unique clathrate hydrate structure that is not seen in other guest substances. In mixed Cl2/Br2 structure I hydrate, the water oxygen-bromine distances are also smaller than the sum of the oxygen and bromine van der Waals radii. We previously studied the structure of three dihalogen clathrate hydrates using single crystal X-ray diffraction and described these structural features in terms of halogen bonding between the dihalogen and water molecules. In this work, we perform molecular dynamics simulations of cubic sI Cl2, mixed Cl2/Br2, and BrCl clathrate hydrate phases. We perform quantum chemical computations on the dihalogen molecules to determine the nature of σ-hole near the halogen atoms. We fit the electrostatic potential of the molecules to point charge models including dummy atoms that represent σ-holes adjacent to the halogen molecules. Molecular dynamics simulations are used to determine the lattice constants, radial distribution functions, and guest dynamics in these phases. We determine the effect of guest size and difference in halogen bonding on the properties of the clathrate hydrate phase. Simulations for the Cl2, BrCl, and mixed Cl2/Br2 hydrates are performed with small cages of the sI clathrate hydrate phases completely full or filled with experimental occupancies with Cl2 guests.
Keywords: Bromine; Chemical bonds; Chlorine; Crystal structure; Distribution functions; Hydration; Lattice constants; Molecular dynamics; Molecules; Oxygen; Quantum chemistry; Single crystals; Van der Waals forces; X ray diffraction; Clathrate hydrate; Electrostatic potentials; Halogen bonding; Molecular dynamics simulations; Quantum chemical computations; Radial distribution functions; Single crystal x-ray diffraction; Van der Waals radius; Hydrates

Vessel performance analysis and fuel management - Mak, Lawrence; Kuczora, Andrew; Seo, Dong Cheol; Sullivan, Michael (Proceedings of the International Conference on Offshore Mechanics and Arctic Engineering - OMAE, 2015)
A prototype Vessel Performance Monitoring and Analysis System (VPMAS) was deployed on a ferry to acquire needed performance data, to help improve vessel performance and reduce fuel consumption. A paper published in 2014 described preliminary data trends observed, key performance indicators computed, data products explored and exploratory tools developed for crews to gain insight into their vessel operation. The current paper describes further analysis of the operational data for speed optimization in calm sea states and the preliminary development of trim optimization software. It was found that trip durations around 7 hours (13.3 knots) use the least amount of fuel. The least amount of fuel is used when the excess distance travelled is minimized and the voyage time is optimized. There is a lot of leeway in terms of voyage time and excess distance travel by the ship before there is a heavy penalty on fuel consumption. Considering only a mean draft of 6 m and an average speed of 14 knots in the current paper, the optimal trim condition for the ferry is around -0.6 m (bow down), which reduces the resistance by 15% compared to the even keel condition. Positive trim causes the considerable increase of the total resistance consistently.
Keywords: Arctic engineering; Benchmarking; Ocean currents; Key performance indicators; Optimization software; Performance analysis; Performance data; Performance monitoring and analysis; Prototype vessels; Speed optimization; Vessel operations; Fuels

Behavior of the residual wave components in a 3D wave basin after the termination of the wave maker - Zaman, M. Hasanat; Mak, Lawrence; Millan, Jim; Kuczora, Andrew (ASME 2015 34th International Conference on Ocean, Offshore and Arctic Engineering: May 31-June 5, 2015, St. John's, Newfoundland, Canada, 2015)
After the termination of the wave making, the characteristics of the existing wave components in a 3D large scale Offshore Engineering wave Basin (OEB) at the National Research Council of Canada have been investigated experimentally. In the generation of any wave in the tank we get the relevant primary wave components along with bounded wave components if the incident primary wave has more than one frequency. Inevitably we also get interacted wave components, natural frequency components of the tank and other free waves. In this paper the tank's natural frequency components, bounded wave components and other free waves after the termination of wave making were investigated using several cases of mono- and bi-chromatic waves. These component energies were then compared with the total energy of the measured primary waves. The magnitudes of the residual undulations are also investigated for mono-, bi- and multichromatic waves over different time segments. Several sets of wave data are analysed to perceive the energy due to natural frequency of the basin, energy transferred to the side bands and the damping rate of the residual waves in the tank with respect to the chosen incident wave conditions. In the analysis it is observed that the energy damping rate varies with the incident wave condition but seems much faster than that of 20 minutes traditional waiting time in between two runs in the OEB. The energies for tank's natural frequency components and other free waves were found to be very small compare to the incident primary wave energies.
Keywords: Arctic engineering; Damping; Natural frequencies; Ocean engineering; Tanks (containers); Data comparisons; Mono; Natural energy; Physical experiments; Residual undulation over time; Arctic vehicles

A mechanism-based approach from low cycle fatigue to thermomechanical fatigue life prediction - Wu, Xijia; Zhang, Zhong (Proceedings of the ASME Turbo Expo, 2015)
Deformation and damage accumulation occur by fundamental dislocation and diffusion mechanisms. An integrated creep-fatigue theory (ICFT) has been developed, based on the physical strain decomposition rule that recognizes the role of each deformation mechanism and thus relate damage accumulation to its underlying physical mechanism(s). The ICFT formulates the overall damage accumulation as a holistic damage process consisting of nucleation and propagation of surface/subsurface cracks in coalescence with internally distributed damage/ discontinuities. These guiding principles run through both isothermal low cycle fatigue (LCF) and thermomechanical fatigue (TMF) under general conditions. This paper presents a methodology using mechanismbased constitutive equations to describe the cyclic stress strain curve and the non-linear damage accumulation equation incorporating i) rate-independent plasticity-induced fatigue, ii) intergranular embrittlement, iii) creep and iv) oxidation to predict LCF and TMF lives of ductile cast iron (DCI). The complication of the mechanisms and their interactions in this material provide a good demonstration case for the model, which is in good agreement with the experimental observations.
Keywords: Cast iron; Constitutive equations; Creep; Deformation; Fatigue of materials; Gas turbines; Stress-strain curves; Turbines; Cyclic stress strain curves; Diffusion mechanisms; Intergranular embrittlement; Isothermal low cycle fatigues; Rate-independent plasticities; Thermo mechanical fatigues (TMF); Fatigue damage

A review of electrolyte materials and compositions for electrochemical supercapacitors - Zhong, Cheng; Deng, Yida; Hu, Wenbin; Qiao, Jinli; Zhang, Lei; Zhang, Jiujun (Chemical Society Reviews, 2015)
Electrolytes have been identified as some of the most influential components in the performance of electrochemical supercapacitors (ESs), which include: electrical double-layer capacitors, pseudocapacitors and hybrid supercapacitors. This paper reviews recent progress in the research and development of ES electrolytes. The electrolytes are classified into several categories, including: aqueous, organic, ionic liquids, solid-state or quasi-solid-state, as well as redox-active electrolytes. Effects of electrolyte properties on ES performance are discussed in detail. The principles and methods of designing and optimizing electrolytes for ES performance and application are highlighted through a comprehensive analysis of the literature. Interaction among the electrolytes, electro-active materials and inactive components (current collectors, binders, and separators) is discussed. The challenges in producing high-performing electrolytes are analyzed. Several possible research directions to overcome these challenges are proposed for future efforts, with the main aim of improving ESs' energy density without sacrificing existing advantages (e.g., a high power density and a long cycle-life) (507 references).

Tabletop imaging using 266nm femtosecond laser pulses, for characterization of structural evolution in, single molecule, chemical reactions - Ibrahim, Heide; Wales, Benji; Beaulieu, Samuel; Schmidt, Bruno E.; Thiré, Nicolas; Bisson, Éric; Hebeisen, Christoph T.; Wanie, Vincent; Giguére, Mathieu; Kieffer, Jean-Claude; Spanner, Michael; Bandrauk, André D.; et al. (Journal of Physics: Conference Series, 2015)
We have demonstrated a generally applicable tabletop approach utilizing a 266nm femtosecond laser pulse pump, 800nm pulse probe, coupled with Coulomb explosion imaging (CEI). We have investigated two simple chemical reactions in C2H2 + simultaneously: proton transfer and C=C bond-breaking, triggered by multiphoton ionization to excited states. Too and fro proton migration results are in excellent agreement with new ab initio trajectory simulations which predict isomerization timescales and pathways.
Keywords: Chemical reactions; Isomerization; Laser pulses; Molecules; Optical pumping; Photoionization; Pumping (laser); Ultrafast lasers; Bond-breaking; Coulomb explosion imaging; Multiphoton ionization; Proton migration; Pulse-probe; Single molecule; Structural evolution; Trajectory simulation; Ultrashort pulses

Sub-wavelength cladding mid-infrared devices - Penades, Jordi Soler; Nedeljkovic, Milos; Khokhar, Ali Z.; Mashanovich, Goran Z.; Ortega-Monux, Alejandro; Wanguermert-Perez, Gonzalo; Halir, Robert; Molina-Fernandez, Inigo; Cheben, Pavel (IEEE International Conference on Group IV Photonics GFP, 2015)
Suspended structures enable low loss propagation in silicon waveguides for mid-infrared wavelengths by removing the lossy buried oxide (BOX) layer. We previously demonstrated suspended waveguides with a silicon core and a sub-wavelength grating (SWG) lateral cladding, which allows access to the buried oxide layer for under-etching with hydrofluoric acid. Here we show that bends, multimode interference couplers (MMI) and Mach-Zehnder interferometers (MZI) can be successfully implemented in this platform. Specifically, we report waveguides with propagation losses of 1.2 dB/cm, 90° bends with 0.03 dB/bend loss, compact MMI couplers with imbalances of 0.5 dB, and MZI structures with extinction ratios in excess of 24 dB.
Keywords: Diffraction gratings; Electric losses; Hydrofluoric acid; Photonics; Silicon on insulator technology; Waveguides; Buried oxide layers; Extinction ratios; Machzehnder interferometers (MZI); Mid-infrared devices; Mid-infrared wavelengths; Multimode interference couplers; Subwavelength grating; Suspended structure; Infrared devices

Magnetic fields in high-mass star-forming regions - Chrysostomou, Antonio; Houde, Martin; Matthews, Brenda C. (Polarimetry of Stars and Planetary Systems, 2015)
The correlation between giant molecular clouds (GMCs) and high-mass star formation (HMSF) is now well established (McKee and Ostriker 2007; Tan et al. 2014; Dobbs et al. 2014 and references therein). From the nearest cluster of high-mass stars and GMC, the Orion Nebula Cluster (390 pc; Sandstrom et al. 2007) to molecular clouds in external galaxies (e.g. Wilson et al. 2000; Sakamoto et al. 2007), the presence of OB stars and young clusters is clearly associated with molecular gas (Lada and Lada 2003). Unlike low-mass star formation, which can occur in relatively quiescent and even isolated clouds, the nature of HMSF requires a clustered, dense environment. This presents particular problems in attempting to understand HMSF as the nascent stars remain deeply embedded in their natal clouds for a few million years, and generally HMSF occurs at large distances from the Sun. The relatively short lifetime of high-mass stars (typically a few 106 years or less) means that they do not have the time to migrate significantly from their birthplace, so HMSF regions are often found adjacent to HII regions and photo-dissociation regions (PDRs), which make observations of the forming stars challenging at short wavelengths. At longer wavelengths (far-IR to millimeter), the optical nebula is not visible and the dust and gas associated with star formation can be studied directly. Furthermore, the formation of high-mass stars can have devastating effects on the surrounding molecular gas, such that the cloud may not survive to host subsequent epochs of star formation. For example, it has been established that clusters older than 5 Myr are not typically associated with molecular clouds, implying that molecular clouds do not survive the onset of star formation by more than 5–10 Myr (Leisawitz et al. 1989). Recent estimates of molecular cloud lifetimes in the LMC and M51 are ~25 Myr (Kawamura et al. 2009) and ~100 Myr (Koda et al. 2009), consistent with the earliest estimates of 10 8 yr (Scoville et al. 1979) based on the detection of GMCs in the inter-arm regions of the Milky Way.

Propidium monoazide (PMA) and ethidium bromide monoazide (EMA) improve DNA array and high-throughput sequencing of porcine reproductive and respiratory syndrome virus identification - Bellehumeur, Christian; Boyle, Brian; Charette, Steve J.; Harel, Josée; L'Homme, Yvan; Masson, Luke; Gagnon, Carl A. (Journal of Virological Methods, 2015)
Pan-viral DNA array (PVDA) and high-throughput sequencing (HTS) are useful tools to identify novel viruses of emerging diseases. However, both techniques have difficulties to identify viruses in clinical samples because of the host genomic nucleic acid content (hg/cont). Both propidium monoazide (PMA) and ethidium bromide monoazide (EMA) have the capacity to bind free DNA/RNA, but are cell membrane-impermeable. Thus, both are unable to bind protected nucleic acid such as viral genomes within intact virions. However, EMA/PMA modified genetic material cannot be amplified by enzymes. In order to assess the potential of EMA/PMA to lower the presence of amplifiable hg/cont in samples and improve virus detection, serum and lung tissue homogenates were spiked with porcine reproductive and respiratory virus (PRRSV) and were processed with EMA/PMA. In addition, PRRSV RT-qPCR positive clinical samples were also tested. EMA/PMA treatments significantly decreased amplifiable hg/cont and significantly increased the number of PVDA positive probes and their signal intensity compared to untreated spiked lung samples. EMA/PMA treatments also increased the sensitivity of HTS by increasing the number of specific PRRSV reads and the PRRSV percentage of coverage. Interestingly, EMA/PMA treatments significantly increased the sensitivity of PVDA and HTS in two out of three clinical tissue samples. Thus, EMA/PMA treatments offer a new approach to lower the amplifiable hg/cont in clinical samples and increase the success of PVDA and HTS to identify viruses.

The most massive ultra-compact dwarf galaxy in the Virgo cluster - Liu, Chengze; Peng, Eric W.; Toloba, Elisa; Mihos, J. Christopher; Ferrarese, Laura; Alamo-Martínez, Karla; Zhang, Hong-Xin; Côté, Patrick; Cuillandre, Jean-Charles; Cunningham, Emily C.; Guhathakurta, Puragra; Gwyn, Stephen; et al. (The Astrophysical Journal Letters, 2015)
We report on the properties of the most massive ultra-compact dwarf galaxy (UCD) in the nearby Virgo Cluster of galaxies using imaging from the Next Generation Virgo Cluster Survey and spectroscopy from Keck/DEIMOS. This object (M59-UCD3) appears to be associated with the massive Virgo galaxy M59 (NGC 4621), has an integrated velocity dispersion of 78 km s-1, a dynamical mass of 3.7 × 108M⊙ and an effective radius (Re) of 25 pc. With an effective surface mass density of 9.4 × 1010M⊙ kpc-2 it is the densest galaxy in the local universe discovered to date, surpassing the density of the luminous Virgo UCD, M60-UCD1. M59-UCD3 has a total luminosity of Mg = -14.2 mag, and a spectral energy distribution consistent with an old (14 Gyr) stellar population with [Fe/H] = 0.0 and [α/Fe]= +0.2. We also examine deep imaging around M59 and find a broad low surface brightness stream pointing toward M59-UCD3, which may represent a tidal remnant of the UCD progenitor. This UCD, along with similar objects like M60-UCD1 and M59cO, likely represents an extreme population of tidally stripped galaxies more akin to larger and more massive compact early-type galaxies than to nuclear star clusters in present-day dwarf galaxies.

Differences in defence responses of Pinus contorta and Pinus banksiana to the mountain pine beetle fungal associate Grosmannia clavigera are affected by water deficit - Arango-Velez, Adriana; El Kayal, Walid; Copeland, Charles C. J.; Zaharia, L. Irina; Lusebrink, Inka; Cooke, Janice E. K. (Plant, Cell and Environment, 2015)
We tested the hypotheses that responses to the mountain pine beetle fungal associate Grosmannia clavigera will differ between the evolutionarily co-evolved host lodgepole pine (Pinus contorta var. latifolia) and the naïve host jack pine (Pinus banksiana) and that these responses will be influenced by water availability. G.clavigera inoculation resulted in more rapid stem lesion development in lodgepole than in jack pine; water deficit delayed lesion development in both species. Decreased hydraulic conductivity was observed in inoculated lodgepole pine seedlings, likely because of tracheid occlusion by fungal hyphae and/or metabolite accumulation. Drought but not inoculation significantly impacted bark abscisic acid levels. Jasmonic and salicylic acid were implicated in local and systemic responses of both species to G.clavigera, with salicylic acid appearing to play a greater role in jack pine response to G.clavigera than lodgepole pine. Water deficit increased constitutive levels and/or attenuated induced responses to G.clavigera for several monoterpenes in lodgepole but not jack pine. Instead, inoculation of well-watered but not water deficit jack pine resulted in a greater number of xylem resin ducts. These findings reveal mechanisms underlying differences in G.clavigera-induced responses between lodgepole and jack pine hosts, and how water availability modulates these responses.

Direct imaging of an asymmetric debris disk in the HD 106906 planetary system - Kalas, P.G.; Rajan, A.; Wang, J.J.; Millar-Blanchaer, M.A.; Duchene, G.; Chen, C.; Fitzgerald, M.P.; Dong, R.; Graham, J.R.; Patience, J.; Macintosh, B.; Murray-Clay, R.; et al. (The Astrophysical Journal, 2015)
We present the first scattered light detections of the HD 106906 debris disk using the Gemini/Gemini Planet Imager in the infrared and Hubble Space Telescope (HST)/Advanced Camera for Surveys in the optical. HD 106906 is a 13 Myr old F5V star in the Sco-Cen association, with a previously detected planet-mass candidate HD 106906b projected 650 AU from the host star. Our observations reveal a near edge-on debris disk that has a central cleared region with radius ∼50 AU, and an outer extent >500 AU. The HST data show that the outer regions are highly asymmetric, resembling the "needle" morphology seen for the HD 15115 debris disk. The planet candidate is oriented ∼21° away from the position angle of the primary's debris disk, strongly suggesting non-coplanarity with the system. We hypothesize that HD 106906b could be dynamically involved in the perturbation of the primary's disk, and investigate whether or not there is evidence for a circumplanetary dust disk or cloud that is either primordial or captured from the primary. We show that both the existing optical properties and near-infrared colors of HD 106906b are weakly consistent with this possibility, motivating future work to test for the observational signatures of dust surrounding the planet. © 2015. The American Astronomical Society. All rights reserved..

MicroRNAs regulate the immunometabolic response to viral infection in the liver - Singaravelu, Ragunath; O'Hara, Shifawn; Jones, Daniel M.; Chen, Ran; Taylor, Nathan G.; Srinivasan, Prashanth; Quan, Curtis; Roy, Dominic G.; Steenbergen, Rineke H.; Kumar, Anil; Lyn, Rodney K.; Özcelik, Dennis; et al. (Nature Chemical Biology, 2015)
Immune regulation of cellular metabolism can be responsible for successful responses to invading pathogens. Viruses alter their hosts' cellular metabolism to facilitate infection. Conversely, the innate antiviral responses of mammalian cells target these metabolic pathways to restrict viral propagation. We identified miR-130b and miR-185 as hepatic microRNAs (miRNAs) whose expression is stimulated by 25-hydroxycholesterol (25-HC), an antiviral oxysterol secreted by interferon-stimulated macrophages and dendritic cells, during hepatitis C virus (HCV) infection. However, 25-HC only directly stimulated miR-185 expression, whereas HCV regulated miR-130b expression. Independently, miR-130b and miR-185 inhibited HCV infection. In particular, miR-185 significantly restricted host metabolic pathways crucial to the HCV life cycle. Interestingly, HCV infection decreased miR-185 and miR-130b levels to promote lipid accumulation and counteract 25-HC's antiviral effect. Furthermore, miR-185 can inhibit other viruses through the regulation of immunometabolic pathways. These data establish these microRNAs as a key link between innate defenses and metabolism in the liver.
Keywords: 25 hydroxycholesterol; microRNA; microRNA 130B; microRNA 185; unclassified drug; animal experiment; animal model; antiviral activity; controlled study; dendritic cell; gene expression; gene expression regulation; gene identification; gene repression; hepatitis C; Hepatitis C virus; human cell; human tissue; immunoregulation; lipid metabolism; lipid storage; liver metabolism; macrophage; metabolic regulation; microenvironment; mouse; nonhuman; virus immunity

The Next Generation Virgo Cluster Survey. X. Properties of ultra-compact dwarfs in the M87, M49, and M60 regions - Liu, Chengze; Peng, Eric W.; Côté, Patrick; Ferrarese, Laura; Jordán, Andrés; Mihos, J. Christopher; Zhang, Hong-Xin; Muñoz, Roberto P.; Puzia, Thomas H.; Lanɥon, Ariane; Gwyn, Stephen; Cuillandre, Jean-Charles; et al. (The Astrophysical Journal, 2015)
We use imaging from the Next Generation Virgo cluster Survey (NGVS) to present a comparative study of ultra-compact dwarf (UCD) galaxies associated with three prominent Virgo sub-clusters: those centered on the massive red-sequence galaxies M87, M49, and M60. We show how UCDs can be selected with high completeness using a combination of half-light radius and location in color-color diagrams (u∗iKs or u∗gz). Although the central galaxies in each of these sub-clusters have nearly identical luminosities and stellar masses, we find large differences in the sizes of their UCD populations, with M87 containing ∼3.5 and 7.8 times more UCDs than M49 and M60, respectively. The relative abundance of UCDs in the three regions scales in proportion to sub-cluster mass, as traced by X-ray gas mass, total gravitating mass, number of globular clusters (GCs), and number of nearby galaxies. We find that the UCDs are predominantly blue in color, with ∼85% of the UCDs having colors similar to blue GCs and stellar nuclei of dwarf galaxies. We present evidence that UCDs surrounding M87 and M49 may follow a morphological sequence ordered by the prominence of their outer, low surface brightness envelope, ultimately merging with the sequence of nucleated low-mass galaxies, and that envelope prominence correlates with distance from either galaxy. Our analysis provides evidence that tidal stripping of nucleated galaxies is an important process in the formation of UCDs.

Coherent control of photoelectron wavepacket angular interferograms - Hockett, P.; Wollenhaupt, M.; Baumert, T. (Journal of Physics B: Atomic, Molecular and Optical Physics, 2015)
Coherent control over photoelectron wavepackets, via the use of polarization-shaped laser pulses, can be understood as a time and polarization-multiplexed process, where the final (time-integrated) observable coherently samples all instantaneous states of the light-matter interaction. In this work, we investigate this multiplexing via computation of the observable photoelectron angular interferograms resulting from multi-photon atomic ionization with polarization-shaped laser pulses. We consider the polarization sensitivity of both the instantaneous and cumulative continuum wavefunction; the nature of the coherent control over the resultant photoelectron interferogram is thus explored in detail. Based on this understanding, the use of coherent control with polarization-shaped pulses as a methodology for a highly multiplexed coherent quantum metrology is also investigated, and defined in terms of the information content of the observable.
Keywords: Interferometry; Ionization; Laser pulses; Measurements; Multiphoton processes; Multiplexing; Photoelectrons; Photons; Polarization; Units of measurement; Wave packets; Coherent control; Information contents; Interferograms; Light-matter interactions; Polarization sensitivity; Quantum metrology; Shaped laser pulse; Shaped pulse; Photoionization

Iron boride-based thermal diffusion coatings for tribo-corrosion oil production applications - Medvedovski, Eugene; Jiang, Jiaren; Robertson, Mark (Ceramics International, 2015)
Engineering components and tubing systems for the down-hole applications in the oil production should withstand severe friction, sliding abrasion and corrosion actions. To resolve wear and corrosion issues, the hard iron boride-based coatings on steels obtained through the thermal diffusion process can be applied on the entire working surfaces of large size and complex shape products. The behavior of these coatings obtained at Endurance Technologies Inc. has been studied in the friction-abrasion, friction-corrosion and friction-abrasion-corrosion conditions simulating oil production service conditions. Tribological studies have been conducted using the "rod-on-flat" reciprocating sliding method in the conditions simulating actual application conditions. The synergistic actions of harsh conditions results in a higher rate of materials destruction. The obtained iron boride coatings demonstrated significantly lower wear losses with no delamination and spalling than untreated steels and Ni- and Cr-based coatings. The encouraging tribo-corrosion test results for boride coatings are explained by their high hardness and chemical inertness, specific structure obtained through the thermal diffusion process with reduced micro-crack propagation and the thin "tribofilm" formed during a friction mode. Successful application of the products with the boride protective coatings is reported.
Keywords: Abrasion; Borides; Coatings; Corrosion; Diffusion; Diffusion coatings; Failure (mechanical); Friction; Hard coatings; Iron; Iron compounds; Protective coatings; Thermal diffusion; Tribology; Wear resistance; Abrasion corrosion; Chemical inertness; Complex shapes; Engineering components; Reciprocating sliding; Sliding abrasion; Synergistic action; Tribo-corrosion; Boride coatings

The oxygenating constituent of 3,6-diketocamphane monooxygenase from the CAM plasmid of Pseudomonas putida: The first crystal structure of a type II Baeyer-Villiger monooxygenase - Isupov, Michail N.; Schröder, Ewald; Gibson, Robert P.; Beecher, Jean; Donadio, Giuliana; Saneei, Vahid; Dcunha, Stephlina A.; Mcghie, Emma J.; Sayer, Christopher; Davenport, Colin F.; Lau, Peter C.; Hasegawa, Yoshie; et al. (Acta Crystallographica Section D: Biological Crystallography, 2015)
The three-dimensional structures of the native enzyme and the FMN complex of the overexpressed form of the oxygenating component of the type II Baeyer-Villiger 3,6-diketocamphane monooxygenase have been determined to 1.9Å resolution. The structure of this dimeric FMN-dependent enzyme, which is encoded on the large CAM plasmid of Pseudomonas putida, has been solved by a combination of multiple anomalous dispersion from a bromine crystal soak and molecular replacement using a bacterial luciferase model. The orientation of the isoalloxazine ring of the FMN cofactor in the active site of this TIM-barrel fold enzyme differs significantly from that previously observed in enzymes of the bacterial luciferase-like superfamily. The Ala77 residue is in a cis conformation and forms a β-bulge at the C-terminus of β-strand 3, which is a feature observed in many proteins of this superfamily.

Surface segregation of Fe in Pt-Fe alloy nanoparticles: Its precedence and effect on the ordered-phase evolution during thermal annealing - Prabhudev, Sagar; Bugnet, Matthieu; Zhu, Guo-Zhen; Bock, Christina; Botton, Gianluigi A. (ChemCatChem, 2015)
Coupling electron microscopy techniques with insitu heating ability allows us to study phase transformations on the single-nanoparticle level. We exploit this setup to study disorder-to-order transformation of Pt-Fe alloy nanoparticles, a material that is of great interest to fuel-cell electrocatalysis and ultrahigh density information storage. In contrast to earlier reports, we show that Fe (instead of Pt) segregates towards the particle surface during annealing and forms a Fe-rich FeOx outer shell over the alloy core. By combining both exsitu and insitu approaches to probe the interplay between ordering and surface-segregation phenomena, we illustrate that the surface segregation of Fe precedes the ordering process and affects the ordered phase evolution dramatically. We show that the ordering initiates preferably at the pre-existent Fe-rich shell than the particle core. While the material-specific findings from this study open interesting perspectives towards a controlled phase evolution of Pt-Fe nanoalloys, the characterization methodologies described are general and should prove useful to probing a wide-range of nanomaterials. Surface-segregation vs atomic-ordering: By using atomic-resolution imaging and electron energy loss spectroscopy and employing both exsitu and insitu approaches, an ongoing interplay between segregation and ordering during the thermal annealing of Pt - Fe alloy nanoparticles is studied. Findings reveal a surface segregation of Fe that is in contrast to earlier reports suggesting Pt surface segregation.
Keywords: Annealing; Characterization; Electrocatalysis; Electron energy levels; Electron energy loss spectroscopy; Electron microscopes; Electron microscopy; Electron scattering; Energy dissipation; Fuel cells; Fuel storage; Image reconstruction; Iron; Nanoparticles; Phase transitions; Platinum; Platinum alloys; Segregation (metallography); Alloy nanoparticle; Atomic-resolution imaging; In-situ electron microscopy; Microscopy technique; Order transformation; Segregation phenomena; Single nanoparticle; Ultrahigh density information storage; Surface segregation

Global precipitation measurement cold season precipitation experiment (GCPEX): For measurement's sake, let it snow - Skofronick-Jackson, Gail; Hudak, David; Petersen, Walter; Nesbitt, Stephen W.; Chandrasekar, V.; Durden, Stephen; Gleicher, Kirstin J.; Huang, Gwo-Jong; Joe, Paul; Kollias, Pavlos; Reed, Kimberly A.; Schwhwaller, Mathew R.; et al. (Bulletin of the American Meteorological Society, 2015)
The GPM Cold Season Precipitation Experiment (GCPEx), a collaboration between NASA GPM ground validation (GV) program and its international partner, Environment Canada (EC), provided both new datasets and physical insights related to the snowfall process to ultimately improve falling-snow retrievals. The GCPEx field campaign occurred in Ontario, Canada, from 15 January to 3 March 2012. GCPEx collected microphysical properties, associated remote sensing observations, and coordinated model simulations of precipitating snow. The coordinated measurement strategy used stacked high-altitude GPM airborne remote sensing simulator instrumentation and in situ cloud aircraft flights with three research aircraft sampling within a broader network of five ground sites taking surface in situ and volumetric observations. Data collected during this field campaign exceeded all expectations, with measurements of heavy fluffy, non-melted, rate, moderate and light falling-snow rates, along with mixed-phase and rain cases. It is anticipated that the GCPEx dataset will satisfy the majority of GPM falling-snow retrieval algorithm validation objectives originally set forward for the experiment. These 3D datasets are suitable for conducting observational and modeling-based studies of bulk- and/or particle-scale snow microphysical and scattering properties observed at the ground, through the atmospheric column, and at high altitudes as observed from the vantage point of remote sensing instrumentation deployed on the GPM Core Observatory.
Keywords: Fighter aircraft; NASA; Precipitation (meteorology); Snow; Airborne remote sensing; Cold season precipitation; Coordinated modeling; Global precipitation measurements; International partners; Measurement strategies; Microphysical property; Snow retrieval algorithm; Remote sensing

Isothermal and cyclic oxidation performance of vertically cracked and columnar tbc structures produced using asps process - Li, Xiaolong; Huang, Xiao; Yang, Qi; Tang, Zhaolin (Proceedings of the ASME Turbo Expo, 2015)
Oxidation performance of thermal barrier coatings (TBCs) deposited by the axial suspension plasma spraying (ASPS) method was evaluated under isothermal and cyclic conditions with a peak temperature of 1080°C. The TBC systems are based on two nickel-based superalloy substrates (CMSX-4 and IN738LC), platinum aluminide bond coat, and yttria stabilized zirconia (8YSZ) top coat of either vertically cracked (VC) or columnar structure. Samples with IN738LC substrate exhibited longer isothermal oxidation lives whereas the ones with CMSX-4 substrate showed greater cyclic oxidation lives. Outward diffusion of W and Ta in TBC systems containing CMSX-4 was found to have progressed to the interface between TGO and top coat; this has contributed to the reduced isothermal oxidation life. The longer cyclic oxidation lives of TBC systems with CMSX-4 were attributed to less CTE mismatch between coating layers (reduced strain energy) and better creep resistance of diffusional bond coat on CMSX-4, hence less TGO rumpling. TBC systems with columnar YSZ had longer isothermal oxidation lives while those with vertically cracked YSZ seemed to result in longer cyclic lives.
Keywords: Coatings; Cracks; Creep resistance; Gas turbines; Isotherms; Oxidation; Plasma spraying; Strain energy; Substrates; Thermal barrier coatings; Thermal spraying; Turbines; Zirconia; Columnar structures; Cyclic conditions; Isothermal oxidations; Nickel- based superalloys; Outward diffusion; Platinum-aluminide bond coat; Suspension plasma spraying; Thermal barrier coating (TBCs); Yttria stabilized zirconia

Sr 88 + single-ion optical clock with a stability approaching the quantum projection noise limit - Dubé, Pierre; Madej, Alan A.; Shiner, Andrew; Jian, Bin (Physical Review A - Atomic, Molecular, and Optical Physics, 2015)
A number of optical frequency standards have been evaluated with fractional uncertainties between 10-17 and 10-18. Reduction of the statistical uncertainty of a clock comparison to this level is challenging, requiring the best possible stability to avoid excessively long averaging times. We report recent improvements of our Sr88+ single-ion standard that have reduced its 1-s Allan deviation from 1×10-14 to 3×10-15, yielding an order of magnitude decrease in averaging time for a given statistical uncertainty level. Among the improvements made are the implementation of a clear-out laser that transfers the ion from the metastable state to the ground state at each cycle, followed by a state preparation step that transfers the ion to the ground-state magnetic sublevel of the probed transition. With these changes, the ion clock transition interacts with the probe laser at every interrogation cycle. The stability of our optical standard is essentially limited by the quantum projection noise for pulse lengths up to ≈100 ms.
Keywords: Clocks; Frequency standards; Ground state; Allan deviation; Clock comparisons; Magnetic sublevels; Meta-stable state; Optical frequency standard; Optical standards; State preparation; Statistical uncertainty; Ions

VLBI for Gravity Probe B: The guide star, IM Pegasi - Bartel, N.; Bietenholz, M. F.; Lebach, D. E.; Ransom, R. R.; Ratner, M. I.; Shapiro, I. I. (Classical and Quantum Gravity, 2015)
We review the radio very long baseline interferometry (VLBI) observations of the guide star, IM Peg, and three compact extragalactic reference sources, made in support of the NASA/Stanford gyroscope relativity mission, Gravity Probe B (GP-B). The main goal of the observations was the determination of the proper motion of IM Peg relative to the distant Universe. VLBI observations made between 1997 and 2005 yield a proper motion of IM Peg of ± 0.09 mas yr-1 in α and ± 0.09 mas yr-1 in δ in a celestial reference frame of extragalactic radio galaxies and quasars virtually identical to the International Celestial Reference Frame 2 (ICRF2). They also yield a parallax for IM Peg of 10.37 ± 0.07 mas, corresponding to a distance of 96.4 ± 0.7 pc. The uncertainties are standard errors with statistical and estimated systematic contributions added in quadrature. These results met the pre-launch requirements of the GP-B mission to not discernibly degrade the estimates of the geodetic and frame-dragging effects.

Repression of lateral organ boundary genes by pennywise and pound-foolish is essential for meristem maintenance and flowering in Arabidopsis - Khan, Madiha; Ragni, Laura; Tabb, Paul; Salasini, Brenda C.; Chatfield, Steven; Datla, Raju; Lock, John; Kuai, Xiahez; Després, Charles; Proveniers, Marcel; Yongguo, Cao; Xiang, Daoquan; et al. (Plant Physiology, 2015)
In the model plant Arabidopsis (Arabidopsis thaliana), endogenous and environmental signals acting on the shoot apical meristem cause acquisition of inflorescence meristem fate. This results in changed patterns of aerial development seen as the transition from making leaves to the production of flowers separated by elongated internodes. Two related BEL1-like homeobox genes, PENNYWISE (PNY) and POUND-FOOLISH (PNF), fulfill this transition. Loss of function of these genes impairs stem cell maintenance and blocks internode elongation and flowering. We show here that pny pnf apices misexpress lateral organ boundary genes BLADE-ON-PETIOLE1/2 (BOP1/2) and KNOTTED-LIKE FROM ARABIDOPSIS THALIANA6 (KNAT6) together with ARABIDOPSIS THALIANA HOMEOBOX GENE1 (ATH1). Inactivation of genes in this module fully rescues pny pnf defects. We further show that BOP1 directly activates ATH1, whereas activation of KNAT6 is indirect. The pny pnf restoration correlates with renewed accumulation of transcripts conferring floral meristem identity, including FD, SQUAMOSA PROMOTER-BINDING PROTEIN LIKE genes, LEAFY, and APETALA1. To gain insight into how this module blocks flowering, we analyzed the transcriptome of BOP1-overexpressing plants. Our data suggest a central role for the microRNA156- SQUAMOSA PROMOTER BINDING PROTEIN-LIKE-microRNA172 module in integrating stress signals conferred in part by promotion of jasmonic acid biosynthesis. These data reveal a potential mechanism by which repression of lateral organ boundary genes by PNY-PNF is essential for flowering.

Optimization of rock berms for pipeline stabilization subject to intense hydrodynamic forcing - Cornett, Andrew; Baker, Scott; Riedel, Peter; Knox, Paul (Proceedings of the International Conference on Offshore Mechanics and Arctic Engineering - OMAE, 2015)
This article describes a comprehensive study in which 2D and 3D physical modelling at 1:40 scale was used to optimize the design and validate the performance of dynamically stable rock berms to be used for stabilizing several large pipelines traversing water depths from 5m to 65m and potentially exposed to large waves and strong currents generated by intense tropical cyclones. For added realism, all of the model rock berms were constructed using a scaled simulation of rock installation by fall pipe vessel to be used in the field. Special attention was also given to simulating the self-stability of the model pipeline segments, including special end constraints designed to mimic the behaviour of a continuous pipeline. A large data set concerning the behaviour of dynamically reshaping rock berms in a range of water depths under intense hydrodynamic forcing due to three-dimensional waves and currents was produced and used to develop efficient and costeffective rock berm designs for all depth zones.
Keywords: Arctic engineering; Fluid dynamics; Hydrodynamics; Pipelines; Storms; Hydrodynamic forcing; Large datasets; Physical modelling; Pipeline segments; Pipeline stabilization; Strong currents; Tropical cyclone; Waves and currents; Rocks

Multi-channel electronic and vibrational dynamics in polyatomic resonant high-order harmonic generation - Ferré, A.; Boguslavskiy, A. E.; Dagan, M.; Blanchet, V.; Bruner, B. D.; Burgy, F.; Camper, A.; Descamps, D.; Fabre, B.; Fedorov, N.; Gaudin, J.; Geoffroy, G.; et al. (Nature Communications, 2015)
High-order harmonic generation in polyatomic molecules generally involves multiple channels of ionization. Their relative contribution can be strongly influenced by the presence of resonances, whose assignment remains a major challenge for high-harmonic spectroscopy. Here we present a multi-modal approach for the investigation of unaligned polyatomic molecules, using SF6 as an example. We combine methods from extreme-ultraviolet spectroscopy, above-threshold ionization and attosecond metrology. Fragment-resolved above-threshold ionization measurements reveal that strong-field ionization opens at least three channels. A shape resonance in one of them is found to dominate the signal in the 20-26 eV range. This resonance induces a phase jump in the harmonic emission, a switch in the polarization state and different dynamical responses to molecular vibrations. This study demonstrates a method for extending high-harmonic spectroscopy to polyatomic molecules, where complex attosecond dynamics are expected.
Keywords: ionization; polarization; ultraviolet spectroscopy; vibration

Covalent functionalization of boron nitride nanotubes via reduction chemistry - Shin, Homin; Guan, Jingwen; Zgierski, Marek Z.; Kim, Keun S.; Kingston, Christopher T.; Simard, Benoit (ACS Nano, 2015)
Boron nitride nanotubes (BNNTs) exhibit a range of properties that hold great potential for many fields of science and technology; however, they have inherently low chemical reactivity, making functionalization for specific applications difficult. Here we propose that covalent functionalization of BNNTs via reduction chemistry could be a highly promising and viable strategy. Through density functional theory calculations of the electron affinity of BNNTs and their binding energies with various radicals, we reveal that their chemical reactivity can be significantly enhanced via reducing the nanotubes (i.e., negatively charging). For example, a 5.5-fold enhancement in reactivity of reduced BNNTs toward NH2 radicals was predicted relative to their neutral counterparts. The localization characteristics of the BNNT π electron system lead the excess electrons to fill the empty p orbitals of boron sites, which promote covalent bond formation with an unpaired electron from a radical molecule. In support of our theoretical findings, we also experimentally investigated the covalent alkylation of BNNTs via reduction chemistry using 1-bromohexane. The thermogravimetric measurements showed a considerable weight loss (12-14%) only for samples alkylated using reduced BNNTs, suggesting their significantly improved reactivity over neutral BNNTs. This finding will provide an insight in developing an effective route to chemical functionalization of BNNTs.
Keywords: Binding energy; Boron nitride; Chemical bonds; Electron affinity; Electrons; Nanotubes; Nitrides; Boron nitride nanotubes; Boron nitride nanotubes (BNNTs); Chemical functionalization; Covalent bond formation; Covalent functionalizations; Science and Technology; Thermogravimetric measurement; Unpaired electrons; Density functional theory

Astrometric confirmation and preliminary orbital parameters of the young exoplanet 51 Eridani b with the Gemini Planet Imager - De Rosa, Robert J.; Nielsen, Eric L.; Blunt, Sarah C.; Graham, James R.; Konopacky, Quinn M.; Marois, Christian; Pueyo, Laurent; Rameau, Julien; Ryan, Dominic M.; Wang, Jason J.; Bailey, Vanessa; Chontos, Ashley; et al. (The Astrophysical Journal Letters, 2015)
We present new Gemini Planet Imager observations of the young exoplanet 51 Eridani b that provide further evidence that the companion is physically associated with 51 Eridani. Combining this new astrometric measurement with those reported in the literature, we significantly reduce the posterior probability that 51 Eridani b is an unbound foreground or background T-dwarf in a chance alignment with 51 Eridani to 2 × 10-7, an order of magnitude lower than previously reported. If 51 Eridani b is indeed a bound object, then we have detected orbital motion of the planet between the discovery epoch and the latest epoch. By implementing a computationally efficient Monte Carlo technique, preliminary constraints are placed on the orbital parameters of the system. The current set of astrometric measurements suggest an orbital semimajor axis of AU, corresponding to a period of years (assuming a mass of 1.75 Mo for the central star), and an inclination of deg. The remaining orbital elements are only marginally constrained by the current measurements. These preliminary values suggest an orbit that does not share the same inclination as the orbit of the distant M-dwarf binary, GJ 3305, which is a wide physically bound companion to 51 Eridani.

Discovery and spectroscopy of the young jovian planet 51 Eri b with the Gemini Planet Imager - Macintosh, B.; Graham, J. R.; Barman, T.; De Rosa, R. J.; Konopacky, Q.; Marley, M. S.; Marois, C.; Nielsen, E. L.; Pueyo, L.; Rajan, A.; Rameau, J.; Saumon, D.; et al. (Science, 2015)
Directly detecting thermal emission from young extrasolar planets allows measurement of their atmospheric compositions and luminosities, which are influenced by their formation mechanisms. Using the Gemini Planet Imager, we discovered a planet orbiting the ∼20-million-year-old star 51 Eridani at a projected separation of 13 astronomical units. Near-infrared observations show a spectrum with strong methane and water-vapor absorption. Modeling of the spectra and photometry yields a luminosity (normalized by the luminosity of the Sun) of 1.6 to 4.0 × 10-6 and an effective temperature of 600 to 750 kelvin. For this age and luminosity, "hot-start" formation models indicate a mass twice that of Jupiter. This planet also has a sufficiently low luminosity to be consistent with the "cold-start" core-accretion process that may have formed Jupiter.
Keywords: methane; absorption; astronomy; imaging method; Jupiter; methane; planet; planetary evolution; spectroscopy; air temperature; contrast; Gemini Planet Imager; luminance; molecular weight; near infrared spectroscopy; photometry; priority journal; sun; telescope; water vapor

Hysteresis free carbon nanotube thin film transistors comprising hydrophobic dielectrics - Lefebvre, J.; Ding, J.; Li, Z.; Cheng, F.; Du, N.; Malenfant, P. R. L. (Applied Physics Letters, 2015)
We present two examples of carbon nanotube network thin film transistors with strongly hydrophobic dielectrics comprising either Teflon-AF or a poly(vinylphenol)/poly(methyl silsesquioxane) (PVP/pMSSQ) blend. In the absence of encapsulation, bottom gated transistors in air ambient show no hysteresis between forward and reverse gate sweep direction. Device threshold gate voltage and On-current present excellent time dependent stability even under dielectric stress. Furthermore, threshold gate voltage for hole conduction is negative upon device encapsulation with PVP/pMSSQ enabling much improved current On/Off ratio at 0 V. This work addresses two major challenges impeding solution based fabrication of relevant thin film transistors with printable single-walled carbon nanotube channels.
Keywords: Dielectric materials; Hydrophobicity; Hysteresis; Nanotubes; Single-walled carbon nanotubes (SWCN); Thin film transistors; Thin films; Threshold elements; Threshold voltage; Transistors; Device encapsulations; Dielectric stress; Hole conduction; Hysteresis free; Methyl silsesquioxanes; Polyvinylphenol; Threshold gate voltage; Carbon nanotubes

Tribenuron-methyl induces male sterility through anther-specific inhibition of acetolactate synthase leading to autophagic cell death - Zhao, Lun; Jing, Xue; Chen, Li; Liu, Yingjun; Su, Yanan; Liu, Tingting; Gao, Changbin; Yi, Bin; Wen, Jing; Ma, Chaozhi; Tu, Jinxing; Zou, Jitao; et al. (Molecular Plant, 2015)
Tribenuron-methyl (TM) is a powerful sulfonylurea herbicide that inhibits branched-chain amino acid (BCAA) biosynthesis by targeting the catalytic subunit (CSR1) of acetolactate synthase (ALS). Selective induction of male sterility by foliar spraying of TM at low doses has been widely used for hybrid seed production in rapeseed (Brassica napus); however, the underlying mechanism remains unknown. Here, we report greater TM accumulation and subsequent stronger ALS inhibition and BCAA starvation in anthers than in leaves and stems after TM application. Constitutive or anther-specific expression of. csr1-1D (a. CSR1 mutant) eliminated anther-selective ALS inhibition and reversed the TM-induced male sterile phenotype in both rapeseed and. Arabidopsis. The results of TM daub-stem experiments, combined with the observations of little TM accumulation in anthers and reversion of TM-induced male sterility by targeted expression of the TM metabolism gene. Bel in either the mesophyll or phloem, suggested that foliar-sprayed TM was polar-transported to anthers mainly through the mesophyll and phloem. Microscopy and immunoblotting revealed that autophagy, a bulk degradation process induced during cell death, was elevated in TM-induced male sterile anthers and by anther-specific knockdown of. ALS. Moreover, TM-induced pollen abortion was significantly inhibited by the autophagy inhibitor 3-MA. These data suggested that TM was polar-transported to anthers, resulting in BCAA starvation via anther-specific ALS inhibition and, ultimately, autophagic cell death in anthers. This paper reports that inhibition of ALS activity in anther by TM could cause BCAA starvation, resulting in autophagy in anther cells and leading to male sterility. The results could provide new insights into the mechanism underlying TM-induced male sterility, and have great application potential in crop hybrid seed production.

Possible link between the power spectrum of interstellar filaments and the origin of the prestellar core mass function - Roy, A.; Andre, P.; Arzoumanian, D.; Peretto, N.; Palmeirim, P.; Konyves, V.; Schneider, N.; Benedettini, M.; Di Francesco, J.; Elia, D.; Hill, T.; Ladjelate, B.; et al. (Astronomy and Astrophysics, 2015)
A complete understanding of the origin of the prestellar core mass function (CMF) is crucial. Two major features of the prestellar CMF are 1) a broad peak below 1 M⊙, presumably corresponding to a mean gravitational fragmentation scale, and 2) a characteristic power-law slope, very similar to the Salpeter slope of the stellar initial mass function (IMF) at the high-mass end. While recent Herschel observations have shown that the peak of the prestellar CMF is close to the thermal Jeans mass in marginally supercritical filaments, the origin of the power-law tail of the CMF/IMF at the high-mass end is less clear. In 2001, InutsGBRa proposed a theoretical scenario in which the origin of the power-law tail can be understood as resulting from the growth of an initial spectrum of density perturbations seeded along the long axis of star-forming filaments by interstellar turbulence. Here, we report the statistical properties of the line-mass fluctuations of filaments in the Pipe, Taurus, and IC 5146 molecular clouds observed with Herschel for a sample of subcritical or marginally supercritical filaments using a 1D power spectrum analysis. The observed filament power spectra were fitted by a power-law function (Ptrue(s) ∝ sα) after removing the effect of beam convolution at small scales. A Gaussian-like distribution of power-spectrum slopes was found, centered at αcorr =-1.6 ± 0.3 The characteristic index of the observed power spectra is close to that of the 1D velocity power spectrum generated by subsonic Kolomogorov turbulence (-1.67). Given the errors, the measured power-spectrum slope is also marginally consistent with the power spectrum index of-2 expected for supersonic compressible turbulence. With such a power spectrum of initial line-mass fluctuations, InutsGBRa's model would yield a mass function of collapsed objects along filaments approaching dN/dM ∝ M-2.3 ± 0.1 at the high-mass end (very close to the Salpeter power law) after a few free-fall times. An empirical correlation, P0.5(s0) ∝ 〈NH2〉 1.4 ± 0.1, was also found between the amplitude of each filament power spectrum P(s0) and the mean column density along the filament 〈NH2〉. Finally, the dispersion of line-mass fluctuations along each filament sMline was found to scale with the physical length L of the filament roughly as σMline ∝ L0.7. Overall, our results are consistent with the suggestion that the bulk of the CMF/IMF results from the gravitational fragmentation of filaments.
Keywords: Functions; Power spectrum; Spectrum analysis; Stars; Turbulence; Characteristic indices; Compressible turbulence; Empirical correlations; Evolution; Gaussian-like distributions; ISM: structure; Mass functions; Stars: formation; Gravitation

Multi-Toxin Resistance Enables Pink Bollworm Survival on Pyramided Bt Cotton - Fabrick, Jeffrey A.; Unnithan, Gopalan C.; Yelich, Alex J.; DeGain, Ben; Masson, Luke; Zhang, Jie; Carrière, Yves; Tabashnik, Bruce E. (Scientific Reports, 2015)
Transgenic crops producing Bacillus thuringiensis (Bt) proteins kill key insect pests, providing economic and environmental benefits. However, the evolution of pest resistance threatens the continued success of such Bt crops. To delay or counter resistance, transgenic plant "pyramids" producing two or more Bt proteins that kill the same pest have been adopted extensively. Field populations of the pink bollworm (Pectinophora gossypiella) in the United States have remained susceptible to Bt toxins Cry1Ac and Cry2Ab, but field-evolved practical resistance to Bt cotton producing Cry1Ac has occurred widely in India. Here we used two rounds of laboratory selection to achieve 18,000- to 150,000-fold resistance to Cry2Ab in pink bollworm. Inheritance of resistance to Cry2Ab was recessive, autosomal, conferred primarily by one locus, and independent of Cry1Ac resistance. We created a strain with high resistance to both toxins by crossing the Cry2Ab-resistant strain with a Cry1Ac-resistant strain, followed by one selection with Cry2Ab. This multi-toxin resistant strain survived on field-collected Bt cotton bolls producing both toxins. The results here demonstrate the risk of evolution of resistance to pyramided Bt plants, particularly when toxins are deployed sequentially and refuges are scarce, as seen with Bt cotton and pink bollworm in India.

A gateway to the brain: Shuttles for brain delivery of macromolecules - Webster, Carl I.; Stanimirovic, Danica B. (Therapeutic Delivery, 2015)
Keywords: antibody; bispecific antibody; antigen binding; blood brain barrier; cell function; central nervous system; clinical trial (topic); complement dependent cytotoxicity; cytoplasm; drug delivery system; endothelium cell; internalization; macromolecule; nonhuman; protein engineering; reticulocyte; signal transduction; transcytosis

Burst predicting neurons survive an in vitro glutamate injury model of cerebral ischemia - Kuebler, Eric S.; Tauskela, Joseph S.; Aylsworth, Amy; Zhao, Xigeng; Thivierge, Jean-Philippe (Scientific Reports, 2015)
Neuronal activity in vitro exhibits network bursts characterized by brief periods of increased spike rates. Recent work shows that a subpopulation of neurons reliably predicts the occurrence of network bursts. Here, we examined the role of burst predictors in cultures undergoing an in vitro model of cerebral ischemia. Dissociated primary cortical neurons were plated on multielectrode arrays and spontaneous activity was recorded at 17 days in vitro (DIV). This activity was characterized by neuronal avalanches where burst statistics followed a power law. We identified burst predictors as channels that consistently fired immediately prior to network bursts. The timing of these predictors relative to bursts followed a skewed distribution that differed sharply from a null model based on branching ratio. A portion of cultures were subjected to an excitotoxic insult (DIV 18). Propidium iodine and fluorescence imaging confirmed cell death in these cultures. While the insult did not alter the distribution of avalanches, it resulted in alterations in overall spike rates. Burst predictors, however, maintained baseline levels of activity. The resilience of burst predictors following excitotoxic insult suggests a key role of these units in maintaining network activity following injury, with implications for the selective effects of ischemia in the brain.

Activity-based profiling of the proteasome pathway during hepatitis C virus infection - Nasheri, Neda; Ning, Zhibin; Figeys, Daniel; Yao, Shao; Goto, Natalie K.; Pezacki, John Paul (Proteomics, 2015)
Hepatitis C virus (HCV) infection often leads to chronic hepatitis, liver cirrhosis, and hepatocellular carcinoma. The stability of the HCV proteins is controlled by ubiquitin-dependent and ubiquitin-independent proteasome pathways. Many viruses modulate proteasome function for their propagation. To examine the interrelationship between HCV and the proteasome pathways we employed a quantitative activity-based protein profiling method. Using this approach we were able to quantify the changes in the activity of several proteasome subunits and found that proteasome activity is drastically reduced by HCV replication. The results imply a link between the direct downregulation of the activity of this pathway and chronic HCV infection.
Keywords: proteasome; ubiquitin; virus protein; chronic hepatitis C; controlled study; down regulation; Hepatitis C virus; protein expression; protein subunit; quantitative analysis; virus replication

Bridging the gap: Fostering competitiveness in the Canadian biobased industry - Johnston, James B. (Industrial Biotechnology, 2015)

Tropospheric Emission Spectrometer (TES) satellite observations of ammonia, methanol, formic acid, and carbon monoxide over the Canadian oil sands: Validation and model evaluation - Shephard, M. W.; McLinden, C. A.; Cady-Pereira, K. E.; Luo, M.; Moussa, S. G.; Leithead, A.; Liggio, J.; Staebler, R. M.; Akingunola, A.; Makar, P.; Lehr, P.; Zhang, J.; et al. (Atmospheric Measurement Techniques, 2015)
The wealth of air quality information provided by satellite infrared observations of ammonia (NH3), carbon monoxide (CO), formic acid (HCOOH), and methanol (CH3OH) is currently being explored and used for a number of applications, especially at regional or global scales. These applications include air quality monitoring, trend analysis, emissions, and model evaluation. This study provides one of the first direct validations of Tropospheric Emission Spectrometer (TES) satellite-retrieved profiles of NH3, CH3OH, and HCOOH through comparisons with coincident aircraft profiles. The comparisons are performed over the Canadian oil sands region during the intensive field campaign (August-September, 2013) in support of the Joint Canada-Alberta Implementation Plan for Oil Sands Monitoring (JOSM). The satellite/aircraft comparisons over this region during this period produced errors of (i) +0.08 ± 0.25 ppbv for NH3, (ii) +7.5 ± 23 ppbv for CO, (iii) +0.19 ± 0.46 ppbv for HCOOH, and (iv) -1.1 ± 0.39 ppbv for CH3OH. These values mostly agree with previously estimated retrieval errors; however, the relatively large negative bias in CH3OH and the significantly greater positive bias for larger HCOOH and CO values observed during this study warrant further investigation. Satellite and aircraft ammonia observations during the field campaign are also used in an initial effort to perform preliminary evaluations of Environment Canada's Global Environmental Multi-scale - Modelling Air quality and CHemistry (GEM-MACH) air quality modelling system at high resolution (2.5 × 2.5 km2). These initial results indicate a model underprediction of ∼ 0.6 ppbv (∼ 60 %) for NH3, during the field campaign period. The TES/model CO comparison differences are ∼ +20 ppbv (∼ +20 %), but given that under these conditions the TES/aircraft comparisons also show a small positive TES CO bias indicates that the overall model underprediction of CO is closer to ∼ 10 % at 681 hPa (∼ 3 km) during this period.

Improving load signal and fatigue life estimation for helicopter components using computational intelligence techniques - Cheung, Catherine; Valdés, Julio J.; Puthuparampil, Jobin (Studies in Computational Intelligence, 2015)
The accurate estimation of helicopter component loads is an important factor in life cycle management and life extension efforts. This chapter explores continued efforts to utilize a number of computational intelligence algorithms, statistical and machine learning techniques, such as artificial neural networks, evolutionary algorithms, fuzzy sets, residual variance analysis, and others, to estimate some of these helicopter dynamic loads. For load prediction using indirect computational methods to be practical and accepted, demonstrating slight over-prediction of these loads is preferable to ensure that the impact of the actual load cycles is captured by the prediction and to incorporate a factor of safety. Subsequent calculation of the component’s fatigue life can verify the slight over-prediction of the load signal. This chapter examines a number of techniques for encouraging slight over-prediction and favoring a conservative estimate for these loads. Estimates for the main rotor normal bending on the Australian S-70-A-9 Black Hawk helicopter during a left rolling pullout at 1.5 g manoeuvre were generated from an input set consisting of thirty standard flight state and control system parameters. The results of this work show that when using a combination of these techniques, a reduction in under-prediction and increase in over-prediction can be achieved. In addition to load signal estimation, the component’s fatigue life and load exceedances can be estimated from the predicted load signal. In helicopter life cycle management, these metrics are more useful performance measures (as opposed to mean squared error or correlation of the load signal), therefore this chapter describes the process followed to calculate these measures from the load signal using Rainflow counting, material specific fatigue data (S-N curves), and damage theory. An evaluation of the proposed techniques based on the fatigue life estimates and/or load exceedances is also made.

Visualization of handwritten signatures based on haptic information - Valdés, Julio J.; Alsulaiman, Fawaz A.; El Saddik, Abdulmotaleb (Studies in Computational Intelligence, 2015)
The problem of user authentication is a crucial component of many solutions related to defense and security. The identification and verification of users allows the implementation of technologies and services oriented to the intended user and to prevent misuse by illegitimate users. It has become an essential part of many systems and it is used in several applications, particularly in the military. The handwritten signature is an element intrinsically endowed with specificity related to an individual and it has been used extensively as a key element in identification/authentication. Haptic technologies allow the use of additional information like kinesthetic and tactile feedback from the user, thus providing new sources of biometric information that can be incorporated within the process in addition to the traditional image-based sources. While work had been done on using haptic information for the analysis of handwritten signatures, most efforts have been oriented to the direct use ofmachine learning techniques for identification/verification. Comparatively fewer targeted information visualization and understanding the internal structure of the data. Here a variety of techniques are used for obtaining representations of the data in low dimensional spaces amenable to visual inspection (two and three dimensions). The approach is unsupervised, although for illustration and comparison purposes, class information is used as qualitative reference. Estimations of the intrinsic dimension for the haptic data are obtained which shows that low dimensional subspaces contains most of the data structure. Implicit and explicit mappings techniques transforming the original high dimensional data to lowdimensional spaces are considered. They include linear and nonlinear, classical and computational intelligence based methods: Principal Components, Sammon mapping, Isomap, Locally Linear Embedding, Spectral Embedding, t-Distributed StochasticNeighbour Embedding, Generative Topographic Mapping, Neuroscale and Genetic Programming. They provided insight about common and specific characteristics found in haptic signatures, their within/among subjects variability and the important role of certain types of haptic variables. The results obtained suggest ways how to design new representations for identification and verification procedures using tactile devices.

Choline supplementation restores substrate balance and alleviates complications of Pcyt2 deficiency - Schenkel, Laila C.; Sivanesan, Sugashan; Zhang, Junzeng; Wuyts, Birgitte; Taylor, Adrian; Verbrugghe, Adronie; Bakovic, Marica (Journal of Nutritional Biochemistry, 2015)
Choline plays a critical role in systemic lipid metabolism and hepatic function. Here we conducted a series of experiments to investigate the effect of choline supplementation on metabolically altered Pcyt2+/- mice. In Pcyt2+/- mice, the membrane phosphatidylethanolamine (PE) turnover is reduced and the formation of fatty acids (FA) and triglycerides (TAG) increased, resulting in hypertriglyceridemia, liver steatosis and obesity. One month of choline supplementation reduced the incorporation of FA into TAG and facilitated TAG degradation in Pcyt2+/- adipocytes, plasma and liver. Choline particularly stimulated adipocyte and liver TAG lipolysis by specific lipases (ATGL, LPL and HSL) and inhibited TAG formation by DGAT1 and DGAT2. Choline also activated the liver AMPK and mitochondrial FA oxidation gene PPARα and reduced the FA synthesis genes SREBP1, SCD1 and FAS. Liver (HPLC) and plasma (tandem mass spectroscopy and 1H-NMR) metabolite profiling established that Pcyt2+/- mice have reduced membrane cholesterol/sphingomyelin ratio and the homocysteine/methionine cycle that were improved by choline supplementation. These data suggest that supplementary choline is beneficial for restoring FA and TAG homeostasis under conditions of obesity caused by impaired PE synthesis.
Keywords: choline; fatty acid; homocysteine; phosphatidylethanolamine; sphingomyelin; triacylglycerol; adipocyte; animal experiment; diet therapy; enzyme deficiency; fatty liver; gene control; hypertriglyceridemia; lipid oxidation; liver function; male; mouse; nonhuman; obesity; phosphoethanolamine cytidylyltransferase 2 deficiency; phosphoethanolamine cytidylyltransferase 2 deficiency; supplementation; synthesis; triacylglycerol blood level; turnover time

Subwavelength index engineered surface grating coupler with sub-decibel efficiency for 220-nm silicon-on-insulator waveguides - Benedikovic, Daniel; Cheben, Pavel; Schmid, Jens H.; Xu, Dan-Xia; Lamontagne, Boris; Wang, Shurui; Lapointe, Jean; Halir, Robert; Ortega-Moñux, Alejandro; Janz, Siegfried; Dado, Milan (Optics Express, 2015)
Surface grating couplers are fundamental components in chip-based photonic devices to couple light between photonic integrated circuits and optical fibers. In this work, we report on a grating coupler with sub-decibel experimental coupling efficiency using a single etch process in a standard 220-nm silicon-on-insulator (SOI) platform. We specifically demonstrate a subwavelength metamaterial refractive index engineered nanostructure with backside metal reflector, with the measured peak fiber-chip coupling efficiency of -0.69 dB (85.3%) and 3 dB bandwidth of 60 nm. This is the highest coupling efficiency hitherto experimentally achieved for a surface grating coupler implemented in 220-nm SOI platform.
Keywords: Efficiency; Optical fibers; Photonic devices; Photonic integration technology; Refractive index; Engineered surfaces; Fiber chip coupling; Fundamental component; Photonic integrated circuits; Silicon on insulator waveguide; Silicon-on- insulators (SOI); Single etch process; Surface grating couplers; Silicon on insulator technology

Suzaku monitoring of the Wolf-Rayet binary WR 140 around periastron passage: An approach for quantifying the wind parameters - Sugawara, Yasuharu; Maeda, Yoshitomo; Tsuboi, Yohko; Hamaguchi, Kenji; Corcoran, Michael; Pollock, Andy M. T.; Moffat, Anthony F. J.; Williams, Peredur M.; Dougherty, Sean; Pittard, Julian (Publications of the Astronomical Society of Japan, 2015)
Suzaku observations of the Wolf-Rayet (W-R) binary WR 140 (WC7pd+O5.5fc) were made at four different times around periastron passage in 2009 January. The spectra changed in shape and flux with the phase. As periastron approached, the column density of the low-energy absorption increased, which indicates that the emission from the wind-wind collision plasma was absorbed by the dense W-R wind. The spectra can be mostly fitted with two different components: a warm component with kBT = 0.3-0.6 keV and a dominant hot component with kBT ∼ 3 keV. The emission measure of the dominant, hot component is not inversely proportional to the distance between the two stars. This can be explained by the O star wind colliding before it has reached its terminal velocity, leading to a reduction in its wind momentum flux. At phases closer to periastron, we discovered a cool plasma component in a recombining phase, which is less absorbed. This component may be a relic of the wind-wind collision plasma, which was cooled down by radiation, and may represent a transitional stage in dust formation.
Keywords: eclipsing binaries; Wolf-Rayet

The nextgeneration Virgo cluster survey. Xii. Stellar populations and kinematics of compact, low-mass early-type galaxies from Gemini Gmos-Ifu spectroscopy - Guérou, Adrien; Emsellem, Eric; McDermid, Richard M.; Côté, Patrick; Ferrarese, Laura; Blakeslee, John P; Durrell, Patrick R.; Macarthur, Lauren A.; Peng, Eric W.; Cuillandre, Jean-Charles; Gwyn, Stephen (The Astrophysical Journal, 2015)
We present Gemini Multi Object Spectrograph integral-field unit (GMOS-IFU) data of eight compact, low-mass early-type galaxies (ETGs) in the Virgo cluster. We analyze their stellar kinematics and stellar population and present two-dimensional maps of these properties covering the central 5″ 7″ region. We find a large variety of kinematics, from nonrotating to highly rotating objects, often associated with underlying disky isophotes revealed by deep images from the Next Generation Virgo Cluster Survey. In half of our objects, we find a centrally concentrated younger and more metal-rich stellar population. We analyze the specific stellar angular momentum through the λR parameter and find six fast rotators and two slow rotators, one having a thin counterrotating disk. We compare the local galaxy density and stellar populations of our objects with those of 39 more extended low-mass Virgo ETGs from the SMAKCED survey and 260 massive (M > 1010 ) ETGs from the ATLAS3D sample. The compact low-mass ETGs in our sample are located in high-density regions, often close to a massive galaxy, and have, on average, older and more metal-rich stellar populations than less compact low-mass galaxies. We find that the stellar population parameters follow lines of constant velocity dispersion in the mass-size plane, smoothly extending the comparable trends found for massive ETGs. Our study supports a scenario where low-mass compact ETGs have experienced long-lived interactions with their environment, including ram-pressure stripping and gravitational tidal forces, that may be responsible for their compact nature.

The haptic interaction in virtual surgery based sliding mode control - Hu, Lingyan; Xiao, Lei; Liu, Xiaoping; Yang, Chunsheng (Proceedings of the 2015 IEEE 19th International Conference on Computer Supported Cooperative Work in Design, CSCWD 2015, 2015)
What operation instruments interact with are human tissues and organs in virtual surgery. Because its impedance is nonlinear and unpredictable, the haptic interaction is difficult to be stable, especially when interacting with rigid tissues such as bone. To solve this difficult problem, this paper presents a sliding mode control algorithm based on Lyapunov theory to realize stable operation for virtual surgery which is never seen in previous research. The simulation results show that 1) the haptic interaction can remain stable when interacting with both soft tissues and large impedance tissues such as bone; 2) the haptic interaction can remain stable even when operation instruments interact with nonlinear impedance tissues.
Keywords: Algorithms; Bone; Convergence of numerical methods; Histology; Interactive computer systems; Sliding mode control; Surgery; Tissue; Virtual reality; Haptic interactions; Human tissues; Lyapunov theories; Nonlinear impedance; Soft tissue; Stable operation; Virtual surgery; Surgical equipment

The cluster ages experiment (CASE). VII. Analysis of two eclipsing binaries in the globular cluster NGC 6362 - Kaluzny, J.; Thompson, I. B.; Dotter, A.; Rozyczka, M.; Schwarzenberg-Czerny, A.; Burley, G. S.; Mazur, B.; Rucinski, S. M. (Astronomical Journal, 2015)
We use photometric and spectroscopic observations of the detached eclipsing binaries V40 and V41 in the globular cluster NGC 6362 to derive masses, radii, and luminosities of the component stars. The orbital periods of these systems are 5.30 and 17.89 days, respectively. The measured masses of the primary and secondary components (Mp, Ms) are (0.8337 ± 0.0063, 0.7947 ± 0.0048) Mo for V40 and (0.8215 ± 0.0058, 0.7280 ± 0.0047) Mo for V41. The measured radii (Rp, Rs) are (1.3253 ± 0.0075, 0.997 ± 0.013) Ro for V40 and (1.0739 ± 0.0048, 0.7307 ± 0.0046) Ro for V41. Based on the derived luminosities, we find that the distance modulus of the cluster is 14.74 ± 0.04 mag - in good agreement with 14.72 mag obtained from color-magnitude diagram (CMD) fitting. We compare the absolute parameters of component stars with theoretical isochrones in mass-radius and mass-luminosity diagrams. For assumed abundances [Fe/H] = -1.07, [α/Fe] = 0.4, and Y = 0.25 we find the most probable age of V40 to be 11.7 ± 0.2 Gyr, compatible with the age of the cluster derived from CMD fitting (12.5 ± 0.5 Gyr). V41 seems to be markedly younger than V40. If independently confirmed, this result will suggest that V41 belongs to the younger of the two stellar populations recently discovered in NGC 6362. The orbits of both systems are eccentric. Given the orbital period and age of V40, its orbit should have been tidally circularized some ∼7 Gyr ago. The observed eccentricity is most likely the result of a relatively recent close stellar encounter.

HERSCHEL observations of the W3 GMC (II): Clues to the formation of clusters of high-mass stars - Rivera-Ingraham, A.; Martin, P. G.; Polychroni, D.; Schneider, N.; Motte, F.; Bontemps, S.; Hennemann, M.; Men'Shchikov, A.; Luong, Q. N.; Zavagno, A.; André, P.; Bernard, J.-P.; et al. (The Astrophysical Journal, 2015)
The W3 giant molecular cloud is a prime target for investigating the formation of high-mass stars and clusters. This second study of W3 within the HOBYS Key Program provides a comparative analysis of subfields within W3 to further constrain the processes leading to the observed structures and stellar population. Probability density functions (PDFs) and cumulative mass distributions (CMDs) were created from dust column density maps, quantified as extinction AV. The shape of the PDF, typically represented with a lognormal function at low AV "breaking" to a power-law tail at high AV, is influenced by various processes including turbulence and selfgravity. The breaks can also be identified, often more readily, in the CMDs. The PDF break from lognormal (AV(SF)≈ 6-10 mag) appears to shift to higher AV by stellar feedback, so that high-mass star-forming regions tend to have higher PDF breaks. A second break at AV > 50 mag traces structures formed or influenced by a dynamic process. Because such a process has been suggested to drive high-mass star formation in W3, this second break might then identify regions with potential for hosting high-mass stars/clusters. Stellar feedback appears to be a major mechanism driving the local evolution and state of regions within W3. A high initial star formation efficiency in a dense medium could result in a self-enhancing process, leading to more compression and favorable star formation conditions (e.g., colliding flows), a richer stellar content, and massive stars. This scenario would be compatible with the "convergent constructive feedback" model introduced in our previous Herschel study.

A highly effective component vaccine against nontyphoidal salmonella enterica infections - Ferreira, Rosana B. R.; Valdez, Yanet; Coombes, Brian K.; Sad, Subash; Gouw, Joost W.; Brown, Eric M.; Li, Yuling; Grassl, Guntram A.; Antunes, L. Caetano M.; Gill, Navkiran; Truong, Mimi; Scholz, Roland; et al. (mBio, 2015)
Nontyphoidal Salmonella enterica (NTS) infections are a major burden to global public health, as they lead to diseases ranging from gastroenteritis to systemic infections and there is currently no vaccine available. Here, we describe a highly effective component vaccine against S. enterica serovar Typhimurium in both gastroenteritis and systemic murine infection models. We devised an approach to generate supernatants of S. enterica serovar Typhimurium, an organism that is highly abundant in virulence factors. Immunization of mice with this supernatant resulted in dramatic protection against a challenge with serovar Typhimurium, showing increased survival in the systemic model and decreased intestinal pathology in the gastrointestinal model. Protection correlated with specific IgA and IgG levels in the serum and specific secretory IgA levels in the feces of immunized mice. Initial characterization of the protective antigens in the bacterial culture supernatants revealed a subset of antigens that exhibited remarkable stability, a highly desirable characteristic of an effective vaccine to be used under suboptimal environmental conditions in developing countries. We were able to purify a subset of the peptides present in the supernatants and show their potential for immunization of mice against serovar Typhimurium resulting in a decreased level of colonization. This component vaccine shows promise with regard to protecting against NTS, and further work should significantly help to establish vaccines against these prevalent infections.
Keywords: immunoglobulin A; immunoglobulin G; salmonellosis vaccine; animal experiment; animal model; animal tissue; bacterial virulence; bacterium identification; blood level; developing country; drug efficacy; drug response; environmental factor; feces analysis; immune response; immunization; infection prevention; mouse; nonhuman; priority journal; Salmonella enterica; Salmonella enterica serovar Typhimurium; supernatant; survival rate; typhoid fever

Semaphorin3A elevates vascular permeability and contributes to cerebral ischemia-induced brain damage - Hou, Sheng T.; Nilchi, Ladan; Li, Xuesheng; Gangaraju, Sandhya; Jiang, Susan X.; Aylsworth, Amy; Monette, Robert; Slinn, Jacqueline (Scientific Reports, 2015)
Semaphorin 3A (Sema3A) increased significantly in mouse brain following cerebral ischemia. However, the role of Sema3A in stroke brain remains unknown. Our aim was to determine wether Sema3A functions as a vascular permeability factor and contributes to ischemic brain damage. Recombinant Sema3A injected intradermally to mouse skin, or stereotactically into the cerebral cortex, caused dose-and time-dependent increases in vascular permeability, with a degree comparable to that caused by injection of a known vascular permeability factor vascular endothelial growth factor receptors (VEGF). Application of Sema3A to cultured endothelial cells caused disorganization of F-actin stress fibre bundles and increased endothelial monolayer permeability, confirming Sema3A as a permeability factor. Sema3A-mediated F-actin changes in endothelial cells were through binding to the neuropilin2/VEGFR1 receptor complex, which in turn directly activates Mical2, a F-actin modulator. Down-regulation of Mical2, using specific siRNA, alleviated Sema3A-induced F-actin disorganization, cellular morphology changes and endothelial permeability. Importantly, ablation of Sema3A expression, cerebrovascular permeability and brain damage were significantly reduced in response to transient middle cerebral artery occlusion (tMCAO) and in a mouse model of cerebral ischemia/haemorrhagic transformation. Together, these studies demonstrated that Sema3A is a key mediator of cerebrovascular permeability and contributes to brain damage caused by cerebral ischemia.

Oscillator strengths and radiative decay rates for spin-changing S-P transitions in helium: Finite nuclear mass effects - Morton, Donald C.; Schulhoff, Eva E.; Drake, G. W. F. (Journal of Physics B: Atomic, Molecular and Optical Physics, 2015)
We have calculated the electric dipole (E1) and magnetic quadrupole (M2) oscillator strengths and spontaneous decay rates for 24 spin-changing transitions of atomic helium. We included the effects of the finite nuclear mass and the anomalous magnetic moment of the electron augmented by the recently derived Pachucki term. The specific transitions for 4He are and with and for For the E1 calculations we used the Breit approximation and pseudostate expansions to perform the perturbation sums over intermediate states in both the length and velocity gauge as a check on both numerical accuracy and validity of the transition operators. The corrections for the nuclear mass and the electron anomaly tend to cancel, indicating that if one is included, then so should be the other. The tables give mass- and anomaly-dependent coefficients permitting the easy generation of results for the other isotopes of helium.
Keywords: Magnetic moments; Anomalous magnetic moment of the electrons; Nuclear mass; Oscillator strengths; Pseudo-state expansion; Radiative decay rates; Relativistic effects; Spontaneous decay rates; Transition operators; Helium

Solvent-free catalyst-free microwave-assisted acylation of lignin - Monteil-Rivera, Fanny; Paquet, Louise (Industrial Crops and Products, 2015)
Valorization of lignin into biomaterials requires its good compatibility with the polymeric matrix it is incorporated into. Softwood Kraft lignin was esterified with various anhydrides (acetic, propionic, butyric, methacrylic, maleic) using a solvent-free, catalyst-free, microwave-assisted method. The esterification was fast and efficient (degrees of substitution >90% after 10 min). The reaction was worked up using water or ethanol as purification agent. Esterified lignins were characterized by FT-IR, GPC, quantitative 31PNMRand TGA/DSC.NMR analyses indicated that non-cyclic anhydrides reacted with both aliphatic and phenolic OH groups, while maleic anhydride reacted exclusively with aliphatic OH groups. All acylated lignins except the maleated one showed higher thermal stability than the unmodified lignin. Lignins acylated with non-cyclic anhydrides can be applied as green fillers in apolar polyolefins while maleated lignin can serve as metal adsorbent or macroreagent for the synthesis of polyesters or polyamides. We showed in this study that lignin can be modified in a fast and easy way.
Keywords: Acetylation; Acylation; Catalysts; Esters; Solvents; Catalyst-free; Degrees of substitution; Maleation; Microwave assisted; Microwave-assisted methods; Polymeric matrices; Softwood kraft lignins; Solvent free; Lignin; Acetylation; Esterification; Lignins; Purification

The effect of dietary energy level on growth and nutrient utilization by juvenile diploid and triploid brook charr, Salvelinus fontinalis - Sacobie, C.F.D.; Burke, H.A.; Lall, S.P.; Benfey, T.J. (Aquaculture Nutrition, 2015)
Triploids are used in aquaculture because they are sterile and do not undergo preharvest loss in flesh quality. Despite this advantage, they do not always perform as well as diploids when fed commercial diets. This study investigated whether differences in dietary energy utilization might explain this reduced performance. Dietary lipid levels were adjusted to supply diets with 22.7, 23.6 or 24.4 MJ kg-1 gross energy and fed to juvenile diploid and triploid brook charr. Fish were fed to satiation twice daily in a 70-day growth trial, with samples collected at days 0 and 70 for proximate composition and plasma insulin-like growth factor I (IGF-I) analysis. This was followed by a digestibility trial using the same diets to determine apparent digestibility coefficients. Triploids had lower growth rates and condition factor than diploids on all three diets, but there was no effect of ploidy on feed conversion efficiency. Triploids also had lower whole-body lipid content, but equal protein content, which resulted in lower energy content at both days 0 and 70. There was no effect of diet or ploidy on plasma IGF-I concentrations. Triploidy did not affect diet digestibility, suggesting that the reduced performance of triploids is due to a difference in metabolism and energy utilization. © 2015 John Wiley & Sons Ltd.

Metabolic engineering of Pichia pastoris to produce ricinoleic acid, a hydroxy fatty acid of industrial importance - Meesapyodsuk, Dauenpen; Chen, Yan; Ng, Siew Hon; Chen, Jianan; Qiu, Xiao (Journal of Lipid Research, 2015)
Ricinoleic acid (12-hydroxyoctadec- cis -9-enoic acid) has many specialized uses in bioproduct industries, while castor bean is currently the only commercial source for the fatty acid. This report describes metabolic engineering of a microbial system ( Pichia pastoris ) to produce ricinoleic acid using a "push" (synthesis) and "pull" (assembly) strategy. CpFAH, a fatty acid hydroxylase from Claviceps purpurea , was used for synthesis of ricinoleic acid, and CpDGAT1, a diacylglycerol acyl transferase for the triacylglycerol synthesis from the same species, was used for assembly of the fatty acid. Coexpression of CpFAH and CpDGAT1 produced higher lipid contents and ricinoleic acid levels than expression of CpFAH alone. Coexpression in a mutant haploid strain defective in the 12 desaturase activity resulted in a higher level of ricinoleic acid than that in the diploid strain. Intriguingly, the ricinoleic acid produced was mainly distributed in the neutral lipid fractions, particularly the free fatty acid form, but with little in the polar lipids. This work demonstrates the effectiveness of the metabolic engineering strategy and excellent capacity of the microbial system for production of ricinoleic acid as an alternative to plant sources for industrial uses.
Keywords: hydroxy fatty acid; ricinoleic acid; biomass; Claviceps purpurea; conceptual framework; enzyme activity; fatty acid analysis; gene amplification; gene cassette; homologous recombination; hydroxylation; Komagataella pastoris; lipid analysis; metabolic engineering; molecular cloning; nonhuman; open reading frame; plasmid; promoter region; transesterification

Young stellar objects in the Gould Belt - Dunham, Michael M.; Allen, Lori E.; Evans Ii, Neal J.; Broekhoven-Fiene, Hannah; Cieza, Lucas A.; Di Francesco, James; Gutermuth, Robert A.; Harvey, Paul M.; Hatchell, Jennifer; Heiderman, Amanda; Huard, Tracy L.; Johnstone, Doug; et al. (Astrophysical Journal, Supplement Series, 2015)
We present the full catalog of Young Stellar Objects (YSOs) identified in the 18 molecular clouds surveyed by the Spitzer Space Telescope "cores to disks" (c2d) and "Gould Belt" (GB) Legacy surveys. Using standard techniques developed by the c2d project, we identify 3239 candidate YSOs in the 18 clouds, 2966 of which survive visual inspection and form our final catalog of YSOs in the GB. We compile extinction corrected spectral energy distributions for all 2966 YSOs and calculate and tabulate the infrared spectral index, bolometric luminosity, and bolometric temperature for each object. We find that 326 (11%), 210 (7%), 1248 (42%), and 1182 (40%) are classified as Class 0 + I, Flat-spectrum, Class II, and Class III, respectively, and show that the Class III sample suffers from an overall contamination rate by background Asymptotic Giant Branch stars between 25% and 90%. Adopting standard assumptions, we derive durations of 0.40-0.78 Myr for Class 0 + I YSOs and 0.26-0.50 Myr for Flat-spectrum YSOs, where the ranges encompass uncertainties in the adopted assumptions. Including information from (sub)millimeter wavelengths, one-third of the Class 0 + I sample is classified as Class 0, leading to durations of 0.13-0.26 Myr (Class 0) and 0.27-0.52 Myr (Class I). We revisit infrared color-color diagrams used in the literature to classify YSOs and propose minor revisions to classification boundaries in these diagrams. Finally, we show that the bolometric temperature is a poor discriminator between Class II and Class III YSOs.

The AU Mic debris disk: far-infrared and submillimeter resolved imaging - Matthews, Brenda C.; Kennedy, Grant; Sibthorpe, Bruce; Holland, Wayne; Booth, Mark; Kalas, Paul; Macgregor, Meredith; Wilner, David; Vandenbussche, Bart; Olofsson, Göran; Blommaert, Joris; Brandeker, Alexis; et al. (The Astrophysical Journal, 2015)
We present far-infrared and submillimeter maps from the Herschel Space Observatory and the James Clerk Maxwell Telescope of the debris disk host star AU Microscopii. Disk emission is detected at 70, 160, 250, 350, 450, 500, and 850 μm. The disk is resolved at 70, 160, and 450 μm. In addition to the planetesimal belt, we detect thermal emission from AU Mic's halo for the first time. In contrast to the scattered light images, no asymmetries are evident in the disk. The fractional luminosity of the disk is and its milimeter-grain dust mass is (±20%). We create a simple spatial model that reconciles the disk spectral energy distribution as a blackbody of 53 ± 2 K (a composite of 39 and 50 K components) and the presence of small (non-blackbody) grains which populate the extended halo. The best-fit model is consistent with the "birth ring" model explored in earlier works, i.e., an edge-on dust belt extending from 8.8 to 40 AU, but with an additional halo component with an surface density profile extending to the limits of sensitivity (140 AU). We confirm that AU Mic does not exert enough radiation force to blow out grains. For stellar mass-loss rates of 10-100 times solar, compact (zero porosity) grains can only be removed if they are very small; consistently with previous work, if the porosity is 0.9, then grains approaching 0.1 μm can be removed via corpuscular forces (i.e., the stellar wind).

A CGPS look at the spiral structure of the outer Milky Way. I. Distances and velocities to star-forming regions - Foster, T.; Brunt, C. M. (Astronomical Journal, 2015)
We present a new catalog of spectrophotometric distances and line of sight systemic velocities to 103 H ii regions between (longitude quadrants II and part of III). Two new velocities for each region are independently measured using 1 arcmin resolution 21 cm H i and 2.6 mm 12CO line maps (from the Canadian Galactic Plane Survey and Five College Radio Astronomy Observatory Outer Galaxy Surveys) that show where gaseous shells are observed around the periphery of the ionized gas. Known and neighboring O- and B-type stars with published UBV photometry and MK classifications are overlaid onto 21 cm continuum maps, and those stars observed within the boundary of the H ii emission (and whose distance is not more than three times the standard deviation of the others) are used to calculate new mean stellar distances to each of the 103 nebulae. Using this approach of excluding distance outliers from the mean distance to a group of many stars in each H ii region lessens the impact of anomalous reddening for certain individuals. The standard deviation of individual stellar distances in a cluster is typically 20% per stellar distance, and the error in the mean distance to the cluster is typically ±10%. Final mean distances of nine common objects with very long baseline interferometry parallax distances show a 1:1 correspondence. Further, comparison with previous catalogs of H ii regions in these quadrants shows a 50% reduction in scatter for the distance to Perseus spiral arm objects in the same region, and a reduction by ∼1/ in scatter around a common angular velocity relative to the Sun (km s-1 kpc-1). The purpose of the catalog is to provide a foundation for more detailed large-scale Galactic spiral structure and dynamics (rotation curve, density wave streaming) studies in the 2nd and 3rd quadrants, which from the Sun's location is the most favorably viewed section of the Galaxy.

Silicon-on-insulator spatial heterodyne spectrometer chip for the mid-infrared - Nedeljkovic, Milos; Khokhar, Ali Z.; Mashanovich, Goran Z.; Velasco, Aitor V.; Cheben, Pavel (IEEE International Conference on Group IV Photonics GFP, 2015)
We demonstrate fur the first linio a silicon-on-insulator spatial hoterodyne waveguide spectrometer chip operating in i ho mid-infrared. The device comprises a MMI splitting tree, followed by an array of 42 Mach-Zehnder interferometers with linearly increasing optical path differences. The fabricated device was characterized in the 3717-3772 nm wavelength range by retrieving the spectral line of a quantum cascade laser line, with a wavelength resolution of 2.8 nm.
Keywords: Infrared devices; Photonics; Quantum cascade lasers; Silicon; Spectrometers; Waveguides; Fabricated device; Midinfrared; Optical path difference; Spatial heterodyne; Splitting tree; Waveguide spectrometers; Wavelength ranges; Wavelength resolution; Silicon on insulator technology

Raven and the center of Maffei 1: Multi-object adaptive optics observations of the center of a nearby elliptical galaxy and the detection of an intermediate age population - Davidge, T. J.; Andersen, D. R.; Lardiere, O.; Bradley, C.; Blain, C.; Oya, S.; Akiyama, M.; Ono, Y. H. (The Astrophysical Journal, 2015)
Near-infrared (NIR) spectra that have an angular resolution of ∼0.15 arcsec are used to examine the stellar content of the central regions of the nearby elliptical galaxy Maffei 1. The spectra were recorded at the Subaru Telescope, with wavefront distortions corrected by the RAVEN Multi-object Adaptive Optics science demonstrator. The Ballick-Ramsey C2 absorption bandhead near 1.76 μm is detected, and models in which ∼10%-20% of the light near 1.8 μm originates from stars of spectral type C5 reproduce the depth of this feature. Archival NIR and mid-infrared images are also used to probe the structural and photometric properties of the galaxy. Comparisons with models suggest that an intermediate age population dominates the spectral energy distribution between 1 and 5 μm near the galaxy center. This is consistent not only with the presence of C stars, but also with the large Hβ index that has been measured previously for Maffei 1. The J - K color is more or less constant within 15 arcsec of the galaxy center, suggesting that the brightest red stars are well-mixed in this area.

Comparison of C-14 liquid scintillation counting at NIST and NRC Canada - Bergeron, Denis E.; Galea, Raphael; Laureano-Pérez, Lizbeth; Zimmerman, Brian E. (Applied Radiation and Isotopes, 2015)
An informal bilateral comparison of 14C liquid scintillation (LS) counting at the National Research Council of Canada (NRC) and the National Institute of Standards and Technology (NIST) has been completed. Two solutions, one containing 14C-labeled sodium benzoate and one containing 14C-labeled n-hexadecane, were measured at both laboratories. Despite observed LS cocktail instabilities, the two laboratories achieved accord in their standardizations of both solutions. At the conclusion of the comparison, the beta spectrum used for efficiency calculations was identified as inadequate and the data were reanalyzed with different inputs, improving accord.
Keywords: Benzoic acid; Efficiency; Paraffins; Benzoate; Bilateral comparison; CNET; Hexadecane; Shape factor; Spectrum shape; TDCR; Triple-to-double coincidence ratio; Scintillation

A compact sideband-separating (2SB) arrangement using a turnstile - Henke, D. (Proceedings of the 2015 International Conference on Electromagnetics in Advanced Applications, ICEAA 2015, 2015)
Important requirements of a millimetre-wave heterodyne receiver for radio astronomy are that it can detect dual-linear polarisation and retain both upper and lower sidebands. One such arrangement, referred to as a sideband-separating (2SB) layout, uses a 90° phase shift on either the LO or signal path before mixing, and the upper and lower sidebands are separated into unique IF outputs once orthogonally re-combined. There is continuing interest to build arrays of heterodyne receivers and part of the challenge is to fit all of the receiver components within a given volume. To realise dual-linear polarisation and 2SB within receiver arrays, a new, more compact approach must be taken. Integrating a turnstile as the signal splitter reduces overall layout space and provides excellent polarisation isolation.
Keywords: Amplitude modulation; Assembly; Feeding; Heterodyning; Machining; Millimeter waves; Mixers (machinery); Phase shift; Phase shifters; Polarization; Radio astronomy; Radio receivers; Receivers (containers); Heterodyne receivers; Linear polarisation; Lower sidebands; Millimetre waves; Radio frequencies; Receiver array; Signal paths; Separation

Development of an anti-vascular cell adhesion protein-1 aptamer for molecular imaging and inflammation detection in transgenic mouse model of Alzheimer's disease - Simao, Teresa; Ng, Andy; Fatehi, Dorothy; Corluka, Slavisa; Abulrob, Abedelnasser; Zourob, Mohammed (Journal of Biomedical Nanotechnology, 2015)
Cerebrovascular inflammation is often involved in the pathogenesis of neurodegenerative disorders such as Alzheimer's disease (AD). Non-invasive and sensitive molecular imaging of cerebrovascular inflammation biomarkers therefore represents a potential AD diagnostic and therapeutic monitoring method. Here, we describe the development of a novel aptamer-based near infrared fluorescence imaging probe targeting Vascular Cell Adhesion Molecule-1 (VCAM-1), an adhesion molecule overexpressed by the activated cerebrovasculature during inflammation. A SELEX-type screening of a random ssDNA library against human VCAM-1 identified a high-affinity ssDNA aptamer with a dissociation constant of 49 nM. We demonstrated that the Cy5.5-labeled aptamer binds to activated endothelial cells, with no affinity to nonactivated cells. A scrambled aptamer labeled with Cy5.5 did not image activated and non-activated endothelial cells, confirming the sequence specificity of the targeting. In vivo, the aptameric imaging agent targeting VCAM-1 successfully identified inflammation associated with amyloid-β plaques deposition in the vessels of the cerebellum of transgenic AD mice. It exhibited excellent retention by remaining bound to vessels 4 hours post-injection, indicating its effectiveness in in vivo imaging and its potential in early detection of cerebrovascular inflammation.
Keywords: Cell adhesion; Cells; Cytology; Diagnosis; Dissociation; Endothelial cells; Infrared devices; Mammals; Molecules; Neurodegenerative diseases; Pathology; Alzheimer's disease; Aptamers; Near-infrared fluorescence imaging; Therapeutic monitoring; Vascular cell adhesion; VCAM-1; Molecular imaging; amyloid beta protein; aptamer; cyanine dye 5 11R6; fluorescein; fluorescent dye; single stranded DNA; vascular cell adhesion molecule 1; animal experiment; animal model; animal tissue; cerebellum; DNA library; DNA sequence; electrophoretic mobility; fluorescence imaging; fluorescence microscopy; gel mobility shift assay; human; human cell; in vitro selection; in vivo study; mouse; nervous system inflammation; nonhuman; protein targeting; umbilical vein endothelial cell; disease model; fluorescence imaging; genetics; inflammation; metabolism; molecular imaging; nucleotide sequence; transgenic mouse; Aptamers, Nucleotide; Base Sequence; Disease Models, Animal; Human Umbilical Vein Endothelial Cells; Humans; Inflammation; Mice, Transgenic; Optical Imaging

Identification of more interstellar C60 +bands - Walker, G. A. H.; Bohlender, D. A.; Maier, J. P.; Campbell, E. K. (The Astrophysical Journal Letters, 2015)
Based on gas-phase laboratory spectra at 6 K, Campbell et al. confirmed that the diffuse interstellar bands (DIBs) at 9632.7 and 9577.5 Å are due to absorption by the fullerene ion C60 +. They also reported the detection of two other, weaker bands at 9428.5 and 9365.9 Å. These lie in spectral regions heavily contaminated by telluric water vapor lines. We acquired CFHT ESPaDOnS spectra of HD 183143 close to the zenith and chopped with a nearby standard to correct for the telluric line absorption which enabled us to detect a DIB at 9365.9 Å of relative width and strength comparable to the laboratory absorption. There is a DIB of similar strength and FWHM at 9362.5 Å. A stellar emission feature at 9429 Å prevented detection of the 9428.5 Å band. However, a CFHT archival spectrum of HD 169454, where emission is absent at 9429 Å, clearly shows the 9428.5 Å DIB with the expected strength and width. These results further confirm C60 + as a DIB carrier.

Broadband polarization independent nanophotonic coupler for silicon waveguides with ultra-high efficiency - Cheben, Pavel; Schmid, Jens H.; Wang, Shurui; Xu, Dan-Xia; Vachon, Martin; Janz, Siegfried; Lapointe, Jean; Painchaud, Yves; Picard, Marie-Josée (Optics Express, 2015)
Coupling of light to and from integrated optical circuits has been recognized as a major practical challenge since the early years of photonics. The coupling is particularly difficult for high index contrast waveguides such as silicon-on-insulator, since the cross-sectional area of silicon wire waveguides is more than two orders of magnitude smaller than that of a standard single-mode fiber. Here, we experimentally demonstrate unprecedented control over the light coupling between the optical fiber and silicon chip by constructing the nanophotonic coupler with ultra-high coupling efficiency simultaneously for both transverse electric and transverse magnetic polarizations. We specifically demonstrate a subwavelength refractive index engineered nanostructure to mitigate loss and wavelength resonances by suppressing diffraction effects, enabling a coupling efficiency over 92% (0.32 dB) and polarization independent operation for a broad spectral range exceeding 100 nm.
Keywords: Nanophotonics; Optical fibers; Optical waveguides; Photonic integration technology; Polarization; Refractive index; Silicon; Silicon on insulator technology; Single mode fibers; Waveguides; Cross sectional area; High-index contrast waveguides; Integrated optical circuit; Polarization independent; Silicon wire waveguides; Standard single mode fibers; Transverse electrics; Transverse magnetic polarization; Optical fiber coupling

Hydrodynamic study of submerged ice collisions - Chander, Subodh; Akinturk, Ayhan; Colbourne, Bruce (Proceedings of the International Conference on Offshore Mechanics and Arctic Engineering - OMAE, 2015)
Most of the research done on ice-structure interaction deals with the ice at the sea surface. Whereas majority of icestrengthened regions of ships and offshore structures are well below the waterline. The aim of this research is to examine the mechanics of ice loads caused by submerged ice blocks colliding with the structure. The kinematics is an essential determinant of the energy that is available to drive the ice crushing process during the collision. The present research aims to develop a model to represent the mechanics of such collisions and set a direction for future work. This study includes experimental and numerical components. Various physical experiments have been conducted using a submerged ice model moving solely due to its buoyancy. Using high speed camera the experiments are recorded and analysed to determine the kinematics of collision. These include location, velocity and acceleration of the model ice as a function of time. In parallel, numerical simulations have being conducted using FLOW 3DTM software. The results of the experiments are used to validate the numerical model of the underwater collision. The results shows that added mass plays an important role during the underwater impact collisions. The paper presents some preliminary results obtained during this research.
Keywords: Arctic engineering; Engineering research; High speed cameras; Kinematics; Numerical models; Ocean engineering; Offshore structures; Surface waters; Added mass; Function of time; Hydrodynamic studies; Ice blocks; Ice-structure interaction; Impact collision; Physical experiments; Sea surfaces; Ice

Appraisal of the IEC technical specification for assessment of wave energy resources - Piche, Steffanie; Cornett, Andrew; Baker, Scott; Nistor, IoanI. (Proceedings of the ASME 2015 34th International Conference on Ocean, Offshore and Arctic Engineering, OMAE2015, May 31-June 5, St. John's, Newfoundland, Canada, 2015)
This article describes and presents results from research focused on appraising the new technical specification (TS) for the assessment of wave energy resources developed by technical committee 114 of the International Electro-technical Commission (IEC-TC-114). The new IEC TS is appraised through an extensive pilot application to the waters off the west coast of Vancouver Island, British Columbia, Canada. A series of wave models are developed and used to simulate the wave conditions and estimate the wave energy resource over the study area. The accuracy of the various resource estimates derived from the model outputs is assessed through comparison with measurements from a directional wave buoy. Furthermore, sensitivity analyses are conducted to determine the main sources of error and uncertainty impacting the precision of resource assessments obtained following the IEC methodology. Preliminary results indicate that the IEC TS can be applied to the estimation of wave energy resources with a reasonable level of effort and accuracy.
Keywords: Arctic engineering; Energy resources; Sensitivity analysis; Specifications; Wave energy conversion; British Columbia, Canada; Comparison with measurements; International electro-technical commissions; Pilot applications; Resource assessments; Technical committees; Technical specifications; Wave energy resources; Uncertainty analysis

Production of lentiviral vectors encoding recombinant factor VIII expression in serum-free suspension cultures - Caron, Angelo Luis; Picanço-Castro, Virgínia; Ansorge, Sven; Covas, Dimas Tadeu; Kamen, Amine; Swiech, Kamilla (Brazilian Archives of Biology and Technology, 2015)
Lentiviral vector-mediated gene transfer offers several advantages over other gene delivery vectors when considering gene and cell therapy applications. However, using these therapies in clinical applications involves large-scale vector production in an efficient and cost-effective manner. Here we describe a high yield production of a lentivirus encoding recombinant factor VIII in a scalable and GMP-compliant culture system, based on serum free suspension cultures and transient transfection with an inexpensive reagent, polyethylenimine (PEI), reaching a total viral yield of 2.48x108 particles.

NGC 4370: A case study for testing our ability to infer dust distribution and mass in nearby galaxies - Viaene, S.; De Geyter, G.; Baes, M.; Fritz, J.; Bendo, G. J.; Boquien, M.; Boselli, A.; Bianchi, S.; Cortese, L.; Côté, P.; Cuillandre, J.-C.; De Looze, I.; et al. (Astronomy and Astrophysics, 2015)
Context. A segment of the early-type galaxy population hosts a prominent dust lane, often decoupled from its stellar body. Methods of quantifying the dust content of these systems based on optical imaging data usually yield dust masses that are an order of magnitude lower than dust masses derived from the observed far-IR (FIR) emission. The discrepancy is often explained by invoking a diffuse dust component that is hard to trace in the UV or optical. Aims. High-quality optical data from the Next Generation Virgo cluster Survey (NGVS) and FIR/sub-mm observations from the Herschel Virgo Cluster Survey (HeViCS) allow us to revisit previous methods of determining the dust content in galaxies and explore new ones. NGC 4370 is an edge-on, early-type galaxy with a conspicuous dust lane and regular morphology, making it suitable for several (semi-)analytical modelling techniques. We aim to derive the dust mass from both optical and FIR data and to investigate the need to invoke a putative diffuse dust component. Methods. We used different methods to determine the total dust mass in the dust lane. We used our exquisite optical data to create colour and attenuation maps, which are converted to approximate dust mass maps based on simple dust geometries. Dust masses were also derived from SED fits to FIR to sub-mm observations. Finally, inverse radiative transfer fitting was performed to investigate more complex dust geometries, such as an exponential dust disc and a dust ring and to treat the dust-starlight interaction in a self-consistent way. Results. We find that the empirical methods applied to the optical data yield lower limits of 3.4 × 105 M⊙, an order of magnitude below the total dust masses derived from SED fitting. In contrast, radiative transfer models yield dust masses that are slightly lower, but fully consistent with the FIR-derived mass. We find that the effect of a nuclear stellar disc on the derivation of the total dust mass is minor. Conclusions. Dust is more likely to be distributed in a ring around the centre of NGC 4370 as opposed to an exponential disc or a simple foreground screen. Moreover, by using inverse radiative transfer fitting, we are able to constrain most of the parameters that describe these geometries. The resulting dust masses are high enough to account for the dust observed at FIR/sub-mm wavelengths, so that no diffuse dust component needs to be invoked. We furthermore caution against interpreting dust masses and optical depths based on optical data alone, when using overly simplistic star-dust geometries and the neglect of scattering effects.
Keywords: Ability testing; Galaxies; Geometry; Inverse problems; Light extinction; Radiative transfer; Stars; Surveys; Dust distribution; Galaxies: fundamental parameters; Galaxies: individuals; Galaxies: ISM; Infrared: ISM; Inverse radiative transfer; Radiative transfer model; Scattering effects; Dust

Hexagonal-layered Na0.7MnO2.05 via solvothermal synthesis as an electrode material for aqueous Na-ion supercapacitors - Hou, Yan; Tang, Hongwei; Li, Bao; Chang, Kun; Chang, Zhaorong; Yuan, Xiao-Zi; Wang, Haijiang (Materials Chemistry and Physics, 2015)
The layered sodium manganese oxides Na0.7MnO2.05 material was synthesized using Na2CO3 and Mn3O4 precursors via a solvothermal method at different temperatures. The X-ray diffraction (XRD) shows that the Na0.7MnO2.05 sample has a high crystallinity with hexagonal crystal system. The electrochemical performance was characterized by cyclic voltammetry (CV), impedance measurements and galvanostatic charge-discharge tests in symmetric Na-ion supercapacitors with 1 mol L-1 Na2SO4 solution as electrolyte. The Na0.7MnO2.05 material shows a high specific capacity of about 162.5 F g-1 at a current density of 50 mA g-1 and a high coulombic efficiency approaching 100%. Even at a current density of 200 mA g-1, the discharge capacity of the material can reach to 146 F g-1. This electrode material holds great promise for practical applications.
Keywords: Capacitors; Chemical compounds; Cyclic voltammetry; Electrochemical electrodes; Electrochemical properties; Electrodes; Electrolytes; Electrolytic capacitors; Inorganic compounds; Manganese; Manganese oxide; Synthesis (chemical); X ray diffraction; Coulombic efficiency; Discharge capacities; Electrochemical performance; Electrochemical techniques; Galvanostatic charge discharges; High specific capacity; Impedance measurement; Solvothermal synthesis; Electric discharges

A census of dense cores in the Aquila cloud complex: SPIRE/PACS observations from the Herschel Gould Belt survey - Könyves, V.; André, Ph.; Men'Shchikov, A.; Palmeirim, P.; Arzoumanian, D.; Schneider, N.; Roy, A.; Didelon, P.; Maury, A.; Shimajiri, Y.; Di Francesco, J.; Bontemps, S.; et al. (Astronomy and Astrophysics, 2015)
We present and discuss the results of the Herschel Gould Belt survey (HGBS) observations in an ∼11 deg2 area of the Aquila molecular cloud complex at d ∼ 260 pc, imaged with the SPIRE and PACS photometric cameras in parallel mode from 70 μm to 500 μm. Using the multi-scale, multi-wavelength source extraction algorithm getsources, we identify a complete sample of starless dense cores and embedded (Class 0-I) protostars in this region, and analyze their global properties and spatial distributions. We find a total of 651 starless cores, ∼60% ± 10% of which are gravitationally bound prestellar cores, and they will likely form stars inthe future. We also detect 58 protostellar cores. The core mass function (CMF) derived for the large population of prestellar cores is very similar in shape to the stellar initial mass function (IMF), confirming earlier findings on a much stronger statistical basis and supporting the view that there is a close physical link between the stellar IMF and the prestellar CMF. The global shift in mass scale observed between the CMF and the IMF is consistent with a typical star formation efficiency of ∼40% at the level of an individual core. By comparing the numbers of starless cores in various density bins to the number of young stellar objects (YSOs), we estimate that the lifetime of prestellar cores is ∼1 Myr, which is typically ∼4 times longer than the core free-fall time, and that it decreases with average core density. We find a strong correlation between the spatial distribution of prestellar cores and the densest filaments observed in the Aquila complex. About 90% of the Herschel-identified prestellar cores are located above a background column density corresponding to AV ∼ 7, and ∼75% of them lie within filamentary structures with supercritical masses per unit length ≳ 16 M⊙/pc. These findings support a picture wherein the cores making up the peak of the CMF (and probably responsible for the base of the IMF) result primarily from the gravitational fragmentation of marginally supercritical filaments. Given that filaments appear to dominate the mass budget of dense gas at AV> 7, our findings also suggest that the physics of prestellar core formation within filaments is responsible for a characteristic "efficiency" SFR/Mdense ∼ 5-2 +2 × 10-8 yr-1 for the star formation process in dense gas.
Keywords: Budget control; Coremaking; Efficiency; Functions; Information dissemination; Population statistics; Spatial distribution; Surveys; ISM : clouds; ISM: individual objects; ISM: structure; Stars: formation; Submillimeter: isms; Stars

Gemini Planet Imager observations of the Au Microscopii debris disk: Asymmetries within one arcsecond - Wang, Jason J.; Graham, James R.; Pueyo, Laurent; Nielsen, Eric L.; Millar-Blanchaer, Max; De Rosa, Robert J.; Kalas, Paul; Ammons, S. Mark; Bulger, Joanna; Cardwell, Andrew; Chen, Christine; Chiang, Eugene; et al. (The Astrophysical Journal Letters, 2015)
We present Gemini Planet Imager (GPI) observations of AU Microscopii, a young M dwarf with an edge-on, dusty debris disk. Integral field spectroscopy and broadband imaging polarimetry were obtained during the commissioning of GPI. In our broadband imaging polarimetry observations, we detect the disk only in total intensity and find asymmetries in the morphology of the disk between the southeast (SE) and northwest (NW) sides. The SE side of the disk exhibits a bump at 1″ (10 AU projected separation) that is three times more vertically extended and three times fainter in peak surface brightness than the NW side at similar separations. This part of the disk is also vertically offset by 69 ± 30 mas to the northeast at 1″ when compared to the established disk midplane and is consistent with prior Atacama Large Millimeter/submillimeter Array and Hubble Space Telescope/Space Telescope Imaging Spectrograph observations. We see hints that the SE bump might be a result of detecting a horizontal sliver feature above the main disk that could be the disk backside. Alternatively, when including the morphology of the NW side, where the disk midplane is offset in the opposite direction ∼50 mas between 0.″4 and 1.″2, the asymmetries suggest a warp-like feature. Using our integral field spectroscopy data to search for planets, we are 50% complete for ∼4 MJup planets at 4 AU. We detect a source, resolved only along the disk plane, that could either be a candidate planetary mass companion or a compact clump in the disk.

From forced collapse to H II region expansion in Mon R2: Envelope density structure and age determination with Herschel - Didelon, P.; Motte, F.; Tremblin, P.; Hill, T.; Hony, S.; Hennemann, M.; Hennebelle, P.; Anderson, L. D.; Galliano, F.; Schneider, N.; Rayner, T.; Rygl, K.; et al. (Astronomy and Astrophysics, 2015)
Context. The surroundings of H ii regions can have a profound influence on their development, morphology, and evolution. This paper explores the effect of the environment on H ii regions in the MonR2 molecular cloud. Aims. We aim to investigate the density structure of envelopes surrounding H ii regions and to determine their collapse and ionisation expansion ages. The Mon R2 molecular cloud is an ideal target since it hosts an H ii region association, which has been imaged by the Herschel PACS and SPIRE cameras as part of the HOBYS key programme. Methods. Column density and temperature images derived from Herschel data were used together to model the structure of H ii bubbles and their surrounding envelopes. The resulting observational constraints were used to follow the development of the Mon R2 ionised regions with analytical calculations and numerical simulations. Results. The four hot bubbles associated with H ii regions are surrounded by dense, cold, and neutral gas envelopes, which are partly embedded in filaments. The envelope's radial density profiles are reminiscent of those of low-mass protostellar envelopes. The inner parts of envelopes of all four H ii regions could be free-falling because they display shallow density profiles: ρ(r) â r- q with \hbox{$q \leqslant 1.5$}. As for their outer parts, the two compact H ii regions show a ρ(r) â r-2 profile, which is typical of the equilibrium structure of a singular isothermal sphere. In contrast, the central UCH ii region shows a steeper outer profile, ρ(r) â r-2.5, that could be interpreted as material being forced to collapse, where an external agent overwhelms the internal pressure support. Conclusions. The size of the heated bubbles, the spectral type of the irradiating stars, and the mean initial neutral gas density are used to estimate the ionisation expansion time, texp ~ 0.1 Myr, for the dense UCH ii and compact H ii regions and ~ 0.35 Myr for the extended H ii region. Numerical simulations with and without gravity show that the so-called lifetime problem of H ii regions is an artefact of theories that do not take their surrounding neutral envelopes with slowly decreasing density profiles into account. The envelope transition radii between the shallow and steeper density profiles are used to estimate the time elapsed since the formation of the first protostellar embryo, tinf ~ 1 Myr, for the ultra-compact, 1.5-3 Myr for the compact, and greater than ~6 Myr for the extended H ii regions. These results suggest that the time needed to form a OB-star embryo and to start ionising the cloud, plus the quenching time due to the large gravitational potential amplified by further in-falling material, dominates the ionisation expansion time by a large factor. Accurate determination of the quenching time of H ii regions would require additional small-scale observationnal constraints and numerical simulations including 3D geometry effects.
Keywords: Clouds; Ionization; Numerical models; Quenching; Stars; Dust , extinction; H II regions; ISM: individual objects: Mon R2; ISM: structure; Stars: protostars; Density of gases

On the uncertainties of stellar mass estimates via colour measurements - Roediger, Joel C.; Courteau, Stéphane (Monthly Notices of the Royal Astronomical Society, 2015)
Mass-to-light versus colour relations (MLCRs), derived from stellar population synthesis models, are widely used to estimate galaxy stellar masses (M*), yet a detailed investigation of their inherent biases and limitations is still lacking. We quantify several potential sources of uncertainty, using optical and near-infrared (NIR) photometry for a representative sample of nearby galaxies from the Virgo cluster. Our method for combining multiband photometry with MLCRs yields robust stellar masses, while errors in M* decrease as more bands are simultaneously considered. The prior assumptions in one's stellar population modelling dominate the error budget, creating a colour-dependent bias of up to 0.6 dex if NIR fluxes are used (0.3 dex otherwise). This matches the systematic errors associated with the method of spectral energy distribution (SED) fitting, indicating that MLCRs do not suffer from much additional bias. Moreover, MLCRs and SED fitting yield similar degrees of random error (~0.1-0.14 dex) when applied to mock galaxies and, on average, equivalent masses for real galaxies with M* ~ 108-11 M⊙. The use of integrated photometry introduces additional uncertainty in M* measurements, at the level of 0.05-0.07 dex. We argue that using MLCRs, instead of timeconsuming SED fits, is justified in cases with complex model parameter spaces (involving, for instance, multiparameter star formation histories) and/or for large data sets. Spatially resolved methods for measuring M* should be applied for small sample sizes and/or when accuracies less than 0.1 dex are required. An appendix provides our MLCR transformations for 10 colour permutations of the grizH filter set.
Keywords: galaxies; galaxy clusters; Virgo galaxy; galaxy formation; galaxy stellar content; fundamental galaxy parameters

Current advances and challenges in the development of acinetobacter vaccines - Chen, Wangxue (Human Vaccines and Immunotherapeutics, 2015)
Acinetobacter baumannii is a major cause of healthcare-associated infections worldwide with high morbidity and mortality. The clinical treatment of A. baumannii infections has become increasingly difficult because of the rapid emerging of multidrug and extremely drug resistant strains. Thus, there is an urgent need for the development of novel intervention strategies to combat this multidrug-resistant pathogen. Vaccine is one of the most effective medical measures for infection control and is likely to overcome the development of multidrug resistance by A. baumannii. Here we discussed the recent advances and potential challenges in development of A. baumannii vaccines with a focus on the 3 most important steps in the preclinical vaccine development: antigen selection, immune correlates of protection, and animal models for efficacy evaluation.

Twin tubular pinch effect in curving confined flows - Clime, Liviu; Morton, Keith J.; Hoa, Xuyen D.; Veres, Teodor (Scientific Reports, 2015)
Colloidal suspensions of buoyancy neutral particles flowing in circular pipes focus into narrow distributions near the wall due to lateral migration effects associated with fluid inertia. In curving flows, these distributions are altered by Dean currents and the interplay between Reynolds and Dean numbers is used to predict equilibrium positions. Here, we propose a new description of inertial lateral migration in curving flows that expands current understanding of both focusing dynamics and equilibrium distributions. We find that at low Reynolds numbers, the ratio δ between lateral inertial migration and Dean forces scales simply with the particle radius, coil curvature and pipe radius as R3R/a4. A critical value δc = 0.148 of this parameter is identified along with two related inertial focusing mechanisms. In the regime below δc, coined subcritical, Dean forces generate permanently circulating, twinned annuli, each with intricate equilibrium particle distributions including eyes and trailing arms. At δ > δc (supercritical regime) inertial lateral migration forces are dominant and particles focus to a single stable equilibrium position.

Effects of Cr–Si diffusion barrier layer on the oxidation resistance of NiCrAlY coating system with aluminized top layer - Gao, F.; Huang, X.; Yang, Q.; Liu, R. (Oxidation of Metals, 2015)
A multilayer coating, which consisted of a Cr–Si co-deposited layer as the diffusion barrier, a plasma sprayed NiCrAlY middle layer, and an aluminized top layer, was developed. During the aluminizing treatment, Cr in the NiCrAlY layer was released as the γ/γ′ structure of this layer transformed to the β phase. The released Cr was inhibited by the inner Cr–Si layer to diffuse into the substrate, and a Cr layer eventually formed over the Cr–Si layer. The Cr layer impeded the inward diffusion of Al due to the low solubility of Al in the Cr layer so that more Al atoms remain in the coating and contributed to the oxidation resistance of the coating. The multilayer coating exhibited better oxidation and spallation resistance than coatings without a Cr–Si layer, at least at 1050 °C for up to 1000 h.
Keywords: Aluminum; Aluminum coatings; Coatings; Diffusion; Diffusion coatings; Multilayers; Oxidation; Oxidation resistance; Plasma spraying; Silicon; Co-deposited layer; Inward diffusion; Multi-layer-coating; NiCrAlY coating; Plasma sprayed; Si diffusion; Si layer; Spallation resistance; Diffusion barriers

Review on cold spray process and technology US patents - Goldbaum, D.; Poirier, D.; Irissou, E.; Legoux, J.-G.; Moreau, C. (Modern Cold Spray: Materials, Process, and Applications, 2015)

Structure of the external aldimine form of PglE, an aminotransferase required for N,N'-diacetylbacillosamine biosynthesis - Riegert, Alexander S.; Young, N. Martin; Watson, David C.; Thoden, James B.; Holden, Hazel M. (Protein Science, 2015)
N,N'-diacetylbacillosamine is a novel sugar that plays a key role in bacterial glycosylation. Three enzymes are required for its biosynthesis in Campylobacter jejuni starting from UDP-GlcNAc. The focus of this investigation, PglE, catalyzes the second step in the pathway. It is a PLP-dependent aminotransferase that converts UDP-2-acetamido-4-keto-2,4,6-trideoxy-d-glucose to UDP-2-acetamido-4-amino-2,4,6-trideoxy-d-glucose. For this investigation, the structure of PglE in complex with an external aldimine was determined to a nominal resolution of 2.0 Å. A comparison of its structure with those of other sugar aminotransferases reveals a remarkable difference in the manner by which PglE accommodates its nucleotide-linked sugar substrate.

Toward precision photometry for the ELT era: The double subgiant branch of NGC 1851 observed with the Gemini/GeMS MCAO system - Turri, P.; McConnachie, A. W.; Stetson, P. B.; Fiorentino, G.; Andersen, D. R.; Véran, J.-P.; Bono, G. (The Astrophysical Journal Letters, 2015)
The Extremely Large Telescopes currently under construction have a collecting area that is an order of magnitude larger than the present largest optical telescopes. For seeing-limited observations the performance will scale as the collecting area, but with the successful use of adaptive optics (AO), for many applications it will scale as D4 (where D is the diameter of the primary mirror). Central to the success of the ELTs, therefore, is the successful use of multi-conjugate adaptive optics (MCAO) which applies a high degree of correction over a field of view larger than the few arcseconds that limits classical AO systems. In this Letter, we report on the analysis of crowded field images taken on the central region of the galactic globular cluster NGC 1851 in the Ks band using the Gemini Multi-conjugate Adaptive Optics System (GeMS) at the Gemini South Telescope, the only science-grade MCAO system in operation. We use this cluster as a benchmark to verify the ability to achieve precise near-infrared photometry by presenting the deepest Ks photometry in crowded fields ever obtained from the ground. We construct a color-magnitude diagram in combination with the F606W band from the Hubble Space Telescope/Advanced Camera for Surveys. As well as detecting the "knee" in the lower main sequence at Ks ≃ 20.5, we also detect the double subgiant branch of NGC 1851, which demonstrates the high photometric accuracy of GeMS in crowded fields.

Characterization of emissions from the use of alternative aviation fuels - Chan, Tak W.; Chishty, Wajid A.; Canteenwalla, Pervez; Buote, David; Davison, Craig R. (Proceedings of the ASME Turbo Expo, 2015)
Alternative fuels for aviation are now a reality. These fuels not only reduce reliance on conventional petroleum-based fuels as the primary propulsion source, but also offer promise for environmental sustainability. While these alternative fuels meet the aviation fuels standards and their overall properties resemble those of the conventional fuel, they are expected to demonstrate different exhaust emissions characteristics because of the inherent variations in their chemical composition resulting from the variations involved in the processing of these fuels. This paper presents the results of back-to-back comparison of emissions characterization tests that were performed using three alternative aviation fuels in a GE CF-700-2D-2 engine core. The fuels used were an unblended synthetic kerosene fuel with aromatics (SKA), an unblended Fischer Tropsch synthetic paraffinic kerosene (SPK) and a semi-synthetic 50-50 blend of Jet A-1 and hydroprocessed SPK. Results indicate that while there is little dissimilarity in the gaseous emissions profiles from these alternative fuels, there is however a significant difference in the particulate matter emissions from these fuels. These differences are primarily attributed to the variations in the aromatic and hydrogen contents in the fuels with some contributions from the hydrogen-to-carbon ratio of the fuels.
Keywords: Blending; Carbon; Fuels; Gas turbines; Kerosene; Sustainable development; Synthetic fuels; Turbines; Characterization tests; Chemical compositions; Environmental sustainability; Hydrogen contents; Hydrogen-to-carbon ratio; Overall properties; Particulate matter emissions; Primary propulsion; Alternative fuels

Evaluation of elastic-viscoplastic self-consistent polycrystal plasticity models for zirconium alloys - Qiao, H.; Wu, P. D.; Wang, H.; Gharghouri, M. A.; Daymond, M. R. (International Journal of Solids and Structures, 2015)
Our elastic viscoplastic self-consistent (EVPSC) model is improved by including thermal strain to allow study of the behavior of a Zircaloy-2 slab under moderately large strains. The approach of introducing thermal strain effect is similar to the one developed by Turner et al. (1995) and used by Xu et al. (2008a). Various self-consistent schemes (SCSs) of the EVPSC model are then evaluated in terms of the deformation behavior of the material under different uniaxial strain paths. The material parameters for the various models are determined by fitting experimental data from uniaxial tension and compression tests along the normal direction (ND) and from uniaxial tension tests along the rolling direction (RD). The quality of the various SCS predictions is assessed based on comparisons of macroscopic deformation behavior (stress-strain curves and R-values) and microscopic mechanical response (the evolution of lattice strains and texture coefficients) between the predicted and experimental data. It is revealed that the Affine and Meff = 0.1 self-consistent models give much better performance than the Secant and Tangent models.
Keywords: Compression testing; Deformation; Stress-strain curves; Stresses; Tensile testing; Zirconium alloys; Lattice strain; R value; Self-consistent scheme; Texture coefficient; Zircaloy-2; Strain

Entrained-flow gasifier and fluidized-bed combustor temperature monitoring using arrays of fs-IR written fiber Bragg gratings - Walker, Robert B.; Ding, Huimin; Coulas, David; Grobnic, Dan; Mihailov, Stephen J.; Duchesne, Marc A.; Hughes, Robin W.; McCalden, David J.; Burchat, Ryan (SPIE - International Society for Optical Engineering. Proceedings, 2015)
Femtosecond written fiber Bragg gratings, have shown great potential for sensing in extreme environments. This paper discusses the fabrication and deployment of several fs-IR written FBG arrays, for monitoring main-spool skin temperatures of an entrained-flow gasifier, as well as the internal temperature gradient of a fluidized bed combustor.
Keywords: Bragg gratings; Combustors; Fibers; Fluidized bed combustors; Fluidized beds; Gasification; Optical fibers; Temperature sensors; Entrained flow gasifiers; Femtoseconds; High temperature; Thermal calibration; Ultra-fast; Fiber Bragg gratings

A simple VOC prioritization method to determine ventilation rate for indoor environment based on building material emissions - Ye, Wei; Won, Doyun; Zhang, Xu (Procedia Engineering, 2015)
Building material emissions could be the major indoor air pollution source in low-occupant-density spaces, e.g., a private office. Lowest Concentration of Interest (LCI) schemes can be used to predict ventilation requirements based on building material emissions. However, it is not practical to obtain emission information on hundreds of chemicals with LCIs. 28 building materials selected from the NRC database were subjected to emission modelling, resulting in 101 VOCs as a starting VOC pool. A method was proposed to generate VOC priority lists. Three priority lists were obtained based on three LCI schemes, i.e., AFSSET, AgBB and EU-LCI, and each consisted of 17 - 21 VOCs, i.e., about 10% of the total substances in the schemes. This paper demonstrated the role of indoor VOCs in determining ventilation requirements and illustrated a way to predict the ventilation rate based on a simplified list of VOCs.
Keywords: Air conditioning; Building materials; Buildings; Indoor air pollution; Neutron emission; AFSSET; AgBB; Emission modelling; Indoor environment; Material emissions; Occupant densities; Source control; Ventilation requirements; Ventilation

First scattered-light image of the debris disk around HD 131835 with the Gemini Planet Imager - Hung, Li-Wei; Duchêne, Gaspard; Arriaga, Pauline; Fitzgerald, Michael P.; Maire, Jérôme; Marois, Christian; Millar-Blanchaer, Maxwell A.; Bruzzone, Sebastian; Rajan, Abhijith; Pueyo, Laurent; Kalas, Paul G.; De Rosa, Robert J.; et al. (The Astrophysical Journal Letters, 2015)
We present the first scattered-light image of the debris disk around HD 131835 in the H band using the Gemini Planet Imager. HD 131835 is a ∼15 Myr old A2IV star at a distance of ∼120 pc in the Sco-Cen OB association. We detect the disk only in polarized light and place an upper limit on the peak total intensity. No point sources resembling exoplanets were identified. Compared to its mid-infrared thermal emission, in scattered light the disk shows similar orientation but different morphology. The scattered-light disk extends from ∼75 to ∼210 AU in the disk plane with roughly flat surface density. Our Monte Carlo radiative transfer model can describe the observations with a model disk composed of a mixture of silicates and amorphous carbon. In addition to the obvious brightness asymmetry due to stronger forward scattering, we discover a weak brightness asymmetry along the major axis, with the northeast side being 1.3 times brighter than the southwest side at a 3σ level.

Crystal engineering and characterization of a structure-H ionic clathrate hydrate - Shin, Kyuchul; Moudrakovski, Igor L.; Udachin, Konstantin A.; Ratcliffe, Christopher I.; Ripmeester, John A. (Canadian Journal of Chemistry, 2015)
Ionic hydrates are known to form numerous clathrate structures in which either the cations or anions sit in cages and the counterions are incorporated into the water framework. Due to the inclusion of the ionic species, such ionic clathrate hydrates not only show many peculiar features such as metal ion encagement and superoxide ion generation, but also exhibit notable physicochemical properties such as outstanding ionic conductivity and thermal stability. Thus, the ionic clathrate hydrates are considered for their potential applicability in various fields, including those that involve solid electrolytes, gas sensors, and energy storage. In this study, we report the design, synthesis, and characterization of the first ionic clathrate hydrate of the hexagonal structure-H (Str.H) crystal type. Diethyl-dimethyl-ammonium hydroxide hydrate was synthesized with CH4 and Xe as help gases, and the crystal structure was identified by powder X-ray diffraction analysis. Further confirmation of the formation of Str.H was obtained from Raman spectroscopy and 13C, 129Xe, and 2H solid-state NMR spectroscopy. From 13C NMR and ab initio calculations, it was shown that the quaternary ion occupies the large cage of Str.H with a conformation different from that in solution, due to constraints imposed by the dimensions of the cage. The H deficiency introduced by substitution of OH- for a water molecule appears, from 129Xe NMR, to be disordered over the framework, and, from 2H NMR, to substantially increase the rate of reorientational mobility of the D atoms in the framework, over that observed for a Str.I hydrate and for ice. The Str.H hydrates are commonly more stable than other structures, thus the present findings on the ionic Str.H clathrate hydrate may offer a new approach for improving the stability of ionic clathrate hydrates for their practical application.
Keywords: Ammonium hydroxide; Gas hydrates; Hydration; Ionic conductivity; Metal ions; Metals; Molecules; Nuclear magnetic resonance spectroscopy; Oxygen; Solid electrolytes; X ray diffraction analysis; Ab initio calculations; Clathrate hydrate; Hexagonal structures; Physicochemical property; Powder X ray diffraction; Quaternary ammonium salt; Solid-state NMR spectroscopy; Structure H-hydrate; Crystal structure

The infrared spectrum of the Ne-C2D2 complex - Moazzen-Ahmadi, N.; McKellar, A. R. W.; Fernández, B.; Farrelly, D. (Journal of Chemical Physics, 2015)
Infrared spectra of Ne-C2D2 are observed in the region of the ?3 fundamental band (asymmetric C-D stretch, ∼2440 cm-1) using a tunable optical parametric oscillator to probe a pulsed supersonic slit jet expansion from a cooled nozzle. Like helium-acetylene, this system lies close to the free rotor limit, making analysis tricky because stronger transitions tend to pile up close to monomer (C2D2) rotation-vibration transitions. Assignments are aided by predicted rotational energies calculated from a published ab initio intermolecular potential energy surface. The analysis extends up to the j = 3 ← 2 band, where j labels C2D2 rotation within the dimer, and is much more complete than the limited infrared assignments previously reported for Ne-C2H2 and Ne-C2HD. Two previous microwave transitions within the j = 1 state of Ne-C2D2 are reassigned. Coriolis model fits to the theoretical levels and to the spectrum are compared. Since the variations observed as a function of C2D2 vibrational excitation are comp able to those noted between theory and experiment, it is evident that more detailed testing of theory will require vibrational averaging over the acetylene intramolecular modes.
Keywords: Acetylene; Dimers; Fighter aircraft; Lighting; Optical parametric oscillators; Parametric oscillators; Piles; Potential energy; Quantum chemistry; Spectroscopy; Supersonic aerodynamics; Fundamental bands; Infrared spectrum; Intermolecular potential energy surfaces; Jet expansion; Microwave transitions; Rotation-vibration transitions; Rotational energy; Vibrational excitation; Vibration analysis

Structure and guest dynamics in binary clathrate hydrates of tetrahydropyran with carbon dioxide/methane - Narayanan, Thaneer Malai; Imasato, Kazuki; Takeya, Satoshi; Alavi, Saman; Ohmura, Ryo (The Journal of Physical Chemistry C, 2015)
Binary structure II (sII) clathrate hydrates of tetrahydropyran (THP) with methane and carbon dioxide are synthesized and characterized with powder X-ray diffraction (PXRD) and molecular dynamics (MD) simulations. Analysis of PXRD results shows that 83% of the small 12-sided (dodecahedral, D) sII cages are occupied by CO2 in CO2 + THP hydrate, whereas 93% of the D cages are occupied by CH4 in CH4 + THP hydrate. The effects of the tighter fit of CO2 molecules in the D cages of the binary hydrate were observed in longer lattice constants and lower cage occupancies compared to binary THP hydrates with CH4 molecule in the D cage. MD simulations of 1,4-twist-boat and chair conformers of the THP in the sII clathrate hydrate phase with the CO2 and CH4 help gases are performed at temperatures between 153 to 250 K. Simulations suggest shape and size of D cage guest molecules does not affect the conformation of H cage guest molecule, but the steric repulsions between CO2 molecule and cages water molecules limits its motion and promotes interaction between H cage guest molecule and the cage at higher extent compared to CH4 molecule.
Keywords: Bins; Gas hydrates; Hydration; Lattice constants; Molecular dynamics; Molecules; X ray diffraction; Binary clathrate hydrates; Binary hydrates; Binary structures; Clathrate hydrate; Guest molecules; Molecular dynamics simulations; Powder X-ray diffraction (pXRD); Steric repulsions; Carbon dioxide

Faraday tomography of the North polar spur: Constraints on the distance to the spur and on the magnetic field of the galaxy - Sun, X. H.; Landecker, T. L.; Gaensler, B. M.; Carretti, E.; Reich, W.; Leahy, J. P.; McClure-Griffiths, N. M.; Crocker, R. M.; Wolleben, M.; Haverkorn, M.; Douglas, K. A.; Gray, A. D. (The Astrophysical Journal, 2015)
We present radio continuum and polarization images of the North Polar Spur (NPS) from the Global Magneto-ionic Medium Survey conducted with the Dominion Radio Astrophysical Observatory 26 m Telescope. We fit polarization angle versus wavelength squared over 2048 frequency channels from 1280 to 1750 MHz to obtain a Faraday rotation measure (RM) map of the NPS. Combining this RM map with a published Faraday depth (FD) map of the entire Galaxy in this direction, we derive the FD introduced by the NPS and the Galactic interstellar medium (ISM) in front of and behind the NPS. The FD contributed by the NPS is close to zero, indicating that the NPS is an emitting only feature. The FD caused by the ISM in front of the NPS is consistent with zero at b > 50°, implying that this part of the NPS is local at a distance of approximately several hundred parsecs. The FD contributed by the ISM behind the NPS gradually increases with Galactic latitude up to b = 44°, and decreases at higher Galactic latitudes. This implies that either the part of the NPS at b < 44° is distant or the NPS is local but there is a sign change of the large-scale magnetic field. If the NPS is local, there is then no evidence for a large-scale anti-symmetry pattern in the FD of the Milky Way. The FD introduced by the ISM behind the NPS at latitudes b > 50° can be explained by including a coherent vertical magnetic field..

Sea level performance of a CF-700 engine core with alternative fuels - Davison, Craig R.; Canteenwalla, Pervez; Chalmers, Jennifer L. Y.; Chishty, Wajid A. (Proceedings of the ASME Turbo Expo, 2015)
The use of alternative fuels has the potential to enhance energy independence and reduce environmental impact of air travel. It is important to characterize gas turbine operation using such fuels under controlled conditions before implementing them in flight. The performance of a CF-700 engine core was examined in a sea level test facility. The following fuels were tested and will be reported on: 1. Jet A-1 - baseline fuel 2. 100% unblended Hydroprocessed Esters and Fatty Acids (HEFA) synthetic kerosene fuel with aromatics (SKA) 3. 100% unblended Fischer-Tropsch (FT) synthetic paraffinic kerosene (SPK) 4. Blended 50% HEFA-SPK and 50% Jet A-1 Fuel 2 above is an alternative fuel that can potentially be used without blending with conventional fuel. One purpose of the static engine testing was to determine if this fuel was suitable for use on subsequent test flights in a Dassault Falcon 20 aircraft. Engine performance testing was conducted at various power settings for each fuel. Relevant plots of performance are presented, compared and discussed. Transient tests were also performed including slams and chops. Observations of the effects of the different fuels on the engine fuel system are presented as some alternative fuels have the potential to cause seals to shrink and leaks to occur. The leaks observed are noted as are the steps taken to mitigate the problem.
Keywords: Air transportation; Blending; Engines; Environmental impact; Fatty acids; Fighter aircraft; Fuels; Gas turbines; Kerosene; Sea level; Controlled conditions; Conventional fuel; Energy independence; Engine performance; Engine testing; Fischer Tropsch; Transient tests; Turbine operation; Alternative fuels

Erratum: Mass spectrometric analysis of products of metabolic glycan engineering with azido-modification of sialic acids (Analytical and Bioanalytical Chemistry (2015) 407 (9191-9193) (DOI 10.1007/s00216-015-9010-x)) - Bodnar, Edward; Raymond, Céline; Lopez, Paul G.; Villacrés, Carina; Butler, Michael; Schoenhofen, Ian C.; Durocher, Yves; Perreault, Hélène (Springer International Publishing, 2015)

Control of Francisella tularensis intracellular growth by pulmonary epithelial cells - Maggio, Savannah; Takeda, Kazuyo; Stark, Felicity; Meierovics, Anda I.; Yabe, Idalia; Cowley, Siobhan C. (PLoS ONE, 2015)
The virulence of F. tularensis is often associated with its ability to grow in macrophages, although recent studies show that Francisella proliferates in multiple host cell types, including pulmonary epithelial cells. Thus far little is known about the requirements for killing of F. tularensis in the non-macrophage host cell types that support replication of this organism. Here we sought to address this question through the use of a murine lung epithelial cell line (TC-1 cells). Our data show that combinations of the cytokines IFN-γ, TNF, and IL-17A activated murine pulmonary epithelial cells to inhibit the intracellular growth of the F. tularensis Live Vaccine Strain (LVS) and the highly virulent F. tularensis Schu S4 strain. Although paired combinations of IFN-γ, TNF, and IL-17A all significantly controlled LVS growth, simultaneous treatment with all three cytokines had the greatest effect on LVS growth inhibition. In contrast, Schu S4 was more resistant to cytokine-induced growth effects, exhibiting significant growth inhibition only in response to all three cytokines. Since one of the main antimicrobial mechanisms of activated macrophages is the release of reactive nitrogen intermediates (RNI) via the activity of iNOS, we investigated the role of RNI and iNOS in Francisella growth control by pulmonary epithelial cells. NOS2 gene expression was significantly up-regulated in infected, cytokine-treated pulmonary epithelial cells in a manner that correlated with LVS and Schu S4 growth control. Treatment of LVS-infected cells with an iNOS inhibitor significantly reversed LVS killing in cytokine-treated cultures. Further, we found that mouse pulmonary epithelial cells produced iNOS during in vivo respiratory LVS infection. Overall, these data demonstrate that lung epithelial cells produce iNOS both in vitro and in vivo, and can inhibit Francisella intracellular growth via reactive nitrogen intermediates.
Keywords: gamma interferon; inducible nitric oxide synthase; interleukin 17; organonitrogen derivative; reactive nitrogen intermediate; tumor necrosis factor alpha; animal cell; animal experiment; animal model; animal tissue; bacterial growth; bacterial growth control; bacterial strain; bacterial virulence; correlational study; epithelium cell; Francisella tularensis; gene expression regulation; growth inhibition; immune response; macrophage; male; mouse; nonhuman; NOS2 gene; pulmonary epithelial cell; respiratory tract infection; tularemia

Situational ethics: Re-thinking approaches to formal ethics requirements for human-computer interaction - Munteanu, Cosmin; Molyneaux, Heather; Moncur, Wendy; Romero, Mario; O'Donnell, Susan; Vines, John (Conference on Human Factors in Computing Systems - Proceedings, 2015)
Most Human-Computer Interaction (HCI) researchers are accustomed to the process of formal ethics review for their evaluation or field trial protocol. Although this process varies by country, the underlying principles are universal. While this process is often a formality, for field research or lab-based studies with vulnerable users, formal ethics requirements can be challenging to navigate - A common occurrence in the social sciences; yet, in many cases, foreign to HCI researchers. Nevertheless, with the increase in new areas of research such as mobile technologies for marginalized populations or assistive technologies, this is a current reality. In this paper we present our experiences and challenges in conducting several studies that evaluate interactive systems in difficult settings, from the perspective of the ethics process. Based on these, we draft recommendations for mitigating the effect of such challenges to the ethical conduct of research. We then issue a call for interaction researchers, together with policy makers, to refine existing ethics guidelines and protocols in order to more accurately capture the particularities of such field-based evaluations, qualitative studies, challenging labbased evaluations, and ethnographic observations.
Keywords: Human engineering; Philosophical aspects; Ethics; Field studies; Research protocol; Situational ethics; Vulnerable populations; Human computer interaction

Improved inter-calibration of Faraday cup and ion counting for in situ Pb isotope measurements using LA-MC-ICP-MS: Application to the study of the origin of the Fangshan pluton, North China - Zhang, Wen; Hu, Zhaochu; Yang, Lu; Liu, Yongsheng; Zong, Keqing; Xu, Haijin; Chen, Haihong; Gao, Shan; Xu, Lei (Geostandards and Geoanalytical Research, 2015)
A laser ablation multi-collector inductively coupled plasma-mass spectrometry (LA-MC-ICP-MS) method was developed to obtain precise and accurate Pb isotopic ratio measurements in low-Pb materials (< 10 μg g-1) using a combination of Faraday cups and ion counters (FC-IC). The low abundance 204Pb (~ 1.4%) was collected using an IC. A NBS 981 standard solution was used to cross-calculate the FC-IC gain and to investigate the signal response characteristics of the IC. A significant, continuous and linear decrease in the FC-IC gain was observed within 1 hr, but this drift could be corrected using the calibrator-sample-calibrator bracketing method. In addition, a non-linear response of the IC used in this study was observed and corrected by a non-linear correction algorithm, which was established by measuring a series of gravimetrically prepared NBS 981 standard solutions (NIST SRM 981). Compared with the conventional arrangement, the use of the newly designed X skimmer cone and Jet sample cone improved the signal intensities from Pb isotopes by a factor of 1.9. Compared with only Faraday cups, using a combination FC-IC array was found to enhance the measurement repeatability (RSD) of 20xPb/204Pb by approximately one order of magnitude when the 204Pb intensity was < 8 mV. Eight natural glasses and the NIST SRM 612 reference material glass (as a calibration material) were measured to evaluate the new protocol for Pb isotope determination. The analytical results were in agreement with the reference values within 2s measurement uncertainties. For MPI-DING ATHO-G (5.67 μg g-1 total Pb), KL2-G (2.07 μg g-1 total Pb) and ML3B-G (1.38 μg g-1 total Pb), the typical accuracies of 20xPb/204Pb were 0.09% of preferred values with precisions of < 0.33% (2RSD). The Pb isotope ratios in feldspars from granodiorite and within mafic microgranular enclaves (MMEs) from the Fangshan pluton, North China, were measured using the present method. The Pb isotopic compositions of feldspars from the whole host granodiorite show that that are radiogenic in the margin zone and gradually become less radiogenic. For the MMEs, the Pb isotopic compositions of feldspars are highly variable and overlap with those of the whole host granodiorite. For single-grain feldspar, the strong rim-core-rim variations of the Pb isotopic compositions and trace elements are interpreted to have been generated via magma mixing. These results suggest that the Fangshan pluton underwent magma mixing of mantle-derived mafic magmas with felsic magmas, and the proportion of the mafic magma influx decreased over time.
Keywords: Calibration; Feldspar; Fighter aircraft; Glass; Inductively coupled plasma mass spectrometry; Ions; Isotopes; Laser ablation; Mass spectrometers; Mass spectrometry; Radiation counters; Trace elements; Uncertainty analysis; Calibration materials; Fangshan pluton; Isotopic composition; Lead isotope; MC-ICP-MS; Measurement repeatability; Measurement uncertainty; Multi-collector inductively coupled plasma mass spectrometry; Lead

Demonstration of integrated polarization control with a 40 dB range in extinction ratio - Sarmiento-Merenguel, J. D.; Halir, R.; Le Roux, X.; Alonso-Ramos, C.; Vivien, L.; Cheben, P.; Durán-Valdeiglesias, E.; Molina-Fernández, I.; Marris-Morini, D.; Xu, D.-X.; Schmid, J. H.; Janz, S.; et al. (Optica, 2015)
Polarization controllers are key elements in many fields of optics, including coherent communications, optical imaging, and quantum applications. Here we present a technology-independent polarization controller scheme based on electrically tunable phase shifters and polarization rotators with largely relaxed fabrication tolerances. Using this scheme, we experimentally demonstrate a fully integrated polarization controller in the silicon-on-insulator platform that is tunable over the complete C-band and achieves a polarization extinction range of 40 dB (±20  dB ). These results constitute, to the best of our knowledge, the highest polarization extinction range achieved in a fully integrated device, and overcome the existing limitation in the trade-off between integration and performance in polarization management circuits.

High-harmonic generation in solids: bridging the gap between attosecond science and condensed matter physics - Vampa, Giulio; McDonald, Chris; Fraser, Alec; Brabec, Thomas (IEEE Journal of Selected Topics in Quantum Electronics, 2015)
Abstract—We review recent progress in understanding the dominant mechanism driving high-harmonic generation in solids. Three-dimensional two-band single active electron calculations predict that the major emission arises from the recombination of electron-hole pairs upon their creation and acceleration in the laser field, in analogy to atomic high-harmonic generation. The main goal of this study is to review a simple quasi-classical trajectory formalism and use it to better understand the fundamental properties of high-harmonic generation in solids and how they compare to high-harmonic generation in atomic and molecular gases. The simple formalism presents a valuable tool for extending attosecond science fromthe gas to the condensed matter phase. This is demonstrated by discussing the potential synthesis of attosecond pulses from solids.
Keywords: High harmonic generation (HHG); solids; nonlinear optics; attoseconds

Simulation of thermomechanical fatigue of ductile cast iron and lifetime calculation - Liu, Xiaoyang; Quan, Guangchun; Wu, Xijia; Zhang, Zhong; Sloss, Clayton (SAE technical papers, 2015)
In this paper, both standard and constrained thermomechanical fatigue (TMF) tests were conducted on a high silicon ductile cast iron (DCI). The standard TMF tests were conducted with independent control of mechanical strain, out-of-phase (OP) and in-phase (IP) strain, and temperature in the range from 300 to 800°C. The constrained TMF tests were conducted with various constraint ratios of 100%, 70%, 60% and 50% at the temperature ranges of 160 to 600°C and 160 to 700°C. Based on a material model as calibrated with low-cycle fatigue (LCF) data of DCI, finite element analyses (FEA) of the above TMF tests were carried out with Abaqus. A damage mechanism-based lifetime model was integrated into a C++ API code to post-process the Abaqus output results. Simulation predictions show good agreement with experiments for stress-strain responses and lifetime under different TMF conditions.
Keywords: thermomechanical fatigue; ductile cast iron; simulation and modeling

Photon-momentum transfer in multiphoton ionization and in time-resolved holography with photoelectrons - Chelkowski, Szczepan; Bandrauk, André D.; Corkum, Paul B. (Physical Review A, 2015)
In most models and theoretical calculations describing multiphoton ionization by infrared light, the dipole approximation is used. This is equivalent to setting the very small photon momentum to zero. Using numerical solutions of the two-dimensional (2-D) time-dependent Schrödinger equation for one electron (H-like) systems, we show that, for linear polarization, the radiation pressure on photoelectrons is very sensitive to the details of the ionization mechanism. The directly ionized photoelectrons, those that never recollide with the parent ion, are driven in the direction of the laser photon momentum, whereas a fraction of slower photoelectrons are pushed in the opposite direction, leading to the counterintuitive shifts observed in recent experiments [Phys. Rev. Lett. 113, 243001 (2014)]. This complex response is due to the interplay between the Lorentz force and the Coulomb attraction from the ion. On average, however, the photoelectron momentum is in the direction of the photon momentum as in the case of circular polarization. The influence of the photon momentum is shown to be discernible in the holographic patterns of time-resolved atomic and molecular holography with photoelectrons, thus suggesting a new research subject in multiphoton ionization.

Laser consolidation: a novel additive manufacturing process for making net-shape functional metallic components for gas turbine applications - Xue, Lijue; Li, Yangsheng; Chen, Jianyin; Wang, Shaodong (ASME Turbo Expo 2015: Turbine Technical Conference and Exposition, June 15-19, 2015, Montreal, Quebec, Canada, 2015)
Laser consolidation (LC) is a novel additive manufacturing process being developed by the National Research Council Canada (NRC) at its London facility. LC offers unique capabilities in the production of net-shape functional metallic parts requiring no further post-machining. NRC’s LC technology has achieved dimensional accuracy of up to +/−0.05 mm with a surface finish up to 1 μm Ra (depending on the materials used in the manufacturing process). The LC process differs from other additive manufacturing technologies by its high precision deposition system that can build functional parts or features on top of existing parts using various high performance materials and alloys. In this paper, laser consolidation of various high performance materials (such as Ni-base super alloys and Ti-6Al-4V alloy) will be discussed and the examples will be given on building complex functional components and repairing parts otherwise unrepairable for gas turbine and other applications.
Keywords: lasers; gas turbines; shapes; additive manufacturing

Cold sprayed Cu-MoS2 and its fretting wear behavior - Zhang, Yinyin; Descartes, Sylvie; Chromik, Richard; Vo, Phuong (Journal of thermal spray technology, 2015)
Cu and Cu-MoS2 coatings were fabricated by cold spray, and the fretting wear performance of the two coatings was compared. A mixture (95 wt.% Cu + 5 wt.% MoS2) was used as feedstock for the composite coating. Coatings were sprayed with identical gas flow conditions on the substrates pre-heated to approximately 170 °C. The morphology of coating top surface and polished cross sections was analyzed by scanning electron microscopy (SEM) and light optical microscopy (LOM). The influence of MoS2 on Cu deposition was examined. The local MoS2 concentration within the coating was found to affect the hardness. Fretting tests were carried out at two different normal loads, and the influence of MoS2 on friction and wear was studied. The morphology and elemental compositions of the wear scars and wear debris were observed by SEM and energy dispersive x-ray spectroscopy (EDS), respectively.
Keywords: cold spray; Cu-MoS2 composite; fretting; normal load; wear debris bed

Application of copper coatings onto used fuel canisters for the Canadian nuclear industry - Vo, Phuong; Poirier, Dominique; Legoux, Jean-Gabriell; Keech, Peter G.; Irissou, Eric (Applications of high pressure cold spray technology, 2015)
The Nuclear Waste Management Organization (NWMO) was established in 2002 under the Nuclear Fuel Waste Act (NFWA) to investigate approaches for managing Canada's used nuclear fuel. Currently, nuclear power plants are operating or undergoing decommissioning in Ontario, Quebec, and New Brunswick. Canada's CANDU reactors generate used fuel with small amounts of fissile nuclides compared to other types of nuclear reactors, owing to the use of unenriched uranium as a fuel source; used nuclear fuel is currently planned for disposal without reuse/reprocessing. The present approach, shown in Figure 1, envisions the conceptual long term storage of radioactive fuel bundles in specially designed canisters. The canisters would be emplaced in the rock of a suitable geological formation at a minimum of 500 m of depth, for an intended lifespan of more than 100,000 years (i.e., indefinite storage). The Canadian spent fuel canister consists of an inner container of steel strong enough to withstand geological pressures, including glaciations scenarios, and an outer shell of copper for corrosion resistance.
Keywords: nuclear fuel waste; reactor

Hydroxylation of longiborneol by a Clm2-encoded CYP450 monooxygenase to produce culmorin in Fusarium graminearum - Bahadoor, Adilah; Schneiderman, Danielle; Gemmill, Larissa; Bosnich, Whynn; Blackwell, Barbara; Melanson, Jeremy E.; McRae, Garnet; Harris, Linda J. (Journal of Natural Products, 2015)
A second structural gene required for culmorin biosynthesis in the plant pathogen Fusarium graminearum is described. Clm2 encodes a regio- and stereoselective cytochrome P450 monooxygenase for C-11 of longiborneol. Clm2 gene disruptants were grown in liquid culture and assessed for culmorin production via HPLC-evaporative light scattering detection. The analysis indicated a complete loss of culmorin from the liquid culture of the ΔClm2 mutants. Culmorin production resumed in a ΔClm2 complementation experiment. A detailed analysis of the secondary metabolites extracted from the large-scale liquid culture of disruptant ΔClm2D20 revealed five new natural products: 3-hydroxylongiborneol, 5-hydroxylongiborneol, 12-hydroxylongiborneol, 15-hydroxylongiborneol, and 11-epi-acetylculmorin. The structures of the new compounds were elucidated by a combination of HRMS, 1D and 2D NMR, and X-ray crystallography.

Review: Volcanic ash and its influence on aircraft engine components - Chen, W. R.; Zhao, L. R. (Procedia Engineering, 2015)
Volcanic ash damages aircraft engine components,thus having a significant impact on engine performance, flight safety and maintenance costs. This paper discusses the properties of volcanic ash and their influence on engine components, as well as some potential protective coatings that may mitigate the impact of volcanic ash.
Keywords: volcanic ash; CMAS; aircraft engine; damage; coating; review

Self-assembly and visualization of poly(3-hexyl-thiophene) chain alignment along boron nitride nanotubes - Martinez-Rubi, Yadienka; Jakubek, Zygmunt J.; Jakubinek, Michael B.; Kim, Keun Su; Cheng, Fuyong; Couillard, Martin; Kingston, Christopher; Simard, Benoit (The Journal of Physical Chemistry C, 2015)
Boron nitride nanotubes (BNNTs) were noncovalently functionalized with poly(3-hexyl-thiophene) (P3HT) to produce stable suspensions. The conjugated polymer and BNNTs interact via π–π stacking, and the resulting self-assembly of regiorandom P3HT on the BNNT surface is immediately evident through a color change and the appearance of a partially resolved absorption band. By employing polarized excitation fluorescence microscopy, we directly visualized the polymer-functionalized BNNTs and determined the conformation of the polymer on BNNT surfaces. Variation of fluorescence intensity with linear polarization direction showed conclusively that the P3HT chains were always aligned parallel to the BNNT long axis.

Dependence of spin dynamics on in-plane magnetic field in AlGaN/GaN quantum wells - Lv, Meng; Yu, Guolin; Xu, Yonggang; Chang, Zhigang; Lin, Tie; Zhao, Degang; Dai, Ning; Chu, Junhao; Lockwood, D. J. (EPL (Europhysics Letters), 2015)
We systematically investigate the weak antilocalization effect and the dependence of spin dynamics on the in-plane magnetic field for two AlₓGa₁₋ₓN/GaN quantum wells, in which these effects are dominated by the spin-orbit interaction originating from the structural inversion asymmetry and the bulk inversion asymmetry, respectively. By fitting the weak antilocalization magnetoconductance, the phase coherence time and spin-orbit scattering time are obtained. With the increase of in-plane magnetic fields, the phase coherence time decreases quadratically while the spin-orbit scattering time increases quadratically. We attribute these variations to the competition between the Zeeman splitting and the spin-orbit interaction. The comparison between systems dominated by structural inversion asymmetry and bulk inversion asymmetry in the in-plane magnetic field is also made. Our findings may provide clues to control the weak antilocalization effect and spin-orbit interaction via the in-plane field.
Keywords: PACS: 71.70.Ej – Spin-orbit coupling, Zeeman and Stark splitting, Jahn-Teller effect / 73.63.Hs – Quantum wells / 75.76.+j – Spin transport effects

Transplanting soil microbiomes leads to lasting effects on willow growth, but not on the rhizosphere microbiome - Yergeau, Etienne; Bell, Terrence H.; Champagne, Julie; Maynard, Christine; Tardif, Stacie; Tremblay, Julien; Greer, Charles W. (Frontiers in Microbiology, 2015)
Plants interact closely with microbes, which are partly responsible for plant growth, health, and adaptation to stressful environments. Engineering the plant-associated microbiome could improve plant survival and performance in stressful environments such as contaminated soils. Here, willow cuttings were planted into highly petroleum-contaminated soils that had been gamma-irradiated and subjected to one of four treatments: inoculation with rhizosphere soil from a willow that grew well (LA) or sub-optimally (SM) in highly contaminated soils or with bulk soil in which the planted willow had died (DE) or no inoculation (CO). Samples were taken from the starting inoculum, at the beginning of the experiment (T0) and after 100 days of growth (TF). Short hypervariable regions of archaeal/bacterial 16S rRNA genes and the fungal ITS region were amplified from soil DNA extracts and sequenced on the Illumina MiSeq. Willow growth was monitored throughout the experiment, and plant biomass was measured at TF. CO willows were significantly smaller throughout the experiment, while DE willows were the largest at TF. Microbiomes of different treatments were divergent at T0, but for most samples, had converged on highly similar communities by TF. Willow biomass was more strongly linked to overall microbial community structure at T0 than to microbial community structure at TF, and the relative abundance of many genera at T0 was significantly correlated to final willow root and shoot biomass. Although microbial communities had mostly converged at TF, lasting differences in willow growth were observed, probably linked to differences in T0 microbial communities.
Keywords: willow, microbiome engineering, phytoremediation, microbiome transplantation, contaminated soils

Characterization of the NPC1L1 gene and proteome from an exceptional responder to ezetimibe - Schweitzer, Morris; Makhoul, Sandra; Paliouras, Miltiadis; Beitel, Lenore K.; Gottlieb, Bruce; Trifiro, Mark; Chowdhury, Shafinaz F.; Zaman, Naif M.; Wang, Edwin; Davis, Harry; Chalifour, Lorraine E. (Atherosclerosis, 2015)
Background - Strategies to reduce LDL-cholesterol involve reductions in cholesterol synthesis or absorption. We identified a familial hypercholesterolemia patient with an exceptional response to the cholesterol absorption inhibitor, ezetimibe. Niemann-Pick C 1-like 1 (NPC1L1) is the molecular target of ezetimibe. Methods and results - Sequencing identified nucleotide changes predicted to change amino acids 52 (L52P), 300 (I300T) and 489 (S489G) in exceptional NPC1L1. In silico analyses identified increased stability and cholesterol binding affinity in L52P-NPC1L1 versus WT-NPC1L1. HEK293 cells overexpressing WT-NPC1L1 or NPC1L1 harboring amino acid changes singly or in combination (Comb-NPC1L1) had reduced cholesterol uptake in Comb-NPC1L1 when ezetimibe was present. Cholesterol uptake was reduced by ezetimibe in L52P-NPC1L1, I300T-NPC1L1, but increased in S489G-NPC1L1 overexpressing cells. Immunolocalization studies found preferential plasma membrane localization of mutant NPC1L1 independent of ezetimibe. Flotillin 1 and 2 expression was reduced and binding to Comb-NPC1L1 was reduced independent of ezetimibe exposure. Proteomic analyses identified increased association with proteins that modulate intermediate filament proteins in Comb-NPC1L1 versus WT-NPC1L1 treated with ezetimibe. Conclusion - This is the first detailed analysis of the role of NPC1L1 mutations in an exceptional responder to ezetimibe. The results point to a complex set of events in which the combined mutations were shown to affect cholesterol uptake in the presence of ezetimibe. Proteomic analysis suggests that the exceptional response may also lie in the nature of interactions with cytosolic proteins.
Keywords: Cholesterol; Cholesterol/absorption; Cholesterol/cell and tissue; Drug therapy/hypolipidemic drugs; Genetics; Proteomics

Spectrophotometric determination of aluminium in hemodialysis water - Santos, Eder J.; Fantin, Eduardo B.; Paixão, Ronei E.; Herrmann, Amanda B.; Sturgeon, Ralph E. (Journal of the Brazilian Chemical Society, 2015)
A spectrophotometric method for the determination of AlIII in hemodialysis water employing alizarin red S complexing agent in the presence of polyvinylpyrrolidone 40 surfactant is described. The complex, formed in pH 4.5 buffered media, is detected at 510 nm. Optimal concentrations of all reagents were investigated as well as the appropriate detection wavelength. A linear analytical curve in the range of 5.0-320 µg L-¹ was obtained, providing a limit of detection (3s, n = 7) of 2 µg L-¹ and quantification limit of 5 µg L-¹. Results were compared with those generated using inductively coupled plasma mass spectrometry (ICP-MS) as an independent technique and method validation was also demonstrated by analysis of AccuStandard certified reference material QCS‑02-R1-5, appropriately diluted to 10 µg L-¹. Equivalent results (t-test at a 95% confidence level) with a relative standard deviation of 4% were obtained. Real samples, spiked at a level of 10 µg L-¹ to conforme to Brazilian legislated limits, showed recoveries between 90-110%. The procedure is simple and fit-for-purpose with sufficient detection power to screen for Al at trace levels in hemodialysis water without pre-concentration of the samples.
Keywords: aluminium; alizarin red S; polyvinylpyrrolidone (PVP40); hemodyalisis water; spectrophotometry

Computational selection of antibody-drug conjugate targets for breast cancer - Fauteux, François; Hill, Jennifer J.; Jaramillo, Maria L.; Pan, Youlian; Phan, Sieu; Famili, Fazel; O'Connor-McCourt, Maureen (Oncotarget, 2015)
The selection of therapeutic targets is a critical aspect of antibody-drug conjugate research and development. In this study, we applied computational methods to select candidate targets overexpressed in three major breast cancer subtypes as compared with a range of vital organs and tissues. Microarray data corresponding to over 8,000 tissue samples were collected from the public domain. Breast cancer samples were classified into molecular subtypes using an iterative ensemble approach combining six classification algorithms and three feature selection techniques, including a novel kernel density-based method. This feature selection method was used in conjunction with differential expression and subcellular localization information to assemble a primary list of targets. A total of 50 cell membrane targets were identified, including one target for which an antibody-drug conjugate is in clinical use, and six targets for which antibody-drug conjugates are in clinical trials for the treatment of breast cancer and other solid tumors. In addition, 50 extracellular proteins were identified as potential targets for non-internalizing strategies and alternative modalities. Candidate targets linked with the epithelial-to-mesenchymal transition were identified by analyzing differential gene expression in epithelial and mesenchymal tumor-derived cell lines. Overall, these results show that mining human gene expression data has the power to select and prioritize breast cancer antibody-drug conjugate targets, and the potential to lead to new and more effective cancer therapeutics.
Keywords: ADC; drug target; microarray; feature selection; ensemble classification

Temperature drift compensation in Fourier-transform integrated micro-spectrometers - Velasco, A. V.; Galindo-Santos, J.; Cheben, P.; Calvo, M. L.; Schmid, J.; Delage, A.; Xu, Dan-Xia; Janz, S.; Corredera, P. (Optica Pura y Aplicada, 2015)
In this work, we analyze the effect of temperature drifts in a spatial heterodyne Fourier-transform micro-spectrometer fabricated in a Silicon-on-insulator chip. The device comprises an array of 32 Mach-Zehnder interferometers implemented with microphotonic spirals of linearly increasing length. This configuration provides a resolution of 42 pm in a footprint under 12 mm2. However, this resolution enhancement implies a greater sensitivity to environmental variations during the spectrometer operation. In this work, the effect of temperature drifts in the spectral retrieval algorithm is studied, and compensation techniques based on multiple calibration matrices is presented.
Keywords: integrated optics; spectroscopy; Fourier transform; Silicon on insulator; temperature drift; spectral retrieval

A spectroscopic study of substituted anthranilic acids as sensitive environmental probes for detecting cancer cells - Culf, Adrian S.; Yin, Huimin; Monro, Susan; Ghosh, Anirban; Barnett, David A.; Ouellette, Rodney J.; Čuperlović-Culf, Miroslava; McFarland, Sherri A. (Bioorganic and Medicinal Chemistry, 2015)
Small-molecule fluorescent reporters of disease states are highly sought after, yet they remain elusive. Anthranilic acids are extremely sensitive environmental probes, and hold promise as general but selective agents for cancer-cell detection if they can be equipped with the appropriate targeting groups. The optical properties of a small library of N-isopropyl invariant anthranilic acids were investigated in methanol and chloroform. Points of variation included: fluoro, trifluoromethyl, or cyano substitution on the aromatic ring, and derivitization of the parent carboxylic acid as esters or secondary carboxamides. Phenylboronic acid conjugation at the carboxylic acid alongside un-, mono-, and dimethylated 2-amino groups was also explored. The boron-containing anthranilic acids were also evaluated as sensitive fluorescent probes for cancer cells using laser scanning confocal microscopy. In general, the compounds produced blue fluorescence that was strongly influenced by substitution and environment. 4-Trifluoromethyl and 4-cyano esters proved to be the most sensitive environmental probes with quantum yields as large as 100% in chloroform, and enhancements of up to 30-fold on going from methanol to chloroform. Stokes shifts ranged from 63 to 120 nm, generally increasing with ortho-substitution and environmental polarity. It was demonstrated that phenylboronic acid conjugation was an attractive method for cancer cell detection via boronate ester formation with overexpressed glycoproteins (with no interference from normal, healthy cells), presumably due to favorable boron-sialic acid interactions.

All-optical reconstruction of crystal band structure - Vampa, G.; Hammond, T. J.; Thiré, N.; Schmidt, B. E.; Légaré, F.; McDonald, C. R.; Brabec, T.; Klug, D. D.; Corkum, P. B. (Physical Review Letters, 2015)
The band structure of matter determines its properties. In solids, it is typically mapped with angle-resolved photoemission spectroscopy, in which the momentum and the energy of incoherent electrons are independently measured. Sometimes, however, photoelectrons are difficult or impossible to detect. Here we demonstrate an all-optical technique to reconstruct momentum-dependent band gaps by exploiting the coherent motion of electron-hole pairs driven by intense midinfrared femtosecond laser pulses. Applying the method to experimental data for a semiconductor ZnO crystal, we identify the split-off valence band as making the greatest contribution to tunneling to the conduction band. Our new band structure measurement technique is intrinsically bulk sensitive, does not require a vacuum, and has high temporal resolution, making it suitable to study reactions at ambient conditions, matter under extreme pressures, and ultrafast transient modifications to band structures.

Octave-spanning hyperspectral coherent diffractive imaging in the extreme ultraviolet range - Meng, Yijan; Zhang, Chunmei; Marceau, Claude; Naumov, A. Yu.; Corkum, P. B.; Villeneuve, D. M. (Optics Express, 2015)
Soft x-ray microscopy is a powerful imaging technique that provides sub-micron spatial resolution, as well as chemical specificity using core-level near-edge x-ray absorption fine structure (NEXAFS). Near the carbon K-edge (280–300 eV) biological samples exhibit high contrast, and the detailed spectrum contains information about the local chemical environment of the atoms. Most soft x-ray imaging takes place on dedicated beamlines at synchrotron facilities or at x-ray free electron laser facilities. Tabletop femtosecond laser systems are now able to produce coherent radiation at the carbon K-edge and beyond through the process of high harmonic generation (HHG). The broad bandwidth of HHG is seemingly a limitation to imaging, since x-ray optical elements such as Fresnel zone plates require monochromatic sources. Counter-intuitively, the broad bandwidth of HHG sources can be beneficial as it permits chemically-specific hyperspectral imaging. We apply two separate techniques – Fourier transform spectroscopy, and lensless holographic imaging – to obtain images of an object simultaneously at multiple wavelengths using an octave-spanning high harmonic source with photon energies up to 30 eV. We use an interferometric delay reference to correct for nanometer-scale fluctuations between the two HHG sources.

Structural and optical properties of axial silicon-germanium nanowire heterojunctions - Wang, X.; Tsybeskov, L.; Kamins, T. I.; Wu, X.; Lockwood, D. J. (Journal of Applied Physics, 2015)
Detailed studies of the structural and optical properties of axial silicon-germanium nanowire heterojunctions show that despite the 4.2% lattice mismatch between Si and Ge they can be grown without a significant density of structural defects. The lattice mismatch induced strain is partially relieved due to spontaneous SiGe intermixing at the heterointerface during growth and lateral expansion of the Ge segment of the nanowire. The mismatch in Ge and Si coefficients of thermal expansion and low thermal conductivity of Si/Ge nanowire heterojunctions are proposed to be responsible for the thermally induced stress detected under intense laser radiation in photoluminescence and Raman scattering measurements.
Keywords: germanium; elemental semiconductors; photoluminescence; semiconductor insulator; semiconductor structures; Raman spectra

Novel flower-like nickel sulfide as an efficient electrocatalyst for non-aqueous lithium-air batteries - Ma, Zhong; Yuan, Xianxia; Zhang, Zhelin; Mei, Delong; Li, Lin; Ma, Zi-Feng; Zhang, Lei; Yang, Jun; Zhang, Jiujun (Scientific Reports, 2015)
In this paper, metal sulfide materials have been explored for the first time as a new choice of bifunctional cathode electrocatalyst materials for non-aqueous lithium-air batteries (LABs). Nickel sulfides with two different morphologies of flower-like (f-NiS) and rod-like (r-NiS) are successfully synthesized using a hydrothermal method with and without the assistance of cetyltrimethyl ammonium bromide. As LAB cathode catalysts, both f-NiS and r-NiS demonstrate excellent catalytic activities towards the formation and decomposition of Li2O2, resulting in improved specific capacity, reduced overpotentials and enhanced cycling performance when compared to those of pure Super P based electrode. Moreover, the morphology of NiS materials can greatly affect LAB performance. Particularly, the f-NiS is more favorable than r-NiS in terms of their application in LABs. When compared to both r-NiS and pure super P materials as LAB cathode materials, this f-NiS catalyst material can give the highest capacity of 6733 mA h g−1 and the lowest charge voltage of 4.24 V at the current density of 75 mA g−1 and also exhibit an quite stable cycling performance.

A mechanism-based approach from low cycle fatigue to thermomechanical fatigue life prediction - Wu, Xijia; Zhang, Zhong (Journal of Engineering for Gas Turbines and Power, 2015)
Deformation and damage accumulation occur by fundamental dislocation and diffusion mechanisms. An integrated creep–fatigue theory (ICFT) has been developed, based on the physical strain decomposition rule that recognizes the role of each deformation mechanism, and thus relate damage accumulation to its underlying physical mechanism(s). The ICFT formulates the overall damage accumulation as a holistic damage process consisting of nucleation and propagation of surface/subsurface cracks in coalescence with internally distributed damage/discontinuities. These guiding principles run through both isothermal low cycle fatigue (LCF) and thermomechanical fatigue (TMF) under general conditions. This paper presents a methodology using mechanism-based constitutive equations to describe the cyclic stress–strain curve and the nonlinear damage accumulation equation incorporating (i) rate-independent plasticity-induced fatigue, (ii) intergranular embrittlement (IE), (iii) creep, and (iv) oxidation to predict LCF and TMF lives of ductile cast iron (DCI). The complication of the mechanisms and their interactions in this material provide a good demonstration case for the model, which is in good agreement with the experimental observations.

A high-performing sulfur-tolerant and redox-stable layered perovskite anode for direct hydrocarbon solid oxide fuel cells - Ding, Hanping; Tao, Zetian; Liu, Shun; Zhang, Jiujun (Scientific Reports, 2015)
Development of alternative ceramic oxide anode materials is a key step for direct hydrocarbon solid oxide fuel cells (SOFCs). Several lanthanide based layered perovskite-structured oxides demonstrate outstanding oxygen diffusion rate, favorable electronic conductivity, and good oxygen surface exchange kinetics, owing to A-site ordered structure in which lanthanide and alkali-earth ions occupy alternate (001) layers and oxygen vacancies are mainly located in [LnOx] planes. Here we report a nickel-free cation deficient layered perovskite, (PrBa)0.95(Fe0.9Mo0.1)2O5 + δ (PBFM), for SOFC anode, and this anode shows an outstanding performance with high resistance against both carbon build-up and sulfur poisoning in hydrocarbon fuels. At 800 °C, the layered PBFM showed high electrical conductivity of 59.2 S cm−1 in 5% H2 and peak power densities of 1.72 and 0.54 W cm−2 using H2 and CH4 as fuel, respectively. The cell exhibits a very stable performance under a constant current load of 1.0 A cm−2. To our best knowledge, this is the highest performance of ceramic anodes operated in methane. In addition, the anode is structurally stable at various fuel and temperature conditions, suggesting that it is a feasible material candidate for high-performing SOFC anode.

The effects of growth conditions on archaellation and N-glycosylation in Methanococcus maripaludis - Ding, Yan; Lau, Zoe; Logan, Susan M.; Kelly, John F.; Berezuk, Alison; Khursigara, Cezar M.; Jarrell, Ken F. (Microbiology, 2015)
In this study, the effects of growth conditions on archaellation in Methanococcus maripaludis were examined. Cells were grown in a variety of media including complex, minimal and with formate as the electron donor, with different nitrogen sources, varied salinities, and at a variety of growth temperatures. Of the conditions tested, western blot results showed that major archaellin FlaB2 levels only varied detectably as a result of growth temperature. While the amount of FlaB2 was similar for cells grown below 35°C, protein levels decreased at 38°C and were barely detectable at 42°C. Quantitative reverse transcription PCR experiments demonstrated that the flaB2 transcript levels were almost undetectable at 42°C. Electron microscopy confirmed that the FlaB2 levels detected by western blots corresponded to the state of archaellation, with cells grown at 42°C being mostly nonarchaellated. Unexpectedly, a lower apparent molecular mass for FlaB2 was observed in western blots of cells grown at temperatures beyond 38°C suggestive of a truncation in the attached N-linked tetrasaccharide at higher growth temperatures. Mass spectrometry analysis of archaella isolated from cells grown at 40°C confirmed that FlaB2 was now decorated with a trisaccharide in which the third sugar was also lacking the attached threonine and acetamidino modifications found in the wildtype glycan.

A cultivated form of a red seaweed (Chondrus crispus), suppresses β-amyloid-induced paralysis in Caenorhabditis elegans - Sangha, Jatinder Singh; Wally, Owen; Banskota, Arjun H.; Stefanova, Roumiana; Hafting, Jeff T.; Critchley, Alan T.; Prithiviraj, Balakrishnan (Marine Drugs, 2015)
We report here the protective effects of a methanol extract from a cultivated strain of the red seaweed, Chondrus crispus, against β-amyloid-induced toxicity, in a transgenic Caenorhabditis elegans, expressing human Aβ1-42 gene. The methanol extract of C. crispus (CCE), delayed β-amyloid-induced paralysis, whereas the water extract (CCW) was not effective. The CCE treatment did not affect the transcript abundance of amy1; however, Western blot analysis revealed a significant decrease of Aβ species, as compared to untreated worms. The transcript abundance of stress response genes; sod3, hsp16.2 and skn1 increased in CCE-treated worms. Bioassay guided fractionation of the CCE yielded a fraction enriched in monogalactosyl diacylglycerols (MGDG) that significantly delayed the onset of β-amyloid-induced paralysis. Taken together, these results suggested that the cultivated strain of C. crispus, whilst providing dietary nutritional value, may also have significant protective effects against β-amyloid-induced toxicity in C. elegans, partly through reduced β-amyloid species, up-regulation of stress induced genes and reduced accumulation of reactive oxygen species (ROS).
Keywords: β-amyloid; Caenorhabditis elegans; cultivated Chondrus crispus; glycolipid; monogalactosyl diacylglycerol (MGDG); neuroprotection; red seaweeds

Effect of C/N ratio and salinity on power generation in compost microbial fuel cells - Khudzari, Jauharah Md; Tartakovsky, Boris; Raghavan, G.S. Vijaya (Waste Management, 2015)
In this work, compost Microbial Fuel Cells (cMFCs) were used to generate electricity from a mix of fruit and vegetable wastes, and soil with different C/N ratios and salinities. Experiments were carried out in 500 mL cMFCs equipped with carbon felt anodes and manganese dioxide cathodes. The cMFCs were loaded with fresh compost and operated at 20–23 °C for up to 97 days. The low C/N ratio (C/N 24) had a greater power production with a maximum power density of 5.29 mW/m2 (71.43 mW/m3), indicating a more favorable condition for microbial growth. High-saline cMFCs produced lower power, suggesting that their level of salinity (10 g/L of NaCl) inhibited electricigenic microorganisms. The closed-circuit cMFC showed an improved degradation of organic matter by 6% to 8% compared to the control MFC operated in an open circuit mode (no external resistor attached).
Keywords: Compost microbial fuel cell; Composting; Anaerobic digestion; Biodegradation

Time resolved single dopant charge dynamics in silicon - Rashidi, Mohammad; Burgess, Jacob; Taucer, Marco; Achal, Roshan; Pitters, Jason L.; Loth, Sebastian; Wolkow, Robert A. (2015)
As the ultimate miniaturization of semiconductor devices approaches, it is imperative that the effects of single dopants be clarified. Beyond providing insight into function and limitations of conventional devices, such information enables identification of new device concepts. Atomically resolved, electronic pump-probe scanning tunneling microscopy permits unprecedented, quantitative measurement of time-resolved single dopant ionization dynamics. Tunneling through the surface dangling bond makes feasible what would otherwise be too weak a signal to observe. We introduce a time-resolved scanning-tunneling-spectroscopy method whereby current measurements are made before the system of study relaxes or adjusts to accommodate an applied field. Distinct ionization and neutralization rates of a single dopant are measured and the physical process controlling those are identified.

H NMR Metabolomics analysis of renal cell carcinoma cells: Effect of VHL inactivation on metabolism - Cuperlovic-Culf, Miroslava; Cormier, Kevin; Touaibia, Mohamed; Reyjal, Julie; Robichaud, Sarah; Belbraouet, Mehdi; Turcotte, Sandra (International Journal of Cancer, 2015)
Von Hippel-Lindau (VHL) is an onco-suppressor involved in oxygen and energy-dependent promotion of protein ubiquitination and proteosomal degradation. Loss of function mutations of VHL (VHL- cells) result in organ specific cancers with the best studied example in renal cell carcinomas. VHL has a well-established role in deactivation of hypoxia-inducible factor (HIF-1) and in regulation of PI3K/AKT/mTOR activity. Cell culture metabolomics analysis was utilized to determined effect of VHL and HIF-1α or HIF-2α on metabolism of renal cell carcinomas (RCC). RCC cells were stably transfected with VHL or shRNA designed to silence HIF-1α or HIF-2α genes. Obtained metabolic data was analysed qualitatively, searching for overall effects on metabolism as well as quantitatively, using methods developed in our group in order to determine specific metabolic changes. Analysis of the effect of VHL and HIF silencing on cellular metabolic footprints and fingerprints provided information about the metabolic pathways affected by VHL through HIF function as well as independently of HIF. Through correlation network analysis as well as statistical analysis of significant metabolic changes we have determined effects of VHL and HIF on energy production, amino acid metabolism, choline metabolism as well as cell regulation and signaling. VHL was shown to influence cellular metabolism through its effect on HIF proteins as well as by affecting activity of other factors. This article is protected by copyright. All rights reserved.
Keywords: NMR Metabolomics; renal cancer; RCC; VHL; hypoxia; HIF; cancer metabolism

Effects of heating on proportions of azaspiracids 1−10 in mussels (Mytilus edulis) and identification of carboxylated precursors for azaspiracid-5, -10, -13 and -15 - Kilcoyne, Jane; McCarron, Pearse; Hess, Philipp; Miles, Christopher O. (Journal of Agricultural and Food Chemistry, 2015)
Azaspiracids (AZAs) are marine biotoxins that induce human illness following the consumption of contaminated shellfish. EU regulation stipulates that only raw shellfish are tested, yet shellfish are often cooked prior to consumption. Analysis of raw and heat-treated mussels (Mytilus edulis) naturally contaminated with AZAs revealed significant differences in toxin profiles due to heat induced chemical conversions. Consistent with previous studies high levels of AZA3, 3, and AZA6, 6, were detected in some samples that were otherwise below the limit of quantitation before heating. Relative to AZA1, 1, in heat treated mussels the average (n=40) levels of 3 (range 11−502%) and 6 (range 3−170%) were 62% and 31% respectively. AZA4, 4, (range <1–27%), AZA5, 5 (range 1–21%) and AZA8, 8 (range 1–27%) were each ~ 5%, while AZA7, 7, AZA9, 9 and AZA10, 10 (range <1–8%) were each under 1.5%. Levels of 5 and 10 (and AZA13, 13 and AZA15, 15) increased after heating leading to the identification of novel carboxylated AZA precursors in raw shellfish extracts which were shown by deuterium labeling to be precursors for 5, 10, 13 and 15.
Keywords: Azaspiracids; marine biotoxins; shellfish; Mytilus edulis

Utilizing CMP-sialic acid analogs to unravel Neisseria gonorrhoeae lipooligosaccharide-mediated complement resistance and design novel therapeutics - Gulati, Sunita; Schoenhofen, Ian C.; Whitfield, Dennis M.; Cox, Andrew D.; Li, Jianjun; St. Michael, Frank; Vinogradov, Evgeny V.; Stupak, Jacek; Zheng, Bo; Ohnishi, Makoto; Unemo, Magnus; Lewis, Lise A.; et al. (PLOS Pathogens, 2015)
Neisseria gonorrhoeae deploys a novel immune evasion strategy wherein the lacto-N-neotetraose (LNnT) structure of lipooligosaccharide (LOS) is capped by the bacterial sialyltransferase, using host cytidine-5’-monophosphate (CMP)-activated forms of the nine-carbon nonulosonate (NulO) sugar N-acetyl-neuraminic acid (Neu5Ac), a sialic acid (Sia) abundant in humans. This allows evasion of complement-mediated killing by recruiting factor H (FH), an inhibitor of the alternative complement pathway, and by limiting classical pathway activation (“serum-resistance”). We utilized CMP salts of six additional natural or synthetic NulOs, Neu5Gc, Neu5Gc8Me, Neu5Ac9Ac, Neu5Ac9Az, legionaminic acid (Leg5Ac7Ac) and pseudaminic acid (Pse5Ac7Ac), to define structural requirements of Sia-mediated serum-resistance. While all NulOs except Pse5Ac7Ac were incorporated into the LNnT-LOS, only Neu5Gc incorporation yielded high-level serum-resistance and FH binding that was comparable to Neu5Ac, whereas Neu5Ac9Az and Leg5Ac7Ac incorporation left bacteria fully serum-sensitive and did not enhance FH binding. Neu5Ac9Ac and Neu5Gc8Me rendered bacteria resistant only to low serum concentrations. While serum-resistance mediated by Neu5Ac was associated with classical pathway inhibition (decreased IgG binding and C4 deposition), Leg5Ac7Ac and Neu5Ac9Az incorporation did not inhibit the classical pathway. Remarkably, CMP-Neu5Ac9Az and CMP-Leg5Ac7Ac each prevented serum-resistance despite a 100-fold molar excess of CMP-Neu5Ac in growth media. The concomitant presence of Leg5Ac7Ac and Neu5Ac on LOS resulted in uninhibited classical pathway activation. Surprisingly, despite near-maximal FH binding in this instance, the alternative pathway was not regulated and factor Bb remained associated with bacteria. Intravaginal administration of CMP-Leg5Ac7Ac to BALB/c mice infected with gonorrhea (including a multidrug-resistant isolate) reduced clearance times and infection burden. Bacteria recovered from CMP-Leg5Ac7Ac-treated mice were sensitive to human complement ex vivo, simulating in vitro findings. These data reveal critical roles for the Sia exocyclic side-chain in gonococcal serum-resistance. Such CMP-NulO analogs may provide a novel therapeutic strategy against the global threat of multidrug-resistant gonorrhea.
Keywords: Neisseria gonorrhoeae; complement inhibitors; complement system; complement activation; mouse models; sialic acids; flow cytometry; gonorrhea

A comprehensive evaluation of different radiation models in a gas turbine combustor under conditions of oxy-fuel combustion with dry recycle - Kez, V.; Liu, F.; Consalvi, J. L.; Ströhle, J.; Epple, B. (Journal of Quantitative Spectroscopy and Radiative Transfer, 2015)
The oxy-fuel combustion is a promising CO2 capture technology from combustion systems. This process is characterized by much higher CO2 concentrations in the combustion system compared to that of the conventional air-fuel combustion. To accurately predict the enhanced thermal radiation in oxy-fuel combustion, it is essential to take into account the non-gray nature of gas radiation. In this study, radiation heat transfer in a 3D model gas turbine combustor under two test cases at 20 atm total pressure was calculated by various non-gray gas radiation models, including the statistical narrow-band (SNB) model, the statistical narrow-band correlated-k (SNBCK) model, the wide-band correlated-k (WBCK) model, the full spectrum correlated-k (FSCK) model, and several weighted sum of gray gases (WSGG) models. Calculations of SNB, SNBCK, and FSCK were conducted using the updated EM2C SNB model parameters. Results of the SNB model are considered as the benchmark solution to evaluate the accuracy of the other models considered. Results of SNBCK and FSCK are in good agreement with the benchmark solution. The WBCK model is less accurate than SNBCK or FSCK. Considering the three formulations of the WBCK model, the multiple gases formulation is the best choice regarding the accuracy and computational cost. The WSGG model with the parameters of Bordbar et al. (2014) [20] is the most accurate of the three investigated WSGG models. Use of the gray WSSG formulation leads to significant deviations from the benchmark data and should not be applied to predict radiation heat transfer in oxy-fuel combustion systems. A best practice to incorporate the state-of-the-art gas radiation models for high accuracy of radiation heat transfer calculations at minimal increase in computational cost in CFD simulation of oxy-fuel combustion systems for pressure path lengths up to about 10 bar m is suggested.
Keywords: Oxy-fuel combustion; Non-gray gas radiation models; SNBCK; WBCK; FSCK; WSGG

Foreword - Sturgeon, R. (New Developments in Mass Spectrometry, 2015)

Factors affecting the performance of ceiling-based PIR occupancy sensors in offices - Newsham, Guy R.; Xue, Henry; Valdes, Julio J.; Scarlett, Elizabeth; Arsenault, Chantal; Burns, Greg J.; Kruithof, Steve; Shen, Weiming (Proceedings of the Illuminating Engineering Society of North America (IESNA) Annual Conference, 2015)
As part of a larger project on occupancy sensing, we collected 5 Hz occupancy detection data (aggregated to the 15-second level) from a commercially-available ceiling-based PIR sensor. Identical sensors were deployed in 28 offices for up to a month per office. Ground truth data were collected simultaneously using a pressure-sensitive floor mat. We evaluated the accuracy (overall, as well as false positives and false negatives) and energy-saving potential in each office with various timeout periods applied post-hoc. The data revealed relatively poor overall detection performance at the 15-second level. Adding a timeout period of 20 minutes produced reasonable false negative performance for the top quartile of offices, but reduced potential energy savings to 65% of the unoccupied time. The results support efforts to improve occupancy sensing in order to garner greater energy savings.

Improving the well-being of high-Arctic residents by modifying light exposure while saving energy - Newsham, Guy R.; Veitch, Jennifer A.; Arsenault, Chantal D.; Kruithof, Steven; Mancini, Sandra; Galasiu, Anca D.; Amow, Gisele (Proceedings of the Illuminating Engineering Society of North America (IESNA) Annual Conference, 2015)
We conducted a lighting retrofit study at Canadian Forces Station Alert (latitude 82°30’N), the world’s most northerly, permanently inhabited settlement. Existing recessed fluorescent troffers with nominally 6500K T8 lamps on electronic ballasts, providing ambient lighting in selected offices, were replaced, one-for-one, by 5000K LED luminaires. The new luminaires had higher efficacy and a high colour rendering index, and were dimmable at the room level with a wall control. A variety of well-being measures pertaining to the office occupants, and energy use data, were collected before and after the retrofit. Preliminary results suggest that, as predicted, the enhanced features of the LED system led to a generally better appraisal of the lighted environment, and substantial lighting energy savings of ~30%.

An experimental investigation on the combustion and emissions performance of a natural gas-diesel dual fuel engine at low and medium loads - Guo, Hongsheng; Neill, W. Stuart; Liko, Brian (Proceedings of the ASME 2015 Internal Combustion Engine Division Fall Technical Conference, 2015)
Natural gas is an abundant and inexpensive fuel in North America. It produces lower greenhouse gas emissions than diesel fuel when burned in an internal combustion engine. It is also considered to be a clean fuel because it generates lower particulate matter emissions than diesel fuel during combustion. In this study, an experimental study was conducted to investigate the combustion and emissions performance of a natural gas – diesel dual fuel engine at low and medium loads. A single cylinder direct injection diesel engine was modified to operate as the dual fuel engine. The diesel fuel was directly injected into the cylinder, while natural gas was injected into the intake port. The operating conditions, such as engine speed, load, intake temperature and pressure, were well controlled during the experiment. The effect of natural gas fraction on energy efficiency, cylinder pressure, exhaust temperature, and combustion stability were recorded and analyzed. The emissions data, including particulate matter, nitric oxides, carbon monoxide, and methane at various natural gas fractions and operating conditions were also analyzed. The results showed that natural gas – diesel dual fuel combustion slightly decreased brake thermal efficiency at low and medium load conditions and significantly reduced carbon dioxide and particulate matter emissions. Methane and NOx emissions increased in dual fuel combustion mode compared to diesel operation. The variation of carbon monoxide emissions in dual fuel mode depended on load and speed conditions.
Keywords: combustion; fuels; engines; stress; natural gas; diesel; emissions

LO Andromedae: a W-type overcontact eclipsing binary - Nelson, R. H.; Robb, R. M. (Information Bulletin on Variable Stars, 2015)

Towards a first principles model of curling ice friction and curling stone dynamics - Lozowski, E.P.; Szilder, K.; Maw, S.; Morris, A.; Poirier, L.; Kleiner, B. (Proceedings of the International Offshore and Polar Engineering Conference, 2015)
Scientific investigations to measure and explain the curl (lateral displacement) of a granite stone sliding on ice in the sport of curling go back almost 100 years (Harrington, 1924). Nevertheless, some prominent researchers in the field remain baffled as to the physical explanation of this lateral displacement. And no one has thus far been able to produce a quantitative model, from first principles, that predicts all the documented characteristics of the observed curl. In this paper, we describe our progress towards producing such a numerical model. After reviewing the history of scientific research on curling, we summarize the experimental observations (quantitative and qualitative) that need to be explained by any successful model; we also summarize the areas of general agreement. Lastly, we formulate a numerical model of ice friction for a non-rotating curling stone, which successfully predicts its longitudinal deceleration. The model also successfully predicts the rotational deceleration of a non-translating curling stone. However, a numerical model for the lateral acceleration that produces the observed curl remains elusive. Copyright © 2015 by the International Society of Offshore and Polar Engineers (ISOPE).
Keywords: ice; ice friction; curling

Conical structures in ice: Relevant relationships for ISO 19906 - Barker, A.; Sudom, D.; Sayed, M. (Proceedings of the International Conference on Port and Ocean Engineering under Arctic Conditions, POAC, 2015)
Conical shapes are often chosen for structures that are exposed to floating ice, such as offshore drilling platforms, bridge piers and offshore wind turbine foundations. The flexural ice failure promoted by the shape of a cone can lead to lower forces on the structure than compressive failure, which would take place if ice is to encounter a vertical surface. In spite of the wide use of conical structures, many aspects of their performance in ice covered waters remain poorly understood. For example, the ISO 19906 Arctic Offshore Structures standard does not provide guidance with respect to ridge keel loading on cones, or the height to which ice could ride up on a conical structure. With the planned revision of that document presently beginning, it is important to address the guidance gaps in order to include new insights in the revised standard. Previous work by the authors employed a numerical model of ice dynamics in order to predict ice failure patterns and forces on various conical structures. The present work extends those studies and predicts the extent of ice ride-up on the structures; the roles of the waterline width of the structure and ice thickness are discussed. The resulting ice force estimates are comparable to those predicted by an approach recommended in ISO 19906. Both the plastic and elastic beam-bending methods recommended by ISO 19906 for determining ice actions on conical structures require an initial assumption of the maximum height of accumulated rubble. Little guidance is given in ISO 19906, except to note that this height depends on the structure geometry and ice regime. For the present calculations, the chosen rubble height for each ice load calculation is based on the results of the corresponding numerical model run. Previous numerical studies by the authors have also been reviewed and the estimates of ice ride-up heights summarized. Numerical simulations could be expanded to produce a comprehensive range of ride-up values to support users of ISO 19906.
Keywords: Bridge piers; Drilling platforms; Meteorological problems; Numerical models; Ocean engineering; Offshore drilling; Offshore structures; Offshore wind turbines; Safety engineering; Wind turbines; Compressive failure; Conical structures; Failure patterns; Ice covered waters; Ice thickness; Provide guidances; Structure geometry; Vertical surface; Ice

Pilot head and body vibration in response to main rotor track-and-balance tuning - Craig, G. Lorne; Wright-Beatty, Heather E.; Alexander, Marc; Keillor, Jocelyn (Annual Forum Proceedings - AHS International, 2015)
While night vision goggles (NVG) have become an essential part of rotorcraft night flight operations for the military, there has been an increase in the reports of neck strain and neck pain in flight crews using the equipment. The neck is required to support the weight of the NVG on the helmet and is constantly stabilizing the head to counteract the helicopter vibrations. The current flight tests examined the magnitude of vibrations at the pilot's head while tuning or slightly de-tuning the track-and-balance of the main rotor on the NRC Bell 412 as well as measuring the physiological response of the pilot to the resulting vibration levels. While the minimal detuning of the main rotor increased the vibration of the helicopter (by about 0.006g), the increase in vibration at the pilots head was substantial (a 0.01g increase). Physiological measures showed increased heart rate and decreased tactile sensitivity as the helicopter vibration increased. While it is likely that the increased vibration resulting from poor rotor track-and-balance increases the level of neck strain on pilots, further research is required to determine the magnitude of these effects and the maximum safe exposure level
Keywords: Goggles; Helicopters; Physiology; Body vibration; Flight operation; Helicopter vibration; Night vision goggles; Physiological measures; Physiological response; Tactile sensitivities; Vibration level; Physiological models

Antimicrobial susceptibility of Canadian isolates of Helicobacter pylori in Northeastern Ontario - Nelson, F.; Ybazeta, G.; Chapman, K.; Fraleigh, N.L.; Letto, R.; Altman, E.; Diaz-Mitoma, F. (Canadian Journal of Infectious Diseases and Medical Microbiology, 2015)
BACKGROUND: Helicobacter pylori plays a significant role in gastritis and ulcers. It is a carcinogen as defined by the WHO, and infection can result in adenocarcinomas and mucosa-associated lymphoid tissue lymphomas. In Canada, rates of antimicrobial resistance are relatively unknown, with very few studies conducted in the past 15 years. Objective: To examine rates of resistance in Sudbury, Ontario, compare antimicrobial susceptibility methods and attempt to determine the molecular basis of antibiotic resistance. METHODS: Patients attending scheduled visits at Health Sciences North (Sudbury, Ontario) provided gastric biopsy samples on a volunteer basis. In total, 20 H pylori isolates were collected, and antimicrobial susceptibility testing (on amoxicillin, tetracycline, metronidazole, ciprofloxacin, levofloxacin and clarithromycin) was conducted using disk diffusion and E-test methods. Subsequently, genomic DNA from these isolates was sequenced to detect mutations associated with antimicrobial resistance. RESULTS: Sixty-five percent of the isolates were found to be resistant to at least one of the listed antibiotics according to E-test. Three isolates were found to be resistant to ≥3 of the above-mentioned antibiotics. Notably, 25% of the isolates were found to be resistant to both metronidazole and clarithromycin, two antibiotics that are normally prescribed as part of first-line regimens in the treatment of H pylori infections in Canada and most of the world. Among the resistant strains, the sequences of 23S ribosomal RNA and gyrA, which are linked to clarithromycin and ciprofloxacin/levofloxacin resistance, respectively, revealed the presence of known point mutations associated with antimicrobial resistance. CONCLUSIONS: In general, resistance to metronidazole, ciprofloxacin/ levofloxacin and clarithromycin has increased since the studies in the early 2000s. These results suggest that surveillance programs of H pylori antibiotic resistance may need to be revisited or improved to prevent antimicrobial therapy failure.
Keywords: amoxicillin; antibiotic agent; ciprofloxacin; clarithromycin; genomic DNA; levofloxacin; metronidazole; RNA 23S; tetracycline; antibiotic resistance; antibiotic sensitivity; Article; bacterium isolate; Canada; disk diffusion; epsilometer test; gene; gene mutation; gyra gene; Helicobacter pylori; human; human tissue; major clinical study; minimum inhibitory concentration; nonhuman; stomach biopsy

Subsonic wind tunnel testing of various parachute types - Underwood, J.C.; Saundersy, A.; Rogersy, S.B.; Stephen Lingardz, J.; Marraffa, L.; Ferracina, L.; Larosek, G.L.; McTavish, S.A.M. (Aerodynamic Decelerator Systems Technology Conferences, 2015)
A wind tunnel test campaign has been carried out to investigate the performance of seven parachute types as part of a European Space Agency programme researching potential subsonic parachutes for future Mars missions. The overall programme also includes high altitude sub-scale drop tests and low altitude, full-scale drop tests of some of the parachute designs. The results of the wind tunnel test campaign are presented and the data for the different designs of parachute are compared.. © 2015, AIAA American Institute of Aeronautics and Astronautics. All rights reserved.
Keywords: Drops; Martian surface analysis; Parachutes; Wind stress; Drop test; European Space Agency; Low altitudes; Mars missions; Parachute design; Subsonic wind tunnels; Wind tunnel tests; Wind tunnels

Implementation of an efficient monte carlo calculation for CBCT scatter correction: Phantom study - Watson, P.G.F.; Mainegra-Hing, E.; Tomic, N.; Seuntjens, J. (Journal of Applied Clinical Medical Physics, 2015)
Cone-beam computed tomography (CBCT) images suffer from poor image quality, in a large part due to contamination from scattered X-rays. In this work, a Monte Carlo (MC)-based iterative scatter correction algorithm was implemented on measured phantom data acquired from a clinical on-board CBCT scanner. An efficient EGSnrc user code (egs_cbct) was used to transport photons through an uncorrected CBCT scan of a Catphan 600 phantom. From the simulation output, the contribution from primary and scattered photons was estimated in each projection image. From these estimates, an iterative scatter correction was performed on the raw CBCT projection data. The results of the scatter correction were compared with the default vendor reconstruction. The scatter correction was found to reduce the error in CT number for selected regions of interest, while improving contrast-to-noise ratio (CNR) by 18%. These results demonstrate the performance of the proposed scatter correction algorithm in improving image quality for clinical CBCT images.
Keywords: cone-beam CT; scatter correction; EGSnrc; Monte Carlo

Ionically-functionalized poly(thiophene) conductive polymers as binders for silicon and graphite anodes for li-ion batteries - Salem, Nuha; Lavrisa, Matt; Abu-Lebdeh, Yaser (Energy Technology, 2015)
Next-generation anode materials for Li-ion batteries such as silicon can lead to ten times more capacity than the state-of-the-art graphite. However, novel binders are required to overcome the detrimental effects of volume changes during battery cycling of silicon because of the poor chemical interaction and electrical conductivity between silicon and the binder. Most studies focus on either ionic binders or electrically conductive binders, but herein it was demonstrated that a new family of polymers based on electrically conductive poly(thiophene) functionalized with an ionic alkyl carboxylate groups of various lengths can successfully work as multifunctional binders for silicon and commercial graphite anodes in Li-ion battery half-cells. It was determined that the polymer with shorter side chain (PT-3-LiA) gives the highest reversible capacity upon pairing with graphite or silicon, reaching 3000 mAh g−1 in the case of the latter, a capacity 500 mAh g−1 (≈22 %) higher than those obtained with the electrically, but non-ionically, conductive PEDOT:PSS binder and the ionically, but non-electrically, conductive sodium carboxymethyl cellulose (NaCMC) binder. It is demonstrated that the superior performance of this new type of multifunctional binders can be attributed to their ability to maintain their doping level and conductivity as well as due to good interaction with the silicon surface during cycling.

Data processing and analysis for the 2012 Canadian Forces 3D anthropometric survey - Shu, Chang; Xi, Pengcheng; Keefe, Allan (Procedia Manufacturing, 2015)
The 2012 Canadian Forces Anthropometric Survey (CFAS 2012) is the first major 3D anthropometric survey of Canadian Forces personnel. 2200 full-body scans were conducted, together with traditional anthropometric measurements. This survey aims at providing accurate, detailed, and up-to-date body shape information for equipment design and procurement. In this paper, we describe the data processing and analysis of this dataset. This includes de-noising, template fitting, landmark identification, and statistical shape analysis. We also compare the military personnel with the general North American population using the CAESAR dataset.

Long-term motor recovery after severe traumatic brain injury: beyond established limits - DʼArcy, R. C. N.; Lindsay, D. S.; Song, X.; Gawryluk, J. R.; Greene, D.; Mayo, C.; Ghosh Hajra, S.; Mandziuk, L.; Mathieson, J.; Greene, T. (Journal of head trauma rehabilitation, 2015)
OBJECTIVE: To report neural plasticity changes after severe traumatic brain injury. SETTING: Case-control study. PARTICIPANTS: Canadian soldier, Captain Trevor Greene survived a severe open-traumatic brain injury during a 2006 combat tour in Afghanistan. DESIGN: Longitudinal follow-up for more than 6 years. MAIN MEASURES: Twelve longitudinal functional magnetic imaging (fMRI) examinations were conducted to investigate lower limb activation changes in association with clinical examination. Trevor Greeneʼs lower limb fMRI activation was compared with control fMRI activation of (1) mental imagery of similar movement and (2) matched control subject data. RESULTS: Trevor Greeneʼs motor recovery and corresponding fMRI activation increased significantly over time (F = 32.54, P < .001). Clinical measures of functional recovery correlated strongly with fMRI motor activation changes (r = 0.81, P = .001). By comparison, while Trevor Greeneʼs mental imagery activated similar motor regions, there was no evidence of fMRI activation change over time. While comparable, control motor activation did not change over time and there was no significant mental imagery activation. CONCLUSION: Motor function recovery can occur beyond 6 years after severe traumatic brain injury, both in neural plasticity and clinical outcome. This demonstrates that continued benefits in physical function due to rehabilitative efforts can be achieved for many years following injury. The finding challenges current practices and assumptions in rehabilitation following traumatic brain injury.

Digitization of trait representation in microarray data analysis of wheat infected by fusarium graminearum - Pan, Youlian; Ouellet, Thérèse; Phan, Sieu; Tchagang, Alain; Fauteux, François; Tulpan, Dan (Conference on Computational Intelligence in Bioinformatics and Computational Biology, 2015)
Fusarium head blight (FHB) limits wheat yield and compromises grain quality. We investigated differentially expressed genes after FHB challenge. FHB-susceptible and -resistant common wheat (Triticum aestivum) cultivars were challenged with the toxigenic fungus Fusarium graminearum and gene expression was analyzed using 61K Affymetrix wheat microarrays. We digitized trait specificity in the susceptible and resistant lines with and without the infection in order to facilitate subsequent data mining. We discovered various patterns of differential gene expression between susceptible and resistant lines in response to the infection. We performed association network analysis among genes in clusters significantly correlated with one or more quantitative trait loci known to contribute to Fusarium resistance. We found 11 interconnected hub genes responsive to FHB infection and significantly correlated with wheat resistance to FHB, among which two are predicted to encode a polygalacturonase-inhibiting protein (PGIP1).
Keywords: microarray; digitization; Fusarium head blight; wheat; disease resistance

Multivariate optimization of photochemical vapor generation for direct determination of arsenic in seawater by inductively coupled plasma mass spectrometry - Gao, Ying; Sturgeon, Ralph E.; Mester, Zoltán; Hou, Xiandeng; Yang, Lu (Analytica Chimica Acta, 2015)
Photochemical vapor generation (PVG) sample introduction coupled to inductively coupled plasma mass spectrometry (ICPMS) is described for the determination of As in seawater. A Plackett–Burman design (PBD) and central composite design (CCD) were employed to evaluate the significance of experimental variables relevant to the optimization of PVG-ICPMS detection. The impact of the saline matrix on the suppression of analyte signal was eliminated by use of a mixture of 20% (v/v) formic and 20% acetic acid (v/v) as the photochemical reductants. Optimized conditions yielded equivalent PVG generation efficiencies for As(III), As(V), monomethylarsonic acids (MMAs) and dimethylarsinic acids (DMAs), permitting direct and rapid determination of total arsenic in seawater without any other sample pre-treatment. Quantitation was accomplished using one point gravimetric standard addition along with a spike of 82Se internal standard to compensate for signal drift and fluctuation during analysis. The resulting method detection limit of 3 pg g−1 (3σ) provided a 15-fold improvement over that obtained using direct solution nebulization, and is comparable to that for conventional chemical hydride generation (HG)-ICPMS. Accuracy was demonstrated by analysis of two Certified Reference Materials (NASS-6 and CASS-5 seawater) with satisfying results characterized by precisions of 3.5% and 3.2% RSD for CASS-5 and NASS-6, respectively.
Keywords: UV photochemical vapor generation; As; One point gravimetric standard addition and internal standardization; Inductively coupled plasma mass spectrometry

Prebiotic effects of diet supplemented with the cultivated red seaweed Chondrus crispus or with fructo-oligo-saccharide on host immunity, colonic microbiota and gut microbial metabolites - Liu, J.; Kandasamy, S.; Zhang, J.; Kirby, C.W.; Karakach, T.; Hafting, J.; Critchley, A.T.; Evans, F.; Prithiviraj, B. (BMC Complementary and Alternative Medicine, 2015)
Background: Gastrointestinal microbial communities are diverse and are composed of both beneficial and pathogenic groups. Prebiotics, such as digestion-resistant fibers, influence the composition of gut microbiota, and can contribute to the improvement of host health. The red seaweed Chondrus crispus is rich in dietary fiber and oligosaccharides, however its prebiotic potential has not been studied to date. Methods: Prebiotic effects were investigated with weaning rats fed a cultivated C. crispus-supplemented diet. Comparison standards included a fructo-oligo-saccharide (FOS) diet and a basal diet. The colonic microbiome was profiled with a 16S rRNA sequencing-based Phylochip array. Concentrations of short chain fatty acids (SCFAs) in the feacal samples were determined by gas chromatography with a flame ionization detector (GC-FID) analysis. Immunoglobulin levels in the blood plasma were analyzed with an enzyme-linked immunosorbent assay (ELISA). Histo-morphological parameters of the proximal colon tissue were characterized by hematoxylin and eosin (H&E) staining. Results: Phylochip array analysis indicated differing microbiome composition among the diet-supplemented and the control groups, with the C. crispus group (2.5 % supplementation) showing larger separation from the control than other treatment groups. In the 2.5 % C. crispus group, the population of beneficial bacteria such as Bifidobacterium breve increased (4.9-fold, p = 0.001), and the abundance of pathogenic species such as Clostridium septicum and Streptococcus pneumonia decreased. Higher concentrations of short chain fatty acids (i.e., gut microbial metabolites), including acetic, propionic and butyric acids, were found in faecal samples of the C. crispus-fed rats. Furthermore, both C. crispus and FOS supplemented rats showed significant improvements in proximal colon histo-morphology Higher faecal moisture was noted in the 2.5 % C. crispus group, and elevated plasma immunoglobulin (IgA and IgG) levels were observed in the 0.5 % C. crispus group, as compared to the basal feed group. Conclusions: The results suggest multiple prebiotic effects, such as influencing the composition of gut microbial communities, improvement of gut health and immune modulation in rats supplemented with cultivated C. crispus.
Keywords: acid; fructose oligosaccharide; immunoglobulin; prebiotic agent; RNA 16S; animal experiment; ascending colon; Bifidobacterium breve; body weight; Chondrus crispus; Clostridium septicum; enzyme linked immunosorbent assay; feces analysis; gas chromatography; immune response; immunoglobulin blood level; immunomodulation; organ weight; rat; RNA sequence; seaweed; Streptococcus pneumonia

Measurements of differential reflectivity in snowstorms and warm season stratiform systems - Williams, E.R.; Smalley, D.J.; Donovan, M.F.; Hallowell, R.G.; Hood, K.T.; Bennett, B.J.; Evaristo, R.; Stepanek, A.; Bals-Elsholz, T.; Cobb, J.; Ritzman, J.; Korolev, A.; et al. (Journal of Applied Meteorology and Climatology, 2015)
The organized behavior of differential radar reflectivity (ZDR) is documented in the cold regions of a wide variety of stratiform precipitation types occurring in both winter and summer. The radar targets and attendant cloud microphysical conditions are interpreted within the context of measurements of ice crystal types in laboratory diffusion chambers in which humidity and temperature are both stringently controlled. The overriding operational interest here is in the identification of regions prone to icing hazards with long horizontal paths. Two predominant regimes are identified: category A, which is typified by moderate reflectivity (from 10 to 30 dBZ) and modest +ZDR values (from 0 to +3 dB) in which both supercooled water and dendritic ice crystals (and oriented aggregates of ice crystals) are present at a mean temperature of -13°C, and category B, which is typified by small reflectivity (from -10 to +10 dBZ) and the largest +ZDR values (from +3 to +7 dB), in which supercooled water is dilute or absent and both flat-plate and dendritic crystals are likely. The predominant positive values for ZDR in many case studies suggest that the role of an electric field on ice particle orientation is small in comparison with gravity. The absence of robust +ZDR signatures in the trailing stratiform regions of vigorous summer squall lines may be due both to the infusion of noncrystalline ice particles (i.e., graupel and rimed aggregates) from the leading deep convection and to the effects of the stronger electric fields expected in these situations. These polarimetric measurements and their interpretations underscore the need for the accurate calibration of ZDR.
Keywords: Atmospheric electricity; Cloud microphysics; Radars/Radar observations

Engineering 3D cellularized collagen gels for vascular tissue regeneration - Meghezi, Sébastien; Seifu, Dawit G.; Bono, Nina; Unsworth, Larry; Mequanint, Kibret; Mantovani, Diego (Journal of Visualized Experiments, 2015)
Synthetic materials are known to initiate clinical complications such as inflammation, stenosis, and infections when implanted as vascular substitutes. Collagen has been extensively used for a wide range of biomedical applications and is considered a valid alternative to synthetic materials due to its inherent biocompatibility (i.e., low antigenicity, inflammation, and cytotoxic responses). However, the limited mechanical properties and the related low hand-ability of collagen gels have hampered their use as scaffold materials for vascular tissue engineering. Therefore, the rationale behind this work was first to engineer cellularized collagen gels into a tubular-shaped geometry and second to enhance smooth muscle cells driven reorganization of collagen matrix to obtain tissues stiff enough to be handled. The strategy described here is based on the direct assembling of collagen and smooth muscle cells (construct) in a 3D cylindrical geometry with the use of a molding technique. This process requires a maturation period, during which the constructs are cultured in a bioreactor under static conditions (without applied external dynamic mechanical constraints) for 1 or 2 weeks. The “static bioreactor” provides a monitored and controlled sterile environment (pH, temperature, gas exchange, nutrient supply and waste removal) to the constructs. During culture period, thickness measurements were performed to evaluate the cells-driven remodeling of the collagen matrix, and glucose consumption and lactate production rates were measured to monitor the cells metabolic activity. Finally, mechanical and viscoelastic properties were assessed for the resulting tubular constructs. To this end, specific protocols and a focused know-how (manipulation, gripping, working in hydrated environment, and so on) were developed to characterize the engineered tissues.

Identification of interactions between abscisic acid and ribulose-1,5-bisphosphate carboxylase/oxygenase - Galka, Marek M.; Rajagopalan, Nandhakishore; Buhrow, Leann M.; Nelson, Ken M.; Switala, Jacek; Cutler, Adrian J.; Palmer, David R. J.; Loewen, Peter C.; Abrams, Suzanne R.; Loewen, Michele C. (PLoS ONE, 2015)
Abscisic acid ((+)-ABA) is a phytohormone involved in the modulation of developmental processes and stress responses in plants. A chemical proteomics approach using an ABA mimetic probe was combined with in vitro assays, isothermal titration calorimetry (ITC), xray crystallography and in silico modelling to identify putative (+)-ABA binding-proteins in crude extracts of Arabidopsis thaliana. Ribulose-1,5-bisphosphate carboxylase/oxygenase (Rubisco) was identified as a putative ABA-binding protein. Radiolabelled-binding assays yielded a Kd of 47 nM for (+)-ABA binding to spinach Rubisco, which was validated by ITC, and found to be similar to reported and experimentally derived values for the native ribulose- 1,5-bisphosphate (RuBP) substrate. Functionally, (+)-ABA caused only weak inhibition of Rubisco catalytic activity (Ki of 2.1 mM), but more potent inhibition of Rubisco activation (Ki of ~ 130 μM). Comparative structural analysis of Rubisco in the presence of (+)-ABA with RuBP in the active site revealed only a putative low occupancy (+)-ABA binding site on the surface of the large subunit at a location distal from the active site. However, subtle distortions in electron density in the binding pocket and in silico docking support the possibility of a higher affinity (+)-ABA binding site in the RuBP binding pocket. Overall we conclude that (+)-ABA interacts with Rubisco. While the low occupancy (+)-ABA binding site and weak non-competitive inhibition of catalysis may not be relevant, the high affinity site may allow ABA to act as a negative effector of Rubisco activation.
Keywords: abscisic acid; hormone binding protein; oxygenase; ribulose 1,5 bisphosphate oxygenase; ribulosebisphosphate carboxylase; unclassified drug; vegetable protein; binding affinity; catalysis; comparative study; computer model; controlled study; electron; enzyme activation; enzyme active site; enzyme activity; enzyme inhibition; enzyme structure; enzyme substrate; isothermal titration calorimetry; molecular docking; protein protein interaction; spinach; structure analysis; validation study

A systematic study of glycopeptide esterification for the semi-quantitative determination of sialylation in antibodies - Gomes De Oliveira, Andrey Giovanni; Roy, Rini; Raymond, Céline; Bodnar, Edward D.; Tayi, Venkata S.; Butler, Michael; Durocher, Yves; Perreault, Hélène (Rapid Communications in Mass Spectrometry, 2015)
Rationale In the expression of recombinant proteins, an important parameter to control or influence is their level of sialylation. Matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) mass spectrometric (MS) methods tend to either underestimate (positive mode) or overestimate (negative mode) the content of sialylated vs. neutral glycans in glycoproteins. Esterification methods have been developed for free sialylated glycans and sialylated Asn-glycans, allowing these acidic groups to ionize with the same efficiency as neutral sugars. Methods Here we describe a method which modifies glycopeptides by esterification. This simple procedure is applied to glycopeptides isolated from tryptic digests of monoclonal antibodies (mAbs), some highly sialylated. To better understand the effect of esterification on the peptide backbone, synthetic EEQYNSTYR was esterified and studied by tandem mass spectrometry (MS/MS). Acetamidation of EEQYNSTYR was also studied as some mAb samples had been overalkylated prior to tryptic digestion. Results As a general trend, ethyl-esterification or lactonization is observed for each sialic acid on glycoforms of EEQYNSTYR (the N-glycosylated tryptic peptide of IgG Fc), depending on the branching position of the sialic acid (α2,3 or α2,6). Esterification also affects the carboxyl groups in the peptide, including the C-terminal COOH. Conclusions For antibody analysis, MALDI-MS ion abundances give a better semi-quantitative estimate of sialylation levels for esterified than for unreacted glycopeptides. The method is simple to use and helps to differentiate the branching patterns of sialic acids in antibodies.

Characterization of shrimp oil from Pandalus borealis by high performance liquid chromatography and high resolution mass spectrometry - Jiao, Guangling; Hui, Joseph P. M.; Burton, Ian W.; Thibault, Marie-Hélène; Pelletier, Claude; Boudreau, Josée; Tchoukanova, Nadia; Subramanian, Balaji; Djaoued, Yahia; Ewart, Stephen; Gagnon, Jacques; Ewart, Kathryn Vanya; et al. (Marine Drugs, 2015)
Northern shrimp (Pandalus borealis) oil, which is rich in omega-3 fatty acids, was recovered from the cooking water of shrimp processing facilities. The oil contains significant amounts of omega-3 fatty acids in triglyceride form, along with substantial long-chain monounsaturated fatty acids (MUFAs). It also features natural isomeric forms of astaxanthin, a nutritional carotenoid, which gives the oil a brilliant red color. As part of our efforts in developing value added products from waste streams of the seafood processing industry, we present in this paper a comprehensive characterization of the triacylglycerols (TAGs) and astaxanthin esters that predominate in the shrimp oil by using HPLC-HRMS and MS/MS, as well as 13C-NMR. This approach, in combination with FAME analysis, offers direct characterization of fatty acid molecules in their intact forms, including the distribution of regioisomers in TAGs. The information is important for the standardization and quality control, as well as for differentiation of composition features of shrimp oil, which could be sold as an ingredient in health supplements and functional foods.
Keywords: astaxanthin; edible oil; fatty acid ester; shrimp oil; triacylglycerol; unclassified drug; carbon nuclear magnetic resonance; fatty acid analysis; gas chromatography; high performance liquid chromatography; lipid composition; mass spectrometry; Pandalus borealis; tandem mass spectrometry; Decapoda (Crustacea)

Instrumented and Vickers Indentation for the characterization of stiffness, hardness and toughness of zirconia toughened Al2O3 and SiC Armor - Nastic, Aleksandra; Merati, Ali; Bielawski, Mariusz; Bolduc, Manon; Fakolujo, Olaniyi; Nganbe, Michel (Journal of Materials Science and Technology, 2015)
Instrumented and Vickers indentation testing and microstructure analysis were used to investigate zirconia toughened alumina (ZTA) and silicon carbide (SiC). Several equations were studied to relate the Vickers indentation hardness, Young's modulus and crack behavior to the fracture toughness. The fracture in SiC is unstable and occurs primarily by cleavage leading to a relatively low toughness of 3MPam1/2, which may be inappropriate for multi-hit capability. ZTA absorbs energy by plastic deformation, pore collapse, crack deviation and crack bridging and exhibits time dependent creep. With a relatively high toughness around 6.6MPam1/2, ZTA is promising for multi-hit capability. The higher accuracy of median equations in calculating the indentation fracture toughness and the relatively high c/a ratios above 2.5 suggest median type cracking for both SiC and ZTA. The Young's modulus of both ceramics was most accurately measured at lower indentation loads of about 0.5kgf, while more accurate hardness and fracture toughness values were obtained at intermediate and at higher indentation loads beyond 5kgf, respectively. A strong indentation size effect (ISE) was observed in both materials. The load independent hardness of SiC is 2563 HV, putting it far above the standard armor hardness requirement of 1500 HV that is barely met by ZTA.
Keywords: Alumina; Armor; Ceramic materials; Cracks; Elastic moduli; Fracture; Silicon carbide; Vickers hardness; Zirconia; Fracture toughness values; Indentation fracture toughness; Indentation size effects; Microstructure analysis; Silicon carbides (SiC); Vickers indentation testing; Zirconia toughened alumina; Fracture toughness

Filaments in the lupus molecular clouds - Benedettini, M.; Schisano, E.; Pezzuto, S.; Elia, D.; André, P.; Könyves, V.; Schneider, N.; Tremblin, P.; Arzoumanian, D.; Di Giorgio, A. M.; Di Francesco, J.; Hill, T.; et al. (Monthly Notices of the Royal Astronomical Society, 2015)
We have studied the filaments extracted from the column density maps of the nearby Lupus 1, 3, and 4 molecular clouds, derived from photometric maps observed with the Herschel satellite. Filaments in the Lupus clouds have quite low column densities, with a median value of ~1.5 × 1021 cm-2 and most have masses per unit length lower than the maximum critical value for radial gravitational collapse. Indeed, no evidence of filament contraction has been seen in the gas kinematics. We find that some filaments, that on average are thermally subcritical, contain dense cores that may eventually form stars. This is an indication that in the low column density regime, the critical condition for the formation of stars may be reached only locally and this condition is not a global property of the filament. Finally, in Lupus we find multiple observational evidences of the key role that the magnetic field plays in forming filaments, and determining their confinement and dynamical evolution.
Keywords: stars: formation; ISM: clouds

Preparation, characterization, and safety evaluation of poly(lactide-co-glycolide) nanoparticles for protein delivery into macrophages - Guedj, A.-S.; Kell, A.J.; Barnes, M.; Stals, S.; Gonçalves, D.; Girard, D.; Lavigne, C. (International Journal of Nanomedicine, 2015)
Following infection, HIV establishes reservoirs within tissues that are inaccessible to optimal levels of antiviral drugs or within cells where HIV lies latent, thus escaping the action of anti-HIV drugs. Macrophages are a persistent reservoir for HIV and may contribute to the rebound viremia observed after antiretroviral treatment is stopped. In this study, we further investigate the potential of poly(lactic-co-glycolic) acid (PLGA)-based nanocarriers as a new strategy to enhance penetration of therapeutic molecules into macrophages. We have prepared stable PLGA nanoparticles (NPs) and evaluated their capacity to transport an active molecule into the human monocyte/macrophage cell line THP-1 using bovine serum albumin (BSA) as a proof-of-concept compound. Intracellular localization of fluorescent BSA molecules encapsulated into PLGA NPs was monitored in live cells using confocal microscopy, and cellular uptake was quantified by flow cytometry. In vitro and in vivo toxicological studies were performed to further determine the safety profile of PLGA NPs including inflammatory effects. The size of the PLGA NPs carrying BSA (PLGA-BSA) in culture medium containing 10% serum was ~126 nm in diameter, and they were negatively charged at their surface (zeta potential =-5.6 mV). Our confocal microscopy studies and flow cytometry data showed that these PLGA-BSA NPs are rapidly and efficiently taken up by THP-1 monocyte-derived macrophages (MDMs) at low doses. We found that PLGA-BSA NPs increased cellular uptake and internalization of the protein in vitro. PLGA NPs were not cytotoxic for THP-1 MDM cells, did not modulate neutrophil apoptosis in vitro, and did not show inflammatory effect in vivo in the murine air pouch model of acute inflammation. In contrast to BSA alone, BSA encapsulated into PLGA NPs increased leukocyte infiltration in vivo, suggesting the in vivo enhanced delivery and protection of the protein by the polymer nanocarrier. We demonstrated that PLGA-based nanopolymer carriers are good candidates to efficiently and safely enhance the transport of active molecules into human MDMs. In addition, we further investigated their inflammatory profile and showed that PLGA NPs have low inflammatory effects in vitro and in vivo. Thus, PLGA nanocarriers are promising as a drug delivery strategy in macrophages for prevention and eradication of intracellular pathogens such as HIV and Mycobacterium tuberculosis.
Keywords: bovine serum albumin; nanocarrier; polyglactin; cell; confocal microscopy; flow cytometry; fluorescence analysis; internalization; macrophage; monocyte; nanoencapsulation; zeta potential

Facile and nonradiation pretreated membrane as a high conductive separator for li-ion batteries - Li, B.; Li, Y.; Dai, D.; Chang, K.; Tang, H.; Chang, Z.; Wang, C.; Yuan, X.-Z.; Wang, H. (ACS Applied Materials and Interfaces, 2015)
PolPolyolefin membranes are widely used as separators in commercialized Li-ion batteries. They have less polarized surfaces compared with polarized molecules of electrolyte, leading to a poor wetting state for separators. Radiation pretreatments are often adopted to solve such a problem. Unfortunately, they can only activate several nanometers deep from the surface, which limits the performance improvement. Here we report a facile and scalable method to polarize polyolefin membranes via a chemical oxidation route. On the surfaces of pretreated membrane, layers of poly(ethylene oxide) and poly(acrylic acid) can easily be coated, thus resulting in a high Li-ion conductivity of the membrane. Assembled with this decorated separator in button cells, both high-voltage (Li1.2Mn0.54Co0.13Ni0.13O2) and moderate-voltage (LiFePO4) cathode materials show better electrochemical performances than those assembled with pristine polyolefin separators.
Keywords: polyolefin membranes; nonradiation; separator; high lithium-ion conductivity; lithium-ion battery

Harnessing phytomicrobiome signaling for rhizosphere microbiome engineering - Quiza, L.; St-Arnaud, M.; Yergeau, E. (Frontiers in Plant Science, 2015)
The goal of microbiome engineering is to manipulate the microbiome toward a certain type of community that will optimize plant functions of interest. For instance, in crop production the goal is to reduce disease susceptibility, increase nutrient availability increase abiotic stress tolerance and increase crop yields. Various approaches can be devised to engineer the plant–microbiome, but one particularly promising approach is to take advantage of naturally evolved plant–microbiome communication channels. This is, however, very challenging as the understanding of the plant–microbiome communication is still mostly rudimentary and plant–microbiome interactions varies between crops species (and even cultivars), between individual members of the microbiome and with environmental conditions. In each individual case, many aspects of the plant–microorganisms relationship should be thoroughly scrutinized. In this article we summarize some of the existing plant–microbiome engineering studies and point out potential avenues for further research.
Keywords: rhizosphere; signaling; beneficial microorganisms; agriculture; plant–microbe interactions

Carbon gel assisted low temperature liquid-phase synthesis of C-LiFePO4/graphene layers with high rate and cycle performances - Tang, Hongwei; Si, Yanli; Chang, Kun; Fu, Xiaoning; Li, Bao; Shangguan, Enbo; Chang, Zhaorong; Yuan, Xiao-Zi; Wang, Haijiang (Journal of Power Sources, 2015)
Nano-scale LiFePO4/graphene oxide (GO) as cathode materials for lithium ion batteries has been successfully synthesized via a one-step carbon gel assisted liquid-phase approach at a low-temperature (108 °C) and normal pressure. C-LiFePO4/graphene layers (G) composites, composed of LiFePO4, amorphous carbon and graphene layers, are then produced after rapid high temperature carbon treatment. Interface tunnel effect, produced by the intimate contact of LiFePO4 particles with amorphous carbon and graphene layers, greatly improves the properties of the composites. Electrochemical tests indicate that the optimal amount of GO addition is 1 wt.% in terms of achieving a high electrochemical performance of the C-LiFePO4/G composites. Discharge capacity of the C-LiFePO4/G composites is 160.0 mAh g-1 at 0.2 C. When the current rate is further increased to 60 C, the discharge capacity of C-LiFePO4/G can reach 68 mAh g-1. At a high current rate of 20 C, the capacity attenuation rate of the C-LiFePO4/G electrode is only 9.6% after 200 cycles, showing excellent high-rate discharge capability and cycle performance. This is achieved under a facile synthesis condition of a simple procedure, low temperature, and normal pressure.
Keywords: Amorphous carbon; Cathodes; Electric discharges; Electrodes; Graphene; Liquids; Lithium; Lithium compounds; Lithium-ion batteries; Low temperature effects; Nanotechnology; Temperature; Discharge capacities; Electrochemical performance; Electrochemical test; Graphene oxides; Liquid-phase method; Liquid-phase synthesis; Lithium iron phosphates; Low temperature synthesis; Lithium alloys

Facile synthesis of high tap density ZnO microspheres as advanced anode material for alkaline nickel-zinc rechargeable batteries - Zhao, T.; Shangguan, E.; Li, Y.; Li, J.; Chang, Z.; Li, Q.; Yuan, X.-Z.; Wang, H. (Electrochimica Acta, 2015)
Anode active materials, high tap-density ZnO microspheres, with enhanced volumetric capacity and improved cycling performance for nickel-zinc rechargeable batteries have been synthesized via a novel complexing co-precipitation method. The physical and electrochemical properties of the obtained ZnO microsphere are investigated. Notably, tap-density of the resultant ZnO microspheres can reach 3.00 g cm-3, three times higher than the commercial conventional ZnO. Compared with the conventional ZnO, the obtained ZnO microspheres have demonstrated superior electrochemical properties, including higher volume specific capacity, improved high-rate ability, and better cyclic stability. At rates of 0.2C and 2C, the obtained ZnO microspheres deliver volumetric capacities of ∼1450 and ∼1110 mAh cm-3, respectively, which are about three times higher than those of the conventional ZnO. These performance improvements are attributed to its unique more dense spherical microstructure, thus leading to better reaction reversibility, excellent anti-corrosion ability, lower charge transfer resistance and better inhibiting effect on shape change of the material. Owing to its facile synthesis and outstanding electrochemical properties, this high-density spherical ZnO sample is a promising anode material for fabricating high performance Ni-Zn secondary batteries.
Keywords: Zinc oxide microspheres; Anode material; High-density; Electrochemical properties; Nickel-zinc rechargeable batteries

HDS of dibenzothiophenes and hydrogenation of tetralin over a SiO2 supported Ni-Mo-S catalyst - Wei, Q.; Chen, J.; Song, C.; Li, G. (Frontiers of Chemical Science and Engineering, 2015)
A one-step synthesized Ni-Mo-S catalyst supported on SiO2 was prepared and used for hydrodesulphurization (HDS) of dibenzothiophene (DBT), and 4,6-dimethyl-dibenzothiophene (4,6-DMDBT), and for hydrogenation of tetralin. The catalyst showed relatively high HDS activity with complete conversion of DBT and 4,6-DMDBT at temperature of 280 °C and a constant pressure of 435 psi. The HDS conversions of DBTand 4,6-DMDBT increased with increasing temperature and pressure, and decreasing liquid hourly space velocity (LHSV). The HDS of DBT proceeded mostly through the direct desulphurization (DDS) pathway whereas that of 4,6-DMDBT occurred mainly through the hydrogenationdesulphurization (HYD) pathway. Although the catalyst showed up to 24% hydrogenation/dehydrogenation conversion of tetralin, it had low conversion and selectivity for ring opening and contraction due to the competitive adsorption of DBTand 4,6-DMDBT and insufficient acidic sites on the catalyst surface.[Figure not available: see fulltext.]
Keywords: hydrodesulphurization (HDS); hydrogenation; dibenzothiophene (DBT); 4,6-dimethyldibenzothiophene (4,6-DMDBT); tetralin

A Gemini/GMOS study of intermediate luminosity early-type Virgo cluster galaxies. I. Globular cluster and stellar kinematics - Li, Biao; Peng, Eric W.; Zhang, Hong-xin; Blakeslee, John P.; Côté, Patrick J D (Pat); Ferrarese, Laura; Jordán, Andrés; Liu, Chengze; Mei, Simona; Puzia, Thomas H.; Takamiya, Marianne; Trancho, Gelys; et al. (The Astrophysical Journal, 2015)
We present a kinematic analysis of the globular cluster (GC) systems and diffuse stellar light of four intermediate luminosity (sub-L*) early-type galaxies in the Virgo cluster based on Gemini Multi-Object Spectrographs (GMOS) data. Our galaxy sample is fainter (-23.8<Mk<-22.7) than most previous studies, nearly doubling the number of galaxies in this magnitude range that now have GC kinematics. The data for the diffuse light extends to 4Re, and the data for the GCs reaches 8–12Re. We find that the kinematics in these outer regions are all different despite the fact that these four galaxies have similar photometric properties, and are uniformly classified as "fast rotators" from their stellar kinematics within 1Re. The GC systems exhibit a wide range of kinematic morphology. The rotation axis and amplitude can change between the inner and outer regions, including a case of counter-rotation. This difference shows the importance of wide-field kinematic studies, and shows that stellar and GC kinematics can change significantly as one moves beyond the inner regions of galaxies. Moreover, the kinematics of the GC systems can differ from that of the stars, suggesting that the formation of the two populations are also distinct.
Keywords: galaxies; elliptical and lenticular; cD; kinematics and dynamics; star clusters

Drying of calcium-silicatehydrates: regeneration of elastic modulus - Pourbeik, P.; Beaudoin, J.J.; Alizadeh, R.; Raki, L. (Advances in Cement Research, 2015)
Dynamic mechanical thermal analysis (DMTA) measurements for layered calcium silicate systems (1.4 nm tobermorite, jennite, synthetic calcium-silicate-hydrate and hydrated Portland cement paste) are reported. Elastic modulus results were obtained for samples initially conditioned to 11% relative humidity (RH) and dried during the DMTA test and for samples subjected to prolonged vacuum and thermal drying prior to a DMTA test. Decreases in elastic modulus relative to the 11% RH starting condition typically observed during a DMTA test were recovered subsequent to the prolonged thermal treatment. A possible 'regeneration' mechanism for the elastic modulus is discussed. The 'regeneration' occurs for all the calcium silicate systems studied. The results are consistent with the notions expressed for nanostructural models of calcium-silicate-hydrate in cement paste that comprise structural units based on 1.4 nm tobermorite and jennite.
Keywords: Calcium; Cements; Dynamic mechanical analysis; Elastic moduli; Hydration; Portland cement; Silicate minerals; Silicates; Thermoanalysis; Calcium silicate hydrate; Cement paste; D. dynamic mechanical thermal analyses (DMTA); Nanostructural; Portland cement paste; Structural unit; Synthetic calcium silicate hydrates; Thermal drying; Calcium silicate

Genetic analysis of seedling resistance to crown rust in five diploid oat (Avena strigosa) accessions - Cabral, A.L.; Park, R.F. (Journal of Applied Genetics, 2015)
Crown rust, caused by Puccinia coronata Corda f. sp. avenae Eriks., is a serious menace in oats, for which resistance is an effective means of control. Wild diploid oat accessions are a source of novel resistances that first need to be characterised prior to introgression into locally adapted oat cultivars. A genetic analysis of resistance to crown rust was carried out in three diverse diploid oat accessions (CIav6956, CIav9020, PI292226) and two cultivars (Saia and Glabrota) of A. strigosa. A single major gene conditioning resistance to Australian crown rust pathotype (Pt) 0000–2 was identified in each of the three accessions. Allelism tests suggested that these genes are either the same, allelic, or tightly linked with less than 1 % recombination. Similarly, a single gene was identified in Glabrota, and possibly two genes in Saia; both cultivars previously reported to carry two and three crown rust resistance genes, respectively. The identified seedling resistance genes could be deployed in combination with other resistance gene(s) to enhance durability of resistance to crown rust in hexaploid oat. Current diploid and hexaploid linkage maps and molecular anchor markers (simple sequence repeat [SSR] and diversity array technology [DArT] markers) should facilitate their mapping and introgression into hexaploid oat.
Keywords: Allelism; Genetic analyses; Puccinia coronata; Seedling resistance

Peer2peer and open pedagogy of MOOCS to support the knowledge commons - Kop, Rita; Fournier, Hélène (MOOCs and Open Education Around the World, 2015)

Investigations into the binding of jadomycin DS to human topoisomerase IIβ by WaterLOGSY NMR spectroscopy - Martinez-Farina, Camilo F.; McCormick, Nicole; Robertson, Andrew W.; Clement, Helen; Jee, Alison; Ampaw, Anna; Chan, Nei-Li; Syvitski, Ray T.; Jakeman, David L. (Organic and Biomolecular Chemistry, 2015)
The jadomycins are a family of secondary metabolites produced by S. venezuelae ISP5230. Specific jadomycins have been shown to possess a variety of anticancer, antifungal, and antibacterial properties, with different molecular mechanisms of action. Herein we demonstrate qualitative and quantitative direct binding between the validated anticancer target human topoisomerase IIβ and jadomycin DS using WaterLOGSY NMR spectroscopy. Additionally, we report for the first time, that jadomycin DS also binds a variety of other proteins, likely in a non-specific manner. Such interactions may rationalize the potential polypharmacology of jadomycin DS.
Keywords: Metabolites; Nuclear magnetic resonance spectroscopy; Anti-fungal; Antibacterial properties; Anticancer targets; Direct bindings; Human topoisomerase; Molecular mechanism; Secondary metabolites; Bins

Comparison between EGSnrc, Geant4, MCNP5 and Penelope for mono-energetic electron beams - Archambault, John Paul; Mainegra-Hing, Ernesto (Physics in Medicine and Biology, 2015)
A simple geometry is chosen to highlight similarities and differences of current electron transport algorithms implemented in four Monte Carlo codes commonly used in radiation physics. Energy deposited in a water-filled sphere by mono-energetic electron beams was calculated using EGSnrc, Geant4, MCNP5 and Penelope as the radius of the sphere varied from 0.25 cm to 4.5 cm for beam energies of 0.5 MeV, 1.0 MeV and 5.0 MeV. The calculations were performed in single-scattering mode (where applicable) and in condensed history mode. A good agreement is found for the single-scattering calculations except for the in-air case at 0.5 MeV where differences increase with decreasing radius up to 5% between EGSnrc and Penelope. Differences between results calculated with the default user settings when compared to their own single-scattering modes are under 5% for all codes when the sphere is surrounded by vacuum, however, large differences occur for Geant4, MCNP5 and Penelope when air is introduced around the sphere. Finally, the parameters associated with the multiple scattering algorithms were tuned reducing these differences below 10% for these codes at the expense of increased computation time.
Keywords: Algorithms; Codes (symbols); Electron beams; Electron scattering; Electron transport properties; Monte Carlo methods; Spheres; Computation time; Electron transport; Energetic electron; Monte Carlo codes; Radiation physics; Radiation transport; Simple geometries; Single scattering; Electrons

Special issue on Spectroscopy with synchrotron radiation - Perrin, A.; McKellar, A. R. W. (Journal of Molecular Spectroscopy, 2015)

Improved performance of a passive air breathing flat-plate microbial fuel cell - Kazemi, S.; Fatih, K.; Mohseni, M. (Canadian Journal of Chemical Engineering, 2015)
This study aims to investigate the effect of the graphite felt (GF) substrate surface treatment, the GF active surface area, and the anode chamber depth on the performance of the passive air breathing flat-plate microbial fuel cell (FPMFC) configuration. Three passive air breathing FPMFCs (depth of anode chamber: 2mm, 4mm, and 8mm) were developed and operated using 1, 2, and 3 packed layers of three-dimensional (3D) graphite felt anodes, respectively, with similar cross sectional (geometric) surface area as the cathode and the membrane. The surface of the GF substrate was treated by soaking in a hot solution of nitric acid prior to inoculation. The 2mm FPMFC generated a peak power density superior to that previously reported for the same configuration with no GF treatment. The peak power density in the 8mm and 4mm FPMFCs with 3 and 2 layers of GF increased by 118 % and 48 %, respectively, compared to the 2mm FPMFC with 1 layer of GF. By using only 1 layer of GF, the peak power density showed no significant variation with the electrode spacing.
Keywords: passive air breathing; flat-plate microbial fuel cell; electrode spacing

Armand-frappier outstanding student award — The emerging role of 25-hydroxycholesterol in innate immunity - Singaravelu, R.; Srinivasan, P.; Pezacki, J.P. (Canadian Journal of Microbiology, 2015)
The metabolic interplay between hosts and viruses plays a crucial role in determining the outcome of viral infection. Viruses reorchestrate the host’s primary metabolic gene networks, including genes associated with mevalonate and isoprenoid synthesis, to acquire the necessary energy and structural components for their viral life cycles. Recent work has demonstrated that the interferon-mediated antiviral response suppresses the sterol pathway through production of a signalling molecule, 25-hydroxycholesterol (25HC). This oxysterol has been shown to exert multiple effects, both through incorporation into host cellular membranes as well as through transcriptional control. Herein, we summarize our current understanding of the multifunctional roles of 25HC in the mammalian innate antiviral response.
Keywords: 25 hydroxycholesterol; cholesterol-25-hydroxylase; metabolism; virus; immunity

Characterization of the lipopolysaccharide produced by Pasteurella multocida serovars 6, 7 and 16: identification of lipopolysaccharide genotypes L4 and L8 - Harper, M.; St Michael, F.; Steen, J.A.; John, M.; Wright, A.; van Dorsten, L.; Vinogradov, E.; Adler, B.; Cox, A.D.; Boyce, J.D. (Glycobiology, 2015)
Pasteurella multocida is an important veterinary pathogen that produces a wide range of lipopolysaccharide (LPS) structures, many of which mimic host glycoproteins. In this study, we complete our analysis of the LPS produced by the P. multocida Heddleston serovars by reporting the LPS structure and the LPS outer core biosynthesis loci of the type strains representing Heddleston serovars 6, 7 and 16. Genetic analysis revealed that the type strains representing serovars 6 and 7 share the same LPS outer core biosynthesis locus which we have designated LPS genotype L4. Comparative bioinformatic analysis revealed that although the serovar 16 type strain contained a different LPS locus, L8, there was a significant degree of nucleotide identity between the L4 and L8 loci. Structural analysis revealed that the LPS glycoforms produced by the L4 and L8 strains all contained the highly conserved inner core produced by all other P. multocida strains examined to date. The residues within the LPS outer core produced by the L4 and L8 strains were either Gal or derivatives of Gal; unlike all other P. multocida Heddleston type strains examined there are no heptosyltransferases encoded in the L4 and L8 outer core biosynthesis loci. The structure of the L4 LPS outer core produced by the serovar 6 type strain consisted of β-Gal-(1-3)-β-N-acetylgalactosamine (GalNAc)-(1-4)-β-GalNAc3OAc-(1-4)-α-GalNAc3OAc-(1-3)-β-Gal, whereas the serovar 7 type strain produced a highly truncated LPS outer core containing only a single β-Gal residue. The structure of the L8 LPS outer core produced by the serovar 16 type strain consisted of β-Gal-(1-3)-β-GalNAc-(1-4)-(α-GalNAc-(1-3)-)-α-GalNAc.
Keywords: core oligosaccharide; genetics; LPS; Pasteurella multocida; structure

Comprehensive synthesis of monohydroxy-cucurbit[n]urils (n = 5, 6, 7, 8): High purity and high conversions - Ayhan, Mehmet M.; Karoui, Hakim; Hardy, Micael; Rockenbauer, Antal; Charles, Laurence; Rosas, Roselyne; Udachin, Konstantin; Tordo, Paul; Bardelang, David; Ouari, Olivier (Journal of the American Chemical Society, 2015)
We describe a photochemical method to introduce a single alcohol function directly on cucurbit[n]urils (n = 5, 6, 7, 8) with conversions of the order 95-100% using hydrogen peroxide and UV light. The reaction was easily scaled up to 1 g for CB[6] and CB[7]. Spin trapping of cucurbituril radicals combined with MS experiments allowed us to get insights about the reaction mechanism and characterize CB[5], CB[6], CB[7], and CB[8] monofunctional compounds. Experiments involving 18O isotopically labeled water indicated that the mechanism was complex and showed signs of both radical and ionic intermediates. DFT calculations allowed estimating the Bond Dissociation Energies (BDEs) of each hydrogen atom type in the CB series, providing an explanation of the higher reactivity of the "equatorial" C-H position of CB[n] compounds. These results also showed that, for CB[8], direct functionalization on the cucurbituril skeleton is more difficult because one of the methylene hydrogen atoms (Hb) has its BDE lowering within the series and coming close to that of Hc, thus opening the way to other types of free radicals generated on the CB[8] skeleton leading to several side products. Yet CB[5]-(OH)1 and CB[8]-(OH)1, the first CB[8] derivative, were obtained in excellent yields thanks to the soft method presented here.
Keywords: Atoms; Free radicals; Bond dissociation energies; Functionalizations; High conversions; Ionic intermediates; Isotopically labeled; Monofunctional compounds; Photochemical method; Reaction mechanism; Musculoskeletal system

Wave spectral finite element model for the prediction of sound transmission loss and damping of sandwich panels - Mejdi, A.; Atalla, N.; Ghinet, S. (Computers and Structures, 2015)
Sandwich panels are usually modeled by considering only asymmetric motion which assumes the core deforms by transversal shearing without any compressive deformation over the thickness. This assumption is acceptable for panels with relatively stiff and thin cores. However, symmetric motion becomes important when the core is thick or soft. Under such conditions, the compressive deformation over the core thickness becomes significant. This paper addresses the prediction of the Sound Transmission Loss (STL) and composite Damping Loss Factor (DLF) of sandwich panels with either thin or thick cores as well as stiff or soft (viscoelastic) cores. Both the skin and the core are assumed to be orthotropic. A spectral finite element based approach is developed wherein the stress and strain components in each layer are described using the properties in that layer for a forced trace wave number and heading direction. The proposed approach provides a reliable and numerically efficient tool to account for the compressive deformation effect of thick orthotropic sandwich layers. Moreover, the proposed model is also able to consider panels with multiple of layers with varying properties.
Keywords: Sandwich structures; Numerical modeling; Viscoelastic materials

Biexciton binding of Dirac fermions confined in colloidal graphene quantum dots - Sun, Cheng; Figge, Florian; Ozfidan, Isil; Korkusinski, Marek; Yan, Xin; Li, Liang-shi; Hawrylak, Pawel; McGuire, John A. (Nano Letters, 2015)
We present transient absorption measurements and microscopic theory of biexciton binding in triangular colloidal graphene quantum dots consisting of 168 sp2-hybridized C atoms. We observe optical transitions from the lowest orbitally dark singlet exciton states to states below the energy of an unbound dark+bright singlet-exciton pair. Through microscopic calculations of the low-energy exciton and biexciton states via tight-binding, Hartree-Fock, and configuration interaction methods, the spectra reveal a biexciton consisting primarily of a dark-bright singlet-pair bound by ∼0.14 eV.
Keywords: Binding energy; Excitons; Graphene; Molecular physics; Nanocrystals; Quantum chemistry; Biexcitons; Configuration interactions; Dirac fermions; Hartree-fock; Transient absorption; Semiconductor quantum dots

Salix purpurea stimulates the expression of specific bacterial xenobiotic degradation genes in a soil contaminated with hydrocarbons - Pagé, Antoine P.; Yergeau, Étienne; Greer, Charles W. (PLoS ONE, 2015)
The objectives of this study were to uncover Salix purpurea-microbe xenobiotic degradation systems that could be harnessed in rhizoremediation, and to identify microorganisms that are likely involved in these partnerships. To do so, we tested S. purpurea's ability to stimulate the expression of 10 marker microbial oxygenase genes in a soil contaminated with hydrocarbons. In what appeared to be a detoxification rhizosphere effect, transcripts encoding for alkane 1-monooxygenases, cytochrome P450 monooxygenases, laccase/ polyphenol oxidases, and biphenyl 2,3-dioxygenase small subunits were significantly more abundant in the vicinity of the plant's roots than in bulk soil. This gene expression induction is consistent with willows' known rhizoremediation capabilities, and suggests the existence of S. purpurea-microbe systems that target many organic contaminants of interest (i.e. C4- C16 alkanes, fluoranthene, anthracene, benzo(a)pyrene, biphenyl, polychlorinated biphenyls). An enhanced expression of the 4 genes was also observed within the bacterial orders Actinomycetales, Rhodospirillales, Burkholderiales, Alteromonadales, Solirubrobacterales, Caulobacterales, and Rhizobiales, which suggest that members of these taxa are active participants in the exposed partnerships. Although the expression of the other 6 marker genes did not appear to be stimulated by the plant at the community level, signs of additional systems that rest on their expression by members of the orders Solirubrobacterales, Sphingomonadales, Actinomycetales, and Sphingobacteriales were observed. Our study presents the first transcriptomics-based identification of microbes whose xenobiotic degradation activity in soil appears stimulated by a plant. It paints a portrait that contrasts with the current views on these consortia's composition, and opens the door for the development of laboratory test models geared towards the identification of root exudate characteristics that limit the efficiency of current willow-based rhizoremediation applications.
Keywords: alkane 1 monooxygenase; catechol oxidase; cytochrome P450; hydrocarbon; Actinomycetales; alkB gene; Alteromonadales; bacterial gene; bacterial xenobiotic degradation; bacterium; bacterium identification; benA gene; bioremediation; bphA1 gene; bphA2 gene; Burkholderiales; Caulobacterales; controlled study; dbfA1 gene; gene expression; genetic variability; microbial degradation; mmoX gene; npah gene; nucleotide sequence; p450 gene; ppah gene; ppo gene; Rhizobiales; rhizoremediation; rhizosphere; Rhodospirillales; Salix purpurea; sequence homology; soil pollution; Solirubrobacterales; Sphingobacteriales; Sphingomonadales; willow; Xanthomonadales

Self-assembly formation of hollow Ni-Fe-O nanocage architectures by metal-organic frameworks with high-performance lithium storage - Guo, Hong; Li, Tingting; Chen, Weiwei; Liu, Lixiang; Qiao, Jinli; Zhang, Jiujun (Scientific Reports, 2015)
A hollow hybrid Ni-Fe-O nanomaterial (NiFe2O4) is synthesized using a precursor of metal-organic frameworks through a simple and cost-effective method. The unique hollow nanocage structures shorten the length of Li-ion diffusion. The hollow structure offers a sufficient void space, which sufficiently alleviates the mechanical stress caused by volume change. Besides, the hybrid elements allow the volume change to take place in a stepwise manner during electrochemical cycle. And thus, the hierarchical hollow NiFe2O4 nanocage electrode exhibits extraordinary electrochemical performance. The stable cyclic performance is obtained for all rates from 1 C to 10 C. Even when the current reaches 10 C, the capacity can also arrive at 652 mAhg-1. Subsequently, a specific capacity of ca. 975 mAhg-1 is recovered when the current rate reduces back to 1 C after 200 cycles. This strategy that derived from NMOFs may shed light on a new route for large-scale synthesis of hollow porous hybrid nanocages for energy storage, environmental remediation and other novel applications.

Surface enhanced raman spectroscopy detection of biomolecules using EBL fabricated nanostructured substrates - Peters, Robert F.; Gutierrez-Rivera, Luis; Dew, Steven K.; Stepanova, Maria (Journal of Visualized Experiments, 2015)
Fabrication and characterization of conjugate nano-biological systems interfacing metallic nanostructures on solid supports with immobilized biomolecules is reported. The entire sequence of relevant experimental steps is described, involving the fabrication of nanostructured substrates using electron beam lithography, immobilization of biomolecules on the substrates, and their characterization utilizing surface-enhanced Raman spectroscopy (SERS). Three different designs of nano-biological systems are employed, including protein A, glucose binding protein, and a dopamine binding DNA aptamer. In the latter two cases, the binding of respective ligands, D-glucose and dopamine, is also included. The three kinds of biomolecules are immobilized on nanostructured substrates by different methods, and the results of SERS imaging are reported. The capabilities of SERS to detect vibrational modes from surface-immobilized proteins, as well as to capture the protein-ligand and aptamer-ligand binding are demonstrated. The results also illustrate the influence of the surface nanostructure geometry, biomolecules immobilization strategy, Raman activity of the molecules and presence or absence of the ligand binding on the SERS spectra acquired.

Bacterial sugar 3,4-ketoisomerases: structural insight into product stereochemistry - Thoden, J.B.; Vinogradov, E.; Gilbert, M.; Salinger, A.J.; Holden, H.M. (Biochemistry, 2015)
3-Acetamido-3,6-dideoxy-d-galactose (Fuc3NAc) and 3-acetamido-3,6-dideoxy-d-glucose (Qui3NAc) are unusual sugars found on the lipopolysaccharides of Gram-negative bacteria and on the S-layers of Gram-positive bacteria. The 3,4-ketoisomerases, referred to as FdtA and QdtA, catalyze the third steps in the respective biosynthetic pathways for these sugars. Whereas both enzymes utilize the same substrate, the stereochemistries of their products are different. Specifically, the hydroxyl groups at the hexose C-4′ positions assume the "galactose" and "glucose" configurations in the FdtA and QdtA products, respectively. In 2007 we reported the structure of the apoform of FdtA from Aneurinibacillus thermoaerophilus, which was followed in 2014 by the X-ray analysis of QdtA from Thermoanaerobacterium thermosaccharolyticum as a binary complex. Both of these enzymes belong to the cupin superfamily. Here we report a combined structural and enzymological study to explore the manner in which these enzymes control the stereochemistry of their products. Various site-directed mutant proteins of each enzyme were constructed, and their dTDP-sugar products were analyzed by NMR spectroscopy. In addition, the kinetic parameters for these protein variants were measured, and the structure of one, namely, the QdtA Y17R/R97H double mutant form, was determined to 2.3-Å resolution. Finally, in an attempt to obtain a model of FdtA with a bound dTDP-linked sugar, the 3,4-ketoisomerase domain of a bifunctional enzyme from Shewanella denitrificans was cloned, purified, and crystallized in the presence of a dTDP-linked sugar analogue. Taken together, the results from this investigation demonstrate that it is possible to convert a "galacto" enzyme into a "gluco" enzyme and vice versa.
Keywords: Bacteria; Cloning; Nuclear magnetic resonance spectroscopy; Proteins; Stereochemistry; Stereoselectivity; Sugars; X ray analysis; Bifunctional enzymes; Binary complexes; Biosynthetic pathway; Gram-negative bacteria; Gram-positive bacterium; Lipopolysaccharides; Structural insights; Thermoanaerobacterium; Enzymes; 3 acetamido 3,6 dideoxy dextro galactose; glucose; 3,4 ketoisomerase; bacterial enzyme; bacterium lipopolysaccharide; carbohydrate; galactose; glucose; hexose; hydroxyl group; isomerase; mutant protein; protein FdtA; QdtA; protein variant

Chemometric optimization of an extraction procedure using tartaric acid for butyltin compounds from sediment samples by GC-PFPD - Bravo, Manuel A.; Flores, Marcos; Parra, Sonnia; Quiroz, Waldo; Maxwell, Paulette; Mester, Zoltan (Journal of the Chilean Chemical Society, 2015)
In this study a simple extraction procedure was developed to minimize the sulfur interferences on the determination of butyltin in sediment samples based on extraction with tartaric acid solution. The optimal conditions were determined using an experimental design methodology and these were achieved using a solution of tartaric acid (0.5 M) with methanol (30% v/v) for 12 hours in an orbital shaker. This protocol could be followed by a liquid-liquid extraction and this organic phase can be analyzed directly by gas chromatography with pulsed flame photometric detection (GC-PFPD) without any further cleanup due to interferences from elemental sulfur were completely eliminated. The accuracy of the procedure was verified analyzing two reference materials (CRM) (BCR-646, freshwater sediment and PACS-2, marine sediment) and comparing the results to the certified values, the optimized method produced satisfactory results certified values in the CRMs. Finally, harbour sediment samples were analyzed in order to evaluate the suitability of the method for organotin control in complex environmental samples containing high concentrations of sulfur compounds.

Characterization of L-Digitoxosyl-phenanthroviridin from Streptomyces venezuelae ISP5230 - Robertson, Andrew W.; Martinez-Farina, Camilo F.; Syvitski, Raymond T.; Jakeman, David L. (Journal of Natural Products, 2015)
The jadomycin-derived compound l-digitoxosyl-phenanthroviridin was isolated from fermentations of Streptomyces venezuelae ISP5230 grown in nutrient-deficient media with l-lysine as the sole nitrogen source. Structural elucidation was accomplished using a combination of high-resolution MS, LC-MS/MS, and 1D- and 2D-NMR. The compound was evaluated against the National Cancer Institute (NCI) 60 human tumor cell line screen in both the one-dose and five-dose screens, and cytotoxicity was compared to a small library of jadomycin analogues to probe the structure-activity relationship.
Keywords: aglycone; daunorubicin; digitoxosyl phenanthroviridin; gyrase inhibitor; lysine; unclassified drug; absorption spectroscopy; amino acid metabolism; cancer cell culture; cytotoxicity; fermentation; heteronuclear multiple bond correlation; heteronuclear single quantum coherence; high performance liquid chromatography; human cell; liquid chromatography; mass spectrometry; nuclear Overhauser effect; protein structure; proton nuclear magnetic resonance; Streptomyces venezuelae; tandem mass spectrometry

Sensitivity of high-order-harmonic generation to aromaticity - Alharbi, A. F.; Boguslavskiy, A. E.; Thiré, N.; Schmidt, B. E.; Légaré, F.; Brabec, T.; Spanner, M.; Bhardwaj, V. R. (Physical Review A: Atomic, Molecular, and Optical Physics, 2015)
The influence of cyclic electron delocalization associated with aromaticity on the high-order-harmonic generation (HHG) process is investigated in organic molecules. We show that the aromatic molecules benzene (C6H6) and furan (C4H4O) produce high-order harmonics more efficiently than nonaromatic systems having the same ring structure. We also demonstrate that the relative strength of plateau harmonics is sensitive to the aromaticity in five-membered-ring molecules using furan, pyrrole (C4H4NH), and thiophene (C4H4S). Numerical time-dependent Schrödinger equation simulations of total orientation-averaged strong-field ionization yields show that the HHG from aromatic molecules comes predominantly from the two highest π molecular orbitals, which contribute to the aromatic character of the systems.
Keywords: Aromatic compounds; Aromatization; Harmonic analysis; Molecular orbitals; Molecular orientation; Organic pollutants; Thiophene; Aromatic molecules; Electron delocalization; Five-membered rings; High order harmonic generation; High order harmonics; Organic molecules; Relative strength; Strong field ionization; Harmonic generation

Laser-induced incandescence: Particulate diagnostics for combustion, atmospheric, and industrial applications - Michelsen, H. A.; Schulz, C.; Smallwood, G. J.; Will, S. (Progress in Energy and Combustion Science, 2015)
The understanding of soot formation in combustion processes and the optimization of practical combustion systems require in situ measurement techniques that can provide important characteristics, such as particle concentrations and sizes, under a variety of conditions. Of equal importance are techniques suitable for characterizing soot particles produced from incomplete combustion and emitted into the environment. Additionally, the production of engineered nanoparticles, such as carbon blacks, may benefit from techniques that allow for online monitoring of these processes.In this paper, we review the fundamentals and applications of laser-induced incandescence (LII) for particulate diagnostics in a variety of fields. The review takes into account two variants of LII, one that is based on pulsed-laser excitation and has been mainly used in combustion diagnostics and emissions measurements, and an alternate approach that relies on continuous-wave lasers and has become increasingly popular for measuring black carbon in environmental applications. We also review the state of the art in the determination of physical parameters central to the processes that contribute to the non-equilibrium nanoscale heat and mass balances of laser-heated particles; these parameters are important for LII-signal analysis and simulation. Awareness of the significance of particle aggregation and coatings has increased recently, and the effects of these characteristics on the LII technique are discussed.Because of the range of experimental constraints in the variety of applications for which laser-induced incandescence is suited, many implementation approaches have been developed. This review discusses considerations for selection of laser and detection characteristics to address application-specific needs. The benefits of using LII for measurements of a range of nanoparticles in the fields mentioned above are demonstrated with some typical examples, covering simple flames, internal-combustion engines, exhaust emissions, the ambient atmosphere, and nanoparticle production. We also remark on less well-known studies employing LII for particles suspended in liquids.An important aspect of the paper is to critically assess the improvement in the understanding of the fundamental physical mechanisms at the nanoscale and the determination of underlying parameters; we also identify further research needs in these contexts. Building on this enhanced capability in describing the underlying complex processes, LII has become a workhorse of particulate measurement in a variety of fields, and its utility continues to be expanding. When coupled with complementary methods, such as light scattering, probe-sampling, molecular-beam techniques, and other nanoparticle instrumentation, new directions for research and applications with LII continue to materialize.
Keywords: Agglomeration; Combustion; Continuous wave lasers; Heat transfer; Internal combustion engines; Laser diagnostics; Laser excitation; Light scattering; Molecular beams; Nanoparticles; Nanotechnology; Pulsed lasers; Soot; Black carbon; Detection characteristics; Engineered nanoparticles; Environmental applications; Laser induced incandescence; Nano-particle production; Nanoscale heat transfers; In situ combustion

Corrigendum to "Measurement and computations for temperature dependences of self-broadened carbon dioxide transitions in the 30012-00001 and 30013-00001 bands" [J. Quant. Spectrosc. Radiat. Transf., 111 (9) (2010) 1065-1079] doi: 10.1016/j.jqsrt.2010.01.003 - Predoi-Cross, Adriana; Liu, W.; Murphy, Reba; Povey, Chad; Gamache, R.; Laraia, A.; McKellar, A. R. W.; Hurtmans, Daniel; Devi, V. M. (Elsevier, 2015)

Harmonization of the quantitative determination of volatile fatty acids profile in aqueous matrix samples by direct injection using gas chromatography and high-performance liquid chromatography techniques: Multi-laboratory validation study - Raposo, Francisco; Borja, Rafael; Cacho, Jesús A.; Mumme, Jan; Mohedano, Ángel F.; Battimelli, Audrey; Bolzonella, David; Schuit, Anthony D.; Noguerol-Arias, Joan; Frigon, Jean-Claude; Peñuela, Gustavo A.; Muehlenberg, Jana; et al. (Journal of Chromatography A, 2015)
The performance parameters of volatile fatty acids (VFAs) measurements were assessed for the first time by a multi-laboratory validation study among 13 laboratories. Two chromatographic techniques (GC and HPLC) and two quantification methods such as external and internal standard (ESTD/ISTD) were combined in three different methodologies GC/ESTD, HPLC/ESTD and GC/ISTD. Linearity evaluation of the calibration functions in a wide concentration range (10-1000mg/L) was carried out using different statistical parameters for the goodness of fit. Both chromatographic techniques were considered similarly accurate. The use of GC/ISTD, despite showing similar analytical performance to the other methodologies, can be considered useful for the harmonization of VFAs analytical methodology taking into account the normalization of slope values used for the calculation of VFAs concentrations. Acceptance criteria for VFAs performance parameters of the multi-laboratory validation study should be established as follows: (1) instrument precision (RSDINST≤1.5%); (2) linearity (R2≥0.998; RSDSENSITIVITY≤4%; REMAX≤8%; REAVER≤ 3%); (3) precision (RSD≤1.5%); (4) trueness (recovery of 97-103%); (5) LOD (≤3mg/L); and (6) LOQ (10mg/L).
Keywords: Chromatography; Direct injection; Fatty acids; Parameter estimation; Aqueous matrices; Chromatographic techniques; Interlaboratory studies; Performance parameters; Quantification methods; Quantitative determinations; Volatile fatty acids (VFAs); Volatile fatty acids; volatile fatty acid; aqueous solution; concentration (parameters); controlled study; fatty acid analysis; gas chromatography; high performance liquid chromatography; limit of detection; limit of quantitation; priority journal; quantitative analysis; validation study

High-efficiency fully etched fiber-chip grating couplers with subwavelength structures for datacom and telecom applications - Benedikovic, Daniel; Cheben, Pavel; Schmid, Jens H.; Xu, Dan-Xia; Lapointe, Jean; Wang, Shurui; Janz, Siegfried; Halir, Robert; Ortega-Moñux, Alejandro; Dado, Milan (Proceedings of SPIE: The International Society for Optical Engineering, 2015)
Surface grating couplers are key components to couple light between planar waveguide circuits in silicon-on-insulator (SOI) platform and optical fibers. Here, we demonstrate by using simulations and experiments that a high coupling efficiency can be achieved for an arbitrary buried oxide thickness by judicious adjustment of the grating radiation angle. The coupler strength is engineered by subwavelength structures, which have pitch and feature sizes smaller than the wavelength of light propagating through it, thereby frustrating diffraction effects and behaving as a homogeneous media with an adjustable equivalent refractive index. This makes it possible to apodize the grating coupler with a preferred single etch fabrication process. The coupling efficiency of the grating coupler is optimized for operating with the transverse electric (TE) polarization state at the wavelengths near 1.3 μm and 1.55 μm, which are the bands relevant for datacom and telecom interconnects applications, respectively. The design and analysis of the grating coupler is carried out using two-dimensional (2-D) Fourier-eigenmode expansion method (F-EEM) and finite difference time domain (FDTD) method. The simulations show a peak fiber-chip coupling efficiency of -1:61 dB and - 1:97 dB at 1.3 μm and 1.55 μm wavelengths, respectively, with a minimum feature size of 100 nm, compatible with 193 nm deep-ultraviolet (DUV) lithography. The measurements of our fabricated continuously apodized grating coupler demonstrate fiber-chip coupling efficiency of - 2:16 dB at a wavelength near 1.55 μm with a 3 dB bandwidth of 64 nm. These results open promising prospects for low-cost and high-volume fabrication of surface grating couplers in SOI using 193 nm DUV lithography, which is now used in several silicon photonics foundries. It is also predicted that a coupling efficiency as high as - 0:42 dB can be achieved for the coupler structure with a bottom dielectric mirror.
Keywords: Fabrication; Fibers; Finite difference time domain method; Integrated optics; Light; Optical fiber fabrication; Optical fibers; Optical interconnects; Photonic devices; Photonics; Refractive index; Silicon on insulator technology; Telecommunication; Time domain analysis; Datacommunications; Dielectric reflectors; Grating couplers; Silicon photonics; Sub-wave length grating; Diffraction gratings

Confirming HD 23478 as a new magnetic B star hosting an Hα-bright centrifugal magnetosphere - Sikora, J.; Wade, G. A.; Bohlender, D. A.; Neiner, C.; Oksala, M. E.; Shultz, M.; Cohen, D. H.; Ud-Doula, A.; Grunhut, J.; Monin, D.; Owocki, S.; Petit, V.; et al. (Monthly Notices of the Royal Astronomical Society, 2015)
In this paper, we report 23 magnetic field measurements of the B3IV star HD23478: 12 obtained from high-resolution Stokes V spectra using the ESPaDOnS (Canada-France-Hawaii Telescope) and Narval (Télescope Bernard Lyot) spectropolarimeters, and 11 from mediumresolution Stokes V spectra obtained with the DimaPol spectropolarimeter (Dominion Astronomical Observatory). HD23478 was one of two rapidly rotating stars identified as potential 'centrifugal magnetosphere' hosts based on IR observations from the Apache Point Observatory Galactic Evolution Experiment survey. We derive basic physical properties of this star including its mass (M = 6.1+0.8-0.7M⊙), effective temperature (Teff = 20 ± 2 kK), radius (R = 2.7+1.6 -0.9 R⊙), and age (τage = 3+37 -1 Myr). We repeatedly detect weakly variable Zeeman signatures in metal, He, and H lines in all our observations corresponding to a longitudinal magnetic field of (Bz) ≈ -2.0 kG. The rotational period is inferred from Hipparcos photometry (Prot = 1.0498(4) d). Under the assumption of the Oblique RotatorModel, our observations yield a surface dipole magnetic field of strength Bd ≥ 9.5 kG that is approximately aligned with the stellar rotation axis. We confirm the presence of strong and broad Hα emission and gauge the volume of this star's centrifugal magnetosphere to be consistent with those of other Hα emitting centrifugal magnetosphere stars based on the large inferred Alfvén to Kepler radius ratio.

Glucose assisted synthesis of hollow spindle LiMnPO4/C nanocomposites for high performance Li-ion batteries - Fu, X.; Chang, Z.; Chang, K.; Li, B.; Tang, H.; Shangguan, E.; Yuan, X.-Z.; Wang, H. (Electrochimica Acta, 2015)
Nano-sized hollow spindle LiMnPO4 with a well-developed olivine-type structure was synthesized with the assistance of glucose in dimethyl sulfoxide (DMSO)/H2O under ambient pressure and 108 °C. The scanning electron microscopy (SEM) and transmission electron microscope (TEM) images show that the LiMnPO4 particles consist of hollow spindles with a mean width of 200 nm, length of 500-700 nm, and wall thickness of about 30-60 nm. The LiMnPO4/C nanocomposite was obtained by sintering nano-sized LiMnPO4 with glucose at 650 °C under an inert atmosphere for 4 h. With a coated carbon thickness of about 10 nm, the obtained composite maintained the morphology and size of the hollow spindle. The electrochemical tests show the specific capacity of LiMnPO4/C nanocomposite is 161.8 mAh g-1 at 0.05C, 137.7 mAh g-1 at 0.1C and 110.8 mAh g-1 at 0.2 C. The retention of discharge capacity maintains 92% after 100 cycles at 0.2 C. After different rate cycles the high capacity of the LiMnPO4/C nanocomposite can be recovered. This high performance is attributed to the composite material's hollow spindle structure, which facilitates the electrolyte infiltration, resulting in an increased solid-liquid interface. The carbon layer covering the hollow spindle also contributes to the high performance of the LiMnPO4/C material as the carbon layer improves its electronic conductivity and the nano-scaled wall thickness decreases the paths of Li deintercalation.
Keywords: Lithium ion battery; lithium manganese phosphate; solution-phased method; low temperature synthesis; dimethyl sulfoxide

Storage and retrieval of ultrafast single photons using a room-temperature diamond quantum memory - Fisher, K.A.G.; England, D.; Maclean, J.-P.; Bustard, P.J.; Lausten, R.; Resch, K.J.; Sussman, B.J. (CLEO: QELS - Fundamental Science, CLEO_QELS 2015, 2015)
We experimentally demonstrated the storage and retrieval of THz-bandwidth single photons in a room-temperature diamond quantum memory. We have shown that the non-classical nature of retrieved light is preserved by the memory process.
Keywords: Quantum memory; Room temperature; Single photons; Storage and retrievals; Ultra-fast; Photons

The novel receptor C5aR2 is required for C5a-mediated human mast cell adhesion, migration, and proinflammatory mediator production - Pundir, Priyanka; MacDonald, Clayton A.; Kulka, Marianna (Journal of Immunology, 2015)
C5a generated during complement activation possesses proinflammatory and immunoregulatory properties critical for the development and modulation of allergic immune responses. In immune cells, C5a mediates its effects through binding to two G protein-coupled receptors, C5aR1 and C5aR2. Mast cells are key effectors in allergic reactions, and decades of research have suggested that the majority of C5a effects on mast cells are mediated through C5aR1, whereas the expression and function of C5aR2 have not been explored. We demonstrated that the human mast cell line Laboratory of Allergic Diseases 2 (LAD2) expresses surface C5aR2 but not C5aR1, whereas CD34+ cell-derived primary mast cells do not express surface C5aR1 or C5aR2. Stem cell factor and IL-4 upregulated C5aR2 expression on LAD2 cells. Furthermore, C5a caused internalization of LAD2 cell-surface C5aR2.We therefore used LAD2 cells as a model to study C5a/C5aR2-induced biological responses and signaling in human mast cells. We found that whereas C5a was unable to induce degranulation, it stimulated GM-CSF, TNF, CXCL10, and CCL2 production. C5a caused ERK phosphorylation, a signaling molecule important in cytokine and chemokine generation. In addition, C5a stimulated adhesion and chemotaxis of mast cells.Wortmannin, an inhibitor of PI3K, and small interfering RNA against b-arrestin-2 blocked C5a-induced adhesion. Silencing of C5aR2 using lentiviral short hairpin RNA rendered the cells unresponsive to C5a-induced adhesion, chemotaxis, and mediator release, as well as ERK phosphorylation. Overall, this study reveals a novel role for C5aR2 in C5a-mediated activation of mast cells and demonstrates that C5aR2 ligation initiates a b-arrestin-2-, PI3K-, and ERK-dependent signaling pathway in these cells.
Keywords: CD34 antigen; complement component C5a receptor; complement component C5a receptor 1; complement component C5a receptor 2; gamma interferon inducible protein 10; granulocyte macrophage colony stimulating factor; mitogen activated protein kinase; monocyte chemotactic protein 1; small interfering RNA; stem cell factor; tumor necrosis factor; unclassified drug; cell adhesion; cell migration; cell surface; chemotaxis; controlled study; cytokine production; enzyme phosphorylation; internalization; mast cell degranulation; protein determination; protein expression; protein function; protein secretion; signal transduction

Inferring aspect-specific opinion structure in product reviews using co-training - Carter, Dave; Inkpen, Diana (Computational Linguistics and Intelligent Text Processing : 16th International Conference, CICLing 2015, Cairo, Egypt, April 14-20, 2015, Proceedings, Part II, 2015)
Opinions expressed about a particular subject are often nuanced:a person may have both negative and positive opinions aboutdifferent aspects of the subject of interest, and these aspect-specific opinionscan be independent of the overall opinion. Being able to identify,collect, and count these nuanced opinions in a large set of data offersmore insight into the strengths and weaknesses of competing productsand services than does aggregating overall ratings. We contribute a newconfidence-based co-training algorithm that can identify product aspectsand sentiments expressed about such aspects. Our algorithm offers betterprecision than existing methods, and handles previously unseen languagewell. We show competitive results on a set of opinionated sentences aboutlaptops and restaurants from a SemEval-2014 Task 4 challenge.
Keywords: Linguistics; Text processing; Co-training; Co-training algorithm; Product reviews; Computational linguistics

The nature of bonding between argon and mixed gold-silver trimers - Shayeghi, A.; Johnston, R. L.; Rayner, D. M.; Schäfer, R.; Fielicke, A. (Angewandte Chemie: International Edition, 2015)
The controversial nature of chemical bonding between noble gases and noble metals is addressed. Experimental evidence of exceptionally strong Au-Ar bonds in Ar complexes of mixed Au-Ag trimers is presented. IR spectra reveal an enormous influence of the attached Ar atoms on vibrational modes, particularly in Au-rich trimers, where Ar atoms are heavily involved owing to a relativistically enhanced covalency. In Ag-rich trimers, vibrational transitions of the metal framework predominate, indicating a pure electrostatic character of the Ag-Ar bonds. The experimental findings are analyzed by means of DFT calculations, which show how the relativistic differences between Au and Ag are manifested in stronger Au-Ar binding energies. Because of the ability to vary composition and charge distribution, the trimers serve as ideal model systems to study the chemical nature of the bonding of noble gases to closed-shell systems containing gold.
Keywords: Binding energy; Gold; Inert gases; Infrared spectroscopy; Ionization of gases; Oligomers; Precious metals; Closed shell system; Clusters; DFT calculation; Experimental evidence; Vibrational transitions; Chemical bonds

Microbial community composition, functions, and activities in the gulf of mexico 1 year after the deepwater horizon accident - Yergeau, E.; Maynard, C.; Sanschagrin, S.; Champagne, J.; Juck, D.; Lee, K.; Greer, C.W. (Applied and Environmental Microbiology, 2015)
Several studies have assessed the effects of the released oil on microbes, either during or immediately after the Deepwater Horizon accident. However, little is known about the potential longer-term persistent effects on microbial communities and their functions. In this study, one water column station near the wellhead (3.78 km southwest of the wellhead), one water column reference station outside the affected area (37.77 km southeast of the wellhead), and deep-sea sediments near the wellhead (3.66 km southeast of the wellhead) were sampled 1 year after the capping of the well. In order to analyze microbial community composition, function, and activity, we used metagenomics, metatranscriptomics, and mineralization assays. Mineralization of hexadecane was significantly higher at the wellhead station at a depth of ~1,200 m than at the reference station. Community composition based on taxonomical or functional data showed that the samples taken at a depth of ~1,200 m were significantly more dissimilar between the stations than at other depths (surface, 100 m, 750 m, and >1,500 m). Both Bacteria and Archaea showed reduced activity at depths of ~1,200 m when the wellhead station was compared to the reference station, and their activity was significantly higher in surficial sediments than in 10-cm sediments. Surficial sediments also harbored significantly different active genera than did 5- and 10-cm sediments. For the remaining microbial parameters assessed, no significant differences could be observed between the wellhead and reference stations and between surface and 5- to 10-cm-deep sediments.
Keywords: Bacteria; Microorganisms; Mineralogy; Sediments; Wellheads; Deepwater horizons; Metatranscriptomics; Microbial communities; Mineralization assays; Reference stations; Surficial sediments

Oleanane triterpenoid saponins of Caragana arborescens and their quantitative determination - Taylor, W.G.; Sutherland, D.H.; Richards, K.W.; Zhang, H. (Industrial Crops and Products, 2015)
Seed extracts of common Caragana (Caragana arborescens), belonging to the pea family (Fabaceae), were prepared by Diaion HP-20 resin technology and examined for the presence of triterpenoid saponins by a combination of chromatographic, spectroscopic and spectrometric techniques. Electrospray LC-MS on the extracts indicated the presence of soyasaponin I (1a), soyasaponin VI (soyasaponin βg,. 1b) possessing a 2,3-dihydro-2,5-dihydroxy-6-methyl-4 H-pyran-4-one (DDMP) group, 22-propionylsoyasaponin I (1c), soyasaponin III (2a), the DDMP conjugate of soyasaponin III (2b) and 22-propionylsoyasaponin III (2c). Alkaline hydrolysis conditions were employed to convert the C-22 conjugates to soyasaponin I (and soyasaponin III), utilizing sodium hydroxide in ethanol and HPLC with an evaporative light scattering detector and internal standard. A quantitative method based on high performance liquid chromatography-tandem mass spectrometry (LC-MS/MS) with digoxin as internal standard was developed to determine 1a in the extracts. After hydrolysis and C18 SepPak clean-up with aqueous ethanol as solvent, seeds of Caragana collected over 3 years gave 1a concentrations of 1041-1563. mg/kg of hexane-defatted flour.
Keywords: Caragana arborescens; Seeds; Triterpenoid saponins; Alkaline hydrolysis; Soyasaponin I; Electrospray LC–MS quantification

Colorless devices and reception techniques for polarization multiplexed communications - Halir, Robert; Reyes-Iglesias, Pedro; Alonso-Ramos, Carlos; Sarmiento-Merenguel, Darío; Wanguemert-Perez, Gonzalo; Cheben, Pavel; Molina-Fernandez, Íñigo; Ortega-Monux, Alejandro (International Conference on Transparent Optical Networks, 2015)
Future optical networks call for flexible, high performance and low cost coherent optical receivers. We present here several advances towards such receivers, including integrated optical couplers with ultra-broad bandwidth, as well as novel reception techniques and architectures that will enable high performance coherent reception without filtering and polarization splitting elements.
Keywords: Network architecture; Coherent receivers; Colorless operation; Multimode interference couplers; OSNR penalty; Polarization splitters; Receiver architecture; Transparent optical networks

Light- and pH-activated intracellular drug release from polymeric mesoporous silica nanoparticles - Tian, Y.; Kong, Y.; Li, X.; Wu, J.; Ko, A.C.-T.; Xing, M. (Colloids and Surfaces B: Biointerfaces, 2015)
Surface modified mesoporous silica nanoparticles (MSNs) with reduced toxicity were prepared for light and pH dual triggerable drug delivery system. Both 413nm light and acidic environment can activate the drug release process, improving the pharmacological action. By applying rhodamine B (RhB) as a model drug, the accumulative RhB release is as high as 95% in pH 5.0 and in irradiation of 413nm light, compared to only 55% in pH 7.4 and in dark. The anti-cancer drug camptothecin (CPT) loaded nanoparticles can kill cancer cells with IC50 value of 0.02μgmL-1 in exposure of 413nm light, which is much lower than free CPT (about 0.1μgmL-1). Multimodal nonlinear optical imaging microscopy (NLOM) was employed to acquire in vitro coherent anti-Stokes Raman (CARS) and two-photon excited fluorescence (TPEF) images of live MCF-7 cells and showed that the nanoparticles can be taken up by breast tumor cell MCF-7 with high efficiency, indicating its great potential for anti-cancer drug delivery system.
Keywords: Mesoporous silica nanoparticle; pH sensitive; Light sensitive; Anticancer drug release; Live cell multimodal nonlinear optical imaging (CARS and TPEF)

Hierarchical progressive surveys: multi-resolution HEALPix data structures for astronomical images, catalogues, and 3-dimensional data cubes - Fernique, P.; Allen, M.G.; Boch, T.; Oberto, A.; Pineau, F.-X.; Durand, D.; Bot, C.; Cambrésy, L.; Derriere, S.; Genova, F.; Bonnarel, F. (Astronomy and Astrophysics, 2015)
Context. Scientific exploitation of the ever increasing volumes of astronomical data requires efficient and practical methods for data access, visualisation, and analysis. Hierarchical sky tessellation techniques enable a multi-resolution approach to organising data on angular scales from the full sky down to the individual image pixels. Aims. We aim to show that the hierarchical progressive survey (HiPS) scheme for describing astronomical images, source catalogues, and three-dimensional data cubes is a practical solution to managing large volumes of heterogeneous data and that it enables a new level of scientific interoperability across large collections of data of these different data types. Methods. HiPS uses the HEALPix tessellation of the sphere to define a hierarchical tile and pixel structure to describe and organise astronomical data. HiPS is designed to conserve the scientific properties of the data alongside both visualisation considerations and emphasis on the ease of implementation. We describe the development of HiPS to manage a large number of diverse image surveys, as well as the extension of hierarchical image systems to cube and catalogue data. We demonstrate the interoperability of HiPS and multi-order coverage (MOC) maps and highlight the HiPS mechanism to provide links to the original data. Results. Hierarchical progressive surveys have been generated by various data centres and groups for ∼200 data collections including many wide area sky surveys, and archives of pointed observations. These can be accessed and visualised in Aladin, Aladin Lite, and other applications. HiPS provides a basis for further innovations in the use of hierarchical data structures to facilitate the description and statistical analysis of large astronomical data sets.
Keywords: surveys; atlases; astronomical databases; virtual observatory tools; statistical methods; geometry; hierarchical systems; interoperability; pixels; catalogs; information management

Erratum: Improving the performance of high voltage LiMn1.5Ni0.5O4 cathode material by carbon coating (Journal of Power Sources 271 (2014) 285-290)) - Niketic, Svetlana; Couillard, Martin; Macneil, Dean; Abu-Lebdeh, Yaser (Elsevier, 2015)

Characterization of the ultrafine and black carbon emissions from different aviation alternative fuels - Chan, T.; Chishty, W.; Davison, C.; Buote, D. (SAE International Journal of Fuels and Lubricants, 2015)
This study reports gaseous and particle (ultrafine and black carbon (BC)) emissions from a turbofan engine core on standard Jet A-1 and three alternative fuels, including 100% hydrothermolysis synthetic kerosene with aromatics (CH-SKA), 50% Hydro-processed Esters and Fatty Acid paraffinic kerosene (HEFA-SPK), and 100% Fischer Tropsch (FT-SPK). Gaseous emissions from this engine for various fuels were similar but significant differences in particle emissions were observed. During the idle condition, it was observed that the non-refractory mass fraction in the emitted particles were higher than during higher engine load condition. This observation is consistent for all test fuels. The 100% CH-SKA fuel was found to have noticeable reductions in BC emissions when compared to Jet A-1 by 28-38% by different BC instruments (and 7% in refractory particle number (PN) emissions) at take-off condition. BC emissions from this fuel were lower than from Jet A-1 by 45-50% (and 25-26% in refractory PN) at idle or cruise condition. The 100% CH-SKA fuel was observed to have a minimum influence on non-refractory PN emissions. A lower volume in naphthalene in the 100% CH-SKA fuel was hypothesized to be one of the factors attributing to the reduced BC emissions when compared to Jet A-1 emissions. For the 50% HEFA-SPK fuel, BC emissions were lower than the BC emissions from Jet A-1 by 58-86% for various engine load conditions. BC emissions from the 100% FT-SPK fuel were lower than from the Jet A-1 by 70-98%. Both the refractory and non-refractory PN emissions from these fuels were lower by comparable magnitude when compared to that from Jet A-1.

Dispersion corrections improve the accuracy of both noncovalent and covalent interactions energies predicted by a density-functional theory approximation - Van Santen, Jeffrey A.; Dilabio, Gino A. (The Journal of Physical Chemistry A, 2015)
The use of pairwise dispersion corrections together with dispersion-correcting potentials (DCPs) offers a computationally low-cost approach to improving the performance of a density-functional theory based method with respect to the prediction of important chemical properties. In this work, we develop DCPs for the C, H, N, and O atoms for use with the BLYP generalized gradient approximation functional coupled with "D3" pairwise dispersion corrections and 6-31+G(2d,2p) basis sets. The combined approach, referred to as BLYP-D3-DCP, offers generally improved performance over both unadorned BLYP and BLYP with D3 corrections with respect to the prediction of noncovalent binding energies (BEs) and covalent bond dissociation enthalpies (BDEs). Predicted barrier heights for a set of pericyclic and Diels-Alder reactions are improved in some instances, as are organic bond separation reaction energies and radical stabilization energies. It is also shown that the BLYP-D3-DCP approach outperforms B3LYP-D3 in the prediction of many chemical properties, in particular noncovalent BEs and BDEs, suggesting that the addition of D3 and DCP corrections, which have negligible computational cost, to simple density functionals like BLYP may elevate their performance to that of more complex functionals such as B3LYP.
Keywords: Binding energy; Chemical bonds; Chemical properties; Computation theory; Dispersions; Bond dissociation enthalpies; Computational costs; Covalent interactions; Density functionals; Diels-Alder reaction; Dispersion correction; Generalized gradient approximations; Radical stabilization energy; Density functional theory

Ultrafast dynamics of o-nitrophenol: An experimental and theoretical study - Ernst, Hanna A.; Wolf, Thomas J. A.; Schalk, Oliver; González-García, Nuria; Boguslavskiy, Andrey E.; Stolow, Albert; Olzmann, Matthias; Unterreiner, Andreas-Neil (The Journal of Physical Chemistry A, 2015)
The photolysis of o-nitrophenol (o-NP), a typical push-pull molecule, is of current interest in atmospheric chemistry as a possible source of nitrous acid (HONO). To characterize the largely unknown photolysis mechanism, the dynamics of the lowest lying excited singlet state (S1) of o-NP was investigated by means of femtosecond transient absorption spectroscopy in solution, time-resolved photoelectron spectroscopy (TRPES) in the gas phase and quantum chemical calculations. Evidence of the unstable aci-nitro isomer is provided both in the liquid and in the gas phase. Our results indicate that the S1 state displays strong charge transfer character, which triggers excited state proton transfer from the OH to the NO2 group as evidenced by a temporal shift of 20 fs of the onset of the photoelectron spectrum. The proton transfer itself is found to be coupled to an out-of-plane rotation of the newly formed HONO group, finally leading to a conical intersection between S1 and the ground state S0. In solution, return to S0 within 0.2-0.3 ps was monitored by stimulated emission. As a competitive relaxation channel, ultrafast intersystem crossing to the upper triplet manifold on a subpicosecond time scale occurs both in solution and in the gas phase. Due to the ultrafast singlet dynamics, we conclude that the much discussed HONO split-off is likely to take place in the triplet manifold.
Keywords: Absorption spectroscopy; Atmospheric chemistry; Charge transfer; Gases; Ground state; Inorganic acids; Ionization of gases; Phenols; Photoelectron spectroscopy; Photoelectrons; Photolysis; Photons; Proton transfer; Quantum chemistry; Quantum theory; Excited-state proton transfer; Femtosecond transient absorption spectroscopy; Inter-system crossings; Out-of-plane rotation; Photoelectron spectrum; Quantum chemical calculations; Subpicosecond time scale; Time-resolved photoelectron spectroscopy

Comparative life cycle assessment of power-to-gas generation of hydrogen with a dynamic emissions factor for fuel cell vehicles - Walker, Sean B.; Fowler, Michael; Ahmadi, Leila (Journal of Energy Storage, 2015)
Power-to-gas, an excellent energy storage technology, is also useful for the role it can play in producing hydrogen for fuel cell vehicles. The replacement of the existing transportation infrastructure and the end of society's reliance on carbon-based fuels is dependent on the development of efficient, cleaner technologies as well as 'smart energy networks'. One of the most touted technological advances is the replacement of internal combustion engines with 'green' hydrogen fuel cell vehicles. Hydrogen fuel cell vehicles do not emit any greenhouse gases or other emissions as such do not directly contribute to climate change or urban air pollution during their operation. With green hydrogen as the fuel, the emissions from the fuel production become dependent not on the vehicle type or electrolyzer technology, but on the sources of electricity being used to generate the hydrogen. In this study, the authors examine the use of electrolytic hydrogen to power vehicles and compare this with its internal combustion counterpoint. In this analysis a dynamic electrical grid emissions factor, based on the total grid mix of energy generation technologies at any given time, is determined. In this case study, the province of Ontario, Canada is used. Unique to this work is that the simulation of the generation of hydrogen is via electrolysis under different control strategies; the strategies considered, specifically, are continuous electrolyzer operation, price threshold operation, or operation based on an emission factor threshold based on the mix of energy generation technologies feeding the grid at any given hour. With the introduction of new policy tools to reduce greenhouse gas emissions, such as carbon taxes and cap-and-trade, the monetization of emissions provides an even greater incentive for industry to reduce their greenhouse gas emissions. In this study, it is illustrated that by using the dynamic emissions factor to control the production of hydrogen, emissions can be significantly reduced over the life of the vehicle.
Keywords: power-to-gas; LCA; green hydrogen; hydrogen economy; dynamic emissions factor

Influence of annealing temperature on the structure and electrochemical performance of the Fe3O4 anode material for alkaline secondary batteries - Li, F.; Shangguan, E.; Li, J.; Li, L.; Yang, J.; Chang, Z.; Li, Q.; Yuan, X.-Z.; Wang, H. (Electrochimica Acta, 2015)
High-performance Fe3O4 polyhedrons as alkaline secondary battery anode materials have successfully been synthesized using a facile co-precipitation method with a subsequent annealing treatment at 700°C for 1 h. The physical and electrochemical properties of the Fe3O4 samples annealed at different temperatures are investigated. It has been discovered that the annealing temperature plays a vital role in improving the physical and electrochemical performances of the Fe3O4 materials. The results also indicate that the Fe3O4 sample annealed at 700°C performs better (faster activation rate, higher specific discharge capacity, better high-rate ability and cycle stability) than the samples annealed at other temperatures. The specific discharge capacity of the 700°C-annealed Fe3O4 reaches 604.2mAh g-1 at a current density of 120 mA g-1 with a charging efficiency of 83.9%. Moreover, discharge capacities of 587.6, 539.5 and 500.1 mAh g-1 are achieved at 240, 600 and 1200 mA g-1, respectively, exhibiting remarkable high-rate discharge capability. This performance improvement may be attributable to better reaction reversibility, lower charge transfer impedance and better inhibiting effect on hydrogen evolution reaction of the material. We believe that this Fe3O4 polyhedron is a promising candidate as the anode material for high-performance alkaline secondary batteries.
Keywords: Anode material; alkaline secondary batteries; Iron electrode; Electrochemical properties

Maximum-information photoelectron metrology - Hockett, P.; Lux, C.; Wollenhaupt, M.; Baumert, T. (Physical Review A: Atomic, Molecular, and Optical Physics, 2015)
Photoelectron interferograms, manifested in photoelectron angular distributions (PADs), are high-information, coherent observables. In order to obtain the maximum information from angle-resolved photoionization experiments it is desirable to record the full, three-dimensional (3D), photoelectron momentum distribution. Here we apply tomographic reconstruction techniques to obtain such 3D distributions from multiphoton ionization of potassium atoms, and fully analyze the energy and angular content of the 3D data. The PADs obtained as a function of energy indicate good agreement with previous 2D data and detailed analysis [Hockett, Phys. Rev. Lett. 112, 223001 (2014)10.1103/PhysRevLett.112.223001] concerning the main spectral features, but also indicate unexpected symmetry breaking in certain regions of momentum space, thus revealing additional continuum interferences which cannot otherwise be observed. These observations reflect the presence of additional ionization pathways and, most generally, illustrate the power of maximum-information measurements of coherent observables for quantum metrology of complex systems.
Keywords: Ionization; Ionization of gases; Photoelectrons; Photoionization; Units of measurement; Angle resolved photoionization; Continuum interference; Information measurement; Momentum distributions; Multiphoton ionization; Photoelectron angular distributions; Threedimensional (3-d); Tomographic reconstruction techniques; Photons

Cellulose nanocrystal cationic derivative induces NLRP3 inflammasome-dependent IL-1β secretion associated with mitochondrial ROS production - Sunasee, R.; Araoye, E.; Pyram, D.; Hemraz, U.D.; Boluk, Y.; Ckless, K. (Biochemistry and Biophysics Reports, 2015)
Crystalline cellulose nanocrystals (CNCs) have emerged as novel materials for a wide variety of important applications such as nanofillers, nanocomposites, surface coatings, regenerative medicine and potential drug delivery. CNCs have a needle-like structure with sizes in the range of 100-200. nm long and 5-20. nm wide and a mean aspect ratio 10-100. Despite the great potential applicability of CNCs, very little is known about their potential immunogenicity. Needle-like materials have been known to evoke an immune response in particular to activate the (NOD-. like receptor, pyrin domain-containing 3)-inflammasome/IL-1β (Interleukin 1β) pathway. In this study we evaluated the capacity of unmodified CNC and its cationic derivatives CNC-AEM (aminoethylmethacrylate)1, CNC-AEM2, CNC-AEMA(aminoethylmethacrylamide)1 and CNC-AEMA2 to stimulate NLRP3-inflammasome/IL-1β pathway and enhance the production of mitochondrial reactive oxygen species (ROS). Mouse macrophage cell line (J774A.1) was stimulated for 24. h with 50. μg/mL with unmodified CNC and its cationic derivatives. Alternatively, J774A1 or PBMCs (peripheral blood mononuclear cells) were stimulated with CNC-AEMA2 in presence or absence of LPS (lipopolysaccharide). IL-1β secretion was analyzed by ELISA, mitochondrial function by JC-1 staining and ATP content. Intracellular and mitochondrial reactive oxygen species (ROS) were assessed by DCF-DA (2',7'-dichlorodihydrofluorescein diacetate) and MitoSOX, respectively. Mitochondrial ROS and extracellular ATP were significantly increased in cells treated with CNC-AEMA2, which correlates with the strongest effects on IL-1β secretion in non-primed cells. CNC-AEMA2 also induced IL-1βsecretion in LPS-primed and non-primed PBMCs. Our data suggest that the increases in mitochondrial ROS and ATP release induced by CNC-AEMA2 may be associated with its capability to evoke immune response. We demonstrate the first evidence that newly synthesized cationic cellulose nanocrystal derivative, CNC-AEMA2, has immunogenic properties, which may lead to the development of a potential non-toxic and safe nanomaterial to be used as a novel adjuvant for vaccines.
Keywords: Cellulose nanocrystals; Cationic needle-like nanomaterial; NLRP3 inflammasome; IL-1β; Mitochondrial ROS; Mouse macrophages

Stable structures of He and H2 O at high pressure - Liu, Hanyu; Yao, Yansun; Klug, Dennis D. (Physical Review B: Condensed Matter and Materials Physics, 2015)
The knowledge of the structures that can exist in compounds containing helium is of interest for understanding the conditions where and if this inert element can form structures where closed shell electrons of helium can participate in bonding that is not describable exclusively by van der Waals interactions alone. In this study we examine stable mixtures of He and H2O at high pressures using a first-principles structure searching method. We find a thermodynamically stable structure that can be characterized by interactions comparable in strength to that of conventional hydrogen bonds. An orthorhombic structure with space group Ibam is identified that has progressively lower enthalpy with increasing pressure above 296 GPa than a mixture of He and H2O. This mechanically and dynamically stable structure is found at pressures that are now becoming accessible to high-pressure techniques.

Complete photoionization experiments via ultrafast coherent control with polarization multiplexing. II. Numerics and analysis methodologies - Hockett, P.; Wollenhaupt, M.; Lux, C.; Baumert, T. (Physical Review A: Atomic, Molecular, and Optical Physics, 2015)
The feasibility of complete photoionization experiments, in which the full set of photoionization matrix elements is determined, using multiphoton ionization schemes with polarization-shaped pulses has recently been demonstrated [P. Hockett, Phys. Rev. Lett. 112, 223001 (2014)10.1103/PhysRevLett.112.223001]. Here we extend our previous work to discuss further details of the numerics and analysis methodology utilized and compare the results directly to new tomographic photoelectron measurements, which provide a more sensitive test of the validity of the results. In so doing we discuss in detail the physics of the photoionization process and suggest various avenues and prospects for this coherent multiplexing methodology.
Keywords: Ionization; Multiphoton processes; Multiplexing; Polarization; Coherent control; Matrix elements; Multiphoton ionization; Photoionization process; Polarization multiplexing; Shaped pulse; Tomographic; Ultra-fast; Photoionization

Charge-induced dipole vs. relativistically enhanced covalent interactions in Ar-tagged Au-Ag tetramers and pentamers - Shayeghi, A.; Schäfer, R.; Rayner, D.M.; Johnston, R.L.; Fielicke, A. (Journal of Chemical Physics, 2015)
Vibrational spectra of Au n Ag m + · Ar k (n + m = 4, 5; k = 1-4) clusters are determined by far-infrared resonant multiple photon dissociation spectroscopy in the range ν = 100 -250 cm-1. The experimental spectra are assigned using density functional theory for geometries obtained by the Birmingham cluster genetic algorithm. Putative global minimum candidates of the Ar complexes are generated by adding Ar atoms to the Au n Ag m + low energy isomers and subsequent local optimization. Differential Ar binding energies indicate exceptionally strong Au-Ar bonds in Au-rich clusters, leading to fundamental changes to the IR spectra. The stronger Ar binding is attributed to a relativistically enhanced covalent character of the Au-Ar bond, while in Au-rich species charge-induced dipole interactions overcompensate the relativistic affinity to Au. Moreover, not only the absolute composition but also the topologies are essential in the description of Ar binding to a certain cluster.
Keywords: Density functional theory; Genetic algorithms; Isomers; Charge-induced dipoles; Covalent character; Covalent interactions; Energy isomers; Experimental spectra; Multiple-photon dissociation; Binding energy

Particle filter-based model fusion for prognostics - García, Claudia Maria; Zou, Yanni; Yang, Chunsheng (Current Approaches in Applied Artificial Intelligence : 28th International Conference on Industrial, Engineering and Other Applications of Applied Intelligent Systems, IEA/AIE 2015, Seoul, South Korea, June 10-12, 2015, Proceedings, 2015)
Predictive maintenance is an emerging technology which aims at increasing availability of systems, reducing maintenance cost, and ensuring the safety of systems. There exist two main issues in predictive maintenance. The first challenge is the system operation region definition, detection and modelling; and another one is estimation of the remaining useful life (RUL). To address these issues, this paper proposes a particle filter (PF)-based model fusion approach for estimating RUL by classifying the system states into different operation regions in which a data-driven model is developed to estimate RUL corresponding to each region, and combined with PF-based fusion algorithm. This paper reports the proposed approach along with some preliminary results obtained from a case study.

Photodissociation dynamics of Cyclopropenylidene, c-C3H2 - Schuurman, M.S.; Giegerich, J.; Pachner, K.; Lang, D.; Kiendl, B.; MacDonell, R.J.; Krueger, A.; Fischer, I. (Chemistry: A European Journal, 2015)
In this joint experimental and theoretical study we characterize the complete dynamical "life cycle" associated with the photoexcitation of the singlet carbene cyclopropenylidene to the lowest lying optically bright excited electronic state: from the initial creation of an excited-state wavepacket to the ultimate fragmentation of the molecule on the vibrationally hot ground electronic state. Cyclopropenylidene is prepared in this work using an improved synthetic pathway for the preparation of the precursor quadricyclane, thereby greatly simplifying the assignment of the molecular origin of the measured photofragments. The excitation process and subsequent non-adiabatic dynamics have been previously investigated employing time-resolved photoelectron spectroscopy and are now complemented with high-level ab initio trajectory simulations that elucidate the specific vibronic relaxation pathways. Lastly, the fragmentation channels accessed by the molecule following internal conversion are probed using velocity map imaging (VMI) so that the identity of the fragmentation products and their corresponding energy distributions can be definitively assigned.
Keywords: Chemical reactions; Electronic states; Life cycle; Molecular dynamics; Molecules; Organic compounds; Phase interfaces; Photodissociation; Photoelectron spectroscopy; Pyrolysis; Reaction kinetics; Ab initio molecular dynamics; Flash pyrolysis; Gas-phase reactions; Non-adiabatic process

A cascaded life cycle: reuse of electric vehicle lithium-ion battery packs in energy storage systems - Ahmadi, L.; Young, S.B.; Fowler, M.; Fraser, R.A.; Achachlouei, M.A. (International Journal of Life Cycle Assessment, 2015)
Purpose: Lithium-ion (Li-ion) battery packs recovered from end-of-life electric vehicles (EV) present potential technological, economic and environmental opportunities for improving energy systems and material efficiency. Battery packs can be reused in stationary applications as part of a “smart grid”, for example to provide energy storage systems (ESS) for load leveling, residential or commercial power. Previous work on EV battery reuse has demonstrated technical viability and shown energy efficiency benefits in energy storage systems modeled under commercial scenarios. The current analysis performs a life cycle assessment (LCA) study on a Li-ion battery pack used in an EV and then reused in a stationary ESS. Methods: A complex functional unit is used to combine energy delivered by the battery pack from the mobility function and the stationary ESS. Various scenarios of cascaded “EV mobility plus reuse in stationary clean electric power scenarios” are contrasted with “conventional system mobility with internal combustion engine vehicles plus natural gas peaking power.” Eight years are assumed for first use; with 10 years for reuse in the stationary application. Operational scenarios and environmental data are based on real time-of-day and time-of-year power use. Additional data from LCA databases are utilized. Ontario, Canada, is used as the geographic baseline; analysis includes sensitivity to the electricity mix and battery degradation. Seven environmental categories are assessed using ReCiPe. Results and discussion: Results indicate that the manufacturing phase of the Li-ion battery will still dominate environmental impacts across the extended life cycle of the pack (first use in vehicle plus reuse in stationary application). For most impact categories, the cascaded use system appears significantly beneficial compared to the conventional system. By consuming clean energy sources for both use and reuse, global and local environmental stress reductions can be supported. Greenhouse gas advantages of vehicle electrification can be doubled by extending the life of the EV batteries, and enabling better use of off-peak low-cost clean electricity or intermittent renewable capacity. However, questions remain concerning implications of long-duration use of raw material resources employed before potential recycling. Conclusions: Li-ion battery packs present opportunities for powering both mobility and stationary applications in the necessary transition to cleaner energy. Battery state-of-health is a considerable determinant in the life cycle performance of a Li-ion battery pack. The use of a complex functional unit was demonstrated in studying a component system with multiple uses in a cascaded application.
Keywords: Electric vehicle; Energy storage systems (ESS); Life cycle assessment (LCA); Li-ion battery; Resource efficiency; Reuse; Second use

Group IV photonics for the mid-infrared - Mashanovich, G.Z.; Nedeljkovic, M.; Soler Penades, J.; Mitchell, C.J.; Khokhar, A.Z.; Littlejohns, C.J.; Stankovic, S.; Troia, B.; Passaro, V.M.N.; Shen, L.; Healy, N.; Peacock, A.C.; et al. (Integrated Photonics Research, Silicon and Nanophotonics, IPRSN 2015, 2015)
In this paper we present SOI, suspended Si, and Ge-on-Si photonic platforms and mid- IR passive and active devices based on these platforms. We demonstrate low loss waveguides, splitters, filters, interferometers and spectrometers in different material platforms. Mid-infrared detection using defect engineered silicon waveguides is reported at the wavelength of 2-2.5 μm. All optical modulation in Ge is also analyzed. Finally, theoretical investigation of electroabsorption and electrorefraction in Ge is reported.
Keywords: Germanium; Infrared devices; Nanophotonics; Active devices; Electro-absorption; Electrorefraction; Group-IV photonics; Low-loss waveguides; Mid-infrared detection; Silicon waveguide; Theoretical investigations; Waveguide filters

Biomolecule conjugated nanoparticle synthons for detection of food contaminants - Zaman, M.B.; Karim, M.R.; Ashrafuzzaman, M.; Hanifi-Moghaddam, P. (Canadian Journal of Chemistry, 2015)
This article investigates recent research on a series of photoluminescent nanoparticles (NPs) and supramolecular chemistry at their surface. This in turn prompts the concept of quantum dots supramolecular synthons (QDSS) and foresees the inevitable path towards biomimetics and bioinspired technology. We highlight the methodology how to create QDSS by functional assembly of photoluminescent semiconductors and the surface binding of supramolecular ligands.
Keywords: supramolecular synthon; quantum dot; nanoparticle; hydrogen-bond

Characterization of the microbial community structure and the physicochemical properties of produced water and seawater from the Hibernia oil production platform - Yeung, C.W.; Lee, K.; Cobanli, S.; King, T.; Bugden, J.; Whyte, L.G.; Greer, C.W. (Environmental Science and Pollution Research, 2015)
Hibernia is Canada’s largest offshore oil platform. Produced water is the major waste byproduct discharged into the ocean. In order to evaluate different potential disposal methods, a comprehensive study was performed to determine the impact from the discharge. Microorganisms are typically the first organisms to respond to changes in their environment. The objectives were to characterize the microbial communities and the chemical composition in the produced water and to characterize changes in the seawater bacterial community around the platform. The results from chemical, physicochemical, and microbial analyses revealed that the discharge did not have a detectable effect on the surrounding seawater. The seawater bacterial community was relatively stable, spatially. Unique microorganisms like Thermoanaerobacter were found in the produced water. Thermoanaerobacter-specific q-PCR and nested-PCR primers were designed, and both methods demonstrated that Thermoanaerobacter was present in seawater up to 1000 m from the platform. These methods could be used to track the dispersion of produced water into the surrounding ocean.
Keywords: Produced water; Petroleumwaste byproduct; Microbial communities; DGGE; q-PCR; Thermoanaerobacter

High efficiency blazed fiber-chip grating coupler with interleaved trenches - Alonso-Ramos, C.; Benedikovic, D.; Cheben, P.; Wang, S.; Halir, R.; Fédéli, J. M.; Ortega-Moñux, A.; Schmid, J. H.; Xu, D. -X.; Dado, M.; Molina-Fernández, I. (Proceedings of SPIE: The International Society for Optical Engineering, 2015)
We demonstrate a fiber-chip surface grating coupler that interleaves standard full and shallow-etched trenches to maximize directionality in the upward direction. The coupler is implemented in a regular SOI substrate with 220 nm silicon thickness and etch depths of 220 nm (full etch) and 70 nm (shallow etch), as offered by silicon photonic foundries. The blazing effect is controlled by adjusting the separation between the two sets of trenches. This way, grating directionality exceeding 95% is achieved independently of the bottom oxide (BOX) thickness. Couplers have been fabricated at LETI using 193 nm DUV lithography on 200 mm SOI wafers with 2 μm BOX. The measured coupling efficiency is-2.1 dB with a 3 dB bandwidth of 52 nm.
Keywords: Integrated optics; Coupling efficiency; DUV lithography; Grating couplers; High-efficiency; Silicon photonics; Silicon thickness; SOI; SOI substrates; Silicon wafers

A rapid field test for the measurement of bovine serum immunoglobulin G using attenuated total reflectance infrared spectroscopy - Elsohaby, I.; Hou, S.; McClure, J.T.; Riley, C.B.; Shaw, R.A.; Keefe, G.P. (BMC Veterinary Research, 2015)
Background: Following the recent development of a new approach to quantitative analysis of IgG concentrations in bovine serum using transmission infrared spectroscopy, the potential to measure IgG levels using technology and a device better designed for field use was investigated. A method using attenuated total reflectance infrared (ATR) spectroscopy in combination with partial least squares (PLS) regression was developed to measure bovine serum IgG concentrations. ATR spectroscopy has a distinct ease-of-use advantage that may open the door to routine point-of-care testing. Serum samples were collected from calves and adult cows, tested by a reference RID method, and ATR spectra acquired. The spectra were linked to the RID-IgG concentrations and then randomly split into two sets: calibration and prediction. The calibration set was used to build a calibration model, while the prediction set was used to assess the predictive performance and accuracy of the final model. The procedure was repeated for various spectral data preprocessing approaches. Results: For the prediction set, the Pearson's and concordance correlation coefficients between the IgG measured by RID and predicted by ATR spectroscopy were both 0.93. The Bland Altman plot revealed no obvious systematic bias between the two methods. ATR spectroscopy showed a sensitivity for detection of failure of transfer of passive immunity (FTPI) of 88%, specificity of 100% and accuracy of 94% (with IgG <1000mg/dL as the FTPI cut-off value). Conclusion: ATR spectroscopy in combination with multivariate data analysis shows potential as an alternative approach for rapid quantification of IgG concentrations in bovine serum and the diagnosis of FTPI in calves.
Keywords: Bovine; Failure of transfer of passive immunity; Attenuated total reflectance infrared spectroscopy; Immunoglobulin G

The kinematic and chemical properties of a potential core-forming clump: perseus B1-E - Sadavoy, S.I.; Shirley, Y.; Francesco, J.D.; Henning, T.; Currie, M.J.; André, P.; Pezzuto, S. (The Astrophysical Journal, 2015)
We present 13CO and C18O (1-0), (2-1), and (3-2) maps toward the core-forming Perseus B1-E clump using observations from the James Clerk Maxwell Telescope, the Submillimeter Telescope of the Arizona Radio Observatory, and the IRAM 30 m telescope. We find that the 13CO and C18O line emission both have very complex velocity structures, indicative of multiple velocity components within the ambient gas. The (10) transitions reveal a radial velocity gradient across B1-E of ∼1 km s-1 pc-1 that increases from northwest to southeast, whereas he majority of the Perseus cloud has a radial velocity gradient increasing from southwest to northeast. In contrast, we see no evidence of a velocity gradient associated with the denser Herschel-identified substructures in B1-E. Additionally, the denser substructures have much lower systemic motions than the ambient clump material, which indicates that they are likely decoupled from the large-scale gas. Nevertheless, these substructures themselves have broad line widths (∼0.4 km s-1) similar to that of the C18O gas in the clump, which suggests they inherited their kinematic properties from the larger-scale, moderately dense gas. Finally, we find evidence of C18 O depletion only toward one substructure, B1-E2, which is also the only object with narrow (transonic) line widths. We suggest that as prestellar cores form, their chemical and kinematic properties are linked in evolution, such that these objects must first dissipate their turbulence before they deplete in CO.

The Next Generation Virgo Cluster Survey. IX. Estimating the efficiency of galaxy formation on the lowest-mass scales - Grossauer, J.; Taylor, J. E.; Ferrarese, L.; MacArthur, L. A.; Côté, P.; Roediger, J.; Courteau, S.; Cuillandre, J.-C.; Duc, P.-A.; Durrell, P. R.; Gwyn, S. D. J.; Jordán, A.; et al. (The Astrophysical Journal, 2015)
The Next Generation Virgo Cluster Survey has recently determined the luminosity function of galaxies in the core of the Virgo cluster down to unprecedented magnitude and surface brightness limits. Comparing simulations of cluster formation to the derived central stellar mass function, we attempt to estimate the stellar-to-halo-mass ratio (SHMR) for dwarf galaxies, as it would have been before they fell into the cluster. This approach ignores several details and complications, e.g., the contribution of ongoing star formation to the present-day stellar mass of cluster members, and the effects of adiabatic contraction and/or violent feedback on the subhalo and cluster potentials. The final results are startlingly simple, however; we find that the trends in the SHMR determined previously for bright galaxies appear to extend down in a scale-invariant way to the faintest objects detected in the survey. These results extend measurements of the formation efficiency of field galaxies by two decades in halo mass or five decades in stellar mass, down to some of the least massive dwarf galaxies known, with stellar masses of ∼105 M⊙.

Type I and II Bragg gratings made with infrared femtosecond radiation in high and low alumina content aluminosilicate optical fibers - Grobnic, Dan; Mihailov, Stephen J.; Ballato, John; Dragic, Peter D. (Optica, 2015)
Aluminosilicate fibers have very low Brillouin scattering gain coefficients, making them interesting fibers for nonlinear optical applications. We manufactured Bragg gratings in high (30 mol.%) and low (4 mol.%) alumina content optical fiber using 800 nm femtosecond pulse duration radiation and a phase mask. Grating spectral characteristics and thermal behavior are presented. Index modulations >10−3 were generated for fundamental pitched Bragg gratings, and >10−4 for higher-order gratings. Gratings were annealed at temperatures up to 900°C. Type II gratings written in fibers with lower alumina content showed better thermal stability than gratings written in fibers with higher alumina content. Bragg gratings in these fibers would be well suited as laser cavity mirrors in high-energy laser systems, as well as in telecommunication and sensor systems where Brillouin scattering restricts power scaling.

Raman spectroscopic study of CO2 in hydrate cages - Chen, L.; Lu, H.; Ripmeester, J.A. (Chemical Engineering Science, 2015)
The Raman spectra of CO2 molecules in hydrate cages was studied for structure I CO2 hydrate and structure II tetrahydrofuran (THF)+CO2 binary hydrate. The results obtained for sII hydrate indicated that the Fermi dyad peaks of CO2 in the small cage of THF-CO2 hydrate are located at 1274cm-1 and 1380cm-1. Numerical fitting of the sI CO2 hydrate Raman spectrum shows CO2 Fermi dyad peaks in the small cage are located at 1275cm-1 and 1382cm-1. The unperturbed frequencies of the symmetric stretching v1 and overtone bending v2 modes were calculated for CO2 in various states. It was found that the v1 frequency does not follow the loose cage-tight cage model for CO2 in hydrate cages. Explanations are given as to why such a relationship is not expected in terms of the incomplete sampling of the void space of the non-spherical cages by the linear guest molecule and the contribution of H-bonding to the guest-host interactions.
Keywords: Carbon dioxide; Hydrate; Raman spectra; Fermi resonance

Color-magnitude diagram constraints on the metallicities, ages, and star formation history of the stellar populations in the carina dwarf spheroidal galaxy - Vandenberg, D.A.; Stetson, P.B.; Brown, T.M. (The Astrophysical Journal, 2015)
Victoria-Regina isochrones for -0.4≤ [α/Fe] ≤ +0.4 and a wide range in [Fe/H], along with complementary zero-age horizontal branch (ZAHB) loci, have been applied to the colormagnitude diagram (CMD) of Carina. The color transformations that we have used have been calibrated so that isochrones provide excellent fits to the [(B - V)0 Mv] diagrams of M3 and M92 when well supported estimates of the globular cluster (GC) reddenings and metallicities are assumed. The adopted distance moduli, for both the GCs and Carina, are based on our ZAHB models, which are able to reproduce the old horizontal branch (HB) component (as well as the luminosity of the HB clump) of the dwarf spheroidal galaxy quite welleven if it spans a range in [Fe/H] of ∼1.5 dex, provided that [α/Fe] varies with [Fe/H] in approximately the way that has been derived spectroscopically. Ages derived here agree reasonably well with those found previously for the old and intermediate-age turnoff (TO) stars, as well as for the period of negligible star formation (SF) activity (∼610 Gyr ago). CMD simulations have been carried out for the faintest TO and subgiant stars. They indicate a clear preference for SF that lasted several Gyr instead of a short burst, with some indication that ages decrease with increasing [Fe/H]. In general, stellar models that assume spectroscopic metallicities provide satisfactory fits to the observations, including the thin giant branch of Carina, though higher oxygen abundances than those implied by the adopted values of [α/Fe] would have favorable consequences.
Keywords: galaxies; abundances; dwarf; individual(Carina); stellar content; globular clusters; individual(M3, M92); stars evolution

Accelerated continuous conditional random fields for load forecasting - Guo, H. (IEEE Transactions on Knowledge and Data Engineering, 2015)
Increasingly, aiming to contain their rapidly growing energy expenditures, commercial buildings are equipped to respond to utility's demand and price signals. Such smart energy consumption, however, heavily relies on accurate short-term energy load forecasting, such as hourly predictions for the next n (n≥2) hours. To attain sufficient accuracy for these predictions, it is important to exploit the relationships among the n estimated outputs. This paper treats such multi-steps ahead regression task as a sequence labeling (regression) problem, and adopts the continuous conditional random fields (CCRF) to explicitly model these interconnected outputs. In particular, we improve the CCRF's computation complexity and predictive accuracy with two novel strategies. First, we employ two tridiagonal matrix computation techniques to significantly speed up the CCRF's training and inference. These techniques tackle the cubic computational cost required by the matrix inversion calculations in the training and inference of the CCRF, resulting in linear complexity for these matrix operations. Second, we address the CCRF's weak feature constraint problem with a novel multi-target edge function, thus boosting the CCRF's predictive performance. The proposed multi-target feature is able to convert the relationship of related outputs with continuous values into a set of "sub-relationships", each providing more specific feature constraints for the interplays of the related outputs. We applied the proposed approach to two real-world energy load prediction systems: one for electricity demand and another for gas usage. Our experimental results show that the proposed strategy can meaningfully reduce the predictive error for the two systems, in terms of mean absolute percentage error and root mean square error, when compared with three benchmarking methods. Promisingly, the relative error reduction achieved by our CCRF model was up to 50 percent.
Keywords: Continuous conditional random fields; energy demand forecast; multi-target decision trees; tridiagonal matrix

Determining air pollutant emission rates based on mass balance using airborne measurement data over the Alberta oil sands operations - Gordon, M.; Li, S.-M.; Staebler, R.; Darlington, A.; Hayden, K.; O'Brien, J.; Wolde, M. (Atmospheric Measurement Techniques, 2015)
Top-down approaches to measure total integrated emissions provide verification of bottom-up, temporally resolved, inventory-based estimations. Aircraft-based measurements of air pollutants from sources in the Canadian oil sands were made in support of the Joint Canada-Alberta Implementation Plan for Oil Sands Monitoring during a summer intensive field campaign between 13 August and 7 September 2013. The measurements contribute to knowledge needed in support of the Joint Canada-Alberta Implementation Plan for Oil Sands Monitoring. This paper describes the top-down emission rate retrieval algorithm (TERRA) to determine facility emissions of pollutants, using SO2 and CH4 as examples, based on the aircraft measurements. In this algorithm, the flight path around a facility at multiple heights is mapped to a two-dimensional vertical screen surrounding the facility. The total transport of SO2 and CH4 through this screen is calculated using aircraft wind measurements, and facility emissions are then calculated based on the divergence theorem with estimations of box-top losses, horizontal and vertical turbulent fluxes, surface deposition, and apparent losses due to air densification and chemical reaction. Example calculations for two separate flights are presented. During an upset condition of SO2 emissions on one day, these calculations are within 5 % of the industry-reported, bottom-up measurements. During a return to normal operating conditions, the SO2 emissions are within 11 % of industry-reported, bottom-up measurements. CH4 emissions calculated with the algorithm are relatively constant within the range of uncertainties. Uncertainty of the emission rates is estimated as less than 30 %, which is primarily due to the unknown SO2 and CH4 mixing ratios near the surface below the lowest flight level.

Comprehensive comparison of chemical kinetics mechanisms for syngas/biogas mixtures - Lee, H.C.; Mohamad, A.A.; Jiang, L.Y. (Energy and Fuels, 2015)
The performance of the most commonly used chemical kinetics mechanisms is compared against a large set of experimental data, accumulated for syngas mixtures diluted with other gases such as CO2, H2O, N2, and CH4. These dilutes are pertinent to syngas/biogas mixtures and could have significant effects on the combustion characteristics. The laminar flame speed and ignition delay are used as quantitative metrics to compare the simulation predictions with the experimental data. The experimental data include ignition measurements obtained from shock tubes and rapid compressions, and flame speed measurements obtained from spherical bombs as well as counterflow configurations covering a wide range of temperature, pressure, and equivalence ratios. The mixture compositions are systematically categorized in this study. After exhaustive comparisons, it is found that the NUIG2013 mechanism is in closest agreement with the measured ignition delay and laminar flame speed for the investigated mixtures. However, the predictions deviated significantly from the measured ignition delays for the H2/CO/CO2, H2/CO/CH4, and H2/CO/CH4/CO2/H2O mixtures. We performed a sensitivity analysis on the ignition delay time of the H2/CO/CO2, H2/CO/CH4, and H2/CO/CH4/CO2/H2O mixtures, using the NUIG2013 mechanism to identify the reactions that are responsible for the deviations. We found that by adopting a much lower rate constant expression [k0(CO2) = 8.82 × 1019 × T[K]-1.40 (cm6/mol2/s)] for H + O2 (+CO2) = HO2 (+CO2) (R2), the NUIG2013 mechanism could accurately predict the ignition delay time of the H2/CO/CO2 mixture at low pressures (P = 1.24-2.36 atm) and low temperatures (<1025 K) range. A new rate constant expression [k3 = 2.3 × 108 × T[K]1.40 exp(-2850/T) (cm3/mol/s)] for the CH4 + OH = CH3 + H2O R3 reaction in the NUIG2013 mechanism is required to reconcile the discrepancy observed between the measured and simulated ignition delay time of the H2/CO/CH4 and H2/CO/CH4/CO2/H2O mixtures at P = 32 atm. In addition, the newly fitted rate constant expression for R3 improved the performance of the NUIG2013 mechanism in predicting the ignition delay of H2/CH4 at P = 5, 10, and 20 atm. More importantly, the modifications made to the reactions (R2) and R3 did not substantially affect the NUIG2013 mechanism's excellent predictions of the flame speed. Hence, it is recommended that the rate constant expressions for (R2) and R3 be incorporated into the NUIG2013 mechanism for any study of the combustion characteristics of biogas/syngas mixtures.
Keywords: Combustion; Rate constants; Sensitivity analysis; Shock tubes; Synthesis gas; Chemical kinetics mechanisms; Combustion characteristics; Counterflow configurations; Laminar flame speed; Mixture compositions; Quantitative metrics; Ignition

Measuring academic influence: Not all citations are equal - Zhu, Xiaodan; Turney, Peter; Lemire, Daniel; Vellino, André (Journal of the Association for Information Science and Technology, 2015)
The importance of a research article is routinely measured by counting how many times it has been cited. However, treating all citations with equal weight ignores the wide variety of functions that citations perform. We want to automatically identify the subset of references in a bibliography that have a central academic influence on the citing paper. For this purpose, we examine the effectiveness of a variety of features for determining the academic influence of a citation. By asking authors to identify the key references in their own work, we created a data set in which citations were labeled according to their academic influence. Using automatic feature selection with supervised machine learning, we found a model for predicting academic influence that achieves good performance on this data set using only four features. The best features, among those we evaluated, were those based on the number of times a reference is mentioned in the body of a citing paper. The performance of these features inspired us to design an influence-primed h-index (the hip-index). Unlike the conventional h-index, it weights citations by how many times a reference is mentioned. According to our experiments, the hip-index is a better indicator of researcher performance than the conventional h-index.
Keywords: Artificial intelligence; Indexing (of information); Learning algorithms; Learning systems; Natural language processing systems; Supervised learning; Automatic feature selection; Data set; H indices; NAtural language processing; Supervised machine learning; Education

Triticale straw and its thermoplastic biocomposites - Ngo, Tri-Dung; Ton-That, Minh-Tan; Hu, Wei (Science and Engineering of Composite Materials, 2015)
The potential of triticale straw for the production of green composites based on polypropylene (PP) was evaluated. The composites were prepared by melt compounding of PP and chopped triticale straw (so-called triticale particles) using different formulations and triticale concentrations. The morphology and crystallization of the PP triticale composites were characterized by means of various techniques, including optical microscopy (OM), scanning electron microscopy (SEM), and differential scanning calorimetry (DSC). The composite mechanical performance was also evaluated. The results obtained demonstrate that, by simply adding triticale particles into PP, they play the role of a conventional filler that increases the modulus while reduces the strength. However, the developed formulation with the combination of coupling agent and reactive additive provides superior strength and modulus for the composites; thus, it can upgrade the triticale particles from filler to reinforcement category.
Keywords: Cellulose; Composite materials; Coupling agents; Differential scanning calorimetry; Fillers; Reinforced plastics; Scanning electron microscopy; Thermoplastics; Bio-composites; Green composites; Mechanical performance; Melt-compounding; Morphology and crystallizations; triticale; Triticale straws; Polypropylenes

Flaxseed lignan secoisolariciresinol diglucoside improves insulin sensitivity through upregulation of GLUT4 expression in diet-induced obese mice - Wang, Yanwen; Fofana, Bourlaye; Roy, Moumita; Ghose, Kaushik; Yao, Xing-Hai; Nixon, Marva-Sweeney; Nair, Sandhya; Nyomba, Gregoire B. L. (Journal of Functional Foods, 2015)
The efficacy and mechanism of flaxseed lignan secoisolariciresinol diglucoside (SDG) on glucose hemostasis in obese mice were examined. Male C57BL/6J mice fed on a high-fat diet (60 kcal% fat) for 15 weeks were divided into four groups and treated by oral gavage with 0, 10, 100, or 1000 mg/kg/d of SDG dissolved in water for 6 weeks. Age-matched mice fed with a low-fat diet (10% kcal fat) were used as the normal control. SDG lowered fasting blood glucose, insulin, and free fatty acid levels and improved oral glucose tolerance, insulin response, and homeostatic model assessment-estimated insulin resistance index in mice fed the high-fat diet. Flaxseed SDG also increased GLUT4 expression and tended to increase phosphorylated AKT to total AKT ratio in the muscle tissue. The data demonstrated that flaxseed SDG improved glycaemic control, at least in part, by enhancing insulin signalling and sensitivity in diet-induced obese mice.
Keywords: diet-induced obese mice; flaxseed SDG; fasting blood glucose; glucose tolerance; Insulin tolerance; GLUT4

Effect of different solvent ratio (ethylene glycol/water) on the preparation of Pt/C catalyst and its activity toward oxygen reduction reaction - Wang, Yan-Jie; Zhao, Nana; Fang, Baizeng; Li, Hui; Bi, Xiaotao T.; Wang, Haijiang (RSC Advances, 2015)
Highly dispersed 50 wt% Pt nanoparticles supported on carbon were successfully synthesized via a simple modified polyol method using different solvent volume ratios (ethylene glycol/water). The control of water proportion is found to have an important effect on the physicochemical properties of the in-house synthesized Pt/C catalysts. The structural and electrochemical characterizations reveal that the addition of water not only favors the homogeneous distribution of Pt particles with reduced particle size but also improves the electrocatalytic properties. In particular, at an optimum volume ratio of ethylene glycol to water of 45 : 23 among all studied ratios, the TEM images indicate that the as-synthesized Pt/C catalyst has a minimum particle size of 2.2 ± 0.5 nm, which is close to that of the commercial 46.6 wt% Pt/TKK catalyst, while the electrochemical measurements disclose electrochemical active surface areas and oxygen reduction reaction activity comparable to those of the commercial 46.6 wt% Pt/TKK catalyst. The simplicity of the synthesis process associated with the ease of the filtering step due to the addition of water has significant implications for its practical application in large scale production of Pt/C catalysts for polymer electrolyte membrane fuel cells.
Keywords: Carbon; Catalysts; Electrolytic reduction; Ethylene; Ethylene glycol; Filtration; Fuel cells; Organic solvents; Particle size; Platinum alloys; Polyelectrolytes; Polyols; Proton exchange membrane fuel cells (PEMFC); Reduction; Synthesis (chemical); Electrocatalytic properties; Electrochemical active surface areas; Electrochemical characterizations; Electrochemical measurements; Homogeneous distribution; Large scale productions; Oxygen reduction reaction; Physicochemical property; Catalyst activity

Optimal level of purple acid phosphatase5 is required for maintaining complete resistance to Pseudomonas syringae - Ravichandran, S.; Stone, S.L.; Benkel, B.; Zhang, J.; Berrue, F.; Prithiviraj, B. (Frontiers in Plant Science, 2015)
Plants possess an exceedingly complex innate immune system to defend against most pathogens. However, a relative proportion of the pathogens overcome host's innate immunity and impair plant growth and productivity. We previously showed that mutation in purple acid phosphatase (PAP5) lead to enhanced susceptibility of Arabidopsis to the bacterial pathogen Pseudomonas syringae pv. tomato DC3000 (Pst DC3000). Here, we report that an optimal level of PAP5 is crucial for mounting complete basal resistance. Overexpression of PAP5 impaired ICS1, PR1 expression and salicylic acid (SA) accumulation similar to pap5 knockout mutant plants. Moreover, plant overexpressing PAP5 was impaired in H2O2 accumulation in response to Pst DC3000. PAP5 is localized in to peroxisomes, a known site of generation of reactive oxygen species for activation of defense responses. Taken together, our results demonstrate that optimal levels of PAP5 is required for mounting resistance against Pst DC3000 as both knockout and overexpression of PAP5 lead to compromised basal resistance.
Keywords: purple acid phosphatase5 (PAP5); Pseudomonas syringae pv. tomato DC3000; disease resistance; Arabidopsis; reactive oxygen species (ROS)

Separation of isomeric short-chain acyl-CoAs in plant matrices using ultra-performance liquid chromatography coupled with tandem mass spectrometry - Purves, Randy W.; Ambrose, Stephen J.; Clark, Shawn M.; Stout, Jake M.; Page, Jonathan E. (Journal of chromatography. B, Analytical technologies in the biomedical and life sciences, 2015)
Acyl coenzyme A (acyl-CoA) thioesters are important intermediates in cellular metabolism and being able to distinguish among them is critical to fully understanding metabolic pathways in plants. Although significant advances have been made in the identification and quantification of acyl-CoAs using liquid chromatography tandem mass spectrometry (LC-MS/MS), separation of isomeric species such as isobutyryl- and n-butyrl-CoA has remained elusive. Here we report an ultra-performance liquid chromatography (UPLC)-MS/MS method for quantifying short-chain acyl-CoAs including isomeric species n-butyryl-CoA and isobutyryl-CoA as well as n-valeryl-CoA and isovaleryl-CoA. The method was applied to the analysis of extracts of hop (Humulus lupulus) and provided strong evidence for the existence of an additional structural isomer of valeryl-CoA, 2-methylbutyryl-CoA, as well as an unexpected isomer of hexanoyl-CoA. The results showed differences in the acyl-CoA composition among varieties of Humulus lupulus, both in glandular trichomes and cone tissues. When compared with the analysis of hemp (Cannabis sativa) extracts, the contribution of isobutyryl-CoAs in hop was greater as would be expected based on the downstream polyketide products. Surprisingly, branched chain valeryl-CoAs (isovaleryl-CoA and 2-methylbutyryl-CoA) were the dominant form of valeryl-CoAs in both hop and hemp. The capability to separate these isomeric forms will help to understand biochemical pathways leading to specialized metabolites in plants.
Keywords: acyl coenzyme A; butyryl-coenzyme A; hexanoyl-coenzyme A; isobutyryl-coenzyme A; isovaleryl-coenzyme A; valeryl-coenzyme A; high performance liquid chromatography; isolation and purification; tandem mass spectrometry; Acyl Coenzyme A; Chromatography, High Pressure Liquid; Tandem Mass Spectrometry

A database of narrow-band parameters for fuels commonly encountered in fire applications - Consalvi, J.L.; Liu, F. (Fire Safety Journal, 2015)
The objective of this paper is to derive narrow band (NB) parameters for the Malkmus statistical narrow band model from the medium resolution transmission measurements carried out at NIST (Wakatsuki et al., Proc. Combust. Inst., vol. 31, 2007, pp. 2573-2580) up to about 1000 K for nine fuels commonly encountered in fire applications, namely methane, methanol, ethane, ethylene, propane, propylene, heptane, methyl methacrylate and toluene. These NB parameters can be used to generate a database of NB k-distributions of these fuels in order to apply the k-distribution methods to model their contributions to radiative heat transfer. The accuracy of this NB database, the EM2C NB database for methane (Perrin and Soufiani, JQSRT, vol. 103, 2007, pp. 3-13), and HITRAN 2012 for methane, methanol, ethane, and ethylene is assessed by comparison with the measured medium resolution transmissivities and spectrally-integrated radiative properties. Results show that the EM2C database is the most accurate for methane over the entire range of the temperature and the fuel partial pressure path length considered. The line parameters in HITRAN 2012 are not available for some important bands of methanol, ethane and ethylene and this spectroscopic database cannot be used with confidence above 600 K. The Malkmus narrow band database derived in the present study is found to reproduce spectrally-integrated radiative properties with error less than 20%, which suggests that it can be used for engineering applications. Finally, applications to radiation calculations along lines of sight with methane concentrations and temperatures representative of pool fires show that both the present Malkmus narrow band and the NIST databases can predict accurately the radiative intensity for small scale pool fires where as discrepancies of the order of 30% are expected in the case of methane pool fires with a heat release rate of 176 kW.
Keywords: Fuels; Medium resolution transmission measurements; Malkmus model; Narrow band database; Narrow band k-distributions; Spectroscopic database

Antibody recognition of carbohydrate epitopes - Haji-Ghassemi, O.; Blackler, R.J.; Young, N.M.; Evans, S.V. (Glycobiology, 2015)
Carbohydrate antigens are valuable as components of vaccines for bacterial infectious agents and human immunodeficiency virus (HIV), and for generating immunotherapeutics against cancer. The crystal structures of anti-carbohydrate antibodies in complex with antigen reveal the key features of antigen recognition and provide information that can guide the design of vaccines, particularly synthetic ones. This review summarizes structural features of anti-carbohydrate antibodies to over 20 antigens, based on six categories of glyco-antigen: (i) the glycan shield of HIV glycoproteins; (ii) tumor epitopes; (iii) glycolipids and blood group A antigen; (iv) internal epitopes of bacterial lipopolysaccharides; (v) terminal epitopes on polysaccharides and oligosaccharides, including a group of antibodies to Kdo-containing Chlamydia epitopes; and (vi) linear homopolysaccharides.
Keywords: Anti-carbohydrate antibodies; carbohydrate recognition; Chlamydia; HIV-1 gp120; lipopolysaccharide; monoclonal antibody; X-ray crystal structures

Sentiment, emotion, purpose, and style in electoral tweets - Mohammad, S.M.; Zhu, X.; Kiritchenko, S.; Martin, J. (Information Processing and Management, 2015)
Social media is playing a growing role in elections world-wide. Thus, automatically analyzing electoral tweets has applications in understanding how public sentiment is shaped, tracking public sentiment and polarization with respect to candidates and issues, understanding the impact of tweets from various entities, etc. Here, for the first time, we automatically annotate a set of 2012 US presidential election tweets for a number of attributes pertaining to sentiment, emotion, purpose, and style by crowdsourcing. Overall, more than 100,000 crowdsourced responses were obtained for 13 questions on emotions, style, and purpose. Additionally, we show through an analysis of these annotations that purpose, even though correlated with emotions, is significantly different. Finally, we describe how we developed automatic classifiers, using features from state-of-the-art sentiment analysis systems, to predict emotion and purpose labels, respectively, in new unseen tweets. These experiments establish baseline results for automatic systems on this new data.
Keywords: Sentiment analysis; Tweets; Elections; Emotions; Purpose; Crowdsourcing

Characteristics and engineering performance of C-S-H/aminobenzoic acid composite systems - Khoshnazar, R.; Beaudoin, J.J.; Raki, L.; Alizadeh, R. (Journal of Advanced Concrete Technology, 2015)
Calcium-silicate-hydrate/aminobenzoic acid (C-S-H/ABA) composite systems were synthetized and characterized for the first time. Each of 3- or 4-aminobenzoic acid with a concentration of 0.01 mol. per mol. of Ca was added to the C-S-H preparations during their hydration. The C-S-H/ABA systems were filtered and dried after three weeks. These were, then, characterized by X-ray diffraction, Fourier transform infrared spectroscopy and nitrogen adsorption analysis. Porous bodies were also prepared from C-S-H/ABA compacted powders and used for the length-change and mass-change measurements in different test solutions. In addition, the microindentation technique was used to determine the creep modulus and hardness of the compacted samples. It is suggested that the C-S-H/ABA systems had improved durability and enhanced mechanical properties compared to the phase pure C-S-H reference materials. The influence of the 3- and 4-aminobenzoic acid on durability factors was similar. The C-S-H/3-ABA, however, had superior mechanical performance.
Keywords: Calcium; Durability; Fourier transform infrared spectroscopy; adsorption; Hydration; Powders; Silicates; X ray diffraction; 4-aminobenzoic acid; Micro-indentation technique; Nitrogen

The DAO liquid crystal spectropolarimeter dimaPol - Monin, Dmitry; Bohlender, David; Hardy, Tim; Saddlemyer, Les (Polarimetry: From the Sun to Stars and Stellar Environments, 2015)
The spectropolarimeter dimaPol measures circular polarization in spectral lines of stellar objects. The instrument is used to simultaneously detect polarization signals in the hydrogen Hβ line as well as nearby metallic lines. A fast switching ferro-electric liquid crystal waveplate synchronized with charge shuffling on the CCD is employed to greatly reduce instrumental systematics. dimaPol has been in use on the DAO 1.8-m Plaskett telescope since 2007. In this presentation we show the capabilities of the instrument as well as some of the main results obtained with it to date.
Keywords: polarization; magnetic fields; instrumentation: polarimeters; stars: magnetic fields

Fiber-chip edge coupler with large mode size for silicon photonic wire waveguides - Papes, Martin; Cheben, Pavel; Ye, Winnie N.; Schmid, Jens H.; Xu, Dan-Xia; Janz, Siegfried; Benedikovic, Daniel; Ramos, Carlos A.; Halir, Robert; Ortega-Moñux, Alejandro; Delâge, André; Vašinek, Vladimir (Proceedings of SPIE: The International Society for Optical Engineering, 2015)
Fiber-chip edge couplers are extensively used in integrated optics as one of the key structures for coupling of light between planar waveguide circuits and optical fibers. In this work, a new fiber-chip edge coupler concept with large mode size for coupling to submicrometer silicon photonic wire waveguides is presented. The coupler allows direct coupling to conventional SMF-28 optical fiber and circumvents the need for lensed fibers. We demonstrate by simulations a 95% mode overlap between the mode at the chip facet and a high numerical aperture single mode optical fiber with 6 μm mode field diameter (MFD). We also demonstrate a modified design with 89% overlap between the mode at the chip facet and a standard SMF-28 fiber with 10.4 μm MFD. The coupler is designed for 220 nm silicon-oninsulator (SOI) platform. An important advantage of our coupler is that large mode size is obtained without the need to increase buried oxide (BOX) thickness, which in our design is set to 3 μm. This remarkable feature is achieved by implementing in the SiO2 upper cladding two thin high-index Si3N4 layers. The high-index layers increase the effective refractive index of the upper cladding layer near the facet and are gradually tapered out along the coupler to provide adiabatic mode transformation to the silicon wire waveguide. Simultaneously, the Si-wire waveguide is inversely tapered along the coupler. The mode overlap at the chip facet is studied using a vectorial 2D mode solver and the mode transformation along the coupler is studied by 3D Finite-Difference Time-Domain simulations. The couplers are optimized for operating with transverse electric (TE) polarization and the operating wavelength is centered at 1.55 μm.
Keywords: Finite difference time domain method; Integrated optics; Laser pulses; Multimode fibers; Optical fibers; Optical waveguides; Photonic devices; Refractive index; Silicon on insulator technology; Silicon oxides; Time domain analysis; Waveguides; 3d finite difference time domains; Effective refractive index; High numerical apertures; Mode transformation; Planar waveguide circuit; Silicon wire waveguides; Single-mode optical fiber; Transverse electric polarizations; Optical fiber coupling

Synthesis of CoO/reduced Graphene Oxide composite as an alternative additive for the Nickel electrode in Alkaline secondary batteries - Fu, G.; Chang, K.; Shangguan, E.; Tang, H.; Li, B.; Chang, Z.; Yuan, X.-Z.; Wang, H. (Electrochimica Acta, 2015)
A series of CoO/reduced graphene oxide (CoO/RGO) composites with different proportions are successfully synthesized via a hydrothermal method. As an additive for the nickel-based alkaline secondary battery cathode, the electrochemical performances of the proposed CoO/RGO composite are systematically investigated on its cyclic stability, rate capability, capacity recovery performance, cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS), in comparison with commercial CoO. Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM) images show that the CoO nanoparticles are in-situ anchored on the surface of soft and flexible graphene sheets. Electrochemical results indicate that the CoO/RGO composites exhibite the highest performance when the weight ratio of CoO and RGO is 5:5. The optimized CoO/RGO composites as an additive for the nickel electrode not only can substantially reduce the CoO additive but also possess good electrochemical performances, especially for the high-rate capability. The discharge capacity of the nickel electrode with 5 wt% of CoO/RGO (5:5) addition deliver a high discharge capacity of 284.3, 264.6,235.4 and 208.6 mAh g-1 at 0.2, 1.0, 5.0 and 10.0 C, respectively. The capacity recovery rate at 0.2 C can reach 98.4%. CV and EIS test indicate that the incorporation of RGO can significantly enhance the reversible property, current density of cathodic peak, proton diffusion and conductivity of the nickel electrode. ©2015 Elsevier Ltd. All rights reserved.
Keywords: Alkaline secondary battery; nickel hydroxide electrode; cathode materials; cobalt oxygen additive; reduced graphene oxide

Biotinylation of the Fcγ receptor ectodomains by mammalian cell co-transfection: Application to the development of a surface plasmon resonance-based assay - Dorion-Thibaudeau, July; St-Laurent, Gilles; Raymond, Céline; De Crescenzo, Gregory; Durocher, Yves (Journal of Molecular Recognition, 2015)
We here report the production of four biotinylated Fcγ receptor (FcγR) ectodomains and their subsequent stable capture on streptavidin-biosensor surfaces. For receptor biotinylation, we first describe an in-cell protocol based on the co-transfection of two plasmids corresponding to one of the FcγR ectodomains and the BirA enzyme in mammalian cells. This strategy is compared with a standard sequential in vitro enzymatic biotinylation with respect to biotinylation level and yield. Biotinylated FcγR ectodomains that have been prepared with both strategies are then compared by analytical ultracentrifugation and surface plasmon resonance (SPR) analyses. Overall, we demonstrate that in-cell biotinylation is an interesting alternative to standard biotinylation protocol, as it requires less purification steps while yielding higher titers. Finally, biotin-tagged FcγRs produced with the in-cell approach are successfully applied to the development of SPR-based assays to evaluate the impact of the glycosylation pattern of monoclonal antibodies on their interaction with CD16a and CD64. In that endeavor, we unambiguously observe that highly galactosylated trastuzumab (TZM-gal), non-glycosylated trastuzumab (TZM-NG), and reference trastuzumab are characterized by different kinetic profiles upon binding to CD16a and CD64 that had been captured at the biosensor surface via their biotin tag. More precisely, while TZM-NG binding to CD16a was not detected, TZM-gal formed a more stable complex with CD16a than our reference TZM. In contrast, both glycosylated TZM bound to captured CD64 in a stable and similar fashion, whereas the interaction of their non-glycosylated form with CD64 was characterized by a higher dissociation rate.

A study of the vaginal microbiome in healthy Canadian women utilizing cpn60-based molecular profiling reveals distinct Gardnerella subgroup community state types - Albert, Arianne Y. K.; Chaban, Bonnie; Wagner, Emily C.; Schellenberg, John J.; Links, Matthew G.; Van Schalkwyk, Julie; Reid, Gregor; Hemmingsen, Sean M.; Hill, Janet E.; Money, Deborah (PLoS ONE, 2015)
The vaginal microbiota is important in women's reproductive and overall health. However, the relationships between the structure, function and dynamics of this complex microbial community and health outcomes remain elusive. The objective of this study was to determine the phylogenetic range and abundance of prokaryotes in the vaginal microbiota of healthy, non-pregnant, ethnically diverse, reproductive-aged Canadian women. Sociodemographic, behavioural and clinical data were collected and vaginal swabs were analyzed from 310 women. Detailed profiles of their vaginal microbiomes were generated by pyrosequencing of the chaperonin-60 universal target. Six community state types (CST) were delineated by hierarchical clustering, including three Lactobacillus-dominated CST (L. crispatus, L. iners, L. jensenii), two Gardnerella-dominated (subgroups A and C) and an "intermediate" CST which included a small number of women with microbiomes dominated by seven other species or with no dominant species but minority populations of Streptococcus, Staphylococcus, Peptoniphilus, E. coli and various Proteobacteria in co-dominant communities. The striking correspondence between Nugent score and deep sequencing CST continues to reinforce the basic premise provided by the simpler Gram stain method, while additional analyses reveal detailed cpn60-based phylogeny and estimated abundance in microbial communities from vaginal samples. Ethnicity was the only demographic or clinical characteristic predicting CST, with differences in Asian and White women (p = 0.05). In conclusion, this study confirms previous work describing four cpn60-based subgroups of Gardnerella, revealing previously undescribed CST. The data describe the range of bacterial communities seen in Canadian women presenting with no specific vaginal health concerns, and provides an important baseline for future investigations of clinically important cohorts.
Keywords: bacterium identification; Canadian; controlled study; ethnic difference; female; Gardnerella; Lactobacillus; microbiome; Peptoniphilus; phylogeny; Proteobacteria; pyrosequencing; Staphylococcus; Streptococcus; vagina flora; vagina smear

High performance cutting of advanced aerospace alloys and composite materials - M'Saoubi, R.; Axinte, D.; Soo, S.L.; Nobel, C.; Attia, H.; Kappmeyer, G.; Engin, S.; Sim, W.-M. (CIRP Annals: Manufacturing Technology, 2015)
This paper presents an overview of the recent advances in high performance cutting of aerospace alloys and composite currently used in aeroengine and aerostructure applications. Progress in cutting tool development and its effect on tool wear and surface integrity characteristics of difficult to machine materials such as nickel based alloys, titanium and composites is presented. Further, advances in cutting technologies are discussed, focusing on the role of hybrid machining processes and cooling strategies (MQL, high pressure coolant, cryogenic) on machining performance. Finally, industrial perspectives are provided in the context of machining specific components where future challenges are discussed.
Keywords: Composite materials; Machinability; Aerospace alloys

Solution to the left-handed DNA challenge - Meija, J. (Analytical and Bioanalytical Chemistry, 2015)

Sustainable carbon nanofibers/nanotubes composites from cellulose as electrodes for supercapacitors - Kuzmenko, V.; Naboka, O.; Haque, M.; Staaf, H.; Göransson, G.; Gatenholm, P.; Enoksson, P. (Energy, 2015)
Supercapacitors are efficient energy storage devices with long lifetime and safe service. Their effectiveness, to a big extent, is dependent on electrode materials used for accumulation of energy in form of electrostatic charges. Over the last decades, variety of carbonaceous electrode materials has been used in supercapacitors. Mostly the production of such electrodes is still oriented on unsustainable fossil fuels as precursors instead of sustainable renewable resources. In this study, freestanding carbonaceous electrode materials for supercapacitors were derived from cellulose, the most abundant renewable resource. They were synthesized via carbonization of fibrillar cellulose impregnated with CNTs (carbon nanotubes). The ensuing composite materials consisted of a CNF (carbon nanofiber) scaffold (fiber diameter in the range of 50-250nm) covered with layers of CNTs (tube diameter in the range of 1-20nm). Moreover, these composites were tested as electrode materials for supercapacitors. Incorporation of the CNTs into the CNFs improved electrical conductivity and also increased the surface area of the produced composite materials, which led to high specific capacitance values (up to 241Fg-1), cyclic stability, and power density of these materials in electrochemical measurements. These results suggest that cellulose-derived original CNF/CNT composites are sustainable and efficient carbonaceous electrodes for supercapacitors.
Keywords: Renewable resources; Carbon nanostructures; Energy storage

New fabrication technique for highly sensitive qPlus sensor with well-defined spring constant - Labidi, Hatem; Kupsta, Martin; Huff, Taleana; Salomons, Mark; Vick, Douglas; Taucer, Marco; Pitters, Jason; Wolkow, Robert A. (Ultramicroscopy, 2015)
A new technique for the fabrication of highly sensitive qPlus sensor for atomic force microscopy (AFM) is described. The focused ion beam was used to cut then weld onto a bare quartz tuning fork a sharp micro-tip from an electrochemically etched tungsten wire. The resulting qPlus sensor exhibits high resonance frequency and quality factor allowing increased force gradient sensitivity. Its spring constant can be determined precisely which allows accurate quantitative AFM measurements. The sensor is shown to be very stable and could undergo usual UHV tip cleaning including e-beam and field evaporation as well as in situ STM tip treatment. Preliminary results with STM and AFM atomic resolution imaging at 4.5. K of the silicon Si. (111). -. 7. ×. 7 surface are presented.
Keywords: Chemical sensors; Focused ion beams; Image reconstruction; Quartz; Scanning probe microscopy; Springs (components); AFM; Atomic-resolution imaging; Fabrication technique; Field evaporation; High resonance frequency; Quartz tuning fork; Spring constants; Atomic force microscopy; silicon dioxide; tungsten; atomic force microscopy; electric conductivity; electric field; electrochemistry; evaporation; measurement accuracy; nanotechnology; qPlus sensor; quantitative analysis; sensitivity analysis; sensor; surface property

Interband Bloch oscillation mechanism for high-harmonic generation in semiconductor crystals - McDonald, C. R.; Vampa, G.; Corkum, P. B.; Brabec, T. (Physical Review A: Atomic, Molecular, and Optical Physics, 2015)
High harmonic generation in semiconductors is analyzed for high mid-infrared laser intensities for which the electron-hole pair is driven beyond the first Brillouin zone and exhibits Bloch oscillations. We find that even a two-band analysis exhibits second and higher plateaus. Whereas the first plateau is shown to be consistent with high harmonic generation through electron-hole recollision, the higher plateaus arise from dynamic Bloch oscillations; however, the driving process is interband in nature, in contrast to the generally accepted intraband Bloch oscillation mechanism. Energy conservation is fulfilled, as harmonics beyond the first plateau come from a cascaded nonlinearity.
Keywords: Harmonic analysis; Optical parametric oscillators; Semiconducting indium gallium arsenide; Bloch oscillations; Electron hole; Electron hole pairs; First Brillouin zone; High harmonic generation; Midinfrared lasers; Recollision; Semiconductor crystals; Harmonic generation

"Omics" Insights into PAH degradation toward improved green remediation biotechnologies - El Amrani, Abdelhak; Dumas, Anne-Sophie; Wick, Lukas Y.; Yergeau, Etienne; Berthomé, Richard (Environmental Science and Technology, 2015)
This review summarizes recent knowledge of polycyclic aromatic hydrocarbons (PAHs) biotransformation by microorganisms and plants. Whereas most research has focused on PAH degradation either by plants or microorganisms separately, this review specifically addresses the interactions of plants with their rhizosphere microbial communities. Indeed, plant roots release exudates that contain various nutritional and signaling molecules that influence bacterial and fungal populations. The complex interactions of these populations play a pivotal role in the biodegradation of high-molecular-weight PAHs and other complex molecules. Emerging integrative approaches, such as (meta-) genomics, (meta-) transcriptomics, (meta-) metabolomics, and (meta-) proteomics studies are discussed, emphasizing how "omics" approaches bring new insight into decipher molecular mechanisms of PAH degradation both at the single species and community levels. Such knowledge address new pictures on how organic molecules are cometabolically degraded in a complex ecosystem and should help in setting up novel decontamination strategies based on the rhizosphere interactions between plants and their microbial associates.
Keywords: Aromatic hydrocarbons; Biodegradation; Microbiology; Microorganisms; Molecules; Soils; Complex molecules; High molecular weight; Molecular mechanism; Organic molecules; Polycyclic aromatic hydrocarbons (PAHS); Rhizosphere microbial communities; Signaling molecules; bacterium

Characterizing the atmospheres of the hr8799 planets with HST/WFC3 - Rajan, A.; Barman, T.; Soummer, R.; Hagan, J.B.; Patience, J.; Pueyo, L.; Choquet, É.; Konopacky, Q.; Macintosh, B.; Marois, C. (The Astrophysical Journal Letters, 2015)
We present results from a Hubble Space Telescope (HST) program characterizing the atmospheres of the outer two planets in the HR8799 system. The images were taken over 15 orbits in three near-infrared (near-IR) medium-band filters - F098M, F127M, and F139M - using the Wide Field Camera 3. One of the three filters is sensitive to a water absorption band inaccessible from ground-based observations, providing a unique probe of the thermal emission from the atmospheres of these young giant planets. The observations were taken at 30 different spacecraft rolls to enable angular differential imaging (ADI), and the full data set was analyzed with the Karhunen-Loéve Image Projection routine, an advanced image processing algorithm adapted to work with HST data. To achieve the required high contrast at subarcsecond resolution, we utilized the pointing accuracy of HST in combination with an improved pipeline designed to combine the dithered ADI data with an algorithm designed to both improve the image resolution and accurately measure the photometry. The results include F127M (J) detections of the outer planets, HR8799b and c, and the first detection of HR8799b in the water-band (F139M) filter. The F127M photometry for HR8799c agrees well with fitted atmospheric models, resolving the longstanding difficulty in consistently modeling the near-IR flux of the planet.

A review of cathode materials and structures for rechargeable lithium-air batteries - Ma, Z.; Yuan, X.; Li, L.; Ma, Z.-F.; Wilkinson, D.P.; Zhang, L.; Zhang, J. (Energy and Environmental Science, 2015)
Rechargeable lithium air (Li-air) batteries, especially the non-aqueous type, are considered the most promising energy storage and conversion device candidates for use in future electric vehicle applications due to their ultrahigh energy density. The air cathode has been identified as a key factor affecting the overall performance of Li-air batteries. The current low level performance of air cathodes is the major challenge hindering commercial applications of Li-air batteries. In the past decade, a great many cathode materials, structures and fabrication processes have been developed and investigated with the goal of enhancing cathode performance. This paper reviews, the role of the cathode in non-aqueous Li-air batteries including the cathode reaction mechanisms and the properties and morphologies of cathode materials, followed by approaches to optimize cathode performance. The most recently published global progress and the main achievements in the field of Li-air batteries are also systematically and critically reviewed in terms of cathode materials, structures and fabrication processes, with the objective of providing some state-of-the-art information. Technical challenges are analyzed, and insights into future research directions for overcoming these development challenges of rechargeable non-aqueous Li-air battery cathodes are also identified in this review paper.
Keywords: Amphibious vehicles; Electric batteries; Electrodes; Cathode performance; Energy storage and conversions; Fabrication process; Lithium-air battery; Vehicle applications; electric vehicle; electrokinesis

Development and evaluation of hybrid seat cushions for helicopter aircrew vibration mitigation - Chen, Yong; Wickramasinghe, Viresh; Zimcik, David (Journal of Intelligent Material Systems and Structures, 2015)
This article investigates the use of novel energy-absorbing materials to reduce vibration transmitted through helicopter pilot seat cushions. A type of engineered material known as the hybrid air cushioning system was integrated into the design of helicopter seat cushions in addition to conventional foam materials. The prototype seat cushions were preliminarily evaluated as the bottom seat cushion on a Bell-412 nonarmored pilot seat through mechanical shaker tests. The promising cushion designs were further evaluated on a Bell-412 helicopter through extensive flight tests. The pilot whole-body vibration levels were assessed in accordance with ISO 2631-1:1997 standard. The flight test results demonstrated that the prototype cushions were able to reduce significantly the pilot whole-body vibration. Therefore, the integration of hybrid air cushioning system with Bell-412 seat cushion can serve as a low-cost solution to mitigate the vibration levels transmitted to helicopter pilots.
Keywords: Air cushioning; Aircraft control; Control; Helicopters; Hybrid materials; Optimization; Vibration control; Vibrations (mechanical); Autonomic structures; Energy-absorbing materials; Engineered materials; Helicopter aircrews; ISO 2631-1: 1997; Low-cost solution; Vibration mitigation; Whole body vibration; Aircraft seats

Three birds with one Fe3cO4 nanoparticle: integration of microwave digestion, solid phase extraction, and magnetic separation for sensitive determination of arsenic and antimony in fish - Jia, Y.; Yu, H.; Wu, L.; Hou, X.; Yang, L.; Zheng, C. (Analytical Chemistry, 2015)
An environmentally friendly and fast sample treatment approach that integrates accelerated microwave digestion (MWD), solid phase extraction, and magnetic separation into a single step was developed for the determination of arsenic and antimony in fish samples by using Fe3O4 magnetic nanoparticles (MNPs). Compared to conventional microwave digestion, the consumption of HNO3 was reduced significantly to 12.5%, and the digestion time and temperature were substantially decreased to 6 min and 80 °C, respectively. This is largely attributed to Fe3O4 magnetic nanoparticles being a highly effective catalyst for rapid generation of oxidative radicals from H2O2, as well as an excellent absorber of microwave irradiation. Moreover, potential interferences from sample matrices were eliminated because the As and Sb species adsorbed on the nanoparticles were efficiently separated from the digests with a hand-held magnet prior to analysis. Limits of detection for arsenic and antimony were in the range of 0.01–0.06 μg g–1 and 0.03–0.08 μg g–1 by using hydride generation atomic fluorescence spectrometry, respectively, and further improved to 0.002–0.005 μg g–1 and 0.005–0.01 μg g–1 when inductively coupled plasma mass spectrometry was used as a detector. The precision of replicate measurements (n = 9) was better than 6% by analyzing 0.1 g test sample spiked with 1 μg g–1 arsenic and antimony. The proposed method was validated by analysis of two certified reference materials (DORM-3 and DORM-4) with good recoveries (90%–106%).
Keywords: Antimony; Arsenic; Fish; Fluorescence spectroscopy; Mass spectrometry; Microwave irradiation; Nanomagnetics; Nanoparticles; Phase separation; Certified reference materials; Hydride generation atomic fluorescence spectrometry; Magnetic nano-particles; Magnetic nanoparti cles (MNPs); Microwave digestion (MWD); Potential interferences; Replicate measurements; Solid-phase extraction

Biodegradation of multiple microcystins and cylindrospermopsin in clarifier sludge and a drinking water source: effects of particulate attached bacteria and phycocyanin - Maghsoudi, E.; Fortin, N.; Greer, C.; Duy, S.V.; Fayad, P.; Sauvé, S.; Prévost, M.; Dorner, S. (Ecotoxicology and Environmental Safety, 2015)
The effects of particulate attached bacteria (PAB) and phycocyanin on the simultaneous biodegradation of a mixture of microcystin-LR, YR, LY, LW, LF and cylindrospermopsin (CYN) was assessed in clarifier sludge of a drinking water treatment plant (DWTP) and in a drinking water source. The biomass from lake water and clarifier sludge was able to degrade all microcystins (MCs) at initial concentrations of 10μgL-1 with pseudo-first order reaction half-lives ranging from 2.3 to 8.8 days. CYN was degraded only in the sludge with a biodegradation rate of 1.0×10-1d-1 and a half-life of 6.0 days. This is the first study reporting multiple MCs and CYN biodegradation in the coagulation-flocculation sludge of a DWTP. The removal of PAB from the lake water and the sludge prolonged the lag time substantially, such that no biodegradation of MCLY, LW and LF was observed within 24 days. Biodegradation rates were shown to increase in the presence of C-phycocyanin as a supplementary carbon source for indigenous bacteria, a cyanobacterial product that accompanies cyanotoxins during cyanobacteria blooms. MCs in mixtures degraded more slowly (or not at all) than if they were degraded individually, an important outcome as MCs in the environment are often present in mixtures. The results from this study showed that the majority of the bacterial biomass responsible for the biodegradation of cyanotoxins is associated with particles or biological flocs and there is a potential for extreme accumulation of cyanotoxins within the DWTP during a transient bloom. © 2015 Elsevier Inc.
Keywords: Biodegradation; Microcystin; Cylindrospermopsin; Clarifier sludge; Phycocyanin; Sludge management

Risk assessment of offshore crude oil pipeline failure - Aljaroudi, Alireda; Khan, Faisal; Akinturk, Ayhan; Haddara, Mahmoud; Thodi, Premkumar (Journal of Loss Prevention in the Process Industries, 2015)
Failure of Leak Detection System (LDS) to detect pipeline leakages or ruptures may result in drastic consequences that could lead to excessive financial losses. To minimize the occurrence of such failure, the functionality of the LDS and the integrity of the pipeline should be assessed on a priority basis. This paper presents an integrated risk-based assessment scheme to predict the failure and the failure consequences of offshore crude oil pipelines. To estimate risk, two important quantities have to be determined, the joint probability of failure of the pipeline and its LDS and the consequences of failure. Consequences incorporate the financial losses associated with environmental damage, oil spill cleanup and lost production. The assessment provides an estimate of the risk in monetary value and determines whether the estimated risk exceeds a predefined target risk. Moreover, the critical year for the asset can be determined. In essence, the outcome of the assessment facilitates an informed decision-making about the future of the asset.
Keywords: Chemical detection; Crude oil; Leak detection; Offshore pipelines; Oil spills; Petroleum pipelines; Pipelines; Risk perception; Crude oil pipelines; Environmental damage; Joint probability; Leak detection systems; Pipeline leakage; Probability of failure; Risk-based assessments; Risk assessment

Isothermal oxidation behavior of VC and Columnar structured thermal barrier coatings deposited by suspension plasma spray technology - Li, Xiaolong; Yang, Qi; Huang, Xiao; Tang, Zhaolin (Journal of Thermal Spray Technology, 2015)
The effects of different thermal barrier coating (TBC) top coat structures and substrate alloys on the isothermal oxidation behaviors of TBC systems were investigated at 1080 °C in lab air. The tested TBC systems consisted of two nickel-based superalloy substrates (CMSX-4 and IN738LC), a platinum aluminide bond coat and two 8YSZ top coats (vertical cracked and columnar structured). Samples with IN738LC substrate demonstrated longer isothermal oxidation lives than the counterparts with CMSX-4 substrate. Outward refractory elemental diffusion in coating systems with CMSX-4 substrate and void formation at the interface between thermally grown oxide and bond coat was found to be responsible for the early failure of TBCs. Columnar structured YSZ top coat seemed to provide better protection of the bond coating and substrate, marginally delaying the failure of the both coating systems with IN738LC and CMSX-4.
Keywords: Coatings; Cracks; Diffusion coatings; Interfaces (materials); Isotherms; Oxidation; Plasma jets; Plasma spraying; Substrates; Yttria stabilized zirconia; Zirconia; CMSX-4; columnar; IN738LC; Isothermal oxidations; Suspension plasma sprays; vertically cracked; Thermal barrier coatings

Optical pumping of individual spins in self-assembled and site-controlled quantum dots - Lagoudakis, K.G.; McMahon, P.L.; Fischer, K.; Mueller, K.M.; Sarmiento, T.; Puri, S.; Dalacu, D.; Poole, P.J.; Reimer, M.E.; Zwiller, V.; Yamamoto, Y.; Vuckovic, J. (CLEO: QELS - Fundamental Science, CLEO_QELS 2015, 2015)
We investigate optical spin pumping of self-assembled p-type δ-doped InAs quantum dots as well as site-controlled InP nanowire quantum dots and find that they are both promising for scalable quantum information processing platforms.
Keywords: Nanowires; Optical pumping; Quantum optics; Delta-doped; InAs quantum dots; InP; Optical spins; P-type; Scalable quantum information; Self-assembled; Site-controlled quantum dots; Semiconductor quantum dots

A study of the solid-electrolyte-interface (SEI) of ZnMn2O4: A conversion-type anode material for Li-Ion batteries - Duncan, Hugues; Courtel, Fabrice M.; Abu-Lebdehz, Yaser (Journal of the Electrochemical Society, 2015)
The formation of a stable solid-electrolyte interface, SEI, is very crucial for the successful cycling of anode materials in Li-ion batteries. There is little known about the SEI layer formed at the surface of conversion-type anode materials in general and at the very high capacity ZnMn2O4 spinel anode material. In this work, Li-ion half-cells with ZnMn2O4 electrodes are assembled and tested at different conditions (cycling, temperature and the nature of the electrolyte) and the surface layer is examined by ex situ X-ray Photoelectron Spectroscopy (XPS) in the delithiated state. It is found that the SEI formed at ZnMn2O4 varies with composition but mostly composed of inorganic and organic components, similar to those observed for graphite. However, changes to the C 1s and O 1s spectra with cycling are not significant to correlate the extra reversible capacity to a polymer-like organic origin but rather to the presence of inorganic species such as LiF and LixPFyOz as evidenced by changes in the F 1s, P 2p and Li 1s spectra.
Keywords: Anodes; Electric batteries; Electrodes; Electrolytes; Interfaces (materials); Ions; Lithium; Lithium compounds; Secondary batteries; Seebeck effect; Solid electrolytes; X ray photoelectron spectroscopy; Anode material; High capacity; Organic components; Reversible capacity; Solid electrolyte interfaces; Surface layers; Lithium-ion batteries

Oxygen evolution catalyzed by nickel-iron oxide nanocrystals with a nonequilibrium phase - Bau, J. A.; Luber, E. J.; Buriak, J. M. (ACS Applied Materials and Interfaces, 2015)
Mixed nickel-iron oxides are of great interest as electrocatalysts for the oxygen evolution reaction (OER), the kinetically challenging half-reaction required for the generation of hydrogen gas from water via electrolysis. Previously, we had reported the synthesis of single crystal, soluble nickel-iron oxide nanoparticles over a wide range of nickel:iron compositions, with a metastable cubic rock salt phase ([Ni,Fe]O) that can be isolated despite the low solubility of iron in cubic nickel oxide at ambient temperatures. Here, activity for OER was examined, catalyzed by these [Ni,Fe]O nanoparticles integrated with indium tin oxide (ITO) electrodes. Because the as-prepared [Ni,Fe]O nanoparticles are oleate-capped, the surface ligands needed to be removed to induce adherence to the ITO substrate, and to enable charge transfer and contact with water to enable OER catalysis. Two different approaches were taken to reduce or eliminate the coverage of oleate ligands in these films: UV irradiation (254 nm) and air plasma. UV irradiation proved to lead to better results in terms of stable and OER-active films at pH 13. Kinetic analysis revealed that the Tafel slopes of these nanoparticle [Ni,Fe]O OER electrodes were limited by the electrochemical surface area and were found to be within the range of 30 to 50 mV/decade. Across the four compositions of Ni:Fe studied, from 24:76 to 88:12, the observed overpotential at 10 mA/cm2 for the OER in basic conditions decreased from 0.47 to 0.30 V as the proportion of nickel increased from 24% to 88%.
Keywords: water oxidation; oxygen evolution; nanocrystals; nonequilibrium; nickel oxide; iron oxide; electrolysis

The distance to nova V959 Mon from VLA imaging - Linford, J.D.; Ribeiro, V.A.R.M.; Chomiuk, L.; Nelson, T.; Sokoloski, J.L.; Rupen, M.P.; Mukai, K.; O'Brien, T.J.; Mioduszewski, A.J.; Weston, J. (The Astrophysical Journal, 2015)
Determining reliable distances to classical novae is a challenging but crucial step in deriving their ejected masses and explosion energetics. Here we combine radio expansion measurements from the Karl G. Jansky Very Large Array with velocities derived from optical spectra to estimate an expansion parallax for nova V959 Mon, the first nova discovered through its γ-ray emission. We spatially resolve the nova at frequencies of 4.5-36.5 GHz in nine different imaging epochs. The first five epochs cover the expansion of the ejecta from 2012 October to 2013 January, while the final four epochs span 2014 February-May. These observations correspond to days 126 through 199 and days 615 through 703 after the first detection of the nova. The images clearly show a non-spherical ejecta geometry. Utilizing ejecta velocities derived from three-dimensional modeling of optical spectroscopy, the radio expansion implies a distance between 0.9 ± 0.2 and 2.2 ± 0.4 kpc, with a most probable distance of 1.4 ± 0.4 kpc. This distance implies a γ-ray luminosity of erg s-1, which is much less than the prototype γ-ray-detected nova, V407 Cyg, possibly due to the lack of a red giant companion in the V959 Mon system. V959 Mon also has a much lower γ-ray luminosity than other classical novae detected in γ-rays to date, indicating a range of at least a factor of 10 in the γ-ray luminosities for these explosions.
Keywords: gamma rays; stars; novae, cataclysmic variables; radio continuum; individual (V959 Mon); white dwarfs

Gigahertz dielectric polarization of substitutional single niobium atoms in defective graphitic layers - Zhang, Xuefeng; Guo, Junjie; Guan, Pengfei; Qin, Gaowu; Pennycook, Stephen J. (Physical Review Letters, 2015)
We synthesize two Nb/C composites with an order of magnitude difference in the density of single niobium atoms substituted into defective graphitic layers. The concentration and sites of single Nb atoms are identified using aberration-corrected scanning transmission electron microscopy and density functional theory. Comparing the experimental complex permittivity spectra reveals that a representative dielectric resonance at ∼16GHz originates from the intrinsic polarization of single Nb atom sites, which is confirmed by theoretical simulations. The single-atom dielectric resonance represents the physical limit of the electromagnetic response of condensed matter, and thus might open up a new avenue for designing electromagnetic wave absorption materials. Single-atom resonance also has important implications in understanding the correlation between the macroscopic dielectric behaviors and the atomic-scale structural origin.
Keywords: Atoms; Condensed matter physics; Density functional theory; Dielectric materials; Dielectric resonators; Electromagnetic wave absorption; High resolution transmission electron microscopy; Niobium; Polarization; Resonance; Scanning electron microscopy; Transmission electron microscopy; Aberration-corrected scanning transmission electron microscopies; Complex permittivity; Dielectric behavior; Dielectric polarization; Dielectric resonances; Electromagnetic response; Structural origin; Theoretical simulation; Niobium compounds

Metaproteomics of aquatic microbial communities in a deep and stratified estuary - Colatriano, David; Ramachandran, Arthi; Yergeau, Etienne; Maranger, Roxane; Gélinas, Yves; Walsh, David A. (Proteomics, 2015)
Here we harnessed the power of metaproteomics to assess the metabolic diversity and function of stratified aquatic microbial communities in the deep and expansive Lower St. Lawrence Estuary, located in eastern Canada. Vertical profiling of the microbial communities through the stratified water column revealed differences in metabolic lifestyles and in carbon and nitrogen processing pathways. In productive surface waters, we identified heterotrophic populations involved in the processing of high and low molecular weight organic matter from both terrestrial (e.g. cellulose and xylose) and marine (e.g. organic compatible osmolytes) sources. In the less productive deep waters, chemosynthetic production coupled to nitrification by MG-I Thaumarchaeota and Nitrospina appeared to be a dominant metabolic strategy. Similar to other studies of the coastal ocean, we identified methanol oxidation proteins originating from the common OM43 marine clade. However, we also identified a novel lineage of methanol-oxidizers specifically in the particle-rich bottom (i.e. nepheloid) layer. Membrane transport proteins assigned to the uncultivated MG-II Euryarchaeota were also specifically detected in the nepheloid layer. In total, these results revealed strong vertical structure of microbial taxa and metabolic activities, as well as the presence of specific "nepheloid" taxa that may contribute significantly to coastal ocean nutrient cycling.
Keywords: carrier protein; methanol; nitrogen; organic matter; RNA 16S; bacterial metabolism; estuary; Euryarchaeota; gene sequence; metagenomics; metaproteomics; microbial community; molecular weight; nitrification; Nitrospira; nutrient cycling; oxidation; proteomics; Thaumarchaeota

Critical review of current and emerging quantification methods for the development of influenza vaccine candidates - Manceur, Aziza P.; Kamen, Amine A. (Vaccine, 2015)
Significant improvements in production and purification have been achieved since the first approved influenza vaccines were administered 75 years ago. Global surveillance and fast response have limited the impact of the last pandemic in 2009. In case of another pandemic, vaccines can be generated within three weeks with certain platforms. However, our Achilles heel is at the quantification level. Production of reagents for the quantification of new vaccines using the SRID, the main method formally approved by regulatory bodies, requires two to three months. The impact of such delays can be tragic for vulnerable populations. Therefore, efforts have been directed toward developing alternative quantification methods, which are sensitive, accurate, easy to implement and independent of the availability of specific reagents. The use of newly-developed antibodies against a conserved region of hemagglutinin (HA), a surface protein of influenza, holds great promises as they are able to recognize multiple subtypes of influenza; these new antibodies could be used in immunoassays such as ELISA and slot-blot analysis. HA concentration can also be determined using reversed-phase high performance liquid chromatography (RP-HPLC), which obviates the need for antibodies but still requires a reference standard. The number of viral particles can be evaluated using ion-exchange HPLC and techniques based on flow cytometry principles, but non-viral vesicles have to be taken into account with cellular production platforms. As new production systems are optimized, new quantification methods that are adapted to the type of vaccine produced are required. The nature of these new-generation vaccines might dictate which quantification method to use. In all cases, an alternative method will have to be validated against the current SRID assay. A consensus among the scientific community would have to be reached so that the adoption of new quantification methods would be harmonized between international laboratories.
Keywords: Influenza vaccines quantification; Hemagglutinin; Universal antibodies; SRID assay; Alternative potency assays; Pandemic; Vaccine release; Viral particle count

Infrared vision: visual inspection beyond the visible spectrum - Ibarra-Castanedo, C.; Sfarra, S.; Genest, M.; Maldague, X. (Advances in Computer Vision and Pattern Recognition, 2015)
Infrared (IR) vision for the nondestructive testing (NDT) of materials has considerably grown in the last few years as a results of the continual technological progress and the development of advanced signal processing techniques. Typical applications can be divided into two groups: (1) reflectography/transmittography in the near (NIR) and short-wave (SWIR) infrared spectra, which have been recently applied in the inspection of semitransparent composite materials such as glass, aramid-phenolic, and a variety of natural fibers; and (2) infrared thermography, which involves the detection of surface and subsurface defects based on the differences in thermal signatures in the mid-wave (MWIR) and long-wave (LWIR) infrared bands. Infrared reflectography and thermography have shown interesting complementarities between them as well as with other NDT methods such as ultrasound testing, eddy current testing, and holographic interferometry. In this chapter, a review of classical and recent applications of infrared vision is provided and discussed in detail with examples.

Bipodal benzoylthiocarbamic acid esters: Crystal and molecular structures of R =?Et (a polymorph), and of a binuclear Cu(I) complex, R =?iPr - Nor, Nabihah Al Muna Mohd; Ahmad, Jimmy; Abdullah, Zanariah; Halim, Siti Nadiah Abdul; Otero-de-la-Roza, Alberto; Tiekink, Edward R. T. (Zeitschrift fur Kristallographie - Crystalline Materials, 2015)
The crystal and molecular structure of a second polymorph (P21/n) of [1,4-ROC( = S)N(H)C( = O)C6H4C( = O) N(H)C( = S)OR], R = Et, is shown to have inversion symmetry and to have a more twisted conformation than the previously reported P43212 form which has 2-fold symmetry. Despite utilising equivalent atoms in forming intermolecular interactions, very distinct crystal packing patterns are observed. Crystal characteristics and theory (DFT) are consistent with the P43212 form being more stable, a conclusion correlated with the observation that this form is the overwhelming majority of the sample (PXRD). An analysis of a binuclear copper(I) complex containing the R = iPr analogue, reveals the neutral ligand to bind via the thione-S atom resulting in a distorted ClP2S tetrahedral geometry.

Dispersion effects of high-order-mode fiber on temperature and axial strain discrimination - Xu, Yanping; Lu, Ping; Song, Jia; Chen, Liang; Bao, Xiaoyi; Dong, Xiaopeng (Photonic Sensors, 2015)
A new approach utilizing effects of dispersion in the high-order-mode fibers (HOMFs) to effectively discriminate changes in environmental temperature and axial strain is proposed and experimentally demonstrated. Experimental characterization of a HOMF-based fiber modal interferometer with a sandwich fiber structure exhibits excellent agreements with numerical simulation results. A Fourier transform method of interferometry in the spatial frequency domain is adopted to distinguish mode coupling between different core-guided modes. Distinct phase sensitivities of multiple dispersion peaks are extracted by employing a novel phase demodulation scheme to realize dual-parameter sensing.
Keywords: Dispersion (waves); Fourier series; Frequency domain analysis; Optical fiber communication; Optical fibers; Environmental temperature; Experimental characterization; Fourier transform method; High-order mode fiber; Modal interferometers; Optical fiber sensor; Sandwich fiber structures; Spatial frequency domains; Fibers

Single-nucleotide polymorphism identification and genotyping in Camelina sativa - Singh, Ravinder; Bollina, Venkatesh; Higgins, Erin E.; Clarke, Wayne E.; Eynck, Christina; Sidebottom, Christine; Gugel, Richard; Snowdon, Rod; Parkin, Isobel A. P. (Molecular Breeding, 2015)
Camelina sativa, a largely relict crop, has recently returned to interest due to its potential as an industrial oilseed. Molecular markers are key tools that will allow C. sativa to benefit from modern breeding approaches. Two complementary methodologies, capture of 3′ cDNA tags and genomic reduced-representation libraries, both of which exploited second generation sequencing platforms, were used to develop a low density (768) Illumina GoldenGate single nucleotide polymorphism (SNP) array. The array allowed 533 SNP loci to be genetically mapped in a recombinant inbred population of C. sativa. Alignment of the SNP loci to the C. sativa genome identified the underlying sequenced regions that would delimit potential candidate genes in any mapping project. In addition, the SNP array was used to assess genetic variation among a collection of 175 accessions of C. sativa, identifying two sub-populations, yet low overall gene diversity. The SNP loci will provide useful tools for future crop improvement of C. sativa.
Keywords: Camelina sativa; reduced representation; SNP; Genetic mapping; Diversity; Polyploidy

The marriage of surgical simulation and telementoring for damage-control surgical training of operational first responders : a pilot study - Kirkpatrick, Andrew W.; Tien, Homer; LaPorta, Anthony T.; Lavell, Kit; Keillor, Jocelyn; Wright Beatty, Heather E.; McKee, Jessica Lynn; Brien, Susan; Roberts, Derek J.; Wong, Jonathan; Ball, Chad G.; Beckett, Andrew (Journal of Trauma and Acute Care Surgery, 2015)
BACKGROUND: Hemorrhage is the leading cause of preventable posttraumatic death. Many such deaths may be potentially salvageable with remote damage-control surgical interventions. As recent innovations in information technology enable remote specialist support to point-of-care providers, advanced interventions, such as remote damage-control surgery, may be possible in remote settings. METHODS: An anatomically realistic perfused surgical training mannequin with intrinsic fluid loss measurements (the “Cut Suit”) was used to study perihepatic packing with massive liver hemorrhage. The primary outcome was loss of simulated blood (water) during six stages, namely, incision, retraction, direction, identification, packing, and postpacking. Six fully credentialed surgeons performed the same task as 12 military medical technicians who were randomized to remotely telementored (RTM) (n = 7) or unmentored (UTM) (n=5) real-time guidance by a trauma surgeon. RESULTS: There were no significant differences in fluid loss between the surgeons and the UTM group or between the UTM and RTM groups. However, when comparing the RTM group with the surgeons, there was significantly more total fluid loss (p = 0.001) and greater loss during the identification (p = 0.002), retraction (p = 0.035), direction (p = 0.014), and packing(p = 0.022) stages. There were no significant differences in fluid loss after packing between the groups despite differences in the number of sponges used; RTM group used more sponges than the surgeons and significantly more than the UTM group (p = 0.048). However, mentoring significantly increased self-assessed nonsurgeon procedural confidence (p = 0.004). CONCLUSION: Perihepatic packing of an exsanguinating liver hemorrhage model was readily performed by military medical technicians after a focused briefing. While real-time telementoring did not improve fluid loss, it significantly increased nonsurgeon procedural confidence, which may augment the feasibility of the concept by allowing them to undertake psychologically daunting procedures.This is an open-access article distributed under the terms of the Creative Commons Attribution-NonCommercial-NoDerivatives 3.0 License, where it is permissible to download and share the work provided it is properly cited. The work cannot be changed in any way or used commercially.

Galaxies at the extremes : ultra-diffuse galaxies in the Virgo Cluster - Mihos, J. Christopher; Durrell, Patrick R.; Ferrarese, Laura; Feldmeier, John J.; Côté, Patrick; Peng, Eric W.; Harding, Paul; Liu, Chengze; Gwyn, Stephen; Cuillandre, Jean-Charles (The Astrophysical Journal Letters, 2015)
We report the discovery of three large (R29 ≳ 1′) extremely low surface brightness (LSB; μV,0 ≈ 27.0) galaxies identified using our deep, wide-field imaging of the Virgo Cluster from the Burrell Schmidt telescope. Complementary data from the Next Generation Virgo Cluster Survey do not resolve red giant branch stars in these objects down to i = 24, yielding a lower distance limit of 2.5 Mpc. At the Virgo distance, these objects have halflight radii 3-10 kpc and luminosities LV = 2-9 × 107 L⊙. These galaxies are comparable in size but lower in surface brightness than the large ultradiffuse LSB galaxies recently identified in the Coma cluster, and are located well within Virgo's virial radius; two are projected directly on the cluster core. One object appears to be a nucleated LSB in the process of being tidally stripped to form a new Virgo ultracompact dwarf galaxy. The others show no sign of tidal disruption, despite the fact that such objects should be most vulnerable to tidal destruction in the cluster environment. The relative proximity of Virgo makes these objects amenable to detailed studies of their structural properties and resolved stellar populations. They thus provide an important new window onto the connection between cluster environment and galaxy evolution at the extremes.
Keywords: galaxies: clusters: individual (Virgo); galaxies: evolution; galaxies: fundamental parameters; galaxies: structure

Left-handed DNA challenge - Meija, J. (Analytical and Bioanalytical Chemistry, 2015)
The special feature of Analytical and Bioanalytical Chemistry invites readers to participate in the Analytical Challenge, which deals with left-handed DNA challenge. The Analytical Challenge reveals that the widespread occurrence of left-handed DNA images has its parallels. Representations of sharpened pencil tips or galloping horses are frequently drawn unrealistically. The depictions of left-handed DNA are similar to an upside-down hoisted British flag, as both are widespread and many people never notice that something is missing.
Keywords: Chemical analysis; Spectroscopic analysis; Analytical and bioanalytical chemistry; Analytical challenge; DNA images; Left handed; DNA; Equidae; DNA; chemistry; conformation; medical illustration; DNA; Medical Illustration; Nucleic Acid Conformation

Introduction of soft x-ray spectromicroscopy as an advanced technique for plant biopolymers research - Karunakaran, Chithra; Christensen, Colleen R.; Gaillard, Cedric; Lahlali, Rachid; Blair, Lisa M.; Perumal, Vijayan; Miller, Shea S.; Hitchcock, Adam P. (PLoS ONE, 2015)
Soft X-ray absorption spectroscopy coupled with nano-scale microscopy has been widely used in material science, environmental science, and physical sciences. In this work, the advantages of soft X-ray absorption spectromicroscopy for plant biopolymer research were demonstrated by determining the chemical sensitivity of the technique to identify common plant biopolymers and to map the distributions of biopolymers in plant samples. The chemical sensitivity of soft X-ray spectroscopy to study biopolymers was determined by recording the spectra of common plant biopolymers using soft X-ray and Fourier Transform mid Infrared (FT-IR) spectroscopy techniques. The soft X-ray spectra of lignin, cellulose, and polygalacturonic acid have distinct spectral features. However, there were no distinct differences between cellulose and hemicellulose spectra. Mid infrared spectra of all biopolymers were unique and there were differences between the spectra of water soluble and insoluble xylans. The advantage of nano-scale spatial resolution exploited using soft X-ray spectromicroscopy for plant biopolymer research was demonstrated by mapping plant cell wall biopolymers in a lentil stem section and compared with the FT-IR spectromicroscopy data from the same sample. The soft X-ray spectromicroscopy enables mapping of biopolymers at the sub-cellular (∼30 nm) resolution whereas, the limited spatial resolution in the micron scale range in the FT-IR spectromicroscopy made it difficult to identify the localized distribution of biopolymers. The advantages and limitations of soft X-ray and FT-IR spectromicroscopy techniques for biopolymer research are also discussed.
Keywords: arabinoxylan; biopolymer; cellulose; hemicellulose; lignin; polygalacturonic acid; amino acid substitution; controlled study; image display; infrared spectroscopy; intermethod comparison; lentil; microscopy; phase transition; plant cell; plant stem; process optimization; sensitivity analysis; soft X ray absorption spectromicroscopy; X ray absorption spectroscopy; Lens culinaris

Type-I interband cascade lasers near 3.2μm - Gupta, J.A.; Aers, G.C.; Dupont, E.; Baribeau, J.-M.; Wu, X.; Jiang, Y.; Li, L.; Yang, R.Q.; Johnson, M.B. (CLEO: Science and Innovations, CLEO-SI 2015, 2015)
Interband cascade lasers with type-I InGaAsSb/AlAsSb quantum well active regions were demonstrated. Ridge-waveguide devices exhibit room-temperature continuous-wave emission at 3.2μm, providing a potential alternative to quantum cascade and diode lasers in this wavelength range.

Different studies of the global pitch angle of the Milky Way's spiral arms - Vallée, Jacques P. (Monthly Notices of the Royal Astronomical Society, 2015)
There are many published values for the pitch angle of individual spiral arms, and their wide distribution (from -3° to -28°) begs for various attempts for a single value. Each of four statistical methods used here yields a mean pitch angle in a small range, between -12° and -14° (Table 7, Fig. 2). The final result of our meta-analysis yields a mean global pitch angle in the Milky Way's spiral arms of -13.1° ± 0.6°.
Keywords: methods: statistical; ISM: general; ISM: structure; Galaxy: disc; Galaxy:structure; galaxies: spiral

Synthesis and photochemical properties of PEGylated coumarin-caged ceramides for cell studies - Kim, Y.A.; Day, J.; Lirette, C.A.; Costain, W.J.; Johnston, L.J.; Bittman, R. (Chemistry and Physics of Lipids, 2015)
Caged ceramide analogues (C6-, C16-, C18-, C22- and C24-Cer) have been prepared by introducing a hydrophilic coumarin-based cage bearing a short polyethylene glycol (PEG) chain. (6-Bromo-7-mTEGylated-coumarin-4-yl)methyl (Btc) caged ceramide showed efficient photo-uncaging to release the parent ceramide upon direct exposure to 350. nm UV light; in contrast (7-mTEGylated-coumarin-4-yl)methyl (Tc) caged ceramide was photolysed more slowly. In preliminary experiments, Btc-caged ceramides were taken up by cells and their photolysis led to decreases in cell viability, but not to activation of caspase enzymes, suggesting that either reactive oxygen species or an alternate caspase-independent pathway may be responsible for the decreases in cell viability caused by photolysis of caged ceramides.
Keywords: Ceramide; PEGylated coumarin cages; Photocage; Photolysis

Mass spectrometric analysis of products of metabolic glycan engineering with azido-modification of sialic acids - Bodnar, E.; Raymond, C.; Lopez, P.G.; Villacrés, C.; Butler, M.; Schoenhofen, I.C.; Durocher, Y.; Perreault, H. (Analytical and Bioanalytical Chemistry, 2015)
Metabolic engineering of glycans present on antibodies and other glycoproteins is becoming an interesting research area for improving our understanding of the glycome. With knowledge of the sialic acid biosynthetic pathways, the experiments described in this report are based on a published procedure involving the addition of a synthesized azido-mannosamine sugar into cell culture media and evaluation of downstream expression as azido-sialic acid. This unique bioorthogonal sugar has the potential for a variety of “click chemistry” reactions through the azide linkage, which allow for it to be isolated and quantified given the choice of label. In this report, mass spectrometry was used to investigate and optimize the cellular absorption of peracetylated N-azidoacetylmannosamine (Ac4ManNAz) to form N-azidoacetylneuraminic acid (SiaNAz) in a Chinese hamster ovary (CHO) cell line transiently expressing a double mutant trastuzumab (TZMm2), human galactosyltransferase 1 (GT), and human α-2,6-sialyltransferase (ST6). This in vivo approach is compared to in vitro enzymatic addition SiaNAz onto TZMm2 using soluble β-galactosamide α-2,6-sialyltransferase 1 and CMP-SiaNAz as donor. The in vivo results suggest that for this mAb, concentrations above 100 μM of Ac4ManNAz are necessary to allow for observation of terminal SiaNAz on tryptic peptides of TZMm2 by matrix-assisted laser desorption ionization (MALDI) mass spectrometry. This is further confirmed by a parallel study on the production of EG2-hFc monoclonal antibody (Zhang J et al. Prot Expr Purific 65(1); 77–82, 2009) in the presence of increasing concentrations of Ac4ManNAz.
Keywords: Sialylation; Monoclonal antibodies; Azido-sialic acid; MALDI-ToF-MS; Enzymatic sialylation; Metabolic sialylation

Comparative assessment of next-generation sequencing, denaturing gradient gel electrophoresis, clonal restriction fragment length polymorphism and cloning-sequencing as methods for characterizing commercial microbial consortia - Samarajeewa, A. D.; Hammad, A.; Masson, L.; Khan, I. U. H.; Scroggins, R.; Beaudette, L. A. (Journal of Microbiological Methods, 2015)
Characterization of commercial microbial consortia products for human and environmental health risk assessment is a major challenge for regulatory agencies. As a means to develop an approach to assess the potential environmental risk of these products, research was conducted to compare four genomics methods for characterizing bacterial communities; (i) Denaturing Gradient Gel Electrophoresis (DGGE), (ii) Clonal-Restriction Fragment Length Polymorphism (C/RFLP), (iii) partial 16S rDNA amplification, cloning followed by Sanger sequencing (PRACS) and (iv) Next-Generation Sequencing (NGS) based on Ion Torrent technology. A commercially available microbial consortium, marketed as a remediation agent for degrading petroleum hydrocarbon contamination in soil and water, was assessed. The bacterial composition of the commercial microbial product was characterized using the above four methods. PCR amplification of 16S rDNA was performed targeting the variable region V6 for DGGE, C/RFLP and PRACS and V5 for Ion Torrent sequencing. Ion Torrent technology was shown to be a promising tool for initial screening by detecting the majority of bacteria in the consortium that were also detected by DGGE, C/RFLP and PRACS. Additionally, Ion Torrent sequencing detected some of the bacteria that were claimed to be in the product, while three other methods failed to detect these specific bacteria. However, the relative proportions of the microbial composition detected by Ion Torrent were found to be different from DGGE, C/RFLP and PRACS, which gave comparable results across these three methods. The discrepancy of the Ion Torrent results may be due to the short read length generated by this technique and the targeting of different variable regions on the 16S rRNA gene used in this study. Arcobacter spp. a potential pathogenic bacteria was detected in the product by all methods, which was further confirmed using genus and species-specific PCR, RFLP and DNA-based sequence analyses. However, the viability of Arcobacter spp. was not confirmed. This study suggests that a combination of two or more methods may be required to ascertain the microbial constituents of a commercial microbial consortium reliably and for the presence of potentially human pathogenic contaminants.
Keywords: DNA 16S; hydrocarbon; diagnostic kit; Arcobacter; bacterium detection; controlled study; denaturing gradient gel electrophoresis; DNA sequence; entomopathogenic bacterium; environmental health; gene amplification; intermethod comparison; microbial community; microbial consortium; molecular cloning; polymerase chain reaction; restriction fragment length polymorphism; risk assessment; sequence analysis; soil pollution; water contamination; amplified fragment length polymorphism; bacterium; bioreactor; comparative study; denaturing gradient gel electrophoresis; diagnostic kit; high throughput sequencing; isolation and purification; restriction fragment length polymorphism; Arcobacter; Bacteria (microorganisms); Amplified Fragment Length Polymorphism Analysis; Bacteria; Bioreactors; Denaturing Gradient Gel Electrophoresis; High-Throughput Nucleotide Sequencing; Microbial Consortia; Polymorphism, Restriction Fragment Length; Reagent Kits, Diagnostic; Sequence Analysis, DNA

Predicting energetics of supramolecular systems using the XDM dispersion model - Otero-De-La-Roza, A.; Johnson, Erin R. (Journal of Chemical Theory and Computation, 2015)
In this article, we examine the ability of the exchange-hole dipole moment (XDM) model of dispersion to treat large supramolecular systems. We benchmark several XDM-corrected functionals on the S12L set proposed by Grimme, which comprises large dispersion-bound host-guest systems, for which back-corrected experimental and Quantum Monte Carlo (QMC) reference data are available. PBE-XDM coupled with the relatively economical and efficient pc-2-spd basis set gives excellent statistics (mean absolute error (MAE) = 1.5 kcal/mol), below the deviation between experimental and QMC data. When compared only to the (more accurate) QMC results, PBE-XDM/pc-2-spd (MAE = 1.2 kcal/mol) outperforms all other dispersion-corrected DFT results in the literature, including PBE-dDsC/QZ4P (6.2 kcal/mol), PBE-NL/def2-QZVP (4.7 kcal/mol), PBE-D2/def2-QZVP′ (3.5 kcal/mol), PBE-D3/def2-QZVP′(2.3 kcal/mol), M06-L/def2-QZVP (1.9 kcal/mol), and PBE-MBD (1.8 kcal/mol), with no significant bias (mean error (ME) = 0.04 kcal/mol). PBE-XDM/pc-2-spd gives binding energies relatively close to the complete basis-set limit and does not necessitate the use of counterpoise corrections, which facilitates its use. The dipole-quadrupole and quadrupole-quadrupole pairwise dispersion terms (C8 and C10) are critical for the correct description of the dimers. XDM-corrected functionals different from PBE that work well for small dimers do not yield good accuracy for the large supramolecular systems in the S12L, presenting errors that scale linearly with the dispersion contribution to the binding energy.

A fuzzy decision tree for processing satellite images and landsat data - Al-Obeidat, Feras; Al-Taani, Ahmad T.; Belacel, Nabil; Feltrin, Leo; Banerjee, Neil (Procedia Computer Science, 2015)
Satellite and airborne images, including Landsat, ASTER, and Hyperspectral data, are widely used in remote sensing and Geographic Information Systems (GIS) to understand natural earth related processes, climate change, and anthropogenic activity. The nature of this type of data is usually multi or hyperspectral with individual spectral bands stored in raster file structures of large size and global coverage. The elevated number of bands (on the order of 200 to 250 bands) requires data processing algorithms capable of extracting information content, removing redundancy. Conventional statistical methods have been devised to reduce dimensionality however they lack specific processing to handle data diversity. Hence, in this paper we propose a new data analytic technique to classify these complex multidimensional data cubes. Here, we use a well-known database consisting of multi-spectral values of pixels from satellite images, where the classification is associated with the central pixel in each neighborhood. The goal of our proposed approach is to predict this classification based on the given multi-spectral values. To solve this classification problem, we propose an improved decision tree (DT) algorithm based on a fuzzy approach. More particularly, we introduce a new hybrid classification algorithm that utilizes the conventional decision tree algorithm enhanced with the fuzzy approach. We propose an improved data classification algorithm that utilizes the best of a decision tree and multi-criteria classification. To investigate and evaluate the performance of our proposed method against other DT classifiers, a comparative and analytical study is conducted on well-known Landsat data.
Keywords: Algorithms; Climate change; Complex networks; Data handling; Data mining; Decision trees; Geographic information systems; Image classification; Image processing; Pixels; Remote sensing; Satellites; Trees (mathematics); Anthropogenic activity; Data processing algorithms; Decision-tree algorithm; Fuzzy classification; LANDSAT; Multi-criteria classification; PROAFTN; Satellite images; Classification (of information)

Comparative study on submillimeter flaws in stitched T-joint carbon fiber reinforced polymer by infrared thermography, microcomputed tomography, ultrasonic c-scan and microscopic inspection - Zhang, Hai; Hassler, Ulf; Genest, Marc; Fernandes, Henrique; Robitaille, Francois; Ibarra-Castanedo, Clemente; Joncas, Simon; Maldague, Xavier (Optical Engineering, 2015)
Stitching is used to reduce dry-core (incomplete infusion of T-joint core) and reinforce T-joint structure. However, it may cause new types of flaws, especially submillimeter flaws. Microscopic inspection, ultrasonic c-scan, pulsed thermography, vibrothermography, and laser spot thermography are used to investigate the internal flaws in a stitched T-joint carbon fiber-reinforced polymer (CFRP) matrix composites. Then, a new microlaser line thermography is proposed. Microcomputed tomography (microCT) is used to validate the infrared results. A comparison between microlaser line thermography and microCT is performed. It was concluded that microlaser line thermography can detect the internal submillimeter defects. However, the depth and size of the defects can affect the detection results. The microporosities with a diameter of less than 54 μm are not detected in the microlaser line thermography results. Microlaser line thermography can detect the microporosity (a diameter of 0.162 mm) from a depth of 90 μm. However, it cannot detect the internal microporosity (a diameter of 0.216 mm) from a depth of 0.18 mm. The potential causes are given. Finally, a comparative study is conducted.
Keywords: Carbon fiber reinforced plastics; Computerized tomography; Defects; Fiber reinforced plastics; Microporosity; Nondestructive examination; Polymer matrix composites; Pulsed lasers; Reinforced plastics; Reinforcement; Thermography (imaging); Tomography; Ultrasonic applications; Ultrasonic testing; Carbon fiber reinforced polymer; Laser lines; Laser spot thermographies; Micro computed tomography (micro-CT); Microcomputed tomography; T-joints; Ultrasonic C-scan; X-ray computed tomography; Thermography (temperature measurement)

A haplotype map of allohexaploid wheat reveals distinct patterns of selection on homoeologous genomes - Jordan, K.W.; Wang, S.; Lun, Y.; Gardiner, L.-J.; MacLachlan, R.; Hucl, P.; Wiebe, K.; Wong, D.; Forrest, K.L.; Sharpe, A.G.; Sidebottom, C.H.D.; Hall, N.; et al. (Genome Biology, 2015)
Background: Bread wheat is an allopolyploid species with a large, highly repetitive genome. To investigate the impact of selection on variants distributed among homoeologous wheat genomes and to build a foundation for understanding genotype-phenotype relationships, we performed population-scale re-sequencing of a diverse panel of wheat lines. Results: A sample of 62 diverse lines was re-sequenced using the whole exome capture and genotyping-by-sequencing approaches. We describe the allele frequency, functional significance, and chromosomal distribution of 1.57 million single nucleotide polymorphisms and 161,719 small indels. Our results suggest that duplicated homoeologous genes are under purifying selection. We find contrasting patterns of variation and inter-variant associations among wheat genomes; this, in addition to demographic factors, could be explained by differences in the effect of directional selection on duplicated homoeologs. Only a small fraction of the homoeologous regions harboring selected variants overlapped among the wheat genomes in any given wheat line. These selected regions are enriched for loci associated with agronomic traits detected in genome-wide association studies. Conclusions: Evidence suggests that directional selection in allopolyploids rarely acted on multiple parallel advantageous mutations across homoeologous regions, likely indicating that a fitness benefit could be obtained by a mutation at any one of the homoeologs. Additional advantageous variants in other homoelogs probably either contributed little benefit, or were unavailable in populations subjected to directional selection. We hypothesize that allopolyploidy may have increased the likelihood of beneficial allele recovery by broadening the set of possible selection targets.
Keywords: allele; allopolyploidy; contig mapping; gene; genotype phenotype correlation; haplotype; phylogeny; genetics; polymorphism; wheat; Triticum aestivum

Analytical modelling of Thirty Meter Telescope optics polarization - Anche, Ramya M.; Anupama, G. C.; Reddy, Krishna; Sen, Asoke; Sankarasubramanian, K.; Ramaprakash, A. N.; Sengupta, Sujan; Skidmore, Warren; Atwood, Jenny; Tirupathi, Sivarani; Pandey, Shashi Bhushan (Proceedings of SPIE: The International Society for Optical Engineering, 2015)
The polarization introduced due to Thirty Meter Telescope (TMT) optics is calculated using an analytical model. Mueller matrices are also generated for each optical element using Zemax, based on which the instrumental polarization due to the entire system at the focal plane is estimated and compared with the analytical model. This study is significant in the estimation of the telescope sensitivity and also has great implications for future instruments.
Keywords: Optical telescopes; Photonics; Polarimeters; Polarization; Telescopes; Astronomical polarimetry; Entire system; Focal Plane; Instrumental polarization; Mueller matrix; Thirty Meter Telescope; Analytical models

A subwavelength structured multimode interference coupler for the 3-4 micrometers mid-infrared band - Sánchez-Postigo, Alejandro; Wangüemert-Pérez, Juan Gonzalo; Halir, Robert; Ortega-Moñux, Alejandro; Alonso-Ramos, Carlos A.; Molina-Fernández, Íñigo; Soler Penadés, Jordi; Nedeljkovic, Milos; Mashanovich, Goran Z.; Cheben, Pavel (Proceedings of SPIE: The International Society for Optical Engineering, 2015)
The mid-infrared is attracting increasing attention since many molecules, including potentially hazardous gases such as methane and carbon dioxide, exhibit very specific absorption spectra in this wavelength region. Integrated silicon photonics circuits are envisioned to enable compact and low-cost measurement solutions for these molecules. Multimode interference couplers (MMIs) are basic building blocks for photonic circuits and a broad operational bandwidth is key if flexible operation is to be achieved, e.g. to detect different gases. Here we overcome the bandwidth limitations found in classical MMIs by segmenting the multimode region at a sub-wavelength pitch to engineer its refractive index and dispersion. We achieve less than 0:5 dB imbalance and excess loss in the complete 3 - 4 μm wavelength range. The sub-wavelength MMI not only exhibits nearly threefold improvement in bandwidth, but is also about three times shorter than the conventional device.
Keywords: Bandwidth; Carbon dioxide; Flexible electronics; Infrared devices; Integrated optics; Molecules; Photonics; Refractive index; Waveguide couplers; Basic building block; Low-cost measurements; MIR; MMI; Multimode interference couplers; Operational bandwidth; SWG; Ultra-broadband; Coupled circuits

Diversity and complexity of microbial communities from a chlor-alkali tailings dump - Zappelini, Cyril; Karimi, Battle; Foulon, Julie; Lacercat-Didier, Laurence; Maillard, François; Valot, Benoit; Blaudez, Damien; Cazaux, David; Gilbert, Daniel; Yergeau, Etienne; Greer, Charles; Chalot, Michel (Soil Biology and Biochemistry, 2015)
Revegetation of the tailings dumps produced by various industrial activities is necessary to prevent dust storms and erosion and represents a great challenge for ecological restoration. Little is known about the microbial colonisation and community structure of revegetated tailings following site exploitation. Here, we report the sequencing of 16S rRNA and internal transcribed spacer (ITS) fungal RNA gene amplicons from chlor-alkali residue and from an adjacent undisturbed soil to define the composition and assembly of the rhizosphere microbial communities. After quality filtering, a total of 72,373 and 89,929 bacterial sequences and 122,618 and 111,209 fungal sequences remained for community analysis from undisturbed soil and tailings dump samples, respectively. These reads were affiliated with 45 bacterial and 9 fungal phyla and 113 bacterial and 35 fungal classes. We observed a clear dominance of Gammaproteobacteria at our study site (24% of total sequences), especially of the Pseudomonas genera (72% of Gammaproteobacteria sequences), together with the dominance of a few fungal taxa, such as Hebeloma and Geopora. However, we also noticed that the core microbiome comprised 64.4% and 62.4% of the bacterial and fungal genera, respectively, despite marked differences in soil physico-chemical properties. A heatmap of correlations between soil parameters and taxa confirmed that approximately 50% of the 33 dominant taxa colonised both types of soil. We further demonstrated that the global bacterial-fungal network topology of the dump approximated that of the undisturbed soil. Our approach illuminates the importance of studying more than just a single component of the microbial community and represents a step forward in uncovering the microbial ecology of disturbed environments beyond what is generally found in conventional studies. Our study also provides novel global community proxies that have led us to conclude that environmental filtering is more likely to occur through the activity of tree roots rather than as a result of specific soil characteristics and could be an important force in the assembly of at least some microbial communities.
Keywords: Bacteria; Complex networks; Ecology; Electric network topology; Microorganisms; Revegetation; RNA; Soil conservation; Anthropogenic soils; Bacterial community; Bar coding; Ecological restoration; Fungal community; Internal transcribed spacers; Rhizosphere microbial communities; Soil physico-chemical properties; Bacteria (microorganisms); Gammaproteobacteria; Geopora; Hebeloma; Pseudomonas

Effects of total pressure on non-grey gas radiation transfer in oxy-fuel combustion using the LBL, SNB, SNBCK, WSGG, and FSCK methods - Chu, Huaqiang; Gu, Mingyan; Consalvi, Jean-Louis; Liu, Fengshan; Zhou, Huaichun (Journal of Quantitative Spectroscopy and Radiative Transfer, 2015)
The effects of total pressure on gas radiation heat transfer are investigated in 1D parallel plate geometry containing isothermal and homogeneous media and an inhomogeneous and non-isothermal CO2-H2O mixture under conditions relevant to oxy-fuel combustion using the line-by-line (LBL), statistical narrow-band (SNB), statistical narrow-band correlated-k (SNBCK), weighted-sum-of-grey-gases (WSGG), and full-spectrum correlated-k (FSCK) models. The LBL calculations were conducted using the HITEMP2010 and CDSD-1000 databases and the LBL results serve as the benchmark solution to evaluate the accuracy of the other models. Calculations of the SNB, SNBCK, and FSCK were conducted using both the 1997 EM2C SNB parameters and their recently updated 2012 parameters to investigate how the SNB model parameters affect the results under oxy-fuel combustion conditions at high pressures. The WSGG model considered is the recently developed one by Bordbar et al. [19] for oxy-fuel combustion based on LBL calculations using HITEMP2010. The total pressure considered ranges from 1 up to 30atm. The total pressure significantly affects gas radiation transfer primarily through the increase in molecule number density and only slightly through spectral line broadening. Using the 1997 EM2C SNB model parameters the accuracy of SNB and SNBCK is very good and remains essentially independent of the total pressure. When using the 2012 EM2C SNB model parameters the SNB and SNBCK results are less accurate and their error increases with increasing the total pressure. The WSGG model has the lowest accuracy and the best computational efficiency among the models investigated. The errors of both WSGG and FSCK using the 2012 EM2C SNB model parameters increase when the total pressure is increased from 1 to 10atm, but remain nearly independent of the total pressure beyond 10atm. When using the 1997 EM2C SNB model parameters the accuracy of FSCK only slightly decreases with increasing the total pressure.
Keywords: Combustion; Computational efficiency; Gases; Heat transfer; Ionization of gases; Isotherms; Pressure effects; Radiation effects; Spectroscopy; Benchmark solutions; Gas radiation; Homogeneous media; Line broadening; Line-by-line calculations; Oxyfuel combustion; Parallel plate geometry; Statistical narrow bands; Fuels

Bioorthogonal labelling of living bacteria using unnatural amino acids containing nitrones and a nitrone derivative of vancomycin - MacKenzie, D.A.; Sherratt, A.R.; Chigrinova, M.; Kell, A.J.; Pezacki, J.P. (Chemical Communications, 2015)
Unnatural D-amino acids bearing endocyclic nitrones were developed for live-cell labelling of the bacterial peptidoglycan layer. Metabolic incorporation of D-Lys and D-Ala derivatives bearing different endocyclic nitrones was observed in E. coli, L. innocua, and L. lactis. The incorporated nitrones of these bacteria then rapidly underwent strain-promoted alkyne-nitrone cycloaddition (SPANC) reactions affording chemically modified bacteria.
Keywords: carboxylic acid; dextro amino acid; dimethyl sulfoxide; macrogol; nitrone derivative; vancomycin; bacterial cell wall; cycloaddition; Escherichia coli; fluorescence microscopy; Gram bacterium; Lactococcus lactis; Listeria innocua; protein structure

Enrichment and analysis of intact phosphoproteins in arabidopsis seedlings - Aryal, Uma K.; Ross, Andrew R. S.; Krochko, Joan E. (PLoS ONE, 2015)
Protein phosphorylation regulates diverse cellular functions and plays a key role in the early development of plants. To complement and expand upon previous investigations of protein phosphorylation in Arabidopsis seedlings we used an alternative approach that combines protein extraction under non-denaturing conditions with immobilized metal-ion affinity chromatography (IMAC) enrichment of intact phosphoproteins in Rubisco-depleted extracts, followed by identification using two-dimensional gel electrophoresis (2-DE) and liquid chromatography-tandem mass spectrometry (LC-MS/MS). In-gel trypsin digestion and analysis of selected gel spots identified 144 phosphorylated peptides and residues, of which only18 phosphopeptides and 8 phosphosites were found in the PhosPhAt 4.0 and P3DB Arabidopsis thaliana phosphorylation site databases. More than half of the 82 identified phosphoproteins were involved in carbohydrate metabolism, photosynthesis/respiration or oxidative stress response mechanisms. Enrichment of intact phosphoproteins prior to 2-DE and LC-MS/MS appears to enhance detection of phosphorylated threonine and tyrosine residues compared with methods that utilize peptide-level enrichment, suggesting that the two approaches are somewhat complementary in terms of phosphorylation site coverage. Comparing results for young seedlings with those obtained previously for mature Arabidopsis leaves identified five proteins that are differentially phosphorylated in these tissues, demonstrating the potential of this technique for investigating the dynamics of protein phosphorylation during plant development.
Keywords: phosphoprotein; ribulosebisphosphate carboxylase; threonine; tyrosine; Arabidopsis thaliana; carbohydrate metabolism; immobilized metal affinity chromatography; liquid chromatography; oxidative stress; photosynthesis; plant development; protein phosphorylation; proteomics; seedling; tandem mass spectrometry; two dimensional gel electrophoresis

Room temperature cation exchange reaction in nanocrystals for ultrasensitive speciation analysis of silver ions and silver nanoparticles - Huang, K.; Xu, K.; Tang, J.; Yang, L.; Zhou, J.; Hou, X.; Zheng, C. (Analytical Chemistry, 2015)
To evaluate the toxicity of silver nanoparticles (AgNPs) and Ag+ and gain deep insight into the transformation of AgNPs in the environment or organisms, ultrasensitive analytical methods are needed for their speciation analysis. About 40-fold of Cd2+ in CdTe ionic nanocrystals can be "bombarded-and-exploded" (exchanged) in less than 1 min simply by mixing the nanocrystals with Ag+ solution at room temperature, while this cation exchange reaction did not occur when only silver nanoparticles were present. On the basis of this striking difference, an ultrasensitive method was developed for speciation analysis of Ag+ and AgNPs in complex matrices. The released Cd2+ was reduced to its volatile species by sodium tetrahydroborate, which was separated and swept to an inductively coupled plasma mass spectrometer (ICPMS) or an atomic fluorescence spectrometer (AFS) for the indirect but ultrasensitive detection of Ag+. Owing to the remarkable signal amplification via the cation exchange reaction and the advantages of chemical vapor generation for sampling, the limit of detection was 0.0003 μg L-1 for Ag+ by ICPMS, which was improved by 100-fold compared to the conventional method. Relative standard deviations are better than 2.5% at a concentration of 0.5 μg L-1 Ag+ or AgNPs regardless of the detector. The proposed method retains several unique advantages, including ultrahigh sensitivity, speciation analysis, simplicity and being organic reagent-free, and has been successfully utilized for speciation analysis of Ag+ and AgNPs in environmental water samples and paramecium cells.
Keywords: Cadmium compounds; Chemical analysis; Inductively coupled plasma mass spectrometry; Ion exchange; Mass spectrometers; Nanoparticles; Spectrometers; Atomic fluorescence spectrometers; Cation exchange reactions; Chemical vapor generation; Inductively coupled plasma mass spectrometer; Relative standard deviations; Silver nanoparticles (AgNps); Ultrasensitive detection

Primer and platform effects on 16S rRNA tag sequencing - Tremblay, J.; Singh, K.; Fern, A.; Kirton, E.S.; He, S.; Woyke, T.; Lee, J.; Chen, F.; Dangl, J.L.; Tringe, S.G. (Frontiers in Microbiology, 2015)
Sequencing of 16S rRNA gene tags is a popular method for profiling and comparing microbial communities. The protocols and methods used, however, vary considerably with regard to amplification primers, sequencing primers, sequencing technologies; as well as quality filtering and clustering. How results are affected by these choices, and whether data produced with different protocols can be meaningfully compared, is often unknown. Here we compare results obtained using three different amplification primer sets (targeting V4, V6-V8, and V7-V8) and two sequencing technologies (454 pyrosequencing and Illumina MiSeq) using DNA from a mock community containing a known number of species as well as complex environmental samples whose PCR-independent profiles were estimated using shotgun sequencing. We find that paired-end MiSeq reads produce higher quality data and enabled the use of more aggressive quality control parameters over 454, resulting in a higher retention rate of high quality reads for downstream data analysis. While primer choice considerably influences quantitative abundance estimations, sequencing platform has relatively minor effects when matched primers are used. Beta diversity metrics are surprisingly robust to both primer and sequencing platform biases.
Keywords: 16S rRNA gene sequencing; microbial population and community ecology; high throughput sequencing; microbial diversity; community assembly; amplification; sequencing error

Role of metastable charge states in a quantum-dot spin-qubit readout - Mason, J. D.; Studenikin, S. A.; Kam, A.; Wasilewski, Z. R.; Sachrajda, A. S.; Kycia, J. B. (Physical Review B: Condensed Matter and Materials Physics, 2015)
Readout of a spin qubit in a lateral gate-defined quantum-dot device typically involves a charge detector and a spin-to-charge conversion technique employing spin blockade. We investigate alternative mechanisms for spin-to-charge conversion involving metastable excited charge states made possible by an asymmetry in the tunneling rates to the leads. This technique is used to observe Landau-Zener-Stückelberg oscillations of the S-T+ qubit within the (1,0) ground state region of the charge stability diagram. The oscillations are π phase shifted relative to those detected using the standard technique and display a nonsinusoidal waveform due to the increased relaxation time from the metastable state.

Protective effect of ginsenosides Rg1 and Re on lipopolysaccharide-induced sepsis by competitive binding to toll-like receptor 4 - Su, F.; Xue, Y.; Wang, Y.; Zhang, L.; Chen, W.; Hu, S. (Antimicrobial Agents and Chemotherapy, 2015)
We previously demonstrated that ginsenosides Rg1 and Re enhanced the immune response in C3H/HeB mice but not in C3H/HeJ mice carrying a mutation in the Tlr4 gene. The results of the present study showed that both Rg1 and Re inhibited mRNA expression and production of proinflammatory mediators that included tumor necrosis factor a, interleukin-1β, interleukin-6, cyclooxygenase-2, and inducible nitric oxide synthase from lipopolysaccharide (LPS)-stimulated macrophages. Rg1 was found to be distributed both extracellularly and intracellularly but Re was located only extracellularly to compete with LPS for binding to Toll-like receptor 4. Preinjection of Rg1 and Re into rats suppressed LPS-induced increases in body temperature, white blood cell counts, and levels of serum proinflammatory mediators. Preinjection of Rg1 and Re into mice prevented the LPS-induced decreases in total white blood cell counts and neutrophil counts, inhibited excessive expression of multiple proinflammatory mediators, and successfully rescued 100% of the mice from sepsis-associated death. More significantly, when administered after lethal LPS inoculation, Rg1, but not Re, still showed a potent antisepsis effect and protected 90% of the mice from death. The better protection efficacy of Rg1 could result from its intracellular distribution, suggesting that Rg1 may be an ideal antisepsis agent.
Keywords: cyclooxygenase; ginsenoside Re; inducible nitric oxide synthase; interleukin; lipopolysaccharide; messenger RNA; protective agent; toll like receptor 4; tumor necrosis factor alpha; animal experiment; antisepsis; controlled study; drug; fever; gene; immune response; in vitro study; in vivo study; leukocyte count; macrophage; mouse; neutrophil count; nonhuman

Particle filter-based approach to estimate remaining useful life for predictive maintenance - Yang, Chunsheng; Lou, Qingfeng; Liu, Jie; Gou, Hongyu; Bai, Yun (Current Approaches in Applied Artificial Intelligence : 28th International Conference on Industrial, Engineering and Other Applications of Applied Intelligent Systems, IEA/AIE 2015, Seoul, South Korea, June 10-12, 2015, Proceedings, 2015)
Estimation of remaining useful life (RUL) plays a vital role in performing predictive maintenance for complex systems today. However, it still remains a challenge. To address this issue, we propose a Particle filter (PF)- based method to estimate remaining useful life for predictive maintenance by employing PF technique to update the nonlinear predictive models for forecasting system states. In particular, we applied PF techniques to estimate remaining useful life by integrating data-driven modeling techniques in order to effectively perform predictive maintenance. After introducing the PF-based algorithm, the paper presents the implementation along with the experimental results through a case study of Auxiliary Power Unit (APU) starter prognostics. The results demonstrated that the developed method is useful for estimating RUL for predictive maintenance.
Keywords: Particle Filter (PF); Remaining Useful Life (RUL); Predictive Maintenance (PM); Predictive model; APU starter prognostics

Surface effects on network formation of conjugated polymer wrapped semiconducting single walled carbon nanotubes and thin film transistor performance - Li, Zhao; Ding, Jianfu; Lefebvre, Jacques; Malenfant, Patrick R. L. (Organic Electronics: physics, materials, applications, 2015)
SWCNT network morphology and TFT performance of polyfluorene wrapped sc-SWCNT on different substrates is reported. The polymer/tube weight ratio and concentration impacts network formation and device performance. Hydrophilic SiO2 surfaces show stronger adsorption compared to poly-l-lysine treated SiO2, which leads to more uniform and higher density networks. TFTs with mobility up to 38 cm2/Vs with <10% variability and on/off ratios on the order of 105 were obtained using an iterative dip-coating process.
Keywords: Amino acids; Carbon; Conjugated polymers; Interfaces (materials); Thin film transistors; Thin films; Yarn; Device performance; Different substrates; Dip-coating process; Interface modification; Network formation; Network morphology; Surface effect; Thin-film transistor (TFTs); Single-walled carbon nanotubes (SWCN)

Investigating a signature of temozolomide resistance in GBM cell lines using metabolomics - St-Coeur, Patrick-Denis; Poitras, Julie J.; Cuperlovic-Culf, Miroslava; Touaibia, Mohamed; Morin, Pier J. (Journal of Neuro-Oncology, 2015)
Glioblastoma multiforme (GBM) is the most common form of malignant glioma. Current therapeutic approach to treat this malignancy involves a combination of surgery, radiotherapy and chemotherapy with temozolomide. Numerous mechanisms contributing to inherent and acquired resistance to this chemotherapeutic agent have been identified and can lead to treatment failure. This study undertook a metabolomics-based approach to characterize the metabolic profiles observed in temozolomide-sensitive and temozolomide-resistant GBM cell lines as well as in a small sub-set of primary GBM tumors. This approach was also utilized to explore the metabolic changes modulated upon cell treatment with temozolomide and lomeguatrib, an MGMT inhibitor with temozolomide-sensitizing potential. Metabolites previously explored for their potential role in chemoresistance including glucose, citrate and isocitrate demonstrated elevated levels in temozolomide-resistant GBM cells. In addition, a signature of metabolites comprising alanine, choline, creatine and phosphorylcholine was identified as up-regulated in sensitive GBM cell line across different treatments. These results present the metabolic profiles associated with temozolomide response in selected GBM models and propose interesting leads that could be leveraged for the development of therapeutic or diagnostic tools to impact temozolomide response in GBMs.
Keywords: aconitic acid; adenosine; alanine; arginine; choline; citric acid; creatine; glucose; glutamic acid; glutamine; glutathione; glycerophosphate; histidine; inositol; isocitric acid; isoleucine; leucine; lomeguatrib; methionine; methylated DNA protein cysteine methyltransferase; phosphorylcholine; proline; serine; succinic acid; taurine; temozolomide; threonine; tryptophan; unindexed drug; valine; amino acid metabolism; antineoplastic activity; cancer cell line; cancer resistance; cell viability; citric acid cycle; concentration response; controlled study; cytotoxicity; down regulation; drug sensitivity; enzyme inhibition; genetic transcription; glioblastoma; glioblastoma multiforme cell line; glycolysis; human cell; human tissue; metabolite; metabolomics; primary tumor; upregulation

Dimensional stability of 1. 4nm tobermorite, jennite and other layered calcium silicate hydrates - Pourbeik, P.; Beaudoin, J.J.; Alizadeh, R.; Raki, L. (Advances in Cement Research, 2015)
Length-change measurements of 1·4 nm tobermorite, jennite and calcium silicate hydrate preparations (with varying calcium/silicon ratio) subjected to drying from the 11% relative humidity condition are reported. The dimensional stability investigation is focused on the role of adsorbed and interlayer water as shrinkage mechanisms involving menisci effects in capillary pores are eliminated in this humidity range. Length change against mass loss curves and the corresponding d002 basal spacing change (obtained by X-ray diffraction) with mass loss are assessed and inferences drawn regarding nanostructural models for calcium silicate hydrates in hydrated Portland cement paste. Length changes of the pure phases were significantly greater than those for hydrated cement paste due to the restraining effect of unhydrated cement particles and calcium hydroxide crystals in the paste. The dimensional stability and the role of the removal of ‘structural water' from the systems studied are discussed in terms of its relevance to cement-based materials.
Keywords: Additives; Calcium; Cements; Dimensional stability; Hydration; Portland cement; Silicate minerals; Silicates; X ray diffraction; Calcium silicate hydrate; Cement based material; Humidity conditions; Hydrated cement pastes; Interlayer waters; Portland cement paste; Shrinkage mechanisms; Structural water; Calcium silicate

Communication: Spectroscopic observation of the O-bonded T-shaped isomer of the CO-CO₂ dimer and two of its intermolecular frequencies - Sheybani-Deloui, S.; Barclay, A. J.; Michaelian, K. H.; McKellar, A. R. W.; Moazzen-Ahmadi, N. (Journal of Chemical Physics, 2015)
Infrared spectra in the carbon monoxide CO stretch region (≈2150 cm-1) are assigned to the previously unobserved O-bonded form of the CO2-CO dimer ("isomer 2"), which has a planar T-shaped structure like that of the previously observed C-bonded form ("isomer 1"), but with the CO rotated by 180°. The effective center of mass intermolecular distances are 3.58 Å for isomer 2 as compared to 3.91 Å for isomer 1. In addition to the fundamental band, two combination bands are observed for isomer 2, yielding values for two intermolecular vibrational modes: 14.19 cm-1 for the in-plane CO bend and 22.68 cm-1 for the out-of-plane bend.
Keywords: Carbon; Carbon monoxide; Center of mass; Combination bands; Fundamental bands; Infrared spectrum; Intermolecular distance; Intermolecular vibrational modes; Out-of plane; Shaped structures; Isomers

Assessment of the hemodynamic profile in periodontal tissues of diabetic subjects with periodontitis by optical spectroscopy - Duarte, P. M.; Sowa, M. G.; Xiang, X.; Zhang, C.; Santos, V. R.; Miranda, T. S.; Reis, A. F.; Liu, K. -Z. (Journal of Periodontal Research, 2015)
Background and Objective: The influence of diabetes mellitus (DM) on the hemodynamics of periodontal tissues has not been assessed previously. The primary objective of this study was to validate optical spectroscopy as a periodontal diagnostic tool for subjects with type 2 DM and chronic periodontitis. Material and Methods: Using a portable optical near-infrared spectrometer, optical spectra were obtained from healthy (n = 127), gingivitis (n = 115), and periodontitis (n = 109) sites of 65 subjects with type 2 DM and chronic periodontitis. Healthy (n = 65) sites of 15 nondiabetic subjects without periodontitis were used as controls. A modified Beer-Lambert unmixing model that incorporates a nonparametric scattering-loss function was used to determine the relative contribution of deoxygenated hemoglobin and oxygenated hemoglobin (HbO2) to the overall spectrum. The balance between tissue oxygen delivery and oxygen utilization in periodontal tissues was assessed. Results: In diabetic subjects, tissue oxygen saturation and HbO2 concentration were significantly decreased in the periodontitis sites (p < 0.01) compared with the healthy and gingivitis sites. Furthermore, tissue oxygenation in healthy sites of control subjects was significantly higher than that in sites of diabetic subjects (p < 0.01). Conclusion: In summary, the results of this study suggest that optical spectroscopy can monitor the hemodynamic profile in diabetic subjects with chronic periodontitis. Furthermore, healthy sites of diabetic subjects presented lower tissue oxygenation than did those of nondiabetic subjects.

VEGAS: a VST early-type galaxy survey: I. Presentation, wide-field surface photometry, and substructures in NGC 4472 - Capaccioli, M.; Spavone, M.; Grado, A.; Iodice, E.; Limatola, L.; Napolitano, N.R.; Cantiello, M.; Paolillo, M.; Romanowsky, A.J.; Forbes, D.A.; Puzia, T.H.; Raimondo, G.; et al. (Astronomy and Astrophysics, 2015)
We present the VST Early-type GAlaxy Survey (VEGAS), which is designed to obtain deep multiband photometry in g,r,i, of about one hundred nearby galaxies down to 27.3, 26.8, and 26 mag/arcsec2 respectively, using the ESO facility VST/OmegaCAM. Aims. The goals of the survey are 1) to map the light distribution up to ten effective radii, re; 2) to trace color gradients and surface brightness fluctuation gradients out to a few re for stellar population characterization; and 3) to obtain a full census of the satellite systems (globular clusters and dwarf galaxies) out to 20% of the galaxy virial radius. The external regions of galaxies retain signatures of the formation and evolution mechanisms that shaped them, and the study of nearby objects enables a detailed analysis of their morphology and interaction features. To clarify the complex variety of formation mechanisms of early-type galaxies (ETGs), wide and deep photometry is the primary observational step, which at the moment has been pursued with only a few dedicated programs. The VEGAS survey has been designated to provide these data for a volume-limited sample with exceptional image quality. Methods. In this commissioning photometric paper we illustrate the capabilities of the survey using g-and i-band VST/OmegaCAM images of the nearby galaxy NGC 4472 and of smaller ETGs in the surrounding field. Results. Our surface brightness profiles reach rather faint levels and agree excellently well with previous literature. Genuine new results concern the detection of an intracluster light tail in NGC 4472 and of various substructures at increasing scales. We have also produced extended (g-i) color profiles. Conclusions. The VST/OmegaCAM data that we acquire in the context of the VEGAS survey provide a detailed view of substructures in the optical emission from extended galaxies, which can be as faint as a hundred times below the sky level.
Keywords: Gravitation; Luminance; Optical data processing; Photometry; Surveys; cD; Galaxies: elliptical and lenticular; Galaxies: formation; Galaxies: fundamental parameters; Techniques: image processing

In vivo and in vitro evidence for biochemical coupling of reactions catalyzed by lysophosphatidylcholine acyltransferase and diacylglycerol acyltransferase - Pan, X.; Chen, G.; Kazachkov, M.; Greer, M.S.; Caldo, K.M.P.; Zou, J.; Weselake, R.J. (Journal of Biological Chemistry, 2015)
Seed oils of flax (Linum usitatissimum L.) and many other plant species contain substantial amounts of polyunsaturated fatty acids (PUFAs). Phosphatidylcholine (PC) is the major site for PUFA synthesis. The exact mechanisms of how these PUFAs are channeled from PC into triacylglycerol (TAG) needs to be further explored. By using in vivo and in vitro approaches, we demonstrated that the PC deacylation reaction catalyzed by the reverse action of acyl-CoA:lysophosphatidylcholine acyltransferase (LPCAT) can transfer PUFAs on PC directly into the acyl-CoA pool, making these PUFAs available for the diacylglycerol acyltransferase (DGAT)-catalyzed reaction for TAG production. Two types of yeast mutants were generated for in vivo and in vitro experiments, respectively. Both mutants provide a null background with no endogenous TAG forming capacity and an extremely low LPCAT activity. In vivo experiments showed that co-expressing flax DGAT1-1 and LPCAT1 in the yeast quintuple mutant significantly increased 18-carbon PUFAs in TAG with a concomitant decrease of 18-carbon PUFAs in phospholipid. We further showed that after incubation of sn-2-[14C]acyl-PC, formation of [14C]TAG was only possible with yeast microsomes containing both LPCAT1 and DGAT1-1. Moreover, the specific activity of overall LPCAT1 and DGAT1-1 coupling process exhibited a preference for transferring 14C-labeled linoleoyl or linolenoyl than oleoyl moieties from the sn-2 position of PC to TAG. Together, our data support the hypothesis of biochemical coupling of the LPCAT1-catalyzed reverse reaction with the DGAT1-1-catalyzed reaction for incorporating PUFAs into TAG. This process represents a potential route for enriching TAG in PUFA content during seed development in flax.
Keywords: Fatty acids; Flax; Glycerol; Linen; Lipids; Oilseeds; Phospholipids; Seed; embryo

Novalike cataclysmic variables are significant radio emitters - Coppejans, Deanne L.; Körding, Elmar G.; Miller-Jones, James C. A.; Rupen, Michael P.; Knigge, Christian; Sivakoff, Gregory R.; Groot, Paul J. (Monthly Notices of the Royal Astronomical Society, 2015)
Radio emission from non-magnetic cataclysmic variables (CVs, accreting white dwarfs) could allow detailed studies of outflows and possibly accretion flows in these nearby, numerous and non-relativistic compact accretors. Up to now, however, very few CVs have been detected in the radio. We have conducted a Very Large Array pilot survey of four close and optically bright novalike CVs at 6 GHz, detecting three, and thereby doubling the number of radio detections of these systems. TT Ari, RW Sex and the old nova V603 Aql were detected in both of the epochs, while V1084 Her was not detected (to a 3σ upper limit of 7.8 μJy beam-1). These observations clearly show that the sensitivity of previous surveys was typically too low to detect these objects and that non-magnetic CVs can indeed be significant radio emitters. The three detected sources show a range of properties, including flaring and variability on both short (~200 s) and longer term (days) time-scales, as well as circular polarization levels of up to 100 per cent. The spectral indices range from steep to inverted; TT Ari shows a spectral turnover at ~6.5 GHz, while the spectral index of V603 Aql flattened from α = 0.54 ± 0.05 to 0.16±0.08 (Fν ∞ να) in the week between observations. This range of properties suggests that more than one emission process can be responsible for the radio emission in non-magnetic CVs. In this sample we find that individual systems are consistent with optically thick synchrotron emission, gyrosynchrotron emission or cyclotron maser emission.
Keywords: accretion; accretion discs; radiation mechanisms; novae; cataclysmic variables; white dwarfs; stars: winds, outflows; radio continuum

Data mining-based methods for fault isolation with validated FMEA model ranking - Yang, C.; Zou, Y.; Lai, P.; Jiang, N. (Applied Intelligence, 2015)
FMEA (Failure Mode and Effects Analysis), which was developed to enhance the reliability of complex systems, is a standard method to characterize and document product and process problems and a systematic method for fault identification/isolation in maintenance. When a failure is predicted or detected, it is expected to identify which component is the root cause or to isolate the fault to a specific contributing component. To efficiently perform fault isolation, we proposed data mining-based methods for fault isolation by using the validated FMEA information to rank data-driven models. However, FMEA, as a standard document, is produced during the design of products or systems. Therefore, FMEA documentation is rarely validated or updated in practice after it was generated. In order to use reliable FMEA information to rank models for fault isolation, it is necessary to validate FMEA before using it. In this paper, we first present brief overview of FMEA validation. Then we introduce the proposed data mining based method for fault isolation. Finally we apply the proposed methods to Auxiliary Power Unit (APU) fault isolation for a given failure mode, “Inability to Start”, by conducting large-scale experiments. The experimental results obtained from a case study demonstrate the usefulness and feasibility of the proposed methods for fault isolation.
Keywords: FMEA; Data mining; Data driven models; Binary classifier; Model ranking; Fault isolation; Failure mode; FMEA validation

The 5:1 neptune resonance as probed by CFEPS: dynamics and population - Pike, R.E.; Kavelaars, J.J.; Petit, J.M.; Gladman, B.J.; Alexandersen, M.; Volk, K.; Shankman, C.J. (Astronomical Journal, 2015)
The Canada-France Ecliptic Plane Survey discovered four trans-Neptunian objects with semimajor axes near the 5:1 resonance, revealing a large and previously undetected intrinsic population. Three of these objects are currently resonant with Neptune, and the fourth is consistent with being an object that escaped the resonance at some point in the past. The non-resonant object may be representative of a detached population that is stable at slightly lower semimajor axes than the 5:1 resonance. We generated clones of these objects by resampling the astrometric uncertainty and examined their behavior over a 4.5 Gyr numerical simulation. The majority of the clones of the three resonant objects (>90%) spend a total of 107 years in resonance during their 4.5 Gyr integrations; most clones experience multiple periods of resonance capture. Our dynamical integrations reveal an exchange between the 5:1 resonance, the scattering objects, and other large semimajor axis resonances, especially the 4:1, 6:1, and 7:1 resonances. The multiple capture events and relatively short resonance lifetimes after capture suggest that these objects are captured scattering objects that stick in the 5:1 resonance. These 5:1 resonators may be representative of a temporary population, requiring regular contributions from a source population. We examined the dynamical characteristics (inclination, eccentricity, resonant island, libration amplitude) of the detected objects and their clones in order to provide an empirical model of the orbit structure of the 5:1 resonance. This resonance is dynamically hot and includes primarily symmetric librators. Given our orbit model, the intrinsic population necessary for the detection of these three objects in the 5:1 resonance is 1900-1400+3300 (95% confidence) objects with Hg < 8 and e > 0.5.
Keywords: Kuiper belt objects: individual (2003 YQ179, 2007 FN51, 2007 LF38, 2008 JO, L3y02, HL7c1, HL7j4, HL8k1)

Damage formation on fused silica illuminated with ultraviolet-infrared femtosecond pulse pairs - Yu, Xiaoming; Chang, Zenghu; Corkum, Paul B.; Lei, Shuting (Proceedings of SPIE: The International Society for Optical Engineering, 2015)
We investigate damage formation on the surface of fused silica by two femtosecond laser pulses, a tightly focused 266 nm (UV) pulse followed by a loosely focused 800 nm (IR) pulse. We show that the damage size is determined by the UV pulse, and only a small fraction of the normal UV damage threshold energy is needed to cause damage when combined with the properly delayed IR pulse. Our results, analyzed with a rate equation model, suggest that the UV pulse generates seed electrons through multiphoton absorption and the IR pulse utilizes these electrons to cause damage by avalanche ionization. By tuning such parameters like pulse energy, time delay, IR pulse duration and polarization, we further demonstrate that damage profile can be controlled.
Keywords: Electromagnetic pulse; Fused silica; Ionization; Laser pulses; Multiphoton processes; Photoionization; Time delay; Ultrafast lasers; Ultrashort pulses; X ray optics; Avalanche ionization; Damage formation; Femtosecond laser machining; Multi-photon absorption; Multiphoton ionization; Pulse durations; Rate-equation models; UV pulse; Pulse generators

High-resolution synchrotron infrared spectroscopy of acrolein: The vibrational levels between 850 and 1020 cm-1 - McKellar, A. R. W.; Billinghurst, B. E.; Xu, Li-Hong; Lees, R. M. (Journal of Molecular Spectroscopy, 2015)
Using spectra obtained at the Canadian Light Source synchrotron radiation facility, a previously unobserved out-of-plane vibration of trans-acrolein (propenal) is reliably assigned for the first time. Its origin is at 1002.01 cm-1, which is about 20 cm-1 higher than usually quoted in the past. This mode is thus labelled as v14, leaving the label v15 for the known vibration at 992.66 cm-1. Weak combination bands 171182 ← 182, 171131 ← 131, 121182 ← 181, and 171182 ← 181 are studied for the first time, and assignments in the known v11, v16, and v15 fundamental bands are also extended. The seven excited vibrations involved in these bands are analyzed, together with five more unobserved vibrations in the same region (850-1020 cm-1), in a large 12-state simultaneous fit which accounts for most of the many observed perturbations in the spectra.
Keywords: Aldehydes; Herbicides; Infrared radiation; Infrared spectroscopy; Light sources; Synchrotron radiation; Synchrotrons; Acrolein; Coriolis; Excited vibrations; Fundamental bands; Out-of-plane vibrations; Perturbation; Synchrotron radiation facility; Vibrational levels; Vibration analysis

ALMA observations of the largest proto-planetary disk in the Orion Nebula, 114-426: a co silhouette - Bally, J.; Mann, R.K.; Eisner, J.; Andrews, S.M.; Francesco, J.D.; Hughes, M.; Johnstone, D.; Matthews, B.; Ricci, L.; Williams, J.P. (The Astrophysical Journal, 2015)
We present ALMA observations of the largest protoplanetary disk in the Orion Nebula, 114-426. Detectable 345 GHz (856 μm) dust continuum is produced only in the 350 AU central region of the ∼1000 AU diameter silhouette seen against the bright background in Hubble Space Telescope images. Assuming optically thin dust emission at 345 GHz, a gas-to-dust ratio of 100, and a grain temperature of 20 K, the disk gas-mass is estimated to be Jupiter masses. If most solids and ices have been incorporated into large grains, however, this value is a lower limit. The disk is not detected in dense-gas tracers such as HCO+ J = 4-3, HCN J = 4-3, or CS = 7-6. These results may indicate that the 114-426 disk is evolved and depleted in some light organic compounds found in molecular clouds. The CO J = 3-2 line is seen in absorption against the bright 50-80 K background of the Orion A molecular cloud over the full spatial extent and a little beyond the dust continuum emission. The CO absorption reaches a depth of 27 K below the background CO emission at VLSR 6.7 km s ∼ 0.″52 (210 AU) northeast and 12 K below the background CO emission at VLSR ≈ 9.7 km s ∼ 0.″34 (140 AU) southwest of the suspected location of the central star, implying that the embedded star has a mass less than 1 M⊙.

Effects of stratification on locally lean, near-stoichiometric, and rich iso-octane/air turbulent V-flames - Vena, P.C.; Deschamps, B.; Guo, H.; Johnson, M.R. (Combustion and Flame, 2015)
The effects of partial premixing on locally rich, near-stoichiometric, and lean flame regions were investigated in stratified, iso-octane/air turbulent V-flames by varying the mean equivalence ratio gradient along the exit plane of a rectangular slot burner. Instantaneous heat release rate (HRR) images were obtained from the product of spatially registered, near-simultaneously acquired OH and CH2O planar laser induced fluorescence (PLIF) images. HRR data were analyzed within a region of interest (ROI) that was determined from separate 3-pentanone tracer PLIF measurements. The ROI was unique to each gradient flame setting, and was configured to ensure the mean range of equivalence ratios being analyzed was constant among gradient conditions. This allowed distinction of the effects of mean equivalence ratio gradient at the flame front from effects associated with having different ranges of equivalence ratios within the flame zone.Individual flame realizations were studied for differences in the local peak HRR and instantaneous flame thickness δt as they varied with curvature among gradient conditions. While general trends for the fully-premixed cases were consistent with Lewis number theory, subtle changes in the normalized distribution of local peak HRR vs. curvature were observed for locally rich and locally lean flames propagating in different mean ϕ gradients. Negligible changes were observed for near-stoichiometric flames, suggesting that gradient effects may influence the local thermodiffusive stability of off-stoichiometric mixtures more significantly.Ensemble averages of individual peak HRR and δt values within each ROI were separately evaluated, and differences among gradient conditions were greater than those observed for the normalized distributions with curvature. For all flame settings considered, an increase in either of the peak HRR or δt led to a decrease in the other. Gradient effects were observed when comparing back- and front-supported locally rich flames, which experienced opposite changes in peak HRR of +10.1% and -5.2% for gradient settings ∂ϕ/∂y=-0.014mm-1 and ∂ϕ/∂y=0.012mm-1 respectively, coupled with a thinning and thickening of δt of -7.2% and +2.4%. Similar but weaker trends were observed for near-stoichiometric flame regions, with a decrease in peak HRR of up to -3.5% and a thickening up to +2.8% for the steepest gradient ∂ϕ/∂y=0.029mm-1. Locally lean flames showed small increases in peak HRR of up to +3.8%, and decreases in δt of up to -2.1% for back-supported gradient case ∂ϕ/∂y=0.024mm-1, however, variations were not as significant as those observed for back-supported rich flame regions of equivalent gradients. The presented results show that mean gradients of equivalence ratio can alter the local characteristics of partially premixed flames. Through subtle differences in the local distribution of peak HRR with curvature, more pronounced variations in the magnitude of the mean local peak HRR and δt, and opposing effects in both peak HRR and δt for back- and front-supported rich flames, the data reveal the specific influence of equivalence ratio gradients in experiments where the mean range of equivalence ratios in the analysis region is fixed.
Keywords: Stratified combustion; Partially premixed; Heat release rate; Turbulent combustion; V-flame; Equivalence ratio gradient; Back-support

(Ag,Cu)-Ta-O ternaries as high-temperature solid-lubricant coatings - Gao, Hongyu; Otero-de-la-Roza, Alberto; Gu, Jingjing; Stone, D’Arcy; Aouadi, Samir M.; Johnson, Erin R.; Martini, Ashlie (ACS Applied Materials and Interfaces, 2015)
Ternary oxides have gained increasing attention due to their potential use as solid lubricants at elevated temperatures. In this work, the tribological properties of three ternary oxides—AgTaO3, CuTaO3, and CuTa2O6—were studied using a combination of density-functional theory (DFT), molecular dynamics (MD) simulations with newly developed empirical potential parameters, and experimental measurements (AgTaO3 and CuTa2O6 only). Our results show that the MD-predicted friction force follows the trend AgTaO3 < CuTaO3 < CuTa2O6, which is consistent with the experimentally measured coefficients of friction. The wear performance from both MD and experiment exhibits the opposite trend, with CuTa2O6 providing the best resistance to wear. The sliding mechanisms are investigated using experimental characterization of the film composition after sliding, quantification of Ag or Cu cluster formation at the interface during the evolution of the film in MD, and DFT energy barriers for atom migration on the material surface. All our observations are consistent with the hypothesis that the formation of metal (or metal oxide) clusters on the surface are responsible for the friction and wear behavior of these materials.
Keywords: solid lubricants; high temperature; ternary metal oxides; silver tantalate; copper tantalate; friction; wear

Wind-blown pool fire, Part II: Comparison of measured flame geometry with semi-empirical correlations - Lam, C.S.; Weckman, E.J. (Fire Safety Journal, 2015)
Experimental measurements of flame drag, flame tilt and flame length, which were obtained for 2 m diameter Jet A fires in crosswinds of 3-10 m/s and described in Part I of this paper, were compared to values predicted using published semi-empirical correlations. Results were shown to be influenced in part by differences in the method used to measure flame geometry and in the boundary conditions between different experiments. Flame tilt values were predicted most successfully by correlations involving a combination of the Froude number U2/gD and the non-dimensionalized heat release rate Q∗. Values estimated using similar correlations for flame drag and flame length were less successful, indicating gaps in the relevant physics modeled by those correlations. Fuel vapor density played an important role in determining the extent of flame drag. At high wind speeds, the horizontal momentum of the wind dominated over buoyancy effects in producing flame drag, physical effects not necessarily captured in the existing correlations. Flame length appeared to be governed by factors such as fuel vapor density and heat of combustion of the fuel, as well as wind speed and fuel burning rate. The restriction in air entrainment under conditions of large flame drag greatly increased flame length, particularly at high wind speeds, and should also be considered in future correlations.
Keywords: Fire; Wind; Flame geometry; Flame tilt; Flame length; Flame drag; Semi-empirical correlation

A non-toxigenic but morphologically and phylogenetically distinct new species of Pseudo-nitzschia, P. sabit sp. nov. (Bacillariophyceae) - Teng, Sing Tung; Lim, Po Teen; Lim, Hong Chang; Rivera-Vilarelle, María; Quijano-Scheggia, Sonia; Takata, Yoshinobu; Quilliam, Michael A.; Wolf, Matthias; Bates, Stephen S.; Leaw, Chui Pin (Journal of Phycology, 2015)
A new species of Pseudo-nitzschia (Bacillariophyceae) is described from plankton samples collected from Port Dickson (Malacca Strait, Malaysia) and Manzanillo Bay (Colima, Mexico). The species possesses a distinctive falcate cell valve, from which they form sickle-like colonies in both environmental samples and cultured strains. Detailed observation of frustules under TEM revealed ultrastructure that closely resembles P. decipiens, yet the new species differs by the valve shape and greater ranges of striae and poroid densities. The species is readily distinguished from the curve-shaped P. subcurvata by the presence of a central interspace. The morphological distinction is further supported by phylogenetic discrimination. We sequenced and analyzed the nuclear ribosomal RNA genes in the LSU and the second internal transcribed spacer, including its secondary structure, to infer the phylogenetic relationship of the new species with its closest relatives. The results revealed a distinct lineage of the new species, forming a sister cluster with its related species, P. decipiens and P. galaxiae, but not with P. subcurvata. We examined the domoic acid (DA) production of five cultured strains from Malaysia by Liquid chromatography-mass spectrometry (LC-MS), but they showed no detectable DA. Here, we present the taxonomic description of the vegetative cells, document the sexual reproduction, and detail the molecular phylogenetics of Pseudo-nitzschia sabit sp. nov.
Keywords: Bacillariophyceae; Pseudo-nitzschia

Direct measurement of electron beam quality conversion factors using water calorimetry - Renaud, James; Sarfehnia, Arman; Marchant, Kristin; McEwen, Malcolm; Ross, Carl; Seuntjens, Jan (Medical Physics, 2015)
Purpose: In this work, the authors describe an electron sealed water calorimeter (ESWcal) designed to directly measure absorbed dose to water in clinical electron beams and its use to derive electron beam quality conversion factors for two ionization chamber types. Methods: A functioning calorimeter prototype was constructed in-house and used to obtain reproducible measurements in clinical accelerator-based 6, 9, 12, 16, and 20 MeV electron beams. Corrections for the radiation field perturbation due to the presence of the glass calorimeter vessel were calculated using Monte Carlo (MC) simulations. The conductive heat transfer due to dose gradients and nonwater materials was also accounted for using a commercial finite element method software package. Results: The relative combined standard uncertainty on the ESWcal dose was estimated to be 0.50% for the 9-20 MeV beams and 1.00% for the 6 MeV beam, demonstrating that the development of a water calorimeter-based standard for electron beams over such a wide range of clinically relevant energies is feasible. The largest contributor to the uncertainty was the positioning (Type A, 0.10%-0.40%) and its influence on the perturbation correction (Type B, 0.10%-0.60%). As a preliminary validation, measurements performed with the ESWcal in a 6 MV photon beam were directly compared to results derived from the National Research Council of Canada (NRC) photon beam standard water calorimeter. These two independent devices were shown to agree well within the 0.43% combined relative uncertainty of the ESWcal for this beam type and quality. Absorbed dose electron beam quality conversion factors were measured using the ESWcal for the Exradin A12 and PTW Roos ionization chambers. The photon-electron conversion factor, kecal, for the A12 was also experimentally determined. Nonstatistically significant differences of up to 0.7% were found when compared to the calculation-based factors listed in the AAPM's TG-51 protocol. General agreement between the relative electron energy dependence of the PTW Roos data measured in this work and a recent MC-based study are also shown. Conclusions: This is the first time that water calorimetry has been successfully used to measure electron beam quality conversion factors for energies as low as 6 MeV (R50 = 2.25 cm).

Characterization of fretting wear of cobalt-based superalloys at high temperature for aero-engine combustor components - Korashy, Ahmed; Attia, Helmi; Thomson, Vince; Oskooei, Saeid (Wear, 2015)
Cobalt-based superalloys are used in aero-engine combustor components due to their high strength and wear resistance at elevated temperatures. The objective of this investigation is to study the role of the surface oxide formed during the fretting process on the tribological behavior of this class of materials, at temperatures up to 550°C. The investigation, which was carried out using a specially designed tribometer, showed that the wear coefficient and the coefficient of friction (COF) generally decrease with the increase of temperature at different work rates. When the work rate was fixed at relatively high value (350mJ/s), the wear coefficient was found to decrease monotonically with temperature, while the COF experienced a peak at 200°C. Analysis of the specimen fretted at 200°C showed that the hard wear debris promoted abrasive wear and caused an increase in the COF. In addition, the formed oxide was thin, non-continuous and contained mainly cobalt monoxide (CoO), which contributed to the increase in the COF. Analysis of the specimen fretted at 550°C showed that the wear damage decreased due to the formation of a continuous thick protective oxide containing mainly chromium (III) oxide (Cr2O3), known for its good tribological characteristics. It has also been observed that delamination wear took place within this oxide layer. When the oxide composition and thickness inside and outside the fretted area were compared, it was concluded that the real contact temperature exceeded 600°C due to the frictional heat.
Keywords: Abstracting; Aircraft engines; Cobalt; Cobalt compounds; Combustors; Engines; Fretting corrosion; Friction; Superalloys; Tribology; Cobalt-based superalloy; Fretting wear; Frictional heating; High temperature; Surface oxide; Wear resistance

Scanning voltage microscopy study of lasing and non-lasing terahertz quantum cascade lasers - Dhar, R.S.; Razavipour, S.G.; Dupont, E.; Wasilewski, Z.R.; Ban, D. (CLEO: Science and Innovations, CLEO-SI 2015, 2015)
Scanning voltage microscopy results clearly show that the formation of electric field domains is responsible for the missing of lasing operation in a resonant-phonon based terahertz quantum cascade laser with a highly diagonal transition.

The distribution of main sequence and premain sequence stars in the young anticenter cluster NGC 2401 - Davidge, T. J. (Publications of the Astronomical Society of the Pacific, 2015)
Images obtained with the Gemini Multiobject Spectrograph on Gemini South are used to examine the photometric properties and spatial distributions of main sequence (MS) and premain sequence (PMS) objects in the star cluster NGC 2401. The data sample several magnitudes fainter than previous studies and a large population of candidate PMS (cPMS) stars are identified. The cPMS stars are traced out to 2.4′ from the cluster center and have a flatter spatial distribution than the brightest MS stars near the cluster center. The luminosity function of all MS and candidate PMS stars can be matched by a model that assumes a solar neighborhood mass function, suggesting that NGC 2401 has not yet shed significant numbers of members with masses ≥0.5 M⊙. The frequency of wide binaries among the MS stars is ~3× higher than among the cPMS stars. It is argued that the difference in the spatial distributions of MS and PMS objects is not the consequence of secular dynamical evolution or structural evolution driven by near-catastrophic mass loss. Rather, it is suggested that the different spatial distributions of these objects is the fossil imprint of primordial subclustering that arises naturally if massive stars form preferentially in the highest density central regions of a protocluster.

Correlation between plasma electrolytic oxidation treatment stages and coating microstructure on aluminum under unipolar pulsed DC mode - Dehnavi, Vahid; Luan, Ben Li; Liu, Xing Yang; Shoesmith, David W.; Rohani, Sohrab (Surface and Coatings Technology, 2015)
Alumina coatings were deposited on 6061 aluminum alloy substrates using plasma electrolytic oxidation (PEO) in an alkaline silicate electrolyte. Different electrical parameters, including frequency, duty cycle, and current density were applied to obtain PEO coatings. Scanning electron microscopy (SEM) and microhardness tests were used to investigate the coating microstructure and properties. For each sample, the voltage-time response of the PEO process was obtained and compared with surface morphology, and coating cross sections and thicknesses. Special consideration was given to the connection between the electrical parameters, different stages of the PEO process, and the morphology and microstructure of the coatings. Applying different electrical parameters changed the duration and ratio of the PEO stages in the voltage-time response curve and affected the growth rate, surface morphology, microstructure and microhardness of the coatings. We report the new finding of a correlation between the stage of the PEO process and the microstructure and morphology of the coating.
Keywords: Aluminum; Coatings; Electrolysis; Microhardness; Microstructure; Morphology; Oxidation; Scanning electron microscopy; Silicates; Surface morphology; 6061 aluminum alloys; Alumina coating; Coating microstructures; Different stages; Electrical parameter; Microhardness tests; Plasma electrolytic oxidation; Voltage-time response

Frequency multiplexing excitation network for ultra-wideband coaxial waveguide feeds - Johnson, A.M.; Landecker, T.L.; Johnson, T.; Veidt, B.G.; Du, X. (Electronics Letters, 2015)
A new technique for exciting the TE11 mode in a number of concentric coaxial waveguides is described. The excitation network is logperiodic and is designed to integrate a frequency multiplexing structure together with suppression of higher order modes (TE21 and TE31). The excitation network enables the implementation of very wide band nested coaxial feeds for reflector antennas where multiple waveguides are fed from a common input port. An excitation network providing continuous coverage over a 1-8 GHz frequency range was built and tested in a three-band coaxial waveguide feed.
Keywords: Circular waveguides; Multiplexing; Muscle; Ultra-wideband (UWB); Coaxial waveguides; Continuous coverage; Frequency multiplexing; GHz frequencies; Higher-order modes; Input port; Reflector antennas; Wide-band

Model testing and performance comparison of plastic and metal tidal turbine rotors - Liu, P.; Bose, N.; Frost, R.; Macfarlane, G.; Lilienthal, T.; Penesis, I. (Applied Ocean Research, 2015)
Experimental model tests were conducted to predict the performance of two sets of metal and plastic bi-directional tidal turbine rotors. This test programme aims to provide reliable and accurate measurement data as references for developers, designers and researchers on both model and full scale. The data set presented in this paper makes available the detailed geometry and motion parameters that are valuable for numerical tools validation. A rotor testing apparatus that was built using an off-the-shelf K&R propeller dynamometer, its configuration, testing set-up, calibration of the apparatus and data acquisition are described. Comparison analysis between the metal and plastic rotors hydrodynamic performance in terms of torque, drag and derived power and drag coefficients are also presented. The results show a substantial decrease in maximum power performance for the plastic rotors - about 40% decrease at a tip speed ratio of around 3.0, compared with rigid metal rotors. The plastic rotors have also a much higher cut-in speed. It showed that materials for rotor models with low rigidity such as polyamide (nylon) produced by selective laser sintering (SLS) systems may substantially under-predict power generation capacity. As a result, they are considered unsuitable for rotor model performance evaluation.
Keywords: Metal and plastic rotor testing; Bi-directional turbine; HATT; HACT

Macrophage mitochondrial energy status regulates cholesterol efflux and is enhanced by anti-miR33 in atherosclerosis - Karunakaran, D.; Thrush, A.B.; Nguyen, M.-A.; Richards, L.; Geoffrion, M.; Singaravelu, R.; Ramphos, E.; Shangari, P.; Ouimet, M.; Pezacki, J.P.; Moore, K.J.; Perisic, L.; et al. (Circulation Research, 2015)
Rationale: Therapeutically targeting macrophage reverse cholesterol transport is a promising approach to treat atherosclerosis. Macrophage energy metabolism can significantly influence macrophage phenotype, but how this is controlled in foam cells is not known. Bioinformatic pathway analysis predicts that miR-33 represses a cluster of genes controlling cellular energy metabolism that may be important in macrophage cholesterol efflux. Objective: We hypothesized that cellular energy status can influence cholesterol efflux from macrophages, and that miR-33 reduces cholesterol efflux via repression of mitochondrial energy metabolism pathways. Methods and Results: In this study, we demonstrated that macrophage cholesterol efflux is regulated by mitochondrial ATP production, and that miR-33 controls a network of genes that synchronize mitochondrial function. Inhibition of mitochondrial ATP synthase markedly reduces macrophage cholesterol efflux capacity, and anti-miR33 required fully functional mitochondria to enhance ABCA1-mediated cholesterol efflux. Specifically, anti-miR33 derepressed the novel target genes PGC-1α, PDK4, and SLC25A25 and boosted mitochondrial respiration and production of ATP. Treatment of atherosclerotic Apoe-/- mice with anti-miR33 oligonucleotides reduced aortic sinus lesion area compared with controls, despite no changes in high-density lipoprotein cholesterol or other circulating lipids. Expression of miR-33a/b was markedly increased in human carotid atherosclerotic plaques compared with normal arteries, and there was a concomitant decrease in mitochondrial regulatory genes PGC-1α, SLC25A25, NRF1, and TFAM, suggesting these genes are associated with advanced atherosclerosis in humans. Conclusions: This study demonstrates that anti-miR33 therapy derepresses genes that enhance mitochondrial respiration and ATP production, which in conjunction with increased ABCA1 expression, works to promote macrophage cholesterol efflux and reduce atherosclerosis.
Keywords: atherosclerosis; cholesterol; macrophages; mitochondria; microRNA-33, mouse

Electrochemical study of corrosion behavior of wrought stellite alloys in sodium chloride and green death solutions - Zhang, X. Z.; Liu, R.; Chen, K. Y.; Yao, M. X.; Collier, R. (Journal of Materials Engineering and Performance, 2015)
Corrosion behavior of wrought Stellite 6B and Stellite 6K, which have similar chemical composition but contain different carbon content, in 3.5 wt.% NaCl solution and in Green Death solution is investigated using various electrochemical methods, including potentiodynamic polarization, cyclic polarization, and electrochemical impedance spectroscopy (EIS). The obtained potentiodynamic polarization curves, cyclic polarization curves, and EIS spectra for these alloys are in good agreement, showing that Stellite 6K with higher carbon content is easier corroded due to its larger volume fraction of carbides but the Cr2O3 film formed on this alloy is stronger and more stable than that on Stellite 6B. Further immersion tests on these alloys show that Stellite 6K has less resistance to pitting corrosion.
Keywords: Carbides; Corrosion; Corrosive effects; Electrochemical impedance spectroscopy; Oxide films; Pitting; Polarization; Potentiodynamic polarization; Sodium alloys; Sodium chloride; Stellite; Chemical compositions; Corrosion behavior; Cyclic polarization; Cyclic polarization curves; ELectrochemical methods; Electrochemical studies; Potentiodynamic polarization curves; Stellite alloy; Electrochemical corrosion

Increasing the electrolyte capacity of Alkaline Zn-Air fuel cells by scavenging Zincate with Ca(OH)2 - Zhu, A.L.; Duch, D.; Roberts, G.A.; Li, S.X.X.; Wang, H.; Duch, K.; Bae, E.; Jung, K.S.; Wilkinson, D.; Kulinich, S.A. (ChemElectroChem, 2015)
The use of calcium hydroxide for scavenging zincate species is demonstrated to be a highly effective approach for increasing the electrolyte capacity and improving the performance of the zinc-air fuel cell system. A fundamental approach is established in this study to quantify the formation of calcium zincate as the product of scavenging and the amount of water compensation necessary for optimal performance. The good agreement between predicted and experimental results proves the validity of the proposed theoretical approach. By applying the results of theoretical predictions, both the electrolyte capacity and the cell longevity have been increased by more than 40%. It is also found that, using Ca(OH)2 to scavenge zincate species in concentrated KOH solutions, affects mostly the removal of zincate, rather than ZnO, from the electrolyte, whereas the presence of excess, free, mobile H2O plays a key role in dissolving ZnO and forming zincate. The results obtained in this study demonstrate that the proposed approach can widely and effectively be applied to all zinc-air cell systems during their discharge cycle.
Keywords: Alkaline fuel cells; Electrolytes; Fuel cells; Hydrated lime; Scavenging; Zinc oxide; Discharge capacities; Effective approaches; Optimal performance; Theoretical approach; Water compensation; Zinc air fuel cells; Zincates; Calcium

Chicken Caecal Microbiome modifications induced by campylobacter Jejuni colonization and by a non-antibiotic feed additive - Thibodeau, Alexandre; Fravalo, Philippe; Yergeau, Étienne; Arsenault, Julie; Lahaye, Ludovic; Letellier, Ann (PLOS ONE, 2015)
Campylobacter jejuni is an important zoonotic foodborne pathogen causing acute gastroenteritis in humans. Chickens are often colonized at very high numbers by C. jejuni, up to 109 CFU per gram of caecal content, with no detrimental effects on their health. Farm control strategies are being developed to lower the C. jejuni contamination of chicken food products in an effort to reduce human campylobacteriosis incidence. It is believed that intestinal microbiome composition may affect gut colonization by such undesirable bacteria but, although the chicken microbiome is being increasingly characterized, information is lacking on the factors affecting its modulation, especially by foodborne pathogens. This study monitored the effects of C. jejuni chicken caecal colonization on the chicken microbiome in healthy chickens. It also evaluated the capacity of a feed additive to affect caecal bacterial populations and to lower C. jejuni colonization. From day-0, chickens received or not a microencapsulated feed additive and were inoculated or not with C. jejuni at 14 days of age. Fresh caecal content was harvested at 35 days of age. The caecal microbiome was characterized by real time quantitative PCR and Ion Torrent sequencing. We observed that the feed additive lowered C. jejuni caecal count by 0.7 log (p<0.05). Alpha-diversity of the caecal microbiome was not affected by C. jejuni colonization or by the feed additive. C. jejuni colonization modified the caecal beta-diversity while the feed additive did not. We observed that C. jejuni colonization was associated with an increase of Bifidobacterium and affected Clostridia and Mollicutes relative abundances. The feed additive was associated with a lower Streptococcus relative abundance. The caecal microbiome remained relatively unchanged despite high C. jejuni colonization. The feed additive was efficient in lowering C. jejuni colonization while not disturbing the caecal microbiome.
Keywords: animal experiment; animal tissue; bacterial colonization; bacterial count; bacterial gene; Bifidobacterium; Campylobacter jejuni; cecum; chicken; Clostridia; controlled study; diet supplementation; gene sequence; intestine flora; microbial diversity; microbiome; Mollicutes; real time polymerase chain reaction; RNA 16S gene; Streptococcus

Acidogenic fermentation of Scenedesmus sp.-AMDD: comparison of volatile fatty acids yields between mesophilic and thermophilic conditions - Gruhn, Marvin; Frigon, Jean-Claude; Guiot, Serge R. (Bioresource Technology, 2015)
This study compared the acidogenic fermentation of Scenedesmus sp.-AMDD at laboratory-scale, under mesophilic (35 °C) and thermophilic conditions (55 °C). Preliminary batch tests were performed to evaluate best conditions for volatile fatty acid (VFA) production from microalgal biomass, with respect to the inoculum, pH and nutrients. The use of bovine manure as inoculum, the operating pH of 4.5 and the addition of a nutrient mix, resulted in a high VFA production of up to 222 mg g-1 total volatile solid (TVS), with a butyrate share of 27%. Both digesters displayed similar hydrolytic activity with 0.38±0.02 and 0.42±0.03 g soluble chemical oxygen demand (COD) g-1 TVS for the digesters operated at 35 and 55 °C, respectively. Mesophilic conditions were more favourable for VFA production, which reached 171±5, compared to 88±12 mg soluble COD g-1 TVS added under thermophilic conditions (94% more). It was shown that in both digesters, butyrate was the predominant VFA.
Keywords: Anaerobic digestion; Carboxylic acid; Fatty acids; Microalgae; Scenedesmus

Metrological characterization of 3D imaging systems: progress report on standards developments - Beraldin, J.-Angelo; Mackinnon, David; Cournoyer, Luc; National Research Council Canada (17th International Congress of Metrology, 2015)
A significant issue for companies or organizations integrating non-contact three-dimensional (3D) imaging systems into their production pipeline is deciding in which technology to invest. Quality non-contact 3D imaging systems typically involve a significant investment when considering the cost of equipment, training, software, and maintenance contracts over the functional lifetime of a given system or systems notwithstanding the requirements of the global nature of manufacturing activities. Numerous methods have been published to “help” users navigate the many products and specifications claims about “quality”. Moreover, the “best” system for one application may not be ideally suited for another application. The lack of publically-available characterization methods from trusted sources for certain areas of 3D imaging make it difficult for a typical user to select a system based on information written on a specification sheet alone. An internationally-recognized standard is a vehicle that allows better communication between users and manufacturers. It is in this context that we present a progress report on standards developments to date in the diverse, but finite, world of non-contact 3D imaging systems from the nanometre to the 100 m range.

Identification of aeroelastic parameters for helicopter tail rotor limit cycle oscillation monitoring - Chen, Yong; Wickramasinghe, Viresh; Zimcik, David G. (Journal of Intelligent Material Systems and Structures, 2015)
The aeroelastic parameters of helicopter tail rotors are required in the monitoring and evaluation of rotor aeroservoelastic instability incidents such as limit cycle oscillations (LCO). However, in-situ measurement of these parameters on helicopters is generally difficult due to the need to transfer vibration data across a rotating interface. This paper presents a novel center frequency scaling factor relationship of the aeroelastic parameters between the rotating and stationary frames. Together with the stochastic parameter identification technique, this methodology enables real-time estimation and tracking of the critical aeroelastic parameters in the rotating frame during LCO events based on vibration information measured exclusively in the stationary frame. The methodology has been validated using flight vibration data measured from both the rotating and stationary frames of a helicopter tail rotor system during an LCO event. Moreover, this methodology has been applied to the analysis of vibration data measured from the teeter tail rotor system on the Canadian CH-149 Cormorant helicopters to derive the critical aeroelastic parameters during several LCO events.
Keywords: structural health monitoring; sensor; embedded intelligence

Open-source computational model of a solid oxide fuel cell - Beale, Steven B.; Choi, Hae-Won; Pharoah, Jon G.; Roth, Helmut K.; Jasak, Hrvoje; Jeon, Dong Hyup (Computer Physics Communications, 2015)
The solid oxide fuel cell is an electro-chemical device which converts chemical energy into electricity and heat. To compete in today’s market, design improvements, in terms of performance and life cycle, are required. Numerical prototypes can accelerate design and development progress. In this programme of research, a three-dimensional solid oxide fuel cell prototype, openFuelCell, based on open-source computational fluid dynamics software was developed and applied to a single cell. Transport phenomena, combined with the solution to the local Nernst equation for the open-circuit potential, as well as the Kirchhoff-Ohm relationship for the local current density, allow local electro-chemistry, fluid flow, multi-component species transport, and multi-region thermal analysis to be considered. The detailed physicochemical hydrodynamics included porous electrodes and electro-chemical effects. The openFuelCell program is developed in an object-oriented open-source C++ library. The code is available at http://openfuelcell.sourceforge.net/. The paper also describes domain decomposition techniques considered in the context of highly efficient parallel programming.
Keywords: Solid oxide fuel cell; Computational fluid dynamics; Physicochemical hydrodynamics; Electro-chemistry

Large deformation characterization of porcine thoracic aortas: inverse modeling fitting of uniaxial and biaxial tests - Delgadillo, Jorge O. Virues; Delorme, Sebastien; Thibault, Francis; DiRaddo, Robert; Hatzikiriakos, Savvas G. (Journal of biomedical science and engineering, 2015)
The elastic behavior of arteries is nonlinear when subjected to large deformations. In order to measure their anisotropic behavior, planar biaxial tests are often used. Typically, hooks are attached along the borders of a square sample of arterial tissue. Cruciform samples clamped with grips can also be used. The current debate on the effect of different biaxial test boundary conditions revolves around the uniformity of the stress distribution in the center of the specimen. Uniaxial tests are also commonly used due to simplicity of data analysis, but their capability to fully describe the in vivo behavior of a tissue remains to be proven. In this study, we demonstrate the use of inverse modeling to fit the material properties by taking into account the non-uniform stress distribution, and discuss the differences between the three types of tests. Square and cruciform samples were dissected from pig aortas and tested equi-biaxially. Rectangular samples were used in uniaxial testing as well. On the square samples, forces were applied on each side of edge sample attached with hooks, and strains were measured in the center using optical tracking of ink dots. On the cruciform and rectangular samples, displacements were applied on grip clamps and forces were measured on the clamps. Each type of experiment was simulated with the finite element method. The parameters of the Mooney-Rivlin constitutive model were adjusted with an optimization algorithm so that the simulation predictions fitted the experimental results. Higher stretch ratios (>1.5) were reached in the cruciform and rectangular samples than in the square samples before failure. Therefore, the nonlinear behavior of the tissue in large deformations was better captured by the cruciform biaxial test and the uniaxial test, than by the square biaxial test. Advantages of cruciform samples over square samples include: 1) higher deformation range; 2) simpler data acquisition and 3) easier attachment of sample. However, the nonuniform stress distribution in cruciform samples requires the use of inverse modeling adjustment of constitutive model parameters.
Keywords: Mechanical Properties; Artery; Inverse Modeling; Uniaxial and Biaxial Testing; Mooney-Rivlin Model

Monte Carlo reference data sets for imaging research: executive summary of the report of AAPM Research Committee Task Group 195 - Sechopoulos, Ioannis; Ali, Elsayed S. M.; Badal, Andreu; Badano, Aldo; Boone, John M.; Kyprianou, Iacovos S.; Mainegra-Hing, Ernesto; McMillan, Kyle L.; McNitt-Gray, Michael F.; Rogers, D. W. O.; Samei, Ehsan; Turner, Adam C. (Medical physics, 2015)
The use of Monte Carlo simulations in diagnostic medical imaging research is widespread due to its flexibility and ability to estimate quantities that are challenging to measure empirically. However, any new Monte Carlo simulation code needs to be validated before it can be used reliably. The type and degree of validation required depends on the goals of the research project, but, typically, such validation involves either comparison of simulation results to physical measurements or to previously published results obtained with established Monte Carlo codes. The former is complicated due to nuances of experimental conditions and uncertainty, while the latter is challenging due to typical graphical presentation and lack of simulation details in previous publications. In addition, entering the field of Monte Carlo simulations in general involves a steep learning curve. It is not a simple task to learn how to program and interpret a Monte Carlo simulation, even when using one of the publicly available code packages. This Task Group report provides a common reference for benchmarking Monte Carlo simulations across a range of Monte Carlo codes and simulation scenarios. In the report, all simulation conditions are provided for six different Monte Carlo simulation cases that involve common x-ray based imaging research areas. The results obtained for the six cases using four publicly available Monte Carlo software packages are included in tabular form. In addition to a full description of all simulation conditions and results, a discussion and comparison of results among the Monte Carlo packages and the lessons learned during the compilation of these results are included. This abridged version of the report includes only an introductory description of the six cases and a brief example of the results of one of the cases. This work provides an investigator the necessary information to benchmark his/her Monte Carlo simulation software against the reference cases included here before performing his/her own novel research. In addition, an investigator entering the field of Monte Carlo simulations can use these descriptions and results as a self-teaching tool to ensure that he/she is able to perform a specific simulation correctly. Finally, educators can assign these cases as learning projects as part of course objectives or training programs.

Polymer-based microfluidic chip for rapid and efficient immunomagnetic capture and release of Listeria monocytogenes - Malic, L.; Zhang, X.; Brassard, D.; Clime, L.; Daoud, J.; Luebbert, C.; Barrere, V.; Boutin, A.; Bidawid, S.; Farber, J.; Corneau, N.; Veres, T. (Lab on a Chip, 2015)
Infections caused by foodborne pathogens such as Listeria monocytogenes pose a threat to public health while timely detection is challenging due to pathogen low numbers. The development of robust and efficient sample preparation techniques is crucial to improve detection sensitivity and workflow. Immunomagnetic separation using magnetic nanoparticles (MNPs) is attractive, as it can efficiently capture target cells. For food safety applications, a platform is needed to rapidly process large sample volumes, allowing capture and release of target bacteria conjugated to immunomagnetic nanoparticles (IMNPs). Herein, we demonstrate a method for magnetic capture and release of bacteria-IMNPs complex based on a 3D magnetic trap integrated on a polymeric microfluidic device. The 3D magnetic capture region consist of a dense array of high-aspect ratio (3 : 1) cylindrical pillars embossed in thermoplastic polymer and coated with soft ferromagnetic nickel by an electroless deposition technique. This allows the generation of strong and switchable magnetic capture regions due to the very low remanence of the nickel shell. We propose and validate an optimized configuration of capture regions for efficient localized capture and rapid release of MNPs and IMNPs conjugated to L. monocytogenes. A maximum recovery rate for MNPs corresponded to 91% while a maximum capture efficiency of 30% was obtained for live bacteria, with a minimum detectable sample concentration of ~10 cfu ml−1 in 1 ml volume using plate-culture method. We believe that the flexible design and low-cost fabrication process of the proposed system will allow rapid sample preparation for applications beyond food and water safety, including point-of-care diagnosis.

Screening of a wide range of pre-treatments for improving the algal biomass solubilization and biogas potential - Guiot, Serge R. (Journal of fundamentals of renewable energy and applications, 2015)
The microalgal biomass conversion into methane as a biofuel offers the best energetic balance among the different biomass–to-biofuel scenarios for microalgae containing less than 40% lipids. The anaerobic degradation limitation of algae at around 50% emphasizes the need for pre-treatment to obtain higher methane production from algae. This study was performed using Scenedesmus sp. AMDD, green microalgae, as a model strain. Over 20 series of different pretreatments were evaluated, alone, or in sequence. The enzymatic pretreatments were performed with pectate-lyase and cellulase at incubation time from 2 to 24 hours. Chemicals pretreatments were done with H2SO4, NaOH or H2O2, at 0.2N and 2N and 2 to 24 h of reaction time. Thermal treatments were completed in an oven or a pressure vessel at 121 – 180°C or using a microwave (175 – 300°C). The enzymatic hydrolysis of Scenedesmus sp. AMDD followed with a three hours incubation in NaOH 0.2N resulted into a 75% solubilization. Similar results were found with incubation in 0.2N NaOH followed with short thermal treatment. Caustic and thermal pretreatments improved the methane production by around 12% compared with the anaerobic digestion of untreated algal biomass, at 335 ± 28 ml CH4 STP/g volatile solid (VS) added. The results from the enzymatic pretreatment were less encouraging with improvement of 2-7% of the methane production only. However, a combination of enzymatic with a thermal treatment successfully solubilized up to 75% of Scenedesmus sp. AMDD biomass. The resulting methane production, although up to 15% higher than for the control biomass, did not fully correlate with the increased dissolved organic matter. In anaerobic digesters continuously fed with solubilized biomass after combined enzymatic and thermal pre-treatment, the CH4 yield was improved by up to 35% in some operational conditions, while the degradation rate was faster, allowing for lower retention time.

Experimental and numerical study of soot formation in laminar coflow diffusion flames of gasoline/ethanol blends - Khosousi, Ali; Liu, Fengshan; Dworkin, Seth B.; Eaves, Nick A.; Thomson, Murray J.; He, Xu; Dai, Yujie; Gao, Yongli; Liu, Fushui; Shuai, Shijin; Wang, Jianxin (Combustion and flame, 2015)
This paper reports the experimental and numerical results of soot formation in laminar coflow diffusion flames of vaporized gasoline/ethanol blends at atmospheric pressure to gain improved understanding of ethanol addition to gasoline on soot formation. Four gasoline/ethanol blends of different ethanol mole fractions in the fuel stream ranging from 0% up to 85%, E0, E20, E50, and E85, were investigated to quantify how soot loading varies with the amount of ethanol blending in the fuel. The laminar coflow diffusion flames were generated using a burner system designed for vaporized liquid fuels. The fuel stream was heavily diluted with nitrogen to lower the boiling points and to prevent the flames from smoking. The soot volume fraction distributions were measured using a 2D line-of-sight attenuation technique. These flames were also modeled numerically using the extensively validated CoFlame code and a recently developed reaction mechanism for gasoline surrogates including PAH formation. The results of experiment and numerical modeling agree quite well in terms of the levels of soot volume fraction and they both show a decrease in the soot loading as more ethanol is added in the fuel stream. The measured peak soot volume fraction occurs in the flame centerline region. The soot model used in this study is unable to capture this experimental feature and predicts the peak soot volume fraction in the co-annular region. Ethanol addition reduces the soot loading primarily by lowering soot inception and PAH condensation rates through decreasing the concentrations of aromatics. Additional measurements in gasoline surrogate/ethanol blend flames indicate that the gasoline surrogate model emulates well the sooting propensity of the real gasoline fuel.
Keywords: Laminar diffusion flame; Soot; Gasoline; Ethanol; Gasoline surrogate

On-line monitoring of microbial fuel cells operated with pulse-width modulated electrical load - Coronado, J.; Tartakovsky, B.; Perrier, M. (Journal of process control, 2015)
This study describes application of an equivalent circuit model (ECM) for on-line monitoring of microbial fuel cells (MFCs). ECM analytical solutions were derived for MFCs operated with pulse-width modulated electrical load connection at high and low frequencies. These analytical solutions were used to develop an on-line procedure for estimating MFC internal resistance, internal capacitance and open circuit voltage. The proposed parameter estimation and monitoring procedure was used to follow MFC startup performance as well as its performance at various organic loads. A comparison of ESM-based on-line estimations with conventional polarization tests confirmed feasibility of the proposed approach.
Keywords: Real-time monitoring; Parameter estimation; MFC; Equivalent circuit model; Internal resistance

Direct imaging of an asymmetric debris disk in the HD 106906 planetary system - Kalas, Paul G.; Rajan, Abhijith; Wang, Jason J.; Millar-Blanchaer, Maxwell A.; Duchene, Gaspard; Chen, Christine; Fitzgerald, Michael P.; Dong, Ruobing; Graham, James R.; Patience, Jennifer; Macintosh, Bruce; Murray-Clay, Ruth; et al. (The Astrophysical Journal, 2015)
We present the first scattered light detections of the HD 106906 debris disk using Gemini/GPI in the infrared and HST/ACS in the optical. HD 106906 is a 13 Myr old F5V star in the Sco-Cen association, with a previously detected planet-mass candidate HD 106906b projected 650 AU from the host star. Our observations reveal a near edge-on debris disk that has a central cleared region with radius ∼ 50 AU, and an outer extent > 500 AU. The HST data show the outer regions are highly asymmetric, resembling the ''needle'' morphology seen for the HD 15115 debris disk. The planet candidate is oriented ∼ 21deg away from the position angle of the primary's debris disk, strongly suggesting non-coplanarity with the system. We hypothesize that HD 106906b could be dynamically involved in the perturbation of the primary's disk, and investigate whether or not there is evidence for a circumplanetary dust disk or cloud that is either primordial or captured from the primary. We show that both the existing optical properties and near-infrared colors of HD 106906b are weakly consistent with this possibility, motivating future work to test for the observational signatures of dust surrounding the planet.
Keywords: Earth and Planetary Astrophysics

Calibration graphs in isotope dilution mass spectrometry - Pagliano, Enea; Mester, Zoltán; Meija, Juris (Analytica Chimica Acta, 2015)
Isotope-based quantitation is routinely employed in chemical measurements. Whereas most analysts seek for methods with linear theoretical response functions, a unique feature that distinguishes isotope dilution from many other analytical methods is the inherent possibility for a nonlinear theoretical response curve. Most implementations of isotope dilution calibration today either eliminate the nonlinearity by employing internal standards with markedly different molecular weight or they employ empirical polynomial fits. Here we show that the exact curvature of any isotope dilution curve can be obtained from three-parameter rational function, y = f(q) = (a0 + a1q)/(1 + a2q), known as the Padé[1,1] approximant. The use of this function allows eliminating an unnecessary source of error in isotope dilution analysis when faced with nonlinear calibration curves. In addition, fitting with Padé model can be done using linear least squares.
Keywords: Isotope dilution; Stable isotope labeled internal standards; Calibration graphs; Nonlinearity

Why are organotin hydride reductions of organic halides so frequently retarded? kinetic studies, analyses, and a few remedies - Ingold, K. U.; Bowry, V.W. (Journal of Organic Chemistry, 2015)
Kinetic data for reduction of organic halides (RX) by tri-n-butylstannane (SnH) reveal a serious flaw in the current view of the kinetic radical chain: the tacit but unproven assumption that the speed of reaction is determined by the slowest propagation step. Our results show this is rarely true for reductive chains and that the observed rate is in fact controlled by unseen side-reactions of propagating R• and Sn• radicals with the solvent (notably, benzene!) or solvent impurities (e.g., trace benzophenone dryness indicator in THF) or, crucially, with allylic-CH and conjugated unsaturated groups in substrates and products. Most R• and/or Sn• radicals are therefore converted into relatively inert delocalized species A• and/or B• that inhibit the chain. Retardation in the degraded chain is given by a simple sum of terms, each being the ratio of the chain-transfer rate divided by the rate of chain-return. The model kinetic equation is linear and easy to ratify, interpret, and apply: to calculate retarding rate constants, optimize reaction conditions, and identify additives or "remedies" that repair the chain and accelerate reaction. The present work is thus expected to have a helpful impact on the practice and design of SnH radical chain based (and related) syntheses. © 2014 American Chemical Society.
Keywords: Integral equations; Kinetic theory; Kinetics; Organic solvents; Organometallics; Rate constants; Repair; Tin; Chain transfer rates; Hydride reduction; Model kinetic equations; Organic halides; Propagation step; Radical chain; Reaction conditions; Side reactions; Chains; anthracene; benzophenone; cyclohexane; organohalogen derivative; organotin compound; radical; addition reaction; Article; chemical analysis; chemical reaction kinetics; chemical structure; reduction

Blank correction in isotope dilution - Pagliano, Enea; Mester, Zoltan; Meija, Juris (Analytical chemistry, 2015)
A novel method for compensation of the procedural blank in isotope dilution is presented. This method - entitled "blank-matching" - copes with the blank through experimental design. Both sample and calibration solutions are exposed to the same amount of isotopic standard and same procedural blank. The identical treatment of sample and calibrators eliminates the need for subtracting the procedural blank from the result obtained by isotope dilution. A further advantage of the method is that quantitation of the analyte in the procedural blank is not required. Blank-matching is simple and fast to implement and it permits direct determination of results without further corrections. This aspect has an important metrological outcome: blank-matching isotope dilution can be considered a primary method of analysis that does not involve the procedural blank as a potential source of bias.

High voltage divider calibration with the reference step method - Parks, harold (2015 NCSL International Conference proceedings, 2015)
High voltage DC measurements, from 10 kV up to several hundred kV, are usually traceable through resistive dividers which have a divider ratio on the order of 10 000 to 100 000. The reference step method providers a highly accurate ratio metric method of calibrating 1000 V calibrators across a wide range of voltages. We adapt this method for measuring the ratio of high voltage dividers at low (equal or less than 1000 V) voltages as a first step to establishing traceability at high voltages.

The 2014 North American Josephson voltage interlaboratory comparison - Tang, Yi-hua; Parks, Harold; Wachter, James (2015 NCSL International Conference proceedings, 2015)
Keywords: automatic comparison; conventional Josephson voltage standard; programmable Josephson voltage standard; uncertainty; Zener standard

Measurements of hydrophobicity for silicone rubber coating on outdoor insulators - Ghunem, Refat Atef; Tay, Li-Lin (2015)
In this paper condition assessment of silicon rubber coating applied to high voltage insulators is proposed. Electrical, thermal and chemical measurement methods are used to evaluate the condition of silicon rubber coating. From an asset management perspective, hydrophobicity is shown to be the key indicator of aging, and this the remnant life, of the coating material. The increase in the content of surface oxygen is an indicator of hydrophobicity deterioration under the power system. In addition, detecting the diffusion of the low-molecular-weight siloxane from the bulk to the surface can be utilized to indicate the relative ability to recover hydrophobicity after aging.

A real-time anvil motion monitoring system - Wu, Lixue (Major challenges in acoustics, noise and vibration research, 2015: proceedings of The 22nd International Congress on Sound and Vibration, 2015)
Most primary shock calibrations, or absolute shock calibrations, are currently performed using laser interferometry under the guideline of the international standard (ISO 16063-13, 2001). The laser interferometric method measures the displacement of a moving anvil with a shock accelerometer mounted on. To achieve high accuracy in the measurement of acceleration it requires a straight motion of the accelerometer with desired shock pulse duration and shape. Unfortunately, shock generators usually present high levels of unwanted motions, such as rotation, transverse motion, and pitch motion. The presence of unsymmetric forces on the anvil causes these motions. To reduce the effect of these motions, measurements may be performed at multiple incidence points equally spaced along the border of the accelerometer on the mounting surface or on the top surface of the accelerometer and the corresponding average is then estimated. Obviously, this method is very time consuming. Alternatively, supporting structures can be added to the anvil in such a way that few or no unsymmetric forces cause rotation and deviations from rectilinear motion. To obtain the best results, the supporting structure should be optimized for a specific type of accelerometer with its dummy mass if any. For this purpose, a real-time anvil motion monitoring system was developed at National Research Council Canada. This paper describes the detail of the system and presents the measurement results under different operating conditions. Static air bearing measurements were performed using the system to study the radial stiffness and pitch stiffness of the anvil. Dynamic air bearing measurements were also performed using the system to ensure that the resonance frequencies of the anvil are at least 10/T, where T is the pulse duration.

Effects of oxygen index on soot production and temperature in an ethylene inverse diffusion flame - Escudero, F.; Fuentes, A.; Demarco, R.; Consalvi, J.-L.; Liu, F.; Elicer-Cortés, J. C.; Fernandez-Pello, C. (Experimental Thermal and Fluid Science, 2015)
An experimental study was conducted to investigate the effects of the Oxygen Index (OI) in an ethylene laminar inverse diffusion flame (IDF). The OI was varied from 21% to 37% and its influence was measured in terms of the flame height, soot volume fraction, soot temperature and radiant fraction. The stoichiometric flame height was measured by the spontaneous emission of CH∗ radicals and was found to decrease when the OI increases. In contrast, the luminous flame height increases with OI because soot can still form and grow beyond the reaction zone. Radial profiles of soot volume fraction and soot temperature were obtained by means of a Modulated Absorption/Emission (MAE) technique. The line-of-sight intensities, integrated along the optical path and captured by ECCD camera at two wavelengths were inverted using deconvolution and regularization techniques in order to obtain radial profiles of soot volume fraction and temperature. The increase in OI enhances soot volume fraction due to higher temperatures and soot formation rates. Both the local and integrated soot quantities increase with OI. The radiant fraction of IDF increases with the OI in a similar way to the integrated soot volume fraction.
Keywords: Laminar inverse diffusion flame; Oxygen index; Soot volume fraction; Soot temperature; Radiant fraction

(Invited) bright light emitting silicon/germanium nanostructures - Lockwood, David J. (ECS Transactions, 2015)
Light emission from Si nanostructures has been of great interest for some time now owing to the need for silicon-based light sources for applications in silicon opto-electronics and photonics. Both Si and Ge possess indirect band gaps, which makes them very inefficient light emitters. Band gap engineering employing quantum wells or quantum dots has been proposed as one way to overcome this limitation and Si/Ge or Si/SiGe-alloy thin-multilayer nanostructures grown on Si have been produced on this principle, and although light emission with greatly improved efficiency has been obtained at low temperatures the emission at room temperature is still very weak, because of exciton dissociation. Recent advances in band gap engineering technology have resulted in the development of new systems incorporating one-, two-, and three-dimensionally confined Si-Ge nanostructures that produce bright light in the near infrared. Here, the novel optical properties of three such nanostructures—super unit cells, nanowires, and nanocluster layers—are explored.

Terahertz spectroscopy: studying carrier dynamics in semiconductor nanostructures - Titova, Lyubov V.; Xu, Sijia; Baribeau, Jean-Marc; Lockwood, David J.; Hegmann, Frank (ECS Transactions, 2015)
Understanding the ultrafast dynamics of photoexcited carriers in semiconductor nanostructures and their dependence on sample morphology is crucial for their incorporation into photonic devices. Time-resolved terahertz (THz) spectroscopy (TRTS) is an all-optical, contact-free technique that directly measures the transient mobile carrier dynamics and terahertz conductivity in materials over picosecond time scales, and is uniquely suited as a probe of conductivity in nanomaterials. Using low temperature MBE-grown silicon films as an example, we show how TRTS can be used to probe microscopic photoconductivity as well as obtain crucial insights into sample morphology. The thin silicon films consist of a mixture of amorphous and crystalline phases, and their relative content changes drastically with growth temperature. Photoexcited carrier dynamics in these films are determined by film crystallinity: in the amorphous phase, carriers are trapped in bandtail states on sub-picosecond time scales, while the carriers excited in crystalline grains remain free for tens of picoseconds. The complex THz conductivity spectra obtained from the TRTS measurements show that the long range conductivity is significantly higher in films grown at higher temperatures that contain a larger fraction of crystalline material with larger crystal grain sizes.

From MOOC to personal learning - Downes, Stephen (Revista FGV Online, 2015)
The cMOOC, is based on connection rather than content, looks more like an online community than a course, and doesn’t have a defined curriculum or formal assignments. What makes a person able to function in such an environment? What constitutes the literacy that is missing in such a case? What type of learning design or learning technology is best suited to support learning in a free-form community-based environment? These are the questions intended to be addressed in this paper. It describes the basis for a personal learning architecture and outlines the elements of the ‘learning and Performance Support System’ project being developed to implement this architecture.
Keywords: MOOC; e-learning; personal learning; web; pedagogy; sharing; learning resources; open educational resources; networks

β Pictoris' inner disk in polarized light and new orbital parameters for β Pictoris b - Millar-Blanchaer, Maxwell A.; Graham, James R.; Pueyo, Laurent; Kalas, Paul; Dawson, Rebekah I.; Wang, Jason; Perrin, Marshall D.; Moon, Dae-Sik; Macintosh, Bruce; Ammons, S. Mark; Barman, Travis; Cardwell, Andrew; et al. (The Astrophysical Journal, 2015)
The dynamical interactions between exoplanets and their local debris disks provide a unique window into the understanding of planetary system architectures and evolution. In this regard, the β Pic system is important as it is one of the rare cases where both a planet and a debris disk have been directly imaged.
Keywords: astrometry; planet–disk interactions; planets and satellites-individual (β Pic b); techniques-polarimetric

Extension of flow stress–strain curves of aerospace alloys after necking - Saboori, M.; Champliaud, H.; Gholipour, J.; Gakwaya, A.; Savoie, J.; Wanjara, P. (The international journal of advanced manufacturing technology, 2015)
To define accurately the expansion limits of aerospace materials, determination of the material behavior before and after the onset of necking, as well as the failure threshold are essential requirements. The plastic flow behavior before necking (pre-necking phase) has been fully identified by various mathematical models, such as Hollomon and Swift constitutive equations, but a criterion to satisfy the material behavior after necking (post-necking phase) is lacking. To obtain or calibrate accurately the damage constants in coupled and decoupled damage models, a precise stress-strain behavior after necking is required to reduce significantly the error in predicting fracture in metal forming processes. A tool was developed to determine the true stress-true strain curve for the post-necking regime of different aerospace alloys, such as inconel 718 (IN 718), stainless steel 321 (SS 321), and titanium (Ti6Al4V). Uniaxial tensile tests based on the ASTM E8M-11 standard were performed to determine the true stress-true strain behavior before necking. Two different methods, a weighted average method and a new hardening function, were utilized to extend the true stress-true strain curve after necking. The two methods resulted in similar post-necking curves for the different materials, with consideration that the new hardening function could be used for more complicated hardening laws. The flow curves were employed in the simulation of the dome height test and then validated through experimentation. The simulation results were compared with the experimental data to verify the accuracy of the proposed methods in this work.
Keywords: Work hardening; Material behavior; Weighted average method; Onset of necking

Microfluidic integration of a cloth-based hybridization array system (CHAS) for rapid, colorimetric detection of enterohemorrhagic Escherichia coli (EHEC) using an articulated, centrifugal platform - Geissler, Matthias; Clime, Liviu; Hoa, Xuyen Dai; Morton, Keith J.; Hebert, Harold; Poncelet, Lucas; Deschenes, Mylene; Gauthier, Martine E.; Huszczynski, George; Corneau, Nathalie; Blais, Burton W.; Veres, Teodor (Analytical Chemistry, 2015)
We describe the translation of a cloth-based hybridization array system (CHAS)—a colorimetric DNA detection method that is used by food inspection laboratories for colony screening of pathogenic agents—onto a microfluidic chip format. We also introduce an articulated centrifugal platform with a novel fluid manipulation concept based on changes in the orientation of the chip with respect to the centrifugal force field to time the passage of multiple components required for the process. The platform features two movable and motorized carriers that can be reoriented on demand between 0 and 360° during stage rotation. Articulation of the chip can be used to trigger on-the-fly fluid dispensing through independently addressable siphon structures or to relocate solutions against the centrifugal force field, making them newly accessible for downstream transfer. With the microfluidic CHAS, we achieved significant reduction in the size of the cloth substrate as well as the volume of reagents and wash solutions. Both the chip design and the operational protocol were optimized to perform the entire process in a reliable, fully-automated fashion. A demonstration with PCR-amplified genomic DNA confirms on-chip detection and identification of Escherichia coli O157:H7 from colony isolates in a colorimetric multiplex assay using rfbO157, fliCH7, vt1, and vt2 genes.

Synergistic electrocatalysis of N,Nʹ-bis(salicylidene)-ethylenediamine-cobalt(II) and conductive carbon black (BP) for high efficient CO2 electroreduction - Fu, Yishu; Liu, Yuyu; Li, Yanan; Li, Jing; Qiao, Jinli; Zhang, Jiujun (Journal of solid state electrochemistry, 2015)
Gas diffusion electrodes (GDEs) modified with N,Nʹ-Bis(salicylidene)-ethylenediamine-cobalt(II) (Cosalen) and conductive carbon black (BP) have been prepared. It is demonstrated that modified BP-Cosalen/GDE electrode is able to catalyze CO2 reduction in a more efficient and selective manner than that of bulk Cosalen/GDE in 0.5 M KHCO3 solution. In the presence of 60 wt% of BP, the as-prepared BP-Cosalen/GDE electrode exhibits the highest activity for catalyzing CO2 reduction reaction, wherever increase or decrease the amount of BP do not benefit to CO2 reduction. Compared to other BP-Cosalen/GDE electrodes, the BP-Cosalen/GDE60 shows the most positive onset potential, and the maximum current density reaches 21 mA cm−2. The improved catalytic activity is largely due to the excellent electrical conductivity and the developed pore structure of BP which provides more active phases for the electrochemical reduction of CO2. Further analysis of reduction product reveals that the product on BP-Cosalen/GDE60 electrode is formate in 0.5 M KHCO3 electrolyte. The highest faradaic efficiency reached 27 % along with the production rate of formate as much as 0.44 mM.
Keywords: Electrochemical reduction of CO2; Gas diffusion electrode; Catalytic activity; Onset potential; Formic acid

A hybrid enrichment process combining conjugated polymer extraction and silica gel adsorption for high purity semiconducting single-walled carbon nanotubes (SWCNT) - Ding, Jianfu; Li, Zhao; Lefebvre, Jacques; Cheng, Fuyong; Dunford, Jeffrey L.; Malenfant, Patrick R. L.; Humes, Jefford; Kroeger, Jens (Nanoscale, 2015)
A novel purification process for the enrichment of sc-SWCNTs that combines selective conjugated polymer extraction (CPE) with selective adsorption using silica gel, termed hybrid-CPE (h-CPE), has been developed, providing a high purity sc-SWCNT material with a significant improvement in process efficiency and yield. Using the h-CPE protocol, a greater than 5 fold improvement in yield can be obtained compared to traditional CPE while obtaining sc-SWCNT with a purity >99.9% as assessed by absorption spectroscopy and Raman mapping. Thin film transistor devices using the h-CPE derived sc-SWCNTs as the semiconductor possess mobility values ranging from 10–30 cm2 V−1 s−1 and current ON/OFF ratio of 104–105 for channel lengths between 2.5 and 20 μm.

Preparation of legionaminic acid analogs of sialo-glycoconjugates by means of mammalian sialyltransferases - Watson, David C.; Wakarchuk, Warren W.; Gervais, Christian; Durocher, Yves; Robotham, Anna; Fernandes, Steve M.; Schnaar, Ronald L.; Young, N. Martin; Gilbert, Michel (Glycoconjugate Journal, 2015)
Legionaminic acids are analogs of sialic acid that occur in several bacteria. The most commonly occurring form is Leg5Ac7Ac, which differs from Neu5Ac only at the C7 (acetamido) and C9 (deoxy) positions. While these differences greatly reduce the susceptibility of Leg compounds to sialidases, several sialyltransferases have been identified that can use CMP-Leg5Ac7Ac as a donor (Watson et al. 2011). We report the successful modification with Leg5Ac7Ac of a glycolipid, GM1a, and two glycoproteins, interferon-α2b and α1-antitrypsin, by means of two mammalian sialyltransferases, namely porcine ST3Gal1 and human ST6Gal1. The Leg5Ac7Ac form of GD1a was not recognized by the myelin-associated glycoprotein (MAG, Siglec-4), confirming the importance of the glycerol moiety in the interaction of sialo-glycans with Siglecs.
Keywords: α1-antitrypsin; GD1a; human ST6Gal1 sialyltransferase; interferon-α2b; porcine ST3Gal1 sialyltransferase

High extinction ratio and broadband silicon TE-pass polarizer using subwavelength grating index engineering - Xiong, Yule; Xu, Dan-Xia; Schmid, Jens H.; Cheben, Pavel; Ye, Winnie N. (IEEE Photonics Journal, 2015)
We propose and experimentally demonstrate a novel approach to implement a low loss, broadband and compact transverse electric (TE)-pass polarizer on a silicon-on-insulator (SOI) platform. The TE-polarizer utilizes a subwavelength grating (SWG) structure to engineer the waveguide equivalent material index. In this work, the SWG-based polarizer only supports its fundamental TE mode while the transverse magnetic (TM) mode is suppressed under the cut-off condition, i.e., the TM mode leaks from the waveguide with a low reflection. The simulations predict that the bandwidth to achieve a polarization extinction ratio (ER) of 35 dB exceeds 200 nm. Experimentally, the measured polarization ER is ~30 dB and the average insertion loss is 0.4 dB, in the wavelength range 1470 nm - 1580 nm. The fabricated TE-polarizer has a compact length of 60 μm.
Keywords: waveguides; subwavelength structures; silicon nanophotonics

Contribution of multiple electron trajectories to high-harmonic generation in the few-cycle regime - Naumov, A. Yu; Villeneuve, D. M.; Niikura, Hiromichi (PhyPhysical Review A, 2015)
We use a few-cycle, carrier-envelope-phase (CEP) stabilized laser system to generate high-harmonic emission in argon, neon, and carbon dioxide. The high-harmonic spectra consist of discrete harmonic orders whose positions shift as a function of the CEP. Near the cutoff harmonic, the peaks are separated by two photon orders, and can correspond to either even or odd harmonics of the driving laser frequency, depending on the value of the CEP. In the plateau region, harmonic orders are separated by only one photon order. We develop a simple model which predicts the observed behavior. We use the observed dependence of the harmonic peaks as a function of CEP as a method to measure the statistical CEP fluctuations of the laser system. The measured rms fluctuation of 0.17 radians agrees with optical measurements. The high-harmonic approach to measuring CEP stability has the advantage that it is less sensitive to laser intensity fluctuations than are optical methods.

Controlling attosecond angular streaking with second harmonic radiation - Hammond, T. J.; Kim, Kyung Taec; Zhang, Chunmei; Villeneuve, D. M.; Corkum, P. B. (Optics Letters, 2015)
High harmonic generation, which produces a coherent burst of radiation every half cycle of the driving field, has been combined with ultrafast wavefront rotation to create a series of spatially separated attosecond pulses, called the attosecond lighthouse. By adding a coherent second harmonic beam with polarization parallel to the fundamental, we decrease the generating frequency from twice per optical cycle to once. The increased temporal separation increases the pulse contrast. By scanning the carrier envelope phase, we see that the signal is 2π periodic.

Experiments in discriminating similar languages - Goutte, Cyril; Léger, Serge (Proceedings of LT4VarDial, 2015)
We describe the system built by the National Research Council (NRC) Canada for the 2015 shared task on Discriminating between similar languages. The NRC system uses various statistical classifiers trained on character and word ngram features. Predictions rely on a two-stage process: we first predict the language group, then discriminate between languages or variants within the group. This year, we focused on two issues: 1) the ngram generation process, and 2) the handling of the anonymized (“blinded”) Named Entities. Despite the slightly harder experimental conditions this year, our systems achieved an average accuracy of 95.24% (closed task) and 95.65% (open task), ending up second or (close) third on the closed task, and first on the open task.

High-directionality fiber-chip grating coupler with interleaved trenches and subwavelength index-matching structure - Benedikovic, Daniel; Alonso-Ramos, Carlos; Cheben, Pavel; Schmid, Jens H.; Wang, Shurui; Xu, Dan-Xia; Lapointe, Jean; Janz, Siegfried; Halir, Robert; Ortega-Moñux, Alejandro; Wangüemert-Pérez, J. Gonzalo; Molina-Fernández, Iñigo; et al. (Optics Letters, 2015)
We present the first experimental demonstration of a new fiber-chip grating coupler concept that exploits the blazing effect by interleaving the standard full (220 nm) and shallow etch (70 nm) trenches in a 220 nm thick silicon layer. The high directionality is obtained by controlling the separation between the deep and shallow trenches to achieve constructive interference in the upward direction and destructive interference toward the silicon substrate. Utilizing this concept, the grating directionality can be maximized independent of the bottom oxide thickness. The coupler also includes a subwavelength-engineered index-matching region, designed to reduce the reflectivity at the interface between the injection waveguide and the grating. We report a measured fiber-chip coupling efficiency of −1.3  dB , the highest coupling efficiency achieved to date for a surface grating coupler in a 220 nm silicon-on-insulator platform fabricated in a conventional dual-etch process without high-index overlays or bottom mirrors.

Video dosimetry as a method to reduce noise induced hearing loss - Mahn, Jeffrey (Noise Control Engineering Journal, 2015)
Risk perception plays an important role in a person's decision to wear hearing protection to reduce the occurrence of noise induced hearing loss. Therefore, as part of the safety training for a worksite, it is important to educate workers about the potential sources of noise exposure at the worksite so that the workers are aware of the risk. However, teaching a workforce with a range of educational and language skill levels about the risk of noise at the workplace can be a challenge. Instructing people that sources of noise such as machinery are loud may not effectively communicate to people that they could be exposed to noise which is loud enough to damage their hearing. Furthermore, not all of the sources of noise at the worksite may be known or included in the safety training, potentially leading the workers to believe that they are not exposed to high noise emission levels when they actually are at the worksite. This paper describes a measurement method called video dosimetry which combines images taken with a wearable camera with sound pressure levels measured using a dosimeter to create first person videos. The videos show the actions the person wearing the camera was engaged in at the worksite and the corresponding exposure levels. This information can help safety advisors to identify the noise exposure risk while engaged in common actions at the worksite. Furthermore, the videos based on first person images represent an engaging tool for educating at risk workers about the noise exposure levels associated with common activities occurring in the worksite.

Flight test investigation of cabin noise exposure in the Royal Canadian Air Force CH-147F helicopter - Ghinet, Sebastian; Price, Andrew; Wickramasinghe, Viresh; Chen, Yong; Grewal, Anant (INTER-NOISE and NOISE-CON Congress and Conference Proceedings, 2015)

Attosecond lighthouse driven by sub-two-cycle, 1.8 μm laser pulses - Zhang, C.; Vampa, G.; Villeneuve, D.M.; Corkum, P.B. (Journal of Physics B: Atomic, Molecular and Optical Physics, 2015)
We generate space-time coupled attosecond pulse trains with a 1.8 μm wavelength laser pulse using the 'attosecond lighthouse' technique. We show low divergence, spatially well-separated beamlets from low ionization potential gas media. We also find that there is little long trajectory contribution - only the short trajectory contribution is clearly visible for any beamlet. These results open a new route for extending attosecond technology to higher cut off energy and shorter pulse duration. © 2015 IOP Publishing Ltd.
Keywords: Ionization of gases; Laser pulses; Lighthouses; Attosecond pulse trains; Attoseconds; Long trajectories; Low divergence; Pulse durations; Short trajectories; Space time; Wavelength lasers; Ionization potential

Linking high harmonics from gases and solids - Vampa, G.; Hammond, T.J.; Thiré, N.; Schmidt, B.E.; Légaré, F.; McDonald, C.R.; Brabec, T.; Corkum, P.B. (Nature, 2015)
When intense light interacts with an atomic gas, recollision between an ionizing electron and its parent ion creates high-order harmonics of the fundamental laser frequency. This sub-cycle effect generates coherent soft X-rays and attosecond pulses, and provides a means to image molecular orbitals. Recently, high harmonics have been generated from bulk crystals, but what mechanism dominates the emission remains uncertain. To resolve this issue, we adapt measurement methods from gas-phase research to solid zinc oxide driven by mid-infrared laser fields of 0.25 volts per ångström. We find that when we alter the generation process with a second-harmonic beam, the modified harmonic spectrum bears the signature of a generalized recollision between an electron and its associated hole. In addition, we find that solid-state high harmonics are perturbed by fields so weak that they are present in conventional electronic circuits, thus opening a route to integrate electronics with attosecond and high-harmonic technology. Future experiments will permit the band structure of a solid to be tomographically reconstructed. © 2015 Macmillan Publishers Limited. All rights reserved.
Keywords: zinc oxide; electron; electronic equipment; gas phase reaction; harmonic analysis; ion exchange; ionization; laser method; measurement method; oxide; solid; spectrum; tomography; X-ray; zinc; Article; electron; gas; ionization; priority journal; solid

Evaluation of expert-based Q-Matrices predictive quality in matrix factorization models - Durand, Guillaume; Belacel, Nabil; Goutte, Cyril (Design for Teaching and Learning in a Networked World : 10th European Conference on Technology Enhanced Learning, EC-TEL 2015, Toledo, Spain, September 15-18, 2015, Proceedings, 2015)
Matrix factorization techniques are widely used to build collaborative filtering recommender systems. These recommenders aim at discovering latent variables or attributes that are supposed to explain and ultimately predict the interest of users. In cognitive modeling, skills and competencies are considered as key latent attributes to understand and assess student learning. For this purpose, Tatsuoka introduced the concept of Q-matrix to represent the mapping between skills and test items. In this paper we evaluate how predictive expert-created Q-matrices can be when used as a decomposition factor in a matrix factorization recommender. To this end, we developed an evaluation method using cross validation and the weighted least squares algorithm that measures the predictive accuracy of Q-matrices. Results show that expert-made Q-matrices can be reasonably accurate at predicting users success in specific circumstances that are discussed at the end of this paper.
Keywords: Cognitive models; matrix factorization; recommender systems; competency-based learning

High resolution mass spectrometry for quantitative analysis and untargeted screening of algal toxins in mussels and passive samplers - Zendong, Zita; McCarron, Pearse; Herrenknecht, Christine; Sibat, Manoella; Amzil, Zouher; Cole, Richard; Hess, Philipp (Journal of Chromatography A, 2015)
Measurement of marine algal toxins has traditionally focussed on shellfish monitoring while, over the last decade, passive sampling has been introduced as a complementary tool for exploratory studies. Since 2011, liquid chromatography-tandem mass spectrometry (LC-MS/MS) has been adopted as the EU reference method (No. 15/2011) for detection and quantitation of lipophilic toxins. Traditional LC-MS approaches have been based on low-resolution mass spectrometry (LRMS), however, advances in instrument platforms have led to a heightened interest in the use of high-resolution mass spectrometry (HRMS) for toxin detection. This work describes the use of HRMS in combination with passive sampling as a progressive approach to marine algal toxin surveys. Experiments focused on comparison of LRMS and HRMS for determination of a broad range of toxins in shellfish and passive samplers. Matrix effects are an important issue to address in LC-MS; therefore, this phenomenon was evaluated for mussels (Mytilus galloprovincialis) and passive samplers using LRMS (triple quadrupole) and HRMS (quadrupole time-of-flight and Orbitrap) instruments. Matrix-matched calibration solutions containing okadaic acid and dinophysistoxins, pectenotoxin, azaspiracids, yessotoxins, domoic acid, pinnatoxins, gymnodimine A and 13-desmethyl spirolide C were prepared. Similar matrix effects were observed on all instruments types. Most notably, there was ion enhancement for pectenotoxins, okadaic acid/dinophysistoxins on one hand, and ion suppression for yessotoxins on the other. Interestingly, the ion selected for quantitation of PTX2 also influenced the magnitude of matrix effects, with the sodium adduct typically exhibiting less susceptibility to matrix effects than the ammonium adduct. As expected, mussel as a biological matrix, quantitatively produced significantly more matrix effects than passive sampler extracts, irrespective of toxin. Sample dilution was demonstrated as an effective measure to reduce matrix effects for all compounds, and was found to be particularly useful for the non-targeted approach. Limits of detection and method accuracy were comparable between the systems tested, demonstrating the applicability of HRMS as an effective tool for screening and quantitative analysis. HRMS offers the advantage of untargeted analysis, meaning that datasets can be retrospectively analyzed. HRMS (full scan) chromatograms of passive samplers yielded significantly less complex data sets than mussels, and were thus more easily screened for unknowns. Consequently, we recommend the use of HRMS in combination with passive sampling for studies investigating emerging or hitherto uncharacterized toxins.
Keywords: Marine toxins; Matrix effects; Monitoring; Passive sampling; SPATT

Fiber laser deposition of nickel-based superalloys using filler wire feed - Zhang, Y.N.; Cao, X.; Wanjara, P. (ASME Turbo Expo 2015: Turbine Technical Conference and Exposition, Volume 6: Ceramics; Controls, Diagnostics and Instrumentation; Education; Manufacturing Materials and Metallurgy; Honors and Awards, 2015)
In this work, a continuous wave fiber laser welding system was used to deposit nickel-based superalloys Inconel 718 (IN 718) and Waspaloy using filler wire feed sources. The multi-bead and multi-layer deposits that were manufactured were characterized in terms of the macro- and microstructures, defects, and hardness in both the as-deposited and fully heat treated conditions. The tensile properties of the deposits in the heat treated condition were also determined and compared to the existing aerospace materials specifications. Using optimized laser processing parameters, high strength deposits could be manufactured, though minor weld metal liquation cracking for IN718 and strain-age cracking for Waspaloy were present, which compromised slightly the ductility as compared to wrought aerospace specifications for the two alloys. The successful development of the direct laser deposition process using wire feeding indicates the potential of employing the fiber laser technology to manufacture nickel-based superalloy aerospace components.
Keywords: nickel; superalloys; wire; fillers (Materials); fiber lasers

Prediction of burst pressure in multi stage tube hydroforming of aerospace alloys - Saboori, M.; Gholipour, J.; Champliaud, H.; Gakwaya, A.; Savoie, J.; Wanjara, P. (ASME Turbo Expo 2015: Turbine Technical Conference and Exposition, Volume 6: Ceramics; Controls, Diagnostics and Instrumentation; Education; Manufacturing Materials and Metallurgy; Honors and Awards, 2015)
Bursting, an irreversible failure in tube hydroforming (THF), results mainly from the local plastic instabilities that occur when the biaxial stresses imparted during the process exceed the forming limit strains of the material. To predict the burst pressure, Oyane’s and Brozzo’s decoupled ductile fracture criteria were implemented as user material models in a dynamic nonlinear commercial 3D finite element (FE) software, Ls-Dyna. THF of a round to V-shape was selected as a generic representative of an aerospace component for the FE simulations and experimental trials. To validate the simulation results, THF experiments up to bursting were carried out using Inconel 718 (IN 718) tubes with a thickness of 0.9 mm to measure the internal pressures during the process. When comparing the experimental and simulation results, the burst pressure predicated based on Oyane’s decoupled damage criterion was found to agree better with the measured data for IN 718 than Brozzo’s fracture criterion.
Keywords: pressure; alloys; aerospace industry

The possible roles of the dentate granule cell’s leptin and other ciliary receptors in Alzheimer’s neuropathology - Whitfield, James F.; Chiarini, Anna; Dal Prà, Ilaria; Armato, Ubaldo; Chakravarthy, Balu (Cells, 2015)
Dentate-gyral granule cells in the hippocampus plus dentate gyrus memory-recording/retrieving machine, unlike most other neurons in the brain, are continuously being generated in the adult brain with the important task of separating overlapping patterns of data streaming in from the outside world via the entorhinal cortex. This “adult neurogenesis” is driven by tools in the mature granule cell’s cilium. Here we report our discovery of leptin’s LepRb receptor in this cilium. In addition, we discuss how ciliary LepRb signaling might be involved with ciliary p75NTR and SSTR3 receptors in adult neurogenesis and memory formation as well as attenuation of Alzheimer’s neuropathology by reducing the production of its toxic amyloid-β-derived drivers.
Keywords: adult neurogenesis; Alzheimer’s disease; amyloid-β; amyloid-β oligomers; ciliary LepRb; dentate gyrus; hippocampus; hyperphosphorylated tau; leptin; memory formation; p75NTR; somatostatin receptor

Direct interspecies electron transfer in anaerobic digestion: a review - Dubé, Charles-David; Guiot, Serge R. (Biogas Science and Technology, 2015)
Direct interspecies electrons transfer (DIET) is a syntrophic metabolism in which free electrons flow from one cell to another without being shuttled by reduced molecules such as molecular hydrogen or formate. As more and more microorganisms show a capacity for electron exchange, either to export or import them, it becomes obvious that DIET is a syntrophic metabolism that is much more present in nature than previously thought. This article reviews literature related to DIET, specifically in reference to anaerobic digestion. Anaerobic granular sludge, a biofilm, is a specialized microenvironment where syntrophic bacterial and archaeal organisms grow together in close proximity. Exoelectrogenic bacteria degrading organic substrates or intermediates need an electron sink and electrotrophic methanogens represent perfect partners to assimilate those electrons and produce methane. The granule extracellular polymeric substances by making the biofilm matrix more conductive, play a role as electrons carrier in DIET.
Keywords: Anaerobic digestion; Direct interspecies electron transfer (DIET); Granular sludge; Extracellular polymeric substance (EPS); Exoelectrogenic bacteria; Electrotrophic methanogen

Evaluating probability of detection using an airborne multi-sensor system for search and rescue operations: a human factors flight test evaluation - Strang, Turner; Craig, Gregory (Greg); Thomas, Russell; Soffer, Raymond J.; Roy, Simon; Brown, Anthony; Keillor, Jocelyn (2015)
A large scale airborne experiment was performed in order to evaluate the visual detection performance of operators while using an advanced sensor system for Search and Rescue tasks. Such an evaluation is timely due to the Government of Canada’s intent to replace its aging Fixed-Wing Search and Rescue aircraft with a more advanced, sensor-equipped fleet. The experiment involved 22 hours of night time flight trials using an infrared sensor system performing a search pattern over an idealized trial range. Ninety search objects resembling downed, fixed wing, general aviation aircraft were placed within a 21 km by 13 km grassland area to compose the trial range. The rate of detection was found to be 81.8% based on 978 total detection opportunities, across two sensor operators.
Keywords: airborne experiment; sensor system; Fixed-Wing; Search and Rescue aircraft

On the radiative properties of soot aggregates part 2: effects of coating - Liu, Fengshan; Yon, Jérôme; Bescond, Alexandre (Journal of quantitative spectroscopy and radiative transfer, 2015)
The effects of weakly absorbing material coating on soot have attracted considerable research attention in recent years due to the significant influence of such coating on soot radiative properties and the large differences predicted by different numerical models. Soot aggregates were first numerically generated using the diffusion limited cluster aggregation algorithm to produce fractal aggregates formed by log-normally distributed polydisperse spherical primary particles in point-touch. These aggregates were then processed by adding a certain amount of primary particle overlapping and necking to simulate the soot morphology observed from transmission electron microscopy images. After this process, a layer of WAM coating of different thicknesses was added to these more realistic soot aggregates. The radiative properties of these coated soot aggregates over the spectral range of 266–1064 nm were calculated by the discrete dipole approximation (DDA) using the spectrally dependent refractive index of soot for four aggregates containing Np=1, 20, 51 and 96 primary particles. The considered coating thicknesses range from 0% (no coating) up to 100% coating in terms of the primary particle diameter. Coating enhances both the particle absorption and scattering cross sections, with much stronger enhancement to the scattering one, as well as the asymmetry factor and the single scattering albedo. The absorption enhancement is stronger in the UV than in the visible and the near infrared. The simple corrections to the Rayleigh–Debye–Gans fractal aggregates theory for uncoated soot aggregates are found not working for coated soot aggregates. The core–shell model significantly overestimates the absorption enhancement by coating in the visible and the near infrared compared to the DDA results of the coated soot particle. Treating an externally coated soot aggregate as an aggregate formed by individually coated primary particles significantly underestimates the absorption enhancement by coating in the visible and the near infrared.
Keywords: radiativeproperties; coated sootaggregates; DDA; RDG-FA

Load path optimization in tube hydroforming - Mojarad, S.; Champliaud, H.; Gholipour, J.; Savoie, J.; Wanjara, P. (Canadian Aeronautics and Space Journal, 2015)
The goal of this work was to identify the optimum combination of the main process parameters, i.e., the internal pressure and end feeding (load path), for tube hydroforming to minimize the thickness reduction, while satisfying the failure constraint defined by the forming limit diagram of the material. To perform process design optimization with minimum experimentation, the LS-OPT software was utilized in combination with a finite element model (FEM) that simulated a round to square tube hydroforming (THF) process for stainless steel 321 in LS-DYNA. The load path obtained through the optimization procedure was applied to the THF process and the tube expansion and the thickness results obtained from the FEM were compared with the experimental results in the critical regions of the hydroformed tube.

Process operational windows and industrialization scenarios for assembly or large aluminium structures by robotic friction stir welding - Wanjara, P.; Monsarrat, B.; Larose, S. (Canadian Aeronautics and Space Journal, 2015)
In this work, friction stir welding (FSW) of 3.18 mm thick AA6061-T6 sheets in the butt- and lap-joint configuration was investigated with the objective of industrializing the process using low-cost serial industrial robots. The influence of weld pitch on the welding defects, microstructure, hardness, and bend performance of butt and lap welds was examined to identify process operational windows for both joint types. In parallel with these trials, a methodology based on kinetostatic analysis was developed to identify and evaluate viable robotized scenarios for FSW. On the basis of the experimental FSW process development results, this methodology was then applied to identify optimized FSW scenarios for the fabrication of large integrated AA6061 structural components with stringer-to-skin and skin-to-skin joints. Candidate workcell layouts are also presented.

Residual stresses and tensile properties of friction stir welded AZ31B-H24 magnesium alloy in lap configuration - Naik, Bhukya Srinivasa; Cao, Xinjin; Wanjara, Priti; Friedman, Jacob; Chen, Daolun (Metallurgical and Materials Transactions B, 2015)
AZ31B-H24 Mg alloy sheets with a thickness of 2 mm were friction stir welded in lap configuration using two tool rotational rates of 1000 and 1500 rpm and two welding speeds of 10 and 20 mm/s. The residual stresses in the longitudinal and transverse directions of the weldments were determined using X-ray diffraction. The shear tensile behavior of the lap joints was evaluated at low [233 K (−40 °C)], room [298 K (25 °C)], and elevated [453 K (180 °C)] temperatures. The failure load was highest for the lower heat input condition that was obtained at a tool rotational rate of 1000 rpm and a welding speed of 20 mm/s for all the test temperatures, due to the smaller hooking height, larger effective sheet thickness, and lower tensile residual stresses, as compared to the other two welding conditions that were conducted at a higher tool rotational rate or lower welding speed. The lap joints usually fractured on the advancing side of the top sheet near the interface between the thermo-mechanically affected zone and the stir zone. Elevated temperature testing of the weld assembled at a tool rotational rate of 1000 rpm and a welding speed of 20 mm/s led to the failure along the sheet interface in shear fracture mode due to the high integrity of the joint that exhibited large plastic deformation and higher total energy absorption.

Hybrid laser-arc welding of cast martensitic stainless steel ca6nm: post-weld tempered microstructure and mechanical properties - Mirakhorli, F.; Cao, X.; Pham, X-T.; Wanjara, P.; Fihey, J.L. (Proceedings of COM 2015, 2015)
Single-pass hybrid laser-arc welding of 10-mm thick cast plates of CA6NM, a low carbon martensitic stainless steel, was carried out in butt joint configuration using a continuous wave fiber laser at its maximum power of 5.2 kW over welding speeds ranging from 0.75 m/min to 1.2 m/min.
Keywords: Hybrid laser-arc welding (HLAW); Cast stainless steel; Post-weld heat treatment; Microstructure; Mechanical properties

Corrigendum to the 2014 NRC determination of Planck’s constant - Sanchez, C. A.; Wood, B. M.; Green, R. G.; Liard, J. O.; Inglis, D. (Metrologia, 2015)

Direct determination of trace antimony in natural waters by photochemical vapor generation ICPMS: method optimization and comparison of quantitation strategies - Gao, Ying; Sturgeon, Ralph E.; Mester, Zoltán; Hou, Xiandeng; Zheng, Chengbin; Yang, Lu (Analytical Chemistry, 2015)
A novel and sensitive approach for the accurate determination of Sb in natural waters is described using photochemical vapor generation (PVG) coupled with inductively coupled plasma mass spectrometry (ICPMS) for detection. Utilizing a unique flow-through photochemical reactor capable of subjecting the samples to deep UV (185 nm) radiation, generation efficiency was found to be independent of whether Sb(III), Sb(V) or organometallic species [trimethyltantimony(V)dibromine, TMSb(V)], eliminating the shortcoming of Sb species depended sensitivity encountered during direct solution nebulization by ICPMS. Furthermore, the potentially severe matrix effect from seawater was efficiently eliminated by using a mixture of 5% (v/v) formic and 15% acetic acids (v/v) as the photochemical reductant, making direct determination of Sb in seawater feasible. The proposed method provides a 15-fold improvement in sensitivity over direct solution nebulization. A method detection limit of 0.0006 ng g-1 based on external calibration was obtained (0.0002 ng g-1 for isotope dilution), yielding a 15-fold improvement over that for direct solution nebulization. Accuracy is demonstrated by analysis of two water Certified Reference Materials (CRMs, e. g., SLRS-6 and NIST 1640a) with satisfying results. In addition, spike recoveries of 100.6 ± 5.5% and 100.8 ± 3.8% (SD, n=3) were obtained for NASS-6 and CASS-5 seawater CRMs, respectively, since no certified values for Sb has been established for these materials. The performance of several calibration strategies, including double isotope dilution (ID), multiple and single point gravimetric standard additions with internal standardization as well as multiple and single point gravimetric standard additions alone was examined. High precision of determination of Sb in four natural water samples (0.51 to 1.4%) was realized based on ID calibration, whereas one point gravimetric standard addition calibration with internal standardization provided precisions of 1.6 and 3.3% at 0.22 and 0.44 ng g-1 levels, respectively, in seawater.

Beyond phage display: non-traditional applications of the filamentous bacteriophage as a vaccine carrier, therapeutic biologic, and bioconjugation scaffold - Henry, Kevin A.; Arbabi-Ghahroudi, Mehdi; Scott, Jamie K. (Frontiers in Microbiology, 2015)
For the past 25 years, phage display technology has been an invaluable tool for studies of protein-protein interactions. However, the inherent biological, biochemical, and biophysical properties of filamentous bacteriophage, as well as the ease of its genetic manipulation, also make it an attractive platform outside the traditional phage display canon. This review will focus on the unique properties of the filamentous bacteriophage and highlight its diverse applications in current research. Particular emphases are placed on: (i) the advantages of the phage as a vaccine carrier, including its high immunogenicity, relative antigenic simplicity and ability to activate a range of immune responses, (ii) the phage's potential as a prophylactic and therapeutic agent for infectious and chronic diseases, (iii) the regularity of the virion major coat protein lattice, which enables a variety of bioconjugation and surface chemistry applications, particularly in nanomaterials, and (iv) the phage's large population sizes and fast generation times, which make it an excellent model system for directed protein evolution. Despite their ubiquity in the biosphere, metagenomics work is just beginning to explore the ecology of filamentous and non-filamentous phage, and their role in the evolution of bacterial populations. Thus, the filamentous phage represents a robust, inexpensive, and versatile microorganism whose bioengineering applications continue to expand in new directions, although its limitations in some spheres impose obstacles to its widespread adoption and use.
Keywords: filamentous phage; vaccine; therapeutic; antimicrobial; bioconjugation

Porous Ni0.14Mn0.86O1.43 hollow microspheres as high-performing anodes for lithium-ion batteries - Ma, Zhong; Yuan, Xianxia; Li, Lin; Ma, Zi-Feng; Zhang, Lei; Mai, Liqiang; Zhang, Jiujun (Journal of power sources, 2015)
A uniformly dispersed bi-component nanocompotise of transition metal oxide (Mn2O3)/mixed transition metal oxide (NiMn2O4) with a porous and hollow microspheric sructure has been successfully prepared with a facile method based on the complexation between Ni2+ and NH3. The obtained nanocomposite of 0.29 Mn2O3/0.14 NiMn2O4, expressed as Ni0.14Mn0.86O1.43, with nanometer-sized building blocks exhibits a high reversible capacity of 615 mA h g−1, which is about 90% of theoretical value at the current density of 800 mA h g−1, and long lifespan with retained capacities of 553 and 408 mA h g−1 after 150 cycles at 200 and 800 mA g−1, respectively, as an anode material for lithium-ion batteries.
Keywords: lithium ion batteries; anode; Ni0.14Mn0.86O1.43; porous and hollow microspheres

Detection, identification and occurrence of thiotetronic acids in drinking water from underground sources by ESI-FAIMS-QTOF-MS - Lyczko, Jadwiga; Beach, Daniel G.; Gabryelski, Wojciech (Analytical chemistry, 2015)
This paper demonstrates that electrospray ionization (ESI) with differential ion mobility spectroscopy (FAIMS) and “soft” mass spectrometry (MS) provide unique analytical capabilities that led to the discovery of sulfur-containing polar congeners of thiotetronic acid (TA) in drinking water from underground sources in Canada and the United States. Polar TAs accumulate in underground aquifers and appear to be the most abundant class of organic compounds in bottled water, but cannot be detected by conventional mass spectrometry methods. We show that normally stable TAs are converted into very reactive ions in ESI which have to be analyzed using special conditions in ESI-FAIMS-MS to avoid extensive dissociation and ion/molecule reactions. De novo identification of 10 TAs was accomplished by the comparative tandem mass spectrometry analysis of authentic TA derivatives from groundwater samples and synthetic TA analogues prepared for this study. We present highlights of gas phase ion chemistry of polar TAs to explain their unique properties and reactivity. TA derivatives were originally isolated from soil bacteria and are of interest in the pharmaceutical industry due to their potent activity against a broad spectrum of pathogenic bacteria and negligible toxicity to mammals. We suspect that TAs are natural disinfection agents protecting groundwater from bacterial contamination, but these compound undergo modifications or decompose during an ozonation water treatment.

Selective quantification of the neurotoxin BMAA by use of hydrophilic-interaction liquid chromatography–differential mobility spectrometry–tandem mass spectrometry (HILIC–DMS–MS–MS) - Beach, Daniel G.; Kerrin, Elliott S.; Quilliam, Michael Arthur (Analytical and bioanalytical chemistry, 2015)
The neurotoxin β-N-methylamino-l-alanine (BMAA) has been reported in cyanobacteria and shellfish, raising concerns about widespread human exposure. However, inconsistent results for BMAA analysis have led to controversy. Liquid chromatography–tandem mass spectrometry (LC–MS–MS) is the most appropriate method for analysis of BMAA, but the risk of interference from isomers, other sample components, and the electrospray background is still present. We have investigated differential mobility spectrometry (DMS) as an ion filter to improve selectivity in the hydrophilic interaction liquid chromatographic (HILIC)–MS–MS determination of BMAA. We obtained standards for two BMAA isomers not previously analyzed by HILIC–MS, β-amino-N-methylalanine and 3,4-diaminobutanoic acid, and the typically used 2,4-diaminobutanoic acid and N-(2-aminoethyl)glycine. DMS separation of BMAA from these isomers was achieved and optimized conditions were used to develop a sensitive and highly selective multidimensional HILIC–DMS–MS–MS method. This work revealed current technical limitations of DMS for trace quantification, and practical solutions were implemented. Accurate control of low levels of DMS carrier gas modifier was essential, but required external metering. The linearity of our optimized method was excellent from 0.01 to 6 μmol L−1. The instrumental LOD was 0.4 pg BMAA injected on-column and the estimated method LOD was 20 ng g−1 dry weight for BMAA in sample matrix. The method was used to analyze cycad plant tissue, a cyanobacterial reference material, and mussel tissues, by use of isotope-dilution quantification with deuterated BMAA. This confirmed the presence of BMAA and several of its isomers in cycad and mussel tissues, including commercially available mussel tissue reference materials certified for other biotoxins.

Thoughts on the proposed SI units - Ross, Carl (Physics Today, 2015)
David Newell’s article (Physics Today, July 2014, page 35) on proposed changes to the International System of Units (SI) was an enjoyable read. The author was able to condense the key points of a rather complicated subject into a few pages. As he pointed out, the SI has undergone continuous improvement over its long history, so the focus on an improved standard for mass seems well justified. However, I am not convinced that the changes in the base quantities, as illustrated in tables 1 and 2 of Newell’s article, are a wise choice.
Keywords: International System of Units; SI

L’histoire de l'univers à ce jour - Tapping, Ken (L'astronomie au gré des saisons, 2015)
Écrire l’histoire de l’Univers est un travail inachevé. L’état actuel des connaissances est le résultat de siècles de découvertes par des scientifiques de tous les pays. Même s’il nous reste encore beaucoup à apprendre et qu’il est peu probable que nous parvenions à déchiffrer toute la suite des évènements qui se sont produits, on ne peut que s’étonner de l’ampleur des découvertes effectuées à ce jour. Voici l’état actuel des connaissances que nous possédons.
Keywords: univers et galaxies

The story so far - Tapping, Ken (Skygazing: Astronomy through the seasons, 2015)
Outlining the history of the universe is definitely a work in progress. Where we are now is the result of centuries of work by scientists all over the world. Although we have we have much more to learn and it is doubtful that we will ever know the whole story, it really is surprising how much we have managed to find out. Here is the story so far.
Keywords: universe and galaxies

Effect of drive cycle and gasoline particulate filter on the size and morphology of soot particles emitted from a gasoline-direct-injection vehicle - Saffaripour, Meghdad; Chan, Tak W.; Liu, Fengshan; Thomson, Kevin; Smallwood, Gregory J.; Kubsh, Joseph; Brezny, Rasto (Environmental science and technology, 2015)
The size and morphology of particulate matter emitted from a light-duty gasoline-direct-injection (GDI) vehicle, over the FTP-75 and US06 transient drive cycles, have been characterized by transmission-electron-microscope (TEM) image analysis. To investigate the impact of gasoline particulate filters on particulate-matter emission, the results for the stock-GDI vehicle, i.e., the vehicle in its original configuration, have been compared to the results for the same vehicle equipped with a catalyzed gasoline particulate filter (GPF). The stock-GDI vehicle emits graphitized fractal-like aggregates over all driving conditions. The mean projected area-equivalent diameter of these aggregates is in the 78.4‒88.4 nm range and the mean diameter of primary particles varies between 24.6 and 26.6 nm. Post-GPF particles emitted over the US06 cycle appear to have an amorphous structure, and a large number of nucleation-mode particles, depicted as low-contrast ultrafine droplets, are observed in TEM images. This indicates the emission of a substantial amount of semivolatile material during the US06 cycle, most likely generated by the incomplete combustion of accumulated soot in the GPF during regeneration. The size of primary particles and soot aggregates does not vary significantly by implementing the GPF over the FTP-75 cycle; however, particles emitted by the GPF-equipped vehicle over the US06 cycle are about 20% larger than those emitted by the stock-GDI vehicle. This may be attributed to condensation of large amounts of organic material on soot aggregates. High-contrast spots, most likely solid nonvolatile cores, are observed within many of the nucleation-mode particles emitted over the US06 cycle by the GPF-equipped vehicle. These cores are either generated inside the engine or depict incipient soot particles which are partially carbonized in the exhaust line. The effect of drive cycle and the GPF on the fractal parameters of particles, such as fractal dimension and fractal prefactor, is insignificant.
Keywords: GDI vehicle; gasoline particulate filter; soot morphology; nucleation-mode particles; transmission electron microscopy

Dual-beam laser interferometer for the accurate determination of rocking motion - Wu, Lixue (International Congress on Sound and Vibration, 2015)
Most primary accelerometer calibrations, or absolute calibrations, are currently performed using laser interferometry under the guideline of the international standard (ISO 16063-11, 1999). Due to rocking motion of vibration shakers, however, the measured accelerometer sensitivities at different laser incidence points can vary for up to a few percent. For the accurate determination of rocking motion on the effect of calibration results, a dual-beam laser interferometer was developed at National Research Council Canada. This paper describes the method and apparatus for simultaneous measurements of displacement amplitudes and its distribution along a straight line using a dual-beam laser interferometer. The interferometer directs two beams that are incident at distinct points on a moving surface. A separation distance between the two sensing spots on the moving surface is provided. In the present setup, the separation distance is adjustable along a straight line. This feature allows the interferometer to measure the displacement distribution along a line. To reduce the measurement uncertainty a model-based estimation is used to accurately determine the displacement amplitudes from the current outputs of photo diodes. This paper also presents the measurement results showing the difference of displacement amplitudes due to rocking motion. The system may also be used for direct quantitative study of moving surface deformation during vibration.
Keywords: Accelerometers; Calibration; Displacement measurement; Interferometry; Laser interferometry; Uncertainty analysis; Displacement amplitudes; Displacement distribution; International standards; Measurement uncertainty; Model-based estimation; National Research Council; Separation distances; Simultaneous measurement; Interferometers

Predictive model evaluation for PHM - Yang, Chunsheng; Zou, Yanni; Liu, Jie; Mulligan, Kyle R. (International Journal of Prognostics and Health Management, 2015)
In the past decades, machine learning techniques or algorithms, particularly, classifiers have been widely applied to various real-world applications such as PHM. In developing high-performance classifiers, or machine learning-based models, i.e. predictive model for PHM, the predictive model evaluation remains a challenge. Generic methods such as accuracy may not fully meet the needs of models evaluation for prognostic applications. This paper addresses this issue from the point of view of PHM systems. Generic methods are first reviewed while outlining their limitations or deficiencies with respect to PHM. Then, two approaches developed for evaluating predictive models are presented with emphasis on specificities and requirements of PHM. A case of real prognostic application is studied to demonstrate the usefulness of two proposed methods for predictive model evaluation. We argue that predictive models for PHM must be evaluated not only using generic methods, but also domain-oriented approaches in order to deploy the models in real-world applications.
Keywords: Machine Learning Algorithms; Generic Methods; binary classifier; prognostics and health management (PHM); prognostics; Time to Failure; Predictive Models Evaluation

Effects of interface roughness scattering on device performance of indirectly pumped terahertz quantum cascade lasers - Razavipour, Seyed Ghasem; Dupont, Emmanuel; Wasilewski, Zbig R.; Ban, Dayan (2015)
The impacts of interface roughness (IR) scattering on device performance of indirectly-pumped (IDP) terahertz quantum cascade lasers are studied. Three different active region designs with almost the same lasing frequency at threshold and comparable oscillator strength are experimentally investigated and the measurement data are analyzed and compared with numerical simulation. The simulation results show that all structures suffer from the detrimental effect of intersubband roughness scattering in terms of threshold current density, and probably operating temperature. The intrasubband IR scattering time could also to be a limiting factor in the IDP structures due to the employed high energetic barrier.

Fatigue disbond growth for an adhesively bonded composite joint under mixed mode I/II loading - Li, Chun; Teng, Tim; Wan, Zhong Yi; Young, Neell G.; Li, Gang; Rans, Calvin; LaPlante, Gabriel (SAMPE 2014 Seattle, 2015)
Adhesive bonding has been increasingly used for part manufacturing and repair of composite aircraft structures. This work focuses on static and fatigue performance of bonded composite joints under mixed mode I/II loading. A series of experiments was performed on bonded composite joint specimens with load mixities (GII/G) of 0, 0.2, 0.4, 0.6 and 0.8. The experimental results show a change in critical fracture toughness and fatigue disbond growth characteristics with load mixity. Failure analysis indicates that these changes are not only attributable to the loading conditions, but they are also affected by failure modes
Keywords: Aircraft manufacture; Airframes; Failure modes; Fracture toughness; Joints (structural components); Repair; Adhesively bonded composite joints; Bonded composite joints; Composite aircraft structure; Critical fracture toughness; Fatigue performance; Growth characteristic; Loading condition; Part manufacturing

Isolation and synthetic diversification of jadomycin 4-amino-l-phenylalanine - Martinez-Farina, Camilo F.; Robertson, Andrew W.; Yin, Huimin; Monro, Susan; McFarland, Sherri A.; Syvitski, Raymond T.; Jakeman, David L. (Journal of Natural Products, 2015)
Streptomyces venezuelae ISP5230 was grown in the presence of phenylalanine analogues to observe whether they could be incorporated into novel jadomycin structures. It was found that the bacteria successfully produced jadomycins incorporating 4-aminophenylalanine enantiomers. Upon isolation and characterization of jadomycin 4-amino-l-phenylalanine (1), it was synthetically derivatized, using activated succinimidyl esters, to yield a small jadomycin amide library. These are the first examples of oxazolone-ring-containing jadomycins that have incorporated an amino functionality subsequently used for derivatization.

Stearidonic acid-enriched flax oil reduces the growth of human breast cancer in vitro and in vivo - Subedi, K.; Yu, H.-M.; Newell, M.; Weselake, R.J.; Meesapyodsuk, D.; Qiu, X.; Shah, S.; Field, C.J. (Breast Cancer Research and Treatment, 2015)
The 20 and 22 carbon n-3 long-chain polyunsaturated fatty acids (LCPUFA) inhibit the growth of tumors in vitro and in animal models, but less is known about the 18 carbon n-3, stearidonic acid (SDA). This study aimed to establish and determine a mechanism for the anti-cancer activity of SDA-enriched oil (SO). SO (26 % of lipid) was produced by genetically engineering flax and used to treat human tumorigenic (MDA-MB-231, MCF-7) and non-tumorigenic (MCF-12A) breast cells. Nu/nu mice bearing MDA-MB-231 tumor were fed SO (SDA, 4 % of fat). Cell/tumor growth, phospholipid (PL) composition, apoptosis, CD95, and pro-apoptotic molecules were determined in SO-treated cells/tumors. Compared to a control lipid mixture, SO reduced (p < 0.05) the number of tumorigenic, but not MCF-12A cells, and resulted in higher concentration of most of the n-3 fatty acids in PL of all cells (p < 0.05). However, docosapentaenoic acid increased only in tumorigenic cells (p < 0.05). SO diet decreased tumor growth and resulted in more n-3 LCPUFA, including DPA and less arachidonic acid (AA) levels in major tumor PL (p < 0.05). Treatment of MDA-MB-231 cells/tumors with SO resulted in more apoptotic cells (in tumors) and in vivo and in vitro, more CD95+ positive cells and a higher expression of apoptotic molecules caspase-10, Bad, or Bid (p < 0.05). Supplementing SO alters total PL and PL classes by increasing membrane content of n-3 LCPUFA and lowering AA (in vivo), which is associated with increased CD95-mediated apoptosis, thereby suggesting a possible mechanism for reduce tumor survival.
Keywords: MDA-MB-231; MCF-7; MCF-12A; Mammary tumor; Polyunsaturated fatty acid; Phospholipids

Beyond free: open learning in a networked world - Downes, S. (Distance Education in China, 2015)
Translation by Junhong Xiao
Keywords: open learning

Beyond institutions: personal learning in a networked world - Downes, S. (Distance Education in China, 2015)
Translation by Junhong Xiao
Keywords: learning models

Beyond assessment: recognizing achievement in a networked world - Downes, S. (Distance Education in China, 2015)
Translation by Junhong Xiao
Keywords: online learning; achievement; assessment

A probabilistic model for knowledge component naming - Goutte, Cyril; Léger, Serge; Durand, Guillaume (Proceedings of the 8th International Conference on Data Mining, 2015)
Recent years have seen significant advances in automatic identifcation of the Q-matrix necessary for cognitive diagnostic assessment. As data-driven approaches are introduced to identify latent knowledge components (KC) based on observed student performance, it becomes crucial to describe and interpret these latent KCs. We address the problem of naming knowledge components using keyword automatically extracted from item text. Our approach identifies the most discriminative keywords based on a simple probabilistic model. We show this is effective on a dataset from the PSLC datashop, outperforming baselines and retrieving unknown skill labels in nearly 50% of cases.

Towards automatic description of knowledge components - Goutte, Cyril; Durand, Guillaume; Léger, Serge (Proceedings of the Tenth Workshop on Innovative Use of NLP for Building Educational Applications, 2015)
A key aspect of cognitive diagnostic models is the specification of the Q-matrix associating the items and some underlying student attributes. In many data-driven approaches, test items are mapped to the underlying, latent knowledge components (KC) based on observed student performance, and with little or no input from human experts. As a result, these latent skills typically focus on modeling the data accurately, but may be hard to describe and interpret. In this paper, we focus on the problem of describing these knowledge components. Using a simple probabilistic model, we extract, from the text of the test items, some keywords that are most relevant to each KC. On a small dataset from the PSLC datashop, we show that this is surprisingly effective, retrieving unknown skill labels in close to 50% of cases. We also show that our method clearly outperforms typical baselines in specificity and diversity.

Analyzing student inquiry data using process discovery and sequence classification - Emond, Bruno; Buffett, Scott (Proceedings of the 8th International Conference on Data Mining, 2015)
This paper reports on results of applying process discovery mining and sequence classifcation mining techniques to a data set of semi-structured learning activities. The main research objective is to advance educational data mining to model and support self-regulated learning in heterogeneous environments of learning content, activities, and social networks. As an example of our current research efforts, we applied temporal data mining analysis techniques to a PSLC DataShop data set [17, 18, 19, 20]. First, we show that process mining techniques allow for discovery of learning processes from student behaviours. Second, sequential pattern mining is used to classify students according to skill. Our results show that considering sequences of activities as opposed to single events improved classifcation by up to 230%.

Measurement of the airborne and resonant radiation efficiencies - Mahn, Jeffery; Hoeller, Christoph; Zeitler, Berndt (The 22nd International Congress on Sound and Vibration, ICSV 22 Florence, Italy, 12-16 July 2015, 2015)
The determination of the total and the resonant components of the radiation efficiency have been shown to be necessary for the accurate prediction of the resonant sound reduction index for the calculation of the flanking sound reduction according to a proposed revision of the ISO 15712 series. However, the total and the resonant radiation efficiency of lightweight building elements can be difficult to determine experimentally and there is often confusion about what has actually been measured. In this paper, measurements in the laboratory of the components of the radiation efficiency are presented for different lightweight walls. The measurements were made using both sound intensity and sound pressure to determine the sound power radiated from the walls. Different methods of excitation are compared. A standard for the measurement of the components of the radiation efficiency of lightweight walls is necessary.

Comparison of theoretical predictions of radiation efficiency with experimental measurements - Davy, John; Mahn, Jeffery; Krajči, Luboš; Wareing, Robin; Pearse, John (Proceedings of the 22nd International Congress on Sound and Vibration (ICSV22 2015), 2015)
The measurement and prediction of radiation efficiency is important in many areas of acoustics. It has recently become an even more important topic, because the radiation efficiency needs to be known in order to predict the flanking sound transmission using EN12354 when the frequency is below the critical frequency of one or more of the walls involved in the flanking sound transmission path. This prediction is more difficult for lightweight walls because they usually consist of a complex construction. This paper uses Maidanik’s and Leppington’s approximate formulae to predict the resonant radiation efficiency of a finite size panel and Davy’s approximate formulae to predict the forced radiation efficiency when a finite size panel is excited by a diffuse sound field. The radiation efficiency of an infinite size panel excited by a point or line force is predicted using Heckl’s approximate formulae. The damping loss factor of the panel is needed in order to calculate the magnitude of the resonant vibration of the panel relative to the point or line near field vibration of the panel or relative to the vibration of the panel forced by an incident diffuse sound field on one side of the panel. The theories used in this paper assume that the finite size panel is mounted in an infinite baffle and the predictions are for the power radiated on one side of the panel. This paper compares the theoretical predictions of radiation efficiency with experimental measurements made in sound insulation laboratories. The surface velocities of the panels were measured with a laser velocimeter or accelerometers. The sound power radiated on one side of the panel was determined using sound intensity measurements or reverberation room measurements of sound power that utilised sound pressure measurements and reverberation time measurements.

Novel quercetin-3-O-glucoside eicosapentaenoic acid ester ameliorates inflammation and hyperlipidemia - Sekhon-Loodu, Satvir; Ziaullah, Ziaullah; Rupasinghe, H.P. Vasantha; Wang, Yanwen; Kulka, Marianna; Shahidi, Fereidoon (Inflammopharmacology, 2015)
Quercetin, a major flavonol, present abundantly in apples and onions, is widely studied for ameliorating metabolic syndrome abnormalities. However, quercetin is mainly present in plant food in the form of quercetin glycosides and has been reported for poor gastrointestinal absorption. The present study was designed with the purpose of imparting a lipophilic property to quercetin-3-O-glucoside (QG) by its acylation with eicosapentaenoic acid (EPA) and to study the influence of eicosapentaenoic acid ester of quercetin-3-O-glucoside (QE) on hyperlipidemia and inflammation in vivo and in vitro. QE was more effective in reducing the production of tumor necrosis factor-alpha (TNF-α), prostaglandin 2 (PGE2), cyclo-oxygenase (COX)-2 levels and nuclear expression of nuclear factor-kappa B (NF-кB) compared to the parent compounds (QG and EPA) and commercial drugs, after lipopolysaccharides (LPS) induced inflammation in THP-1 derived macrophages. Serum high-density lipoprotein (HDL)-cholesterol was significantly higher and hepatic total cholesterol concentration was lower in the rats fed high-fat diet supplemented with QE, compared to the high-fat diet with inflammation (HFL). The serum concentrations of C-reactive protein (CRP), interleukin (IL)-6, and interferon-gamma (IFN-γ) were significantly lower in QE treatment group than HFL group. EPA conjugated flavonol, QE, had significant anti-inflammatory and hypolipidemic properties and may be effective for the treatment of obesity-related disorders.
Keywords: flavonols; eicosapentaenoic acid ester; cytokines; hyperlipidemia; inflammation; macrophage

Prediction and control of drilling-induced damage in fibre-reinforced polymers using a new hybrid force and temperature modelling approach - Sadek, A.; Shi, B.; Meshreki, M.; Duquesne, J.; Attia, M. H. (CIRP Annals: Manufacturing Technology, 2015)
Reliable force and temperature prediction in drilling of fibre-reinforced polymers (FRPs) is the key to controlling drilling-induced damage. A novel hybrid analytical-numerical model is developed to capture time-varying forces and temperatures during transient and steady-state drilling of FRPs. Although the generalized force model is calibrated using a unidirectional FRP material and a single tool type, it can apply to wide ranges of drilling conditions, tool geometries, and laminate configurations. A methodology to define the damage criteria is presented. Extensive experimental validation confirmed the accurate predictions of delamination and thermal damage; such performance cannot be achieved by any available model.
Keywords: Drilling; Composite; Defect

Impact of the laurina mutation in Coffea arabica L. on semi-dwarfism, cell number and hormonal profiles in hypocotyls of seedlings growing under daylight - Adler, Sophie; Verdeil, Jean-Luc; Conejero, Geneviève; Zaharia, Irina L.; Sarrazin, Amélie; Hoareau, Julien; Fock-Bastide, Isabelle; Noirot, Michel (Trees: Structure and Function, 2015)
Coffea arabica ‘Laurina’ is a natural mutant of Coffea arabica ‘Bourbon’ (B) and is known under the trade name ‘Bourbon Pointu’ (BP). Under daylight, the laurina mutation leads to pleiotropic effects, including semi-dwarf hypocotyls. At the opposite, semi-dwarfism of BP seedlings disappeared under darkness conditions. The first step was to describe the morphological impact of the mutation in seedlings growing under daylight by comparison with seedlings growing under darkness. As the hypocotyl length was mainly affected, the second step was to investigate histological modifications in the organ comparing B and BP seedlings growing under daylight. Result of this investigation indicated that the mutation does not impact on cell length. Moreover, cytometry analyses showed absence of endoreduplication. Actually, the mutation influenced the cell number and this effect appeared before the 40th day after sowing. The length difference of hypocotyls between B and BP was due to lower cell number in BP, indicating possible involvement of phytohormones. Investigations showed the decrease of cytokinin and auxin levels in BP compared to B, while the cytokinin/auxin ratio remained constant in both varieties. By contrast, abscisic acid content increased in BP. Concurrently these results indicate the lowering of cell division, due to the mutation.

Three-spin coherent oscillations and interference - Poulin-Lamarre, G.; Thorgrimson, J.; Studenikin, S. A.; Aers, G. C.; Kam, A.; Zawadzki, P.; Wasilewski, Z. R.; Sachrajda, A. S. (Physical Review B - Condensed Matter and Materials Physics, 2015)
We utilize magnetic field dependencies to identify two hitherto unobserved quantum interference processes in a triple quantum dot circuit. The first observation involves the interplay of Landau-Zener-Stückelberg behavior from two separate anticrossings between two energy levels that anticross twice as a function of a detuning parameter. The second process involves quantum interference between all-exchange and hyperfine qubits activated in a three-spin system.

Effects of iron-rich intermetallics on tensile deformation of Al-Cu 206 cast alloys - Liu, K.; Cao, X.; Chen, X. -G. (Metallurgical and Materials Transactions B: Process Metallurgy and Materials Processing Science, 2015)
An investigation has been carried out of the influence of iron on the tensile properties and fracture behavior of a series of Al-Cu 206 cast alloys. Iron contents are explored from 0.15 to 0.5 wt pct, and at two levels of silicon and manganese. The types, morphologies and quantities of the various iron-rich intermetallics are characterized metallographically, and their effects on the tensile properties and the nucleation and growth of cracks during tensile deformation are studied. In addition, oxide films are shown to play an important role in both the nucleation of the iron-rich intermetallics and the formation of tensile cracks.
Keywords: Aluminum; Cast iron; Copper alloys; Cracks; Deformation; Fracture mechanics; Iron; Nucleation; Oxide films; Cast alloys; Fracture behavior; Iron content; Iron rich; Nucleation and growth; Tensile crack; Tensile deformation; Intermetallics

Measurement of soot concentration and bulk fluid temperature and velocity using modulated laser-induced incandescence - Snelling, David R.; Sawchuk, Robert A.; Smallwood, Gregory J.; Thomson, Kevin (Applied Physics B: Lasers and Optics, 2015)
The use of a modulated LII two-colour technique to measure soot temperature in a laminar diffusion flame is described, and the results compared to CARS experiments. A sinusoidal modulated diode laser is used to excite the soot, and both the modulated LII intensity and its relative phase to the excitation source are measured with a lock-in amplifier and recorded. Modulation frequencies from 25 to 200,000 Hz were employed. The temperature is derived from the ratio of the modulated LII radiation signal at 445 and 750 nm, and the results compared to values obtained by CARS spectroscopy. The modulated LII temperatures were largely independent of modulation frequency and agreed well with the CARS temperatures. A theory is developed to explain the dependence of the phase delay of the modulated LII signal (with reference to that of the laser excitation source) on gas replacement time in the sample volume, soot cooling rate and soot volume fraction. The theory is shown to give a reasonable fit to the experimental results at all frequencies. At lower frequencies, the phase delay is dominated by the gas replacement time in the sample volume and at higher frequencies by the cooling rate of the heated soot. Time constants for both processes and the soot volume fraction are derived from the data and shown to be largely in agreement with the expected values. Using modulated LII-determined soot volume fraction and inverted and scatter corrected line-of-sight attenuation-determined absorption coefficients, the soot refractive index absorption function E(m) was measured to be between 0.45 and 0.42 over the wavelength range of 436–825 nm.
Keywords: Coherent scattering; Cooling; Laser excitation; Laser theory; Modulation; Raman spectroscopy; Refractive index; Soot; Volume fraction; Absorption co-efficient; Excitation sources; Fluid temperatures; Higher frequencies; Laminar diffusion flames; Line-of-sight attenuations; Modulation frequencies; Soot volume fraction; Dust

Comment on "human time-frequency acuity beats the Fourier uncertainty principle" - Thekkadath, G. S.; Spanner, Michael (Physical Review Letters, 2015)

Enhancing the detection of Giardia duodenalis cysts in foods by inertial microfluidic separation - Ganz, Kyle R.; Clime, Liviu; Farber, Jeffrey M.; Corneau, Nathalie; Veres, Teodor; Dixon, Brent R. (Applied and Environmental Microbiology, 2015)
The sensitivity and specificity of current Giardia cyst detection methods for foods are largely determined by the effectiveness of the elution, separation, and concentration methods used. The aim of these methods is to produce a final suspension with an adequate concentration of Giardia cysts for detection and a low concentration of interfering food debris. In the present study, a microfluidic device, which makes use of inertial separation, was designed and fabricated for the separation of Giardia cysts. A cyclical pumping platform and protocol was developed to concentrate 10-ml suspensions down to less than 1 ml. Tests involving Giardia duodenalis cysts and 1.90-μm microbeads in pure suspensions demonstrated the specificity of the microfluidic chip for cysts over smaller nonspecific particles. As the suspension cycled through the chip, a large number of beads were removed (70%) and the majority of the cysts were concentrated (82%). Subsequently, the microfluidic inertial separation chip was integrated into a method for the detection of G. duodenalis cysts from lettuce samples. The method greatly reduced the concentration of background debris in the final suspensions (10-fold reduction) in comparison to that obtained by a conventional method. The method also recovered an average of 68.4% of cysts from 25-g lettuce samples and had a limit of detection (LOD) of 38 cysts. While the recovery of cysts by inertial separation was slightly lower, and the LOD slightly higher, than with the conventional method, the sample analysis time was greatly reduced, as there were far fewer background food particles interfering with the detection of cysts by immunofluorescence microscopy.
Keywords: Fluidic devices; Microfluidics; Protozoa; Concentration method; Conventional methods; Immunofluorescence microscopy; Inertial microfluidics; Limit of detection; Low concentrations; Micro-fluidic devices; Sensitivity and specificity; Suspensions (fluids); biotechnology; concentration (composition); cyst; food; protozoan; Giardia; Giardia intestinalis; Lactuca

In situ Nd isotope analyses in geological materials with signal enhancement and non-linear mass dependent fractionation reduction using laser ablation MC-ICP-MS - Xu, Lei; Hu, Zhaochu; Zhang, Wen; Yang, Lu; Liu, Yongsheng; Gao, Shan; Luo, Tao; Hu, Shenghong (Journal of Analytical Atomic Spectrometry, 2015)
To improve the precision and accuracy of in situ Nd isotope analyses in geological samples, high analytical sensitivity and minimized non-linear mass dependent fractionation are desirable. In this study, we investigated the effects of three different cone combinations and the addition of N2 with the guard electrode, either grounded or floating, on the performance of Nd isotope analyses. Signal enhancements (2.5-3 folds) were observed for the Jet sample cone + X skimmer cone and for the standard sample cone + X skimmer cone, which were compared to those of the standard sample cone + H skimmer cone with the addition of N2 at 3 or 6 ml min-1. The influence of a guard electrode on the LA-MC-ICP-MS sensitivity was minimal for dry plasma conditions but became significant in the presence of N2. The addition of 3 or 6 ml min-1 N2 into the carrier gas increased the sensitivity for Nd by a factor of 1.6 with the GE-on mode for the Jet sample cone + X skimmer cone. However, in the GE-off mode, the addition of 2-3 ml min-1 N2 decreased the signal intensity of Nd by a factor of two to three. The makeup gas flow rate was found to have a significant effect on the mass bias stability of Nd isotopes, and this effect was different for different cone combinations. To stabilize the mass bias, measurements at elevated makeup gas flow rates was required for the combination of the X skimmer cone with the standard sample cone or Jet sample cone, at the expense of sensitivity. In notable contrast, the mass bias was stable for the combination of the standard sample cone and H skimmer cone under their corresponding optimum makeup gas flow rates. However, we found that the neodymium isotopes exhibited a large non-linear component at elevated makeup gas flow rates that could not be corrected by the accepted mass fractionation laws. The addition of 3-6 ml min-1 nitrogen to the central gas flow in laser ablation MC-ICP-MS was found to not only significantly enlarge the mass bias stability zone, but also to suppress the non-linear mass dependent fractionation for the combination of X skimmer cone with Jet sample cone or standard sample cone. The accuracy and precision of the developed analytical method for Nd isotope using Jet sample cone + X skimmer cone with the addition of nitrogen has been demonstrated by analyzing a series of reference glasses (JNdi-1 glass, LREE glass, NIST 610) and minerals (apatite, monazite and titanite). Results obtained for 143Nd/144Nd ratios in these reference materials are in excellent agreement with published values, demonstrating the capability of the developed analytical method to be an important tool for providing high-quality in situ Nd isotope data in geological samples.
Keywords: Ablation; Electrodes; Flow of gases; Flow rate; Gases; Glass; Inductively coupled plasma mass spectrometry; Isotopes; Laser ablation; Mass spectrometers; Phosphate minerals; Geological materials; Geological samples; Mass fractionations; Neodymium isotopes; Signal enhancement; Signal intensities; Nitrogen

Nasal and pulmonary vaccine delivery using particulate carriers - Jia, Yimei; Krishnan, Lakshmi; Omri, Abdelwahab (Expert Opinion on Drug Delivery, 2015)
Introduction: Many human pathogens cause respiratory illness by colonizing and invading the respiratory mucosal surfaces. Preventing infection at local sites via mucosally active vaccines is a promising and rational approach for vaccine development. However, stimulating mucosal immunity is often challenging. Particulate adjuvants that can specifically target mucosal immune cells offer a promising opportunity to stimulate local immunity at the nasal and/or pulmonary mucosal surfaces.Areas covered: This review analyzes the common causes of respiratory infections, the challenges in the induction of mucosal and systemic responses and current pulmonary and nasal mucosal vaccination strategies. The ability of various particulate adjuvant formulations, including lipid-based particles, polymers and other particulate systems, to be effectively utilized for mucosal vaccine delivery is discussed.Expert opinion: Induction of antibody and cell-mediated mucosal immunity that can effectively combat respiratory pathogens remains a challenge. Particulate delivery systems can be developed to target mucosal immune cells and effectively present antigen to evoke a rapid and long-term local immunity in the respiratory mucosa. In particular, particulate delivery systems offer the versatility of being formulated with multiple adjuvants and antigenic cargo, and can be tailored to effectively prime immune responses across the mucosal barrier. The opportunity for rational design of novel subunit particulate vaccines is emerging.
Keywords: BCG vaccine; chemokine receptor CCR7; chickenpox measles mumps rubella vaccine; chitosan nanoparticle; cholera toxin; diphtheria pertussis poliomyelitis tetanus Haemophilus influenzae type b vaccine; diphtheria pertussis tetanus vaccine; diphtheria vaccine; DNA vaccine; gamma interferon; gold nanoparticle; Haemophilus influenzae type b vaccine; influenza vaccine; interleukin 12; interleukin 18; interleukin 2; ISCOM; liposome; macrogol; measles mumps rubella vaccine; measles vaccine; Pneumococcus vaccine; polyethyleneimine; polylactic acid; polymer; severe acute respiratory syndrome vaccine; tumor necrosis factor alpha; vaccine; virosome; adaptive immunity; antigen presenting cell; B lymphocyte; CD4+ T lymphocyte; CD8+ T lymphocyte; cross presentation; Haemophilus infection; human; influenza; influenza A (H5N1); inhalation; innate immunity; measles; mucosal immunity; nanoemulsion; pertussis; pneumococcal infection; respiratory tract infection; severe acute respiratory syndrome; T lymphocyte; tuberculosis; virus like agent

Octanol-water partition coefficient from 3D-RISM-KH molecular theory of solvation with partial molar volume correction - Huang, Wenjuan; Blinov, Nikolay; Kovalenko, Andriy (The Journal of Physical Chemistry B, 2015)
The octanol-water partition coefficient is an important physical-chemical characteristic widely used to describe hydrophobic/hydrophilic properties of chemical compounds. The partition coefficient is related to the transfer free energy of a compound from water to octanol. Here, we introduce a new protocol for prediction of the partition coefficient based on the statistical-mechanical, 3D-RISM-KH molecular theory of solvation. It was shown recently that with the compound-solvent correlation functions obtained from the 3D-RISM-KH molecular theory of solvation, the free energy functional supplemented with the correction linearly related to the partial molar volume obtained from the Kirkwood-Buff/3D-RISM theory, also called the 'universal correction' (UC), provides accurate prediction of the hydration free energy of small compounds, compared to explicit solvent molecular dynamics [ Palmer, D. S.; J. Phys.: Condens. Matter 2010, 22, 492101 ]. Here we report that with the UC reparametrized accordingly this theory also provides an excellent agreement with the experimental data for the solvation free energy in nonpolar solvent (1-octanol) and so accurately predicts the octanol-water partition coefficient. The performance of the Kovalenko-Hirata (KH) and Gaussian fluctuation (GF) functionals of the solvation free energy, with and without UC, is tested on a large library of small compounds with diverse functional groups. The best agreement with the experimental data for octanol-water partition coefficients is obtained with the KH-UC solvation free energy functional.
Keywords: Chemical compounds; Functional groups; Molecular dynamics; Solvation; Solvents; Volume measurement; Chemical characteristic; Explicit solvent molecular dynamics; Hydration free energies; Hydrophobic/hydrophilic; Molecular theory of solvation; Octanol-water partition coefficient; Partition coefficient; Solvation free energies; Free energy

On the radiative properties of soot aggregates part 1: Necking and overlapping - Yon, J.; Bescond, A.; Liu, F. (Journal of Quantitative Spectroscopy and Radiative Transfer, 2015)
There is a strong interest in accurately modelling the radiative properties of soot aggregates (also known as black carbon particles) emitted from combustion systems and fires to gain improved understanding of the role of black carbon to global warming. This study conducted a systematic investigation of the effects of overlapping and necking between neighbouring primary particles on the radiative properties of soot aggregates using the discrete dipole approximation. The degrees of overlapping and necking are quantified by the overlapping and necking parameters. Realistic soot aggregates were generated numerically by constructing overlapping and necking to fractal aggregates formed by point-touch primary particles simulated using a diffusion-limited cluster aggregation algorithm. Radiative properties (differential scattering, absorption, total scattering, specific extinction, asymmetry factor and single scattering albedo) were calculated using the experimentally measured soot refractive index over the spectral range of 266-1064. nm for 9 combinations of the overlapping and necking parameters. Overlapping and necking affect significantly the absorption and scattering properties of soot aggregates, especially in the near UV spectrum due to the enhanced multiple scattering effects within an aggregate. By using correctly modified aggregate properties (fractal dimension, prefactor, primary particle radius, and the number of primary particle) and by accounting for the effects of multiple scattering, the simple Rayleigh-Debye-Gans theory for fractal aggregates can reproduce reasonably accurate radiative properties of realistic soot aggregates.
Keywords: Absorption spectroscopy; Aggregates; Carbon; Dust; Fractal dimension; Fractals; Global warming; Heat radiation; Morphology; Multiple scattering; Refractive index; Soot; Ultraviolet spectroscopy; Absorption and scatterings; Diffusion limited cluster aggregation; Discrete dipole approximation; Multiple scattering effect; Necking; Radiative properties; RDG-FA; Single scattering albedo; Agglomeration

Rapid and multiplex detection of Legionella's RNA using digital microfluidics - Foudeh, Amir M.; Brassard, Daniel; Tabrizian, Maryam; Veres, Teodor (Lab on a Chip - Miniaturisation for Chemistry and Biology, 2015)
Despite recent advances in the miniaturization and automation of biosensors, technologies for on-site monitoring of environmental water are still at an early stage of development. Prevention of outbreaks caused by pathogens such as Legionella pneumophila would be facilitated by the development of sensitive and specific bioanalytical assays that can be easily integrated in miniaturized fluidic handling systems. In this work, we report on the integration of an amplification-free assay in digital microfluidics (DMF) for the detection of Legionella bacteria based on targeting 16s rRNA. We first review the design of the developed DMF devices, which provide the capability to store up to one hundred nL-size droplets simultaneously, and discuss the challenges involved with on-chip integration of the RNA-based assay. By optimizing the various steps of the assay, including magnetic capture, hybridization duration, washing steps, and assay temperature, a limit of detection as low as 1.8 attomoles of synthetic 16s rRNA was obtained, which compares advantageously to other amplification-free detection systems. Finally, we demonstrate the specificity of the developed assay by performing multiplex detection of 16s rRNAs from a pathogenic and a non-pathogenic species of Legionella. We believe the developed DMF devices combined with the proposed detection system offers new prospects for the deployment of rapid and cost-effective technologies for on-site monitoring of pathogenic bacteria.
Keywords: RNA 16S; cost effectiveness analysis; gene targeting; lab on a chip; Legionella pneumophila; limit of detection; microfluidics; particle size; RNA analysis; RNA hybridization; temperature; Legionella; Legionella pneumophila

Creep of 45 year old cement paste: the role of structural water - Pourbeik, P.; Beaudoin, J. J.; Alizadeh, R.; Raki, L. (Materials and Structures/Materiaux et Constructions, 2015)
Microindentation creep and dynamic mechanical thermo-analysis measurements were carried out on compacted specimens of cement paste prepared at water/cement ratios of 1.00, 0.50 and 0.40 and hydrated for 45 years. Similar data was obtained for pastes prepared at w/c = 0.40 and hydrated only 2 months. Creep modulus–mass-loss curves were plotted for all the systems studied. These curves were used to emphasize salient differences between all the paste systems. The influence of degree of hydration, volume concentration of C–S–H, capillary porosity, C–S–H chain-length and the restraining effect of the unhydrated cement particles on creep are parameters that are used to provide a possible explanation for the observation that the creep of the old pastes is higher than creep of the young pastes. The structural role of water in the creep process at various stages of equilibrium drying from the 11 % RH condition is discussed.
Keywords: Cements; Dynamic mechanical analysis; Dynamics; Hydration; Ageing effects; Cement paste; Creep modulus; Dynamic mechanical; Structural models; Creep

The first H-band spectrum of the giant planet β Pictoris b - Chilcote, Jeffrey; Barman, Travis; Fitzgerald, Michael P.; Graham, James R.; Larkin, James E.; Macintosh, Bruce; Bauman, Brian; Burrows, Adam S.; Cardwell, Andrew; De Rosa, Robert J.; Dillon, Daren; Doyon, René; et al. (The Astrophysical Journal Letters, 2015)
Using the recently installed Gemini Planet Imager (GPI), we have obtained the first H-band spectrum of the planetary companion to the nearby young star β Pictoris. GPI is designed to image and provide low-resolution spectra of Jupiter-sized, self-luminous planetary companions around young nearby stars. These observations were taken covering the H band (1.65 μm). The spectrum has a resolving power of ∼45 and demonstrates the distinctive triangular shape of a cool substellar object with low surface gravity. Using atmospheric models, we find an effective temperature of 1600-1700K and a surface gravity of log(g) = 3.5-4.5 (cgs units). These values agree well with "hot-start" predictions from planetary evolution models for a gas giant with mass between 10 and 12 MJup and age between 10 and 20 Myr.

Excited state non-adiabatic dynamics of pyrrole: A time-resolved photoelectron spectroscopy and quantum dynamics study - Wu, Guorong; Neville, Simon P.; Schalk, Oliver; Sekikawa, Taro; Ashfold, Michael N. R.; Worth, Graham A.; Stolow, Albert (Journal of Chemical Physics, 2015)
The dynamics of pyrrole excited at wavelengths in the range 242-217 nm are studied using a combination of time-resolved photoelectron spectroscopy and wavepacket propagations performed using the multi-configurational time-dependent Hartree method. Excitation close to the origin of pyrrole's electronic spectrum, at 242 and 236 nm, is found to result in an ultrafast decay of the system from the ionization window on a single timescale of less than 20 fs. This behaviour is explained fully by assuming the system to be excited to the A2(πσ∗) state, in accord with previous experimental and theoretical studies. Excitation at shorter wavelengths has previously been assumed to result predominantly in population of the bright A1(ππ∗) and B2(ππ∗) states. We here present time-resolved photoelectron spectra at a pump wavelength of 217 nm alongside detailed quantum dynamics calculations that, together with a recent reinterpretation of pyrrole's electronic spectrum [S. P. Neville and G. A. Worth, J. Chem. Phys. 140, 034317 (2014)], suggest that population of the B1(πσ∗) state (hitherto assumed to be optically dark) may occur directly when pyrrole is excited at energies in the near UV part of its electronic spectrum. The B1(πσ∗) state is found to decay on a timescale of less than 20 fs by both N-H dissociation and internal conversion to the A2(πσ∗) state.
Keywords: Aromatic compounds; Dynamics; Photoelectron spectroscopy; Photoelectrons; Photons; Quantum theory; Electronic spectrum; Internal conversions; Non-adiabatic dynamics; Photoelectron spectrum; Quantum dynamics calculations; Time-dependent Hartree method; Time-resolved photoelectron spectroscopy; Wave packet propagation; Excited states

Formation of methane nano-bubbles during hydrate decomposition and their effect on hydrate growth - Bagherzadeh, S.Alireza; Alavi, Saman; Ripmeester, John; Englezos, Peter (Journal of Chemical Physics, 2015)
Molecular dynamic simulations are performed to study the conditions for methane nano-bubble formation during methane hydrate dissociation in the presence of water and a methane gas reservoir. Hydrate dissociation leads to the quick release of methane into the liquid phase which can cause methane supersaturation. If the diffusion of methane molecules out of the liquid phase is not fast enough, the methane molecules agglomerate and form bubbles. Under the conditions of our simulations, the methane-rich quasi-spherical bubbles grow to become cylindrical with a radius of ∼11 Å. The nano-bubbles remain stable for about 35 ns until they are gradually and homogeneously dispersed in the liquid phase and finally enter the gas phase reservoirs initially set up in the simulation box. We determined that the minimum mole fraction for the dissolved methane in water to form nano-bubbles is 0.044, corresponding to about 30% of hydrate phase composition (0.148). The importance of nano-bubble formation to the mechanism of methane hydrate formation, growth, and dissociation is discussed.
Keywords: Bubble formation; Dissociation; Hydration; Liquids; Methane; Molecular dynamics; Molecules; Dissolved methane; Hydrate decomposition; Hydrate dissociation; Methane hydrate dissociation; Methane hydrates; Methane molecules; Presence of water; Spherical bubbles; Gas hydrates

Corrosion properties of plasma electrolytic oxidation coatings on an aluminium alloy - The effect of the PEO process stage - Dehnavi, Vahid; Shoesmith, David W.; Luan, Ben Li; Yari, Mehdi; Liu, Xing Yang; Rohani, Sohrab (Materials Chemistry and Physics, 2015)
Plasma electrolytic oxidation (PEO) coatings were grown on an aluminium alloy substrate using different processing parameters which enabled samples to be coated to different stages of the PEO process. Electrochemical impedance spectroscopy (EIS) and linear polarization resistance (LPR) techniques were employed to investigate the impedance properties of the resulting oxide coatings which will determine the corrosion performance of the coated alloy. Scanning electron microscopy was used to relate the morphology of the coatings with their corrosion performance. A direct relationship was found between the stage of the PEO process, which affects the microstructure of the coatings, and the corrosion performance. Coating thickness and phase composition did not have any measurable influence on coating corrosion performance. To some degree corrosion performance could be tailored by the processing parameters.
Keywords: Alloys; Aluminum; Aluminum alloys; Coatings; Corrosion; Electrochemical corrosion; Electrochemical impedance spectroscopy; Electrolysis; Electron microscopy; Microstructure; Oxidation; Plasma deposition; Protective coatings; Scanning electron microscopy; Thickness measurement; Ceramics; Corrosion performance; Corrosion property; Impedance properties; Linear polarization resistance; Plasma electrolytic oxidation; Plasma electrolytic oxidation coatings; Processing parameters; Aluminum corrosion

Energy recovery from agro-industrial wastewaters through biohydrogen production: Kinetic evaluation and technological feasibility - Lucas, S. D. M.; Peixoto, G.; Mockaitis, G.; Zaiat, M.; Gomes, S. D. (Renewable Energy, 2015)
Biohydrogen production from cassava, dairy and citrus processing wastewaters (WWs) without nutritional supplementation was evaluated in anaerobic single-batch reactors at 37°C for 70h. Hydrogen production from cassava, dairy and citrus WW was 31.41, 37.25 and 28.95mLg-1 of chemical oxygen demand (COD). The kinetic parameters indicated that H2 production rates for cassava processing WW (0.32mLh-1) and dairy WW (0.31mLh-1) were similar, whereas citrus processing WW exhibited the highest value (0.59mLh-1). The carbohydrate degradation rate (k1App) was highest for dairy WW (0.045h-1), but the most efficient overall conversion of organic matter to H2(k2App) was observed with cassava WW (0.014h-1). The rate of conversion of the organic matter of the cassava WW together with its ready availability resulted in a recovery of 0.59 109MJyear-1, the highest in this study. Cassava WW showed the highest hydrogen production potential (97.9mL), when compared with dairy (76.1mL) and citrus WW (66.6mL). The economic estimation based on the gasoline energetic equivalent indicated that a single process of H2 production allowed the maximum economic yield of US$ 0.009 cents L-1 WW. Alternatively, a sequential hydrogen and methane process could increase energy recoveries and economic yields to values near 10.48kJg-1 COD and US$ 0.61 cents L-1 WW (US$ 6.10m-3 WW).
Keywords: Batch reactors; Biogeochemistry; Biological materials; Chemical oxygen demand; Degradation; Enzyme kinetics; Industrial economics; Industrial wastes; Kinetics; Organic compounds; Agro-industrial wastes; Bio-hydrogen production; Citrus processing; Industrial wastewaters; Kinetic evaluations; Technological feasibility; Hydrogen production; agroindustry; bioenergy; biofuel; biotechnology; cassava; dairy farming; economic analysis; feasibility study; hydrogen; reaction kinetics; renewable resource; wastewater

Analysis of integrity and microstructure of linear friction welded Waspaloy - Chamanfar, A.; Jahazi, M.; Gholipour, J.; Wanjara, P.; Yue, S. (Materials Characterization, 2015)
Nickel-base superalloy, Waspaloy, was linear friction welded (LFWed) under different axial shortening conditions of 2.0, 3.4, and 4.6 mm. The tensile properties and microhardness of the weldments were investigated in the as-LFWed condition and compared with those in the post-weld heat treated (PWHTed) condition. Mechanical properties were related to microstructures following examination by optical microscopy, high resolution scanning electron microscopy, and electron backscatter diffraction (EBSD). Analyses of the EBSD results in terms of the misorientation angle distribution, which represents the stored energy, were performed. In the as-LFWed condition, the yield strength (YS) and ultimate tensile strength (UTS) increased with axial shortening due to greater expulsion of the softened interfacial material toward the periphery as flash. In contrast, with increasing axial shortening the total elongation initially remained constant and then decreased. This was also related to the expulsion of the softened interfacial material into the bifurcated flash. Extensive dissolution of the strengthening phase (γ′) in the weld area during linear friction welding (LFW) contributed to the lower YS and UTS in the as-welded condition compared to the PWHTed condition where the γ′ particles were recovered. After performing post-weld heat treatment (PWHT), the total elongation improved due to the relaxation of stored energy and grain growth in the thermomechanically affected zone (TMAZ).
Keywords: Friction; Grain growth; Mechanical properties; Microstructure; Scanning electron microscopy; Stainless steel; Strength of materials; Tensile strength; Tribology; Welding; Welds; Electron back scatter diffraction; High-resolution scanning electron microscopies; Linear friction welding; Linear friction welding (LFW); Mis-orientation; Stored energy; Thermomechanically affected zones; Waspaloy; Friction welding

Size-dependent activity of Pt/yttria-stabilized zirconia catalyst for ethylene and carbon monoxide oxidation in oxygen-free gas environment - Isaifan, Rima J.; Ntais, Spyridon; Couillard, Martin; Baranova, Elena A. (Journal of Catalysis, 2015)
The effect of Pt average particle size (1.9-6.7 nm) on the catalytic activity of 909 ppm carbon monoxide and ethylene oxidation by O2- from yttria-stabilized zirconia (YSZ) was studied at 25-400 °C. The results show that CO and C2H4 oxidation in the absence of oxygen in the gas feed is strongly size dependent in analogy to their catalytic oxidation in oxygen-rich environment. Without oxygen, the local nano-galvanic cell mechanism is proposed, where CO and C2H4 electrooxidation at the three-phase boundary (tpb) is accompanied by partial surface electroreduction of zirconia. The smallest Pt nanoparticles (NPs) (1.9 ± 0.4 nm) have higher TOF, higher intrinsic rates and lower activation energies compared with the larger Pt NPs (4.4 ± 0.3 nm), for example 30.3 vs. 64.8 kJ mol-1 for CO and 12.5 vs. 38.4 kJ mol-1 for C2H4 oxidation, respectively. In the presence of oxygen, the catalytic oxidation occurs at significantly lower temperatures than without O2. In this case, the oxidation reaction takes place via a sacrificial promoter-type mechanism, proposed earlier for catalyst nanoparticles supported on YSZ, where thermally induced O2- backspillover migrates from YSZ to the gas-exposed surface of Pt NPs in parallel with the electrooxidation reaction at tpb.

Two-temperature pair potentials and phonon spectra for simple metals in the warm dense matter regime - Harbour, L.; Dharma-wardana, M. W. C.; Klug, D. D.; Lewis, L. J. (Contributions to Plasma Physics, 2015)
We develop ion-ion pair potentials for Al, Na and K for densities and temperatures relevant to the warm-densematter (WDM) regime. Furthermore, we emphasize non-equilibrium states where the ion temperature Ti differs from the electron temperature Te. This work focuses mainly on ultra-fast laser-metal interactions where the energy of the laser is almost exclusively transferred to the electron sub-system over femtosecond time scales. This results in a two-temperature system with Te > Ti and with the ions still at the initial room temperature Ti = Tr. First-principles calculations, such as density functional theory (DFT) or quantum Monte Carlo, are as yet not fully feasible for WDM conditions due to lack of finite-T features, e.g. pseudopotentials, and extensive CPU time requirements. Simpler methods are needed to study these highly complex systems. We propose to use two-temperature pair potentials Uii(r, Ti, Te) constructed from linear-response theory using the non-linear electron density n (r) obtained from finite-T DFT with a single ion immersed in the appropriate electron fluid. We compute equilibrium phonon spectra at Tr which are found to be in very good agreement with experiments. This gives credibility to our non-equilibrium phonon dispersion relations which are important in determining thermophysical properties, stability, energy-relaxation mechanisms and transport coefficients.

Kinugasa reactions in water: From green chemistry to bioorthogonal labelling - Chigrinova, Mariya; MacKenzie, Douglas A.; Sherratt, Allison R.; Cheung, Lawrence L. W.; Pezacki, John Paul (Molecules, 2015)
The Kinugasa reaction has become an efficient method for the direct synthesis of β-lactams from substituted nitrones and copper(I) acetylides. In recent years, the reaction scope has been expanded to include the use of water as the solvent, and with micelle-promoted [3+2] cycloadditions followed by rearrangement furnishing high yields of β-lactams. The high yields of stable products under aqueous conditions render the modified Kinugasa reaction amenable to metabolic labelling and bioorthogonal applications. Herein, the development of methods for use of the Kinugasa reaction in aqueous media is reviewed, with emphasis on its potential use as a bioorthogonal coupling strategy.

Assessment of debond simulation and cohesive zone length in a bonded composite joint - Li, Gang; Li, Chun (Composites Part B: Engineering, 2015)
Finite element methods combined with cohesive elements were used to simulate progressive failure behaviour in a bonded double cantilever beam configuration. The introduced cohesive zone was represented by three cases. Responses of both global load-displacement and local cohesive traction-separation were investigated. An unexpected finding was that the overall cohesive traction stiffness was much less than the assumed input value. In addition, the local nodal separation moment was identified. Consequently, correct cohesive zone lengths were obtained using the extracted traction profile along the cohesive zone path at this moment. Information of the global load-displacement profile, traction stiffness, and cohesive zone length induced by the three zone cases was explored. Moreover, the study can explain why very small cohesive zone lengths are generated numerically, as compared to theoretical solutions. Recommendations on the application of the numerical model with cohesive elements to practical experimental analysis were suggested.
Keywords: Bonded composite joints; Cohesive zones; Traction law; Cohesive tractions; Double cantilever beam; Experimental analysis; Progressive failure; Theoretical solutions; Cantilever beams; Finite element method; Joints (structural components); Stiffness

Elemental abundance analyses with DAO spectrograms. XXXVI. The hot metallic line stars theta Leonis and omicron Pegasi - Adelman, Saul J.; Gulliver, Austin F.; Heaton, Robert J. (Publications of the Astronomical Society of the Pacific, 2015)
This series contains high-quality LTE elemental abundance analyses of sharp-lined and moderately rotating normal and peculiar Main Sequence Band B, A, and F stars. Their compositions were determined for comparison with analyses of somewhat similar stars and with theoretical predictions. Here we provide new and improved elemental abundances analyses for the well-studied hot metallic line stars θ Leonis and o Pegasi to better understand their relationship with other A stars. The analyses, which employ Kurucz’s ATLAS9 model atmospheres and WIDTH9 codes and high signal-to-noise ratio (S/N) spectrograms obtained with Reticon and CCD detectors, are consistent with our previous analyses based upon coadded photographic plates. The spectral synthesis program STELLAR is used with the fluxes, the Hγ profiles, and the spectra to provide better estimates of the effective temperature, surface gravity, and metallicity. The agreement of the results for two species of the same element are usually improved. The errors have been slightly reduced compared to those of their previous analyses using DAO spectrograms. Abundances of additional elements have been determined. The very high S/N (≥500) spectra of o Peg (used previously for the stellar atlas of Gulliver et al.) were critical to finding the weakest lines and to defining the profiles of all lines. High-quality spectrograms of additional regions especially those longward of Hβ can be used to obtain some missing elemental abundances in both stars.

High-resolution synchrotron infrared spectroscopy of acrolein: The vibrational levels between 700 and 820cm-1 - McKellar, A. R. W.; Billinghurst, B. E. (Journal of Molecular Spectroscopy, 2015)
The weak combination bands ν12 +ν18 and ν17 +ν18 of trans-acrolein in the 700-760cm-1 region are observed at high resolution (<0.001cm-1) using spectra obtained at the Canadian Light Source synchrotron radiation facility. A detailed rotational analysis of the 121181 and 171181 upper states is made which includes the nearby perturbing states 185, 132181, and 131183. Taking the results of this 5-state fit, together with earlier results on lower lying vibrations, we now have experimental characterization for all 15 excited vibrational states of acrolein lying below 820cm-1.
Keywords: Aldehydes; Infrared radiation; Infrared spectroscopy; Light sources; Synchrotron radiation; Synchrotrons; Acrolein; Coriolis; Excited vibrational state; Experimental characterization; Perturbation; Rotational analysis; Synchrotron radiation facility; Vibrational levels; Herbicides

Thermomechanical fatigue of ductile cast iron and its life prediction - Wu, Xijiax; Quan, Guangchun; MacNeil, Ryan; Zhang, Zhong; Liu, Xiaoyang; Sloss, Clayton (Metallurgical and Materials Transactions A: Physical Metallurgy and Materials Science, 2015)
Thermomechanical fatigue (TMF) behaviors of ductile cast iron (DCI) were investigated under out-of-phase (OP), in-phase (IP), and constrained strain-control conditions with temperature hold in various temperature ranges: 573 K to 1073 K, 723 K to 1073 K, and 433 K to 873 K (300 °C to 800 °C, 450 °C to 800 °C, and 160 °C to 600 °C). The integrated creep-fatigue theory (ICFT) model was incorporated into the finite element method to simulate the hysteresis behavior and predict the TMF life of DCI under those test conditions. With the consideration of four deformation/damage mechanisms: (i) plasticity-induced fatigue, (ii) intergranular embrittlement, (iii) creep, and (iv) oxidation, as revealed from the previous study on low cycle fatigue of the material, the model delineates the contributions of these physical mechanisms in the asymmetrical hysteresis behavior and the damage accumulation process leading to final TMF failure. This study shows that the ICFT model can simulate the stress–strain response and life of DCI under complex TMF loading profiles (OP and IP, and constrained with temperature hold).
Keywords: Creep; Fatigue damage; Fatigue of materials; Finite element method; Hysteresis; Iron; Iron compounds; Stress analysis; Damage accumulation; Ductile cast irons; Hysteresis behavior; Intergranular embrittlement; Low cycle fatigues; Physical mechanism; Temperature range; Thermo mechanical fatigues (TMF); Cast iron

Determination of thiocyanate in saliva by headspace gas chromatography-mass spectrometry, following a single-step aqueous derivatization with triethyloxonium tetrafluoroborate - Ammazzini, Sara; Onor, Massimo; Pagliano, Enea; Mester, Zoltán; Campanella, Beatrice; Pitzalis, Emanuela; Bramanti, Emilia; D'Ulivo, Alessandro (Journal of Chromatography A, 2015)
A novel method for the determination of salivary thiocyanate is presented. Thiocyanate was converted into ethyl thiocyanate by single-step aqueous derivatization based on triethyloxonium tetrafluoroborate and measured by gas chromatography-mass spectrometry (15min runtime). The ethyl thiocyanate derivative is volatile and can be sampled from the headspace. The derivatization chemistry proposed allows for separation of the analyte from saliva matrix whose introduction in the measurement system is avoided. Quantitation of the analyte was obtained by isotope dilution, employing a 13C-enriched thiocyanate as internal standard. Technical details and fundamental aspects of derivatization chemistry and calibration strategy are presented.The method was validated by comparison with a standard method based on ion chromatography. The two independent methodologies produced results in agreement within 3%. Also a three level spike recovery test was carried out for validation purpose and quantitative recoveries were attained. The method is fast, simple, safe, and sensitive. Measurement of a 1. mL volume 50. ng/g of thiocyanate standard produced a signal-to-noise ratio of 250 for the analytical peak. This method is therefore suitable for ultra-trace determination of thiocyanate (low part-per-billion range). For the application described the full detection potential of the method was not required and the sample preparation presented has been designed for quantitation of saliva samples containing 1-400. μg/g of thiocyanate with a combined standard uncertainty of 2% relative for saliva samples containing 25. μg/g of thiocyanate. This method was applied for the determination of thiocyanate in human saliva samples.
Keywords: Thiocyanate; Saliva; Smokers and nonsmokers; Triethyloxonium tetrafluoroborate derivatization; GC/MS; Isotope dilution

Nanolayered CrAlTiN and multilayered CrAlTiN-AlTiN coatings for solid particle erosion protection - Yang, Q.; McKellar, R. (Tribology International, 2015)
Applying hard coatings on airfoil surfaces is proven to be an effective approach to mitigating erosion damage to engine components. Nanolayered or multilayered coatings, because of their capability of tailoring hardness and toughness through modifications in the chemistry and architecture of layer constituents, have been explored as potential candidates for this specific application. In this study, nanolayered CrAlTiN (CrN/AlTiN) coatings with different modulation periods, along with multilayered CrAlTiN-AlTiN coatings having different number of layers and different thickness of individual layers, were fabricated, characterized and evaluated. All the coatings significantly outperformed the CrN baseline in erosion resistance, and their performance was strongly affected by the bilayer period of the nanolayered coatings or the layer architectural characteristics of multilayered coatings.
Keywords: Erosion; Cathodic arc; Different thickness; Effective approaches; Erosion resistance; Multi-layered coatings; Nano layers; Nanolayered coatings; Solid particle erosion; Hard coatings

Iron and s-elements abundance variations in NGC 5286: Comparison with 'anomalous' globular clusters and Milky Way satellites - Marino, A. F.; Milone, A. P.; Karakas, A. I.; Casagrande, L.; Yong, D.; Shingles, L.; Da Costa, G.; Norris, J. E.; Stetson, P. B.; Lind, K.; Asplund, M.; Collet, R.; et al. (Monthly Notices of the Royal Astronomical Society, 2015)
We present a high-resolution spectroscopic analysis of 62 red giants in the Milky Way globular cluster (GC) NGC 5286. We have determined abundances of representative light proton-capture, α, Fe-peak and neutron-capture element groups, and combined them with photometry of multiple sequences observed along the colour-magnitude diagram. Our principal results are: (i) a broad, bimodal distribution in s-process element abundance ratios, with two main groups, the s-poor and s-rich groups; (ii) substantial star-to-star Fe variations, with the s-rich stars having higher Fe, e.g. 〈 [Fe/H]〉s-rich - 〈 [Fe/H]〉s-poor ~ 0.2 dex; and (iii) the presence of O-Na-Al (anti)correlations in both stellar groups. We have defined a new photometric index, cBVI = (B - V) - (V - I), to maximize the separation in the colour-magnitude diagram between the two stellar groups with different Fe and s-element content, and this index is not significantly affected by variations in light elements (such as the O-Na anticorrelation). The variations in the overall metallicity present in NGC 5286 add this object to the class of anomalous GCs. Furthermore, the chemical abundance pattern of NGC 5286 resembles that observed in some of the anomalous GCs, e.g. M 22, NGC 1851, M 2, and the more extreme ω Centauri, that also show internal variations in s-elements, and in light elements within stars with different Fe and s-elements content. In view of the common variations in s-elements, we propose the term s-Fe-anomalous GCs to describe this sub-class of objects. The similarities in chemical abundance ratios between these objects strongly suggest similar formation and evolution histories, possibly associated with an origin in tidally disrupted dwarf satellites.

Detection of bromine by ICP-oa-ToF-MS following photochemical vapor generation - Sturgeon, Ralph E. (Analytical Chemistry, 2015)
A unique flow-through photochemical reactor is utilized for the generation of volatile methyl bromide from aqueous solutions of bromide and bromate ions in a medium of 2% acetic acid containing 3000 μg/mL NH4Cl. The volatile product is transported to a thin-film gas-liquid phase separator and directed to an inductively coupled plasma (ICP) tine-of-flight mass spectrometer for detection and quantitation using either of the 79Br or 81Br isotopes. Utilizing a sample flow rate of 3.3 mL/min and a 13 s irradiation time, a detection limit of 0.14 ng/mL is achieved, yielding a 17-fold enhancement over conventional solution nebulization. The estimated generation efficiency of 95% provides for a significant increase in analyte transport efficiency to the ICP. Precision of replicate measurement is 2.5% (RSD) at 20 ng/mL. The methodology was validated by successful determination of bromine in reference materials, including IRMM (BCR-611) low level bromide in groundwater, NIST SRM 1568b Rice Flour, and SRM 1632 bituminous coal.
Keywords: Bituminous coal; Bromine; Groundwater; Isotopes; Detection limits; Inductively coupled plasma (ICP); Irradiation time; Photochemical reactor; Reference material; Replicate measurements; Transport efficiency; Volatile products; Inductively coupled plasma

High rate SnO2-Graphene Dual Aerogel anodes and their kinetics of lithiation and sodiation - Li, Zhi; Ding, Jia; Wang, Huanlei; Cui, Kai; Stephenson, Tyler; Karpuzov, Dimitre; Mitlin, David (Nano Energy, 2015)
We created a unique SnO2–Graphene Dual Aerogel (SnO2/GDA) nanocomposite with exquisite lithium and sodium ion battery anode performance (LIB, NIB NAB SIB). In parallel we employed electrochemical methods to be the first to analyze the transition from kinetic control to diffusion control for the conversion reaction (SnO2+4Li++4e−↔Sn+2Li2O) vs. for the alloying reaction (Sn+xLi++xe−↔LixSn, x≤4.4). The material displays a high reversible capacity (1299 mA h g−1 for Li at 0.1 A g−1, 448 mA h g−1 for Na at 0.05 A g−1), very good cycling life (148% after 450 cycles for Li, 82% from 20 to 200 cycles for Na), and superb rate capacity retention (450 mA h g−1 for Li at 25 A g−1, 184 mA h g−1 for Na at 1 Ag−1). In fact, these rate capabilities are among the most favorable reported in literature for each system.
Keywords: Aerogels; Capacitors; Electrodes; Graphene; Ions; Lithium alloys; Lithium-ion batteries; Metal ions; Tin; Tin oxides; Battery; Conversion reactions; ELectrochemical methods; High reversible capacities; Lithium ions; Rate capabilities; Sodium ion batteries; Sodium ions; Lithium

Kinetics of the addition of olefins to Si-centered radicals: The critical role of dispersion interactions revealed by theory and experiment - Johnson, Erin R.; Clarkin, Owen J.; Dale, Stephen G.; Dilabio, Gino A. (The Journal of Physical Chemistry A, 2015)
Solution-phase rate constants for the addition of selected olefins to the triethylsilyl and tris(trimethylsilyl)silyl radicals are measured using laser-flash photolysis and competition kinetics. The results are compared with predictions from density functional theory (DFT) calculations, both with and without dispersion corrections obtained from the exchange-hole dipole moment (XDM) model. Without a dispersion correction, the rate constants are consistently underestimated; the errors increase with system size, up to 106 s-1 for the largest system considered. Dispersion interactions preferentially stabilize the transition states relative to the separated reactants and bring the DFT-calculated rate constants into excellent agreement with experiment. Thus, dispersion interactions are found to play a key role in determining the kinetics for addition reactions, particularly those involving sterically bulky functional groups.
Keywords: Addition reactions; Density functional theory; Electromagnetic dispersion; Functional groups; Kinetics; Olefins; Photolysis; Competition kinetic; Dispersion correction; Dispersion interaction; Laser flash photolysis; Silyl radical; Solution phase; Transition state; Trimethylsilyl; Rate constants

The star-forming histories of the nucleus, bulge, and inner disk of NGC 5102: Clues to the evolution of a nearby lenticular galaxy - Davidge, T. J. (The Astrophysical Journal, 2015)
Long slit spectra recorded with the Gemini Multi-Object Spectrograph on Gemini South are used to examine the star-forming history (SFH) of the lenticular galaxy NGC 5102. Structural and supplemental photometric information are obtained from archival Spitzer [3.6] images. Absorption features at blue and visible wavelengths are traced out along theminor axis to galactocentric radii ∼ 60 arcsec (∼0.9 kpc), sampling the nucleus, bulge, and disk components. Comparisons with model spectra point to luminosity-weighted metallicities that are consistent with the colors of resolved red giant branch stars in the disk. The nucleus has a luminosity-weighted age at visiblewavelengths of ∼1-0.1 +0.2 Gyr, and the integrated light is dominated by stars that formed over a time period of only a few hundred Myr. For comparison, the luminosity-weighted ages of the bulge and disk are ∼2-0.2 +0.5 Gyr and 10-2 +2 Gyr, respectively. The g′ - [3.6] colors of the nucleus and bulge are consistent with the spectroscopically based ages. In contrast to the nucleus, models that assume star-forming activity spanning many Gyr provide a better match to the spectra of the bulge and disk than simple stellar population models. Isophotes in the bulge have a disky shape, hinting that the bulge was assembled from material with significant rotational support. The SFHs of the bulge and disk are consistent with the bulge forming from the collapse of a long-lived bar, rather than from the collapse of a transient structure that formed as the result of a tidal interaction. It is thus suggested that the progenitor of NGC 5102 was a barred disk galaxy that morphed into a lenticular galaxy through the buckling of its bar.

Counting of escherichia coli by a microflow cytometer based on a photonic-microfluidic integrated device - Guo, Tianyi; Wei, Yin; Xu, Changqing; Watts, Benjamin R.; Zhang, Zhiyi; Fang, Qiyin; Zhang, Haiying; Selvaganapathy, P.Ravi; Deen, M. Jamal (Electrophoresis, 2015)
Counting of Escherichia coli DH5α-cell suspensions in PBS is performed using a microflow cytometer based on a photonic-microfluidic integrated device. Side-scattered light signals are used to count the E. coli cells. A detection efficiency of 92% is achieved when compared with the expected count from a hemocytometer. The detection efficiency is correlated to the ratio of sample to sheath flow rates. It is demonstrated that E. coli can be easily distinguished from beads of similar sizes (2-4 μm) as their scattering intensities are different.
Keywords: polystyrene; analytical equipment; bacterial count; bacterial strain; bacterium culture; bacterium detection; biochip; concentration (parameters); Escherichia coli; flow cytometer; flow kinetics; hemocytometer; laboratory device; light scattering; microfluidics; particle size; photonic microfluidic integrated device; signal detection; suspension

An environmental survey of surface waters using mitochondrial DNA from human, bovine and porcine origin as fecal source tracking markers - Villemur, Richard; Imbeau, Marianne; Vuong, Minh N.; Masson, Luke; Payment, Pierre (Water Research, 2015)
Fecal contamination of surface waters is one the major sources of waterborne pathogens and consequently, is an important concern for public health. For reliable fecal source tracking (FST) monitoring, there is a need for a multi-marker toolbox as no single all-encompassing method currently exists. Mitochondrial DNA (mtDNA) as a source tracking marker has emerged as a promising animal-specific marker. However, very few comprehensive field studies were done on the occurrence of this marker in surface waters. In this report, water samples were obtained from 82 sites in different watersheds over a six year period. The samples were analyzed for the presence of human, bovine and porcine mtDNA by endpoint nested PCR, along with the human-specific Bacteroidales HF183 marker. These sites represented a mix of areas with different anthropogenic activities, natural, urban and agricultural. The occurrences of mitoHu (human), mitoBo (bovine), mitoPo (porcine) and HF183 specific PCR amplifications from the samples were 46%, 23%, 6% and 50%, respectively. The occurrence of mitoHu and HF183 was high in all environment types with higher occurrence in the natural and urban areas, whereas the occurrence of mitoBo was higher in agricultural areas. FST marker concentrations were measured by real-time PCR for samples positive for these markers. The concentration of the mitoHu markers was one order of magnitude lower than HF183. There was co-linearity between the concentrations of the mitoHu and HF183 markers. Co-linearity was also observed between HF183 concentration and fecal coliform levels. Such a relationship was not observed between the mitoHu concentration and fecal coliform levels. In summary, our results showed a high incidence of human fecal pollution throughout the environment while demonstrating the potential of mtDNA as suitable FST markers.
Keywords: DNA; River pollution; Urban growth; Watersheds; Anthropogenic activity; Bacteroidales HF183; Environmental surveys; Fecal sources; Human fecal pollution; Mitochondrial DNA; Mitochondrial DNA (mtDNA); Water-borne pathogens; biological marker; surface water; cattle; concentration (composition); fecal coliform; feces; genetic marker; human activity; water pollution; animal cell; bacterial strain; Bacteroidales; controlled study; environmental monitoring; fecal coliform; feces; human; human cell; mitochondrion; nonhuman; polymerase chain reaction; real time polymerase chain reaction; rural area; swine; urban area; water contamination; water sampling; Bovinae; Sus

The JCMT Gould Belt survey: Evidence for radiative heating in serpens MWC 297 and its influence on local star formation - Rumble, D.; Hatchell, J.; Gutermuth, R. A.; Kirk, H.; Buckle, J.; Beaulieu, S. F.; Berry, D. S.; Broekhoven-Fiene, H.; Currie, M. J.; Fich, M.; Jenness, T.; Johnstone, D.; et al. (Monthly Notices of the Royal Astronomical Society, 2015)
We present SCUBA-2 450 and 850 μm observations of the Serpens MWC 297 region, part of the James Clerk Maxwell Telescope (JCMT) Gould Belt Survey of nearby star-forming regions. Simulations suggest that radiative feedback influences the star formation process and we investigate observational evidence for this by constructing temperature maps. Maps are derived from the ratio of SCUBA-2 fluxes and a two-component model of the JCMTbeam for a fixed dust opacity spectral index of β = 1.8.Within 40 arcsec of the B1.5Ve Herbig star MWC 297, the submillimetre fluxes are contaminated by free-free emission with a spectral index of 1.03 ± 0.02, consistent with an ultracompact HII region and polar winds/jets. Contamination accounts for 73 ± 5 per cent and 82 ± 4 per cent of peak flux at 450 μm and 850 μm, respectively. The residual thermal disc of the star is almost undetectable at these wavelengths. Young stellar objects (YSOs) are confirmed where SCUBA-2 850 μm clumps identified by the FELLWALKER algorithm coincide with Spitzer Gould Belt Survey detections. We identify 23 objects and use Tbol to classify nine YSOs with masses 0.09 to 5.1M⊙. We find two Class 0, one Class 0/I, three Class I and three Class II sources. The mean temperature is 15 ± 2 K for the nine YSOs and 32 ± 4 K for the 14 starless clumps. We observe a starless clump with an abnormally high mean temperature of 46 ± 2 K and conclude that it is radiatively heated by the star MWC 297. Jeans stability provides evidence that radiative heating by the star MWC 297 may be suppressing clump collapse.

Tailoring the surface of a gene delivery vector with carboxymethylated dextran: a systematic analysis - Fortier, Charles; Louvier, Elodie; Durocher, Yves; De Crescenzo, Gregory (Biomacromolecules, 2015)
Polymeric nanocarriers are attractive nonviral vectors for gene delivery purposes in vivo. For such applications, numerous physiological and subcellular bottlenecks have to be overcome. In that endeavor, each structural feature of nanocarriers can be optimized with respect to its corresponding challenges. Here, we focused on the interface between a model gene delivery nanocarrier and relevant constituents of the physiological environment. We screened a library of carboxymethylated dextrans (CMD) for the electrostatic coating of positively charged nanocarriers. We evaluated the jointed influence of the CMD molecular weight and charge density upon nanocarrier coating with respect to DNase, small ions, plasma proteins, red blood cells, and target cells. A total of 4 out of 26 CMD coated nanocarriers successfully passed every screening assay, but did not yield increased reporter gene expression in target cells compared to uncoated nanocarriers. The fine-tuning of CMD for nanocarrier coating yielded a relevant shortlist of candidates that will be further tested in vivo.
Keywords: dextran; electrostatic coatings; gene transfer; physiological models; carboxymethylated dextran; gene delivery vectors; physiological environment; polymeric nanocarriers; positively charged; reporter-gene expression; gene expression; carboxymethyldextran; deoxyribonuclease; nanocarrier; plasma protein; plasmid DNA; polymer; adsorption; erythrocyte; human cell; nanoencapsulation; nonviral gene delivery system; particle size; sheep; surface property; target cell

Modeling of erodent particle trajectories in slurry flow - Ma, Liang; Huang, Cheng; Xie, Yongsong; Jiang, Jiaren; Tufa, Kidus Yoseph; Hui, Rob; Liu, Zhong-Sheng (Wear, 2015)
This paper presents a method for calculating erodent particle trajectories in slurry flow. It involves computational fluid dynamics (CFD) for calculating fluid phase flow, the discrete phase method (DPM) for capturing the movement of erodent particles, and the volume of fluid method (VOF) for calculating interfaces between fluid phase and gas phase. The method is illustrated by application to a lab slurry jet testing system, which considers free water/air interface tracking, particle size distribution and local particle concentration. The validation of the modeling is done by comparing to a glass bead/water jet testing. Using the proposed method, further parametric studies are performed for calculating actual particle speeds and impingement angles under different operating conditions and physical explanations of the modeling results are provided in the end.
Keywords: Fluid dynamics; Particle size; Particle size analysis; Phase interfaces; Trajectories; Different operating conditions; Discrete phase methods; Erosion testing; Impingement angle; Particle concentrations; Particle trajectories; Slurry flow; Volume of fluid method; Computational fluid dynamics

Semiclassical analysis of high harmonic generation in bulk crystals - Vampa, G.; McDonald, C. R.; Orlando, G.; Corkum, P. B.; Brabec, T. (Physical Review B: Condensed Matter and Materials Physics, 2015)
High harmonic generation (HHG) in solids is investigated. We find that interband emission is dominant for the midinfrared laser driver frequencies, whereas intraband emission dominates the far-infrared range. Interband HHG is similar to atomic HHG and therewith opens the possibility to apply atomic attosecond technology to the condensed matter phase. Interband emission is investigated with a quasiclassical method, by which HHG can be modeled based on the classical trajectory analysis of electron-hole pairs. This analysis yields a simple approximate cutoff law for HHG in solids. Differences between HHG in atoms and solids are identified that are important for adapting atomic attosecond technology to make it applicable to condensed matter.

Spectrochimica Acta - Part B Atomic Spectroscopy: Preface - Omenetto, Nicoló; Sturgeon, Ralph (Spectrochimica Acta - Part B Atomic Spectroscopy, 2015)

High-speed transition patterns for video projection, 3D reconstruction, and copyright protection - Boisvert, Jonathan; Drouin, Marc-Antoine; Jodoin, Pierre-Marc (Pattern Recognition, 2015)
This paper presents a camera-projector system which allows for 3D reconstruction and copyright protection. Our approach relies on video-embedded binary patterns whose proportion of black and white at each pixel correspond to the original grayscale value. When projected at a sufficiently high frame rate, these binary patterns are seamless to the observer and look as if a normal video was projected. These patterns have been designed to encode pixel position based on a collection of on-off/off-on transitions. When the camera is properly adjusted, these temporal transitions can be detected with a change detection method and converted into a 3D surface. However, when filmed by an uncalibrated camera, these transitions are not only unreadable, they induce spatial parasitic patterns in the recorded video. Our method is motivated by two families of applications. First, all applications for which a creative visual work needs to be pre-warped according to a 3D model to prevent geometric distortion when displayed on a dynamic scene. Typical examples include augmented reality and plays involving artistic staging. Second, all applications for which a multimedia copyrighted document (e.g. a movie projected in a theater) shall not be copied integrally with a hand-held digital video camera. The interference between the on-off/off-on transitions and the acquisition rate of most consumer-grade cameras creates disturbing visual artifacts. The system can even be adjusted to make sure a 'VOID' pattern appears in the recorded video. In this paper, we present how video frames are encoded and decoded and how the detection (and the nondetection) of temporal transitions allows for 3D reconstruction and copyright protection at the same time. Experimental results reveal that our system computes dense 3D maps at a rate of 11.25 fps and with an accuracy of approximately ±1/2 pixel, i.e. 56 microns when in focus and using a standoff distance of 75 cm.
Keywords: Augmented reality; Cameras; Multimedia systems; Pixels; Signal detection; Three dimensional computer graphics; Video cameras; 3D reconstruction; Camera-projector systems; Change detection; Copyright protections; Digital video cameras; Stand-off distance (SoD); Structured Light; Un-calibrated camera; Copyrights

Detectability of Planck-scale-induced blurring with gamma-ray bursts - Steinbring, Eric (The Astrophysical Journal, 2015)
Microscopic fluctuations inherent to the fuzziness of spacetime at the Planck scale might accumulate in wavefronts propagating a cosmological distance and lead to noticeable blurring in an image of a pointlike source. Distant quasars viewed in the optical and ultraviolet with Hubble Space Telescope (HST) may show this weakly, and if real suggests a stronger effect should be seen for gamma-ray bursts (GRBs) in X-rays and γ-rays. Those telescopes, however, operate far from their diffraction limits. A description of how Planck-scale-induced blurring could be sensed at high energy, including with cosmic rays, while still agreeing with the HST results is discussed. It predicts dilated apparent source size and inflated uncertainties in positional centroids, effectively a threshold angular accuracy restricting knowledge of source location on the sky. These outcomes are found to be consistent with an analysis of the 10 highest-redshift GRB detections reported for the Fermi satellite. Confusion with photon cascade and scattering phenomena is also possible; prospects for a definitive multiwavelength measurement are considered.

A megacam survey of outer halo satellites. IV. Two foreground populations possibly associated with the Monoceros substructure in the direction of NGC 2419 and Koposov 2 - Carballo-Bello, Julio A.; Muñoz, Ricardo R.; Carlin, Jeffrey L.; Côté, Patrick; Geha, Marla; Simon, Joshua D.; Djorgovski, S. G. (The Astrophysical Journal, 2015)
The origin of the Galactic halo stellar structure known as the Monoceros Ring is still under debate. In this work, we study this halo substructure using deep Canada-France-Hawaii Telescope wide-field photometry obtained for the globular clusters NGC 2419 and Koposov 2, where the presence of Monoceros becomes significant because of their coincident projected position. Using Sloan Digital Sky Survey photometry and spectroscopy in the area surrounding these globulars and beyond, where the same Monoceros population is detected, we conclude that a second feature, which is not likely to be associated with Milky Way disk stars along the line of sight, is present as a foreground population. Our analysis suggests that the Monoceros Ring might be composed of an old stellar population of age t ∼9 Gyr and a new component ∼4 Gyr younger at the same heliocentric distance. Alternatively, this detection might be associated with a second wrap of Monoceros in that direction of the sky and might also indicate a metallicity spread in the ring. The detection of such a low-density feature in other sections of this halo substructure will shed light on its nature.

Nanoscale plasmonic stamp lithography on silicon - Liu, Fenglin; Luber, Erik J.; Huck, Lawrence A.; Olsen, Brian C.; Buriak, Jillian M. (ACS Nano, 2015)
Nanoscale lithography on silicon is of interest for applications ranging from computer chip design to tissue interfacing. Block copolymer-based self-assembly, also called directed self-assembly (DSA) within the semiconductor industry, can produce a variety of complex nanopatterns on silicon, but these polymeric films typically require transformation into functional materials. Here we demonstrate how gold nanopatterns, produced via block copolymer self-assembly, can be incorporated into an optically transparent flexible PDMS stamp, termed a plasmonic stamp, and used to directly functionalize silicon surfaces on a sub-100 nm scale. We propose that the high intensity electric fields that result from the localized surface plasmons of the gold nanoparticles in the plasmonic stamps upon illumination with low intensity green light, lead to generation of electron-hole pairs in the silicon that drive spatially localized hydrosilylation. This approach demonstrates how localized surface plasmons can be used to enable functionalization of technologically relevant surfaces with nanoscale control.
Keywords: Block copolymers; Copolymers; Electric fields; Films; Functional materials; Gold; Hydrosilylation; Lithography; Nanolithography; Nanotechnology; Semiconducting silicon; Semiconductor device manufacture; Silicon; Surface plasmon resonance; Block copolymer self-assembly; Directed self-assembly; Electron hole pairs; Functionalizations; Localized surface plasmon; Nano pattern; Nanoscale lithography; Semiconductor industry; Plasmons

Sodiation vs. lithiation phase transformations in a high rate-high stability SnO2 in carbon nanocomposite - Ding, Jia; Li, Zhi; Wang, Huanlei; Cui, Kai; Kohandehghan, Alireza; Tan, Xuehai; Karpuzov, Dimitre; Mitlin, David (Journal of Materials Chemistry A, 2015)
We employed a glucose mediated hydrothermal self-assembly method to create a SnO2-carbon nanocomposite with promising electrochemical performance as both a sodium and a lithium ion battery anode (NIBs NABs SIBs, LIBs), being among the best in terms of cyclability and rate capability when tested against Na. In parallel we provide a systematic side-by-side comparison of the sodiation vs. lithiation phase transformations in nano SnO2. The high surface area (338 m2 g-1) electrode is named C-SnO2, and consists of a continuous Li and Na active carbon frame with internally imbedded sub-5 nm SnO2 crystallites of high mass loading (60 wt%). The frame imparts excellent electrical conductivity to the electrode, allows for rapid diffusion of Na and Li ions, and carries the sodiation/lithiation stresses while preventing cycling-induced agglomeration of the individual crystals. C-SnO2 employed as a NIB anode displays a reversible capacity of 531 mA h g-1 (at 0.08 A g-1) with 81% capacity retention after 200 cycles, while capacities of 240, 188 and 133 mA h g-1 are achieved at the much higher rates of 1.3, 2.6 and 5 A g-1. As a LIB anode C-SnO2 maintains a capacity of 1367 mA h g-1 (at 0.5 A g-1) after 400 cycles, and 420 mA h g-1 at 10 A g-1. Combined TEM, XRD and XPS prove that the much lower capacity of SnO2 as a NIB anode is due to the kinetic difficulty of the Na-Sn alloying reaction to reach the terminal Na15Sn4 intermetallic, whereas for Li-Sn the Li22Sn5 intermetallic is readily formed at 0.01 V. Rather, with applied voltage a significant portion of the material effectively shuffles between SnO2 and β-Sn + NaO2. The conversion reaction proceeds differently in the two systems: LiO2 is reduced directly to SnO2 and Li, whereas the NaO2 to SnO2 reaction proceeds through an intermediate SnO phase.
Keywords: Carbon; Intermetallics; Lithium; Lithium alloys; Lithium-ion batteries; Nanocomposites; Phase transitions; Reaction intermediates; Self assembly; Tin; Capacity retention; Carbon nanocomposite; Conversion reactions; Electrical conductivity; Electrochemical performance; Lithium-ion battery anodes; Reversible capacity; Self-assembly method; Electrodes

Complex of GM1-and GD1a-Likelipo-Oligosaccharide mimics GM1b,inducing anti-GM1b antibodies - Koga, Michiaki; Gilbert, Michel; Li, Jianjun; Yuki, Nobuhiro (PLoS ONE, 2015)
Objective Molecular mimicry between Campylobacter jejuni lipo-oligosaccharides (LOSs) and human gangliosides GM1 and GD1a induces the production of anti-GM1 and anti-GD1a antibodies, and the development of Guillain-Barré syndrome. Complexes of two different gangliosides form new molecular shapes capable of enhancing recognition by anti-ganglioside antibodies. To test the hypothesis that the complex of GM1-like and GD1a-like LOSs of C. jejuni induces the development of anti-GM1b antibodies in Guillain-Barré syndrome patients. Methods Mass spectrometry analysis determined the LOS outer core structures, with which mice were immunized. IgG antibodies to single gangliosides and complex of gangliosides were tested in sera from Guillain-Barré syndrome patients from whom C. jejuni LOS had been isolated. Results Two isolates from GBS patients who had anti-GM1b antibodies, but neither anti-GM1 nor -GD1a antibodies, expressed both GM1-like and GD1a-like LOSs, but not GM1b-like LOS. Anti-GM1b antibodies were induced in one of the mice immunized with the C. jejuni bearing GM1-like and GD1a-like LOS. Sera from 20 patients had antibodies to the complex of GM1 and GD1a, all of which carried anti-GM1b reactivity. Five of these sera harbored neither anti-GM1 nor anti-GD1a antibodies. IgG antibodies to the complex were absorbed by GM1b, but by neither GM1 nor GD1a. Conclusions GM1-like and GD1a-like LOSs form a GM1b epitope, inducing the development of anti- GM1b antibodies in patients with Guillain-Barré syndrome subsequent to C. jejuni enteritis. Here, we present a new paradigm that the complex of two different structures forms a new molecular mimicry, inducing the production of autoantibodies.
Keywords: ganglioside GD 1a; ganglioside GD 1a like lipooligosaccharide; ganglioside GM1; ganglioside GM1 antibody; ganglioside GM1b; ganglioside GM1b antibody; immunoglobulin G antibody; lipooligosaccharide; adolescent; adult; aged; animal experiment; bacterial strain; Campylobacter jejuni; controlled study; cross reaction; enzyme linked immunosorbent assay; female; Guillain Barre syndrome; human; immunization; immunohistochemistry; major clinical study; male; mass spectrometry; mouse; nonhuman; thin layer chromatography; Campylobacter jejuni

Chemical bonding and surface interactions in Bi2Se3 and Bi4Se3 - Christian, Matthew S.; Whittleton, Sarah R.; Otero-de-la-Roza, Alberto; Johnson, Erin R. (Computational and Theoretical Chemistry, 2015)
Topological insulators are a new class of materials that are insulators in the bulk but have near zero electron transport dissipation behavior on the surface. These surface states are topologically robust (resistant to impurities, defects, and geometry deformations), which makes these materials ideal candidates for a number of technological applications. Well-known three-dimensional topological insulators are bismuth selenide (Bi2Se3), which is composed of five-atom-thick layers that interact non-covalently with each other, and Bi-Se alloys resulting from combining these quintuple layers with elemental bismuth bilayers. In this article, we examine the surface sliding and binding energetics of the combinations of quintuple layers and bisumth bilayers found in Bi2Se3 and Bi4Se3. In addition, we investigate the nature of the chemical bonding in these systems and its relation to the surface energetics.

Nitrous oxide, methane and carbon dioxide dynamics from experimental pig graves - Dalva, M.; Moore, T. R.; Kalacska, M.; Leblanc, G.; Costopoulos, A. (Forensic Science International, 2015)
Twelve pig carcasses were buried in single, shallow and deep (30 and 90cm, respectively) graves at an experimental site near Ottawa, Ontario, Canada, with three shallow and three deep wrapped in black plastic garbage bags. An additional six carcasses were left at the surface to decompose, three of which were bagged. Six reference pits without remains were also dug. The objective of this three-year study was to examine the biogeochemistry and utility of nitrous oxide (N2O), methane (CH4) and carbon dioxide (CO2) in grave detection and whether grave depth or cadaver condition (bagged versus bare) affected soil pore air concentrations and emission of the three gases. Graves showed significantly higher (α=0.05) concentrations and surface fluxes of N2O and CO2 than reference pits, but there was no difference in CH4 between graves and reference pits. While CH4 decreased with depth in the soil profiles, N2O and CO2 showed a large increase compared to reference pits. Shallow graves showed significantly higher emissions and pore air concentrations of N2O and CO2 than deep graves, as did bare versus bagged carcasses.
Keywords: carbon dioxide; methane; nitrous oxide; air pollution; air temperature; biogeochemistry; carbon footprint; carcass; concentration (parameters); controlled study; gas transport; methane emission; nitrous oxide emission; swine

Probabilistic analysis of local ice loads on a lifeboat measured in full-scale field trials - Rahman, Md Samsur; Taylor, Rocky S.; Kennedy, Allison; Ré, António Simões; Veitch, Brian (Journal of Offshore Mechanics and Arctic Engineering, 2015)
This paper presents an analysis of local ice loads measured during full-scale field trials conducted in 2014 with a totally enclosed motor propelled survival craft (TEMPSC) in controlled pack ice conditions. These data were collected as part of an ongoing research program that aims to identify the limitations of conventional TEMPSC operating in sea ice environments and to provide insight as to how these limitations might be extended. During the 2014 trials, local ice loads were measured at two locations on the TEMPSC's bow area. These loads were the most severe measured to date and corresponded to an average ice floe mass that was approximately 1.25 times the mass of the fully loaded TEMPSC. The event-maximum method of local ice pressure analysis was used to analyze these field data to improve understanding of the nature of ice loads for such interactions and to evaluate the suitability of this approach for design load estimation for TEMPSCs (i.e., lifeboats) in ice. The event-maximum method was adapted for the present application, so as to link exceedance probabilities with design load levels for a given scenario. Comparison of the 2014 results with a previous analysis of 2013 field trials data supports earlier conclusions that these interactions are highly influenced by kinetic energy, since more massive ice floes are observed to impart significantly higher loads on the lifeboats. Illustrative examples examining the influence of ice concentration and sail-away distance have also been provided. The work establishes links between extreme loads and the exposure of the lifeboat to ice for different operating conditions. Based on this work it is concluded that the event-maximum method provides a promising approach for establishing risk-based design criteria for lifeboats if field data are available which adequately represent ice conditions encountered during the design life of the lifeboat.
Keywords: Kinetics; Lifeboats; Sea ice; Different operating conditions; Exceedance probability; Full-scale field trials; Ice concentration; Pressure analysis; Probabilistic analysis; Risk-based design; Ice; kinetic energy; pack ice; ship design

Detection of atherosclerotic plaque from optical coherence tomography images using texture-based segmentation - Prakash, Ammu; Hewko, Mark D.; Sowa, Michael; Sherif, Sherif S. (Sovremennye Tehnologii v Medicine, 2015)
Detection of atherosclerotic plaque from optical coherence tomography (OCT) images by visual inspection is difficult. We developed a texture based segmentation method to identify atherosclerotic plaque automatically from OCT images without any reliance on visual inspection. Our method involves extraction of texture statistical features (spatial gray level dependence matrix method), application of an unsupervised clustering algorithm (K-means) on these features, and mapping of the clustered regions: background, plaque, vascular tissue and an OCT degraded signal region in feature-space, back to the actual image. We verified the validity of our results by visual comparison to photographs of the vascular tissue with atherosclerotic plaque that were used to generate our OCT images. Our method could be potentially used in clinical studies in OCT imaging of atherosclerotic plaque.
Keywords: atherosclerotic plaque; automatic thresholding technique; binary image; controlled study; histogram; image analysis; image clustering algorithm; image processing; image quality; interferometer; optical coherence tomography; spatial dependence matrix; spatial gray level dependent matrix method; swept source optical coherence tomography; texture segmentation; vascular tissue; Watanabe heritable hyperlipidemic rabbit

Evaluation, design and optimization for strength and integrity of polar class propellers - Liu, Pengfei; Bose, Neil; Veitch, Brian (Cold Regions Science and Technology, 2015)
An advanced 3D unsteady panel method was developed for the design and optimization of the strength and integrity of polar class propellers. Blade ice loading specification in both milling and impact cases, under the Unified Polar Class Rules (URI3), by the International Association of Classification Societies (IACS), was implemented. An optimization example and analysis were given for an R-class propeller. The strength of the R-class propeller was assessed for all 7 polar classes and 5 loading cases. Comparison was also made for all polar classes and ice loading cases. As the blade has little skew with a wide chord, both the spindle torque and the in-plane bending moment are small, so only out-of-plane bending failure is the key factor for strength. It was also found that by URI3, there is little difference in strength requirement between polar classes 1 (strongest requirement) and 7 (the weakest). An integrity design and optimization example showed a saving of 1.4. tonnes of blade material (22% saving) by decreasing the safety factor to 1.51 (the minimum safety factor under URI3 is 1.5), for which case the blade thickness is about 80% of the existing design.
Keywords: Bending moments; Ice; Offshore structures; Pipeline bends; Propellers; Safety factor; Design and optimization; Ice-structure interaction; In-plane bending moment; International association of classification societies; Minimum safety factor; Out-of-plane bending; Polar class; R-class; Loading; bending; design; fluid-structure interaction; ice breaker; ice-structure interaction; navigation; optimization; panel data

Classical-map hypernetted chain calculations for dense plasmas - Bredow, R.; Bornath, T.; Kraeft, W. -D.; Dharma-wardana, M. W. C.; Redmer, R. (Contributions to Plasma Physics, 2015)
Warm dense matter is of interest for modeling the interiors of planets and Brown Dwarfs. Corresponding pump-probe experiments are performed at free electron laser facilities such as FLASH, LCLS or the future XFEL in Hamburg. X-ray Thomson scattering is of special interest to extract the plasma parameters. In order to explain or predict the X-ray Thomson scattering spectra, simulations on the structural properties of plasmas are performed. While ab initio simulations are computationally expensive, semi-classical approaches can deliver results fast for pair distribution functions and static structure factors, even for dense systems. We solve the Ornstein-Zernike equation within the hypernetted chain approximation for dense multi-component plasmas using the classical-map method. This approach proposes to treat the quantum features of the electrons using an adapted temperature for the electron system while the ions are treated classically. Results for pair distribution functions and static structure factors are presented for dense hydrogen, beryllium, carbon and CH plasmas.

Effective density and mass-mobility exponent of aircraft turbine particulate matter - Johnson, Tyler J.; Olfert, Jason S.; Symonds, Jonathan P. R.; Johnson, Mark; Rindlisbacher, Theo; Swanson, Jacob J.; Boies, Adam M.; Thomson, Kevin; Smallwood, Greg; Walters, David; Sevcenco, Yura; Crayford, Andrew; et al. (Journal of Propulsion and Power, 2015)
A centrifugal particle mass analyzer and a modified differential mobility spectrometer were used to measure the mass and mobility of particulate matter emitted by CFM56-5B4/2P, CFM56-7B26/3, and PW4000-100 gas turbine engine sources. The mass-mobility exponent of the particulate matter from the CFM56-5B4/2P engine ranged from 2.68 to 2.82, whereas the effective particle densities varied from 600 to 1250 kg/m3, depending on the static engine thrust and sampling methodology used. The effective particle densities from the CFM56-7B26/3 and PW4000-100 engines also fell within this range. The sample was conditioned with or without a catalytic stripper and with or without dilution, which caused the effective density to change, indicating the presence of condensed semivolatile material on the particles. Variability of the determined effective densities across different engine thrusts, based on the scattering about the line of best fit, was lowest for the diluted samples and highest for the undiluted sample without a catalytic stripper. This variability indicates that the relative amount of semivolatile material produced was engine thrust dependent. It was found that the nonvolatile particulate matter, effective particle density (in kilograms per cubic meter) of the CFM56-5B4/2P engine at relative thrusts below 30% could be approximated using the particle mobility diameter (dme in meters) with 11.92d(2.76-3) me.
Keywords: Engines; Gas turbines; Aircraft turbines; Catalytic stripper; Centrifugal particle mass analyzers; Differential mobility spectrometers; Effective density; Particle densities; Particulate Matter; Semi-volatile materials; Particles (particulate matter)

Algae-dewatering using rotary drum vacuum filters: Process modeling, simulation and techno-economics - Shao, Pinghai; Darcovich, Ken; McCracken, Thom; Ordorica-Garcia, Guillermo; Reith, Michael; O'Leary, Stephen (Chemical Engineering Journal, 2015)
Clean and energy-efficient rotary drum vacuum filtration was selected to conduct algae-dewatering. The dynamic formation of an algal cake-layer on the filter surface was modeled by correlating the cake-layer permeability to the physical parameters of algae and cake-layer. The compressibility of algal cake-layer was taken into consideration in the modeling, and its effect on the algae-dewatering is discussed.The dewatering process was simulated to determine the process energy demand. Process economics were assessed considering the dewatering cost, which includes capital investment and energy cost and also labor, installation, maintenance and infrastructure. Optimal operating conditions and minimum dewatering cost were achieved by process optimization, and two cost-sensitive zones in operating the filtration were identified. The techno-economics showed that the dewatering cost can be further reduced by scaling up the process.
Keywords: Algae; Costs; Economics; Energy efficiency; Filtration; Investments; Optimization; Process control; Process engineering; Vacuum technology; Algae dewatering; Capital and energy; Capital investment; Optimal operating conditions; Physical parameters; Process modeling and simulations; Rotary drum vacuum filter; Techno-economics; Dewatering; algae

Critical assessment of influenza VLP production in Sf9 and HEK293 expression systems - Thompson, Christine M.; Petiot, Emma; Mullick, Alaka; Aucoin, Marc G.; Henry, Olivier; Kamen, Amine A. (BMC Biotechnology, 2015)
Background: Each year, influenza is responsible for hundreds of thousand cases of illness and deaths worldwide. Due to the virus' fast mutation rate, the World Health Organization (WHO) is constantly on alert to rapidly respond to emerging pandemic strains. Although anti-viral therapies exist, the most proficient way to stop the spread of disease is through vaccination. The majority of influenza vaccines on the market are produced in embryonic hen's eggs and are composed of purified viral antigens from inactivated whole virus. This manufacturing system, however, is limited in its production capacity. Cell culture produced vaccines have been proposed for their potential to overcome the problems associated with egg-based production. Virus-like particles (VLPs) of influenza virus are promising candidate vaccines under consideration by both academic and industry researchers. Methods: In this study, VLPs were produced in HEK293 suspension cells using the Bacmam transduction system and Sf9 cells using the baculovirus infection system. The proposed systems were assessed for their ability to produce influenza VLPs composed of Hemagglutinin (HA), Neuraminidase (NA) and Matrix Protein (M1) and compared through the lens of bioprocessing by highlighting baseline production yields and bioactivity. VLPs from both systems were characterized using available influenza quantification techniques, such as single radial immunodiffusion assay (SRID), HA assay, western blot and negative staining transmission electron microscopy (NSTEM) to quantify total particles. Results: For the HEK293 production system, VLPs were found to be associated with the cell pellet in addition to those released in the supernatant. Sf9 cells produced 35 times more VLPs than HEK293 cells. Sf9-VLPs had higher total HA activity and were generally more homogeneous in morphology and size. However, Sf9 VLP samples contained 20 times more baculovirus than VLPs, whereas 293 VLPs were produced along with vesicles. Conclusions: This study highlights key production hurdles that must be overcome in both expression platforms, namely the presence of contaminants and the ensuing quantification challenges, and brings up the question of what truly constitutes an influenza VLP candidate vaccine.
Keywords: Antigen-antibody reactions; Antigens; Cell culture; Cytology; Disease control; Mammals; Transmission electron microscopy; Vaccines; Viruses; Mammalian cells; Process development; Virus-like particles; influenza vaccine; matrix protein; virus hemagglutinin; virus sialidase; animal cell; baculovirus expression system; drug design; drug purity; drug synthesis; HEK293 cell line; human; immunodiffusion; influenza; Influenza virus; insect cell; negative staining transmission electron microscopy; nonhuman; protein analysis; SF9 cell line; transmission electron microscopy; virus like agent; Western blotting; Hexapoda; Mammalia; Orthomyxoviridae

On the onset of the asymptotic stable fracture region in the mode II fatigue delamination growth behaviour of composites - Rans, Calvin David; Atkinson, Jeremy; Li, Chun (Journal of Composite Materials, 2015)
An experimental investigation aimed at identifying the presence and onset of an asymptotic stable fracture region in the mode II fatigue delamination growth behaviour of composites is presented. The study is motivated by the possibility that experimental data sets, particularly those obtained at high R-ratios, may unknowingly contain data points within the asymptotic stable fracture region that influence its perceived log-linear behaviour and the fit of various log-linear delamination growth models. Results from the experimental investigation indicate that the asymptotic stable fracture region can extend to GIImax values as low as 0.7GIIc. The implications of this result on characterizing and fitting of various delamination growth models (including models assuming log-linear behaviour) to delamination growth behaviour are discussed.
Keywords: Fatigue of materials; Fracture; Asymptotic behaviour; Data points; Delamination growth; Experimental investigations; Fatigue delamination; High R-ratio; Mode II; Delamination

Toxin profile of Gymnodinium catenatum (Dinophyceae) from the Portuguese coast, as determined by liquid chromatography tandem mass spectrometry - Costa, Pedro R.; Robertson, Alison; Quilliam, Michael A. (Marine Drugs, 2015)
The marine dinoflagellate Gymnodinium catenatum has been associated with paralytic shellfish poisoning (PSP) outbreaks in Portuguese waters for many years. PSP syndrome is caused by consumption of seafood contaminated with paralytic shellfish toxins (PSTs), a suite of potent neurotoxins. Gymnodinium catenatum was frequently reported along the Portuguese coast throughout the late 1980s and early 1990s, but was absent between 1995 and 2005. Since this time, G. catenatum blooms have been recurrent, causing contamination of fishery resources along the Atlantic coast of Portugal. The aim of this study was to evaluate the toxin profile of G. catenatum isolated from the Portuguese coast before and after the 10-year hiatus to determine changes and potential impacts for the region. Hydrophilic interaction liquid chromatography tandem mass spectrometry (HILIC-MS/MS) was utilized to determine the presence of any known and emerging PSTs in sample extracts. Several PST derivatives were identified, including the N-sulfocarbamoyl analogues (C1-4), gonyautoxin 5 (GTX5), gonyautoxin 6 (GTX6), and decarbamoyl derivatives, decarbamoyl saxitoxin (dcSTX), decarbamoyl neosaxitoxin (dcNeo) and decarbamoyl gonyautoxin 3 (dcGTX3). In addition, three known hydroxy benzoate derivatives, G. catenatum toxin 1 (GC1), GC2 and GC3, were confirmed in cultured and wild strains of G. catenatum. Moreover, two presumed N-hydroxylated analogues of GC2 and GC3, designated GC5 and GC6, are reported. This work contributes to our understanding of the toxigenicity of G. catenatum in the coastal waters of Portugal and provides valuable information on emerging PST classes that may be relevant for routine monitoring programs tasked with the prevention and control of marine toxins in fish and shellfish.
Keywords: 3 hydroxybenzoic acid; decarbamoyl gonyautoxin 3; decarbamoyl neosaxitoxin; decarbamoylsaxitoxin; gonyautoxin; gonyautoxin 5; gonyautoxin 6; gymnodinium catenatum toxin 1; gymnodinium catenatum toxin 2; gymnodinium catenatum toxin 3; gymnodinium catenatum toxin 5; gymnodinium catenatum toxin 6; marine toxin; n sulfocarbamoyl derivative; shellfish toxin; conformation; dinoflagellate; Gymnodinium catenatum; hydrophilic interaction chromatography; nonhuman; phase transition; Portugal; tandem mass spectrometry; toxin analysis; algae; Dinophyceae

Synchrotron based phase contrast X-ray imaging combined with FTIR spectroscopy reveals structural and biomolecular differences in spikelets play a significant role in resistance to Fusarium in wheat - Lahlali, Rachid; Karunakaran, Chithra; Wang, Lipu; Willick, Ian; Schmidt, Marina; Liu, Xia; Borondics, Ferenc; Forseille, Lily; Fobert, Pierre R.; Tanino, Karen; Peng, Gary; Hallin, Emil (BMC Plant Biology, 2015)
Background: Fusarium head blight (FHB), a scab principally caused by Schw., is a serious disease of wheat. The purpose of this study is to evaluate the potential of combining synchrotron based phase contrast X-ray imaging (PCI) with Fourier Transform mid infrared (FTIR) spectroscopy to understand the mechanisms of resistance to FHB by resistant wheat cultivars. Our hypothesis is that structural and biochemical differences between resistant and susceptible cultivars play a significant role in developing resistance to FHB. Results: Synchrotron based PCI images and FTIR absorption spectra (4000-800 cm) of the floret and rachis from Fusarium-damaged and undamaged spikes of the resistant cultivar 'Sumai3', tolerant cultivar 'FL62R1', and susceptible cultivar 'Muchmore' were collected and analyzed. The PCI images show significant differences between infected and non-infected florets and rachises of different wheat cultivars. However, no pronounced difference between non-inoculated resistant and susceptible cultivar in terms of floret structures could be determined due to the complexity of the internal structures. The FTIR spectra showed significant variability between infected and non-infected floret and rachis of the wheat cultivars. The changes in absorption wavenumbers following pathogenic infection were mostly in the spectral range from 1800-800 cm. The Principal Component Analysis (PCA) was also used to determine the significant chemical changes inside floret and rachis when exposed to the FHB disease stress to understand the plant response mechanism. In the floret and rachis samples, PCA of FTIR spectra revealed differences in cell wall related polysaccharides. In the florets, absorption peaks for Amide I, cellulose, hemicellulose and pectin were affected by the pathogenic fungus. In the rachis of the wheat cultivars, PCA underlines significant changes in pectin, cellulose, and hemicellulose characteristic absorption spectra. Amide II and lignin absorption peaks, persistent in the rachis of Sumai3, together with increased peak shift at 1245 cm after infection with FHB may be a marker for stress response in which the cell wall compounds related to pathways for lignification are increased. Conclusions: Synchrotron based PCI combined with FTIR spectroscopy show promising results related to FHB in wheat. The combined technique is a powerful new tool for internal visualisation and biomolecular monitoring before and during plant-microbe interactions to understand both the differences between cultivars and their different responses to disease stress.

Passive air breathing flat-plate microbial fuel cell operation - Kazemi, Sona; Mohseni, Madjid; Fatih, Khalid (Journal of Chemical Technology and Biotechnology, 2015)
BACKGROUND: High cost and ohmic loss are two issues that microbial fuel cells (MFC) face before becoming economically viable. To address the high cost and ohmic loss issues, a flat-plate MFC (FPMFC) configuration applying a passive air-breathing cathode and a three-dimensional anode was introduced. Electricity generation was examined in the FPMFC through operation in the presence and absence of a proton exchange membrane (PEM), and in batch and continuous modes. RESULTS: Continuous operation of the FPMFC in the presence of a PEM favored power generation, mainly due to elimination of oxygen and biomass in the anode. Peak power density of 18 Wm-3 was produced in the presence of a PEM (ohmic resistance 40 Ω cm2), which was more than 5-fold higher than that with J-cloth. During batch operation, the power density increased and reached maximum in the third batch (18 W m-3 at 60 A m-3). Greater stability was observed during continuous operation resulting in a 2.5-fold increase in peak power density (44 W m-3 at 146 A m-3). CONCLUSION: The passive air-breathing FPMFC showed promising performance, offering a more economically viable configuration than the conventional FPMFCs using active (air, ferricyanide, and ferric iron) cathodes.
Keywords: Cathodes; Electrodes; Fuel cells; Ohmic contacts; Wastewater treatment; Batch operation; Biocatalysis; Continuous operation; Ethanol oxidation; Flat plate; Passive air; batch process; biocatalyst; biomass; chemical oxygen demand; chemical reaction kinetics; density; electricity; electrochemical impedance spectroscopy; flat plate microbial fuel cell; membrane; microbial fuel cell; passive air breathing; peristaltic pump; polarization; proton exchange membrane

Continuous resistance welding of thermoplastic composites: Modelling of heat generation and heat transfer - Shi, Huajie; Villegas, Irene Fernandez; Octeau, Marc-André; Bersee, Harald E. N.; Yousefpour, Ali (Composites Part A: Applied Science and Manufacturing, 2015)
A process model composed of electrical and heat transfer models was developed to simulate continuous resistance welding of thermoplastic composites. Glass fabric reinforced polyphenylenesulfide welded in a lap-shear configuration with a stainless steel mesh as the heating element was considered for modelling and experimental validation of the numerical results. The welding temperatures predicted by the model showed good agreement with the experimental results. Welding input power and welding speed were found to be the two most important parameters influencing the welding temperature. The contact quality between the electrical connectors and the heating element was found to influence the distribution of the welding temperature transverse to the welding direction. Moreover, the size of the electrical connectors was found to influence the achievable welding speed and required power input for a certain welding temperature.
Keywords: Composite materials; Electric connectors; Electric heating elements; Heat resistance; Heat transfer; Plastics; Polymer matrix composites; Reinforced plastics; Resistance welding; Stainless steel; Thermoplastics; Continuous resistances; E. Joints/Joining; Electrical connectors; Experimental validations; Thermoplastic composite; Welding temperatures; Welding

Influence of feeding a high plant protein diet on growth and nutrient utilization to combined 'all-fish' growth-hormone transgenic diploid and triploid Atlantic salmon (Salmo salar L.) - Ganga, R.; Tibbetts, S. M.; Wall, C. L.; Plouffe, D. A.; Bryenton, M. D.; Peters, A. R.; Runighan, C. D.; Buchanan, J. T.; Lall, S. P. (Aquaculture, 2015)
This study assessed the capacity of non-transgenic (NTG) and growth-hormone transgenic (TG; gene construct EO-1α) Atlantic salmon (. Salmo salar L.), comprised of conventional diploid (DIP) and reproductively-sterile triploid (TRIP) fish, to utilize a diet containing relatively high amounts of plant protein (PP) concomitant with lower levels of fish meal (FM) protein. Triplicate groups of full-sibling NTG/DIP, NTG/TRIP, TG/DIP and TG/TRIP salmon (initial weight, 27-35. g) were held in freshwater and fed two experimental diets until they exceeded 400% growth. Two isonitrogenous (50% crude protein), isolipidic (21% lipid) and isoenergetic (22. MJ/kg gross energy) experimental diets were tested. The control diet (FM) contained 64 and 36%, while PP diet contained 32 and 68% of total dietary protein from FM and PP, respectively. TG and NTG fish achieved the target (>. 150. g) weight in 89 and 206. days, respectively. TG fish exhibited significantly higher specific growth rates (SGR) (2.48 vs 0.7%/day) and thermal growth coefficient (TGC) (3.04 vs 0.79) than NTG, regardless of ploidy or diet. TG/TRIP fish had significantly lower growth rates than DIP due to lower feed intake, while no ploidy effect was observed within the NTG group. Feed conversion ratio (FCR) was significantly better in TG/DIP and TG/TRIP fish having achieved the same target weight with 20-25% less feed due to improved protein utilization and retention efficiency compared to NTG fish. NTG fish had higher digestibility of protein (93% vs 89%), lipid (95% vs 94%) and energy (89% vs 85%) relative to their TG siblings, and was similar between DIP and TRIP fish. Nutrients' digestibility was significantly lower in TG fish fed PP diet than those fed FM diet, regardless of ploidy. At the end of the study, TG fish had significantly lower whole-body protein (56% vs 59%) and higher lipid (36% vs 34%) and energy (2746 vs 2694. kJ/100. g) content than NTG fish. However, as a result of the rapid growth rate and efficient feed utilization, nutrient gain and retention efficiencies were significantly higher in TG than NTG fish. DIP and TRIP TG Atlantic salmon have the ability to maintain accelerated growth even when fed a high PP diet (68% of dietary protein), which may have important benefits for the production of growth hormone transgenic Atlantic salmon. Statement of relevance: The results from the present study are innovative and may have important benefits for the optimization and production of growth hormone transgenic Atlantic salmon using sustainable feed ingredients.
Keywords: artificial diet; digestibility; feeding; genetically modified organism; growth rate; hormone; ploidy; protein; salmonid culture; weight; Salmo salar

Cancer modeling and network biology: Accelerating toward personalized medicine - Masoudi-Nejad, Ali; Wang, Edwin (Seminars in Cancer Biology, 2015)
The complexity of cancer progression can manifests itself on at least three scales that can be described using mathematical models, namely microscopic, mesoscopic and macroscopic scales. Multiscale cancer models have proven to be advantageous in this context because they can simultaneously incorporate the many different characteristics and scales of complex diseases such as cancer. This has driven the expansion of more predictive data-driven models, coupled to experimental and clinical data. These models are defining the foundations that facilitate the forthcoming design of patient specific cancer therapy. This should be considered as a great leap toward the era of personalized medicine. Consequently, further improvements in mathematical modeling of cancer will lead to the design of more sophisticated cancer therapy approaches.
Keywords: artificial neural network; cancer modeling; cancer therapy; mathematical model; network biology; personalized medicine; prediction; rating scale; systems biology

Suppressing RNA silencing with small molecules and the viral suppressor of RNA silencing protein p19 - Danielson, Dana C.; Filip, Roxana; Powdrill, Megan H.; O'Hara, Shifawn; Pezacki, John P. (Biochemical and Biophysical Research Communications, 2015)
RNA silencing is a gene regulatory and host defense mechanism whereby small RNA molecules are engaged by Argonaute (AGO) proteins, which facilitate gene knockdown of complementary mRNA targets. Small molecule inhibitors of AGO represent a convenient method for reversing this effect and have applications in human therapy and biotechnology. Viral suppressors of RNA silencing, such as p19, can also be used to suppress the pathway. Here we assess the compatibility of these two approaches, by examining whether synthetic inhibitors of AGO would inhibit p19-siRNA interactions. We observe that aurintricarboxylic acid (ATA) is a potent inhibitor of p19's ability to bind siRNA (IC50=0.43μM), oxidopamine does not inhibit p19:siRNA interactions, and suramin is a mild inhibitor of p19:siRNA interactions (IC50=430μM). We observe that p19 and suramin are compatible inhibitors of RNA silencing in human hepatoma cells. Our data suggests that at least some inhibitors of AGO may be used in combination with p19 to inhibit RNA silencing at different points in the pathway.

Simultaneous soot temperature and volume fraction measurements in axis-symmetric flames by a two-dimensional modulated absorption/emission technique - Legros, G.; Wang, Q.; Bonnety, J.; Kashif, M.; Morin, C.; Consalvi, J.-L.; Liu, F. (Combustion and Flame, 2015)
The original contribution of the present paper is to present a joint theoretical and experimental approach to implement the modulated absorption/emission technique. Two-dimensional fields of soot temperature and volume fraction can then be measured simultaneously in a reference steady laminar coflow axis-symmetric non-premixed ethylene flame established over the Santoro burner. The spontaneous flame emission is captured by two CMOS cameras that allow the measurements of the flame emission intensity at two different wavelengths, i.e., 645. nm and 785. nm in this study. Concomitantly, two 70. mm diameter laser beams are used to pass through the flame, enabling the spectral line-of-sight attenuation to be imaged at the two wavelengths by the CMOS sensors. In these spectral ranges, both absorption and emission phenomena are dominated by soot. The local spectral absorption coefficient and spectral emission rate at both wavelengths are obtained by the onion-peeling method with Tikhonov regularization. The soot volume fraction map is inferred from the spectral absorption coefficient field. Mapping soot temperature does not require any model correlating soot volume fraction and local spectral absorption coefficient. Only the measurements of the latter at both wavelengths are required to enable the self-calibration of the technique and infer soot temperature from the ratio of the local spectral emission rates. Thus, the issue of the large discrepancies in the wavelength-dependent soot refractive index reported in the literature does not arise. Within the region of high soot temperatures, the results obtained by the methodology are in good agreement with numerical and experimental data available in the literature. The use of continuous wave lasers as the light sources enables future investigations in flickering flames where the phenomenon of intermittent soot release through the flame tip still needs to be better understood. © 2015 The Combustion Institute.
Keywords: CMOS integrated circuits; Continuous wave lasers; Ethylene; Flame research; Laser beams; Light sources; Particulate emissions; Photomapping; Refractive index; Soot; Volume fraction; Absorption and emissions; Experimental approaches; Flame emission; Soot diagnostics; Soot volume fraction; Tikhonov regularization; Two different wavelengths; Two dimensional field; Dust

The importance of Au ⋯ π(aryl) interactions in the formation of spherical aggregates in binuclear phosphane gold(I) complexes of a bipodal thiocarbamate dianion: A combined crystallographic and computational study, and anti-microbial activity - Yeo, Chien Ing; Khoo, Chai-Hoon; Chu, Wern-Cui; Chen, Bao-Jing; Chu, Pek-Lim; Sim, Jiun-Horng; Cheah, Yoke-Kqueen; Ahmad, Jimmy; Abdul Halim, Siti Nadiah; Seng, Hoi-Ling; Ng, Soon; Otero-De-La-Roza, A.; et al. (RSC Advances, 2015)
Binuclear phosphanegold(i) complexes of a bipodal thiocarbamate dianion, (R3PAu)2L, R = Et (1), Ph (2) and Cy (3), where LH2 is {1,4-[MeOC(S)N(H)]2C6H4}, have been synthesised, and characterised spectroscopically (NMR and IR) and by X-ray crystallography. The gold atoms are linearly coordinated within a P-,S-donor set, and are oriented toward the central ring to form intramolecular Au ⋯π(aryl) interactions, rather than the intramolecular Au ⋯O interactions normally observed in mononuclear analogues. This phenomenon has been investigated by theory (LC-ωPBE-XDM) for 1 which revealed that the geometry optimised species with two Au ⋯π(aryl) interactions is more stable by at least 12 kcal mol-1 compared to conformations having one or more Au ⋯O interactions instead. The disk diffusion, minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) methods were used to observe the inhibitory effect of complexes 1-3. The disk diffusion results demonstrated that 1 exhibited a broad spectrum of anti-bacterial activity toward 24 strains of Gram-positive and Gram-negative bacteria. By contrast, the anti-bacterial activity of 2 and 3 was limited to Gram-positive bacteria. Further evaluation showed that 1 exhibited marked bactericidal activity against B. cereus, B. subtilis, E. faecalis, L. monocytogenes, S. aureus, S. saprophyticus and methicillin resistant S. aureus cf. standard antibiotics tetracycline and chloramphenicol.
Keywords: Antibiotics; Bacteria; Computation theory; Crystallography; Gold; Gold compounds; Anti-bacterial activity; Anti-microbial activity; Bactericidal activity; Computational studies; Gram-negative bacteria; Gram-positive bacterium; Minimum bactericidal concentration (MBC); Minimum inhibitory concentration; X ray crystallography

Internal photoemission in molecular junctions: Parameters for interfacial barrier determinations - Fereiro, Jerry A.; Kondratenko, Mykola; Bergren, Adam J.; McCreery, Richard L. (Journal of the American Chemical Society, 2015)
The photocurrent spectra for large-area molecular junctions are reported, where partially transparent copper top contacts permit illumination by UV-vis light. The effect of variation of the molecular structure and thickness are discussed. Internal photoemission (IPE), a process involving optical excitation of hot carriers in the contacts followed by transport across internal system barriers, is dominant when the molecular component does not absorb light. The IPE spectrum contains information regarding energy level alignment within a complete, working molecular junction, with the photocurrent sign indicating transport through either the occupied or unoccupied molecular orbitals. At photon energies where the molecular layer absorbs, a secondary phenomenon is operative in addition to IPE. In order to distinguish IPE from this secondary mechanism, we show the effect of the source intensity as well as the thickness of the molecular layer on the observed photocurrent. Our results clearly show that the IPE mechanism can be differentiated from the secondary mechanism by the effects of variation of experimental parameters. We conclude that IPE can provide valuable information regarding interfacial energetics in intact, working molecular junctions, including clear discrimination of charge transport mediated by electrons through unoccupied system orbitals from that mediated by hole transport through occupied system orbitals.
Keywords: Molecular orbitals; Photocurrents; Self assembly; Energy level alignment; Experimental parameters; Interfacial barriers; Interfacial energetics; Internal photoemission; Molecular components; Photocurrent spectrum; Secondary mechanisms; Photoemission; molecular layer; chemical structure; electrochemical analysis; electron transport; illumination; internal photoemission; light absorption; light intensity; molecular electronics; orbit; photon; steady state

Dissociation conditions and Raman spectra of CO2 + SO2 and CO2 + H2S hydrates - Chen, Litao; Lu, Hailong; Ripmeester, John A. (Industrial and Engineering Chemistry Research, 2015)
To further define the information needed for CO2 gas sequestration and storage in the presence of impurities, the stability of hydrates made from CO2 + SO2 and CO2 + H2S mixtures was measured by an isochoric dissociation method. The hydrates were characterized with powder X-ray diffraction, confirming that CO2 + SO2 formed a structure I hydrate. The Raman spectra of CO2 + SO2 and CO2 + H2S hydrates were also measured along with those of THF + CO2 + SO2 and THF + CO2 + H2S hydrates to observe and assign the Raman peaks of SO2 or H2S in the small cages. It was found the SO2 Raman peaks are at 1147.1 and 1155.4 cm–1 in large and small cages, respectively; the H2S Raman peaks are at 2594.0 and 2603.0 cm–1 in large and small cages, respectively. At the equilibrium points established, the composition of the released gas mixture was analyzed by gas chromatography. Measurements for gas pressures (ranging from 0.72 to 3.59 MPa) and gas compositions (ranging from 0.04% to 7.63%, mole fraction of SO2 or H2S) at specific temperatures (ranging from 263.15 to 283.15 K) are reported. The SO2 and H2S impurities tend to stabilize the mixed CO2 hydrates formed, with almost all of the impurity gases reporting with the hydrate phase at low concentrations.
Keywords: Chromatography; Gas chromatography; Gas hydrates; Hydration; Impurities; Raman scattering; X ray diffraction; Dissociation conditions; Dissociation methods; Equilibrium point; Gas compositions; Gas pressures; Hydrate phase; Low concentrations; Powder X ray diffraction; Gases

Influence of the solvent quality on ring polymer dimensions - Gooßen, Sebastian; Brás, Ana R.; Pyckhout-Hintzen, Wim; Wischnewski, Andreas; Richter, Dieter; Rubinstein, Michael; Roovers, Jacques; Lutz, Pierre J.; Jeong, Youncheol; Chang, Taihyun; Vlassopoulos, Dimitris (Macromolecules, 2015)
We present a systematic investigation of well-characterized, experimentally pure polystyrene (PS) rings with molar mass of 161000 g/mol in dilute solutions. We measure the ring form factor at θ- and good-solvent conditions as well as in a polymeric solvent (linear PS of roughly comparable molar mass) by means of small-angle neutron scattering (SANS). Additional dynamic light scattering (DLS) measurements support the SANS data and help elucidate the role of solvent quality and solution preparation. The results indicate the increase of ring dimensions as the solvent quality improves. Furthermore, the experimental form factors in both θ-solvent and linear matrix behave as ideal rings and are fully superimposable. The nearly Gaussian conformations of rings in a melt of linear chains provide evidence of threading of linear chains through rings. The latter result has implications for the dynamics of ring-linear polymer mixtures.
Keywords: Approximation theory; Chains; Dynamic light scattering; Light scattering; Nanocomposites; Neutron scattering; Polymers; Dilute solution; Linear polymers; Ring dimension; Ring polymers; Role of solvents; Solution preparations; Solvent conditions; Solvent quality; Solvents

Cold sprayed Cu-Ni-Fe anode for Al production - Goupil, G.; Jucken, S.; Poirier, D.; Legoux, J. G.; Irissou, E.; Davis, B.; Guay, D.; Roué, L. (Corrosion Science, 2015)
Inert anodes for Al electrolysis were produced by cold spray deposition of mechanical alloyed 65Cu20Ni15Fe powder. No structural change of the 65Cu20Ni15Fe alloy was observed during the cold spray processing apart from a small crystallite size increase. The electrochemical characterization was performed at 700°C in a potassium cryolite-based electrolyte. A progressive increase of the cell voltage was observed during the 50h of electrolysis. This is thought to reflect a decrease of the electrical conductivity of the anode attributed to the accumulation of electrolyte at the oxide/alloy interface and to the formation of insulating FeF2 precipitates in the bulk alloy.
Keywords: Alloys; Crystallite size; Electrodes; Electrolysis; Electrolytes; Mechanical alloying; Cold spray deposition; Cold spray processing; Electrical conductivity; Electrochemical characterizations; Galvanostatics; High temperature corrosions; Mechanical alloyed; Potassium cryolites; Aluminum

Ukaliq: Seeing long-term with small, precise arctic telescopes - Steinbring, Eric; Leckie, Brian; Murowinski, Rick (Journal of Physics: Conference Series, 2015)
Time-domain astrophysics benefits from extreme-latitude sites, which can combine intrinsically extended nighttime with good sky conditions. One such location is the Polar Environment Atmospheric Research Laboratory (PEARL), at 80° North latitude, on the northwestern edge of Ellesmere Island, Canada. Experience gained deploying seeing monitors there has been incorporated into an automated system called "Ukaliq" after the common arctic hare, which is also very well suited to its local environment. Even with modest aperture, high photometric reliability may be achieved using simple adaptive optics together with observing strategies that best fit the unique set of advantages available at PEARL: excellent image quality maintained during many clear, calm, dark periods of 100 hours or more. A potential multi-year search for gravitational microlensing of quasars with Ukaliq helps illustrate this niche in the era of large wide-field survey facilities.
Keywords: Astrophysics; Automation; Research laboratories; Atmospheric research; Automated systems; Local environments; North latitudes; Polar environments; Seeing monitors; Simple adaptive; Wide-field surveys; Adaptive optics

Processing-formulation-performance relationships of polypropylene/short flax fiber composites - Mihai, Mihaela; Chapleau, Nathalie; Denault, Johanne (Journal of Applied Polymer Science, 2015)
This work is a comprehensive study of the effect of extrusion process parameters and formulation on the properties of polypropylene (PP)/short flax fiber composites. The parameters that were varied during the twin-screw extrusion process were screw configuration, revolutions per minute (rpm), extrusion temperature, and flow rate. The effect of the feeding zone location of cellulosic fiber was also considered. This study investigates the effect of the formulation, cellulosic fiber content, the presence of a coupling agent, and of a reactive additive on composite performance. The composites were characterized in terms of morphology and microstructure, fiber length, rheological, thermal, and mechanical properties. Sensibility to humidity and recyclability were also considered. When compared with as-received PP, the tensile strength of injection-molded parts increased with cellulosic content by up to 40 vol %, and the tensile modulus increased 3.5 times when a combination of coupling and reactive agents was used. Exposed to controlled humidity of 50% during 1 year, these composites exhibited a very low level of humidity uptake around 0.85 wt %. The processability of these materials using a cast film line and the mechanical properties of extruded sheets are also presented. Furthermore, these materials demonstrate a good recyclability using injection molding by keeping the integrality of their mechanical properties after five reprocessing cycles.
Keywords: Biological materials; Biomaterials; Cements; Composite materials; Coupling agents; Fibers; Flax; Humidity control; Injection molding; Linen; Mechanical properties; Polypropylenes; Screws; Tensile strength; Thermoplastics; Wood; Yarn; Cellulosic fibers; Controlled humidities; Extrusion process; Extrusion temperatures; Reprocessing cycles; Revolutions per minutes; Screw configurations; Twin screw extrusion; Extrusion

From cellular lysis to microarray detection, an integrated thermoplastic elastomer (TPE) point of care Lab on a Disc - Roy, Emmanuel; Stewart, Gale; Mounier, Maxence; Malic, Lidija; Peytavi, Régis; Clime, Liviu; Madou, Marc; Bossinot, Maurice; Bergeron, Michel G.; Veres, Teodor (Lab on a Chip - Miniaturisation for Chemistry and Biology, 2015)
We present an all-thermoplastic integrated sample-to-answer centrifugal microfluidic Lab-on-Disc system (LoD) for nucleic acid analysis. The proposed CD system and engineered platform were employed for analysis of Bacillus atrophaeus subsp. globigii spores. The complete assay comprised cellular lysis, polymerase chain reaction (PCR) amplification, amplicon digestion, and microarray hybridization on a plastic support. The fluidic robustness and operating efficiency of the assay were ensured through analytical optimization of microfluidic tools enabling beneficial implementation of capillary valves and accurate control of all flow timing procedures. The assay reliability was further improved through the development of two novel microfluidic strategies for reagents mixing and flow delay on the CD platform. In order to bridge the gap between the proof-of-concept LoD and production prototype demonstration, low-cost thermoplastic elastomer (TPE) was selected as the material for CD fabrication and assembly, allowing the use of both, high quality hot-embossing and injection molding processes. Additionally, the low-temperature and pressure-free assembly and bonding properties of TPE material offer a pertinent solution for simple and efficient loading and storage of reagents and other on-board components. This feature was demonstrated through integration and conditioning of microbeads, magnetic discs, dried DNA buffer reagents and spotted DNA array inserts. Furthermore, all microfluidic functions and plastic parts were designed according to the current injection mold-making knowledge for industrialization purposes. Therefore, the current work highlights a seamless strategy that promotes a feasible path for the transfer from prototype toward realistic industrialization. This work aims to establish the full potential for TPE-based centrifugal system as a mainstream microfluidic diagnostic platform for clinical diagnosis, water and food safety, and other molecular diagnostic applications.
Keywords: DNA; elastomer; plastic; thermoplastic elastomer; Bacillus atrophaeus; Bacillus subtilis; bacterial gene; bacterial spore; food safety; industrialization; lysis; microarray analysis; microfluidic analysis; molecular diagnosis; nucleic acid analysis; polymerase chain reaction; Bacillus atrophaeus

Identification of escherichia coli F4ac-binding proteins in porcine milk fat globule membrane - Novakovic, Predrag; Huang, Yanyun Y.; Lockerbie, Betty; Shahriar, Farshid; Kelly, John; Gordon, John R.; Middleton, Dorothy M.; Loewen, Matthew E.; Kidney, Beverly A.; Simko, Elemir (Canadian Journal of Veterinary Research, 2015)
F4ac-positive enterotoxigenic Escherichia coli (ETEC) must attach to the intestinal mucosa to cause diarrhea in piglets. Prevention of bacterial attachment to the intestinal mucosa is the most effective defense against ETEC-induced diarrhea. Porcine milk fat globule membranes (MFGM) were shown to be able to inhibit attachment of ETEC to the intestinal brush border; however, the specific components of porcine MFGM that inhibited attachment of ETEC to enterocytes were not identified. Accordingly, the purpose of this study was to identify F4ac-binding MFGM proteins by overlay Western blot and affinity chromatography. The proteome of porcine MFGM was characterized and the following F4ac-binding proteins were detected by overlay Western blot and affinity chromatography: lactadherin, butyrophilin, adipophilin, acyl-CoA synthetase 3, and fatty acid-binding protein 3. The biological function of these proteins was not investigated but it is possible that their interaction with F4ac fimbria interferes with bacterial attachment and colonization.
Keywords: adipophilin; binding protein; butyrophilin; fatty acid binding protein 3; lactadherin; long chain fatty acid coenzyme A ligase 3; membrane protein; affinity chromatography; binding affinity; enterotoxigenic Escherichia coli; F4ac fimbria; fimbria; liquid chromatography; mass spectrometry; membrane; milk fat globule membrane; nonhuman; polyacrylamide gel electrophoresis; protein analysis; swine; Western blotting; Bacteria (microorganisms); Escherichia coli; Sus

Nanoporous twinned PtPd with highly catalytic activity and stability - Zhang, Xuefeng; Guan, Pengfei; Malic, Lidija; Trudeau, Michel; Rosei, Federico; Veres, Teodor (Journal of Materials Chemistry A, 2015)
Growing needs for highly efficient energy storage devices have prompted increasing research efforts in energy-efficient and sustainable materials. In this context, nanoporous noble metals have been studied extensively because of their extraordinary properties. However, existing electrochemical/chemical dealloying approaches for their synthesis largely lack the ability to optimize their structure/function relationships. To overcome this limitation, we developed a thermal-decomposition strategy for the synthesis of component-controllable nanoporous PtPd alloys composed of ∼2 nm sawtooth-like ligaments induced by a high density of twinning boundaries (boundary spacing ∼ 1 nm). Such twinned and ultrathin ligaments exhibit large curvatures between concave and convex regions, associated with abundant low-coordination surface atomic steps and kinks. These low-coordination atoms are sites of high catalytic activity, as confirmed by theoretical simulations. The optimized Pt25Pd75 sample exhibits the best catalytic performance among all the currently reported catalysts, and has a mass activity of 1110 mA mg-1Pt-1 and high stability for the electro-oxidation of methanol.
Keywords: Catalytic oxidation; Decomposition; Electrooxidation; Energy efficiency; Palladium; Platinum; Catalytic performance; Decomposition strategy; Low coordination; Structure/function relationships; Sustainable materials; Theoretical simulation; Catalyst activity

DC inclined-plane tracking and erosion test of insulating materials - Cherney, E. A.; Gorur, R. S.; Krivda, A.; Jayaram, S. H.; Rowland, S. M.; Li, S.; Marzinotto, M.; Ghunem, R. A.; Ramirez, I. (IEEE Transactions on Dielectrics and Electrical Insulation, 2015)
The paper reviews previous work on the DC inclined plane test and suggests equivalent DC voltage levels in parallel to AC voltage in the ASTM inclined plane tracking and erosion test. The aim of this work is to provide a basis for standardizing the inclined plane test for DC voltage. Round robin tests done in five laboratories on five specimens of a silicone rubber material were done with the purpose of establishing appropriate ratios by which the equivalent DC voltages can be determined with respect to the corresponding AC voltages. These levels were determined as 67% and 87%, for +DC and-DC respectively, of the AC initial tracking voltage, and for practical purposes, these levels are rounded to 70 and 90%.
Keywords: Erosion; Machinery; Routers; Silicones; ASTM D2303; DC voltage; DC voltage level; Erosion test; Inclined planes; Inclined-plane tests; Round Robin test; Silicone rubber; Testing

Identification of the Mamestra configurata (Lepidoptera: Noctuidae) peritrophic matrix proteins and enzymes involved in peritrophic matrix chitin metabolism - Toprak, Umut; Erlandson, Martin; Baldwin, Doug; Karcz, Steve; Wan, Lianglu; Coutu, Cathy; Gillott, Cedric; Hegedus, Dwayne D. (Insect Science, 2015)
The peritrophic matrix (PM) is essential for insect digestive system physiology as it protects the midgut epithelium from damage by food particles, pathogens, and toxins. The PM is also an attractive target for development of new pest control strategies due to its per os accessibility. To understand how the PM performs these functions, the molecular architecture of the PM was examined using genomic and proteomic approaches in Mamestra configurata (Lepidoptera: Noctuidae), a major pest of cruciferous oilseed crops in North America. Liquid chromatography-tandem mass spectrometry analyses of the PM identified 82 proteins classified as: (i) peritrophins, including a new class with a CBDIII domain; (ii) enzymes involved in chitin modification (chitin deacetylases), digestion (serine proteases, aminopeptidases, carboxypeptidases, lipases and α-amylase) or other reactions (β-1,3-glucanase, alkaline phosphatase, dsRNase, astacin, pantetheinase); (iii) a heterogenous group consisting of polycalin, REPATs, serpin, C-Type lectin and Lsti99/Lsti201 and 3 novel proteins without known orthologs. The genes encoding PM proteins were expressed predominantly in the midgut. cDNAs encoding chitin synthase-2 (McCHS-2), chitinase (McCHI), and β-N-acetylglucosaminidase (McNAG) enzymes, involved in PM chitin metabolism, were also identified. McCHS-2 expression was specific to the midgut indicating that it is responsible for chitin synthesis in the PM, the only chitinous material in the midgut. In contrast, the genes encoding the chitinolytic enzymes were expressed in multiple tissues. McCHS-2, McCHI, and McNAG were expressed in the midgut of feeding larvae, and NAG activity was present in the PM. This information was used to generate an updated model of the lepidopteran PM architecture.

Highly tunable microwave and millimeter wave filtering using photonic technology - Seregelyi, Joe; Lu, Ping; Paquet, Stéphane; Celo, Dritan; Mihailov, Stephen J. (Optical Engineering, 2015)
The design for a photonic microwave filter tunable in both bandwidth and operating frequency is proposed and experimentally demonstrated. The circuit is based on a single sideband modulator used in conjunction with two or more transmission fiber Bragg gratings (FBGs) cascaded in series. It is demonstrated that the optical filtering characteristics of the FBGs are instrumental in defining the shape of the microwave filter, and the numerical modeling was used to optimize these characteristics. A multiphase-shift transmission FBG design is used to increase the dynamic range of the filter, control the filter ripple, and maximize the slope of the filter skirts. Initial measurements confirmed the design theory and demonstrated a working microwave filter with a bandwidth tunable from approximately 2 to 3.5 GHz and an 18 GHz operating frequency tuning range. Further work is required to refine the FBG manufacturing process and reduce the impact of fabrication errors.
Keywords: Bandwidth; Bragg gratings; Fiber Bragg gratings; Microwaves; Millimeter waves; Photonics; Fabrication errors; Manufacturing process; Operating frequency; Photonic microwave filters; Photonic technologies; Radiofrequency signals; Single-sideband modulators; Transmission fibers; Microwave filters

In-situ temperature-controllable shear flow device for neutron scattering measurement - An example of aligned bicellar mixtures - Xia, Yan; Li, Ming; Kučerka, Norbert; Li, Shutao; Nieh, Mu-Ping (Review of Scientific Instruments, 2015)
We have designed and constructed a temperature-controllable shear flow cell for in-situ study on flow alignable systems. The device has been tested in the neutron diffraction and has the potential to be applied in the small angle neutron scattering configuration to characterize the nanostructures of the materials under flow. The required sample amount is as small as 1 ml. The shear rate on the sample is controlled by the flow rate produced by an external pump and can potentially vary from 0.11 to 3.8 × 105 s-1. Both unidirectional and oscillational flows are achievable by the setting of the pump. The instrument is validated by using a lipid bicellar mixture, which yields non-alignable nanodisc-like bicelles at low T and shear-alignable membranes at high T. Using the shear cell, the bicellar membranes can be aligned at 31 °C under the flow with a shear rate of 11.11 s-1. Multiple high-order Bragg peaks are observed and the full width at half maximum of the "rocking curve" around the Bragg's condition is found to be 3.5°-4.1°. It is noteworthy that a portion of the membranes remains aligned even after the flow stops. Detailed and comprehensive intensity correction for the rocking curve has been derived based on the finite rectangular sample geometry and the absorption of the neutrons as a function of sample angle [See supplementary material at http://dx.doi.org/10.1063/1.4908165 for the detailed derivation of the absorption correction]. The device offers a new capability to study the conformational or orientational anisotropy of the solvated macromolecules or aggregates induced by the hydrodynamic interaction in a flow field.
Keywords: Mixtures; Neutron diffraction; Neutron scattering; Shear deformation; Temperature control; Absorption corrections; Hydrodynamic interaction; In-Situ Study; In-situ temperature; Neutron scattering measurements; Orientational anisotropy; Rectangular samples; Rocking curves; Shear flow

Elemental characterization of single-wall carbon nanotube certified reference material by neutron and prompt γ activation analysis - Kučera, Jan; Bennett, John W.; Oflaz, Rabia; Paul, Rick L.; De Nadai Fernandes, Elisabete A.; Kubešová, Marie; Bacchi, Mario A.; Stopic, Attila J.; Sturgeon, Ralph E.; Grinberg, Patricia (Analytical Chemistry, 2015)
Instrumental neutron activation analysis with both relative and k0 standardization was used in four experienced laboratories to determine element mass fractions in single-wall carbon nanotube certified reference material (CRM) SWCNT-1. Results obtained were evaluated using the National Institute of Standards and Technology (NIST) "Type B On Bias" approach and yielded consensus values in agreement with National Research Council Canada (NRCC) certified values for Fe, Co, Ni, and Mo and provided mass fraction values for 13 additional elements, namely, Na, Mg, Al, K, Ca, Ti, V, Cr, Mn, Br, La, W, and Au. In addition, prompt γ neutron activation analysis was employed to determine mass fractions of H, B, Co, Ni, and Mo. Results of this work provide a basis for the establishment of reference values of element mass fractions in CRM SWCNT-1, thus expanding its usability for more accurate characterization and benchmarking of similar nanotechnology materials.
Keywords: Activation analysis; Carbon nanotubes; Chemical activation; Gold; Magnesium; Manganese; Nanotechnology; Neutrons; Nickel; Single-walled carbon nanotubes (SWCN); Titanium; Certified reference materials; Certified values; Instrumental neutron activation analysis; National Institute of Standards and Technology; National Research Council Canada; Prompt gamma activation analysis; Prompt gamma neutron activation analysis; Neutron activation analysis

Mapping seed phytic acid concentration and iron bioavailability in a pea recombinant inbred line population - Shunmugam, A. S. K; Liu, X.; Stonehouse, R.; Tar’An1, B.; Bett, K. E.; Sharpe, A. G.; Warkentin, T. D. (Crop Science, 2015)
Phytate, the storage form of P in seeds, is not well digested by monogastrics, thereby contributing to micronutrient deficiency, decreased feed efficiency, and environmental pollution. This research was aimed at developing a single nucleotide polymorphism (SNP) based genetic linkage map and mapping genomic regions associated with phytic acid-phosphorus (PAP) concentration using a recombinant inbred line (RIL) population (PR -15) derived from a cross between a low phytate (low phytic acid [lpa]) mutant pea (Pisum sativum L.) genotype, 1-2347-144, and a normal phytate cultivar CDC Meadow. A total of 163 RILs were genotyped using a 1536-SNP Illumina GoldenGate array. Three hundred and sixty-seven polymorphic SNP markers ordered into seven linkage groups (LGs) were used to generate a linkage map with a total length of 437.2 cM. PR -15 lines were grown in replicated field trails in Saskatoon and Rosthern, SK, in 2012 and 2013. Chi-square statistics confirmed the single gene inheritance of PA-P concentration in these RILs. Phytic acidphosphorus (PA-P) phenotype was mapped to LG5. Iron bioavailability (FEBIO) of PR -15 lines estimated using the Caco-2 cell culture bioassay was negatively correlated with PA-P concentration. A quantitative trait locus (QTL) for FEBIO was mapped on to the same location on LG5 as phytic acid concentration. The QTL with a maximum LOD score of 15.1 explained 60.5% of the phenotypic variation in FEBIO. The markers flanking this QTL region can be employed in marker-assisted selection to select pea lines with low phytate and greater Fe bioavailability.
Keywords: Pisum sativum

A landscape of hairy and twisted: Hunting for new trichome mutants in the Saskatoon Arabidopsis T-DNA population - Taheri, A.; Gao, P.; Yu, M.; Cui, D.; Regan, S.; Parkin, I.; Gruber, M. (Plant Biology, 2015)
A total of 88 new Arabidopsis lines with trichome variation were recovered by screening 49,200 single-seed descent T3 lines from the SK activation-tagged population and from a new 20,000-line T-DNA insertion population (called pAG). Trichome variant lines were classified into 12 distinct phenotype categories. Single or multiple T-DNA insertion sites were identified for 89% of these mutant lines. Alleles of the well-known trichome genes TRY, GL2 and TTG1 were recovered with atypical phenotype variation not reported previously. Moreover, atypical gene expression profiles were documented for two additional mutants specifying TRY and GL2 disruptions. In remaining mutants, ten lines were disrupted in genes coding for proteins not implicated in trichome development, five were disrupted in hypothetical proteins and 11 were disrupted in proteins with unknown function. The collection represents new opportunities for the plant biology community to define trichome development more precisely and to refine the function of individual trichome genes.
Keywords: allele; dicotyledon; gene expression; mutation; phenotype; plant community; protein; trichome; Arabidopsis

Metal-free, acid-catalyzed ortho -directed synthesis of anthranilic acid derivatives using carbodiimides - Culf, Adrian S.; Čuperlović-Culf, Miroslava; Ouellette, Rodney J.; Decken, Andreas (Organic Letters, 2015)
One-pot syntheses of fluorescent o-aminobenzoates, o-aminopyridine carboxylates, and a 2′-amino-[1,1′-biphenyl]-2-carboxylic acid are described. Carbodiimides are used as the source of the 2-amino function which inserts onto an aromatic ring using SNAr reaction conditions. This method proceeds regiospecifically with a range of 2-fluoroaromatic acids or esters bearing further aryl fluorine, trifluoromethyl, and cyano substituents.

High-harmonic generation: To the extreme - Vampa, Giulio; Villeneuve, David M. (Nature Physics, 2015)

Theory vs. experiment for molecular clusters: Spectra of OCS trimers and tetramers - Evangelisti, Luca; Perez, Cristobal; Seifert, Nathan A.; Pate, Brooks H.; Dehghany, M.; Moazzen-Ahmadi, N.; McKellar, A. R. W. (Journal of Chemical Physics, 2015)
All singly substituted 13C, 18O, and 34S isotopomers of the previously known OCS trimer are observed in natural abundance in a broad-band spectrum measured with a chirped-pulse Fourier transform microwave spectrometer. The complete substitution structure thus obtained critically tests (and confirms) the common assumption that monomers tend to retain their free structure in a weakly bound cluster. A new OCS trimer isomer is also observed, and its structure is determined to be barrel-shaped but with the monomers all approximately aligned, in contrast to the original trimer which is barrel-shaped with two monomers aligned and one anti-aligned. An OCS tetramer spectrum is assigned for the first time, and the tetramer structure resembles an original trimer with an OCS monomer added at the end with two sulfur atoms. Infrared spectra observed in the region of the OCS ν1 fundamental (≈2060 cm-1) are assigned to the same OCS tetramer, and another infrared band is tentatively assigned to a different tetramer isomer. The experimental results are compared and contrasted with theoretical predictions from the literature and from new cluster calculations which use an accurate OCS pair potential and assume pairwise additivity.
Keywords: Isomers; Monomers; Organic polymers; Broad-band spectrum; Cluster calculations; Free structures; Infrared bands; Infrared spectrum; Molecular clusters; Pair potential; Oligomers

Flexo printed sol-gel derived vanadium oxide films as an interfacial hole-transporting layer for organic solar cells - Kololuoma, Terho; Lu, Jiangping; Alem, Salima; Graddage, Neil; Movileanu, Raluca; Moisa, Simona; Tao, Ye (SPIE - International Society for Optical Engineering. Proceedings, 2015)
In this paper we report on the synthesis and development of vanadium oxide precursor flexographic ink for the printing of hole-transporting layers in organic solar cells. For the synthesis of vanadium oxide inks, a sol-gel methodology was utilized. By modifying the vanadium alkoxide precursor with a right type of coordinating ligands a stable and flexoprintable ink has been successfully developed. Flexo-printing afforded smooth and uniform vanadium oxide sol-gel films on top of PCDTBT:PC70BM films. The conversion of the synthesized sol-gel film into a corresponding vanadium oxide layer was followed by DSC/TGA and XPS analyses. The inks were used for the fabrication of inverted organic solar cells by flexo-printing. Power conversion efficiencies ranging between 3.5 % and 4.5 % were achieved, which are slightly lower than the reference cells using vacuum-deposited MoO3 as the hole-transporting layers.
Keywords: Dye-sensitized solar cells; Hole mobility; Metallic films; Oxides; Printing; Printing presses; Sol-gel process; Sol-gels; Solar cells; Vanadium; Coordinating ligands; Hole transporting layers; Inverted organic solar cells; Organic solar cell; Power conversion efficiencies; Vanadium oxides; Oxide films

Collaborative wireless sensor networks: architectures, algorithms and applications - Fortino, Giancarlo; Bal, Mert; Li, Wenfeng; Shen, Weiming (Information Fusion, 2015)
Before title: Guest Editorial
Avant le titre: Guest Editorial

Do astrocytes collaborate with neurons in spreading the "infectious" Aβ and Tau drivers of Alzheimer's disease? - Dal Prà, Ilaria; Chiarini, Anna; Gui, Li; Chakravarthy, Balu; Pacchiana, Raffaella; Gardenal, Emanuela; Whitfield, James F.; Armato, Ubaldo (Neuroscientist, 2015)
Evidence has begun emerging for the "contagious" and destructive Aβ42 (amyloid-beta42) oligomers and phosphorylated Tau oligomers as drivers of sporadic Alzheimer's disease (AD), which advances along a pathway starting from the brainstem or entorhinal cortex and leading to cognition-related upper cerebral cortex regions. Seemingly, Aβ42 oligomers trigger the events generating the neurotoxic Tau oligomers, which may even by themselves spread the characteristic AD neuropathology. It has been assumed that only neurons make and spread these toxic drivers, whereas their associated astrocytes are just janitorial bystanders/scavengers. But this view is likely to radically change since normal human astrocytes freshly isolated from adult cerebral cortex can be induced by exogenous Aβ25-35, an Aβ42 proxy, to make and secrete increased amounts of endogenous Aβ42. Thus, it would seem that the steady slow progression of AD neuropathology along specific cognition-relevant brain networks is driven by both Aβ42 and phosphorylated Tau oligomers that are variously released from increasing numbers of "contagion-stricken" members of tightly coupled neuron-astrocyte teams. Hence, we surmise that stopping the oversecretion and spread of the two kinds of "contagious" oligomers by such team members, perhaps via a specific CaSR (Ca2+-sensing receptor) antagonist like NPS 2143, might effectively treat AD.
Keywords: amyloid beta protein; amyloid beta protein[1-42]; amyloid beta protein[25-35]; calcium antagonist; calcium sensing receptor; monomer; neuroprotective agent; nootropic agent; nps 2143; oligomer; tau protein; Alzheimer disease; astrocyte; brain cortex; cell interaction; cognition; default mode network; human; nerve cell; nerve cell degeneration; neuropathology; neuroprotection; protein function; protein phosphorylation; protein secretion; senile plaque

High-rate biomethane production from microalgal biomass in a UASB reactor - Tartakovsky, Boris; Lebrun, Frederique Matteau; Guiot, Serge R. (Algal Research, 2015)
Biomethane production from the microalga Scenedesmus sp. AMDD was demonstrated in an upflow anaerobic sludge bed (UASB) reactor. A full factorial design experiment was used to identify the effect of organic loading rate (OLR) of algal biomass and hydraulic retention time (HRT) on the volumetric rate of methane production. At an HRT of 4days and an OLR of 3.23gTVSLR -1d-1 corresponding to an influent microalgae concentration of 12g total volatile solids (TVS) L-1, the volumetric rate of CH4 production reached 0.6LSTPL-1 Rd-1. A methane yield of 0.18-0.2L per gTVS of fed microalgae was estimated. A stable performance was observed throughout 3months of UASB reactor operation. Due to the short HRT and the good performance of UASB reactor, operated at influent microalgae concentrations in a range of 4-12gTVSL-1, this reactor type is suitable for coupling with photobioreactors equipped with gravitational settlers.
Keywords: algae; Scenedesmus

Application of a Whole-Building Hygrothermal model in energy, durability, and indoor humidity retrofit design - Tariku, Fitsum; Kumaran, Kumar; Fazio, Paul (Journal of Building Physics, 2015)
A building shall be classified as high performance building if it is energy efficient and durable and at the same time provides comfortable and healthy indoor environment for occupants. To achieve this objective, the hygrothermal performance of alternative building designs should be evaluated based on the simultaneous analysis of these three functional requirements rather than separately. In this article, a Whole-Building Hygrothermal model is used for evaluation of various retrofit design parameters that potentially enhance the overall performance of an existing residential house. The retrofit options considered in this study include changes to the reference house's ventilation rate and operation, windows, insulation level, and various combinations of these options. Energy efficiency, building envelope and moisture management potential, indoor humidity control, and window condensation potentials are considered to be the four performance indicators in searching for a retrofit option that delivers an optimal performance. The hygrothermal simulation results indicate that changing a design parameter to improve one of the design goals may result in less optimal results in the other one or both goals, or even in some cases result in severe negative consequences.
Keywords: Architectural design; Buildings; Design; Durability; Energy efficiency; Energy utilization; Humidity control; Large scale systems; Retrofitting; Durability assessment; Energy simulation; Hygrothermal performance; Indoor air; integrated HAM analysis; Structural design

Cancer systems biology and modeling: Microscopic scale and multiscale approaches - Masoudi-Nejad, Ali; Bidkhori, Gholamreza; Hosseini Ashtiani, Saman; Najafi, Ali; Bozorgmehr, Joseph H.; Wang, Edwin (Seminars in Cancer Biology, 2015)
Cancer has become known as a complex and systematic disease on macroscopic, mesoscopic and microscopic scales. Systems biology employs state-of-the-art computational theories and high-throughput experimental data to model and simulate complex biological procedures such as cancer, which involves genetic and epigenetic, in addition to intracellular and extracellular complex interaction networks. In this paper, different systems biology modeling techniques such as systems of differential equations, stochastic methods, Boolean networks, Petri nets, cellular automata methods and agent-based systems are concisely discussed. We have compared the mentioned formalisms and tried to address the span of applicability they can bear on emerging cancer modeling and simulation approaches. Different scales of cancer modeling, namely, microscopic, mesoscopic and macroscopic scales are explained followed by an illustration of angiogenesis in microscopic scale of the cancer modeling. Then, the modeling of cancer cell proliferation and survival are examined on a microscopic scale and the modeling of multiscale tumor growth is explained along with its advantages.
Keywords: algorithm; angiogenesis; Boolean network; cancer growth; cancer modeling; cell interaction; cell proliferation; cell survival; cellular automata; epigenetics; genetics; high throughput screening; malignant neoplastic disease; mathematical model; microscopy; multi agent systems; multiscale modeling; Petri nets; simulation; stochastic model; systems biology

Enhanced electrochemical performance of high-density Al-substituted α-nickel hydroxide by a novel anion exchange method using NaCl solution - Li, Jing; Shangguan, Enbo; Nie, Mengzhen; Jin, Qingxiao; Zhao, Kang; Chang, Zhaorong; Yuan, Xiao-Zi; Wang, Haijiang (International Journal of Hydrogen Energy, 2015)
High-density Al-substituted α-nickel hydroxide with interlayer NO3 - for alkaline nickel-based rechargeable batteries has been synthesized using a polyacrylamide (PAM) assisted two-step drying method. In order to improve its electrochemical performance, Al-substituted α-Ni(OH)2 with interlayer NO3 - is modified by a simple anion exchange method using NaCl solution. The physical and electrochemical properties of the synthesized material are characterized by means of X-ray diffraction (XRD), infrared spectroscopy (IR), scanning electron microscopy (SEM), cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS), and a charge-discharge test. Compared with NO3 - intercalated α-Ni(OH)2 precursor, the resulting Cl- intercalated α-Ni(OH)2 samples possess more excellent electrochemical activities, including higher proton diffuse coefficient, lower electrochemical impedance, higher specific capacity, and better cyclic stability. Especially, it is also found that the introduction of Cl- can greatly accelerate the activation process of α-Ni(OH)2 electrodes.
Keywords: Aluminum; Cathodes; Cyclic voltammetry; Electric discharges; Infrared spectroscopy; Ions; Nickel; Scanning electron microscopy; Secondary batteries; X ray diffraction; Anion exchange; Anion-exchange methods; Cath-ode materials; Charge-discharge tests; Electrochemical activities; Electrochemical impedance; Electrochemical performance; Nickel hydroxides; Electrochemical impedance spectroscopy

Guest Editorial - Landim, R.; Di Lillo, L.; Djokić, B.; Ferrero, A. (IEEE Transactions on Instrumentation and Measurement, 2015)
The Conference on Precision Electromagnetic Measurements (CPEM) 2014 was held at Windsor Barra Hotel in Rio de Janeiro, Brazil, from August 24 to August 29, 2014 (http://www.inmetro.gov.br/cpem2014). Experts working in the field of precision metrology and its applications to real-world situations gathered to present and discuss recent advances and open issues/questions.

Nickel hydroxides and related materials: A review of their structures, synthesis and properties - Hall, David S.; Lockwood, David J.; Bock, Christina; MacDougall, Barry R. (Proceedings of the Royal Society A: Mathematical, Physical and Engineering Sciences, 2015)
This review article summarizes the last few decades of research on nickel hydroxide, an important material in physics and chemistry, that has many applications in engineering including, significantly, batteries. First, the structures of the two known polymorphs, denoted as α-Ni(OH)2 and β-Ni(OH)2, are described. The various types of disorder,which are frequently present in nickel hydroxide materials, are discussed including hydration, stacking fault disorder, mechanical stresses and the incorporation of ionic impurities. Several related materials are discussed, including intercalated α-derivatives and basic nickel salts. Next, a number of methods to prepare, or synthesize, nickel hydroxides are summarized, including chemical precipitation, electrochemical precipitation, sol - gel synthesis, chemical ageing, hydrothermal and solvothermal synthesis, electrochemical oxidation, microwaveassisted synthesis, and sonochemical methods. Finally, the known physical properties of the nickel hydroxides are reviewed, including their magnetic, vibrational, optical, electrical and mechanical properties. The last section in this paper is intended to serve as a summary of both the potentially useful properties of these materials and the methods for the identification and characterization of 'unknown' nickel hydroxide-based samples.
Keywords: Characterization; Electrochemical oxidation; Hydrothermal synthesis; Impurities; Intercalation; Materials properties; Mechanical properties; Nickel; Sol-gels; Stresses; Structure (composition); Synthesis (chemical); Vibrations (mechanical); Chemical precipitation; Electrical and mechanical properties; Electrochemical precipitation; Microwave assisted synthesis; Nickel hydroxides; Solvothermal synthesis; Sonochemical method; Precipitation (chemical)

Identification of a mast-cell-specific receptor crucial for pseudo-allergic drug reactions - McNeil, Benjamin D.; Pundir, Priyanka P.; Meeker, Sonya; Han, Liang; Undem, Bradley J.; Kulka, Marianna; Dong, Xinzhong (Nature, 2015)
Mast cells are primary effectors in allergic reactions, and may have important roles in disease by secreting histamine and various inflammatory and immunomodulatory substances. Although they are classically activated by immunoglobulin (Ig)E antibodies, a unique property of mast cells is their antibody-independent responsiveness to a range of cationic substances, collectively called basic secretagogues, including inflammatory peptides and drugs associated with allergic-type reactions. The pathogenic roles of these substances have prompted a decades-long search for their receptor(s). Here we report that basic secretagogues activate mouse mast cells in vitro and in vivo through a single receptor, Mrgprb2, the orthologue of the human G-protein-coupled receptor MRGPRX2. Secretagogue-induced histamine release, inflammation and airway contraction are abolished in Mrgprb2-null mutant mice. Furthermore, we show that most classes of US Food and Drug Administration (FDA)-approved peptidergic drugs associated with allergic-type injection-site reactions also activate Mrgprb2 and MRGPRX2, and that injection-site inflammation is absent in mutant mice. Finally, we determine that Mrgprb2 and MRGPRX2 are targets of many small-molecule drugs associated with systemic pseudo-allergic, or anaphylactoid, reactions; we show that drug-induced symptoms of anaphylactoid responses are significantly reduced in knockout mice; and we identify a common chemical motif in several of these molecules that may help predict side effects of other compounds. These discoveries introduce a mouse model to study mast cell activation by basic secretagogues and identify MRGPRX2 as a potential therapeutic target to reduce a subset of drug-induced adverse effects.
Keywords: atracurium besilate; beta n acetylhexosaminidase; cetrorelix; ciprofloxacin; compound 48-80; G protein coupled receptor; histamine; icatibant; immunoglobulin E antibody; insulin; leuprorelin; octreotide; prostaglandin D2; quinolone derivative; sermorelin; tumor necrosis factor; anaphylaxis; animal experiment; animal model; artificial ventilation; cell activation; cell survival; drug hypersensitivity; HEK293 cell line; histamine release; human; human cell; in vitro study; in vivo study; injection site inflammation; mouse; peritoneum mast cell; reverse transcription polymerase chain reaction; structure activity relation

Rapid and specific SPRi detection of L. pneumophila in complex environmental water samples - Foudeh, A.M.; Trigui, H.; Mendis, N.; Faucher, S.P.; Veres, T.; Tabrizian, M. (Analytical and Bioanalytical Chemistry, 2015)
Legionellosis is a very devastating disease worldwide mainly due to unpredictable outbreaks in man-made water systems. Developing a highly specific and sensitive rapid detection system that detects only metabolically active bacteria is a main priority for water quality assessment. We previously developed a versatile technique for sensitive and specific detection of synthetic RNA. In the present work, we further investigated the performance of the developed biosensor for detection of Legionella pneumophila in complex environmental samples, particularly those containing protozoa. The specificity and sensitivity of the detection system were verified using total RNA extracted from L. pneumophila in spiked water co-cultured with amoebae. We demonstrated that the expression level of ribosomal RNA (rRNA) is extremely dependent on the environmental conditions. The presence of amoebae with L. pneumophila, especially in nutrition-deprived samples, increased the amount of L. pneumophila 15-fold after 1 week as measured through the expression of 16s rRNA. Using the developed surface plasmon resonance imaging (SPRi) detection method, we were also able to successfully detect L. pneumophila within 3 h, both in the presence and absence of amoebae in the complex environmental samples obtained from a cooling water tower. These findings suggest that the developed biosensing system is a viable method for rapid, real-time and effective detection not only for L. pneumophila in environmental samples but also to assess the risk associated with the use of water contaminated with other pathogens. © 2015 Springer-Verlag Berlin Heidelberg
Keywords: Biosensors; Cooling water; Nucleic acids; Optical sensors; Protozoa; Risk assessment; Surface plasmon resonance; Water quality; Water towers; Environmental conditions; Environmental sample; Environmental water samples; Legionella pneumophila; Nanoparticles/Nanotechnology; Rapid detection systems; Surface plasmon resonance imaging; Water quality assessments; RNA

The role of turbulence and magnetic fields in simulated filamentary structure - Kirk, Helen; Klassen, Mikhail; Pudritz, Ralph; Pillsworth, Samantha (The Astrophysical Journal, 2015)
We use numerical simulations of turbulent cluster-forming regions to study the nature of dense filamentary structures in star formation. Using four hydrodynamic and magnetohydrodynamic simulations chosen to match observations, we identify filaments in the resulting column density maps and analyze their properties. We calculate the radial column density profiles of the filaments every 0.05 Myr and fit the profiles with the modified isothermal and pressure-confined isothermal cylinder models, finding reasonable fits for either model. The filaments formed in the simulations have similar radial column density profiles to those observed. Magnetic fields provide additional pressure support to the filaments, making "puffier" filaments less prone to fragmentation than in the pure hydrodynamic case, which continue to condense at a slower rate. In the higher density simulations, the filaments grow faster through the increased importance of gravity. Not all of the filaments identified in the simulations will evolve to form stars: some expand and disperse. Given these different filament evolutionary paths, the trends in bulk filament width as a function of time, magnetic field strength, or density are weak, and all cases are reasonably consistent with the finding of a constant filament width in different star-forming regions. In the simulations, the mean FWHM lies between 0.06 and 0.26 pc for all times and initial conditions, with most lying between 0.1 to 0.15 pc; the range in FWHMs is however, larger than seen in typical Herschel analyses. Finally, the filaments display a wealth of substructure similar to the recent discovery of filament bundles in Taurus.

Influence of HEK293 metabolism on the production of viral vectors and vaccine - Petiot, Emma; Cuperlovic-Culf, Miroslava; Shen, Chun Fang; Kamen, Amine (Vaccine, 2015)
Mammalian cell cultures are increasingly used for the production of complex biopharmaceuticals including viral vectors and vaccines. HEK293 is the predominant cell line used for the transient expression of recombinant proteins and a well-established system for the production of viral vectors. Understanding metabolic requirements for high productivity in HEK293 cells remains an important area of investigation. Many authors have presented approaches for increased productivity through optimization of cellular metabolism from two distinct perspectives. One is a non-targeted approach, which is directed to improving feeding strategies by addition of exhausted or critical substrates and eventually removal of toxic metabolites. Alternatively, a targeted approach has attempted to identify specific targets for optimization through better understanding of the cellular metabolism under different operating conditions. This review will present both approaches and their successes with regards to improvement of viral production in HEK293 cells outlining the key relations between HEK293 cell metabolism and viral vector productivity. Also, we will summarize the current knowledge on HEK293 metabolism indicating remaining issues to address and problems to resolve to maximize the productivity of viral vectors in HEK293 cells.

Vanishing current hysteresis under competing nuclear spin pumping processes in a quadruplet spin-blockaded double quantum dot - Amaha, S.; Hatano, T.; Tarucha, S.; Gupta, J. A.; Austing, D. G. (Applied Physics Letters, 2015)
We investigate nuclear spin pumping with five-electron quadruplet spin states in a spin-blockaded weakly coupled vertical double quantum dot device. Two types of hysteretic steps in the leakage current are observed on sweeping the magnetic field and are associated with bidirectional polarization of nuclear spin. Properties of the steps are understood in terms of bias-voltage-dependent conditions for the mixing of quadruplet and doublet spin states by the hyperfine interaction. The hysteretic steps vanish when up- and down-nuclear spin pumping processes are in close competition.
Keywords: Hysteresis; Magnetic leakage; Nanocrystals; Pumps; Quantum theory; Spin dynamics; Current hysteresis; Double quantum dots; Double-quantum dot device; Hyperfine interactions; Nuclear spins; Spin state; Semiconductor quantum dots

Diagnosis of machining outcomes based on machine learning with Logical Analysis of Data - Shaban, Yasser; Yacout, Soumaya; Balazinski, Marek; Meshreki, Mouhab; Attia, Helmi (IEOM 2015 - 5th International Conference on Industrial Engineering and Operations Management, Proceeding, 2015)
Force is considered to be one of the indicators that best describe the machining process. Measured force can be used to evaluate the quality and geometric profile of the machined part. In this paper, a combinatorial optimization approach is used to characterize the effect of force on the quality of a machined part made of Carbon Fiber Reinforced Polymers (CFRP) material. The approach is called Logical Analysis of Data (LAD) and is based on machine learning and pattern recognition. LAD is used in order to map the machining conditions, in terms of force and torque that lead to conforming products and those which lead to nonconforming products. In this paper, the LAD technique is applied to the drilling of CFRP plates, and the results, based on data obtained experimentally, are reported. A discussion of the potential use of LAD in manufacturing concludes the paper.
Keywords: Artificial intelligence; Carbon; Carbon fiber reinforced plastics; Combinatorial optimization; Failure analysis; Fault detection; Fiber reinforced plastics; Information analysis; Machining; Pattern recognition; Carbon fiber reinforced polymer; CFRP plates; Force and torques; Geometric profile; Logical analysis of data; Machining conditions; Machining Process; Nonconforming products; Quality control

Effects of office environment on employee satisfaction: a new analysis - Leder, Solange; Newsham, Guy R.; Veitch, Jennifer A.; Mancini, Sandra; Charles, Kate E. (Building Research and Information, 2015)
Two large and detailed field studies of the effect of office environment parameters on aspects of environmental and job satisfaction were conducted. The first study focused on open-plan offices in nine conventional buildings, whereas the second encompassed open-plan and private offices in 24 buildings (12 green and 12 conventional). The data collection for these studies was separated by approximately a decade, but the data collection methods, contexts and analysis procedures were very similar. This offered the opportunity to compare the results of the studies at the workstation level, with the goal of identifying parameters consistent in affecting occupant satisfaction, and of exploring the effects of office type (open-plan versus private) and building type (green versus conventional). Satisfaction with acoustics and privacy was most strongly affected by workstation size and office type; satisfaction with lighting was most strongly affected by window access and glare conditions; and satisfaction with ventilation and temperature was most strongly affected by pollutant concentration. Occupants of green buildings rated all aspects of environmental satisfaction more highly. Finally, job satisfaction was most strongly affected by pollutant concentration and office type.
Keywords: Acoustics; Air quality; Buildings; Data acquisition; Job satisfaction; Lighting; Office buildings; Pollution; Thermal comfort; Green buildings; Occupant satisfaction; offices; Post occupancy evaluation; workplace

The next generation Virgo cluster survey. VI. The kinematics of ultra-compact dwarfs and globular clusters in m87 - Zhang, Hong-Xin; Peng, Eric W.; Côté, Patrick J D (Pat); Liu, Chengze; Ferrarese, Laura; Cuillandre, Jean-Charles; Caldwell, Nelson; Gwyn, Stephen D. J.; Jordán, Andrés; Lançon, Ariane; Li, Biao; Muñoz, Roberto P.; et al. (The Astrophysical Journal, 2015)
The origin of ultra-compact dwarfs (UCDs; rh ≳ 10 pc) - objects larger and more massive than typical globular clusters (GCs), but more compact than typical dwarf galaxies - has been hotly debated in the 15 years since their discovery. Even whether UCDs should be considered galactic in origin, or simply the most extreme star clusters, is not yet settled. We present the dynamical properties of 97 spectroscopically confirmed UCDs and 911 GCs associated with the central cD galaxy of the Virgo cluster, M87. Our UCDs, of which 89% have M s ≳ 2× 106 MO and 92% are as blue as the classic blue GCs, nearly triple the confirmed sample of Virgo UCDs, providing by far the best opportunity for studying global dynamics of a UCD system. We found that (1) UCDs have a surface number density profile that is shallower than that of blue GCs in the inner 70 kpc and as steep as that of red GCs at larger radii; (2) UCDs exhibit a significantly stronger rotation than GCs, and blue GCs seem to have a velocity field that is more consistent with that of the surrounding dwarf ellipticals than with that of UCDs; (3) UCDs have an orbital anisotropy profile that is tangentially biased at radii ≲40 kpc and radially biased farther out, whereas blue GCs become more tangentially biased at larger radii beyond 40 kpc; (4) GCs with M s ≳ 2 × 106 MO have rotational properties indistinguishable from the less massive ones, suggesting that it is the size, instead of mass, that differentiates UCDs from GCs as kinematically distinct populations. We conclude that most UCDs in M87 are not consistent with being merely the most luminous and extended examples of otherwise normal GCs. The radially biased orbital structure of UCDs at large radii is in general agreement with the "tidally threshed dwarf galaxy" scenario.
Keywords: galaxies: clusters: individual (Virgo); galaxies: dwarf; galaxies: elliptical and lenticular, cD; galaxies: halos; galaxies: star clusters: general; globular clusters: general

Sequence determination by MALDI-TOF mass spectrometry of an insecticidal lentil peptide of the PA1b type - Taylor, Wesley G.; Sutherland, Daniel H.; Zhang, Haixia; Hegedus, Dwayne D. (Phytochemistry Letters, 2015)
Mature seeds of lentil (Lens culinaris Medik.) were previously reported to contain an insecticidal cysteine-rich peptide, likely of the albumin-1 subunit b type. The purpose of this work was to determine the amino acid sequence of this insecticidal lentil peptide in an Eston lentil extract by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS), after reduction of the disulfide bridges, alkylation of the cysteine residues and hydrolysis by pronase, trypsin, chymotrypsin and endoproteinase Asp-N. Sequences of key fragments were supported by monoisotopic mass measurements and by sequence ions from collision-induced dissociation (CID) experiments with a MALDI-TOF/TOF analyzer (MS/MS analysis). The new 37 amino acid sequence revealed strong similarities to a histidine-containing pea PA1b peptide and to soybean leginsulins but with a unique segment of RSSA in the middle. The lentil PA1b peptide sequence agreed completely with that derived from a L. culinaris genomic DNA sequence. © 2015 Phytochemical Society of Europe.
Keywords: arginine; asparagine; aspartic acid; chymotrypsin; cysteine; disulfide; flavone; genomic DNA; glutamic acid; lentil extract; microsomal aminopeptidase; octapeptide; PA1b peptide; peptide; plant extract; proline; pronase; quinestrol; serine; trypsin; tyrosine; alkylation; amino acid sequence; amino terminal sequence; carboxy terminal sequence; collisionally activated dissociation; high performance liquid chromatography; hydrolysis; legume; lentil; matrix assisted laser desorption ionization time of flight mass spectrometry; nucleotide sequence; open reading frame; plant gene; soybean; Glycine max; Lens culinaris; Pisum sativum

Ion chamber absorbed dose calibration coefficients, ND,w, measured at ADCLs: Distribution analysis and stability - Muir, B. R. (Medical Physics, 2015)
Purpose: To analyze absorbed dose calibration coefficients, ND,w, measured at accredited dosimetry calibration laboratories (ADCLs) for client ionization chambers to study (i) variability among ND,w coefficients for chambers of the same type calibrated at each ADCL to investigate ion chamber volume fluctuations and chamber manufacturing tolerances; (ii) equivalency of ion chamber calibration coefficients measured at different ADCLs by intercomparing ND,w coefficients for chambers of the same type; and (iii) the long-term stability of ND,w coefficients for different chamber types by investigating repeated chamber calibrations. Methods: Large samples of ND,w coefficients for several chamber types measured over the time period between 1998 and 2014 were obtained from the three ADCLs operating in the United States. These are analyzed using various graphical and numerical statistical tests for the four chamber types with the largest samples of calibration coefficients to investigate (i) and (ii) above. Ratios of calibration coefficients for the same chamber, typically obtained two years apart, are calculated to investigate (iii) above and chambers with standard deviations of old/new ratios less than 0.3% meet stability requirements for accurate reference dosimetry recommended in dosimetry protocols. Results: It is found that ND,w coefficients for a given chamber type compared among different ADCLs may arise from differing probability distributions potentially due to slight differences in calibration procedures and/or the transfer of the primary standard. However, average ND,w coefficients from different ADCLs for given chamber types are very close with percent differences generally less than 0.2% for Farmer-type chambers and are well within reported uncertainties. Conclusions: The close agreement among calibrations performed at different ADCLs reaffirms the Calibration Laboratory Accreditation Subcommittee process of ensuring ADCL conformance with National Institute of Standards and Technology standards. This study shows that ND,wcoefficients measured at different ADCLs are statistically equivalent, especially considering reasonable uncertainties. This analysis of ND,w coefficients also allows identification of chamber types that can be considered stable enough for accurate reference dosimetry.
Keywords: accreditation; accredited dosimetry calibration laboratory; analysis; Article; calibration; distribution analysis; dosimetry; histogram; ionization chamber; laboratory; probability; uncertainty

Why ice-binding type I antifreeze protein acts as a gas hydrate crystal inhibitor - Bagherzadeh, S. Alireza; Alavi, Saman; Ripmeester, John A.; Englezos, Peter (Physical Chemistry Chemical Physics, 2015)
Antifreeze proteins (AFPs) prevent ice growth by binding to a specific ice plane. Some AFPs have been found to inhibit the formation of gas hydrates which are a serious safety and operational challenge for the oil and gas industry. Molecular dynamics simulations are used to determine the mechanism of action of the winter flounder AFP (wf-AFP) in inhibiting methane hydrate growth. The wf-AFP adsorbs onto the methane hydrate surface via cooperative binding of a set of hydrophobic methyl pendant groups to the empty half-cages at the hydrate/water interface. Each binding set is composed of the methyl side chain of threonine and two alanine residues, four and seven places further down in the sequence of the protein. Understanding the principle of action of AFPs can lead to the rational design of green hydrate inhibitor molecules with potential superior performance.

A comparative study of structural and electrochemical properties of high-density aluminum substituted α-nickel hydroxide containing different interlayer anions - Shangguan, Enbo; Li, Jing; Guo, Dan; Guo, Litan; Nie, Mengzhen; Chang, Zhaorong; Yuan, Xiao-Zi; Wang, Haijiang (Journal of Power Sources, 2015)
Al-substituted α-type nickel hydroxides (α-Ni(OH)2) containing different interlayer anions (NO3 -, SO4 2-, Cl-, CO32-, OH-) are synthesized via a polyacrylamide (PAM) assisted two-step drying method. The effects of interlayer anions on the microstructure, morphology and electrochemical performance of Al-substituted α-Ni(OH)2 are investigated by X-ray diffraction (XRD), infrared spectroscopy (IR), scanning electron microscope (SEM), cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS), and charge/discharge tests. The results demonstrate that the intercalated anions have a critical effect on the basal plane spacing, degree of crystallinity, and electrochemical properties of the end products. Especially, the intercalated anions have a marked impact on the activation process of the nickel electrodes. The Cl- intercalated α-Ni(OH)2 sample exhibits better high-rate discharge ability and cycle stability than samples with other interlayer anions. This is attributed to the higher crystallinity, better exchange ability and smaller anion size of Cl-. The anion exchange ability and the size of anions also play an important role in the proton diffusion rate, which directly affects the electrochemical properties of α-Ni(OH)2. The relationships between the specific capacity and basal spacing are also discussed in details for the five samples.
Keywords: Aluminum; Cathodes; Cyclic voltammetry; Electric discharges; Electrochemical impedance spectroscopy; Electrochemical properties; Electrodes; Infrared spectroscopy; Negative ions; Nickel; Organic polymers; Scanning electron microscopy; X ray diffraction; Alpha nickel hydroxide; Anion doping; Cath-ode materials; Degree of crystallinity; Electrochemical performance; High rate discharge ability; Nickel hydroxides; Proton diffusion rates; Ions

Effects of exogenously applied gibberellins and thidiazuron on phytohormone profiles of long-shoot buds and cone gender determination in lodgepole pine - Kong, Lisheng; von Aderkas, Patrick; Zaharia, L. Irina (Journal of Plant Growth Regulation, 2015)
In long-shoot buds of lodgepole pine (Pinus contorta Dougl. ex Loud. var. latifolia Engelm), cone-bud initiation and gender differentiation occur in a site-specific manner: female cone buds are normally restricted to the distal portion, whereas male cone buds are located in the proximal portion. Application of a paste containing two plant growth regulators gibberellins A4 + A7 (GA4/7) combined with thidiazuron (TDZ) to long-shoot buds prior to cone-bud gender determination altered endogenous phytohormone profiles and induced female cone-bud formation in the proximal portion of the long-shoot bud, where male cone buds normally occur. Induced cone clusters observed in the following spring were either entirely female or a mixture of both female and male cones. Endogenous phytohormones in the long-shoot bud tissues were quantified by the stable isotope dilution method using high performance liquid chromatography-electrospray ionization tandem mass spectrometry in multiple-reaction monitoring mode. Applied GA4/7 + TDZ led to increased concentrations of endogenous zeatin-type cytokinins, that is, trans-zeatin riboside and dihydrozeatin riboside, whereas concentrations of abscisic acid (ABA) and its catabolite, ABA glucose ester, were decreased, all relative to control, in untreated long-shoot bud tissue. Concentrations of extractable GA4 and GA7 declined in long-shoot bud tissues over 4 weeks following treatment with exogenous GA4/7. This study demonstrates that high levels of endogenous zeatin-type cytokinins, together with reduced levels of ABA, both induced by applied GA4/7 + TDZ, are positively associated with an increased female cone-bud formation in long-shoot buds.
Keywords: Cone gender determination; Gibberellins; Lodgepole pine; Paste treatment; Phytohormone profiles; Thidiazuron

Early rhizosphere microbiome composition is related to the growth and Zn uptake of willows introduced to a former landfill - Bell, Terrence H.; Cloutier-Hurteau, Benoît; Al-Otaibi, Fahad; Turmel, Marie-Claude; Yergeau, Etienne; Courchesne, François; St-Arnaud, Marc (Environmental Microbiology, 2015)
Although plants introduced for site restoration are pre-selected for specific traits (e.g. trace element bioaccumulation, rapid growth in poor soils), the in situ success of these plants likely depends on the recruitment of appropriate rhizosphere microorganisms from their new environment. We introduced three willow (Salix spp.) cultivars to a contaminated landfill, and performed soil chemical analyses, plant measurements, and Ion Torrent sequencing of rhizospheric fungal and bacterial communities at 4 and 16 months post-planting. The abundance of certain dominant fungi was linked to willow accumulation of Zn, the most abundant trace element at the site. Interestingly, total Zn accumulation was better explained by fungal community structure 4 months post-planting than 16 months post-planting, suggesting that initial microbial recruitment may be critical. In addition, when the putative ectomycorrhizal fungi Sphaerosporella brunnea and Inocybe sp. dominated the rhizosphere 4 months post-planting, Zn accumulation efficiency was negatively correlated with fungal diversity. Although field studies such as this rely on correlation, these results suggest that the soil microbiome may have the greatest impact on plant function during the early stages of growth, and that plant-fungus specificity may be essential.

FeS/C composite as high-performance anode material for alkaline nickel-iron rechargeable batteries - Shangguan, Enbo; Li, Fei; Li, Jing; Chang, Zhaorong; Li, Quanmin; Yuan, Xiao-Zi; Wang, Haijiang (Journal of Power Sources, 2015)
FeS and its composite, FeS/C, are synthesized via a simple calcination method followed by a co-precipitation process. The electrochemical properties of the bare FeS and FeS/C composite as anode materials for alkaline nickel-iron batteries are investigated. The results show that the FeS/C-3wt%Bi2O3-mixed electrode delivers a high specific capacity of 325 mAh g-1 at a current density of 300 mA g-1 with a faradaic efficiency of 90.3% and retains 99.2% of the initial capacity after 200 cycles. For the first time, it is demonstrated that even at a discharge rate as high as 1500 mA g-1 (5C) the FeS/C-3wt%Bi2O3-mixed electrode delivers a specific capacity of nearly 230 mAh g-1. SEM results confirm that after 200 discharge-charge cycles, the size of FeS/C particles reduces from 5 to 15 μm to less than 300 nm in diameter and the particles are highly dispersed on the surface of carbon black, which is likely caused by the dissolution-deposition process of Fe(OH)2 and Fe via intermediate iron species. As a result, the FeS/C composite exhibits considerably high charge efficiency, high discharge capacities, excellent rate capability and superior cycling stability. We believe that this composite is a potential candidate of high-performance anode materials for alkaline iron-based rechargeable batteries.
Keywords: Anodes; Carbon black; Cyclic voltammetry; Electric batteries; Electric discharges; Electrochemical electrodes; Electrochemical properties; Electrodes; Iron; Nickel; Precipitation (chemical); Anode material; Co-precipitation process; Discharge-charge cycle; Faradaic efficiencies; High specific capacity; High-performance anode materials; Iron electrodes; Nickel irons; Secondary batteries

Global optimisation of the production of complex aluminium tubes by the hydroforming process - Bihamta, R.; Bui, Q. -H.; Guillot, M.; D'Amours, G.; Rahem, A.; Fafard, M. (CIRP Journal of Manufacturing Science and Technology, 2015)
With the recent development of analysis software products, designers and engineers are able to design more complex parts to obtain better performance in the final products. In this study, the tube hydroforming process, including preceding processes, i.e. variable thickness tube drawing and two-step bending, are globally optimised to obtain parts without any problems like bursting or un-filled zones at the end of the forming processes. Unlike most previous studies which searched for an optimum hydroforming process by changing two hydroforming parameters, i.e. axial load feeding and internal pressure, in this study, the distribution of initial tube wall thickness and the variation of thickness due to bending steps will be taken into account in a global optimisation algorithm. The developed algorithm is a general-purpose algorithm that can encompass different processes and change various parameters in each process to be able to reach the global objective. The case study used was a part that needs two-step variable thickness tube drawing, and two bending steps before hydroforming. To verify the numerical results in each forming stage and at the end of all forming processes, extensive experiments were performed, and acceptable agreements were observed.
Keywords: Algorithms; Aluminum; Drawing (forming); Global optimization; Metal forming; Optimization; Parameter estimation; Product design; Thickness control; Tubes (components); AA6061; Analysis softwares; Global optimisation; Hydroforming process; Tube bending; Tube drawing; Tube hydroforming; Tube hydroforming process; Bending (forming)

Complete genome sequence of hypervirulent and outbreak-associated Acinetobacter baumannii strain LAC-4: Epidemiology, resistance genetic determinants and potential virulence factors - Ou, Hong-Yu; Kuang, Shan N.; He, Xinyi; Molgora, Brenda M.; Ewing, Peter J.; Deng, Zixin; Osby, Melanie; Chen, Wangxue; Xu, H. Howard (Scientific Reports, 2015)
Acinetobacter baumannii is an important human pathogen due to its multi-drug resistance. In this study, the genome of an ST10 outbreak A. baumannii isolate LAC-4 was completely sequenced to better understand its epidemiology, antibiotic resistance genetic determinants and potential virulence factors. Compared with 20 other complete genomes of A. baumannii, LAC-4 genome harbors at least 12 copies of five distinct insertion sequences. It contains 12 and 14 copies of two novel IS elements, ISAba25 and ISAba26, respectively. Additionally, three novel composite transposons were identified: Tn6250, Tn6251 and Tn6252, two of which contain resistance genes. The antibiotic resistance genetic determinants on the LAC-4 genome correlate well with observed antimicrobial susceptibility patterns. Moreover, twelve genomic islands (GI) were identified in LAC-4 genome. Among them, the 33.4-kb GI12 contains a large number of genes which constitute the K (capsule) locus. LAC-4 harbors several unique putative virulence factor loci. Furthermore, LAC-4 and all 19 other outbreak isolates were found to harbor a heme oxygenase gene (hemO)-containing gene cluster. The sequencing of the first complete genome of an ST10 A. baumannii clinical strain should accelerate our understanding of the epidemiology, mechanisms of resistance and virulence of A. baumannii.

Influence of the stem fixation scenario on load transfer in a hip resurfacing arthroplasty with a biomimetic stem - Caouette, C.; Bureau, M. N.; Vendittoli, P.-A.; Lavigne, M.; Nuño, N. (Journal of the Mechanical Behavior of Biomedical Materials, 2015)
Finite element (FE) analysis is a widely used tool for extensive preclinical testing of orthopaedic implants such as hip resurfacing femoral components, including evaluation of different stem fixation scenarios (cementation vs osseointegration, etc.). Most FE models use surface-to-surface contact elements to model the load-bearing interfaces that connect bone, cement and implant and neglect the mechanical effects of phenomena such as residual stresses from bone cement curing. The objective of the current study is to evaluate and quantify the effect of different stem fixation scenarios and related phenomena such as residual stresses from bone cement curing. Four models of a previously clinically available implant (Durom) were used to model different stem fixation scenarios of a new biomimetic stem: a cemented stem, a frictional stem, a partially and completely bonded stem, with and without residual stresses from bone cement curing. For the frictional stem, stem-bone micromotions were increased from 0% to 61% of the available surface subjected to micromotions between 10 and 40. μm with the inclusion of residual stresses from bone cement curing. Bonding the stem, even partially, increased stress in the implant at the stem-head junction. Complete bonding of the stem decreased bone strain at step tip, at the cost of increased strain shielding when compared with the frictional stem and partially bonded stem. The increase of micromotions and changes in bone strain highlighted the influence of interfacial conditions on load transfer, and the need for a better modeling method, one capable of assessing the effect of phenomena such as interdigitation and residual stresses from bone cement curing.
Keywords: Bearings (machine parts); Biomimetics; Bone; Curing; Finite element method; Friction; Residual stresses; Femoral component; Hip resurfacing prosthesis; Interfacial conditions; Load bearing; Mechanical effects; Orthopaedic implants; Pre-clinical testing; Surface-to-surface contacts; bone cement; bone density; bone implant; bone remodeling; bone stress; femur head; finite element analysis; hip arthroplasty; human; human tissue; motion

Infrared and radio observations of a small group of protostellar objects in the molecular core, L1251-C - Kim, Jungha; Lee, Jeong-Eun; Choi, Minho; Bourke, Tyler L.; Ii, Neal J. E.; Francesco, James D.; Cieza, Lucas A.; Dunham, Michael M.; Kang, Miju (Astrophysical Journal, Supplement Series, 2015)
We present a multi-wavelength observational study of a low-mass star-forming region, L1251-C, with observational results at wavelengths from the near-infrared to the millimeter. Spitzer Space Telescope observations confirmed that IRAS 22343+7501 is a small group of protostellar objects. The extended emission in the east-west direction with its intensity peak at the center of L1251A has been detected at 350 and 850 μm with the Caltech Submillimeter Observatory and James Clerk Maxwell telescopes, tracing dense envelope material around L1251A. The single-dish data from the Korean VLBI Network and TRAO telescopes show inconsistencies between the intensity peaks of several molecular emission lines and that of the continuum emission, suggesting complex distributions of molecular abundances around L1251A. The Submillimeter Array interferometer data, however, show intensity peaks of CO 2-1 and 13CO 2-1 located at the position of IRS 1, which is both the brightest source in the Infrared Array Camera image and the weakest source in the 1.3 mm dust-continuum map. IRS 1 is the strongest candidate for the driving source of the newly detected compact CO 2-1 outflow. Over the entire region (14′ × 14′) of L125l-C, 3 Class I and 16 Class II sources have been detected, including three young stellar objects (YSOs) in L1251A. A comparison between the average projected distance among the 19 YSOs in L1251-C and that among the 3 YSOs in L1251A suggests that L1251-C is an example of low-mass cluster formation where protostellar objects form in a small group.

Entanglement over global distances via quantum repeaters with satellite links - Boone, K.; Bourgoin, J.-P.; Meyer-Scott, E.; Heshami, K.; Jennewein, T.; Simon, C. (Physical Review A - Atomic, Molecular, and Optical Physics, 2015)
We study entanglement creation over global distances based on a quantum repeater architecture that uses low-Earth-orbit satellites equipped with entangled photon sources, as well as ground stations equipped with quantum nondemolition detectors and quantum memories. We show that this approach allows entanglement creation at viable rates over distances that are inaccessible via direct transmission through optical fibers or even from very distant satellites.
Keywords: Light transmission; Optical fibers; Orbits; Satellite communication systems; Satellite links; Satellites; Entangled photons; Ground stations; Low earth orbit satellites; Quantum memory; Quantum non-demolition; Quantum repeaters; Quantum entanglement

Fatigue crack growth in 7249-T76511 aluminium alloy under constant-amplitude and spectrum loading - Newman, J. C.; Walker, K. F.; Liao, M. (Fatigue and Fracture of Engineering Materials and Structures, 2015)
Fatigue crack growth tests were conducted on compact, C(T), specimens made of 7249-T76511 aluminium alloy. These tests were conducted to generate crack growth rate data from threshold to near fracture over a wide range of load ratios (R). Four methods were used to generate near threshold data: (1) ASTM E-647 load reduction (LR), (2) compression pre-cracking constant-amplitude (CPCA), (3) compression pre-cracking LR, and (4) constant crack mouth opening displacement LR method. A crack closure analysis was used to develop an effective stress-intensity factor range against rate relation using a constraint factor (α = 1.85). Simulated aircraft wing spectrum tests were conducted on middle crack tension, M(T), specimens using a modified full-scale fatigue test spectrum. The tests were used to develop the constraint-loss regime (plane strain to plane stress; α = 1.85 to 1.15) behaviour. Comparisons were made between the spectrum tests and calculations made with the FASTRAN life prediction code; and the calculated crack growth lives were generally with ±10% of the test results.
Keywords: Alloys; Aluminum; Aluminum alloys; Amplitude modulation; Crack closure; Crack propagation; Fatigue crack propagation; Fatigue of materials; Fatigue testing; Strain; Stress analysis; Stress intensity factors; Wings; Compression pre crackings; Constant amplitude; Constraint factor; Crack mouth opening displacement; Effective stress intensity factor range; Fatigue-crack-growth tests; Full-scale fatigue test; Spectrum loading; Cracks

Type-I interband cascade lasers near 3.2 μm - Jiang, Yuchao; Li, Lu; Yang, Rui Q.; Gupta, James A.; Aers, Geof C.; Dupont, Emmanuel; Baribeau, Jean-Marc; Wu, Xiaohua; Johnson, Matthew B. (Applied Physics Letters, 2015)
Interband cascade (IC) lasers have been demonstrated based on type-I InGaAsSb/AlAsSb quantum well (QW) active regions. These type-I IC lasers are composed of 6-cascade stages and InAs/AlSb superlattice cladding layers. In contrast to the use of quinary AlGaInAsSb barriers for active region in previous type-I QW lasers, the type-I QW active region in each stage is sandwiched by digitally graded multiple InAs/AlSb QW electron injector and GaSb/AlSb QW hole injector. The fabricated type-I IC lasers were able to operate in continuous wave and pulsed modes at temperatures up to 306 and 365 K, respectively. The threshold current densities of broad-area lasers were around 300 A/cm2 at 300 K with a lasing wavelength near 3.2 μm. The implications and prospects of these initial results are discussed.
Keywords: Quantum wells; Current density; III-V Semiconductors; Cladding; Laser diodes

Elemental abundance analyses with DAO spectrograms XXXVII. The normal A0 IV star γ Geminorum - Adelman, Saul J.; Gulliver, Austin F.; Kaewkornmaung, Pongsakorn (Publications of the Astronomical Society of the Pacific, 2015)
We performed a fine analysis of the normal sharp-lined A0 IV star γ Geminorum with spectra having signal-to-noise ratios at the continuum of 500–1200 that were consistent with previous studies of this series. Our spectra have wavelength ranges of λλ3829–4730, 4873–4931, 4983–5042, and 5070–5210. The spectra measured with the program REDUCE have a two-pixel resolution of 0.072 Å. We used ATLAS9 models and the program WIDTH9 to derive the abundances of the metals. Most derived abundances are close to solar with the abundances of the heaviest elements Zr, Ba, La, Ce, and Nd showing greater than solar values. This suggests by comparison with the abundances of other normal and Am stars that γ Gem might exhibit an incipient Am star phenomenon.

Is cancer a genetic disease or a metabolic disease? - Wishart, David S. (EBioMedicine, 2015)

Mechanical properties, sliding wear and solid particle erosion behaviors of plasma enhanced magnetron sputtering CrSiCN coating systems - Cai, Feng; Huang, Xiao; Yang, Qi (Wear, 2015)
CrSiCN coating systems with different concentrations of Cr, Si, C, and N were investigated for their microstructure, mechanical properties (hardness H, elastic modulus E and indentation fracture toughness KIC) and tribological behaviors using SEM, nano-indentation, indentation, pin-on-disk wear test, and sand particle erosion test. The wear behaviors, such as specific wear rate and Archard wear coefficient, showed inverse relationships with H3/E2 ratio, confirming that the resistance to plastic deformation is the essential factor governing sliding wear behavior. High H3/E2 ratios also contributed to increased resistances to erosion at low impingement angles. However, at higher impingement angles (>60°), coatings with lower index of brittleness (B=2.656μm-1/2), higher critical load (P*=6.670N) for crack initiation and fracture surface energy (γf=0.123Jm-2) offered a higher erosion resistance. The indentation fracture toughness (KIC), hardness (H) and elastic modulus (E) are limited to interpret erosion behaviors in a comprehensive approach, suggesting that erosion is a complex process where multiple mechanical properties contribute to erosion performance.
Keywords: Amorphous films; Elastic moduli; Erosion; Fracture mechanics; Fracture toughness; Physical vapor deposition; Plastic coatings; Plastic deformation; Wear of materials; Coatings; Mechanical properties; Indentation fracture toughness; Inverse relationship; Pin-on-disk wear test; Plasma enhanced magnetron sputtering; Sliding wear behaviors; Solid particle erosion; Specific wear rates; Tribological behaviors; Fracture

Differential MR delayed enhancement patterns of chronic myocardial infarction between extracellular and intravascular contrast media - Wang, Jian; Xiang, Bo; Lin, Hung Yu; Liu, Hongyu; Freed, Darren; Arora, Rakesh C.; Tian, Ganghong (PLoS ONE, 2015)
Objectives: Because the distribution volume and mechanism of extracellular and intravascular MR contrast media differ considerably, the enhancement pattern of chronic myocardial infarction with extracellular or intravascular media might also be different. This study aims to investigate the differences in MR enhancement patterns of chronic myocardial infarction between extracellular and intravascular contrast media. Materials and Methods: Twenty pigs with myocardial infarction underwent cine MRI, first pass perfusion MRI and delayed enhancement MRI with extracellular or intravascular media at four weeks after coronary occlusion. Myocardial blood flow (MBF) was determined with microsphere measurement. The infarction histopathological changes were evaluated by hematoxylin and eosin staining and Masson's trichrome method. Results: Cine MRI revealed the reduced wall thickening in chronic infarction compared with normal myocardium. Moreover, significant wall thinning in chronic infarction was observed in cine MRI. Peak first-pass signal intensity didn' t significantly differ between chronic infarction and normal myocardium no matter what kinds of contrast media. At the following delayed enhancement phase, extracellular media-enhanced signal intensity was significantly higher in chronic infarction than in normal myocardium. Conversely, intravascular media-enhanced signal intensity was almost equivalent among chronic infarction and normal myocardium. At four weeks after infarction, MBF in chronic infarction approached to that in normal myocardium. Large thick-walled vessels were detected at peri-infarction zones. The cardiomyocytes were replaced by scar tissue consisting of dilated blood vessels and discrete fibers of collagen. Conclusions: Chronic infarction was characterized by the significantly reduced wall thickening and the definite wall thinning. First-pass myocardial perfusion defect was not detected in chronic infarction with two media due to the significantly recovered MBF and well-developed collateral vessels. Infarction remodeling enlarged the extracellular compartment, which was available for extracellular media but not accessible to intravascular media. Extracellular media identified chronic infarction as the hyper-enhancement; nonetheless, intravascular media didn't provide delayed enhancement.
Keywords: collagen; dye; eosin; gadolinium pentetate meglumine; gadomelitol; hematoxylin; Masson trichrome stain; animal experiment; animal model; animal tissue; chronic heart infarction; cineradiography; collagen fiber; contrast enhancement; controlled study; coronary artery occlusion; heart hypertrophy; heart infarction; heart muscle blood flow; heart muscle cell; heart muscle perfusion; heart ventricle remodeling; histopathology; image analysis; nonhuman; nuclear magnetic resonance imaging; nuclear magnetic resonance scanner; scar; signal processing; swine; vasodilatation; Suidae

Carbon-supported Pt-based alloy electrocatalysts for the oxygen reduction reaction in polymer electrolyte membrane fuel cells: particle size, shape, and composition manipulation and their impact to activity - Wang, Yan-Jie; Zhao, Nana; Fang, Baizeng; Li, Hui; Bi, Xiaotao T.; Wang, Haijiang (Chemical Reviews, 2015)
A scientific review addresses the current development of size-dependent, shape-selected, and composition-controlled carbon-supported Pt-alloy electrocatalysts for enhancing electrochemical catalytic performance in polymer electrolyte membrane fuel cells (PEMFCs). It starts with an overview of carbon support in carbon-supported Pt-alloy electrocatalysts and proceeds to the theoretical studies on the impact of Pt-alloy particle size, shape, and composition, and the experimental research on the particle size, shape, and composition of Pt-alloy catalysts. It particularly emphasizes on strategies to control particle size, shape, composition, and their impacts on catalyst activity toward the oxygen reduction reaction.
Keywords: Alloys; Carbon; Catalyst activity; Catalysts; Electrocatalysts; Electrolysis; Electrolytes; Electrolytic reduction; Fuel cells; Molecular biology; Oxygen; Particle size; Platinum; Platinum alloys; Polyelectrolytes; Proton exchange membrane fuel cells (PEMFC); Carbon support; Carbon-supported Pt; Catalytic performance; Oxygen reduction reaction; Polymer electrolyte membrane fuel cell (PEMFCs); Theoretical study; Solid electrolytes

Does the presence of planets affect the frequency and properties of extrasolar kuiper belts? Results from the herschel debris and dunes surveys - Moro-Martín, A.; Marshall, J. P.; Kennedy, G.; Sibthorpe, B.; Matthews, B. C.; Eiroa, C.; Wyatt, M. C.; Lestrade, J.-F.; Maldonado, J.; Rodriguez, D.; Greaves, J. S.; Montesinos, B.; et al. (The Astrophysical Journal, 2015)
The study of the planet-debris disk connection can shed light on the formation and evolution of planetary systemsand may help "predict" the presence of planets around stars with certain disk characteristics. In preliminary analyses of subsamples of the Herschel DEBRIS and DUNES surveys, Wyatt et al. and Marshall et al. identified a tentative correlation between debris and the presence of low-mass planets. Here we use the cleanest possible sample out of these Herschel surveys to assess the presence of such a correlation, discarding stars without known ages, with ages Gyr, and with binary companions AUto rule out possible correlations due to effects other than planet presence. In our resulting subsample of 204 FGK stars, we do not find evidence that debris disks are more common or more dusty around stars harboring high-mass or low-mass planets compared to a control sample without identified planets. There is no evidence either that the characteristic dust temperature of the debris disks around planet-bearing stars is any different from that in debris disks without identified planets, nor that debris disks are more or less common (or more or less dusty) around stars harboring multiple planets compared to single-planet systems. Diverse dynamical histories may account for the lack of correlations. The data show a correlation between the presence of high-mass planets and stellar metallicity, but no correlation between the presence of low-mass planets or debris and stellar metallicity. Comparing the observed cumulative distribution of fractional luminosity to those expected from a Gaussian distribution in logarithmic scale, we find that a distribution centered on the solar system's value fits the data well, while one centered at 10 times this value can be rejected. This is of interest in the context of future terrestrial planet detection and characterization because it indicates that there are good prospects for finding a large number of debris disk systems (i.e., with evidence of harboring planetesimals, the building blocks of planets) with exozodiacal emission low enough to be appropriate targets for an ATLAST-type mission to search for biosignatures.

Commercial formaldehyde standard for mass calibration in mass spectrometry - Lyczko, Jadwiga; Beach, Daniel G.; Gabryelski, Wojciech (Journal of Mass Spectrometry, 2015)
Common calibration standards for mass spectrometry can be a source of many problems including instrument contamination, ionization suppression and formation of unidentified ions during subsequent analysis. In this article, we present a new approach for the calibration of mass analyzers such as a quadrupole-time-of-flight mass spectrometry using a diluted solution of commercial formaldehyde. Formaldehyde is an inexpensive and commonly used solvent, and its intrinsic polymerization leads to the formation of polyoxymethylene (POM) oligomers, which are excellent multiple calibration standards for a low-mass spectral region (up to m/z 400) in the positive and negative mode of electrospray ionization. We explore the nature and origin of these polymeric species and attributed them to chemical reactions of formaldehyde and stabilizing agents in commercial formaldehyde solutions and during electrospray ionization. In contrast to other calibrants, POM oligomers do not contaminate the instrument and can easily be removed from the sample delivery system. Using tandem mass spectrometry, we elucidate the structures of the detected POM oligomers and report their reference masses, which are tightly spaced by 30 mass units. In our calibration method, mass errors of <5ppm can be obtained from m/z 20-400 using external calibration with a simple one-point zero-order correction of spectral data and without the need for operation of a dual spray or internal calibrants. Our approach will be particularly useful for those interested in the analysis of fragile ions with low m/z values and can function at instrumental conditions required for analysis of the most labile metabolites and environmental contaminants.
Keywords: Acetal resins; calibration; Ionization; Mass spectrometry; Oligomers; Polymers; Spectrometry; Environmental contaminant; External calibration; Formaldehyde solutions; Quadrupole-time of flights; Tandem mass spectrometry; Electrospray ionization; carbene; formaldehyde; polyoxymethylene; chemical reaction; chemical structure; depolymerization; electrospray; fragmentation reaction; hydrogen bond; low temperature; nucleophilicity; polymerization; proton transport; quadrupole mass spectrometry; time of flight mass spectrometry

Iceberg sightings, shapes and management techniques for offshore Newfoundland and Labrador: Historical data and future applications - Sudom, Denise; Timco, Garry; Tivy, Adrienne (2014 Oceans - St. John's, OCEANS 2014, 2015)
For safe and efficient operations in the iceberg-infested waters offshore eastern Canada, accurate information on icebergs is needed. Databases on iceberg sightings, shapes and management techniques have been developed in order to bring all relevant iceberg information into one repository. Iceberg sightings have been recorded offshore Newfoundland and Labrador since the 1600s. Sighting methods, locations, yearly variability and uncertainties are discussed. In more recent times, detailed 2D and 3D measurements have been made of iceberg geometries, which are useful for structural load calculations. Techniques to deflect iceberg drift from critical offshore locations have also evolved over the past 40 years. The various methods that have been used for iceberg management are discussed, as well as the factors that affect their success rates. Relationships between historical iceberg populations and sea ice can be used to forecast iceberg severity in future seasons; updated correlations have been made between sea ice coverage and iceberg severity.
Keywords: Ice; Industrial management; Future applications; Grand Banks; iceberg shapes; iceberg sightings; Labrador; Load calculation; Management techniques; Offshore locations; Sea ice

Polarimetry with the gemini planet imager: Methods, performance at first light, and the circumstellar ring around HR 4796A - Perrin, Marshall D.; Duchene, Gaspard; Millar-Blanchaer, Max; Fitzgerald, Michael P.; Graham, James R.; Wiktorowicz, Sloane J.; Kalas, Paul G.; Macintosh, Bruce; Bauman, Brian; Cardwell, Andrew; Chilcote, Jeffrey; De Rosa, Robert J.; et al. (The Astrophysical Journal, 2015)
We present the first results from the polarimetry mode of the Gemini Planet Imager (GPI), which uses anew integral field polarimetry architecture to provide high contrast linear polarimetry with minimal systematic biases between the orthogonal polarizations. We describe the design, data reduction methods, and performance of polarimetry with GPI. Point-spread function (PSF) subtraction via differential polarimetry suppresses unpolarized starlight by a factor of over 100, and provides sensitivity to circumstellar dust reaching the photon noise limit for these observations. in the case of the circumstellar disk around HR 4796A,GPI's advanced adaptive optics system reveals the disk clearly even prior to PSF subtraction. In polarized light, the disk is seen all the way in to its semi-minor axis for the first time. The disk exhibits surprisingly strong asymmetry in polarized intensity, with the west side ≳9 times brighter than the east side despite the fact that the east side is slightly brighter in total intensity. Based on a synthesis of the total and polarized intensities, we now believe that the west side is closer to us, contrary to most prior interpretations. Forward scattering by relatively large silicate dust particles leads to the strong polarized intensity on thewest side, and the ring must be slightly optically thick in order to explain the lower brightness in total intensity there. These findings suggest that the ring is geometrically narrow and dynamically cold, perhaps shepherded by larger bodies in the same manner as Saturn's Fring.

4D MR phase and magnitude segmentations with GPU parallel computing - Bergen, Robert V.; Lin, Hung-Yu; Alexander, Murray E.; Bidinosti, Christopher P. (Magnetic Resonance Imaging, 2015)
The increasing size and number of data sets of large four dimensional (three spatial, one temporal) magnetic resonance (MR) cardiac images necessitates efficient segmentation algorithms. Analysis of phase-contrast MR images yields cardiac flow information which can be manipulated to produce accurate segmentations of the aorta. Phase contrast segmentation algorithms are proposed that use simple mean-based calculations and least mean squared curve fitting techniques. The initial segmentations are generated on a multi-threaded central processing unit (CPU) in 10. seconds or less, though the computational simplicity of the algorithms results in a loss of accuracy. A more complex graphics processing unit (GPU)-based algorithm fits flow data to Gaussian waveforms, and produces an initial segmentation in 0.5. seconds. Level sets are then applied to a magnitude image, where the initial conditions are given by the previous CPU and GPU algorithms. A comparison of results shows that the GPU algorithm appears to produce the most accurate segmentation.
Keywords: algorithm; aorta flow; cardiovascular magnetic resonance; central processing unit; contrast radiography; graphics processing unit; image acquisition; image analysis; image processing; information processing; magnitude segmentation; mathematical computing; normal distribution; phase transition; segmentation algorithm; waveform

Transition-path probability as a test of reaction-coordinate quality reveals DNA hairpin folding is a one-dimensional diffusive process - Neupane, Krishna; Manuel, Ajay P.; Lambert, John; Woodside, Michael T. (The Journal of Physical Chemistry Letters, 2015)
Chemical reactions are typically described in terms of progress along a reaction coordinate. However, the quality of reaction coordinates for describing reaction dynamics is seldom tested experimentally. We applied a framework for gauging reaction-coordinate quality based on transition-path analysis to experimental data for the first time, looking at folding trajectories of single DNA hairpin molecules measured under tension applied by optical tweezers. The conditional probability for being on a reactive transition path was compared with the probability expected for ideal diffusion over a 1D energy landscape based on the committor function. Analyzing measurements and simulations of hairpin folding where end-to-end extension is the reaction coordinate, after accounting for instrumental effects on the analysis, we found good agreement between transition-path and committor analyses for model two-state hairpins, demonstrating that folding is well-described by 1D diffusion. This work establishes transition-path analysis as a powerful new tool for testing experimental reaction-coordinate quality.
Keywords: Optical tweezers; Probability; Regression analysis; Energy landscape; Force spectroscopy; Reaction coordinates; Reaction theory; Transition state

Control strategies and cycling demands for Li-ion storage batteries in residential micro-cogeneration systems - Darcovich, K.; Kenney, B.; MacNeil, D. D.; Armstrong, M. M. (Applied Energy, 2015)
Energy storage units have become important components in residential micro-cogeneration (MCG) systems. As MCG systems are often connected to single residences or buildings in a wide variety of settings, they are frequently unique and highly customized. Lithium-ion batteries have recently gained some profile as energy storage units of choice, because of their good capacity, high efficiency, robustness and ability to meet the demands of typical residential electrical loads. In the present work, modeled scenarios are explored which examine the performance of a MCG system with an internal combustion engine, photovoltaic input and a Li-ion storage battery. An electricity demand profile from new data collected in Ottawa, Canada is used to provide a full year energy use context for the analyses. The demands placed on the battery are examined to assess the suitability of the battery size and performance, as well as control related functionalities which reveal significantly varying battery use, and led to a quantitative expression for equivalent cycles. The energy use simulations are derived from electrochemical fundamentals adapted for a larger battery pack. Simulation output provides the basis for techno-economic commentary on how to assess large-scale Li-ion batteries for effective electrical storage purposes in MCG systems, and the impact of the nature of the control strategy on the battery service life.
Keywords: Cogeneration plants; Computer simulation; Digital storage; Electric batteries; Electric energy storage; Electric power supplies to apparatus; Energy utilization; Internal combustion engines; Ion engines; Ions; Lithium; Lithium alloys; Lithium compounds; Secondary batteries; Electrochemical modeling; Energy use; Lithium-ion battery; Residential micro cogenerations; Techno-economics; Lithium batteries; cogeneration; control system; demand-side management; electricity supply; electrochemical method; energy conservation; energy use; photovoltaic system

Characteristics of an autogenous single pass electron beam weld in thick gage CA6NM steel - Sarafan, S.; Wanjara, P.; Champliaud, H.; Thibault, D. (International Journal of Advanced Manufacturing Technology, 2015)
CA6NM is a low carbon martensitic stainless steel that is widely applied in hydroelectric turbine manufacturing. Using conventional fusion welding techniques, the fabrication of a thick section in CA6NM requires a V-groove joint design and multiple passes to achieve the required penetration. However, exposure to a substantial heat input through this process renders large fusion and heat-affected zones, microstructural variations, as well as distortion of the assembly, which pose difficulties for the manufacture and performance of the component. The application of a high energy density technique, namely electron beam (EB) welding, was used in the present work to penetrate a 60-mm-thick section in CA6NM with a single pass without filler metal. To prevent cracking in the weldment, the CA6NM was heated to 100–170 °C before EB welding using a zonal preheat treatment, which was applied in situ using a defocused beam. The as-welded CA6NM exhibited a narrow fusion zone (FZ) and a series of distinct yet very small heat-affected zones (HAZ) with different microstructural characteristics. As compared to the base metal (BM) hardness of 289 ± 4 HV, the EB weldment exhibited a hardness maximum of 425 HV in the HAZs and an average hardness of 395 ± 6 HV in the FZ. Post-weld heat treatment (PWHT) was effective in lowering the hardness in the FZ of the EB weldment to a mean value of 346 ± 13 HV.
Keywords: Corrosion; Electron beam welding; Electron beams; Filler metals; Heat affected zone; Heat treatment; Low carbon steel; Martensitic stainless steel; Microhardness; Microstructure; Preheating; Welding; Welds; CA-6NM martensitic stainless steels; Defocused beams; High energy densities; Micro-structural characteristics; Microstructural variation; Post weld heat treatment; Pre-heat treatment; V-groove joints; Stainless steel

Exploration of attenuated total reflectance mid-infrared spectroscopy and multivariate calibration to measure immunoglobulin G in human sera - Hou, Siyuan; Riley, Christopher B.; Mitchell, Cynthia A.; Shaw, R. Anthony; Bryanton, Janet; Bigsby, Kathryn; McClure, J. Trenton (Talanta, 2015)
Immunoglobulin G (IgG) is crucial for the protection of the host from invasive pathogens. Due to its importance for human health, tools that enable the monitoring of IgG levels are highly desired. Consequently there is a need for methods to determine the IgG concentration that are simple, rapid, and inexpensive. This work explored the potential of attenuated total reflectance (ATR) infrared spectroscopy as a method to determine IgG concentrations in human serum samples. Venous blood samples were collected from adults and children, and from the umbilical cord of newborns. The serum was harvested and tested using ATR infrared spectroscopy. Partial least squares (PLS) regression provided the basis to develop the new analytical methods. Three PLS calibrations were determined: one for the combined set of the venous and umbilical cord serum samples, the second for only the umbilical cord samples, and the third for only the venous samples. The number of PLS factors was chosen by critical evaluation of Monte Carlo-based cross validation results. The predictive performance for each PLS calibration was evaluated using the Pearson correlation coefficient, scatter plot and Bland-Altman plot, and percent deviations for independent prediction sets. The repeatability was evaluated by standard deviation and relative standard deviation. The results showed that ATR infrared spectroscopy is potentially a simple, quick, and inexpensive method to measure IgG concentrations in human serum samples. The results also showed that it is possible to build a united calibration curve for the umbilical cord and the venous samples. © 2015 Elsevier B.V. All rights reserved.
Keywords: Body fluids; Calibration; Correlation methods; Infrared spectroscopy; Reflection; Statistics; ATR-Infrared spectroscopy; Attenuated total reflectance; Immunoglobulin; Partial least squares regression; Pearson correlation coefficients; Relative standard deviations; Umbilical cords; Venous; Least squares approximations

Storage and retrieval of THZ-bandwidth single photons using a room-temperature diamond quantum memory - England, Duncan G.; Fisher, Kent A. G.; Maclean, Jean-Philippe W.; Bustard, Philip J.; Lausten, Rune; Resch, Kevin J.; Sussman, Benjamin J. (Physical Review Letters, 2015)
We report the storage and retrieval of single photons, via a quantum memory, in the optical phonons of a room-temperature bulk diamond. The THz-bandwidth heralded photons are generated by spontaneous parametric down-conversion and mapped to phonons via a Raman transition, stored for a variable delay, and released on demand. The second-order correlation of the memory output is g(2)(0)=0.65±0.07, demonstrating a preservation of nonclassical photon statistics throughout storage and retrieval. The memory is low noise, high speed and broadly tunable; it therefore promises to be a versatile light-matter interface for local quantum processing applications.
Keywords: Bandwidth; Optical frequency conversion; Phonons; Heralded photons; Nonclassical photon statistics; Optical phonons; Processing applications; Raman transition; Spontaneous parametric down conversion; Photons

Development of a highly effective multi-stage surface acoustic wave SU-8 microfluidic concentrator - Mu, Canjun; Zhang, Zhiyi; Lin, Min; Dai, Zheng; Cao, Xudong (Sensors and Actuators, B: Chemical, 2015)
As an important step in sample preparation, sample concentration step helps to improve sampling techniques that are often necessary to detect low levels of pathogenic bacteria in food safety inspections, reducing or completely eliminating the need for time-consuming cell enrichment process for detection. In this study, we investigated strategies to significantly enhance performances of a surface acoustic wave (SAW) microfluidic device to concentrate various particles, including microbeads, bacterial and mammalian cells in suspensions. A low acoustic energy loss material, SU-8, was used to fabricate the microfluidic concentrator, and SAW reflectors were designed to efficiently use the SAW generated acoustic energy for particle concentration. The concentration performance was further improved by using a two-stage concentration design. We demonstrated that the SU-8 microfluidic concentrator with a two-stage concentration configuration was able to concentrate 2.00 μm bead samples at an overall concentration factor of ∼65-fold with a particle recovery efficiency of 81.9 ± 5.9% at a inflow rate of 300 μl/h. Similarly, when the concentrator was used to concentrate E. coli DH5α and NIH/3T3 cells, overall concentration factors of ∼59 and 75-fold with particle recovery efficiencies of 81.0 ± 17.2% and 90.8 ± 5.0% were obtained, respectively. These results show significant improvements upon those previously reported for either bacterial or mammalian cell concentration applications. In addition, the device fabrication process developed in this work is fully compatible with regular microfabrication processes, making this microfluidic concentrator readily integrable with other on-chip functionalities for cell manipulation and detection applications.
Keywords: Acoustic surface wave devices; Acoustic waves; Acoustics; Bacteria; Concentration (process); Energy dissipation; Escherichia coli; Food safety; Importance sampling; Mammals; Molecular biology; Suspensions (fluids); Bacteria detection; Concentrator; Food safety inspection; Microfabrication process; On-chip functionalities; Particle concentrations; Sample preparation; Surface acoustic waves; Microfluidics

Use of Fourier-transform infrared spectroscopy to quantify immunoglobulin G concentration and an analysis of the effect of signalment on levels in canine serum - Seigneur, A.; Hou, S.; Shaw, R. A.; McClure, J. T.; Gelens, H.; Riley, C. B. (Veterinary Immunology and Immunopathology, 2015)
Deficiency in immunoglobulin G (IgG) is associated with an increased susceptibility to infections in humans and animals, and changes in IgG levels occur in many disease states. In companion animals, failure of transfer of passive immunity is uncommonly diagnosed but mortality rates in puppies are high and more than 30% of these deaths are secondary to septicemia. Currently, radial immunodiffusion (RID) and enzyme-linked immunosorbent assays are the most commonly used methods for quantitative measurement of IgG in dogs. In this study, a Fourier-transform infrared spectroscopy (FTIR) assay for canine serum IgG was developed and compared to the RID assay as the reference standard. Basic signalment data and health status of the dogs were also analyzed to determine if they correlated with serum IgG concentrations based on RID results.Serum samples were collected from 207 dogs during routine hematological evaluation, and IgG concentrations determined by RID. The FTIR assay was developed using partial least squares regression analysis and its performance evaluated using RID assay as the reference test. The concordance correlation coefficient was 0.91 for the calibration model data set and 0.85 for the prediction set. A Bland-Altman plot showed a mean difference of -89. mg/dL and no systematic bias. The modified mean coefficient of variation (CV) for RID was 6.67%, and for FTIR was 18.76%.The mean serum IgG concentration using RID was 1943. ±. 880. mg/dL based on the 193 dogs with complete signalment and health data. When age class, gender, breed size and disease status were analyzed by multivariable ANOVA, dogs <2 years of age (. p=. 0.0004) and those classified as diseased (. p=. 0.03) were found to have significantly lower IgG concentrations than older and healthy dogs, respectively.
Keywords: immunoglobulin G; analysis of variance; calibration; correlation coefficient; dog; female; health status; immunodiffusion; infrared spectroscopy; male; partial least squares regression; prediction; radial immunodiffusion; serum; Animalia; Canis familiaris

Investigation of nanofiber nonwoven meshes produced by electrospinning of cellulose nanocrystal suspensions in cellulose acetate solutions - Sun, Chenggui; Boluk, Yaman; Ayranci, Cagri (Cellulose, 2015)
The development of nonwoven meshes based on cellulose acetate (CA) reinforced by cellulose nanocrystals (CNC) is reported. The meshes were electrospun from 15 wt% CA (Mn = 30,000) in dimethylacetamide/acetone (1:2, w/w) solutions with various concentrations of CNC dispersions. The investigated six levels of CNC dispersions in CA solutions were: 0, 0.075, 0.147, 0.225, 0.300 and 0.382 wt%, which corresponded to 0, 0.50, 1.00, 1.50, 1.99 and 2.55 wt% of CNC in solid fibers. The basis of the impact of CNC nano-particles on fiber diameter and morphology was explored by assessing their contributions to the viscosity, conductivity and homogeneity of CA/CNC solutions. CA/CNC nonwoven meshes spun from suspensions with 0.075 wt% CNC had best results in morphology and fiber uniformity. Additionally, mechanical properties of CA nonwoven meshes with five levels of CNC loading (0, 0.50, 1.00, 1.50 and 1.99 wt%) were examined. The CA nonwoven mesh with 0.50 wt% CNC showed best mechanical properties, and its elastic modulus (E) was improved to an average value of 1.68 GPa from 1.17 GPa of neat CA nanofiber nonwoven mesh. These improved meshes would have applications such as separation membranes, supports for catalysts and sensors, engineered tissues and other smart materials.
Keywords: Cellulose; Cellulose derivatives; Dispersions; Electrospinning; Mechanical properties; Membranes; Morphology; Nanocrystals; Nanofibers; Nanoparticles; Nonwoven fabrics; Spinning (fibers); Volatile fatty acids; Cellulose acetates; Cellulose nano-crystals; Cellulose nanocrystal (CNC); Composite nanofibers; Dimethylacetamide; Engineered tissues; Non-woven meshes; Separation membranes; Weaving

Multilocus sequence typing and virulence gene profiles associated with Escherichia coli from human and animal sources - Manges, Amee R.; Harel, Josée; Masson, Luke; Edens, Thaddeus J.; Portt, Andrea; Reid-Smith, Richard J.; Zhanel, George G.; Kropinski, Andrew M.; Boerlin, Patrick (Foodborne Pathogens and Disease, 2015)
We investigated whether specific sequence types, and their shared virulence gene profiles, may be associated with both human and food animal reservoirs. A total of 600 Escherichia coli isolates were assembled from human (n=265) and food-animal (n=335) sources from overlapping geographic areas and time periods (2005-2010) in Canada. The entire collection was subjected to multilocus sequence typing and a subset of 286 E. coli isolates was subjected to an E. coli-specific virulence gene microarray. The most common sequence type (ST) was E. coli ST10, which was present in all human and food-animal sources, followed by ST69, ST73, ST95, ST117, and ST131. A core group of virulence genes was associated with all 10 common STs including artJ, ycfZ, csgA, csgE, fimA, fimH, gad, hlyE, ibeB, mviM, mviN, and ompA. STs 73, 92, and 95 exhibited the largest number of virulence genes, and all were exclusively identified from human infections. ST117 was found in both human and food-animal sources and shared virulence genes common in extraintestinal pathogenic E. coli lineages. Select groups of E. coli may be found in both human and food-animal reservoirs.
Keywords: animal food; bacterial virulence; bacterium isolate; beef cattle meat; beef meat; chicken meat; controlled study; Escherichia coli; hospital infection; human; meat; multidimensional scaling; multilocus sequence typing; nonhuman; pathotype; pig meat; pork meat; Escherichia coli

Protoplanetary disk masses in the young NGC 2024 cluster - Mann, Rita K.; Andrews, Sean M.; Eisner, Josh A.; Williams, Jonathan P.; Meyer, Michael R.; Di Francesco, James; Carpenter, John M.; Johnstone, Doug (The Astrophysical Journal, 2015)
We present the results from a Submillimeter Array survey of the 887 μm continuum emission from the protoplanetary disks around 95 young stars in the young cluster NGC 2024. Emission was detected from 22 infrared sources, with flux densities from ∼5 to 330 mJy; upper limits (at 3σ) for the other 73 sources range from 3 to 24 mJy. For standard assumptions, the corresponding disk masses range from ∼0.003 to 0.2 M⊙, with upper limits at 0.002-0.01 M⊙. The NGC 2024 sample has a slightly more populated tail at the high end of its disk mass distribution compared to other clusters, but without more information on the nature of the sample hosts it remains unclear if this difference is statistically significant or a superficial selection effect. Unlike in the Orion Trapezium, there is no evidence for a disk mass dependence on the (projected) separation from the massive star IRS 2b in the NGC 2024 cluster. We suggest that this is due to either the cluster youth or a comparatively weaker photoionizing radiation field.

VEGAS-SSS. A VST early-type galaxy survey: Analysis of small stellar systems - Testing the methodology on the globular cluster system in NGC3115 - Cantiello, Michele; Capaccioli, Massimo; Napolitano, Nicola; Grado, Aniello; Limatola, Luca; Paolillo, Maurizio; Iodice, Enrica; Romanowsky, Aaron J.; Forbes, Duncan A.; Raimondo, Gabriella; Spavone, Marilena; La Barbera, Francesco; et al. (Astronomy and Astrophysics, 2015)
We present a study of globular clusters (GCs) and other small stellar systems (SSSs) in the field of NGC3115, observed as part of the ongoing wide-field imaging survey VEGAS, carried out with the 2.6 m VST telescope. We used deep g and i observations of NGC3115, a well-studied lenticular galaxy that is covered excellently well in the scientific literature. This is fundamental to test the methodologies, verify the results, and probe the capabilities of the VEGAS-SSS. Leveraging the large field of view of the VST allowed us to accurately study the distribution and properties of SSSs as a function of galactocentric distance, well beyond ∼20 galaxy effective radii, in a way that is rarely possible. Our analysis of colors, magnitudes, and sizes of SSS candidates confirms the results from existing studies, some of which were carried out with 8-10 m class telescopes, and further extends them to previously unreached galactocentric distances with similar accuracy. In particular, we find a color bimodality for the GC population and a de Vaucouleurs r1/4 profile for the surface density of GCs similar to the galaxy light profile. The radial color gradient of blue and red GCs previously found, for instance, by the SLUGGS survey with Subaru and Keck data, is further extended out to the largest galactocentric radii inspected, ∼65 kpc. In addition, the surface density profiles of blue and red GCs taken separately are well approximated by a r1/4 density profile, with the fraction of blue GCs being slightly larger at larger radii. We do not find hints of a trend for the red GC subpopulation and for the GC turnover magnitude to vary with radius, but we observe a ∼0.2 mag difference in the turnover magnitude of the blue and red GC subpopulations. Finally, from inspecting SSS sizes and colors, we obtain a list of ultracompact dwarf galaxies and GC candidates suitable for future spectroscopic follow-up. In conclusion, our study shows i) the reliability of the methodologies developed to study SSSs in the field of bright early-type galaxies; and ii) the great potential of the VEGAS survey to produce original results on SSSs science, mainly thanks to the wide-field imaging adopted.
Keywords: Color; Stars; Surveying; Telescopes; Catalogs; Galaxies: individuals; Galaxies: star clusters: generals; Galaxies: statistics; Galaxies: stellar content; Galaxies

An approach towards synthesis of nanoarchitectured LiNi1/3Co1/3Mn1/3O2 cathode material for lithium ion batteries - Hua, Weibo; Wang, Yanjie; Zhong, Yanjun; Wang, Guoping; Zhong, Benhe; Fang, Baizeng; Guo, Xiaodong; Liao, Shixuan; Wang, Haijiang (Chinese Journal of Chemistry, 2015)
To explore advanced cathode materials for lithium ion batteries (LIBs), a nanoarchitectured LiNi1/3Co1/3Mn1/3O2 (LNCM) material is developed using a modified carbonate coprecipitation method in combination with a vacuum distillation-crystallisation process. Compared with the LNCM materials produced by a traditional carbonate coprecipitation method, the prepared LNCM material synthesized through this modified method reveals a better hexagonal layered structure, smaller particle sizes (ca. 110.5 nm), and higher specific surface areas. Because of its unique structural characteristics, the as-prepared LNCM material demonstrates excellent electrochemical properties including high rate capability and good cycleability when it is utilized as a cathode in the lithium ion battery (LIB).

Understanding the biochemical basis of temperature-induced lipid pathway adjustments in plants - Li, Qiang; Zheng, Qian; Shen, Wenyun; Cram, Dustin.; Fowler, D. Brian; Wei, Yangdou; Zou, Jitao (Plant Cell, 2015)
Glycerolipid biosynthesis in plants proceeds through two major pathways compartmentalized in the chloroplast and the endoplasmic reticulum (ER). The involvement of glycerolipid pathway interactions in modulating membrane desaturation under temperature stress has been suggested but not fully explored. We profiled glycerolipid changes as well as transcript dynamics under suboptimal temperature conditions in three plant species that are distinctively different in the mode of lipid pathway interactions. In Arabidopsis thaliana, a 16:3 plant, the chloroplast pathway is upregulated in response to low temperature, whereas high temperature promotes the eukaryotic pathway. Operating under a similar mechanistic framework, Atriplex lentiformis at high temperature drastically increases the contribution of the eukaryotic pathway and correspondingly suppresses the prokaryotic pathway, resulting in the switch of lipid profile from 16:3 to 18:3. In wheat (Triticum aestivum), an 18:3 plant, low temperature also influences the channeling of glycerolipids from the ER to chloroplast. Evidence of differential trafficking of diacylglycerol moieties from the ER to chloroplast was uncovered in three plant species as another layer of metabolic adaptation under temperature stress. We propose a model that highlights the predominance and prevalence of lipid pathway interactions in temperature-induced lipid compositional changes.
Keywords: Arabidopsis thaliana; Atriplex lentiformis; Eukaryota; Prokaryota; Triticum aestivum

Observatory/data centre partnerships and the VO-centric archive: The JCMT Science Archive experience - Economou, Frossie; Gaudet, S.; Jenness, T.; Redman, R. O.; Goliath, S.; Dowler, P.; Currie, M. J.; Bell, G. S.; Graves, S. F.; Ouellette, J.; Johnstone, D.; Schade, D.; et al. (Astronomy and Computing, 2015)
We present, as a case study, a description of the partnership between an observatory (JCMT) and a data centre (CADC) that led to the development of the JCMT Science Archive (JSA). The JSA is a successful example of a service designed to use Virtual Observatory (VO) technologies from the start. We describe the motivation, process and lessons learned from this approach.

Electrochemical supercapacitors for energy storage and delivery: advanced materials, technologies and applications - Yu, A.; Chen, Z.; Maric, R.; Zhang, L.; Zhang, J.; Yan, J. (Applied Energy, 2015)

Competition H(D) kinetic isotope effects in the autoxidation of hydrocarbons - Muchalski, Hubert; Levonyak, Alexander J.; Xu, Libin; Ingold, Keith U.; Porter, Ned A. (Journal of the American Chemical Society, 2015)
Hydrogen atom transfer is central to many important radical chain sequences. We report here a method for determination of both the primary and secondary isotope effects for symmetrical substrates by the use of NMR. Intramolecular competition reactions were carried out on substrates having an increasing number of deuterium atoms at symmetry-related sites. Products that arise from peroxyl radical abstraction at each position of the various substrates reflect the competition rates for H(D) abstraction. The primary KIE for autoxidation of tetralin was determined to be 15.9 ± 1.4, a value that exceeds the maximum predicted by differences in H(D) zero-point energies (∼7) and strongly suggests that H atom abstraction by the peroxyl radical occurs with substantial quantum mechanical tunneling.
Keywords: Abstracting; Atoms; Carrier mobility; Isotopes; Oxidation; Quantum theory; Competition reactions; H-atom abstraction; Hydrogen-atom transfer; Kinetic isotope effects; Peroxyl radical; Quantum-mechanical tunneling; Various substrates; Zero-point energies; Free radical reactions; deuterium; hydrocarbon; hydrogen; isotope; peroxy radical; tetralin derivative; atomic particle; autooxidation; chemical reaction kinetics; chemical structure; intramolecular competition; nuclear magnetic resonance; proton transport; quantum chemistry; reaction analysis

Capacitive effects of nitrogen doping on cellulose-derived carbon nanofibers - Kuzmenko, Volodymyr; Naboka, Olga; Staaf, Henrik; Haque, Mazharul; Göransson, Gert; Lundgren, Per; Gatenholm, Paul; Enoksson, Peter (Materials Chemistry and Physics, 2015)
Carbons with valuable electrochemical characteristics are among the most convenient electrode materials used for energy storage. At the moment, their production is mostly reliant on unsustainable fossil fuels. A preferential sustainable production of enhanced carbonaceous electrodes can be achieved with more extensive utilization of abundant renewable resources instead of fossils. In this study, nitrogen-doped carbon nanofibers (CNFs) were synthesized from cellulose, the most abundant renewable resource, via consecutive steps of cellulose acetate electrospinning, subsequent deacetylation to cellulose, impregnation with nitrogen-containing additive (ammonium chloride), and carbonization. Results of material characterization showed that the carbonization of functionalized cellulose samples led to formation of CNFs doped with 4-5.6 at.% of nitrogen. In comparison with pristine CNFs N-doped samples had a slightly lower specific surface area, but higher conductivity and hydrophilicity. Moreover, electrochemical measurements indicated that the enhanced N-doped materials had about 2.5 times higher specific capacitance which was increasing throughout 1000 charge-discharge cycles. These results suggest that nitrogen doping method used in this study has a positive pseudocapacitive effect on the electrochemical performance of carbonized cellulose materials.
Keywords: Acetylation; Carbon nanofibers; Carbonization; Cellulose; Characterization; Chlorine compounds; Doping (additives); Electric discharges; Electrochemical properties; Electrodes; Nanofibers; Nanostructures; Nitrogen; Charge-discharge cycle; Electrochemical characteristics; Electrochemical measurements; Electrochemical performance; Material characterizations; Nitrogen-doped carbon nanofibers; Specific capacitance; Sustainable production; Electrochemical electrodes

Raman microscopy mapping for the purity assessment of chirality enriched carbon nanotube networks in thin-film transistors - Li, Zhao; Ding, Jianfu; Finnie, Paul; Lefebvre, Jacques; Cheng, Fuyong; Kingston, Christopher T.; Malenfant, Patrick R. L. (Nano Research, 2015)
With recent improvements in carbon nanotube separation methods, the accurate determination of residual metallic carbon nanotubes in a purified nanotube sample is important, particularly for those interested in using semiconducting single-walled carbon nanotubes (SWCNTs) in electronic device applications such as thin-film transistors (TFTs). This work demonstrates that Raman microscopy mapping is a powerful characterization tool for quantifying residual metallic carbon nanotubes present in highly enriched semiconducting nanotube networks. Raman mapping correlates well with absorption spectroscopy, yet it provides greater differentiation in purity. Electrical data from TFTs with channel lengths of 2.5 and 5 μm demonstrate the utility of the method. By comparing samples with nominal purities of 99.0% and 99.8%, a clear differentiation can be made when evaluating the current on/off ratio as a function of channel length, and thus the Raman mapping method provides a means to guide device fabrication by correlating SWCNT network density and purity with TFT channel scaling.
Keywords: Raman spectroscopy; carbon nanotubes; thin film transistors; microscopy mapping; purity assessment

Magnetic fields of the W4 superbubble - Gao, X.Y.; Reich, W.; Reich, P.; Han, J. L.; Kothes, R. (Astronomy and Astrophysics, 2015)
Context. Superbubbles and supershells are the channels for transferring mass and energy from the Galactic disk to the halo. Magnetic fields are believed to play a vital role in their evolution. Aims. We study the radio continuum and polarized emission properties of the W4 superbubble to determine its magnetic field strength. Methods. New sensitive radio continuum observations were made at λ6 cm, λ11 cm, and λ21 cm. The total intensity measurements were used to derive the radio spectrum of the W4 superbubble. The linear polarization data were analysed to determine the magnetic field properties within the bubble shells. Results. The observations show a multi-shell structure of the W4 superbubble. A flat radio continuum spectrum that stems from optically thin thermal emission is derived from 1.4 GHz to 4.8 GHz. By fitting a passive Faraday screen model and considering the filling factor fne, we obtain the thermal electron density ne = 1,0/ ne 1.0/fne (±5%) cm-3 and the strength of the line-of-sight component of the magnetic field B// = -5.0/fne 5,0/ ne (±10%) μG (i.e. pointing away from us) within the western shell of the W4 superbubble. When the known tilted geometry of the W4 superbubble is considered, the total magnetic field Btot in its western shell is greater than 12 μG. The electron density and the magnetic field are lower and weaker in the high-latitude parts of the superbubble. The rotation measure is found to be positive in the eastern shell but negative in the western shell of the W4 superbubble, which is consistent with the case where the magnetic field in the Perseus arm is lifted up from the plane towards high latitudes. Conclusions. The magnetic field strength and the electron density we derived for the W4 superbubble are important parameters for evolution models of superbubbles breaking out of the Galactic plane.
Keywords: Carrier concentration; Electron density measurement; Electrons; Magnetic fields; Shells (structures); Solar system; Thermionic emission; Intensity measurements; ISM: individual objects; ISM: magnetic fields; Line-of-sight components; Magnetic field strengths; Multishell structures; Polarized emissions; Radio continuum: ISM; Magnetism

Synthesis and electrochemical properties of high performance polyhedron sphere like lithium manganese oxide for lithium ion batteries - Guo, Donglei; Wei, Xiuge; Chang, Zhaorong; Tang, Hongwei; Li, Bao; Shangguan, Enbo; Chang, Kun; Yuan, Xiao-Zi; Wang, Haijiang (Journal of Alloys and Compounds, 2015)
Polyhedron structured sphere-like lithium manganese oxide (LiMninf2/infOinf4/inf) is successfully synthesized from β-MnOinf2/inf nanorod precursor via a solid state reaction at a temperature of 800 °C. For comparison, LiMninf2/infOinf4/inf materials with nanorod and octahedron structures are also obtained from β-MnOinf2/inf nanorod precursor at temperatures of 700 °C and 900 °C, respectively. The galvanostatic charge-discharge result shows that the polyhedron sphere-like LiMninf2/infOinf4/inf sample exhibits the best electrochemical performance at high rate and high temperature. After 100 cycles at 5 C, this electrode is able to maintain 94% of its capacity at 25 °C and 81% at 55 °C. This is attributed to that the polyhedron sphere-like spinel LiMninf2/infOinf4/inf can suppress the dissolution of manganese ions. Based on Brunauer Emmett Teller (BET), cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS), the polyhedron sphere-like LiMninf2/infOinf4/inf sample has the lowest BET surface area, largest diffusion coefficient of Lisup+/sup and least charge transfer resistance. This study provides an insight into the capacity fading of LiMninf2/infOinf4/inf electrodes and the polyhedron structured sphere-like LiMninf2/infOinf4/inf can be a promising material for lithium ion batteries.
Keywords: Cathodes; Charge transfer; Cyclic voltammetry; Diffusion; Electric batteries; Electric discharges; Electrochemical impedance spectroscopy; Electrodes; Geometry; Ions; Lithium; Lithium alloys; Lithium compounds; Manganese; Manganese oxide; Nanorods; Oxides; Secondary batteries; Solid state reactions; Spheres; Synthesis (chemical); BET surface area; Brunauer emmett tellers; Cath-ode materials; Charge transfer resistance; Electrochemical performance; Galvanostatic charge discharges; Lithium manganese oxide; Polyhedron sphere like; Lithium batteries

Elemental abundance analyses with DAO spectrograms. XXXVIII. The SB2 stars HR 104 (A2 V) and θ Aql (B9.5 III) - Adelman, Saul J.; Yüce, Kutluay; Gulliver, Austin F. (Publications of the Astronomical Society of the Pacific, 2015)
The study of the elemental abundances of double-lined spectroscopic binaries should provide information on the chemical differentiation of a once uniform prestellar nebula. To determine the effective temperatures and surface gravities of the primary and secondary stellar components of HR 104 and θ Aql, we used parameters derived from their orbital analyses and the requirement of equal abundances derived from Fe I and Fe II lines. For constraints we had optical region spectrophotometry for θ Aql and the large equivalent width ratios for the many spectral metal lines which were produced in both stellar atmospheres for HR 104. Since the primary stars were much brighter than the secondary stars, the abundances are considerably better determined for the primary stars. For HR 104 A we found Teff = 9875 K, log g = 4:26, and ξ = 1:7 km s−1; for HR 104 B Teff = 7200 K, log g = 4:26, and ξ = 0:6 km s−1; for θ Aql A Teff = 10400 K, log = 3:63, and ξ = 0:3 km s−1; and for θ Aql B Teff = 10250 K, log = 4:20, and ξ = 1:9 km s−1. The abundances of HR 104 A, HR 104 B, and θ Aql A are best described as the solar pattern. Those of θ Aql B suggest a weak nonmagnetic CP star pattern. While there is no trace of the Hg II 3984 line for θ Aql, the most extreme observed abundance anomalies for the secondary are those of Ca, V, Mn, and Ni. Further study of this hot marginal Am star could provide insights into the origin of the nonsolar chemical abundances.

The infrared spectrum of the He-C2D2 complex - Moazzen-Ahmadi, N.; McKellar, A. R. W.; Fernández, B.; Farrelly, D. (Journal of Chemical Physics, 2015)
Spectra of the helium-acetylene complex are elusive because this weakly bound system lies close to the free rotor limit. Previously, limited assignments of He-C2D2 transitions in the R(0) region of the ν3 fundamental band (≈2440 cm-1) were published. Here, new He-C2D2 infrared spectra of this band are obtained using a tunable optical parametric oscillator laser source to probe a pulsed supersonic slit jet expansion from a cooled nozzle, and the analysis is extended to the weaker and more difficult P(1) and R(1) regions. A term value approach is used to obtain a consistent set of "experimental" energy levels. These are compared directly with calculations using two recently reported ab initio intermolecular potential energy surfaces, which exhibit small but significant differences. Rovibrational energies for the He-C2H2 complex are also calculated using both surfaces. A Coriolis model, useful for predicting spectral intensities, is used to interpret the energy level patterns, and a comparison with the isoelectronic complex He-CO is made.
Keywords: Optical parametric oscillators; Potential energy; Quantum chemistry; Spectroscopy; Supersonic aerodynamics; Acetylene complex; Fundamental bands; Infrared spectrum; Intermolecular potential energy surfaces; Isoelectronic complexes; Jet expansion; Ro-vibrational energies; Spectral intensity; Parametric oscillators

General phenomenology of ionization from aligned molecular ensembles - Hockett, Paul (New Journal of Physics, 2015)
Single and multi-photon ionization of aligned molecular ensembles is examined, with a particular focus on the link between the molecular axis distribution and observable in various angle-integrated and angle-resolved measurements. To maintain generality the problem is treated geometrically, with the aligned ensemble cast in terms of axis distribution moments, and the response of observables in terms of couplings to these moments. Within this formalism the angular momentum coupling is treated analytically, allowing for general characteristics - independent of the details of the ionization dynamics of a specific molecule - to be determined. Limiting cases are explored in order to provide a phenomenology which should be readily applicable to a range of experimental measurements, and illustrate how observables can be sensitive to fine details of the alignment, i.e. higher-order moments of the axis distribution, which are often neglected in experimental studies. We hope that this detailed and comprehensive treatment will bridge the gap between existing theoretical and experimental works, and provide both quantitative physical insights and a useful general phenomenology for researchers working with aligned molecular ensembles.
Keywords: Ionization; Molecular orientation; Multiphoton processes; Photons; Angle-resolved; Angular momentum coupling; Distribution moments; Higher order moments; Ionization dynamics; Molecular axis; Multiphoton ionization; Photoelectron angular distributions; Photoionization

Formation of inter-diffusion layer between NiCrAlY coating and Nb substrate during vacuum heat-treatment - Saito, Shigeru; Takashima, Toshiyuki; Miyama, Katsumi; Narita, Toshio; Zhao, Linruo (Materials Transactions, 2015)
The formation of the inter-diffusion layer between NiCrAlY coating and Nb substrate during vacuum heat treatment was investigated. A NiCrAlY coating was applied on Nb substrate by cathode arc deposition. Vacuum heat treatments were carried out at 800, 900, and 1000°C for 2 h. SEM, EPMA, EDS, and XRD were performed to analyze the microstructure of the inter-diffusion layer and the results were interpreted using the 1002°C isothermal ternary Nb-Ni-Cr phase diagram. It was found that at 800°C the inter-diffusion layer has a single NbNi3 layer; at 900°C the inter-diffusion layer consists of an outer NbNi3 layer, a thin intermediate NbCr2(HT) layer, and an inner Nb7Ni6 layer; at 1000°C the interdiffusion layer has three well-developed layers of an outer NbNi3 layer, an inner Nb7Ni6 layer, and an intermediate layers comprising NbCr2(HT) and NbNi3. A small amount of Cr exists in both the NbNi3 and the Nb7Ni6 phases as solid solution, and a large amount of Ni in the NbCr2(HT) phase as solid solution.
Keywords: Cathodes; Coatings; Deposition; Diffusion; Electrodes; Heat treatment; Nickel; Solid solutions; Arc deposition; NbCr2(HT) phase; NbNi3 phase; Nickel chromium; Vacuum heat treatment; Diffusion coatings

Structure formation in biological molecules as a diffusive process probed by optical tweezers - Woodside, Michael (Optical Trapping Applications, OTA 2015, 2015)
Folding of proteins and nucleic acids involves diffusion over a multidimensional energy landscape. Optical tweezers provide a powerful method for measuring this landscape using single-molecule force spectroscopy, whereby individual molecules are unfolded and refolded under mechanical load applied by the tweezers and the resulting changes in extension of the molecule are monitored to follow changes in the molecular structure. Methods are discussed for measuring energy landscapes, approximated as a 1D projection of the full multi-dimensional energy surface, via equilibrium fluctuations of the extension or non-equilibrium force-ramps. The correct approach for determining the diffusion coefficient for structural changes from such measurements, wherein the effects of instrumental compliance and time resolution are taken into account, is described. Finally, the approximation of folding as a 1D diffusive process is shown to be good for simple molecules like DNA hairpins, despite the high dimensionality of the full folding problem.
Keywords: Diffusion; Molecules; Nucleic acids; Regulatory compliance; Biological molecule; Diffusive process; Equilibrium fluctuation; High dimensionality; Mechanical loads; Multi dimensional; Single molecule force spectroscopy; Structure formations; Optical tweezers

Response to reply on "Structural and magnetic behavior of the cubic oxyfluoride SrFeO2F studied by neutron diffraction" - Thompson, Corey M.; Blakely, Colin K.; Flacau, Roxana; Greedan, John E.; Poltavets, Viktor V. (Journal of Solid State Chemistry, 2015)
Clemens et al. reported on the results published by us (Thompson et al. J. Solid State Chem. 219 (2014) 173-178) on the crystal structure of SrFeO2F, which they suggest to actually crystallize in the orthorhombic space group Imma rather than the cubic Pm-3m structure at lower temperatures (Clemens et al. J. Solid State Chem. (2015), http://dx.doi.org/10.1016/j.jssc.2015.02.022). In this report, we provide evidence to support their claim that at lower temperatures (<523K) the structure is evidently Imma. Furthermore, we will highlight the significance of our previous report and comment on the proposed explanations of the magnetic behavior of SrFeO2F reported by both groups.
Keywords: Aluminum; Antiferromagnetism; Crystallography; Magnetic structure; Neutron diffraction; Lower temperatures; Magnetic behavior; Orthorhombic space groups; Oxyfluorides; Thompson; Crystal structure

Interfacing GHz-bandwidth heralded single photons with a warm vapour Raman memory - Michelberger, P. S.; Champion, T. F. M.; Sprague, M. R.; Kaczmarek, K. T.; Barbieri, M.; Jin, X. M.; England, D. G.; Kolthammer, W. S.; Saunders, D. J.; Nunn, J.; Walmsley, I. A. (New Journal of Physics, 2015)
Broadband quantum memories, used as temporal multiplexers, are a key component in photonic quantum information processing, as they make repeat-until-success strategies scalable. We demonstrate a prototype system, operating on-demand, by interfacing a warm vapour, high time-bandwidth-product Raman memory with a travelling wave spontaneous parametric down-conversion source. We store single photons and observe a clear influence of the input photon statistics on the retrieved light, which we find currently to be limited by noise. We develop a theoretical model that identifies four-wave mixing as the sole important noise source and point towards practical solutions for noise-free operation.
Keywords: Bandwidth; Four wave mixing; Multiplexing; Multiplexing equipment; Optical frequency conversion; Particle beams; Photons; Quantum computers; Quantum optics; Quantum memory; Raman interactions; Room temperature; Single photon storage; temporal multiplexer; Quantum communication

Investigation into photostability of soybean oils by thermal lens spectroscopy - Savi, E. L.; Malacarne, L. C.; Baesso, M. L.; Pintro, P. T. M.; Croge, C.; Shen, J.; Astrath, N. G. C. (Spectrochimica Acta - Part A: Molecular and Biomolecular Spectroscopy, 2015)
Assessment of photochemical stability is essential for evaluating quality and the shelf life of vegetable oils, which are very important aspects of marketing and human health. Most of conventional methods used to investigate oxidative stability requires long time experimental procedures with high consumption of chemical inputs for the preparation or extraction of sample compounds. In this work we propose a time-resolved thermal lens method to analyze photostability of edible oils by quantitative measurement of photoreaction cross-section. An all-numerical routine is employed to solve a complex theoretical problem involving photochemical reaction, thermal lens effect, and mass diffusion during local laser excitation. The photostability of pure oil and oils with natural and synthetic antioxidants is investigated. The thermal lens results are compared with those obtained by conventional methods, and a complete set of physical properties of the samples is presented.
Keywords: Chemical compounds; Chemical stability; Diffusion in solids; Laser excitation; Oil shale; Photochemical reactions; Photoreactivity; Molecular diffusion; Photo-stability; Photochemical stability; Photoreactions; Quantitative measurement; Synthetic antioxidants; Thermal lens; Thermal lens spectroscopy; Soybean oil

Dynamic wind effects on suspension and cable-stayed bridges - Larsen, Allan; Larose, Guy L. (Journal of Sound and Vibration, 2015)
Cable supported bridges are flexible structures which may be excited into oscillations by the wind. The excitation forces acting on cable supported bridges are aerodynamic by nature, but are for a large part set into play by the underlying structural dynamics of the bridge structures. The paper discusses the various types of dynamic wind effects commonly encountered for suspension and cable-stayed bridges emphasizing the importance of the structural dynamics.
Keywords: Cables; Flexible structures; Structural dynamics; Suspensions (components); Wind effects; Bridge structures; Cable-supported bridges; Dynamic winds; Excitation force; Cable stayed bridges

Group IV mid-infrared photonics - Mashanovich, G. Z.; Nedeljkovic, M.; Soler Penades, J.; Mitchell, C. J.; Khokhar, A. Z.; Littlejohns, C. J.; Stankovic, S.; Troia, B.; Wang, Y.; Reynolds, S.; Passaro, V. M. N.; Shen, L.; et al. (SPIE - International Society for Optical Engineering. Proceedings, 2015)
In this paper we present SOI, suspended Si, and Ge-on-Si photonic platforms and devices for the mid-infrared. We demonstrate low loss strip and slot waveguides in SOI and show efficient strip-slot couplers. A Vernier configuration based on racetrack resonators in SOI has been also investigated. Mid-infrared detection using defect engineered silicon waveguides is reported at the wavelength of 2-2.5 μm. In order to extend transparency of Si waveguides, the bottom oxide cladding needs to be removed. We report a novel suspended Si design based on subwavelength structures that is more robust than previously reported suspended designs. We have fabricated record low loss Ge-on-Si waveguides, as well as several other passive devices in this platform. All optical modulation in Ge is also analyzed.
Keywords: Germanium; Infrared devices; Mach-Zehnder interferometers; Photonic devices; Photonics; Resonators; Silicon on insulator technology; Waveguides; Mid-infrared detection; Midinfrared; Multi-mode interference; Passive devices; Racetrack resonators; Ring resonator; Silicon waveguide; Sub-wavelength structures; Silicon

An integrated feature-based dynamic control system for on-line machining, inspection and monitoring - Li, Yingguang; Liu, Changqing; Gao, James X.; Shen, Weiming (Integrated Computer-Aided Engineering, 2015)
Manufacturing companies dealing with high value, high accuracy and complex parts are facing increasing demand for higher quality and efficiency at lower costs and reduced lead times from their global customers. In real-life production such as the Numerical Control (NC) machining processes, there are continuous changes in machine tool performance, cutting tool conditions, workpiece deformation, cutting parameters, in addition to the changes in the geometry and properties of the parts being machined. Some changes are caused by 'predictable' factors such as cutting forces and machine tool deterioration over time, whilst others are caused by 'unpredictable' factors such as sudden breakdowns, uneven material property, vibration and machining chatter, or even human errors. These dynamic factors impose significant difficulties to ensuring machining accuracy effectively especially the controlling of unrecoverable over-cut errors normally causing part failures. This project aims to establish a set of integrated information models to address the dynamics of machining conditions based on the Dynamic Feature concept proposed by the authors, which are used as the basis for integrating machining, monitoring, and on-line inspection operations for optimized machining process control of high value complex parts. A prototype framework based on an open platform has been developed to enable the application of the proposed method. Industrial examples used to validate the prototype will be presented in this paper.
Keywords: Cutting tools; Dynamics; Inspection; Machine tools; Machining; Machining centers; Social networking (online); Software prototyping; Dynamic control systems; Integrated informations; Machine tool performance; Manufacturing companies; Numerical control machining; Workpiece deformation; Process control

A review of studies on strongly-coupled coulomb systems since the rise of DFT and SCCS-1977 - Dharma-Wardana, M. W. C. (Contributions to Plasma Physics, 2015)
The conferences on "Strongly Coupled Coulomb Systems" (SCCS) arose from the "Strongly Coupled Plas-mas" meetings, inaugurated in 1977. The progress in SCCS theory is reviewed in an 'author-centered' frame to limit its scope. Our efforts, i.e., with François Perrot, sought to apply density functional theory (DFT) to SCCS calculations. DFT was then poised to become the major computational scheme for condensed matter physics. The ion-sphere models of Salpeter and others evolved into useful average-atom models for finite-T Coulomb systems, as in Lieberman's Inferno code. We replaced these by correlation-sphere models that exploit the description of matter via density functionals linked to pair-distributions. These methods provided practical computational means for studying strongly interacting electron-ion Coulomb systems like warm-dense matter (WDM). The staples of SCCS are wide-ranged, viz., equation of state, plasma spectroscopy, opacity (absorption, emission), scattering, level shifts, transport properties, e.g., electrical and heat conductivity, laser- and shock-created plasmas, their energy relaxation and transient properties etc. These calculations need pseudopotentials and exchange-correlation functionals applicable to finite-T Coulomb systems that may be used in ab initio codes, molecular dynamics, etc. The search for simpler computational schemes has proceeded via proposals for orbital-free DFT, statistical potentials, classical maps of quantum systems using classical schemes like HNC to include strong coupling effects (CHNC). Laughlin's classical plasma map for the fractional quantum Hall effect (FQHE) is a seminal example where we report new results for graphene.

Electroactive and photoactive poly[isoindigo-alt-EDOT] synthesized using direct (hetero)arylation polymerization in batch and in continuous flow - Grenier, François; Aïch, Badrou R.; Lai, Yu-Ying; Guérette, Maxime; Holmes, Andrew B.; Tao, Ye; Wong, Wallace W. H.; Leclerc, Mario (Chemistry of Materials, 2015)
In this work, a combined approach was used to obtain a low-cost material for organic electronics by focusing on inexpensive monomers, short synthetic pathway, high-yielding polymerization method, low waste, and easy scalability. To achieve this, a new material, poly[isoindigo-alt-3,4-ethylenedioxythiophene], was synthesized using direct (hetero)arylation polymerization (DHAP). Only a few synthetic steps are required to obtain this material, and no organometallic intermediates are used. In order to make a bigger step toward a truly inexpensive technology, continuous flow methods were applied for the first time to DHAP. This method helped solving a common problem encountered in conjugated polymers synthesis, namely, batch-to-batch variations. Electronic properties of this polymeric material were evaluated using field effect transistors (μh = 7 × 10-3 cm2·V-1·s-1) and solar cells (η = 3.0%).
Keywords: Aromatic compounds; Chemical reactions; Conjugated polymers; Electronic properties; Organometallics; Polymerization; Solar cells; Batch-to-batch variations; Continuous flow methods; Continuous flows; Electro actives; Organic electronics; Organometallic intermediates; Polymerization method; Synthetic pathways; Field effect transistors

Oscillatory motion in layered materials: Graphene, boron nitride, and molybdenum disulfide - Ye, Zhijiang; Otero-De-La-Roza, Alberto; Johnson, Erin R.; Martini, Erin (Nanotechnology, 2015)
Offset-driven self-retraction and oscillatory motion of bilayer graphene has been observed experimentally and is potentially relevant for nanoscale technological applications. In a previous article, we showed that friction between laterally offset graphene layers is controlled by roughness and proposed a simple reduced-order model based on density-functional theory (DFT) and molecular dynamics (MD) data, with which predictions on the experimental size-scale could be made. In this article, we extend our study to other layered materials, with emphasis on boron nitride (BN) and molybdenum disulfide (MoS2). Using MD and DFT simulations of these systems and a generalized version of the reduced-order model, we predict that BN will exhibit behavior similar to graphene (heavily-damped oscillation with a decay rate that increases with roughness) and that MoS2 shows no oscillatory behavior even in the absence of roughness. This is attributed to the higher energy barrier for sliding in MoS2 as well as the surface structure. Our generalized reduced-order model provides a guide to predicting and tuning experimental oscillation behavior using a few parameters that can be derived from simulation data.
Keywords: Boron nitride; Data reduction; Decay (organic); Graphene; Molecular dynamics; Molybdenum; Molybdenum compounds; Nitrides; Sulfur compounds; grapheme; Higher-energy barriers; Molybdenum disulfide; Oscillation behavior; Oscillatory motion; Reduced order models; Technological applications; Density functional theory

In situ neutron diffraction analysis of stress-free d-spacing during solution heat treatment of modified 319 Al alloy engine blocks - Lombardi, A.; Sediako, D.; Ravindran, C.; MacKay, R. (Canadian Metallurgical Quarterly, 2015)
Aluminium alloy engine blocks have successfully replaced ferrous materials in order to maximise weight savings and improve vehicle fuel efficiency. However, the development of an optimal heat treatment process is required to improve engine block casting integrity and prevent potential problems such as in-service cylinder distortion. Optimisation of heat treatment parameters requires an in-depth study to determine how residual stresses are relieved with time during solution heat treatment. In order to perform this analysis, however, in situ neutron diffraction must first be carried out on stress-free samples of the same composition and processing history as the engine blocks to account for factors such as thermal expansion and changes in lattice parameter due to dissolution of secondary phases. The results from this study suggest that thermal expansion caused the largest change in d0 spacing, while prolonged exposure at the solutionising temperature resulted in relatively small changes in {311} and {331} d0 spacing due to phase dissolution.
Keywords: Aluminum; Aluminum alloys; Dissolution; Engine cylinders; Engines; Fuels; Heat treatment; Neutron diffraction; Neutrons; Thermal expansion; Engine blocks; Heat treatment parameters; Heat treatment process; In-situ neutron diffraction; Processing history; Solution heat treatment; Vehicle fuel efficiencies; In situ processing

The chromatin regulator Brpf1 regulates embryo development and cell proliferation - You, Linya; Yan, Kezhi; Zou, Jinfeng; Zhao, Hong; Bertos, Nicholas R.; Park, Morag; Wang, Edwin; Yang, Xiang-Jiao (Journal of Biological Chemistry, 2015)
With hundreds of chromatin regulators identified in mammals, an emerging issue is how they modulate biological and pathological processes. BRPF1 (bromodomain-and PHD finger-containing protein 1) is a unique chromatin regulator possessing two PHD fingers, one bromodomain and a PWWP domain for recognizing multiple histone modifications. In addition, it binds to the acetyltransferases MOZ, MORF, and HBO1 (also known as KAT6A, KAT6B, and KAT7, respectively) to promote complex formation, restrict substrate specificity, and enhance enzymatic activity.Wehave recently showed that ablation of the mouse Brpf1 gene causes embryonic lethality at E9.5. Here we present systematic analyses of the mutant animals and demonstrate that the ablation leads to vascular defects in the placenta, yolk sac, and embryo proper, as well as abnormal neural tube closure. At the cellular level, Brpf1 loss inhibits proliferation of embryonic fibroblasts and hematopoietic progenitors. Molecularly, the loss reduces transcription of a ribosomal protein L10 (Rpl10)-like gene and the cell cycle inhibitor p27, and increases expression of the cell-cycle inhibitor p16 and a novel protein homologous to Scp3, a synaptonemal complex protein critical for chromosome association and embryo survival. These results uncover a crucial role of Brpf1 in controlling mouse embryo development and regulating cellular and gene expression programs.
Keywords: Ablation; Cell culture; Cell proliferation; Chromosomes; Gene expression; Mammals; Mobile security; Proteins; Transcription; Complex formations; Embryonic fibroblasts; Embryonic lethality; Histone modification; Pathological process; Ribosomal proteins; Substrate specificity; Systematic analysis; bromodomain and PHD finger containing protein 1; genomic DNA; membrane protein; nuclear protein; protein p16; protein p27; protein Scp3; regulator protein; animal cell; animal tissue; cell proliferation; controlled study; embryo; embryo cell; embryo development; embryonic fibroblast; embryopathy; fibroblast; gene; gene expression regulation; growth inhibition; hematopoietic stem cell; immunohistochemistry; mouse; mouse mutant; neural tube defect; nonhuman; placenta disorder; protein analysis; protein depletion; protein expression; protein function; ribosomal protein L10 like gene; survival rate; transcription regulation; yolk sac

Finite element based tracking of deforming surfaces - Wuhrer, Stefanie; Lang, Jochen; Tekieh, Motahareh; Shu, Chang (Graphical Models, 2015)
We present an approach to robustly track the geometry of an object that deforms over time from a set of input point clouds captured from a single viewpoint. The deformations we consider are caused by applying forces to known locations on the object's surface. Our method combines the use of prior information on the geometry of the object modeled by a smooth template and the use of a linear finite element method to predict the deformation. This allows the accurate reconstruction of both the observed and the unobserved sides of the object. We present tracking results for noisy low-quality point clouds acquired by either a stereo camera or a depth camera, and simulations with point clouds corrupted by different error terms. We show that our method is also applicable to large non-linear deformations.
Keywords: Cameras; Deformation; Geometry; Stereo image processing; Depth camera; Geometry processing; Linear finite elements; Low qualities; Nonlinear deformations; Prior information; Stereo cameras; Surface tracking; Finite element method; deformation; finite element method; geometry; linear programing; nonlinearity; simulation; surface

Toxic cyanobacterial bloom triggers in missisquoi bay, lake champlain, as determined by next-generation sequencing and quantitative PCR - Fortin, Nathalie; Munoz-Ramos, Valentina; Bird, David; Lévesque, Benoît; Whyte, Lyle G.; Greer, Charles W. (Life, 2015)
Missisquoi Bay (MB) is a temperate eutrophic freshwater lake that frequently experiences toxic Microcystis-dominated cyanobacterial blooms. Non-point sources are responsible for the high concentrations of phosphorus and nitrogen in the bay. This study combined data from environmental parameters, E. coli counts, high-throughput sequencing of 16S rRNA gene amplicons, quantitative PCR (16S rRNA and mcyD genes) and toxin analyses to identify the main bloom-promoting factors. In 2009, nutrient concentrations correlated with E. coli counts, abundance of total cyanobacterial cells, Microcystis 16S rRNA and mcyD genes and intracellular microcystin. Total and dissolved phosphorus also correlated significantly with rainfall. The major cyanobacterial taxa were members of the orders Chroococcales and Nostocales. The genus Microcystis was the main mcyD-carrier and main microcystin producer. Our results suggested that increasing nutrient concentrations and total nitrogen:total phosphorus (TN:TP) ratios approaching 11:1, coupled with an increase in temperature, promoted Microcystis-dominated toxic blooms. Although the importance of nutrient ratios and absolute concentrations on cyanobacterial and Microcystis dynamics have been documented in other laboratories, an optimum TN:TP ratio for Microcystis dominance has not been previously observed in situ. This observation provides further support that nutrient ratios are an important determinant of species composition in natural phytoplankton assemblages.
Keywords: Chroococcales; Cyanobacteria; Microcystis; Nostocales

Multiview self-learning - Fakeri-Tabrizi, Ali; Amini, Massih-Reza; Goutte, Cyril; Usunier, Nicolas (Neurocomputing, 2015)
In many applications, observations are available with different views. This is, for example, the case with image-text classification, multilingual document classification or document classification on the web. In addition, unlabeled multiview examples can be easily acquired, but assigning labels to these examples is usually a time consuming task. We describe a multiview self-learning strategy which trains different voting classifiers on different views. The margin distributions over the unlabeled training data, obtained with each view-specific classifier are then used to estimate an upper-bound on their transductive Bayes error. Minimizing this upper-bound provides an automatic margin-threshold which is used to assign pseudo-labels to unlabeled examples. Final class labels are then assigned to these examples, by taking a vote on the pool of the previous pseudo-labels. New view-specific classifiers are then trained using the labeled and pseudo-labeled training data. We consider applications to image-text classification and to multilingual document classification. We present experimental results on the NUS-WIDE collection and on Reuters RCV1-RCV2 which show that despite its simplicity, our approach is competitive with other state-of-the-art techniques.
Keywords: Classification (of information); Information retrieval systems; Text processing; Document Classification; Image annotation; Labeled training data; Margin distributions; Multi-view learning; Multilingual documents; Self-learning; State-of-the-art techniques; Image classification; algorithm; Bayes theorem; classification; classifier; image processing; intermethod comparison; machine learning; multiview self learning

Traceability of loss measurements of extra high voltage three-phase shunt reactors - So, Eddy; Verhoeven, Rob; Dorpmanns, Luc; Angelo, Dave (IEEE Transactions on Instrumentation and Measurement, 2015)
An overview of traceability issues of loss measurements of extra high voltage three-phase shunt reactors is presented. Loss measurements of a 345-kV-55-MVAr three-phase shunt reactor at Royal SMIT Transformers, including their uncertainties, are presented and discussed. The measurement results are confirmed with those obtained using a special high-voltage inductance bridge.
Keywords: Electric reactors; Extra high voltage; Measurement uncertainty; Shunt reactors; Three phase; traceability; Uncertainty analysis

Theory of biexcitons and biexciton-exciton cascade in graphene quantum dots - Ozfidan, Isil; Korkusinski, Marek; Hawrylak, Pawel (Physical Review B - Condensed Matter and Materials Physics, 2015)
We present a microscopic theory of biexcitons in colloidal graphene quantum dots, and we discuss the possibility of a biexciton-exciton cascade generation. Assuming a pz orbital on each carbon atom, the single-particle properties are described in the tight-binding model. The screened direct, exchange, and scattering matrix elements of the Coulomb matrix are calculated using Slater pz orbitals. The many-body ground and excited states are constructed as a linear combination of a finite number of electron-hole pair excitations from the Hartree-Fock ground state by exact diagonalization techniques. The exciton and biexciton states are constructed exploiting the degeneracy of the valence- and conduction-band edges. The two degenerate exciton (X) states and a corresponding biexciton (XX) state are identified for generation of the XX-X cascade in threefold-symmetric quantum dots. Finally, the Auger coupling of the XX state with the excited X states is predicted.

A review of radiation-grafted polymer electrolyte membranes for alkaline polymer electrolyte membrane fuel cells - Zhou, Tianchi; Shao, Rong; Chen, Song; He, Xuemei; Qiao, Jinli; Zhang, Jiujun (Journal of Power Sources, 2015)
The past two decades have witnessed many efforts to develop radiation-grafted alkaline membranes for alkaline PEM fuel cell applications, as such membranes have certain advantages over other kinds of alkaline membranes, including well-controlled composition, functionality, and other promising properties. To facilitate research and development in this area, the present paper reviews radiation-grafted alkaline membranes. We examine their synthesis/fabrication/characterization, membrane material selection, and theoretical approaches for fundamental understanding. We also present detailed examinations of their application in fuel cell in terms of the working principles of the radiation grafting process, the fabrication of MEAs using radiation-grafted membranes, the membranes' corresponding performance in alkaline PEM fuel cells, as well as performance optimization. The paper also summarizes the challenges and mitigation strategies for radiation-grafted alkaline membranes and their application in PEM fuel cells, presenting an overall picture of the technology as it presently stands.
Keywords: Alkaline fuel cells; Convergence of numerical methods; Copolymers; Electrolytes; Fuel cells; Gas fuel purification; Grafting (chemical); Ion exchange membranes; Membranes; Polyelectrolytes; Proton exchange membrane fuel cells (PEMFC); Radiation; Alkaline anion exchange membrane; Hydroxide conductivities; Membrane electrode assemblies; PEM fuel cell; Radiation grafting; Solid electrolytes

Doppler winds mapped around the lower thermospheric terminator of Venus: 2012 solar transit observations from the James Clerk Maxwell Telescope - Clancy, R. Todd; Sandor, Brad J.; Hoge, James (Icarus, 2015)
Doppler shifts of sub-millimeter (330. GHz) and millimeter (230. GHz) line absorptions were mapped around the circum-disk terminator of Venus before, during, and after the June 5, 2012 solar transit, employing the James Clerk Maxwell Telescope (JCMT). Radiative transfer analysis of the solar transit thermal line absorptions yields cross-terminator winds in the Venus lower thermosphere (100-120. km) over the local time (LT) and latitude extent of the atmospheric limb presented by the inferior conjunction, nightside apparent disk of Venus. The unique solar transit geometry provides enhanced spatial resolution of the terminator (0.2. h in local time, LT) associated with solar illumination of this atmospheric limb region, and so provides the first characterization of the instantaneous distribution of cross terminator flow in the Venus lower thermosphere versus LT and latitude. Furthermore, by mapping Doppler winds over the nightside disk preceding and following the solar transit, we place the highly variable zonal and subsolar-to-antisolar (SSAS) circulation components of the nightside lower thermosphere (Clancy, R.T., Sandor, B.J., Moriarty-Schieven, G.H. [2012a]. Icarus 217, 794-812) in the context of the day-to-night cross terminator flow that drives this chaotic nightside dynamical regime. The solar transit observations indicate substantially supersonic (200-300. m/s) day-to-night cross terminator winds that are significantly (by 50-150. m/s) stronger over the evening versus the morning terminator. They also exhibit surprisingly large (50%) variations over a 1-2. h timescale that challenge explanation. These behaviors likely contribute to both the variability and the apparent retrograde zonal component of circulation in the Venus nightside upper atmosphere. Hence, these observations support dynamical arguments for preferential deceleration of the morning sector SSAS circulation (e.g., Alexander, M.J. [1992]. Geophys. Res. Lett. 19, 2207-2210), as recently simulated in the Venus thermospheric general circulation model of Hoshino et al. (Hoshinom, N. et al. [2013]. J. Geophys. Res. 118, 2004-2015).

Correction: Chigrinova, M., et al. Kinugasa reactions in water: From green chemistry to bioorthogonal labelling. Molecules 2015, 20, 6959-6969 - Chigrinova, Mariya; MacKenzie, Douglas A.; Sherratt, Allison R.; Cheung, Lawrence L. W.; Pezacki, John Paul (MDPI AG, 2015)

Synthesis and characterization of highly organized crystalline rutile nanoparticles by low-temperature dissolution-reprecipitation process - Karim, Mohammad Rezaul; Bhuiyan, Mohammad Tauhidul Islam; Dar, Mushtaq Ahmad; Seikh, Asiful Hossain; Shar, Muhammad Ali; Zaman, Mohammed Badruz; Lee, Chul Jae; Kim, Hee Jin; Lee, Mu Sang (Journal of Materials Research, 2015)
Rutile nanoparticles have been synthesized by acid hydrolysis of titanium isopropoxide by low-temperature dissolution-reprecipitation process. High-resolution transmission electron micrographs of the rutile colloidal solution show needle-shaped rutile nanoparticles with the dimensions of 10-30 nm in diameter and 100-150 nm in length. X-ray diffraction (XRD) data show the existence of only the rutile polymorph in TiO2 powder with a crystallite size of 11.3 nm. The dielectric constant of rutile nanoparticles has been found to be 57 at 10 MHz AC frequency and DC conductance as 2.3 × 10-6 S/cm. Transmission electron micrographs and XRD data analysis imply that the rutile crystallites are self-organized in a regular fashion to produce multilayer three-dimensional linear clusters. The clusters have been found to be microporous (average porosity 1.4 nm) with high specific surface area (132.2 m2/g). At higher concentration, the clusters aggregate to produce interconnected network of star- or flower-like structures. This organized crystalline microporous metal-oxide semiconductor might find various practical applications.
Keywords: Crystalline materials; Crystallite size; Dielectric properties; Dissolution; Metals; Microporosity; MOS devices; Nanoparticles; Nanostructures; Semiconductor materials; Synthesis (chemical); X ray diffraction; Dissolution-reprecipitation; Flower-like structures; High specific surface area; Interconnected network; Metal oxide semiconductor; Rutile TiO; Synthesis and characterizations; Transmission electron micrograph; Oxide minerals

Calibrations of resistance welding equipment with high pulsed currents - Djokić, Branislav (IEEE Transactions on Instrumentation and Measurement, 2015)
Rogowski coils are widely used as high pulsed current sensors in resistance welding applications. The operating conditions of the coils determine the requirements for their calibration. A new calibration system has been developed at National Research Council (NRC) Canada for calibrating current sensing coils and weld current monitors (WCMs) used in AC resistance welding. The calibration system, which includes a high-current source and a coaxial copper cage, has been evaluated at peak pulsed currents of up to 80 kA at 60 Hz. The expanded measurement uncertainties (k = 2) have been estimated to be less than 350 μA/A for magnitude. A method for the calibration of WCMs separately from their Rogowski coils at conditions that correspond to those obtained at high pulsed currents but without the need to use actual high pulsed currents has also been developed.
Keywords: Calibration; Electric current control; Uncertainty analysis; Welding; Welds; AC measurements; Digital sampling; Measurement uncertainty; Pulsed currents; Rogowski Coil; Weld current; Resistance welding

First-principles molecular simulations of Li diffusion in solid electrolytes Li3PS4 - Yang, Jianjun; Tse, John S. (Computational Materials Science, 2015)
Recently it was found that nanoporous β-Li3PS4 (Liu et al., 2013), has an ionic conductivity three orders of magnitude higher than the two known crystalline phases. The exciting discovery has raised the optimism that this material may be a suitable candidate as solid state electrolyte. Here the lithium transport mechanisms in nanoporous and the crystalline phases were investigated with first-principles molecular dynamics calculations. The theoretical results reproduced the experimental trend. In all three systems the lithium migrations are found to be the similar through site-to-site hopping rather than free diffusion. The presence of vacant Li sites combined with the large surface area may be one of the reasons for the fast ionic conductivity in the nanoporous phase.
Keywords: Calculations; Crystalline materials; Diffusion; Electrolytes; Ionic conductivity; Lithium; Molecular dynamics; Potentiometric sensors; Crystalline phasis; First principles; First principles molecular dynamics; Large surface area; Molecular simulations; Site-to-site hopping; Solid-state electrolyte; Three orders of magnitude; Solid electrolytes

Facilitating guest transport in clathrate hydrates by tuning guest-host interactions - Moudrakovski, Igor L.; Udachin, Konstantin A.; Alavi, Saman; Ratcliffe, Christopher I.; Ripmeester, John A. (Journal of Chemical Physics, 2015)
The understanding and eventual control of guest molecule transport in gas hydrates is of central importance for the efficient synthesis and processing of these materials for applications in the storage, separation, and sequestration of gases and natural gas production. Previously, some links have been established between dynamics of the host water molecules and guest-host hydrogen bonding interactions, but direct observation of transport in the form of cage-to-cage guest diffusion is still lacking. Recent calculations have suggested that pairs of different guest molecules in neighboring cages can affect guest-host hydrogen bonding and, therefore, defect injection and water lattice motions. We have chosen two sets of hydrate guest pairs, tetrahydrofuran (THF)-CO2 and isobutane-CO2, that are predicted to enhance or to diminish guest-host hydrogen bonding interactions as compared to those in pure CO2 hydrate and we have studied guest dynamics in each using 13C nuclear magnetic resonance (NMR) methods. In addition, we have obtained the crystal structure of the THF-CO2 sII hydrate using the combined single crystal X-ray diffraction and 13C NMR powder pattern data and have performed molecular dynamics-simulation of the CO2 dynamics. The NMR powder line shape studies confirm the enhanced and delayed dynamics for the THF and isobutane containing hydrates, respectively, as compared to those in the CO2 hydrate. In addition, from line shape studies and 2D exchange spectroscopy NMR, we observe cage-to-cage exchange of CO2 molecules in the THF-CO2 hydrate, but not in the other hydrates studied. We conclude that the relatively rapid intercage guest dynamics are the result of synergistic guest A-host water-guest B interactions, thus allowing tuning of the guest transport properties in the hydrates by choice of the appropriate guest molecules. Our experimental value for inter-cage hopping is slower by a factor of 106 than a published calculated value.
Keywords: Bonding; Crystal structure; Digital storage; Gas hydrates; Hydration; Hydrogen bonds; Molecular dynamics; Molecules; Natural gas; Natural gas well production; Nuclear magnetic resonance; Nuclear magnetic resonance spectroscopy; Organic solvents; Single crystals; Synthesis (chemical); Water injection; X ray diffraction; 2D exchange spectroscopy; Direct observations; Guest-host interactions; Hydrogen bonding interactions; Molecular dynamics simulations; Natural-gas production; Nuclear magnetic resonance(NMR); Single crystal x-ray diffraction; Carbon dioxide

Alcohol-soluble, sulfonated poly(arylene ether)s: Investigation of hydrocarbon ionomers for proton exchange membrane fuel cell catalyst layers - Strong, Aaron; Britton, Benjamin; Edwards, Dave; Peckham, Timothy J.; Lee, Hsu-Feng; Huang, Wen Y.; Holdcroft, Steven (Journal of the Electrochemical Society, 2015)
Novel sulfonated poly(arylene ether)s, characterized as being highly sterically encumbered, were synthesized for investigation as the ionomer in proton exchange membrane fuel cell (PEMFC) catalyst layers. Catalyst-coated membranes were prepared via their incorporation into alcohol-based catalyst inks, devoid of the high-boiling, polar aprotic solvents typically required for hydrocarbon-based ionomer inks. Catalyst layers thicknesses increased from 8.5 to 9.1 μm when the hydrocarbon ionomer loading was increased from 20 to 40 wt%, but resulted in a 77% loss in pore volume for fully hydrated electrodes. The catalyst layers possessed similar electrochemical surface areas and net ionic conductivity, yet catalyst layers containing 20 wt% ionomer yielded the highest overall fuel cell performance and considerably outperformed catalyst layers prepared from inks that contained high-boiling solvents.
Keywords: Catalysts; Ethers; Fuel cells; Hydrocarbons; Ionomers; Alcohol soluble; Catalyst coated membranes; Electrochemical surface area; Fuel cell performance; High boiling solvents; Hydrocarbon ionomers; Polar aprotic solvent; Polyarylene ethers; Proton exchange membrane fuel cells (PEMFC)

Roles of reactive oxygen species-degrading enzymes of Francisella tularensis SCHU S4 - Binesse, Johan; Lindgren, Helena; Lindgren, Lena; Conlan, Wayne; Sjöstedt, Anders (Infection and Immunity, 2015)
Francisella tularensis is a facultative intracellular bacterium utilizing macrophages as its primary intracellular habitat and is therefore highly capable of resisting the effects of reactive oxygen species (ROS), potent mediators of the bactericidal activity of macrophages. We investigated the roles of enzymes presumed to be important for protection against ROS. Four mutants of the highly virulent SCHU S4 strain with deletions of the genes encoding catalase (katG), glutathione peroxidase (gpx), a DyP-type peroxidase (FTT0086), or double deletion of FTT0086 and katG showed much increased susceptibility to hydrogen peroxide (H2O2) and slightly increased susceptibility to paraquat but not to peroxynitrite (ONOO-) and displayed intact intramacrophage replication. Nevertheless, mice infected with the double deletion mutant showed significantly longer survival than SCHU S4-infected mice. Unlike the aforementioned mutants, deletion of the gene coding for alkyl-hydroperoxide reductase subunit C (ahpC) generated a mutant much more susceptible to paraquat and ONOO- but not to H2O2. It showed intact replication in J774 cells but impaired replication in bone marrow-derived macrophages and in internal organs of mice. The live vaccine strain, LVS, is more susceptible than virulent strains to ROS-mediated killing and possesses a truncated form of FTT0086. Expression of the SCHU S4 FTT0086 gene rendered LVS more resistant to H2O2, which demonstrates that the SCHU S4 strain possesses additional detoxifying mechanisms. Collectively, the results demonstrate that SCHU S4 ROS-detoxifying enzymes have overlapping functions, and therefore, deletion of one or the other does not critically impair the intracellular replication or virulence, although AhpC appears to have a unique function.
Keywords: alkyl hydroperoxide reductase subunit c; bacterial enzyme; catalase; glutathione peroxidase; hydrogen peroxide; live vaccine; paraquat; peroxidase; peroxynitrite; reactive oxygen metabolite; animal cell; animal experiment; animal model; bacterial gene; bacterial strain; bacterial survival; bacterial viability; bacterial virulence; bacterium identification; bacterium mutant; bone marrow derived macrophage; cell division; colony forming unit; detoxification; Francisella tularensis; gene deletion; macrophage; protein expression; protein function; tularemia

Accurate determination of Sr isotopic compositions in clinopyroxene and silicate glasses by LA-MC-ICP-MS - Tong, Xirun; Liu, Yongsheng; Hu, Zhaochu; Chen, Haihong; Zhou, Lian; Hu, Qinghai; Xu, Rong; Deng, Lixu; Chen, Chunfei; Yang, Lu; Gao, Shan (Geostandards and Geoanalytical Research, 2015)
The low-Sr content (generally < 100 μg g-1) in clinopyroxene from peridotite makes accurate Sr isotopic determination by LA-MC-ICP-MS a challenge. The effects of adding N2 to the sample gas and using a guard electrode (GE) on instrumental sensitivity for Sr isotopic determination by LA-MC-ICP-MS were investigated. Results revealed no significant sensitivity enhancement of Sr by adding N2 to the ICP. Although using a GE led to a two-fold sensitivity enhancement, it significantly increased the yield of polyatomic ion interferences of Ca-related ions and TiAr+ on Sr isotopes. Applying the method established in this work, 87Sr/86Sr ratios (Rb/Sr < 0.14) of natural clinopyroxene from mantle and silicate glasses were accurately measured with similar measurement repeatability (0.0009-0.00006, 2SE) to previous studies but using a smaller spot size of 120 μm and low-to-moderate Sr content (30-518 μg g-1). The measurement reproducibility was 0.0004 (2s, n = 33) for a sample with 100 μg g-1 Sr. Destruction of the crystal structure by sample fusion showed no effect on Sr isotopic determination. Synthesised glasses with major element compositions similar to natural clinopyroxene have the potential to be adopted as reference materials for Sr isotopic determination by LA-MC-ICP-MS.
Keywords: Crystal structure; Glass; Inductively coupled plasma mass spectrometry; Isotopes; Mass spectrometers; Silicates; Clinopyroxenes; Isobaric interferences; MC-ICP-MS; Silicate glass; Sr isotopes; Strontium

Evidence for (and against) progenitor bias in the size growth of compact red galaxies - Keating, Stephanie K.; Abraham, Roberto G.; Schiavon, Ricardo; Graves, Genevieve; Damjanov, Ivana; Yan, Renbin; Newman, Jeffrey; Simard, Luc (The Astrophysical Journal, 2015)
Most massive, passive galaxies are compact at high redshifts, but similarly compact massive galaxies are rare in the local universe. The most common interpretation of this phenomenon is that massive galaxies have grown in size by a factor of about five since redshift z = 2. An alternative explanation is that recently quenched massive galaxies are larger (a "progenitor bias"). In this paper, we explore the importance of progenitor bias by looking for systematic differences in the stellar populations of compact early-type galaxies in the DEEP2 survey as a function of size. Our analysis is based on applying the statistical technique of bootstrap resampling to constrain differences in the median ages of our samples and to begin to characterize the distribution of stellar populations in our co-added spectra. The light-weighted ages of compact early-type galaxies at redshifts 0.5 < z < 1.4 are compared to those of a control sample of larger galaxies at similar redshifts.We find that massive compact early-type galaxies selected on the basis of red color and high bulge-to-total ratio are younger than similarly selected larger galaxies, suggesting that size growth in these objects is not driven mainly by progenitor bias, and that individual galaxies grow as their stellar populations age. However, compact early-type galaxies selected on the basis of image smoothness and high bulge-to-total ratio are older than a control sample of larger galaxies. Progenitor bias will play a significant role in defining the apparent size changes of early-type galaxies if they are selected on the basis of the smoothness of their light distributions.

Feasibility study on production of a matrix reference material for cyanobacterial toxins - Hollingdale, Christie; Thomas, Krista; Lewis, Nancy; Békri, Khalida; McCarron, Pearse; Quilliam, Michael A. (Analytical and Bioanalytical Chemistry, 2015)
The worldwide increase in cyanobacterial contamination of freshwater lakes and rivers is of great concern as many cyanobacteria produce potent hepatotoxins and neurotoxins (cyanotoxins). Such toxins pose a threat to aquatic ecosystems, livestock, and drinking water supplies. In addition, dietary supplements prepared from cyanobacteria can pose a risk to consumers if they contain toxins. Analytical monitoring for toxins in the environment and in consumer products is essential for the protection of public health. Reference materials (RMs) are an essential tool for the development and validation of analytical methods and are necessary for ongoing quality control of monitoring operations. Since the availability of appropriate RMs for cyanotoxins has been very limited, the present study was undertaken to examine the feasibility of producing a cyanobacterial matrix RM containing various cyanotoxins. The first step was large-scale culturing of various cyanobacterial cultures that produce anatoxins, microcystins, and cylindrospermopsins. After harvesting, the biomass was lyophilized, blended, homogenized, milled, and bottled. The moisture content and physical characteristics were assessed in order to evaluate the effectiveness of the production process. Toxin levels were measured by liquid chromatography with tandem mass spectrometry and ultraviolet detection. The reference material was found to be homogeneous for toxin content. Stability studies showed no significant degradation of target toxins over a period of 310 days at temperatures up to +40 °C except for the anatoxin-a, which showed some degradation at +40 °C. These results show that a fit-for-purpose matrix RM for cyanotoxins can be prepared using the processes and techniques applied in this work.
Keywords: Agriculture; Aquatic ecosystems; Consumer products; Consumer protection; Dietary supplements; Liquid chromatography; Mass spectrometry; Metabolites; Potable water; Public health; Quality control; Water supply; Anatoxins; Cyanobacteria; Cylindrospermopsins; Microcystins; Reference material; Toxic materials

Study of processing conditions on the forming of ribbed features using randomly oriented strands thermoplastic composites - LeBlanc, D.; Landry, B.; Levy, A.; Hubert, P.; Roy, S.; Yousefpour, A.; Quinlan, E. (Journal of the American Helicopter Society, 2015)
Compression molding of randomly oriented strands (ROS) composites offers the possibility to manufacture complex parts with a fast processing cycle. In this paper, effects of pressure, strand size, temperature, and material placement in the mold cavity on the quality of a T-shape part were studied experimentally with carbon/polyether ether ketone ROS composites. Minimum filling pressure was obtained for the consolidation of a 25-mm deep cavity. Parts processed at filling pressure showed a void content no greater than 1.2%. Increasing pressure to 70 bar resulted in decreased void content as low as 0.03%. Mechanical testing of the T-shape showed similar strengths for parts processed at filling pressure and higher (70 bar). At the component level, initial strand placement greatly affected mechanical performance as the presence of a knit line was responsible for a reduction of 60% in tensile strength. The main findings show that processing a complex feature at filling pressure Pfill was sufficient to reach nominal mechanical properties. This suggested that moderate porosity was not detrimental to the mechanical performance for the given tests where fatigue performance was not evaluated. © 2015 The American Helicopter Society.
Keywords: Compression molding; Filling; Ketones; Mechanical properties; Mechanical testing; Molds; Tensile strength; Complex parts; Component levels; Fast Processing; Fatigue performance; Filling pressures; Mechanical performance; Processing condition; Thermoplastic composite; Processing

Neutron diffraction investigation of phase compositions in as received and modified Zr-2·5Nb pressure tube materials - Fluke, A.I.; Fong, R.W.L.; Flacau, R. (Canadian Metallurgical Quarterly, 2015)
Zr-2·5Nb alloy is used for the pressure tubes in CANDU [CANDU® (CANada Deuterium Uranium) is a registered trademark of Atomic Energy of Canada Limited.] reactor fuel channels. Three phases (α, β and ω) of zirconium are known to exist in Zr-2·5Nb alloy pressure tube materials. An as received pressure tube is composed mainly of a phase and approximately 8% b phase material. In the last step of production, the pressure tube is given a steam autoclave treatment (i.e. thermal aging at 400°C for 24 h). This treatment results in decomposing the b phase into an Nb enriched b phase and a metastable v phase material. In the present experiment, as received pressure tube materials were modified by high temperature annealing and thermal aging treatments. This paper presents a neutron diffraction investigation into the phase compositions in the modified materials at room temperature using the C-2 high resolution neutron powder diffractometer at the Canadian Neutron Beam Centre. © 2015 Canadian Institute of Mining, Metallurgy and Petroleum Published by Maney on behalf of the Institute.
Keywords: Diffractometers; Neutron diffraction; Neutrons; Nuclear fuels; Phase composition; Thermal aging; Tubes (components); Zirconium; Atomic energy of canada limiteds; High-temperature annealing; Modified materials; Neutron powder diffractometer; Pressure tubes; Room temperature; Steam autoclave treatments; Thermal aging treatments; Pressure tube reactors

A receptor-binding protein of Campylobacter jejuni bacteriophage NCTC 12673 recognizes flagellin glycosylated with acetamidino-modified pseudaminic acid - Javed, Muhammad Afzal; van Alphen, Lieke B.; Sacher, Jessica; Ding, Wen; Kelly, John; Nargang, Cheryl; Smith, David F.; Cummings, Richard D.; Szymanski, Christine M. (Molecular Microbiology, 2015)
Bacteriophage receptor-binding proteins (RBPs) confer host specificity. We previously identified a putative RBP (Gp047) from the campylobacter lytic phage NCTC 12673 and demonstrated that Gp047 has a broader host range than its parent phage. While NCTC 12673 recognizes the capsular polysaccharide (CPS) of a limited number of Campylobacter jejuni isolates, Gp047 binds to a majority of C.jejuni and related Campylobacter coli strains. In this study, we demonstrate that Gp047 also binds to acapsular mutants, suggesting that unlike the parent phage, CPS is not the receptor for Gp047. Affinity chromatography and far-western analyses of C.jejuni lysates using Gp047 followed by mass spectrometry indicated that Gp047 binds to the major flagellin protein, FlaA. Because C.jejuni flagellin is extensively glycosylated, we investigated this binding specificity further and demonstrate that Gp047 only recognizes flagellin decorated with acetamidino-modified pseudaminic acid. This binding activity is localized to the C-terminal quarter of the protein and both wild-type and coccoid forms of C.jejuni are recognized. In addition, Gp047 treatment agglutinates vegetative cells and reduces their motility. Because Gp047 is highly conserved among all campylobacter phages sequenced to date, it is likely that this protein plays an important role in the phage life cycle.
Keywords: Campylobacter; Campylobacter coli; Campylobacter jejuni; Coccoidea

Deficiency of the chromatin regulator Brpf1 causes abnormal brain development - You, Linya; Zou, Jinfeng; Zhao, Hong; Bertos, Nicholas R.; Park, Morag; Wang, Edwin; Yang, Xiang-Jiao (Journal of Biological Chemistry, 2015)
Epigenetic mechanisms are important in different neurological disorders, and one such mechanism is histone acetylation. The multivalent chromatin regulator BRPF1 (bromodomainand plant homeodomain-linked (PHD) zinc finger-containing protein 1) recognizes different epigenetic marks and activates three histone acetyltransferases, so it is both a reader and a co-writer of the epigenetic language. The three histone acetyltransferases are MOZ, MORF, and HBO1, which are also known as lysine acetyltransferase 6A (KAT6A), KAT6B, and KAT7, respectively. The MORF gene is mutated in four neurodevelopmental disorders sharing the characteristic of intellectual disability and frequently displaying callosal agenesis. Here, we report that forebrain-specific inactivation of the mouse Brpf1 gene caused early postnatal lethality, neocortical abnormalities, and partial callosal agenesis. With respect to the control, the mutant forebrain contained fewer Tbr2-positive intermediate neuronal progenitors and displayed aberrant neurogenesis. Molecularly, Brpf1 loss led to decreased transcription of multiple genes, such as Robo3 and Otx1, important for neocortical development. Surprisingly, elevated expression of different Hox genes and various other transcription factors, such as Lhx4, Foxa1, Tbx5, and Twist1, was also observed. These results thus identify an important role of Brpf1 in regulating forebrain development and suggest that it acts as both an activator and a silencer of gene expression in vivo.
Keywords: Acetylation; Amino acids; Chromosomes; Gene expression; Transcription; Acetyl transferase; Epigenetic mechanisms; Histone acetylation; Histone acetyltransferases; Intellectual disability; Multiple genes; Neurological disorders; Gene expression regulation; chromatin regulator BRPF1; HBO1 protein; histone acetyltransferase; homeodomain protein; lysine acetyltransferase 6A; lysine acetyltransferase 6B; lysine acetyltransferase 7; MORF protein; MOZ protein; protein; transcription factor; transcription factor Foxa1; transcription factor Lhx4; transcription factor TBX5; transcription factor Twist1; zinc finger protein; agenesis; animal experiment; brain cortex; brain development; brain malformation; controlled study; corpus callosum; corpus callosum agenesis; epigenetics; forebrain; forebrain development; gene; gene expression; gene mutation; genetic transcription; histone acetylation; Hox gene; in vivo study; intellectual impairment; mouse; nervous system development; neurologic disease; Otx1 gene; Robo3 gene

Quantitative analysis of TAG in oils using lithium cationization and direct-infusion ESI tandem mass spectrometry - Ramaley, Louis; Herrera, Lisandra Cubero; Melanson, Jeremy E. (JAOCS, Journal of the American Oil Chemists' Society, 2015)
This study was undertaken to determine whether triple-stage mass spectrometry (MS3) could be employed to obtain quantitative and regioisomeric data from complex oil samples without the need for a chromatographic step in the analysis protocol. Lithium-7 trifluoroacetate and electrospray ionization were used to form lithium adducts of the triacylglycerols (TAG) in a fish oil sample. The first-generation precursor ion was the lithium-TAG adduct, the second-generation precursor ion was formed by loss of a neutral acid side chain in the first fragmentation. The ions used for analysis were formed in the second fragmentation by loss of the lactones of the acid side chains remaining after the first fragmentation. This analysis scheme provided quantitative and regioisomeric data without interference from TAG in the sample other than TAG with the same acyl carbon number, one more double bond, and two acyl side chains in common with the analyte. Even in this case a majority of the interferences could be estimated and compensated. Analysis of synthetic samples containing the fish oil matrix indicated that both absolute and relative quantitative data could be obtained with average errors of approximately 5 %. The method proved well suited to routine analyses of complex oil samples.
Keywords: Chains; Electrospray ionization; Fish; Glycerol; Ions; Lithium; Mass spectrometry; Oil wells; Spectrometry; Direct infusions; ESI tandem mass spectrometry; Oil analysis; Quantitative data; Tandem mass spectrometry; Triacylglycerols; Triple stage mass spectrometry; Oil shale

Reaction pathways for pyridine adsorption on silicon (0 0 1) - Bennett, J. M.; Marks, N. A.; Miwa, J. A.; Lopinski, G. P.; Rosei, F.; McKenzie, D. R.; Warschkow, O. (Journal of Physics Condensed Matter, 2015)
Density functional theory is used to describe the reactions of chemisorption of pyridine on the silicon (0 0 1) surface. Adsorption energies of six relevant structures, and the activation energies between them are reported. We consider in detail the dative to tight-bridge transition for which conflicting results have been reported in the literature, and provide a description of the formation of inter-row chains observed in high-coverage experiments. We demonstrate that the choice of DFT functional has a considerable effect on the relative energetics and of the four DFT functionals considered, we find that the range-separated hybrid ωB97X-D functional with empirical dispersion provides the most consistent description of the experiment data.
Keywords: Activation energy; Adsorption; Pyridine; Silicon; Adsorption energies; Functionals; Pyridine adsorption; Reaction pathways; Si(0 0 1); Density functional theory

Corrosion of copper in distilled water without O2 and the detection of produced hydrogen - Hultquist, G.; Graham, M. J.; Kodra, O.; Moisa, S.; Liu, R.; Bexell, U.; Smialek, J. L. (Corrosion Science, 2015)
This paper reports on hydrogen pressures measured during ~19,000. h immersion of copper in oxygen-free liquid distilled water. Copper corrosion products have been examined ex-situ by SEM and characterized by XPS and SIMS. XPS strongly indicates a corrosion product containing both oxygen and hydrogen. SIMS shows that oxygen is mainly present in the outer 0.3. μm surface region and that hydrogen penetrates to depths well below the corrosion product. Thermal desorption spectroscopy shows that the reaction product formed near room-temperature is less stable than that formed in air at 350. °C.
Keywords: Copper; Copper corrosion; Corrosion; Oxygen; Thermal desorption spectroscopy; X ray photoelectron spectroscopy; B. AES; Corrosion products; Distilled water; Ex situ; Hydrogen absorption; Hydrogen pressures; Near room temperature; Surface region; Hydrogen

Effect of autoclave process on the quality of thermoplastic composite truncated cones manufactured using automated fiber placement technique - Shadmehri, Farjad; Cai, Xiao; Hojjati, Mehdi; Chen, Jihua; Hoa, Suong V. (Science and Engineering of Composite Materials, 2015)
In order to investigate the effect of autoclave process on the stiffness properties of thermoplastic composite truncated cones made by automated fiber placement technique (AFP), two short truncated cones were made out of advanced thermoplastic composite material (carbon fiber/PEEK). Then, the truncated cones were tested by impulse excitation of vibration to get experimental natural frequencies. Tensile and compression test coupons were made out of the same material using hand layup and autoclave process, and stiffness properties were characterized experimentally. Furthermore, finite element analysis was performed to extract theoretical natural frequencies using material properties obtained from coupon testing. Comparison between the natural frequencies obtained using the finite element method and experimental modal analysis was conducted. Furthermore, the two truncated cones were treated inside the autoclave, and changes in the thickness and density were measured. After autoclave treatment, experimental modal analysis was repeated to investigate the possible changes in natural frequencies. The finite element model was also updated upon the changes in thickness and density of the truncated cones, and consequently, comparison between the theoretical and experimental natural frequencies was carried out again. Also, micrographs of two truncated cones were taken before and after autoclave treatment to examine the autoclave effect on the quality of the samples.
Keywords: Automation; Carbon fibers; Composite materials; Compression testing; Fibers; Modal analysis; Natural frequencies; Plastics; Pressure vessels; Reinforced plastics; Stiffness; Thermoplastics; Autoclave process; Autoclave treatments; Experimental modal analysis; Fiber placement; Impulse excitations; Stiffness properties; Thermoplastic composite; Thermoplastic composite material; Finite element method

The lysine acetyltransferase activator Brpf1 governs dentate gyrus development through neural stem cells and progenitors - You, Linya; Yan, Kezhi; Zhou, Jinfeng; Zhao, Hong; Bertos, Nicholas R.; Park, Morag; Wang, Edwin; Yang, Xiang-Jiao (PLoS Genetics, 2015)
Lysine acetylation has recently emerged as an important post-translational modification in diverse organisms, but relatively little is known about its roles in mammalian development and stem cells. Bromodomain- and PHD finger-containing protein 1 (BRPF1) is a multidomain histone binder and a master activator of three lysine acetyltransferases, MOZ, MORF and HBO1, which are also known as KAT6A, KAT6B and KAT7, respectively. While the MOZ and MORF genes are rearranged in leukemia, the MORF gene is also mutated in prostate and other cancers and in four genetic disorders with intellectual disability. Here we show that forebrain-specific inactivation of the mouse Brpf1 gene causes hypoplasia in the dentate gyrus, including underdevelopment of the suprapyramidal blade and complete loss of the infrapyramidal blade. We trace the developmental origin to compromised Sox2+ neural stem cells and Tbr2+ intermediate neuronal progenitors. We further demonstrate that Brpf1 loss deregulates neuronal migration, cell cycle progression and transcriptional control, thereby causing abnormal morphogenesis of the hippocampus. These results link histone binding and acetylation control to hippocampus development and identify an important epigenetic regulator for patterning the dentate gyrus, a brain structure critical for learning, memory and adult neurogenesis.
Keywords: acyltransferase; eomesodermin; histone; protein Brpf1; regulator protein; transcription factor Sox2; unclassified drug; animal cell; animal experiment; animal tissue; brain development; Brpf1 gene; cell cycle progression; cell migration; dentate gyrus; developmental gene; epigenetics; forebrain; gene inactivation; hippocampus; histone acetylation; hypoplasia; learning; memory; mouse; nerve cell differentiation; nervous system development; neural stem cell; protein binding; protein depletion; transcription regulation

Impact of residential building regulations on reducing indoor exposures to outdoor PM2.5 in Toronto - Zuraimi, M. S.; Tan, Zhongchao (Building and Environment, 2015)
We conducted a cost benefit analysis of residential building regulations on reducing the exposure to outdoor PM2.5 in Toronto. By combining a combined mass balanced model, a time-weighted activity exposure model, epidemiological based concentration-response, and monetary valuation method, various morbidity and mortality outcomes were estimated for different residential building scenarios. It was found that retrofitting residential buildings to comply with minimum building code regulations can save US$2.3 billion/year in health care. Citywide adoption of R2000 standard from current housing corresponds to US$3.8 billion/year. Use of mechanical HVAC systems, improved filtration (with recirculation) and tighter building envelope (lower infiltration rate) were noted as the key factors that influence PM2.5 exposure reductions and health impacts. Estimated costs of retrofitting existing homes to adopt these regulations were about 2.3-2.9 times of the health savings. Citywide use of filters with better efficiency is anticipated to lead to annual health savings significantly exceeding the capital and running costs.
Keywords: Building codes; Climate control; Cost effectiveness; Housing; Public health; Retrofitting; Building envelopes; Exposure modeling; Exposure reduction; Infiltration rate; Monetary valuations; Outdoor PM2.5; Residential building; Cost benefit analysis; air conditioning; building; compliance; cost-benefit analysis; morbidity; mortality; particulate matter; public health; regulatory framework; ventilation; Ontario [Canada]; Toronto

Reduction in predicted survival times in cold water due to wind and waves - Power, Jonathan; Simoes Ré, Antonio; Barwood, Martin; Tikuisis, Peter; Tipton, Michael (Applied Ergonomics, 2015)
Recent marine accidents have called into question the level of protection provided by immersion suits in real (harsh) life situations. Two immersion suit studies, one dry and the other with 500mL of water underneath the suit, were conducted in cold water with 10-12 males in each to test body heat loss under three environmental conditions: calm, as mandated for immersion suit certification, and two combinations of wind plus waves to simulate conditions typically found offshore. In both studies mean skin heat loss was higher in wind and waves vs. calm; deep body temperature and oxygen consumption were not different. Mean survival time predictions exceeded 36h for all conditions in the first study but were markedly less in the second in both calm and wind and waves. Immersion suit protection and consequential predicted survival times under realistic environmental conditions and with leakage are reduced relative to calm conditions.
Keywords: Ergonomics; Calm conditions; Environmental conditions; Marine accidents; cold water; adult; body temperature; heat loss; immersion suit; oxygen consumption; protective clothing; survival time prediction; tsunami; water immersion; wind

N-3 polyunsaturated fatty acids and mast cell activation - Wang, Xiaofeng; Kulka, Marianna (Journal of Leukocyte Biology, 2015)
Mast cells are known to play a vital role in the development of inflammation in allergic responses. Recent studies have indicated that mast cell activation could be modulated by n-3 PUFAs, which have a wide range of well-documented health benefits. In our review, we summarize the recent findings and potential mechanisms of the effect of n-3 PUFAs on mast cell activation. This knowledge could provide new strategies for the development of therapeutic interventions for diseases mediated by mast cells.
Keywords: arachidonic acid; carboxypeptidase A; chymase; docosahexaenoic acid; docosapentaenoic acid; heparin; histamine; icosanoid; icosapentaenoic acid; interleukin 10; interleukin 13; interleukin 17; interleukin 1beta; interleukin 33; interleukin 4; interleukin 5; interleukin 6; interleukin 8; leukotriene B4; leukotriene C4; leukotriene D4; linolenic acid; major basic protein; omega 3 fatty acid; prostaglandin D2; prostaglandin E; serotonin; thrombocyte activating factor; tryptase; tumor necrosis factor; bone marrow derived mast cell; cell activation; cell adhesion; cell migration; cell viability; cytokine production; gene expression; inflammation; lipid raft; mast cell; mast cell degranulation; mediator release; phagocytosis; signal transduction

Influence of different chemical modifications on the icephobic properties of superhydrophobic surfaces in a condensate environment - Wang, Yuanyi; Li, Mingzhen; Lv, Ting; Wang, Qingjun; Chen, Qingmin; Ding, Jianfu (Journal of Materials Chemistry A, 2015)
Three superhydrophobic surfaces have been prepared on an aluminium substrate, which was roughened by acid etching to form a nano-/micro-topological surface structure, and then the surface was modified by coating with a PTES (a fluorinated coupling agent), TTPS (a siloxane coupling agent) or PA (an aliphatic coupling agent) layer. Their surface wettability in terms of water contact angle (CA), sliding angle (SA) and water droplet impact dynamics was studied under different humidities at -10 °C. The reduction of ice adhesion was also investigated under both ambient and condensate environments. The results indicated that the icephobic properties of these three superhydrophobic surfaces in the sub-zero environment varied wildly. The PTES surface can maintain excellent sliding and rebounding ability of a water droplet even under extremely condensate conditions (-10 °C and relative humidity (RH) 90%), while others cannot. It is worth noting that the ice adhesion obviously increased under the condensate environment, but no apparent ice-anchoring effect was observed on any of the three superhydrophobic surfaces. In addition, a water condensing dynamic study at sub-zero temperature revealed a distinctive Leidenfrost phenomenon-like jumping behavior of condensed droplets on all three superhydrophobic surfaces with the highest jumping scale and frequency on the PTES surface. The excellent icephobic property of the PTES surface indicates that the choice of a suitable chemical modification for superhydrophobic surfaces has a significant influence on preserving water-repellency and icephobicity under extremely condensing conditions.
Keywords: Adhesion; Atmospheric humidity; Chemical modification; Coupling agents; Drops; Ice; Surface properties; Surface structure; Anchoring effects; Condensing condition; Leidenfrost phenomenon; Sub-zero temperatures; Super-hydrophobic surfaces; Surface wettability; Water contact angle; Water repellency; Hydrophobicity

Effect of recondensation of sublimed species on nanoparticle temperature evolution in time-resolved laser-induced incandescence - Memarian, F.; Liu, F.; Thomson, K. A.; Daun, K. J.; Snelling, D. R.; Smallwood, G. J. (Applied Physics B: Lasers and Optics, 2015)
In high-fluence laser-induced incandescence (LII), current LII models significantly overpredict the soot nanoparticle temperature decay rate compared to that inferred from two-color pyrometry at the first 100 ns after the peak laser pulse in atmospheric pressure flames. One possible cause is the back flow of sublimed species, which to date has been neglected in LII modeling. In this study, the transient direct simulation Monte Carlo (DSMC) method has been used, for the first time, to calculate the temperature evolution of soot particles, taking into account recondensation of sublimed species. In this algorithm, the physical time is discretized into a number of time steps called ensemble time steps, and the heat flux is calculated by performing several DSMC runs in each ensemble time step before proceeding to the next ensemble time step until the variance reaches an acceptable value. This heat flux is then used to update the nanoparticle temperature over the ensemble time step. Using the new algorithm, the temperature evolution of the particle can be predicted by the DSMC code, which is an improvement to previous DSMC simulations in which predetermined temperature decay curves must be prescribed. The results show that recondensation of sublimed species on the originating nanoparticle is not significant. Although accounting for condensation of sublimed species originating from neighboring soot particles enhances the role of recondensation of sublimed species in slowing down the soot particle temperature decay, it is still not sufficient to be considered as a plausible cause for the discrepancy between modeled soot temperature and the two-color pyrometry measured one in high-fluence LII.
Keywords: Atmospheric pressure; Dust; Heat flux; Monte Carlo methods; Nanoparticles; Pyrometers; Pyrometry; Soot; Atmospheric pressure flames; Direct simulation Monte Carlo method; DSMC simulation; Laser induced incandescence; Temperature decay; Temperature evolution; Time-resolved laser induced incandescence; Two color pyrometry; Atmospheric temperature

Indirect determination of the mobility of structure-borne sound sources - Höller, Christoph; Gibbs, Barry M. (Journal of Sound and Vibration, 2015)
Methods are considered for the indirect determination of the mobility of structure-borne sound sources. Instead of performing measurements on the source in the free state, the source mobility is obtained from measurements made in-situ. This approach is beneficial if the source is difficult to suspend, or if it contains nonlinear structural elements. Two formulations for an indirect source mobility are derived theoretically. The first requires measurement of velocities at or near to the contact points. The second involves measurement of remote velocities only. Neither of the methods requires excitation at the contacts in the coupled state. Numerical simulations of coupled beams are used to validate the two methods and investigate their accuracy and reliability with respect to typical measurement errors, such as background noise and inaccuracies in sensor positioning. It is found that these can have a significant effect on the methods considered. Several experimental case studies with single-contact and multi-contact sources are performed. The results confirm the validity of the two methods in principle, but highlight their sensitivity to experimental errors. In a representative case study with a fan unit, average errors range between ±5 dB and ±10 dB, with occasional errors of up to 30 dB.
Keywords: Acoustic generators; Acoustic wave transmission; Errors; Excited states; Numerical methods; Average errors; Background noise; Experimental errors; Measurement of velocity; Representative case; Sensor positioning; Structural elements; Structure-borne sound sources; Measurement errors

Redox shuttles for lithium-ion batteries at concentrations up to 1 M using an electroactive ionic liquid based on 2,5-di-tert-butyl-1,4-dimethoxybenzene - Khakani, Soumia E.; Forgie, John C.; Macneil, Dean D.; Rochefort, Dominic (Journal of the Electrochemical Society, 2015)
In this work, we designed two redox shuttles with high solubility (up to 1 M) in conventional carbonate-based lithium-ion battery (LIB) electrolytes. At this high concentration, redox shuttles ensure improved overcharge protection than lower concentrations. We developed electroactive imidazolium salts by modifying imidazolium with 2,5-di-tert-butyl-1,4-dimethoxybenzene. Two salts with the cation 1-(3-(2,5-di-tert-butyl-1,4-methoxyphenoxy)propyl)-3-methyl-1H-imidazol-3-ium (EMIm) were synthesized using either hexafluorophosphate (DDB-EMIm-PF6) or bis(trifluromethanesulfonyl)amide (DDB-EMIm-TFSI)) anions. The electrochemical properties of DDB-EMIm-PF6 and DDB-EMIm-TFSI dissolved in ethylene carbonate: diethyl carbonate (EC:DEC), in the presence of either LiPF6 or LiTFSI, were evaluated. Cyclic voltammetry showed a compatible potential (∼3.85 V vs. Li/Li+) for use in LIBs using LiFePO4 as cathodes. Electrolytes using 0.1 M of DDB-EMIm-PF6 or 0.3, 0.7 and 1 M of DDB-EMIm-TFSI were prepared and evaluated in Li/LiFePO4 (LFP) test cells to demonstrate overcharge protection. Electrochemical cycling at C/10 showed an overcharge protection for all concentrations of the redox ionic salts under 100% overcharge conditions. Among these salts, DDBEMIm-TFSI, at a concentration of 0.7 M, was effective in shuttling excess current for over 200 cycles, representing over 6000 operating hours, while maintaining nominal values for the discharge capacity of LiFePO4.
Keywords: Charging (batteries); Cyclic voltammetry; Electric batteries; Electric discharges; Electrolytes; Ethylene; Ionic liquids; Ions; Lithium; Lithium alloys; Lithium compounds; Negative ions; Salts; Secondary batteries; Diethyl carbonates; Discharge capacities; Electrochemical cycling; Ethylene carbonate; Hexafluorophosphates; Imidazolium salt; Overcharge protection; Lithium-ion batteries

Antigenic potential of a highly conserved Neisseria meningitidis lipopolysaccharide inner core structure defined by chemical synthesis - Reinhardt, Anika; Yang, You; Claus, Heike; Pereira, Claney; Cox, Andrew; Vogel, Ulrich; Anish, Chakkumka; Seeberger, Peter (Chemistry and Biology, 2015)
Neisseria meningitidis is a leading cause of bacterialmeningitis worldwide. We studied the potential ofsynthetic lipopolysaccharide (LPS) inner core structures as broadly protective antigens against N.meningitidis. Based on the specific reactivity of human serum antibodies to synthetic LPS cores, we selected a highly conserved LPS core tetrasaccharide as a promising antigen. This LPS inner core tetrasaccharide induced a robust IgG response in mice when formulated as an immunogenic glycoconjugate. Binding of raised mouse serum to a broad collection of N.meningitidis strains demonstrated the accessibility of the LPS core on viable bacteria. The distal trisaccharide was identified as the crucial epitope, whereas the proximal Kdo moiety was immunodominant and induced mainly nonprotective antibodies that are responsible for lack of functional protection in polyclonal serum. Our results identified key antigenic determinants of LPS core glycan and, hence, may aid the design of a broadly protective immunization against N.meningitidis. The human pathogen N.meningitidis expresses a highly conserved LPS inner core glycan that represents a potential antigen for the recognition of several N.meningitidis strains. Reinhardt etal. perform a systematic biochemical evaluation using a library of synthetic LPS inner core glycans and identify the crucial immunogenic epitopes.

The surface magnetic field and chemical abundance distributions of the B2V helium-strong star HD 184927 - Yakunin, I.; Wade, G.; Bohlender, D.; Kochukhov, O.; Marcolino, W.; Shultz, M.; Monin, D.; Grunhut, J.; Sitnova, T.; Tsymbal, V. (Monthly Notices of the Royal Astronomical Society, 2015)
A new time series of high-resolution Stokes I and V spectra of the magnetic B2V star HD 184927 has been obtained in the context of the Magnetism in Massive Stars Large Program with an Echelle SpectroPolarimetric Device for the Observation of Stars (ESPaDOnS) spectropolarimeter at the Canada-France-Hawaii Telescope and dimaPol liquid crystal spectropolarimeter at 1.8-m telescope of Dominion Astrophysical Observatory. We model the optical and UV spectrum obtained from the International Ultraviolet Explorer (IUE) archive to infer the stellar physical parameters. Using magnetic field measurements, we derive an improved rotational period of 9.531 02 ± 0.0007 d. We infer the longitudinal magnetic field from lines of H, He, and various metals, revealing large differences between the apparent field strength variations determined from different elements. Magnetic Doppler Imaging using He and O lines yields strongly non-uniform surface distributions of these elements. We demonstrate that the diversity of longitudinal field variations can be understood as due to the combination of element-specific surface abundance distributions in combination with a surface magnetic field that is comprised of dipolar and quadrupolar components. We have reanalysed IUE high-resolution spectra, confirming strong modulation of wind-sensitive C IV and S IV resonance lines. However, we are unable to detect any modulation of the Hα profile attributable to a stellar magnetosphere. We conclude that HD 184927 hosts a centrifugal magnetosphere (η~ 2.4+22 -1.1 × 104), albeit one that is undetectable at optical wavelengths. The magnetic braking time-scale of HD 184927 is computed to be τ J = 0.96 or 5.8 Myr. These values are consistent with the slow rotation and estimated age of the star.

Wear resistance of materials used for slurry transport - Xie, Yongsong; Jiang, Jiaren (Jimmy); Tufa, Kidus Yoseph; Yick, Sing (Wear, 2015)
More and more slurry transport systems are used in mining operations to efficiently and cost-effectively transport ores and tailings. The materials used for slurry transport are often subjected to severe wear attack. In this study, the wear modes and wear resistance of materials commonly used for slurry transport are discussed. Slurry jet erosion, Coriolis slurry scouring erosion and slurry sliding abrasion tests are used to simulate these wear modes and to characterize the wear resistance of the materials. The wear resistance of selected materials from each material category commonly used for slurry transport, including steels, high chromium white cast irons, chrome carbide-based and tungsten carbide-based overlays, elastomers, plastics, ceramics and cermets, are reported. The relationships of the wear resistance of these materials with their mechanical properties are also briefly discussed.
Keywords: Abrasion; Elastomers; Erosion; Mechanical properties; Strength of materials; Tungsten carbide; Chrome carbide; High chromium white cast iron; Mineral processing; Mining operations; Sliding abrasion; Slurry erosion; Transport systems; Wear-testing; Wear resistance

Pancreatic lipid content is not associated with beta cell dysfunction in youth-onset Type 2 Diabetes - Wicklow, Brandy A.; Griffith, Brandy T.; Dumontet, Jacqueline N.; Venugopal, Niranjan; Ryner, Lawrence N.; McGavock, Jonathan M. (Canadian Journal of Diabetes, 2015)
Objective: To determine whether pancreatic lipid content is associated with type 2 diabetes and beta cell function in Indigenous and Caucasian adolescents. Methods: This was a cross-sectional study comparing 1H-magnetic resonance spectroscopy-derived pancreatic triglyceride content in adolescents 13 to 18 years of age with type 2 diabetes (n=20) and body mass index-matched normoglycemic controls (n=34). Beta cell function was measured by the acute insulin response and disposition index derived from intravenous glucose tolerance tests. Results: Pancreatic lipid content was not significantly different in youth with type 2 diabetes and their normoglycemic body mass index-matched peers (2.41 [95% CI: 0.63, 5.60] vs. 1.22 [0.08, 5.93]; p=0.27). Pancreatic triglyceride levels were not associated with measures of beta cell function in the cohort. In subgroup analyses, pancreatic lipid content was ~4-fold higher in youth with type 2 diabetes who were carriers of the G319S mutation in the HNF-1alpha gene (7.45 [2.85, 26.8] vs. 2.20 [0.350, 3.30] % Fat to Water Ratio F/W; p=0.032). Conclusions: Pancreatic lipid content is not elevated in Indigenous or Caucasian youth with type 2 diabetes compared to normoglycemic youth, nor is it associated with beta cell function. The presence of the G319S mutation in the HNF-1alpha gene in Indigenous youth with type 2 diabetes is associated with higher pancreatic lipid content. Further research is needed to understand the mechanisms that explain beta cell failure in overweight youth with type 2 diabetes.
Keywords: adolescent; lipotoxicity; nuclear magnetic resonance (NMR) spectroscopy; pancreas; steatosis; type 2 diabetes

The James Clerk Maxwell Telescope legacy survey of the Gould belt: A molecular line study of the ophiuchus molecular cloud - White, Glenn J.; Drabek-Maunder, Emily; Rosolowsky, Erik; Ward-Thompson, Derek; Davis, C. J.; Gregson, Jon; Hatchell, Jenny; Etxaluze, Mireya; Stickler, Sarah; Buckle, Jane; Johnstone, Doug; Friesen, Rachel; et al. (Monthly Notices of the Royal Astronomical Society, 2015)
CO, 13CO, and C18O J = 3-2 observations are presented of the Ophiuchus molecular cloud. The 13CO and C18O emission is dominated by the Oph A clump, and the Oph B1, B2, C, E, F, and J regions. The optically thin(ner) C18O line is used as a column density tracer, from which the gravitational binding energy is estimated to be 4.5 × 1039 J (2282 M⊙ km2 s-2). The turbulent kinetic energy is 6.3 × 1038 J (320 M⊙ km2 s-2), or seven times less than this, and therefore the Oph cloud as a whole is gravitationally bound. 30 protostars were searched for high-velocity gas, with 8 showing outflows, and 20 more having evidence of high-velocity gas along their lines of sight. The total outflow kinetic energy is 1.3 × 1038 J (67 M⊙ km2 s-2), corresponding to 21 per cent of the cloud's turbulent kinetic energy. Although turbulent injection by outflows is significant, but does not appear to be the dominant source of turbulence in the cloud. 105 dense molecular clumplets were identified, which had radii~0.01-0.05 pc, virial masses~0.1-12M⊙, luminosities~0.001-0.1K km s-1 pc-2, and excitation temperatures ~10-50 K. These are consistent with the standard Giant Molecular Cloud (GMC) based size-linewidth relationships, showing that the scaling laws extend down to size scales of hundredths of a parsec, and to subsolar-mass condensations. There is however no compelling evidence that the majority of clumplets are undergoing free-fall collapse, nor that they are pressure confined.

High-resolution synchrotron infrared spectroscopy of thiophosgene: The ν 1, ν 5, 2ν4, and ν2+2ν6 bands - McKellar, A. R. W.; Billinghurst, B. E. (Journal of Molecular Spectroscopy, 2015)
Thiophosgene (Cl2CS) is a favorite model system for studies of photophysics, vibrational dynamics, and intersystem interactions. But its infrared spectra tend to be very congested due to hot bands and multiple isotopic species. This paper reports the first detailed study of the ν 1 (~1139cm- 1) and ν 5 (~820cm-1) fundamental bands for the two most abundant isotopologues, 35Cl2CS and 35Cl37ClCS, based on spectra with a resolution of about 0.001cm-1 obtained at the Canadian Light Source far-infrared beamline using synchrotron radiation and a Bruker IFS125 Fourier transform spectrometer. The 2ν 4 (~942cm- 1) and ν 2 +2ν 6 (~1104cm-1) bands are also studied here, but the ν 2 + ν 6 band (~795cm- 1) resisted full analysis.
Keywords: Fourier transform infrared spectroscopy; Infrared radiation; Infrared spectroscopy; Light sources; Spectrometers; Synchrotron radiation; Fourier transform spectrometers; Fundamental bands; High resolution; Infrared spectrum; Intersystem interaction; Isotopic species; Thiophosgenes; Vibrational dynamics; Synchrotrons

Eight-membered ring-containing jadomycins: implications for non-enzymatic natural products biosynthesis - Robertson, Andrew W.; Martinez-Farina, Camilo F.; Smithen, Deborah A.; Yin, Huimin; Monro, Susan; Thompson, Alison; McFarland, Sherri A.; Syvitski, Raymond T.; Jakeman, David L. (Journal of the American Chemical Society, 2015)
Jadomycin Oct (1) was isolated from Streptomyces venezuelae ISP5230 and characterized as a structurally unique eight-membered l-ornithine ring-containing jadomycin. The structure was elucidated through the semisynthetic derivatization of starting material via chemoselective acylation of the l-ornithine α-amino group using activated succinimidyl esters. Incorporation of 5-aminovaleric acid led to jadomycin AVA, a second eight-membered ring-containing jadomycin. These natural products illustrate the structural diversity permissible from a non-enzymatic step within a biosynthetic pathway and exemplifies the potential for discovery of novel scaffolds.

Effects of TiO₂ nanoparticles on ROS production and growth inhibition using freshwater green algae pre-exposed to UV irradiation - Fu, Ling; Hamzeh, Mahsa; Dodard, Sabine; Zhao, Yuan H.; Sunahara, Geoffrey I. (Environmental Toxicology and Pharmacology, 2015)
This study investigated the possibility that titanium dioxide nanoparticles (nano-TiO2) toxicity in Pseudokirchneriella subcapitata involves reactive oxygen species (ROS) production, using the dichlorodihydroﬂuorescein (DCF) assay. Algae were exposed to nano-TiO2 under laboratory fluorescent lamps supplemented with UV irradiation for 3 h, with or without a UV filter. Results showed that nano-TiO2 increased ROS production in UV-exposed cells, with or without a UV filter (LOEC values were 250 and 10 mg/L, respectively). Sublethal effects of nano-TiO2 on UV pre-exposed algae were also examined. Toxicity studies indicated that exposure to nano-TiO2 agglomerates decreased algal growth following 3 h pre-exposure to UV, with or without a UV filter (EC50s were 8.7 and 6.3 mg/L, respectively). The present study suggests that the growth inhibitory effects of nano-TiO2 in algae occurred at concentrations lower than those that can elevate DCF fluorescence, and that ROS generation is not directly involved with the sublethal effects of nano-TiO2 in algae.
Keywords: Pseudokirchneriella subcapitata; TiO2 nanoparticle; Toxicity mechanism; Reactive oxygen species

Toxicogenomic effects of nano- and bulk-TiO2 particles in the soil nematode Caenorhabditis elegans - Rocheleau, Sylvie; Arbour, Mélanie; Elias, Miria; Sunahara, Geoffrey I.; Masson, Luke (Nanotoxicology, 2015)
The toxicity and toxicogenomics of selected anatase and rutile nanoparticles (NP) and bulk titanium dioxide (TiO2) particles were evaluated in the soil nematode Caenorhabditis elegans. Results indicated that bulk or nano-TiO2 particles were slightly toxic to soil nematode C. elegans, as measured by reproduction EC50 values ranging from 4 to 32 mg/L. Whole-genome microarray results indicated that the regulation of glutathione-S-transferase gst-3, cytochrome P450 cypp33-c11, stress resistance regulator scl-1, oxidoreductase wah-1 and embryonic development pod-2 genes were significantly affected by nano-sized and bulk-TiO2 particles. More specifically, it was determined that anatase particles exerted a greater effect on metabolic pathways, whereas rutile particles had a greater effect on developmental processes. The up-regulation of the pod-2 gene corroborated the phenotypic effect observed in the reproduction test. Our results demonstrated that C. elegans is a good genomic model for nano-TiO2 toxicity assessment.
Keywords: Gene expression; juglone; nanoparticles; oxidative stress; titanium dioxide

Biochemical composition and amino acid profiles of Nannochloropsis granulata algal biomass before and after supercritical fluid CO2 extraction at two processing temperatures - Tibbetts, Sean M.; Bjornsson, William J.; McGinn, Patrick J. (Animal Feed Science and Technology, 2015)
To assess the effect of supercritical fluid CO2 (SCFCO2) extraction on the biochemical composition of algal biomass, samples of untreated Nannochloropsis granulata biomass (Initial) and residual biomass after SCFCO2 extraction at 70 and 90 °C (C70 and C90) were analyzed. SCFCO2 extraction significantly reduced crude lipid content from 285.5 g/kg to 256.2–256.3 g/kg (P=0.032) and caloric content from 23.4 MJ/kg to 23.0–23.1 MJ/kg (P=0.004). Concomitantly, significant increases in ash content from 77.8 g/kg to 83.8–86.2 g/kg (P=0.002) and carbohydrate content from 149.1 g/kg to 155.9–165.9 g/kg (P=0.033) were observed and no significant differences between C70 and C90. Small, but significantly lower levels of crude protein (CP, N × 6.25 or N × 4.78) and non-protein N (NPN) were observed for C70 with no differences between Initial and C90. However, sum of amino acid (AA) residues (ΣAA), a more direct estimate of true protein content, indicated no significant difference in protein content (P=0.536) between treatments (average, 362.0 g/kg). Only minor differences in total and free AA profiles were observed between Initial, C70 and C90 and the free AA content as percentage of total AA was insignificant (P=0.564) between treatments (average, 4.9%). However, several free essential AAs (EAAs) were significantly higher in C70 and C90 than Initial resulting in SCFCO2-extracted biomass having significantly higher (P=0.007) total free EAA content (2438.0–2697.0 μg/g of DW) than Initial (2100.4 μg/g of DW) indicating some protein damage and free EAA liberation. While there was a trend toward most AAs slightly increasing in C70 and C90, the EAA lysine; particularly sensitive to high-temperature processing, was significantly lower (P=0.003) in C90 (6.0 g lysine/100 g protein) than Initial (6.9 g lysine/100 g protein) while C70 was intermediate (6.4 g lysine/100 g protein) providing evidence that lysine damage was more severe at 90 °C than 70 °C. The essential AA index (EAAI) of 0.9 for N. granulata biomass is highly comparable to reference proteins such as egg albumin, soy, Chlorella and Spirulina (0.9–1.0) indicating very good potential for use in animal and fish feeds. Further investigations involving species-specific in vitro protein quality and in vivo biological performance of target animals fed diets supplemented with these products are warranted.
Keywords: microalgae; nannochloropsis; supercritical fluid extraction; proximate composition; amino acids

Seasonal isolation of microalgae from municipal wastewater for remediation and biofuel applications - Park, K.C.; Whitney, C.G.E.; Kozera, C.; O'Leary, S.J.B.; McGinn, P.J. (Journal of Applied Microbiology, 2015)
The objective of the study was to isolate the microalgae strains from treated municipal wastewater in both summer and winter seasons in order to identify strains better suited for nutrient remediation and biofuel production under either cooler or warmer temperatures. Methods and Results Fifty-six strains in total were isolated and identified by DNA sequencing from effluent samples collected from a local wastewater treatment plant during the summer and winter of 2011. Screening of 41 isolates based on the fatty acid productivity at either 22 or 10°C resulted in the selection of 12 strains organized into two groups of 6—the M (mild) and C (cool) groups, respectively. Four of the C-group strains were isolated from the winter sample, while four of the M-group isolates were isolated from the summer sample. Fatty acid pools in M-group strains were heavily regulated in response to growth temperature while C-group strains were more insensitive. In three of the six C-group strains, the rates of biomass and fatty acid productivity at 10°C exceeded the corresponding rates at 22°C. Conversely, M group were always more productive at 22 compared to 10°C. Mixotrophic strategies to enhance productivity were generally unsuccessful in M-group strains at 22°C but proved to be more effective in C-group cultures at 10°C. Conclusions In general, C-group strains appeared better suited for growth in municipal wastewater at 10°C, while M-group strains were better suited at 22°C. On balance, C-group isolates were more likely to come from winter wastewater samples while M-group strains were more likely to come from the summer sample. Significance and Impact of the Study Our results demonstrate that the effects of temperature on microalgal growth for wastewater remediation can be mitigated somewhat by isolation and careful selection of strains adapted to seasonal wastewater conditions.
Keywords: biofuel; biomass productivity; bioremediation; CO2 capture; fatty acids; microalgae; temperature; wastewater

Genetics, structure, and prevalence of FP967 (CDC Triffid) T-DNA in flax - Young, Lester; Hammerlindl, Joseph; Babic, Vivijan; McLeod, Jamille; Sharpe, Andrew; Matsalla, Chad; Bekkaoui, Faouzi; Marquess, Leigh; Booker, Helen M. (SpringerPlus, 2015)
The detection of T-DNA from a genetically modified flaxseed line (FP967, formally CDC Triffid) in a shipment of Canadian flaxseed exported to Europe resulted in a large decrease in the amount of flax planted in Canada. The Canadian flaxseed industry undertook major changes to ensure the removal of FP967 from the supply chain. This study aimed to resolve the genetics and structure of the FP967 transfer DNA (T-DNA). The FP967 T-DNA is thought to be inserted in at single genomic locus. The junction between the T-DNA and genomic DNA consisted of two inverted Right Borders with no Left Border (LB) flanking genomic DNA sequences recovered. This information was used to develop an event-specific quantitative PCR (qPCR) assay. This assay and an existing assay specific to the T-DNA construct were used to determine the genetics and prevalence of the FP967 T-DNA. These data supported the hypothesis that the T-DNA is present at a single location in the genome. The FP967 T-DNA is present at a low level (between 0.01 and 0.1%) in breeder seed lots from 2009 and 2010. None of the 11,000 and 16,000 lines selected for advancement through the Flax Breeding Program in 2010 and 2011, respectively, tested positive for the FP967 T-DNA, however. Most of the FP967 T-DNA sequence was resolved via PCR cloning and next generation sequencing. A 3,720 bp duplication of an internal portion of the T-DNA (including a Right Border) was discovered between the flanking genomic DNA and the LB. An event-specific assay, SAT2-LB, was developed for the junction between this repeat and the LB.
Keywords: FP967; CDC Triffid; T-DNA; Flaxseed; Linum usitatissimum

Development of a sensitive in vitro assay to quantify the biological activity of pro-inflammatory phorbol esters in Jatropha oil - Pelletier, Guillaume; Padhi, Bhaja K.; Hawari, Jalal; Sunahara, Geoffrey I.; Poon, Raymond (In Vitro Cellular and Developmental Biology - Animal, 2015)
The use of biodiesel is promoted worldwide as it can contribute to a reduction of fossil fuel dependency and greenhouse gas emissions (Adler et al. 2007; Huo et al. 2009). Biodiesels are generally less toxic than fossils (Poon et al. 2007; Poon et al. 2009), but potential human health hazards arising from their increasing use also need to be properly assessed, especially for biodiesels manufactured from non-edible or toxic feedstock (Poon et al. 2013).
Keywords: in vitro bioassay; Jatropha oil; MDCK cell line; Phorbolester; Cyclooxygenase

Abscisic acid acts as a blocker of the bitter taste G protein-coupled receptor T2R4 - Pydi, Sai P.; Jaggupilli, Appalaraju; Nelson, Ken M.; Abrams, Suzanne R.; Bhullar, Rajinder P.; Loewen, Michele C.; Chelikani, Prashen (Biochemistry, 2015)
Bitter taste receptors (T2Rs) belong to the G protein-coupled receptor superfamily. In humans, 25 T2Rs mediate bitter taste sensation. In addition to the oral cavity, T2Rs are expressed in many extraoral tissues, including the central nervous system, respiratory system, and reproductive system. To understand the mechanistic roles of the T2Rs in oral and extraoral tissues, novel blockers or antagonists are urgently needed. Recently, we elucidated the binding pocket of T2R4 for its agonist quinine, and an antagonist and inhibitory neurotransmitter, γ-aminobutyric acid. This structure−function information about T2R4 led us to screen the plant hormone abscisic acid (ABA), its precursor (xanthoxin), and catabolite phaseic acid for their ability to bind and activate or inhibit T2R4. Molecular docking studies followed by functional assays involving calcium imaging confirmed that ABA is an antagonist with an IC50 value of 34.4 ± 1.1 μM. However, ABA precursor xanthoxin acts as an agonist on T2R4. Interestingly, molecular model-guided site-directed mutagenesis suggests that the T2R4 residues involved in quinine binding are also predominantly involved in binding to the novel antagonist, ABA. The antagonist ability of ABA was tested using another T2R4 agonist, yohimbine. Our results suggest that ABA does not inhibit yohimbineinduced T2R4 activity. The discovery of natural bitter blockers has immense nutraceutical and physiological significance and will help in dissecting the T2R molecular pathways in various tissues.

The IVAIRE project: a randomized controlled study of the impact of ventilation on indoor air quality and the respiratory symptoms of asthmatic children in single family homes - Lajoie, P.; Aubin, D.; Gingras, V.; Daigneaule, P.; Ducharme, F.M.; Gauvin, D.; Fugler, D.; Leclerc, J.M.; Won, D.; Courteau, M.; Gingras, S.; Héroux, M.È.; et al. (Indoor air, 2015)
A randomized controlled trial was carried out to measure the impact of an intervention on ventilation, indoor air contaminants, and asthma symptoms of children. Eighty-three asthmatic children living in low-ventilated homes were followed over 2 years. Several environmental parameters were measured during the summer, fall, and winter. The children were randomized after Year 1 (43 Intervention; 40 Control). The intervention included the installation of either a Heat Recovery Ventilator (HRV) or Energy Recovery Ventilator (ERV). During the fall and winter seasons, there was a significant increase in the mean ventilation rate in the homes of the intervention group. A statistically significant reduction in mean formaldehyde, airborne mold spores, toluene, styrene, limonene, and α-pinene concentrations was observed in the intervention group. There was no significant group difference in change in the number of days with symptoms per 14 days. However, there was a significant decrease in the proportion of children who experienced any wheezing (≥1 episode) and those with ≥4 episodes in the 12-month period in the intervention group. This study indicates that improved ventilation reduces air contaminants and may prevent wheezing. Due to lack of power, a bigger study is needed.
Keywords: Asthma; children; respiratory symptoms; field study; ventilation; indoor air; home

Construct validity of a Neck Palpation Simulator - Sivarajah, Priya; Glicksman, Jordan Thomas; Chow, Winsion; Campbell, Gord; Fung, Kevin (The Laryngoscope, 2015)
Objectives/Hypothesis: To assess the construct validity of a high-fidelity neck model with simulated lymph adenopathy. Study design: Prospective experimental validation study. Methods: Six first year medical students with prior training (novice learners) and six otolaryngology-head and neck surgery (OtoHNS) residents (experts) performed the head and neck lymph node examination on a novel tissue-mimicking construct model of the neck region. Two otolaryngologists, blinded to training type, evaluated the videotaped performances, using two assessment tools specifically designed for the head and neck lymph node examination: a global rating scale (GRS), and a task-based checklist (TBC). Results: The OtoHNS residents scored significantly higher than the medical student s on the GRS (p=0.008). There was also a trend towards better scores for the residents on the TBC (p=0.085). Conclusion: This is the first reported stud y of a high-fidelity lymphadenopathy model with task¬ specific assessment tools. The neck model demonstrated construct validity, by easily distinguishing between experts and novices on the basis of procedural competence. Using the global rating scale and task-based checklist, this model can be used to provide formative feedback, and to assess technical skill s acquisition in trainees.
Keywords: neck model

Production of α2,6-sialylated IgG1 in CHO cells - Raymond, Céline; Robotham, Anna; Spearman, Maureen; Butler, Michael; Kelly, John; Durocher, Yves (mAbs, 2015)
The presence of α2,6-sialic acids on the Fc N-glycan provides anti-inflammatory properties to the IgGs through a mechanism that remains unclear. Fc-sialylated IgGs are rare in humans as well as in industrial host cell lines such as Chinese hamster ovary (CHO) cells. Facilitated access to well-characterized α2,6-sialylated IgGs would help elucidate the mechanism of this intriguing IgG's effector function. This study presents a method for the efficient Fc glycan α2,6-sialylation of a wild-type and a F243A IgG1 mutant by transient co-expression with the human α2,6-sialyltransferase 1 (ST6) and β1,4-galactosyltransferase 1 (GT) in CHO cells. Overexpression of ST6 alone only had a moderate effect on the glycoprofiles, whereas GT alone greatly enhanced Fc-galactosylation, but not sialylation. Overexpression of both GT and ST6 was necessary to obtain a glycoprofile dominated by α2,6-sialylated glycans in both antibodies. The wild-type was composed of the G2FS(6)1 glycan (38%) with remaining unsialylated glycans, while the mutant glycoprofile was essentially composed of G2FS(6)1 (25%), G2FS(3,6)2 (16%) and G2FS(6,6)2 (37%). The α2,6-linked sialic acids represented over 85% of all sialic acids in both antibodies. We discuss how the limited sialylation level in the wild-type IgG1 expressed alone or with GT results from the glycan interaction with Fc's amino acid residues or from intrinsic galactosyl- and sialyl-transferases substrate specificities.
Keywords: B4GALT1; CHO cells; ECL, Erythrina Cristagalli lectin; GT, β1,4-galactosyltransferase 1; HILIC, hydrophilic interaction liquid chromatography; IgG1; LC-ESI-MS, liquid chromatography coupled to electrospray ionization mass spectrometry; MAL-II, Maackia Amurensis lectin II; N-glycosylation; PEI, polyethylenimine; SIAT1; SNA, Sambucus Nigra agglutinin; ST6, α2,6-sialyltransferase 1; TZM, trastuzumab (Herceptin®); cIEF, capillary zone electrophoresis isoelectric focusing; mAbs, monoclonal antibodies; sialylation; transfection; α2,3SA, α2,3-linked sialic acid; α2,6SA, α2,6-linked sialic acid

Targeting surface-layer proteins with single-domain antibodies : a potential therapeutic approach against Clostridium difficile-associated disease - Kandalaft, Hiba; Hussack, Greg; Aubry, Annie; van Faassen, Henk; Guan, Yonghong; Arbabi-Ghahroudi, Mehdi; Mackenzie, Roger; Logan, Susan M.; Tanha, Jamshid (Applied Microbiology and Biotechnology, 2015)
Clostridium difficile is a leading cause of death from gastrointestinal infections in North America. Antibiotic therapy is effective, but the high incidence of relapse and the rise in hypervirulent strains warrant the search for novel treatments. Surface layer proteins (SLPs) cover the entire C. difficile bacterial surface, are composed of high-molecular-weight (HMW) and low-molecular-weight (LMW) subunits, and mediate adherence to host cells. Passive and active immunization against SLPs has enhanced hamster survival, suggesting that antibody-mediated neutralization may be an effective therapeutic strategy. Here, we isolated a panel of SLP-specific single-domain antibodies (VHHs) using an immune llama phage display library and SLPs isolated from C. difficile hypervirulent strain QCD-32g58 (027 ribotype) as a target antigen. Binding studies revealed a number of VHHs that bound QCD-32g58 SLPs with high affinity (K D = 3–6 nM) and targeted epitopes located on the LMW subunit of the SLP. The VHHs demonstrated melting temperatures as high as 75 °C, and a few were resistant to the gastrointestinal protease pepsin at physiologically relevant concentrations. In addition, we demonstrated the binding specificity of the VHHs to the major C. difficile ribotypes by whole cell ELISA, where all VHHs were found to bind 001 and 027 ribotypes, and a subset of antibodies were found to be broadly cross-reactive in binding cells representative of 012, 017, 023, and 078 ribotypes. Finally, we showed that several of the VHHs inhibited C. difficile QCD-32g58 motility in vitro. Targeting SLPs with VHHs may be a viable therapeutic approach against C. difficile-associated disease.
Keywords: Clostridium difficile; Surface layer protein; Single-domain antibody; VHH; Nanobody

Guidance for the model developer on representing human behavior in egress models - Gwynne, S.M.V.; Hulse, L.M.; Kinsey, M.J. (Fire Technology, 2015)
Structures are currently designed and typically constructed in accordance with prescriptive and performance-based methodologies to ensure a certain level of safety. The performance-based approach requires the quantification of both available safe egress time (ASET) and required safe egress time (RSET) to determine the degree of safety provided. This article focuses on the RSET side of the equation, for which an engineer would use some type of egress modelling approach to estimate evacuation performance. Often, simple engineering equations are applied to estimate the RSET value; however, over time, more sophisticated computational tools have appeared. Irrespective of the approach adopted, appropriate and accurate representation of human behavior in fire within these approaches is limited, mainly due to the lack of a comprehensive conceptual model of evacuee decision-making and behavior during fire emergencies. This article initially presents a set of behavioral statements that represent the primary elements of current understanding regarding evacuee behavior. Once presented, guidance is provided on how these behavioral statements might be incorporated by the model developer into an egress model. The intent here is to assist in the advancement of current egress models by outlining the model structures required to represent the current understanding of egress behavior.
Keywords: egress models; evacuee behavior; model development human behavior in fire

Active pneumatic control of centrifugal microfluidic flows for lab-on-a-chip applications - Clime, Liviu; Brassard, Daniel; Geissler, Matthias; Veres, Teodor (Lab Chip, 2015)
This paper reports a novel method of controlling liquid motion on a centrifugal microfluidic platform based on the integration of a regulated pressure pump and a programmable electromechanical valving system. We demonstrate accurate control over the displacement of liquids within the system by pressurizing simultaneously multiple ports of the microfluidic device while the platform is rotating at high speed. Compared to classical centrifugal microfluidic platforms where liquids are solely driven by centrifugal and capillary forces, the method presented herein adds a new degree of freedom for fluidic manipulation, which represents a paradigm change in centrifugal microfluidics. We first demonstrate how various core microfluidic functions such as valving, switching, and reverse pumping (i.e., against the centrifugal field) can be easily achieved by programming the pressures applied at dedicated access ports of the microfluidic device. We then show, for the first time, that the combination of centrifugal force and active pneumatic pumping offers the possibility of mixing fluids rapidly (~0.1 s) and efficiently based on the creation of air bubbles at the bottom of a microfluidic reservoir. Finally, the suitability of the developed platform for performing complex bioanalytical assays in an automated fashion is demonstrated in a DNA harvesting experiment where recovery rates of about 70% were systematically achieved. The proposed concept offers the interesting prospect to decouple basic microfluidic functions from specific material properties, channel dimensions and fabrication tolerances, surface treatments, or on-chip active components, thus promoting integration of complex assays on simple and low-cost microfluidic cartridges.

Direct sound transmission loss of heavy gauge steel stud walls - Hoeller, Christoph; Zeitler, Berndt; Mahn, Jeffrey (EuroNoise Proceedings 2015, 2015)
In a recent study at the National Research Council of Canada, the direct sound transmission loss of heavy gauge steel stud walls was investigated. Mid-rise buildings (4 to 6 stories) using steel stud walls are becoming more and more common in North America. In addition to the steel studs, the walls typically include bridging channels and steel straps for bracing against lateral and shear loads. The sound transmission losses of more than thirty of the steel stud walls were measured in this study. The parameters that were varied between walls included the stud spacing, stud gauge, stud depth, cavity insulation, and sheathing. In addition to the standardized transmission loss tests, structural measurements were performed to investigate the effect of stud stiffness and other parameters.

Apparent airborne sound insulation of hybrid wood-concrete masonry assemblies - Zeitler, Berndt; Sabourin, Ivan; Hoeller, Christoph; Mahn, Jeffrey; Schoenwald, Stefan (EuroNoise proceedings, 2015)
As part of a research project to develop design solutions for concrete-masonry buildings for the Canadian market, the apparent sound insulation performance of hybrid assemblies with concrete masonry walls and wood joist floors was evaluated. In this paper, the effect of junction coupling is investigated in an ISO 15712 flanking prediction context. Airborne flanking path data predicted according to ISO 15712 are compared to data measured using the indirect ISO 10848 shielding method. Recommendations are made on how appropriate the application of ISO 15712 is for this type of hybrid assembly.

Glycoproteomic comparison of clinical triple-negative and luminal breast tumors - Hill, Jennifer J.; Tremblay, Tammy-Lynn; Fauteux, François; Li, Jie; Wang, Edwin; Aguilar-Mahecha, Adriana; Basik, Mark; O'Connor-McCourt, Maureen (Journal of Proteome Research, 2015)
Triple-negative (TN) breast cancer accounts for ∼15% of breast cancers and is characterized by a high likelihood of relapse and a lack of targeted therapies. In contrast, luminal-type tumors that express the estrogen and progesterone receptors (ER+/PR+) and lack expression of human epidermal growth factor receptor 2 (Her2−) are treated with targeted hormonal therapy and carry a better prognosis. To identify potential targets for the development of future therapeutics aimed specifically at TN breast cancers, we have used a hydrazide-based glycoproteomic workflow to compare protein expression in clinical tumors from nine TN (Her2–/ER-/PR-) and nine luminal (Her2–/ER+/PR+) patients. Using a label-free LC–MS based approach, we identified and quantified 2264 proteins. Of these, 90 proteins were more highly expressed and 86 proteins were underexpressed in the TN tumors relative to the luminal tumors. The expression level of four of these potential targets was verified in the original set of tumors by Western blot and correlated well with our mass-spectrometry-based quantification. Furthermore, 30% of the proteins differentially expressed between luminal and TN tumors were validated in a larger cohort of 406 TN and 469 luminal tumors through corresponding differences in their mRNA expression in publically available microarray data. A group of 29 of these differentially expressed proteins was shown to correctly classify 88% of TN and luminal tumors using microarray data of their associated mRNA levels. Interestingly, even within a group of TN breast cancer patients, the expression levels of these same mRNAs were able to significantly predict patient survival, suggesting that these proteins play a role in the aggressiveness seen in TN tumors. This study provides a comprehensive list of potential targets for the development of diagnostic and therapeutic agents specifically aimed at treating TN breast cancer and demonstrates the utility of using publicly available microarray data to further prioritize potential targets.
Keywords: triple-negative breast cancer; luminal breast cancer; proteomics; glycoproteomics; mass spectrometry; tumor

The IGF-trap: novel inhibitor of carcinoma growth and metastasis - Wang, Ni; Rayes, Roni F.; Elahi, Seyyed Mehdy; Lu, Yifan; Hancock, Mark A.; Massie, Bernard; Rowe, Gerald E.; Aomari, Hafida; Hossain, Sazzad; Durocher, Yves; Pinard, Maxime; Tabaries, Sébastian; et al. (Molecular Cancer Therapeutics, 2015)
The IGFI receptor promotes malignant progression and has been recognized as a target for cancer therapy. Clinical trials with anti-IGFIR antibodies provided evidence of therapeutic efficacy but exposed limitations due in part to effects on, and the compensatory function of, the insulin receptor system. Here, we report on the production, characterization, and biologic activity of a novel, IGF-targeting protein (the IGF-Trap) comprising a soluble form of hIGFIR and the Fc portion of hIgG1. The IGF-Trap has a high affinity for hIGFI and hIGFII but low affinity for insulin, as revealed by surface plasmon resonance. It efficiently blocked IGFIR signaling in several carcinoma cell types and inhibited tumor cell proliferation, migration, and invasion in vitro. In vivo, the IGF-Trap showed favorable pharmacokinetic properties and could suppress the growth of established breast carcinoma tumors when administered therapeutically into tumor-bearing mice, improving disease-free survival. Moreover, IGF-Trap treatment markedly reduced experimental liver metastasis of colon and lung carcinoma cells, increasing tumor cell apoptosis and reducing angiogenesis. Finally, when compared with an anti-IGFIR antibody or IGF-binding protein-1 that were used at similar or higher concentrations, the IGF-Trap showed superior therapeutic efficacy to both inhibitors. Taken together, we have developed a targeted therapeutic molecule with highly potent anticancer effects that could address limitations of current IGFIR-targeting agents
Keywords: IGF; Trap; breast cancer; colon cancer; liver metastasis

Role of microRNAs in progression and recurrence of early-stage lung adenocarcinoma - Singh, Rama K.; Bethune, Drew C.; Xu, Zhaolin; Douglas, Susan E. (Pulmonary Research and Respiratory Medicine, 2015)
Lung cancer is the leading cause of cancer-related death worldwide, and the majority of cases (77%) are not diagnosed until the disease has spread to regional lymph nodes or distant sites. Even among Non-Small Cell Lung Cancer (NSCLC) adenocarcinoma patients who have been diagnosed early and where there has been no spread to lymph nodes, recurrence after surgical intervention is high. Improved understanding of the molecular alterations involved in aggressivity and recurrence of these tumors may provide better biomarkers for the identification of patients who would benefit from adjuvant chemotherapy. By comparing the expression of microRNAs in advanced Stage II/III tumors with those expressed in earlier Stage I tumors, we aimed to identify differentially expressed molecular biomarkers that could underly progression and recurrence of Stage I tumors. This pilot study utilized TaqMan qPCR assays to assess the expression of microRNAs in tumor tissue, matched normal tissue and plasma samples from Stage I and Stage II/III lung adenocarcinoma patients. Seven microRNAs were identified from plasma that could distinguish between patients with Stage I and Stage II/III adenocarcinoma. The up-regulation of miR-29a in plasma of patients with later-stage adenocarcinoma would result in enhanced expression of several molecules involved in integrin signaling, migration and proliferation. Analysis of differential expression of microRNAs in later-stage compared to early-stage lung adenocarcinoma implicates focal adhesion and ECM-receptor pathways in progression and recurrence. Plasma miR-29a is a promising biomarker that can be assessed non-invasively and whose clinical utility should be pursued.
Keywords: Adenocarcinoma; Biomarker; microRNAs; Non-Small Cell Lung Cancer; Recurrence; Transcriptome

Association of anti-GT1a antibodies with an outbreak of Guillain-Barré syndrome and analysis of ganglioside mimicry in an associated Campylobacter jejuni strain - Zhang, Maojun; Gilbert, Michel; Yuki, Nobuhiro; Cao, Fangfang; Li, Jianjun; Liu, Hongying; Li, Qun; Meng, Fanliang; Zhang, Jianzhong (PLoS ONE, 2015)
An outbreak of Guillain-Barré syndrome (GBS), subsequent to Campylobacter jejuni enteritis, occurred in China in 2007. Serum anti-ganglioside antibodies were measured in GBS patients and controls. Genome sequencing was used to determine the phylogenetic relationship among three C. jejuni strains from a patient with GBS (ICDCCJ07001), a patient with gastroenteritis (ICDCCJ07002) and a healthy carrier (ICDCCJ07004), which were all associated with the outbreak. The ganglioside-like structures of the lipo-oligosaccharides of these strains were determined by mass spectrometry. Seventeen (53%) of the GBS patients had anti-GT1a IgG antibodies. GT1a mimicry was found in the lipo-oligosaccharides of strain ICDCCJ07002 and ICDCCJ07004; but a combination of GM3/GD3 mimics was observed in ICDCCJ07001, although this patient had anti-GT1a IgG antibodies. A single-base deletion in a glycosyltransferase gene caused the absence of GT1a mimicry in ICDCCJ07001. The phylogenetic tree showed that ICDCCJ07002 and ICDCCJ07004 were genetically closer to each other than to ICDCCJ07001. C. jejuni, bearing a GT1a-like lipo-oligosaccharide, might have caused the GBS outbreak and the loss of GT1a mimicry may have helped ICDCCJ07001 to survive in the host.
Keywords: anti-ganglioside antibody; phylogenetic analysis; antigenic drift; ganglioside antibody; ganglioside GD 1b; ganglioside GD3; ganglioside GM1; ganglioside GM2; ganglioside GQ 1b; ganglioside GT 1a; glycosyltransferase; immunoglobulin G antibody; immunoglobulin M antibody; lipooligosaccharide; antibody blood level; bacterial genome; bacterial strain; cgtA gene; cgtB gene; cst II gene; diarrhea; DNA sequence; gastroenteritis; molecular mimicry; phylogenetic tree; phylogeny; single nucleotide polymorphism

Fretting behavior of cold-sprayed Cu and Cu-MoS2 coatings - Zhang, Yinyin; Chromik, Richard R.; Descartes, Sylvie; Regis, Edouard; Vo, Phuong (Proceedings from the International Thermal Spray Conference, 2015)
Cu and Cu-MoS2 coatings were fabricated by cold gas dynamic spray and the fretting wear performance of the two coatings was compared. A mixture (95 wt.% Cu + 5 wt.% MoS2) was used as feedstock for the composite coating. Coatings were sprayed with identical gas flow conditions on the substrates preheated to approximately 170°C. The cross section of the coatings was analyzed by scanning electron microscope (SEM) and MoS2 concentration was measured, as well as coating microhardness. Fretting tests were carried out under gross slip conditions in ambient environment. SEM observation on wear scars and counterspheres revealed the development of third bodies, by which the sliding was accommodated. For the Cu-MoS2 coating, solid lubrication effects in the form of friction drops occurred in early cycles (< 5k), but eventually (> 5k) the coating's friction behavior was similar to the pure Cu coating. Third body morphology and wear of the two coatings were distinctly different, which could largely be attributed to the hardness reduction of the Cu-MoS2 composite due to poorly bonded interfaces induced by the effect of MoS2 during particle impact and coating formation.

Investigation of the deposition mechanism of cold spray onto carbon fiber reinforced polymers - Che, Hanqing; Yue, Stephen; Vo, Phuong (Proceedings from the International Thermal Spray Conference, 2015)
Carbon fibre reinforced polymers (CFRPs) are more and more used in a wide range of industries, especially in the aerospace industry, but their low electrical conductivity has limited their application. During the past few years, metallization of CFRP has attracted increasing interest. To make the polymer composites electrically conductive, a conductive media must be either embedded into or coated onto the composites. Cold spray is one coating approach to achieve this. In this work, metallic powders were cold sprayed onto the CFRPs used in aircraft by using two different cold spray systems. The coatings as well as the coating/substrate interfaces were characterized and the deposition mechanism onto the CFRP substrate was determined.

Improving cold sprayability: mixed metal powders - Yue, Stephen; Wong, Wilson; Aydin, Huseyin; Mongrain, Rosaire; Barua, Rajib; Vo, Phuong; Dolbec, Richard (Proceedings from the International Thermal Spray Conference, 2015)
In this paper, it is shown that mixing metal powders can lead to improvements in cold sprayability (i.e. increases in the deposition efficiency and decreases in the porosity) of the ‘matrix' powder. This finding is illustrated with the following ‘binary' mixtures: Ti – 6Al-4 V and commercial purity Ti; stainless steel and iron; spherical tantalum with irregular tantalum and two types of spherical tantalum with different characteristics. It is shown that a critical addition can significantly influence cold sprayability, but above this, there is little change in cold sprayability. Hardness differences are considered to be the first order influence, but differences in particle sizes and morphology may also be contributing factors.

The influence of Al2O3 particle morphology on the coating formation and dry sliding wear behavior of cold sprayed Al–Al2O3 composites - Shockley, J. M.; Descartes, S.; Vo, P.; Irissou, É.; Chromik, R. R. (Surface and Coatings Technology, 2015)
Five Al–Al2O3 coatings were deposited by gas dynamic cold spray, using feedstocks containing 0, 10, and 50 wt.% of Al2O3 particles admixed into commercially pure Al powders. Two feedstocks were made using Al2O3 powders with an angular, blocky Al2O3 morphology, two feedstocks used Al2O3 powders with a spherical morphology, and the fifth consisted of 100% Al. The influence of Al2O3 concentration and morphology in the feedstock powders on the cold spray coating formation was measured in terms of Al2O3 recovery in the coatings, deposition efficiency, and microstructural analysis. The Al–Al2O3 coatings were then subjected to dry sliding wear experiments from which the friction, wear, and microevolution of third body structures in the wear track and transfer film were observed. The spherical Al2O3 morphology was associated with improved tribological behavior compared to the angular morphology when comparing similar coating concentrations of Al2O3.
Keywords: Cold spray; Dry sliding wear; In situ tribometry; Al–Al2O3; Metal matrix composites

Integration of nanotube paper into UHMWPE multilayer structures - Martinez-Rubi, Y.; Ashrafi, Behnam; Jakubinek, M.; Denommee, Stephane; Guan, J.W.; Simard, Benoit (Proceedings of the Tenth Joint Canada-Japan Workshop on Composites, 2015)

Sialyltransferases with enhanced legionaminic acid transferase activity for the preparation of analogs of sialoglycoconjugates - Watson, David C.; Wakarchuk, Warren W.; Leclerc, Sonia; Schur, Melissa J.; Schoenhofen, Ian C.; Young, N. Martin; Gilbert, Michel (Glycobiology, 2015)
Legionaminic acids (Leg) are bacterial analogs of neuraminic acid, with the same stereochemistry but different substituents at C5, C7 and C9. Hence they may be incorporated into useful analogs of sialoglycoconjugates, and we previously reported two sialyltransferases that could utilize cytidine monophosphate (CMP)-Leg5Ac7Ac for preparation of Leg glycoconjugates, which were resistant to sialidases [Watson DC, Leclerc S, Wakarchuk WW, Young NM. 2011. Enzymatic synthesis and properties of glycoconjugates with legionaminic acid as a replacement for neuraminic acid. Glycobiology. 21:99–108.]. These were the porcine ST3Gal1 and Pasteurella multocida sialyltransferases. We now report two additional sialyltransferases with superior Leg-transferase properties to the previous two. These are (i) a truncated form of a Photobacterium α2,6-sialyltransferase with an Ala-Met mutation in its active site, and (ii) an α2,3-sialyltransferase from Neisseria meningitidis MC58 with a higher transferase activity than the P. multocida enzyme, with either CMP-Neu5Ac or CMP-Leg5Ac7Ac as the donor. These enzymes will enable the production of useful Leg5Ac7Ac glycoconjugate derivatives with either α2,6 or α2,3 linkages and unique biological properties.
Keywords: Neisseria gonorrhoeae; Neisseria meningitidis; Pasteurella multocida; Photobacterium; legionaminic acid; sialyltransferase

Improved arterial tissue differentiation by spectroscopic optical coherence tomography - Flueraru, C.; Popescu, D.P.; Mao, Y.; Chang, S.; Sowa, M.G.; Vitkin, A. (CTM, 2015)
Optical coherence tomography (OCT) is a relatively new imaging modality similar with ultrasound where the sound waves are replaced by ballistic photons. OCT provides images at high spatial resolution which allow for the identification of micron size morphological tissue structures. A high impact application is visualization of arterial wall and atherosclerotic plaques. Despite high spatial resolution to complete the transfer of this imaging modality into clinical environment there is a need for markers which would quantify the physiological condition of the sample. Finding the proper markers is a topic of high interest for many research groups. A potential marker suggested by the OCT community is the optical attenuation coefficient. Although OCT image itself provides important diagnostic and structural information there are also new methods of tissue characterization that have been developed through spectroscopic OCT and quantitative OCT. Spectroscopic OCT investigates the spectral response while the quantitative OCT extends the investigation to non-spectral parameters. Here we investigate two procedures for calculation of optical attenuation coefficient dependence versus wavelength. The wavelength analysis will provide new insight into the chemical nature of the sample, because the spectral backreflected signal depends on sample absorption and scattering properties. In this study we demonstrate the application of OCT for quantitative and spectral analysis of vulnerable plaque morphology on Watanabe heritable hyperlipidemic — myocardial infarction (WHHLMI) rabbit model. The results suggest that the spectral dependence of the derived OCT attenuation coefficient can be used for tissue differentiation. We demonstrated that differences and the spectral dependence of the optical attenuation coefficient are linked to the macrophage content of the region of interest.
Keywords: optical coherence tomography; quantitative and spectral analysis; WHHLMI rabbits.

Measurement of aircraft engine non-volatile PM emissions: results of the Aviation-Particle Regulatory Instrumentation Demonstration Experiment (A-PRIDE) 4 campaign - Lobo, Prem; Durdina, Lukas; Smallwood, Gregory J.; Rindlisbacher, Theodor; Siegerist, Frithjof; Black, Elizabeth A.; Yu, Zhenhong; Mensah, Amewu A.; Hagen, Donald E.; Miake-Lye, Richard C.; Thomson, Kevin A.; Brem, Benjamin T.; et al. (Aerosol Science and Technology, 2015)
This study reports the first of a kind data on aircraft engine non-volatile particulate matter (nvPM) number- and mass-based emissions using standardized systems. Two compliant sampling and measurement systems operated by Missouri University of Science and Technology (Missouri S&T) and Empa were evaluated during the Aviation - Particle Regulatory Instrumentation Demonstration Experiment (A-PRIDE) 4 campaign at the SR Technics facilities in Zürich, Switzerland, in November 2012. The Missouri S&T and Empa systems were compared during a series of dedicated engine tests using a CFM56-5B4/2P engine source, and maintenance engine testing using CFM56-7B24/3 and PW4168A engine sources at a range of engine operating conditions. These two compliant systems were found to agree within 6% of each other in terms of nvPM number-based emissions, and within 15% for nvPM mass-based emissions. For the three engine sources studied, at several engine power conditions the mass instruments approached their limit of detection, resulting in high measurement uncertainties. Ancillary instrumentation was used to determine PM size distributions, chemical composition, and effective density from mass-mobility experiments. Particle geometric mean mobility diameter ranged 20–45 nm, and geometric standard deviation varied from 1.55 to 1.9 for the three engine types studied. The fraction of PM organic content measured in the emissions from the CFM56-5B4/2P engine was ∼4% while the size-dependent particle effective density was parameterized with a mass-mobility exponent of 2.57 and a pre-factor of 0.606. Results of this study will contribute to the development of the new nvPM emissions certification standard and emissions inventories from commercial aviation operations.

Conquering the barriers: are antibody therapeutics feasible for CNS indications? - Stanimirovic, Danica; Kemmerich, Kristin (Future Neurology, 2015)
The major hurdles on the development path of CNS therapeutics include an inherent complexity of the CNS, highly restricted drug access to CNS targets by the blood–brain barrier (BBB), paucity of translational preclinical disease models, safety risks, and lack of clinical biomarkers to aid in patient selection and early assessment of efficacy in clinical trials. Drug development for CNS is therefore highly complex and risky – more expensive and lengthy than for any other indication. The CNS drugs have one of the highest pipeline attrition rates and longest development times (114 months); clinical trial failures tend to occur later in the clinical development, making the cost of developing a CNS drug among the highest of any therapeutic indication.
Keywords: CNS therapeutics; blood–brain barrier; drug development

Observation of the metallic-type selective etching of single walled carbon nanotubes by real-time in situ two-laser Raman spectroscopy - Li-Pook-Than, Andrew; Finnie, Paul (Carbon, 2015)
Real time, in situ Raman spectroscopy with two simultaneously incident laser excitation wavelengths is used to investigate the dynamics of single-walled carbon nanotube etching. For the source material, nanotubes of diameter 1.4 nm, a 532 nm laser is resonant with semiconducting nanotubes and a 633 nm laser is resonant with metallic nanotubes. Changes in metallic and semiconducting population are tracked separately and simultaneously. In oxygen, metals consistently etch faster than semiconductors, and all etch rates increase with the process temperature and the defect density in the source material. A similar evolution is observed in carbon dioxide. Simultaneous two-color Raman spectroscopy provides information beyond standard Raman spectroscopy and can be effective as an instantaneous measure of metallicity for nanotubes.
Keywords: carbon nanotube; situ two-laser Raman spectroscopy

Microfluidic filtration and extraction of pathogens from food samples by hydrodynamic focusing and inertial lateral migration - Clime, Liviu; Hoa, Xuyen D.; Corneau, Nathalie; Morton, Keith J.; Luebbert, Christian; Mounier, Maxence; Brassard, Daniel; Geissler, Matthias; Bidawid, Sabah; Farber, Jeff; Veres, Teodor (Biomedical Microdevices, 2015)
Detecting pathogenic bacteria in food or other biological samples with lab-on-a-chip (LOC) devices requires several sample preparation steps prior to analysis which commonly involves cleaning complex sample matrices of large debris. This often underestimated step is important to prevent these larger particles from clogging devices and to preserve initial concentrations when LOC techniques are used to concentrate or isolate smaller target microorganisms for downstream analysis. In this context, we developed a novel microfluidic system for membrane-free cleaning of biological samples from debris particles by combining hydrodynamic focusing and inertial lateral migration effects. The microfluidic device is fabricated using thermoplastic elastomers being compatible with thermoforming fabrication techniques leading to low-cost single-use devices. Microfluidic chip design and pumping protocols are optimized by investigating diffusive losses numerically with coupled Navier–Stokes and convective-diffusion theoretical models. Stability of inertial lateral migration and separation of debris is assessed through fluorescence microscopy measurements with labelled particles serving as a model system. Efficiency of debris cleaning is experimentally investigated by monitoring microchip outlets with in situ optical turbidity sensors, while retention of targeted pathogens (i.e., Listeria monocytogenes) within the sample stream is assessed through bacterial culture techniques. Optimized pumping protocols can remove up to 50 % of debris from ground beef samples while percentage for preserved microorganisms can account for 95 % in relatively clean samples. However, comparison between inoculated turbid and clean samples (i.e., with and without ground beef debris) indicate some degree of interference between debris inertial lateral migration and hydrodynamic focusing of small microorganisms. Although this interference can lead to significant decrease in chip performance through loss of target bacteria, it remains possible to reach 70 % for sample recovery and more than 50 % for debris removal even in the most turbid samples tested. Due to the relatively simple design, the robustness of the inertial migration effect itself, the high operational flow rates and fabrication methods that leverage low-cost materials, the proposed device can have an impact on a wide range of applications where high-throughput separation of particles and biological species is of interest.
Keywords: Microfluidic filtration; Sample preparation; Hot embossing; Food safety inspection

A comparison between the NIST PVJSBased Power Standard and the NRC Current-Comparator-Based Power Standard - Waltrip, B.C.; Nelson, T.L.; So, E.; Angelo, D. (IEEE Transactions on Instrumentation and Measurement, 2015)
The results of a comparison of active/reactive power meter calibrations between the National Institute of Standards and Technology (NIST) and the National Research Council (NRC) are presented. The comparison was implemented using a transfer standard consisting of a highly stable commercial sampling-type power/energy meter. The measurements were made at 120 V, 5 A, 50 Hz and 60 Hz, at power factors of 1.0, 0.5 lead and lag, and 0.0 lead and lag. The results of the comparison indicate agreement to within the stated uncertainties of the participants.

Metal ion-assisted photochemical vapor generation for the determination of lead in environmental samples by Multicolletor-ICPMS - Gao, Ying; Xu, Mo; Sturgeon, Ralph E.; Mester, Zoltán; Shi, Zeming; Galea, Raphael; Saull, Patrick; Yang, Lu (Analytical chemistry, 2015)
A novel and sensitive approach for the accurate and precise determination of Pb in environmental samples is presented using transition metal ion-assisted photochemical vapor generation (PVG) for sample introduction with multicollector inductively coupled plasma mass spectrometry (MC-ICPMS) detection. A significant improvement in PVG efficiency of lead is achieved in the presence of transition metal ions (Co(2+) and Ni(2+)) in solutions of 5% (v/v) formic acid. The determination of Pb in digests of sediment or soil samples is readily achieved due to coexisting transition metal ions which facilitate the PVG reaction. The method detection limit of 0.005 ng g(-1) (3σ) using external calibration is comparable to that obtained using hydride generation (HG) ICPMS. However, PVG methodology is simpler, results in lower blanks, and avoids unstable reagents. The accuracy of the proposed method was demonstrated by analysis of several environmental certified reference materials (CRMs; SLRS-5 and SRM1640a river water CRMs and MESS-3, MESS-4, and SRM2702 sediments) with satisfying results. High precision of determination (<0.4% RSD) of Pb in river water and sediments was realized on the basis of isotope dilution calibration.
Keywords: UV photochemical vapor generation; isotope dilution; Pb; standard additions calibration; multi-collector inductively coupled plasma mass spectrometry

Influence of rapid laser heating on the optical properties of in-flame soot - Saffaripour, M.; Geigle, K.-P.; Snelling, D.R.; Smallwood, G.J.; Thomson, K.A. (Applied physics B, 2015)
To understand the effect of rapid heating on the optical properties of in-flame soot and its potential influence on the laser-induced incandescence (LII) signal, the time-resolved extinction coefficient of soot is measured in diffusion and premixed flames during laser heating. Heating is performed using a 1064-nm pulsed laser with fluences ranging from 0.2 to 6.2 mJ/mm2. Extinction measurements are carried out using continuous-wave lasers at four different wavelengths. A rapid enhancement of extinction, by up to 10 % in the diffusion flame and 18 % in the premixed flame, occurs during laser heating most likely as a result of temperature-dependent optical properties and laser-induced thermal annealing of soot. The thermal expansion of flame gases causes a gradual decline of soot concentration for about 2 μs after the laser pulse. Significant loss of soot material by sublimation is observed at fluences as low as 1.03 and 2.06 mJ/mm2 for the diffusion and premixed flames, respectively. A secondary rise in extinction coefficient is observed from about 50 to 800 ns after the laser pulse at low monitoring wavelengths, attributed to the formation of light-absorbing gaseous species from the sublimated soot material. These effects may impact the LII signal and should be accounted for in LII analysis.

Neuroprotective effects of the cultivated Chondrus crispus in a C. elegans model of Parkinson's disease - Liu, J.; Banskota, A.H.; Critchley, A.T.; Hafting, J.; Prithiviraj, B. (Marine Drugs, 2015)
Parkinson's disease (PD) is the second most common neurodegenerative disorder in the elderly people, currently with no cure. Its mechanisms are not well understood, thus studies targeting cause-directed therapy or prevention are needed. This study uses the transgenic Caenorhabditis elegans PD model. We demonstrated that dietary supplementation of the worms with an extract from the cultivated red seaweed Chondrus crispus decreased the accumulation of α-synulein and protected the worms from the neuronal toxin-, 6-OHDA, induced dopaminergic neurodegeneration. These effects were associated with a corrected slowness of movement. We also showed that the enhancement of oxidative stress tolerance and an up-regulation of the stress response genes, sod-3 and skn-1, may have served as the molecular mechanism for the C. crispus-extract-mediated protection against PD pathology. Altogether, apart from its potential as a functional food, the tested red seaweed, C. crispus, might find promising pharmaceutical applications for the development of potential novel anti-neurodegenerative drugs for humans.
Keywords: Chondrus crispus; neuroprotective effect; oxidative stress; Parkinson's disease

Polymer nanocomposites from free-standing, macroscopic boron nitride nanotube assemblies - Su Kim, Keun; Jakubinek, Michael B.; Martinez-Rubi, Yadienka; Ashrafi, Behnam; Guan, Jingwen; O'Neill, K.; Plunkett, Mark; Hrdina, Amy; Lin, Shugiong; Dénommée, Stéphane; Kingston, Christopher; Simard, Benoit (RSC Advances, 2015)
Here we report the fabrication of free-standing boron nitride nanotube (BNNT) sheets by direct deposition and by vacuum filtration methods, including novel hybrid assemblies with BNNT and carbon nanotubes. Such sheets have enabled production of polymer nanocomposites with high nanotube content. Two example cases, BNNT–epoxy nanocomposites (>30 wt% BNNTs) produced by impregnation of dry sheets and BNNT sheets modified by integration of a thermoplastic polyurethane are described. Related methods have proven advantageous for carbon nanotube composites and, enabled by new technology for large scale BNNT production, such composites have now been realized with BNNTs. This represents an important milestone towards the development of BNNT-based multifunctional composites.
Keywords: boron nitride; nanotubes; BNNT

The Fricke dosimeter as an absorbed dose to water primary standard for Ir-192 brachytherapy - Gamal, Islam El; Cojocaru, Claudiu; Mainegra-Hing, Ernesto; McEwen, Malcolm (Physics in Medicine and Biology, 2015)
The aim of this project was to develop an absorbed dose to water primary standard for lr-192 brachytherapy based on the Fricke dosimeter. To achieve this within the framework of the existing TG-43 protocol, a determination of the absorbed dose to water at the reference position, Dw(r0,80), was undertaken. Prior to this investigation, the radiation chemical yield of the ferric ions (G-value) at the lr-192 equivalent photon energy was established by interpolating between G-values obtained for Co-60 and 250 kV x-rays. An irradiation geometry was developed with a cylindrical holder to contain the Fricke solution and allow irradiations in a water phantom to be conducted using a standard Nucletron microSelectron V2 HDR Ir-192 afterloader. Once the geometry and holder were optimized, the dose obtained with the Fricke system was compared to the standard method used in North America, based on air-kerma strength. Initial investigations focused on reproducible positioning of the ring-shaped holder for the Fricke solution with respect to the Ir-192 source and obtaining an acceptable type A uncertainty in the optical density measurements required to yield the absorbed dose. Source positioning was found to be reproducible to better than 0.3 mm, and a careful cleaning and control procedure reduced the variation in optical density reading due to contamination of the Fricke solution by the PMMA holder. It was found that fewer than 10 irradiations were required to yield a type A standard uncertainty of less than 0.5%. Correction factors to take account of the non-water components of the geometry and the volume averaging effect of the Fricke solution volume were obtained from Monte Carlo calculations. A sensitivity analysis showed that the dependence on the input data used (e.g. interaction cross-sections) was small with a type B uncertainty for these corrections estimated to be 0.2%. The combined standard uncertainty in the determination of absorbed dose to water at the reference position for TG-43 (1 cm from the source on the transverse axis, in a water phantom) was estimated to be 0.8% with the dominant uncertainty coming from the determination of the G-value. A comparison with absorbed dose to water obtained using the product of air-kerma strength and the dose rate constant gave agreement within 1.5% for three different Ir-192 sources, which is within the combined standard uncertainties of the two methods.
Keywords: absorbed dose; water primary standard; brachytherapy; Fricke dosimeter

The visibility study of S-T+ Landau-Zener-Stiickelberg oscillations without applied initialization - Granger, G.; Aers, G.C.; Studenikin, S.A.; Kam, A.; Zawadzki, P.; Wasilewski, Z.R.; Sachrajda, A.S. (Physical review B, 2015)
Probabilities deduced from quantum information studies are usually based on averaging many identical experiments separated by an initialization step. Such initialization steps become experimentally more challenging to implement as the complexity of quantum circuits increases. To better understand the consequences of imperfect initialization on the deduced probabilities, we study the effect of not initializing the system between measurements. For this we utilize Landau-Zener-Stückelberg oscillations in a double quantum dot circuit. Experimental results are successfully compared to theoretical simulations.
Keywords: Quantum dots; Coulomb blockade; single-electron tunneling

Evaluating dense 3D surface reconstruction techniques using a metrological approach - Toschi, Isabella; Beraldin, Jean-Angelo (Angelo); Cournoyer, Luc; De Luca, Livio; Capra, Alessandro (NCSLI Measure : The Journal of Measurement Science, 2015)
This paper discusses an approach for evaluating the accuracy of dense 3D surface reconstruction techniques based on images. So far, the emergence of these novel techniques has not been supported by the definition of an internationally recognized standard which is fundamental for user confidence and market growth. In order to provide an element of reflection and solution to the different communities involved in image-based 3D modelling, we present an approach for the assessment of the metric performance of an open-source set of routines for bundle block adjustment and dense image matching (Apero/MicMac). The evaluation is performed using a metrological approach, through comparisons between image-based 3D generated data and 'reference' data acquired with two hemispherical laser scanners, one total station, and one laser tracker. Aspects of traceability and measurement uncertainty of all these reference 3D data are discussed. The methodology is applied to two case studies, tailored to analyze the software capabilities in dealing with both outdoor and environmentally controlled conditions. Comparative data and accuracy evidence provided by both tests allow the study of some key factors affecting 3D model accuracy.

Use of Ga for mass bias correction for the accurate determination of copper isotope ratio in the NIST SRM 3114 Cu standard and geological samples by MC-ICPMS - Hou, QingHua; Zhou, Lian; Gao, Shan; Zhang, Ting; Feng, Lanping; Yang, Lu (Journal of analytical atomic spectrometry, 2015)
The absolute determination of the Cu isotope ratio in NIST SRM 3114 based on a regression mass bias correction model is performed for the first time with NIST SRM 944 Ga as the calibrant. A value of 0.4471 ± 0.0013 (2SD, n = 37) for the 65Cu/63Cu ratio was obtained with a value of +0.18 ± 0.04‰ (2SD, n = 5) for δ65Cu relative to NIST 976. The availability of the NIST SRM 3114 material, now with the absolute value of the 65Cu/63Cu ratio and a δ65Cu value relative to NIST 976 makes it suitable as a new candidate reference material for Cu isotope studies.

High-temperature platinum resistance thermometry: the problem with silver and the case for gold - Hill, Kenneth D. (Metrologia, 2015)
The diffusion of silver through quartz at high temperatures leads to contamination of the platinum sensing element of high temperature platinum resistance thermometers. While some protection of the PRT element may be afforded by the application of appropriate electric fields, the contamination of the quartz elements of silver fixed points causes their premature failure. Contamination is evidenced by the yellowish colour imparted to the glass by the silver particles growing within the quartz glass matrix. The presence of silver as the contaminating element has been confirmed unambiguously through energy dispersive x-ray analysis and secondary ion mass spectrometry. To mitigate the risk of silver contamination , the gold point is proposed as an alternative calibration point. PRT resistance ratios measured at the freezing points of silver and gold in different laboratories at different times are highly correlated. This suggests that the ITS-90 reference function might be extrapolated to 1064.18 °C (the gold fixed point). However, it remains unclear from the gold and silver PRT resistance ratios from the literature whether extrapolation of the reference function leads to the correct value at the gold point. A direct comparison of gold fixed points may be required to resolve the inconsistencies. Additional PRT data may help resolve the discrepancy.
Keywords: platinum resistance thermometer; silver fixed point; gold fixed point; contamination

Single-plane versus three-plane methods for relative range error evaluation of medium-range 3D imaging systems - MacKinnon, David K.; Cournoyer, Luc; Beraldin, J.-Angelo (SPIE Proceedings, 2015)
Within the context of the ASTM E57 working group WK12373, we compare the two methods that had been initially proposed for calculating the relative range error of medium-range (2 m to 150 m) optical non-contact 3D imaging systems: the first is based on a single plane (single-plane assembly) and the second on an assembly of three mutually non-orthogonal planes (three-plane assembly). Both methods are evaluated for their utility in generating a metric to quantify the relative range error of medium-range optical non-contact 3D imaging systems. We conclude that the three plane assembly is comparable to the single-plane assembly with regard to quantification of relative range error while eliminating the requirement to isolate the edges of the target plate face.
Keywords: relative range error; 3D imaging system; lidar; performance assessment; medium-range optical non-contact 3D imaging system; terrestrial laser scanners; ASTM E57 standards development

Measurements and modeling of laser-induced incandescence of soot at different heights in a flat premixed flame - Bejaoui, Salma; Batut, Sébastien; Therssen, Eric; Lamoureux, Nathalie; Desgroux, Pascale; Liu, Fengshan (Applied physics B: lasers and optics, 2015)
Laser-induced incandescence (LII) measurements were conducted in a laminar flat rich premixed CH4/ O2/N2 flame at atmospheric pressure using a Nd:YAG laser operated at 1,064 nm. Time-resolved LII signals were measured at 610 nm (20 nm FWHM) at different heights above the burner exit surface and at different laser fluences. The averaged soot temperature over 10 ns around the laser peak was determined from spectrally resolved LII signals over the spectral range of 500–630 nm. Flame temperature and soot primary particle diameter and aggregate size at several flame heights were obtained using the NO-LIF thermometry and from image analyses of sampled soot. The time-resolved LII signal and the averaged soot temperature were modeled using two LII models. To achieve reasonable agreement between the modeled and experimental LII signal and soot temperature at low laser fluences, it is necessary to use flame height-dependent soot absorption functions. Such practice can be attributed to the continuous variation of soot thermal and/or radiative properties during the surface growth process after inception. At high laser fluences, both LII models are unable to reproduce the overall shape of the normalized time-resolved LII signal profiles and the averaged soot temperatures.
Keywords: flat premixed flame; laser-induced incandescence; time-resolved LII intensity; soot absorption function; LIF thermometry

Increasing efficiency of BEAMnrc-simulated Co-60 beams using directional source biasing - Walters, B. R. B. (Medical Physics, 2015)
This study describes the implementation of a directional source biasing (DSB) scheme for efficiently simulating Cobalt-60 treatment heads using the BEAMnrc Monte Carlo code. Pre-10 vious simulation of Co-60 beams with BEAMnrc were impractical because of the time required to track photons not directed into the treatment field as well as secondary charged particles (> 100 hours on 15 1.8 GHz CPU's to obtain < 0.1% uncertainty on doses in 0.5 em x 0.5 em x 0.5 em voxels in water).

Analysis of paralytic shellfish toxins using high field asymmetric waveform Ion mobility spectrometry with liquid chromatography-mass spectrometry - Beach, Daniel G.; Melanson, Jeremy E.; Purves, Randy W. (Analytical and bioanalytical chemistry, 2015)
We investigate the potential utility of high-field asymmetric waveform ion mobility spectrometry (FAIMS) as a gas-phase ion separation tool for analysis of PSTs by mass spectrometry.We investigate the separation of PSTs using FAIMS with two divergent goals: using FAIMS as a primary separation tool for rapid screening by electrospray ionization (ESI)-FAIMSMS or combined with LC in a multidimensional LC-ESIFAIMS-MS separation.
Keywords: Differential Mobility Spectrometry (DMS); Paralytic Shellfish Poisoning (PSP); Algal Toxins

Numerical and experimental study of the influence of CO₂ and N₂ dilution on soot formation in laminar coflow C₂H₄/air diffusion flames at pressures between 5 and 20 atm - Liu, Fengshan; Karata, Ahmet E.; Gülder, Örner L.; Gu, Mingyan (Combustion and Flame, 2015)
The effects of fuel dilution by C02 and N2 on soot formation and the flame structure in laminar coflow C2HJair diffusion flames at pressures between 5 and 20 atm were investigated both experimentally and numerically. Experimentally a constant ethylene flow rate and a constant dilution rate of 1:2 (fuel:diluent by mass) were maintained throughout the experiments. The flames were stable and non-smoking over the pressure range investigated. The radially resolved soot volume fraction and temperature distributions were measured by the spectral soot emission (SSE) technique. Numerical calculations were conducted using two C2 chemistry models with formation of PAHs up to pyrene and a soot model incorporating pyrene collision as the soot inception step and hydrogen-abstraction acetylene addition mechanism and PAH condensation as the surface growth processes.
Keywords: soot formation; laminar diffusion flame; pressure effect; C02 chemical effect

Numerical study of the effects of pressure on soot formation in laminar coflow n-heptane/air diffusion flames between 1 to 10 atm - Consalvi, Jean-Louis; Liu, Fengshan (Proceedings of the Combustion Institute, 2015)
Laminar nitrogen-diluted n-heptane diffusion flames burning in coflow air were numerically simulated at pressures from 1 to 10 atm. Numerical simulations were performed by using a detailed reaction mechanism containing 175 species and 1086 reactions with PAH formation up to pyrene and a sectional soot model. The soot model consists of inception as a result of the collision of two pyrene molecules, heterogeneous surface growth and oxidation following the hydrogen abstraction acetylene addition (HACA) mechanism, and soot particle coagulation and PAH surface condensation. Comparisons with available experimental data indicate that the numerical model reproduces successfully the influence of pressure on the flame structure and soot production. All the soot formation processes are enhanced with increasing pressure and HACA dominates the soot mass growth over the pressure range considered. PAH condensation is the most sensitive process to pressure whereas the inception and HACA processes exhibit similar pressure dependency. These trends are directly related to the pressure dependence of the molar concentrations of the species involved in soot formation. The increase in the molar concentrations of benzene and pyrene with pressure results from both physical and chemical effects. Propargyl recombination and interconversion of phenyl to benzene dominate the formation of benzene low in the flame over the pressure range considered, though the contributions of the addition of acetylene to n-butadienyl radical increases significantly with pressure in the flame centerline region.
Keywords: laminar diffusion flame; n-Heptane; soot production; high pressure; PAH-based soot model

Platinum resistivity below 273.16 K: a tale of two reference functions - Hill, K.D. (Metrologia, 2015)
Four platinum resistance thermometer data sets of resistance ratio as a function of temperature from 13.8033 K to 273.16 K are fitted to two different functions. One has the form of the ITS-90 reference function (the "Kemp model") while the second is the mathematically more complex model of Nicholas. Both are shown to fit the resistivity data well, though the residuals for the Kemp model are lower. Both models also cope well with adjustments to the input temperatures consistent with the most recent consensus estimates of T-Tgo. There is no evidence from the work reported herein that either of the models is useful as an arbiter of thermodynamic temperature data.
Keywords: instrumentation and measurement; statistical physics and nonlinear systems

Structure elucidation, relative LC-MS response and in vitro toxicity of Azaspiracids 7-10 isolated from blue mussels (Mytilus edulis) - Kilcoyne, Jane; Twiner, Michael J.; McCarron, Pearse; Crain, Sheila; Sabrina, L.; Giddings, D.; Foley, Barry; Rise, Frode; Hess, Philipp; Wilkins, Alistair L.; Mileso, Christopher O. (Journal of Agricultural and Food Chemistry, 2015)
Azaspiracids (AZAs) 7-10 (7-10) were isolated from shellfish and their structures, previously proposed based only on LC-MS/MS data, were confirmed by NMR spectroscopy. Samples of AZA4-6 (4-6) and 7-10 were accurately quantitated by qNMR, and used to prepare reference standards and assay cytotoxicity with Jurkat T lymphocyte cells. LC-MS molar response studies performed using isocratic and gradient elution, in both SIM and SRM modes, showed that responses for the analogues ranged from 0.3 to 1.2 relative to AZA1 (1). All AZA analogues tested were cytotoxic to Jurkat T lymphocyte cells in a time- and concentration dependent manner. However, there were distinct differences in their EC50 values, with cytotoxicity potencies being 6 > 8 > 1 > 4 ≈ 5 ≈9 > 10. This provides valuable information on structure-activity relationships.
Keywords: azaspiracid; relative molar response; NMR; mass spectrometry; purification; toxicity

Influence of interface potential on the effective mass in Ge nanostructures - Barbagiovanni, E.G.; Cosentino, S.; Lockwood, D.J.; Costa Filho, R.N.; Terrasi, A.; Mirabella, S. (Journal of applied physics, 2015)
The role of the interface potential on the effective mass of charge carriers is elucidated in this work. We develop a new theoretical formalism using a spatially dependent effective mass that is related to the magnitude of the interface potential. Using this formalism, we studied Ge quantum dots (QDs) formed by plasma enhanced chemical vapour deposition (PECVD) and co-sputtering (sputter). These samples allowed us to isolate important consequences arising from differences in the interface potential. We found that for a higher interface potential, as in the case of PECVD QDs, there is a larger reduction in the effective mass, which increases the confinement energy with respect to the sputter sample. We further understood the action of O interface states by comparing our results with Ge QDs grown by molecular beam epitaxy. It is found that the O states can suppress the influence of the interface potential. From our theoretical formalism, we determine the length scale over which the interface potential influences the effective mass.
Keywords: nanostructure

Enrichment of Triticum aestivum gene annotations using ortholog cliques and gene ontologies in other plants - Tulpan, Dan; Leger, Serge; Tchagang, Alain; Pan, Youlian (BMC Genomics, 2015)
While the gargantuan multi-nation effort of sequencing T. aestivum gets close to completion, the annotation process for the vast number of wheat genes and proteins is in its infancy. Previous experimental studies carried out on model plant organisms such as A. thaliana and O. sativa provide a plethora of gene annotations that can be used as potential starting points for wheat gene annotations, proven that solid cross-species gene-to-gene and protein-to-protein correspondences are provided. Results DNA and protein sequences and corresponding annotations for T. aestivum and 9 other plant species were collected from Ensembl Plants release 22 and curated. Cliques of predicted 1-to-1 orthologs were identified and an annotation enrichment model was defined based on existing gene-GO term associations and phylogenetic relationships among wheat and 9 other plant species. A total of 13 cliques of size 10 were identified, which represent putative functionally equivalent genes and proteins in the 10 plant species. Eighty-five new and more specific GO terms were associated with wheat genes in the 13 cliques of size 10, which represent a 65% increase compared with the previously 130 known GO terms. Similar expression patterns for 4 genes from Arabidopsis, barley, maize and rice in cliques of size 10 provide experimental evidence to support our model. Overall, based on clique size equal or larger than 3, our model enriched the existing gene-GO term associations for 7,838 (8%) wheat genes, of which 2,139 had no previous annotation. Conclusions Our novel comparative genomics approach enriches existing T. aestivum gene annotations based on cliques of predicted 1-to-1 orthologs, phylogenetic relationships and existing gene ontologies from 9 other plant species.
Keywords: Triticum aestivum; gene annotations; gene ontologies

Multilayer graphene synthesized using magnetron sputtering for planar supercapacitor application - Ionescu, Mihnea Ioan; Sun, Xueliang; Luan, Ben (Canadian Journal of Chemistry, 2015)
This study reports the direct preparation of graphene-based films using magnetron sputtering of graphite target. The nanomaterial was deposited at a low temperature of 620 °C on silicon wafers and on metallic foils including aluminum. The films were used in fabrication of supercapacitors with a planar geometry. Electrochemical characterizations demonstrated that the films produced showed nearly ideal electrical capacitive behavior. The maximum capacitance obtained from cyclic voltammetry analysis was 325 F/g for a scan rate of 1 mV/s. The device is capable of delivering an energy density of 13.9 Wh/kg at a very high power density of 50 000 W/kg for ultrafast scan rate of 1000 mV/s. The graphene nanomaterial electrode retains the electrochemical stability over a large number of charge-discharge cycles.
Keywords: nanomaterials; graphenes; magnetron sputtering; supercapacitor

Pancreatic lipase inhibitory activity of monogalactosyldiacylglycerols isolated from the freshwater microalga Chlorella sorokiniana - Banskota, Arjun H.; Steevensz, Aaron J.; Stefanova, Roumiana; Sperker, Sandra; Melanson, Ronald; Osborne, Jane A.; O'Leary, Stephen J.B.; Melanson, Jeremy E. (Journal of Applied Phycology, 2015)
Chemical investigation of the freshwater microalga Chlorella sorokiniana led to the isolation of a monogalactosyldiacylglycerol (MGDG)-rich fraction possessing dose-dependent inhibitory activity against pancreatic lipase activity. The MGDG-rich fraction contains 12 MGDGs identified by LC/HRMS analysis. Among them, three MGDGs were new compounds, namely, (2S)-1-O-(7Z,10Z-hexadecadienoyl)-2-O-(7Z,10Z,13Z-hexadecatrienoyl)-3-O-β-D-galactopyranosylglycerol (1), (2S)-1-O-linoleoyl-2-O-(7Z,10Z-hexadecadienoyl)-3-O-β-D-galactopyranosylglycerol (6), and (2S)-1-O-oleoyl-2-O-(7Z,10Z-hexadecadienoyl)-3-O-β-D-galactopyranosylglycerol (8). The major galactolipids were isolated by semipreparative HPLC and tested for their effect toward pancreatic lipase inhibitory activity. All the tested MGDGs showed significant reduction of pancreatic lipase activity indicating possible beneficial use for management of lipase-related disorders such as obesity.
Keywords: Chlorella sorokiniana; Monogalactosyldiacylglycerol; Galactolipid; Lipase; Obesity; Microalgae

WIG (wing-in-ground) effect dual-foil turbine for high renewable energy performance - Liu, Pengfei (Energy, 2015)
Traditional HATs (horizontal axis turbines) are predominantly used for wind and tidal energy generation. HATs have higher power production than VATs (vertical axis turbines) for which also requires a rotational motion of their rotors. Existing HAT installations and operations are widely seen as wind turbines on land and hydrokinetic turbines underwater. However, the operation of both HAT and VAT requires large rotor diameter for large energy production. These introduce some disadvantages: requirement of large profile height on land and water depth underwater; high rotor tip speed and hence impact on surrounding ecology; and requirement of large kick-in speed and hence a low wind/tidal resource utilization or inapplicability in slow inflow energy sites. A dual-foil dynamic WIG (Wing-In-Ground) effect turbine, WIGT (Wing-in-ground effect turbine) for short, was developed and its renewable energy performance and characteristics were investigated. A performance comparison between traditional HATT (horizontal axis tidal turbine) and a WIGTT (wing-in-ground effect tidal turbine) was made, based on the tidal flow probability distribution of the Minas Passage, the Bay of Fundy, Canada. With about the same swept area, the WIGTT produces 1.73 times annual energy as an HATT. WIGT uses an active pitch control but the required power to pitch the foils was found to be about 10% generated power at the maximum. The use of trapezoidal pitch control produces 1.44 times as much power as either single-foil or dual-foil turbines. With a minimum gap of 16% chord between the foils, dynamic WIG effect produces 1.42 times as much energy. WIGT could generate 5 times power as much as a single foil with sinusoidal pitch and heave. WIGTs also have some outstanding advantages such as large power capacity under confined profile height on land or in shallow waters, power generation capability for low speed inflow, environmental friendly operation and better flow characteristics.
Keywords: WIGT (wing-in-ground effect turbine); Oscillating foil turbine; Tidal and wind turbine; Hydro-kinetic turbine

Environmental fate of 2,4-dinitroanisole (DNAN) and its reduced products - Hawari, J.; Monteil-Rivera, F.; Perreault, N.N.; Halasz, A.; Paquet, L.; Radovic-Hrapovic, Z.; Deschamps, S.; Thiboutot, S.; Ampleman, G. (Chemosphere, 2015)
Several defense departments intend to replace 2,4,6-trinitrotoluene (TNT) in munitions formulations by the less sensitive 2,4-dinitroanisole (DNAN). To help understand environmental behavior and ecological risk associated with DNAN we investigated its key initial abiotic and biotic reaction routes and determined relevant physicochemical parameters (pKa, log Kow, aqueous solubility (Sw), partition coefficient (Kd)) for the chemical and its products. Reduction of DNAN with either zero valent iron or bacteria regioselectively produced 2-amino-4-nitroanisole (2-ANAN) which, under strict anaerobic conditions, gave 2,4-diaminoanisole (DAAN). Hydrolysis under environmental conditions was insignificant whereas photolysis gave photodegradable intermediates 2-hydroxy-4-nitroanisole and 2,4-dinitrophenol. Physicochemical properties of DNAN and its amino products drastically depended on the type and position of substituent(s) on the aromatic ring. Sw followed the order (TNT < DNAN < 2-ANAN < 4-ANAN < DAAN) whereas log Kow followed the order (DAAN < 4-ANAN < 2-ANAN < DNAN < TNT). In soil, successive replacement of single bondNO2 by single bondNH2 in DNAN enhanced irreversible sorption and reduced bioavailability under oxic conditions. Although DNAN is more soluble than TNT, its lower hydrophobicity and its tendency to form aminoderivatives that sorb irreversibly to soil contribute to make it less toxic than the traditional explosive TNT.
Keywords: 2,4-Dinitroanisole; 2,4-Diaminoanisole; Regioselectivity; Insensitive munition

Single-walled carbon nanotube–epoxy composites for structural and conductive aerospace adhesives - Jakubinek, Michael B.; Ashrafi, Behnam; Zhang, Yunfa; Martinez-Rubi, Yadienka; Kingston, Christopher T.; Johnston, Andrew; Simard, Benoit (Composites Part B: Engineering, 2015)
Single-walled carbon nanotubes (SWCNTs) were incorporated at low loading (up to ∼1 wt%) into an unfilled aerospace-grade epoxy system, to impart electrical conductivity while maintaining structural bonding capability, as a route for development of a structural and conductive adhesive. At these low SWCNT loadings the tensile properties were maintained or improved, while strength decreased in a higher loading case. The structural bonding performance of composite-to-composite joints, evaluated in lap-shear and peel tests, was reasonably maintained for adhesives containing 0.5 wt% or 1 wt% SWCNTs. In the case of the 0.5 wt% SWCNT–adhesive, peel and lap-shear strength were unchanged while the addition of 1 wt% resulted in 30% increase of peel strength but the lap-shear strength was reduced by 10–15%. For 1 wt% SWCNT–adhesives, conductivities as high as 10−1 S m−1 and typically ∼10−3 S m−1 were achieved. Joint electrical resistance measured between aluminum adherends was larger than predicted by the bulk conductivity, but was reduced by a post-treatment step resulting in apparent joint conductivities within one order of magnitude of the bulk samples.
Keywords: Nano-structures; Polymer–matrix composites; Electrical properties; Joints/joining; Conductive adhesives

Pulse-width modulated external resistance increases the microbial fuel cell power output - Coronado, J.; Perrier, M.; Tartakovsky, B. (Bioresource Technology, 2015)
This study describes MFC operation with a pulse-width modulated connection of the external resistor (R-PWM mode) at low and high frequencies. Analysis of the output voltage profiles acquired during R-PWM tests showed the presence of slow and fast dynamic components, which can be described by a simple equivalent circuit model suitable for process control applications. At operating frequencies above 100. Hz a noticeable improvement in MFC performance was observed with the power output increase of 22-43% as compared to MFC operation with a constant external resistance.
Keywords: MFC; Periodic operation; Pulse-width modulation; Power output maximization

Control law design for handling qualities improvement and structural load alleviation in rotorcraft - Walker, D.J.; Manimala, B.J.; Voskuijl, M.; Gubbels, A.W. (2007 European Control Conference, ECC 2007, 2015)
Recent results are presented on the modelling, control and identification of helicopters carried out under the Helicopter Active Control (HELI-ACT) project. Designing high-bandwidth control systems pushes the existing flight mechanics models to their limits, especially if structural load prediction and alleviation are to be investigated. We describe how engine dynamics have been added to the simulations we have developed and how time-domain system identification has been used to obtain an updated linearized model. This has been done in an effort to address deficiencies that were observed in the original models. The use of nonlinear elements is discussed in the context of optimizing handling quality metrics. Results are presented from the flight-test of control laws incorporating nonlinear elements, designed to optimize attitude quickness, and it is shown how extremely accurate predictions of bandwidth and quickness were made using the new model.
Keywords: Aircraft control; Bandwidth; Control theory; Flight control systems; Helicopters; Identification (control systems); Structural loads; Accurate prediction; Control law design; Flight mechanics; Handling quality; Linearized models; Load alleviation; Nonlinear elements; Time domain system identification; Quality control